A method for using MR to evaluate the effects of cardiovascular disease on the brain: the cardiovascular health study. - Bryan, R N; Manolio, T A; Schertz, L D; Jungreis, C; Poirier, V C; Elster, A D; Kronmal, R A (AJNR Am J Neuroradiol, 1994)
PURPOSE: To do a pilot study for the Cardiovascular Health Study (a population-based, longitudinal study of coronary heart disease and stroke in adults 65 years of age and older designed to identify risk factors related to cerebrovascular disease, particularly stroke): (a) to determine the feasibility of adding brain MR to the full-scale study; (b) to evaluate the reliability of standardized MR image interpretation in a multicenter study; and (c) to compare the prevalence of stroke determined by MR with that by clinical history. METHODS: Protocol-defined MR studies were performed in 100 subjects with clinical histories of stroke and 203 subjects without reported histories of stroke. MR scans were independently evaluated by two trained neuroradiologists for the presence of small (< or = 3 mm) and large (> 3 mm) "infarctlike" lesions. The sizes of the cerebral sulci and lateral ventricles and the extent of white matter disease were graded on a scale of 0 to 9. RESULTS: Eighty percent of the Cardiovascular Health Study participants who were invited to undergo MR studies agreed to do so; 95% of those agreeing to the procedure successfully completed the exams. Intrareader and interreader reliability of infarctlike lesion identification was high for large lesions (kappa, 0.71 and 0.78, respectively) but not for small lesions (kappa, 0.71 and 0.32, respectively). Relaxed intrareader and interreader kappa scores for sulcal and ventricular sizes and extent of white matter disease were greater than 0.8 MR evidence of infarctlike lesions was present in 77% of the participants with histories of stroke but was also present in 23% of the participants without clinical histories of stroke. Seventy-nine percent of the infarctlike lesions were larger than 3 mm. CONCLUSIONS: This preliminary study indicates that a large, prospective, epidemiologic study of elderly subjects using MR scans of the brain for identification of cerebrovascular disease is feasible and that the interpretative results are reproducible, and suggests that MR evidence of stroke is more prevalent than reported clinical history of stroke.
Keywords: Aged; Brain; Cerebral Infarction; Cerebral Ventricles; Cerebrovascular Disorders; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Diagnosis, Differential; Feasibility Studies; Female; Humans; Image Interpretation, Computer-Assisted; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mass Screening; Observer Variation; Pilot Projects; Prospective Studies; Risk Factors; United States

Clinical correlates of white matter findings on cranial magnetic resonance imaging of 3301 elderly people. The Cardiovascular Health Study. - Longstreth, W T; Manolio, T A; Arnold, A; Burke, G L; Bryan, N; Jungreis, C A; Enright, P L; O'Leary, D; Fried, L (Stroke, 1996)
BACKGROUND AND PURPOSE: Our aim was to identify potential risk factors for and clinical manifestations of white matter findings on cranial MRI in elderly people. METHODS: Medicare eligibility lists were used to obtain a representative sample of 5888 community-dwelling people aged 65 years or older. Correlates of white matter findings were sought among 3301 participants who underwent MRI scanning and denied a history of stroke or transient ischemic attack. Participants underwent extensive standardized evaluations at baseline and on follow-up, including standard questionnaires, physical examination, multiple blood tests, electrocardiogram, pulmonary function tests, carotid sonography, and M-mode echocardiography. Neuroradiologists graded white matter findings from 0 (none) to 9 (maximal) without clinical information. RESULTS: Many potential risk factors were related to the white matter grade, but in the multivariate model the factors significantly (all P < .01) and independently associated with increased grade were greater age, clinically silent stroke on MRI, higher systolic blood pressure, lower forced expiratory volume in 1 second (FEV1), and income less than $50,000 per year. If excluded, FEV1 was replaced in the model by female sex, history of smoking, and history of physician-diagnosed hypertension at the baseline examination. Many clinical features were correlated with the white matter grade, especially those indicating impaired cognitive and lower extremity function. CONCLUSIONS: White matter findings were significantly associated with age, silent stroke, hypertension, FEV1, and income. The white matter findings may not be considered benign because they are associated with impaired cognitive and lower extremity function.
Keywords: Age Factors; Aged; Aging; Blood Pressure; Brain; Cardiovascular Diseases; Cerebrovascular Disorders; Cohort Studies; Female; Humans; Ischemic Attack, Transient; Magnetic Resonance Imaging; Male; Multivariate Analysis; Risk Factors; Sex Factors

Current estrogen-progestin and estrogen replacement therapy in elderly women: association with carotid atherosclerosis. CHS Collaborative Research Group. Cardiovascular Health Study. - Jonas, H A; Kronmal, R A; Psaty, B M; Manolio, T A; Meilahn, E N; Tell, G S; Tracy, R P; Robbins, J A; Anton-Culver, H (Ann Epidemiol, 1996)
The cardioprotective effects of combined estrogen/progestin replacement therapy have been questioned. Therefore, we have compared carotid arterial wall thickening and the prevalence of carotid stenosis in elderly women (> or = 65 years old) currently using replacement estrogen/progestins (E + P) with arterial pathology and its prevalence in women using unopposed estrogens (E). This cross-sectional study used baseline data from all 2962 women participating in the Cardiovascular Health Study, a population-based study of coronary heart disease and stroke in elderly adults. Users of hormone replacement therapy (HRT) were categorized as never (n = 1726), past (n = 787), current E (n = 280), or current E + P (n = 73). Maximal intimal-medial thicknesses of the internal and common carotid arteries and stenosis of the internal carotid arteries were measured by ultrasonography. Current E + P users resembled current E users in most respects, although some lifestyle factors were more favorable among E + P users. Current E + P use and current E use (as compared with no use) were associated with smaller internal carotid wall thicknesses (-0.22 mm; P = 0.003; and -0.09 mm; P = 0.05, respectively) and smaller common carotid wall thicknesses (-0.05 mm; P = 0.03; and -0.02 mm; P = 0.1, respectively) and lower odds ratios (OR) for carotid stenosis (> or = 1% vs. 0%); OR = 0.61; 95% confidence interval [CI]: 0.36 to 1.01; and OR = 0.91, 95% CI: 0.67 to 1.24, respectively), after adjustment for current lifestyle and risk factors. When both groups of current HRT users were compared, there were no significant differences in carotid wall thicknesses or prevalence of carotid stenosis. For this sample of elderly women, both current E + P therapy and current E therapy were associated with decreased measures of carotid atherosclerosis. These measures did not differ significantly between the two groups of HRT users.
Keywords: Aged; Arteriosclerosis; Carotid Arteries; Carotid Stenosis; Cohort Studies; Confidence Intervals; Cross-Sectional Studies; Databases, Factual; Drug Therapy, Combination; Estrogen Replacement Therapy; Estrogens; Female; Health Status Indicators; Humans; Odds Ratio; Progestins; Reproductive History; Ultrasonography; United States; Women's Health

Clinically serious abnormalities found incidentally at MR imaging of the brain: data from the Cardiovascular Health Study. - Yue, N C; Longstreth, W T; Elster, A D; Jungreis, C A; O'Leary, D H; Poirier, V C (Radiology, 1997)
PURPOSE: To determine the prevalence of clinically serious findings unrelated to stroke on cranial magnetic resonance (MR) images in a population of community-dwelling elderly people. MATERIALS AND METHODS: Neuroradiologists reviewed MR images of 3,672 people aged 65 years and older who were enrolled in a longitudinal, population-based study of cardiovascular and cerebrovascular disease. The neuroradiologists alerted MR imaging field centers about potentially serious abnormalities. Clinical information was obtained from clinical examinations performed before MR imaging, hospital discharge summaries, and the field centers at which MR imaging was performed. RESULTS: On 3,672 image sets, 64 (1.74%) clinically serious abnormalities were found. Among the presumptive diagnoses were 19 meningiomas (0.52%), six pituitary adenomas (0.16%), five cavernous malformations (0.14%), eight vascular stenoses (0.22%), four aneurysms (0.11%), two intraventricular masses (0.05%), two subdural fluid collections (0.05%), and two other tumors (0.05%). Only nine participants with these abnormalities required surgery. All but one of the meningiomas were in women, and the prevalence of the tumor decreased with increasing age. CONCLUSION: Physicians should be alert to the possible presence of clinically serious conditions in otherwise asymptomatic elderly individuals.
Keywords: Aged; Aged, 80 and over; Brain; Brain Diseases; Cardiovascular Diseases; Cohort Studies; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male

Health effects of caregiving: the caregiver health effects study: an ancillary study of the Cardiovascular Health Study. - Schulz, R; Newsom, J; Mittelmark, M; Burton, L; Hirsch, C; Jackson, S (Ann Behav Med, 1997)
We propose that two related sources of variability in studies of caregiving health effects contribute to an inconsistent pattern of findings: the sampling strategy used and the definition of what constitutes caregiving. Samples are often recruited through self-referral and are typically comprised of caregivers experiencing considerable distress. In this study, we examine the health effects of caregiving in large population-based samples of spousal caregivers and controls using a wide array of objective and self-report physical and mental health outcome measures. By applying different definitions of caregiving, we show that the magnitude of health effects attributable to caregiving can vary substantially, with the largest negative health effects observed among caregivers who characterize themselves as being strained. From an epidemiological perspective, our data show that approximately 80% of persons living with a spouse with a disability provide care to their spouse, but only half of care providers report mental or physical strain associated with caregiving.
Keywords: Activities of Daily Living; Aged; Arousal; Cardiovascular Diseases; Caregivers; Cerebrovascular Disorders; Coronary Disease; Cost of Illness; Female; Geriatric Assessment; Health Behavior; Health Status; Humans; Male; Psychophysiologic Disorders; Risk Factors; Spouses; Stress, Psychological

Infarctlike lesions in the brain: prevalence and anatomic characteristics at MR imaging of the elderly--data from the Cardiovascular Health Study. - Bryan, R N; Wells, S W; Miller, T J; Elster, A D; Jungreis, C A; Poirier, V C; Lind, B K; Manolio, T A (Radiology, 1997)
PURPOSE: To determine the prevalence and anatomic characteristics of infarctlike lesions seen on cranial magnetic resonance (MR) images. MATERIALS AND METHODS: The study cohort consisted of 5,888 community-living individuals aged 65 years and older enrolled in a longitudinal, population-based study of cardiovascular disease. MR images were obtained from 3,658 participants and evaluated by trained readers. Lesion size, anatomic location, and signal intensity were recorded. Infarctlike lesion was defined as a nonmass, hyperintense region on spin-density- and T2-weighted images and, in cerebral white matter and brain stem, a hypointense region on T1-weighted images. RESULTS: Infarctlike lesions were depicted on MR images of 1,323 (36%) participants. Eighty-five percent (1,128 participants) had lesions 3 mm or larger in maximum dimension, although 70.9% (1,320 of 1,861) of these lesions were 10 mm or less. Lesion prevalence increased with age, especially with lesions 3 mm or larger, which increased from 22.1% (86 of 389) in the 65-69-year age group to 42.9% (88 of 205) in the over-85-year age group (P < .0001). Lesion prevalence was slightly greater in men (497 of 1,527 [32.5%]) than in women (631 of 2,131 [29.6%]), but did not differ between blacks and non-blacks. The deep nuclei were the most commonly affected anatomic sites, with 78.2% (1,451 of 1,856) of lesions. Lesions that involved the cerebrum and posterior fossa accounted for 11.7% (218 of 1,856) and 10.1% (187 of 1,856) of lesions, respectively. CONCLUSION: If the lesions reported in this study indicate cerebrovascular disease, subclinical disease may be more prevalent than clinical disease, and the prevalence of disease may rise with age. Also, infarctlike lesions have a distinctive anatomic profile.
Keywords: Aged; Brain; Cardiovascular Diseases; Cerebral Infarction; Cohort Studies; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Prevalence

Sulcal, ventricular, and white matter changes at MR imaging in the aging brain: data from the cardiovascular health study. - Yue, N C; Arnold, A M; Longstreth, W T; Elster, A D; Jungreis, C A; O'Leary, D H; Poirier, V C; Bryan, R N (Radiology, 1997)
PURPOSE: To determine the distribution of changes in sulcal size, ventricular size, and white matter signal intensity depicted on cranial magnetic resonance (MR) images, with stratification according to age, race, and sex. MATERIALS AND METHODS: Ventricular size, sulcal size, and white matter signal intensity changes were graded on cranial MR images of 3,660 community-living, elderly participants in the Cardiovascular Health Study. A healthier subgroup was also defined. Summary statistics for both groups were generated for age, race, and sex. RESULTS: Regression models of the entire imaged cohort showed higher grades of all variables with increasing age, and higher ventricular and sulcal grades in men and in nonblack individuals. White matter grade was greater in women and in black individuals. Regression models of the healthier subgroup showed similar associations, except for a lack of association of sulcal and ventricular size with race. CONCLUSION: Sulcal width, ventricular size, and white matter signal intensity change with age, sex, and race. Knowledge of these changes is important in appropriate interpretation of MR images of the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Brain; Cardiovascular Diseases; Cerebral Ventricles; Cohort Studies; Continental Population Groups; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Reproducibility of Results; Sex Factors

Differences in prevalence of and risk factors for subclinical vascular disease among black and white participants in the Cardiovascular Health Study. - Kuller, L; Fisher, L; McClelland, R; Fried, L; Cushman, M; Jackson, S; Manolio, T (Arterioscler Thromb Vasc Biol, 1998)
A composite measure of subclinical vascular disease has been developed in the Cardiovascular Health Study (CHS). In previous reports, we measured the prevalence of subclinical disease among the original 5201 participants in the CHS, the relationship of risk factors to subclinical disease, and the association of subclinical disease to clinical coronary heart disease. In 1992 to 1993 (year 4 of the study), a larger cohort of 424 black women and 248 black men was added to the study. In this study, we have compared the prevalence of subclinical disease among blacks and whites in the CHS and the association with cardiovascular risk factors. The prevalence of subclinical disease for all participants (aged > or =65 years) was 41.3% for white women, 39.7% for black women, 41.9% for white men, and 43.7% for black men. The prevalence increased with age. The risk factor associations for subclinical disease were similar among blacks and whites. In multivariate analysis, age, systolic blood pressure, LDL cholesterol, smoking, and family history of myocardial infarction were independently associated with subclinical disease among both black and white women, while for white men, systolic blood pressure, use of antihypertensive medication, smoking, body mass index, and diastolic blood pressure (inverse) were related to subclinical disease. In black men, blood triglyceride level, use of antihypertensive medications, and family history of myocardial infarction (inverse) were associated with subclinical disease.
Keywords: African Americans; Aged; Cardiovascular Physiological Phenomena; Cohort Studies; European Continental Ancestry Group; Female; Health Status; Humans; Male; Multivariate Analysis; Prevalence; Regression Analysis; Risk Factors; Vascular Diseases

Lacunar infarcts defined by magnetic resonance imaging of 3660 elderly people: the Cardiovascular Health Study. - Longstreth, W T; Bernick, C; Manolio, T A; Bryan, N; Jungreis, C A; Price, T R (Arch Neurol, 1998)
OBJECTIVE: To identify risk factors for and functional consequences of lacunar infarct in elderly people. METHODS: The Cardiovascular Health Study (CHS) is a longitudinal study of people 65 years or older, in which 3660 participants underwent cranial magnetic resonance imaging (MRI). Neuroradiologists read scans in a standard fashion without any clinical information. Lacunes were defined as subcortical areas consistent with infarcts measuring 3 to 20 mm. In cross-sectional analyses, clinical correlates were contrasted among groups defined by MRI findings. RESULTS: Of the 3660 subjects who underwent MRI, 2529 (69%) were free of infarcts of any kind and 841 (23%) had 1 or more lacunes without other types present, totaling 1270 lacunes. For most of these 841 subjects, their lacunes were single (66%) and silent (89%), namely without a history of transient ischemic attack or stroke. In multivariate analyses, factors independently associated with lacunes were increased age, diastolic blood pressure, creatinine, and pack-years of smoking (listed in descending order of strength of association; for all, P < .005), as well as maximum internal carotid artery stenosis of more than 50% (odds ratio [OR], 1.81; P < .005), male sex (OR, 0.74; P < .005), and history of diabetes at entrance into the study (OR, 1.33; P < .05). Models for subgroups of single, multiple, silent, and symptomatic lacunes differed only minimally. Those with silent lacunes had more cognitive, upper extremity, and lower extremity dysfunction not recognized as stroke than those whose MRIs were free of infarcts. CONCLUSIONS: In this group of older adults, lacunes defined by MRI are common and associated with factors that likely promote or reflect small-vessel disease. Silent lacunes are also associated with neurologic dysfunction.
Keywords: Aged; Cerebral Infarction; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Multivariate Analysis; Risk Factors

Relation of sleepiness to respiratory disturbance index: the Sleep Heart Health Study. - Gottlieb, D J; Whitney, C W; Bonekat, W H; Iber, C; James, G D; Lebowitz, M; Nieto, F J; Rosenberg, C E (Am J Respir Crit Care Med, 1999)
Obstructive sleep apnea syndrome is a well recognized cause of excessive sleepiness; however, the relation of sleepiness to mild sleep-disordered breathing (SDB), which affects as much as half the adult population, is uncertain. In order to explore this relation, we conducted a cross-sectional cohort study of community-dwelling adults participating in the Sleep Heart Health Study, a longitudinal study of the cardiovascular consequences of SDB. The study sample comprises 886 men and 938 women, with a mean age of 65 (SD 11) yr. Sleepiness was quantified using the Epworth Sleepiness Scale (ESS). Sleep-disordered breathing was quantified by the respiratory disturbance index (RDI), defined as the number of apneas plus hypopneas per hour of sleep, measured during in-home polysomnography. When RDI was categorized into four groups (< 5, 5 to < 15, 15 to < 30, >/= 30), a significantly progressive increase in mean ESS score was seen across all four levels of SDB, from 7.2 (4.3) in subjects with RDI < 5 to 9.3 (4.9) in subjects with RDI >/= 30 (p < 0.001). There was no significant modification of this effect by age, sex, body mass index, or evidence of chronic restriction of sleep time or periodic limb movement disorder. The percentage of subjects with excessive sleepiness, defined as an ESS score >/= 11, increased from 21% in subjects with RDI < 5 to 35% in those with RDI >/= 30 (p < 0. 001). We conclude that SDB is associated with excess sleepiness in community-dwelling, middle-aged and older adults, not limited to those with clinically apparent sleep apnea.
Keywords: Aged; Cardiovascular Diseases; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Polysomnography; Respiration; Retrospective Studies; Severity of Illness Index; Sleep Apnea Syndromes; Surveys and Questionnaires

The role of APOE epsilon4 in modulating effects of other risk factors for cognitive decline in elderly persons. - Haan, M N; Shemanski, L; Jagust, W J; Manolio, T A; Kuller, L (JAMA, 1999)
CONTEXT: Cognitive decline in elderly persons is often an early predictor of dementia. Subclinical cardiovascular disease (CVD) and diabetes mellitus may contribute to substantial decline in cognitive function in the elderly. These risks may be modified by gene-environment interactions between apolipoprotein E (APOE) genotype and CVD risk factors or subclinical CVD. OBJECTIVES: To examine the association between subclinical CVD and decline in cognitive functioning in the elderly and to examine effect modification by the APOE genotype of the association between subclinical disease and cognitive decline. DESIGN: The Cardiovascular Health Study, a population-based, prospective cohort study. SETTING AND POPULATION: A total of 5888 randomly selected Medicare-eligible participants from Sacramento County, California; Forsyth County, North Carolina; Washington County, Maryland; and Pittsburgh, Pa, aged 65 years or older, who were recruited in 1989-1990 (n = 5201) and in 1992-1993 (n = 687) and who were followed up for 7 and 5 years, respectively. MAIN OUTCOME MEASURES: Change over time in scores on the Modified Mini-Mental State Examination and the Digit Symbol Substitution Test as a function of APOE genotype, subclinical CVD, and diabetes mellitus. RESULTS: Seventy percent of participants had no significant decline on the Modified Mini-Mental State Examination. Systolic blood pressure, the ankle-arm brachial index, atherosclerosis of the internal carotid artery, diabetes mellitus, and several diagnoses of prevalent CVD were significantly associated with declines in scores on the Modified Mini-Mental State Examination and the Digit Symbol Substitution Test. The rate of cognitive decline associated with peripheral vascular disease, atherosclerosis of the common and internal carotid arteries, or diabetes mellitus was increased by the presence of any APOE epsilon4 allele. CONCLUSIONS: Most healthy elderly people did not experience cognitive decline. Measures of subclinical CVD were modest predictors of cognitive decline. Those with any APOE epsilon4 allele in combination with atherosclerosis, peripheral vascular disease, or diabetes mellitus were at substantially higher risk of cognitive decline than those without the APOE epsilon4 allele or subclinical CVD. High levels of atherosclerosis increased cognitive decline independently of APOE genotype.
Keywords: Aged; Aging; Alleles; Apolipoproteins E; Cardiovascular Diseases; Cognition Disorders; Cohort Studies; Diabetes Mellitus; Genotype; Humans; Mental Status Schedule; Prospective Studies; Risk Factors

Clinical correlates of ventricular and sulcal size on cranial magnetic resonance imaging of 3,301 elderly people. The Cardiovascular Health Study. Collaborative Research Group. - Longstreth, W T; Arnold, A M; Manolio, T A; Burke, G L; Bryan, N; Jungreis, C A; O'Leary, D; Enright, P L; Fried, L (Neuroepidemiology, 2000)
To identify potential risk factors for and clinical manifestations of ventricular and sulcal enlargement on cranial magnetic resonance imaging (MRI), 3,301 community-dwelling people 65 years or older without a history of stroke or transient ischemic attack underwent extensive standardized evaluations and MRI. In the multivariate model, increased age and white matter grade on MRI were the dominant risk factors for ventricular and sulcal grade. For ventricular grade, other than race, for which non-Blacks had higher grades, models for men and women shared no other factors. For sulcal grades, models for men and women shared variables reflecting cigarette smoking and diabetes. Clinical features were correlated more strongly with ventricular than sulcal grade and more strongly for women than men. Significant age-adjusted correlations between ventricular grade and the Digit-Symbol Substitution Test were found for men and women. Prospective studies will be needed to extend findings of this cross-sectional analysis.
Keywords: Age Distribution; Age Factors; Aged; Aging; Cerebral Ventricles; Continental Population Groups; Cross-Sectional Studies; Diabetes Complications; Female; Humans; Hypertrophy; Linear Models; Magnetic Resonance Imaging; Male; Multivariate Analysis; Risk Factors; Severity of Illness Index; Sex Distribution; Sex Factors; Smoking; Stroke

Negative and positive health effects of caring for a disabled spouse: longitudinal findings from the caregiver health effects study. - Beach, S R; Schulz, R; Yee, J L; Jackson, S (Psychol Aging, 2000)
Data from the first 2 waves of the Caregiver Health Effects Study (n = 680) were analyzed to examine the effects of changes in caregiving involvement on changes in caregiver health-related outcomes in a population-based sample of elders caring for a disabled spouse. Caregiving involvement was indexed by levels of (a) spouse physical impairment, (b) help provided to the spouse, and (c) strain associated with providing help. Health-related outcomes included perceived health, health-risk behaviors, anxiety symptoms, and depression symptoms. Increases in spouse impairment and caregiver strain were generally related to poorer outcomes over time (poorer perceived health, increased health-risk behaviors, and increased anxiety and depression), whereas increased helping was related to better outcomes (decreased anxiety and depression). Results suggest that caring for a disabled spouse is a complex phenomenon that can have both deleterious and beneficial consequences.
Keywords: Aged; Anxiety; Caregivers; Depression; Disabled Persons; Female; Health Behavior; Health Status; Humans; Longitudinal Studies; Male; Mental Health; Risk-Taking; Spouses

Area characteristics and individual-level socioeconomic position indicators in three population-based epidemiologic studies. - Diez-Roux, A V; Kiefe, C I; Jacobs, D R; Haan, M; Jackson, S A; Nieto, F J; Paton, C C; Schulz, R (Ann Epidemiol, 2001)
PURPOSE: There is growing interest in incorporating area indicators into epidemiologic analyses. Using data from the 1990 U.S. Census linked to individual-level data from three epidemiologic studies, we investigated how different area indicators are interrelated, how measures for different sized areas compare, and the relation between area and individual-level social position indicators. METHODS: The interrelations between 13 area indicators of wealth/income, education, occupation, and other socioenvironmental characteristics were investigated using correlation coefficients and factor analyses. The extent to which block-group measures provide information distinct from census tract measures was investigated using intraclass correlation coefficients. Loglinear models were used to investigate associations between area and individual-level indicators. RESULTS: Correlations between area measures were generally in the 0.5--0.8 range. In factor analyses, six indicators of income/wealth, education, and occupation loaded on one factor in most geographic sites. Correlations between block-group and census tract measures were high (correlation coefficients 0.85--0.96). Most of the variability in block-group indicators was between census tracts (intraclass correlation coefficients 0.72--0.92). Although individual-level and area indicators were associated, there was evidence of important heterogeneity in area of residence within individual-level income or education categories. The strength of the association between individual and area measures was similar in the three studies and in whites and blacks, but blacks were much more likely to live in more disadvantaged areas than whites. CONCLUSIONS: Area measures of wealth/income, education, and occupation are moderately to highly correlated. Differences between using census tract or block-group measures in contextual investigations are likely to be relatively small. Area and individual-level indicators are far from perfectly correlated and provide complementary information on living circumstances. Differences in the residential environments of blacks and whites may need to be taken into account in interpreting race differences in epidemiologic studies.
Keywords: Adult; Black or African American; Cardiovascular Diseases; Demography; Educational Status; Factor Analysis, Statistical; Humans; Income; Linear Models; Occupations; Risk Factors; Social Class; Social Environment; Socioeconomic Factors; Statistics, Nonparametric; United States; White People

Cluster analysis and patterns of findings on cranial magnetic resonance imaging of the elderly: the Cardiovascular Health Study. - Longstreth, W T; Diehr, P; Manolio, T A; Beauchamp, N J; Jungreis, C A; Lefkowitz, D (Arch Neurol, 2001)
OBJECTIVE: To characterize patterns of findings on cranial magnetic resonance imaging (MRI) of the elderly using a statistical technique called cluster analysis. SUBJECTS AND METHODS: The Cardiovascular Health Study is a population-based, longitudinal study of 5888 people 65 years and older. Of these, 3230 underwent cranial MRI scans, which were coded for presence of infarcts and grades for white matter, ventricles, and sulci. Cluster analysis separated participants into 5 clusters based solely on patterns of MRI findings. Participants comprising each cluster were contrasted with respect to cardiovascular risk factors and clinical manifestations. RESULTS: One cluster was low on all the MRI findings (normal) and another was high on all of them (complex infarcts). Another cluster had evidence for infarcts alone (simple infarcts), whereas the last 2 clusters lacked infarcts, one having enlarged ventricles and sulci (atrophy) and the other having prominent white matter changes and enlarged ventricles (leukoaraiosis). Factors that distinguished these clusters in a discriminant analysis were age, sex, several measures of hypertension, internal carotid artery wall thickness, smoking, and prevalent claudication before the MRI. The atrophy group had the highest percentage of men and the normal group had the lowest. Cognitive and motor performance also differed across clusters, with the atrophy cluster performing better than may have been expected. CONCLUSIONS: These MRI patterns identified participants with different vascular disease risk factors and clinical manifestations. Results of these exploratory analyses warrant consideration in other populations of elderly people. Such patterns may provide clues about the pathophysiology of structural brain changes in the elderly.
Keywords: Aged; Brain; Cerebral Infarction; Cerebrovascular Disorders; Cluster Analysis; Cohort Studies; Discriminant Analysis; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors

Incidence and predictors of coronary heart disease among older African Americans--the Cardiovascular Health Study. - Jackson, S A; Burke, G L; Thach, C; Cushman, M; Ives, D; Powe, N; Manolio, T A (J Natl Med Assoc, 2001)
Although coronary heart disease (CHD) is the leading cause of death and morbidity in older African Americans, relatively little is known about the incidence and predictors of CHD in this population. This study was undertaken to determine the incidence and predictors of CHD in African-American men and women aged 65 years and older. The participants in this study included a total of 924 African-American men and women aged 65 years of age and older who participated in the Cardiovascular Health Study (CHS). The overall CHD incidence was 26.6 per 1,000 person-years of risk. Rates were higher in men than women (35.3 vs. 21.6) and in those 75 years or older than in those less than 75 years (31.3 vs. 24.5). In multivariate analysis, factors associated with higher risk of incident disease were male gender [relative risk (RR) = 1.8, 95% confidence interval (CI) = 1.1, 2.7], diabetes mellitus (RR = 1.9, 95% CI = 1.2, 2.9), total cholesterol (RR for 40 mg/dL increment = 1.3, 95% CI = 1.0, 1.5), and low (i.e., <0.9) ankle-arm index (RR = 2.1, 95% CI = 1.3, 3.4) after adjusting for age. Within this cohort of older African Americans, male gender, diabetes mellitus, total cholesterol, and low ankle-arm index and were independently predictive of incident events. These results suggest that the ankle-arm index, a measure of advanced atherosclerosis, should be further evaluated for its efficacy in identifying older African Americans at risk for incident clinical events.
Keywords: Age Distribution; Aged; Black or African American; Coronary Disease; Female; Health Status; Humans; Incidence; Male; Predictive Value of Tests

Involvement in caregiving and adjustment to death of a spouse: findings from the caregiver health effects study. - Schulz, R; Beach, S R; Lind, B; Martire, L M; Zdaniuk, B; Hirsch, C; Jackson, S; Burton, L (JAMA, 2001)
CONTEXT: Most deaths in the United States occur among older persons who have 1 or more disabling conditions. As a result, many deaths are preceded by an extended period during which family members provide care to their disabled relative. OBJECTIVE: To better understand the effect of bereavement on family caregivers by examining predeath vs postdeath changes in self-reported and objective health outcomes among elderly persons providing varying levels of care prior to their spouse's death. DESIGN AND SETTING: Prospective, population-based cohort study conducted in 4 US communities between 1993 and 1998. PARTICIPANTS: One hundred twenty-nine individuals aged 66 to 96 years whose spouse died during an average 4-year follow-up. Individuals were classified as noncaregivers (n = 40), caregivers who reported no strain (n = 37), or strained caregivers (n = 52). MAIN OUTCOME MEASURES: Changes in depression symptoms (assessed by the 10-item Center for Epidemiological Studies-Depression [CES-D] scale), antidepressant medication use, 6 health risk behaviors, and weight among the 3 groups of participants. RESULTS: Controlling for age, sex, race, education, prevalent cardiovascular disease at baseline, and interval between predeath and postdeath assessments, CES-D scores remained high but did not change among strained caregivers (9.44 vs 9.19; P =.76), while these scores increased for both noncaregivers (4.74 vs 8.25; F(1,116) = 14.33; P<.001) and nonstrained caregivers (4.94 vs 7.13; F(1,116) = 4.35; P =.04). Noncaregivers were significantly more likely to be using nontricyclic antidepressant medications following the death than the nonstrained caregiver group (odds ratio [OR], 12.85; 95% confidence interval [CI], 1.02-162.13; P =.05). The strained caregiver group experienced significant improvement in health risk behaviors following the death of their spouse (1.47 vs 0.66 behaviors; F(1,118) = 20.23; P<.001), while the noncaregiver and nonstrained caregiver groups showed little change (0.27 vs 0.27 [P =.99] and 0.46 vs 0.27 [P =.39] behaviors, respectively). Noncaregivers experienced significant weight loss following the death (149.1 vs 145.3 lb [67.1 vs 65.4 kg]; F(1,101) = 8.12; P =.005), while the strained and nonstrained caregiving groups did not show significant weight change (156.2 vs 155.2 lb [70.3 vs 69.8 kg] [P =.41] and 156.2 vs 154.0 lb [70.3 vs 69.3 kg] [P =.12], respectively). CONCLUSIONS: These data indicate that the impact of losing one's spouse among older persons varies as a function of the caregiving experiences that precede the death. Among individuals who are already strained prior to the death of their spouse, the death itself does not increase their level of distress. Instead, they show reductions in health risk behaviors. Among noncaregivers, losing one's spouse results in increased depression and weight loss.
Keywords: Aged; Aged, 80 and over; Antidepressive Agents; Bereavement; Caregivers; Death; Depression; Female; Follow-Up Studies; Health Behavior; Humans; Male; Socioeconomic Factors; Spouses; Weight Loss

In the elderly, interleukin-6 plasma levels and the -174G>C polymorphism are associated with the development of cardiovascular disease. - Jenny, Nancy S; Tracy, Russell P; Ogg, Malcolm S; Luong, Le Ahn; Kuller, Lewis H; Arnold, Alice M; Sharrett, A Richey; Humphries, Steve E (Arterioscler Thromb Vasc Biol, 2002)
OBJECTIVE: Interleukin (IL)-6-mediated inflammation is involved in cardiovascular disease (CVD). We assessed IL-6 levels and the -174G>C genotype in a case-control study of men and women (average age 73 years) within the Cardiovascular Health Study. METHODS AND RESULTS: Cases included incident angina, myocardial infarction (MI), and stroke (5-year follow-up), prevalent MI, and MRI-detectable infarcts. A control group and a group free of subclinical CVD were used for comparison. The -174C allele was associated with higher C-reactive protein (11% higher, P=0.02), fibrinogen (3% higher, P=0.02), and IL-6 (5% higher; P=0.16). IL-6 was associated with increased atherosclerosis when the control group was compared with the group free of subclinical CVD. No further association with CVD events was found when case groups were compared with the control group. Compared with its absence, presence of the -174C allele was associated with risk of MRI infarcts (odds ratio 1.5). CONCLUSIONS: IL-6 levels differentiated those with subclinical CVD from those without. Although the -174C allele was not associated with incident events, associations of the genotype with inflammation and MRI infarcts, combined with the plasma IL-6 results, suggest that IL-6 may chronically predispose an individual to develop atherosclerosis.
Keywords: Age Factors; Aged; Biomarkers; Cardiovascular Diseases; Case-Control Studies; Cytosine; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Guanine; Health Surveys; Humans; Inflammation; Interleukin-6; Linear Models; Male; Polymorphism, Genetic; Predictive Value of Tests; Promoter Regions, Genetic

No association of plasma prothrombin concentration or the G20210A mutation with incident cardiovascular disease: results from the Cardiovascular Health Study. - Smiles, Adam M; Jenny, Nancy S; Tang, Zhonghua; Arnold, Alice; Cushman, Mary; Tracy, Russell P (Thromb Haemost, 2002)
Prothrombin is a key factor in blood clotting, a process intimately involved in thrombotic disease. We assessed prothrombin levels and G20210A genotype in a case-control study within the Cardiovascular Health Study. Cases included angina, myocardial infarction, stroke, and the presence of MRI-detectable infarcts (n approximately 250 each). Population-based controls free of clinical cardiovascular disease (CVD) (n approximately 500) and a subset free of clinical and subclinical CVD (n approximately 250) were used for comparison. The 20210 A allele, frequency 2.9%, was associated with higher mean prothrombin levels: 166.3 vs. 139.5 microg/ml (P <0.001). Significant correlates of prothrombin included gender, plasma lipids, other vitamin K-dependent proteins, and inflammatory markers, but not race, smoking, hypertension, diabetes, measures of subclinical CVD, or markers of procoagulant activity. Compared to controls, neither genotype nor prothrombin level was associated with any CVD case group. We conclude that, in the elderly, neither prothrombin level nor 20210 genotype were associated with either CVD risk factors or events. This is consistent with the lack of association of prothrombin levels with measures of underlying CVD or procoagulant markers.
Keywords: 3' Untranslated Regions; Aged; Aged, 80 and over; Alleles; Angina Pectoris; Blood Proteins; Cardiovascular Diseases; Case-Control Studies; Comorbidity; Diabetes Mellitus; Female; Genetic Predisposition to Disease; Humans; Hyperlipidemias; Hypertension; Male; Mutation; Myocardial Infarction; Obesity; Promoter Regions, Genetic; Prothrombin; Risk Factors; Smoking; Stroke; Vermont

Prevalence of neuropsychiatric symptoms in dementia and mild cognitive impairment: results from the cardiovascular health study. - Lyketsos, Constantine G; Lopez, Oscar; Jones, Beverly; Fitzpatrick, Annette L; Breitner, John; DeKosky, Steven (JAMA, 2002)
CONTEXT: Mild cognitive impairment (MCI) may be a precursor to dementia, at least in some cases. Dementia and MCI are associated with neuropsychiatric symptoms in clinical samples. Only 2 population-based studies exist of the prevalence of these symptoms in dementia, and none exist for MCI. OBJECTIVE: To estimate the prevalence of neuropsychiatric symptoms in dementia and MCI in a population-based study. DESIGN: Cross-sectional study derived from the Cardiovascular Health Study, a longitudinal cohort study. SETTING AND PARTICIPANTS: A total of 3608 participants were cognitively evaluated using data collected longitudinally over 10 years and additional data collected in 1999-2000 in 4 US counties. Dementia and MCI were classified using clinical criteria and adjudicated by committee review by expert neurologists and psychiatrists. A total of 824 individuals completed the Neuropsychiatric Inventory (NPI); 362 were classified as having dementia, 320 as having MCI; and 142 did not meet criteria for MCI or dementia. MAIN OUTCOME MEASURE: Prevalence of neuropsychiatric symptoms, based on ratings on the NPI in the previous month and from the onset of cognitive symptoms. RESULTS: Of the 682 individuals with dementia or MCI, 43% of MCI participants (n = 138) exhibited neuropsychiatric symptoms in the previous month (29% rated as clinically significant) with depression (20%), apathy (15%), and irritability (15%) being most common. Among the dementia participants, 75% (n = 270) had exhibited a neuropsychiatric symptom in the past month (62% were clinically significant); 55% (n = 199) reported 2 or more and 44% (n = 159) 3 or more disturbances in the past month. In participants with dementia, the most frequent disturbances were apathy (36%), depression (32%), and agitation/aggression (30%). Eighty percent of dementia participants (n = 233) and 50% of MCI participants (n = 139) exhibited at least 1 NPI symptom from the onset of cognitive symptoms. There were no differences in prevalence of neuropsychiatric symptoms between participants with Alzheimer-type dementia and those with other dementias, with the exception of aberrant motor behavior, which was more frequent in Alzheimer-type dementia (5.4% vs 1%; P =.02). CONCLUSIONS: Neuropsychiatric symptoms occur in the majority of persons with dementia over the course of the disease. These are the first population-based estimates for neuropsychiatric symptoms in MCI, indicating a high prevalence associated with this condition as well. These symptoms have serious adverse consequences and should be inquired about and treated as necessary. Study of neuropsychiatric symptoms in the context of dementia may improve our understanding of brain-behavior relationships.
Keywords: Aged; Aggression; Anxiety; Behavioral Symptoms; Cognition Disorders; Comorbidity; Cross-Sectional Studies; Delusions; Dementia; Depression; Feeding and Eating Disorders; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Prevalence; Sleep Wake Disorders

Prevalence of renovascular disease in the elderly: a population-based study. - Hansen, Kimberley J; Edwards, Matthew S; Craven, Timothy E; Cherr, Gregory S; Jackson, Sharon A; Appel, Richard G; Burke, Gregory L; Dean, Richard H (J Vasc Surg, 2002)
PURPOSE: The purpose of this investigation was to estimate the population-based prevalence of renovascular disease (RVD), defined as > or = 60% diameter-reducing renal artery stenosis or occlusion, and to define its associations with age, gender, race, and other potential risk factors among participants in the Cardiovascular Health Study (CHS). METHODS: The CHS is a multicenter, longitudinal cohort study of cardiovascular disease risk factors, morbidity, and mortality among free-living adults of more than 65 years of age. As part of an ancillary investigation, participants in the Forsyth County cohort of the CHS were invited to undergo renal duplex sonography (RDS) to define the presence or absence of RVD. RVD was defined as stenosis with a focal renal artery peak systolic velocity exceeding 1.8 m/s in the main renal artery and defined as occlusion when an imaged renal artery lacked a Doppler signal. Demographic and atherosclerotic risk factor data were gathered as part of the baseline CHS examination. Univariable tests of association were performed with chi(2) and Student t tests and logistic regression analysis. Multivariate associations were examined with logistic regression analysis. RESULTS: Eight hundred seventy CHS participants underwent RDS. Of these examinations, 834 (96%) were technically adequate to define the presence or absence of RVD. The RDS study cohort had a mean age of 77.2 +/- 4.9 years and consisted of 63% women and 37% men. Participant race was 76% white and 23% African American. The overall prevalence rate of RVD was 6.8%. Among the 57 patients with RVD, 50 (88%) had unilateral disease and seven (12%) had bilateral disease. Seven cases were seen of renal artery occlusion, including one case with contralateral renal artery stenosis. The mean ages of patients with and without RVD were 78.7 +/- 5.7 years and 77.1 +/- 4.9 years (P =.018). RVD was present in 5.5% of women and 9.1% of men (P =.053). RVD was present in 6.9% of white participants and 6.7% of African American participants (P =.933). Multivariate analysis revealed increasing participant age (P =.028; odds ratio, 1.34; 95% CI, 1.03, 1.73), high-density lipoprotein cholesterol levels of less than 40 mg/dL (P =.003; odds ratio, 2.63; 95% CI, 1.40, 4.93), and increasing systolic blood pressure (P =.007; odds ratio, 1.44; 95% CI, 1.10, 1.87) to be significantly and independently associated with the presence of RVD. CONCLUSION: This investigation provides the first population-based estimate of the prevalence of RVD among free-living, elderly black and white Americans. RVD was present in 6.8% of the study cohort. RVD showed no association with ethnicity. However, its presence was significantly and independently associated with increasing age, low high-density lipoprotein cholesterol levels, and increasing systolic blood pressure.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Ethnic Groups; Female; Humans; Longitudinal Studies; Male; Prevalence; Prospective Studies; Renal Artery; Renal Artery Obstruction; Risk Factors; Sex Factors; Ultrasonography, Doppler, Duplex

Weight-modification trials in older adults: what should the outcome measure be? - Diehr, Paula; Newman, Anne B; Jackson, Sharon A; Kuller, Lewis; Powe, Neil (Curr Control Trials Cardiovasc Med, 2002)
BACKGROUND: Overweight older adults are often counseled to lose weight, even though there is little evidence of excess mortality in that age group. Overweight and underweight may be more associated with health status than with mortality, but few clinical trials of any kind have been based on maximizing years of healthy life (YHL), as opposed to years of life (YOL). OBJECTIVE: This paper examines the relationship of body mass index (BMI) to both YHL and YOL. Results were used to determine whether clinical trials of weight-modification based on improving YHL would be more powerful than studies based on survival. DESIGN: We used data from a cohort of 4,878 non-smoking men and women aged 65-100 at baseline (mean age 73) and followed 7 years. We estimated mean YHL and YOL in four categories of BMI: underweight, normal, overweight, and obese. RESULTS: Subjects averaged 6.3 YOL and 4.6 YHL of a possible 7 years. Both measures were higher for women and whites. For men, none of the BMI groups was significantly different from the normal group on either YOL or YHL. For women, the obese had significantly lower YHL (but not YOL) than the normals, and the underweight had significantly lower YOL and YHL. The overweight group was not significantly different from the normal group on either measure. CONCLUSIONS: Clinical trials of weight loss interventions for obese older women would require fewer participants if YHL rather than YOL was the outcome measure. Interventions for obese men or for the merely overweight are not likely to achieve differences in either YOL or YHL. Evaluations of interventions for the underweight (which would presumably address the causes of their low weight) may be conducted efficiently using either outcome measure.

Lack of association of the plasminogen activator inhibitor-1 4G/5G promoter polymorphism with cardiovascular disease in the elderly. - Crainich, P; Jenny, N S; Tang, Z; Arnold, A M; Kuller, L H; Manolio, T; Sharrett, A R; Tracy, R P (J Thromb Haemost, 2003)
Elevated circulating plasminogen activator inhibitor-1 (PAI-1) may increase risk of cardiovascular disease (CVD). The 4G allele of the 4G/5G PAI-1 promoter polymorphism is associated with higher levels of PAI-1. We examined the association of PAI-1 4G/5G genotype and CVD events in the elderly participants of the Cardiovascular Health Study (CHS). We measured 4G/5G genotype in a nested case-control study within the CHS. Cases included incident angina, myocardial infarction (MI), and stroke. 4G/5G genotype was not found to be associated with markers of fibrinolysis or CVD risk in the selected elderly cohort. There were no differences in genotype frequencies by case-control status (5G/5G frequency 16-22%; chi2P= 0.07). The 5G allele was not associated with incident CVD events when individuals with at least one 5G allele were compared to 4G/4G homozygotes. The presence of at least one 4G allele was likewise not associated with incident CVD when those with 4G/4G and 4G/5G genotypes were compared to 5G/5G homozygotes. Our results suggest that the PAI-1 4G/5G promoter polymorphism is not associated CVD risk factors or incident CVD events in the elderly.
Keywords: African Continental Ancestry Group; Aged; Alleles; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Risk

Prevalence and classification of mild cognitive impairment in the Cardiovascular Health Study Cognition Study: part 1. - Lopez, Oscar L; Jagust, William J; DeKosky, Steven T; Becker, James T; Fitzpatrick, Annette; Dulberg, Corinne; Breitner, John; Lyketsos, Constantine; Jones, Beverly; Kawas, Claudia; Carlson, Michelle; Kuller, Lewis H (Arch Neurol, 2003)
OBJECTIVE: To examine the prevalence of mild cognitive impairment (MCI) and its diagnostic classification in the Cardiovascular Health Study (CHS) Cognition Study. DESIGN: The CHS Cognition Study is an ancillary study of the CHS that was conducted to determine the presence of MCI and dementia in the CHS cohort. SETTING: Multicenter population study. PATIENTS: We examined 3608 participants in the CHS who had undergone detailed neurological, neuropsychological, neuroradiological, and psychiatric testing to identify dementia and MCI. MAIN OUTCOME MEASURES: The prevalence of MCI was determined for the whole cohort, and specific subtypes of MCI were examined in detail only at the Pittsburgh, Pa, center (n = 927). Mild cognitive impairment was classified as either MCI amnestic-type or MCI multiple cognitive deficits-type. RESULTS: The overall prevalence of MCI was 19% (465 of 2470 participants); prevalence increased with age from 19% in participants younger than 75 years to 29% in those older than 85 years. The overall prevalence of MCI at the Pittsburgh center was 22% (130 of 599 participants); prevalence of the MCI amnesic-type was 6% and of the MCI multiple cognitive deficits-type was 16%. CONCLUSIONS: Twenty-two percent of the participants aged 75 years or older had MCI. Mild cognitive impairment is a heterogeneous syndrome, where the MCI amnestic-type is less frequent than the MCI multiple cognitive deficits-type. Most of the participants with MCI had comorbid conditions that may affect their cognitive functions.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognition Disorders; Cohort Studies; Dementia; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Memory Disorders; Neuropsychological Tests; Pennsylvania; Population; Psychiatric Status Rating Scales

Risk factors for mild cognitive impairment in the Cardiovascular Health Study Cognition Study: part 2. - Lopez, Oscar L; Jagust, William J; Dulberg, Corinne; Becker, James T; DeKosky, Steven T; Fitzpatrick, Annette; Breitner, John; Lyketsos, Constantine; Jones, Beverly; Kawas, Claudia; Carlson, Michelle; Kuller, Lewis H (Arch Neurol, 2003)
OBJECTIVE: To examine the risk factors for mild cognitive impairment (MCI) in a longitudinal population study-the Cardiovascular Health Study Cognition Study. DESIGN: We examined the factors that in the period 1991 through 1994 predicted the development of MCI in all participants of the Cardiovascular Health Study Cognition Study. Further examination was conducted in the Pittsburgh, Pa, cohort (n = 927), where participants with MCI were classified as having either the MCI amnestic-type or the MCI multiple cognitive deficits-type. SETTING: Multicenter population study. PATIENTS: This study includes all participants of the Cardiovascular Health Study Cognition Study (n = 3608) who had a magnetic resonance imaging (MRI) scan of the brain between 1991 and 1994, and detailed neuropsychological, neurological, and medical evaluations to identify the presence of MCI or dementia in the period 1998 to 1999. The mean time between the closest clinical examination to the MRI and the diagnostic evaluation for cognitive disorders was 5.8 years for the Cardiovascular Health Study Cognition Study cohort and 6.0 years for the Pittsburgh cohort. MAIN OUTCOME MEASURES: Risk factors for MCI at the time of the MRI were identified using logistic regression, controlling for age, race, educational level, baseline Modified Mini-Mental State Examination and Digit Symbol Test scores, measurements of depression, MRI findings (atrophy, ventricular volume, white matter lesions, and infarcts), the presence of the apolipoprotein E (APOE) epsilon4 allele, hypertension, diabetes mellitus, and heart disease. RESULTS: Mild cognitive impairment (n = 577) was associated with race (African American), low educational level, low Modified Mini-Mental State Examination and Digit Symbol Test scores, cortical atrophy, MRI-identified infarcts, and measurements of depression. The MCI amnestic-type was associated with MRI-identified infarcts, the presence of the APOE epsilon4 allele, and low Modified Mini-Mental State Examination scores. The MCI multiple cognitive deficits-type was associated with low Modified Mini-Mental State Examination and Digit Symbol Test scores. CONCLUSIONS: The development of MCI is associated with measurements of cognition and depression, racial and constitutional factors, and cerebrovascular disease. Early cognitive deficits seem to be a common denominator for the 2 forms of MCI; the presence of cerebrovascular disease and the APOE epsilon4 allele is associated with the amnestic type of MCI.
Keywords: Aged; Apolipoprotein E4; Apolipoproteins E; Brain; Cardiovascular Diseases; Cognition Disorders; Cohort Studies; Depressive Disorder; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mood Disorders; Pennsylvania; Population; Risk Factors

Transitions in spousal caregiving. - Burton, Lynda C; Zdaniuk, Bozena; Schulz, Richard; Jackson, Sharon; Hirsch, Calvin (Gerontologist, 2003)
PURPOSE: This study describes transitions over 5 years among community-dwelling elderly spouses into and within caregiving roles and associated health outcomes. DESIGN AND METHODS: Participants in the Caregiver Health Effects Study (n = 818) were interviewed four times over 5 years with changes in their caregiving status described. Analyses of the effect on health outcomes of transitions were performed on those for whom four observations were available (n = 428). RESULTS: Only half (49.5%) of noncaregivers at baseline remained noncaregivers at 5-year follow-up. The remainder experienced one or more transitions, including moving into the caregiving role, their own or their spouse's death, or placement of their spouse in a long-term care facility. The trajectory of health outcomes associated with caregiving was generally downward. Those who transitioned to heavy caregiving had more symptoms of depression, and poorer self-reported health and health behaviors. IMPLICATIONS: Transitions into and within the caregiving role should be monitored for adverse health effects on the caregiver, with interventions tailored to the individual's location in the caregiving trajectory.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Caregivers; Female; Health Behavior; Health Status; Humans; Long-Term Care; Male; Residence Characteristics; Spouses; Stress, Psychological; Time Factors

The association of personal and neighborhood socioeconomic indicators with subclinical cardiovascular disease in an elderly cohort. The cardiovascular health study. - Nordstrom, Cheryl K; Diez Roux, Ana V; Jackson, Sharon A; Gardin, Julius M (Soc Sci Med, 2004)
There has been recent interest in determining whether neighborhood characteristics are related to the cardiovascular health of residents. However, there are no data regarding the relationship between neighborhood socioeconomic status (SES) and prevalence of subclinical cardiovascular disease (CVD) in the elderly. We related personal SES (education, income, and occupation type) and neighborhood socioeconomic characteristics (a block-group score summing six variables reflecting neighborhood income and wealth, education, and occupation) to the prevalence of subclinical CVD (asymptomatic peripheral vascular disease or carotid atherosclerosis, electrocardiogram or echocardiogram abnormalities, and/or positive responses to Rose Questionnaire claudication or angina pectoris) among 3545 persons aged 65 and over, without prevalent CVD, in the Cardiovascular Health Study. Sixty percent of participants had at least one indicator of subclinical disease. Compared to those without, those with subclinical disease had significantly lower education, income, and neighborhood scores and were more likely to have blue-collar jobs. After adjustment for age, gender, and race, those in the lowest SES groups had increased prevalence of subclinical disease compared with those in the highest SES groups (OR = 1.50; 95% CI 1.21, 1.86 for income; OR = 1.41; 95% CI 1.18, 1.69 for education; OR = 1.39; 95% CI 1.16, 1.67 for block-group score). Those reporting a blue-collar lifetime occupation had greater prevalence of subclinical disease relative to those reporting a white-collar occupation (OR = 1.29; 95% CI 1.02-1.59). After adjustment for behavioral and biomedical risk factors, all of these associations were reduced. Neighborhood score tended to remain inversely associated with subclinical disease after adjustment for personal socioeconomic indicators but associations were not statistically significant. Personal income and blue-collar occupation remained significantly associated with subclinical disease after simultaneous adjustment for neighborhood score and education. Personal and neighborhood socioeconomic indicators were associated with subclinical disease prevalence in this elderly cohort. These relationships were reduced after controlling for traditional CVD risk factors.
Keywords: Aged; California; Cardiovascular Diseases; Cohort Studies; Female; Geography; Humans; Male; Maryland; Medicare; North Carolina; Pennsylvania; Residence Characteristics; Risk Factors; Social Class; Socioeconomic Factors; Surveys and Questionnaires

Cognitive impairment and decline are associated with carotid artery disease in patients without clinically evident cerebrovascular disease. - Johnston, S Claiborne; O'Meara, Ellen S; Manolio, Teri A; Lefkowitz, David; O'Leary, Daniel H; Goldstein, Steven; Carlson, Michelle C; Fried, Linda P; Longstreth, W T (Ann Intern Med, 2004)
BACKGROUND: Whether carotid artery disease is a cause of cognitive impairment in persons who have not had stroke is unknown. If this is the case, diminished performance on the Modified Mini-Mental State Examination should be more common in persons with left carotid artery disease than in those with right carotid artery disease. OBJECTIVE: To determine whether left carotid artery disease is associated with cognitive impairment. DESIGN: Cross-sectional and cohort study. SETTING: Four U.S. communities participating in the Cardiovascular Health Study. PATIENTS: 4006 right-handed men and women 65 years of age or older without history of stroke, transient ischemic attack, or carotid endarterectomy. MEASUREMENTS: Internal carotid artery stenosis and intima-media thickness of the common carotid artery were assessed by using duplex ultrasonography. Cognitive impairment was defined as a score less than 80 on the Modified Mini-Mental State Examination, and cognitive decline was defined as an average decrease of more than 1 point annually in Modified Mini-Mental State Examination score during up to 5 years of follow-up. Multivariate logistic regression models were used to estimate the risk for cognitive impairment and decline associated with left internal carotid artery stenosis and intima-media thickness, after adjustment for measures of right-sided disease and risk factors for vascular disease. RESULTS: After adjustment for right-sided stenosis, high-grade (> or =75% narrowing of diameter) stenosis of the left internal carotid artery (32 patients) was associated with cognitive impairment (odds ratio, 6.7 [95% CI, 2.4 to 18.1] compared with no stenosis) and cognitive decline (odds ratio, 2.6 [CI, 1.1 to 6.3]). Intima-media thickness of the left common carotid artery was associated with cognitive impairment and decline in univariate analysis, but this effect did not persist after adjustment. CONCLUSIONS: Cognitive impairment and decline are associated with asymptomatic high-grade stenosis of the left internal carotid artery. The persistence of the association after adjustment for right-sided stenosis indicates that the association is not due to underlying vascular risk factors or atherosclerosis in general.
Keywords: Aged; Carotid Stenosis; Cognition Disorders; Cohort Studies; Cross-Sectional Studies; Female; Humans; Male; Neuropsychological Tests; Odds Ratio; Risk Factors; Tunica Intima

Concurrent and long-term predictors of older adults' use of community-based long-term care services: the Caregiver Health Effects Study. - Bookwala, Jamila; Zdaniuk, Bozena; Burton, Lynda; Lind, Bonnie; Jackson, Sharon; Schulz, Richard (J Aging Health, 2004)
OBJECTIVE: This study examined concurrent and long-term associations between caregiver-related characteristics and the use of community long-term care services in a sample of 186 older adults caring for a disabled spouse. METHOD: We used two waves of data from the Caregiver Health Effects Study, an ancillary study of the Cardiovascular Health Study. Caregiver-related need variables as predictors of service use were of primary interest and included caregiving demands, caregiver mental and physical health, and mastery. Their contribution to service use was examined after controlling for known predictors of service use. RESULTS: At Time 1, more caregiver depressive symptoms predicted greater service use; at Time 2, more caregiver activity restriction and depressive symptoms predicted greater formal service use; increases in caregiver activity restriction and depressive symptomatology over time predicted increases in service use. DISCUSSION: Caregiver-related need variables play a significant role in defining utilization patterns of community-based long-term care services among older adults.
Keywords: Aged; Caregivers; Community Health Services; Disabled Persons; Forecasting; Health Services for the Aged; Humans; Long-Term Care; Regression Analysis; Spouses; United States

Incidence and prevalence of dementia in the Cardiovascular Health Study. - Fitzpatrick, Annette L; Kuller, Lewis H; Ives, Diane G; Lopez, Oscar L; Jagust, William; Breitner, John C S; Jones, Beverly; Lyketsos, Constantine; Dulberg, Corinne (J Am Geriatr Soc, 2004)
OBJECTIVES: To estimate the incidence and prevalence of dementia, Alzheimer's disease (AD), and vascular dementia (VaD) in the Cardiovascular Health Study (CHS) cohort. DESIGN: Longitudinal cohort study using prospectively and retrospectively collected data to evaluate dementia. SETTING: Four U.S. communities. PARTICIPANTS: There were 3,602 CHS participants, including 2,865 white and 492 African-American participants free of dementia, who completed a cranial magnetic resonance image between 1992 and 1994 and were followed for an average of 5.4 years. MEASUREMENTS: Dementia was classified by neurologist/psychiatrist committee review using neuropsychological tests, neurological examinations, medical records, physician questionnaires, and proxy/informant interviews. Demographics and apolipoprotein E (APOE) genotype were collected at baseline. Incidence by type of dementia was determined using National Institute of Neurological and Communicative Disorders and Stroke-Alzheimer's Disease and Related Disorders Association criteria for AD and Alzheimer's Disease Diagnostic and Treatment Center's State of California criteria for VaD. RESULTS: Classification resulted in 227 persons with prevalent dementia at entry into the study and 480 incident cases during follow-up. Incidence rates of dementia scaled to age 80 were 34.7 per 1,000 person-years for white women, 35.3 for white men, 58.8 for African-American women, and 53.0 for African-American men. Sex differences were not significant within race. Adjusted for age and education, racial differences were only of borderline significance and may have been influenced by ascertainment methodology. Rates differed substantially by educational attainment but were only significant for whites. Those with the APOE epsilon4 allele had an incidence rate at age 80 of 56.4, compared with 29.6 for those without this allele (P<.001). In whites, type-specific incidence at age 80 was 19.2 for AD versus 14.6 for VaD. These rates were 34.7 and 27.2 for African Americans. At termination of observation, women had only a slightly higher prevalence of dementia (16.0%) than men (14.7%). CONCLUSION: Sex and racial differences were not found, and VaD was higher than reported in other studies. These data provide new estimates of dementia incidence in a community sample for projection of future burden.
Keywords: African Americans; Age Distribution; Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Dementia; Dementia, Vascular; Education; European Continental Ancestry Group; Female; Humans; Incidence; Longitudinal Studies; Male; Prevalence; Proportional Hazards Models; Risk Factors; Sex Distribution; United States

Neighbourhood environments and mortality in an elderly cohort: results from the cardiovascular health study. - Diez Roux, Ana V; Borrell, Luisa N; Haan, Mary; Jackson, Sharon A; Schultz, Richard (J Epidemiol Community Health, 2004)
BACKGROUND: It has been postulated that neighbourhood conditions are related to the health of the elderly population but longitudinal studies are rare and confounding by individual level variables remains a possibility. METHODS: Data were obtained from the cardiovascular health study, a population based study of adults aged 65 years and older. Census block groups were used as proxies for neighbourhoods. A summary score was used to characterise the neighbourhood socioeconomic environment. Information on personal socioeconomic indicators, cardiovascular disease prevalence, and cardiovascular risk factors was obtained from the baseline examination. Proportional hazards regression and propensity score matching were used to control for individual level variables. RESULTS: Over the eight year follow up there were 1346 deaths among the 5074 participants, of which 43% were attributable to cardiovascular disease. Among white participants, living in the most disadvantaged neighbourhood group was associated with higher rates of cardiovascular death, after adjustment for income, education, and occupation (hazard ratio (HR) 1.5, 95% confidence intervals (CI) 1.2 to 1.9). No neighbourhood differences were observed for non-cardiovascular deaths. Estimates for black participants were 1.3 (95% CI 0.7 to 2.3) for cardiovascular deaths and 1.4 (95% CI 0.8 to 2.4) for non-cardiovascular deaths, but sample size was small. In white participants, associations of neighbourhood characteristics with cardiovascular mortality persisted after adjustment for prevalent baseline disease and cardiovascular risk factors. The use of propensity score matching led to similar results (HR for the lowest compared with the highest neighbourhood score group: 1.6 95% CI 1.1 to 2.5, controlling for personal socioeconomic indicators). CONCLUSION: Neighbourhood disadvantage is related to rates of cardiovascular death in elderly white adults.
Keywords: African Americans; Aged; Cardiovascular Diseases; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Income; Male; Poverty Areas; Residence Characteristics; Risk Factors; Socioeconomic Factors; United States

Stroke risk factors and loss of high cognitive function. - Elkins, J S; O'Meara, E S; Longstreth, W T; Carlson, M C; Manolio, T A; Johnston, S C (Neurology, 2004)
BACKGROUND: Modifiable stroke risk factors may contribute to age-associated declines in cognitive function. Individuals with high levels of cognitive function after midlife may have less exposure to these stroke risk factors or may be less susceptible to their effects on cognition. METHODS: The Cardiovascular Health Study (CHS)* is a population-based, longitudinal cohort study of 5,888 people age 65 years and older. Participants (n = 4,129) who were free of dementia, stroke, or TIA at the time of baseline cranial MRI were selected for analysis. High cognitive function at baseline was defined by performance at or above midlife norms on the Modified Mini-Mental State Examination (3MS). RESULTS: The odds of having high cognitive function at baseline decreased by quartile of stroke risk (highest vs lowest risk quartile, adjusted odds ratio [OR] 0.68; 95% CI 0.52 to 0.88; p for trend = 0.005). Stroke risk was a predictor of decline on the 3MS in those with typical levels of cognitive function at baseline, even in the absence of incident stroke or TIA (highest vs lowest risk quartile for 3MS decline, adjusted OR 2.11; 95% CI 1.42 to 3.13; p for trend < 0.001). In contrast, stroke risk was not associated with decline on the 3MS in those with high cognitive function at baseline (p = 0.03 for interaction). CONCLUSIONS: In a cohort of older adults without stroke, TIA, or dementia, cognitive function and incident cognitive decline were associated with risk for stroke. Additional studies are needed to determine whether modification of stroke risk factors can reduce the cognitive decline that is often attributed to normal aging.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Cohort Studies; Comorbidity; Female; Follow-Up Studies; Higher Nervous Activity; Humans; Incidence; Male; Risk Assessment; Risk Factors; Sampling Studies; Sensitivity and Specificity; Severity of Illness Index; Stroke; United States

Alcohol use and risk of ischemic stroke among older adults: the cardiovascular health study. - Mukamal, Kenneth J; Chung, Hyoju; Jenny, Nancy S; Kuller, Lewis H; Longstreth, W T; Mittleman, Murray A; Burke, Gregory L; Cushman, Mary; Beauchamp, Norman J; Siscovick, David S (Stroke, 2005)
BACKGROUND AND PURPOSE: The association of light to moderate alcohol consumption with risk of ischemic stroke remains uncertain, as are the roles of potentially mediating factors and modification by apolipoprotein E (apoE) genotype. METHODS: We studied the prospective association of alcohol consumption and risk of ischemic stroke among 4410 participants free of cardiovascular disease at baseline in the Cardiovascular Health Study, a population-based cohort study of older adults from 4 US communities. Participants reported their consumption of alcoholic beverages yearly. RESULTS: During an average follow-up period of 9.2 years, 434 cases of incident ischemic stroke occurred. Compared with long-term abstainers, the multivariate relative risks of ischemic stroke were 0.85 (95% CI, 0.63 to 1.13), 0.75 (95% CI, 0.53 to 1.06), 0.82 (95% CI, 0.51 to 1.30), and 1.03 (95% CI, 0.68 to 1.57) among consumers of <1, 1 to 6, 7 to 13, and > or =14 drinks per week (P quadratic trend 0.06). ApoE genotype appeared to modify the alcohol-ischemic stroke relationship (P interaction 0.08), with generally lower risks among drinkers than abstainers in apoE4-negative participants but higher risks among drinkers than abstainers among apoE4-positive participants. We could not identify candidate mediators among lipid, inflammatory, and prothrombotic factors. CONCLUSIONS: In this study of older adults, the association of alcohol use and risk of ischemic stroke was U-shaped, with modestly lower risk among consumers of 1 to 6 drinks per week. However, apoE genotype may modify this association, and even moderate alcohol intake may be associated with an increased risk of ischemic stroke among apoE4-positive older adults.
Keywords: Aged; Alcohol Drinking; Apolipoproteins E; Brain Infarction; Brain Ischemia; Cohort Studies; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Inflammation; Ischemia; Lipids; Male; Middle Aged; Multivariate Analysis; Myocardial Infarction; Prospective Studies; Risk; Risk Factors; Stroke; Substance-Related Disorders; Thrombosis; Time Factors; Vascular Diseases

Classification of vascular dementia in the Cardiovascular Health Study Cognition Study. - Lopez, O L; Kuller, L H; Becker, J T; Jagust, W J; DeKosky, S T; Fitzpatrick, A; Breitner, J; Lyketsos, C; Kawas, C; Carlson, M (Neurology, 2005)
OBJECTIVE: To describe the diagnostic classification of subjects with incident vascular dementia (VaD) participating in the Cardiovascular Health Study (CHS) Cognition Study. METHODS: The CHS classified 480 incident cases between 1994 and 1999 among 3,608 CHS participants who had brain MRI in 1992 through 1994 and in 1997 through 1998. The patients were diagnosed before and after reviewing the brain MRI. RESULTS: The pre-MRI classification showed that 52 participants had VaD and 76 had both Alzheimer disease (AD) and VaD. The post-MRI classification showed that the Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV) criteria classified 61 subjects as having VaD, the National Institute of Neurological Disorders and Stroke-Association Internationale pour la Recherche et l'Enseignement en Neurosciences (NINDS-AIREN) criteria classified 43 subjects as having probable VaD and 10 as possible VaD, and the State of California Alzheimer's Disease Diagnostic and Treatment Center (ADDTC) criteria classified 117 as having probable VaD and 96 as possible. The combination of the ADDTC and National Institute of Neurological and Communication Disorders and Stroke-Alzheimer's Disease and Related Disorders Association criteria was used to examine the spectrum of vascular disease in dementia. The dementia was attributable to only vascular factors in 56 cases (probable VaD); VaD coexisted with AD in 61 cases, although the VaD component was the leading cause of dementia (probable VaD with AD); AD was the leading cause of dementia in 61 cases (possible VaD and probable AD); and in 29 cases, it was not clear that either AD or VaD was the primary diagnosis (possible AD and possible VaD). CONCLUSIONS: None of the clinical criteria for VaD identified the same group of subjects. The diagnosis of vascular dementia is difficult in epidemiologic studies because poststroke dementia can be due to Alzheimer disease (AD) and evidence of vascular disease can be found in the MRI of dementia cases without clinical strokes. Whether the clinical progression is related to AD pathology or vascular disease is difficult to establish.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cerebral Arteries; Cohort Studies; Dementia, Vascular; Diagnosis, Differential; Disease Progression; Female; Humans; Magnetic Resonance Imaging; Male; Predictive Value of Tests; Stroke; United States

Common promoter polymorphisms of inflammation and thrombosis genes and longevity in older adults: the cardiovascular health study. - Reiner, Alexander P; Diehr, Paula; Browner, Warren S; Humphries, Stephen E; Jenny, Nancy S; Cushman, Mary; Tracy, Russell P; Walston, Jeremy; Lumley, Thomas; Newman, Anne B; Kuller, Lewis H; Psaty, Bruce M (Atherosclerosis, 2005)
Inflammatory response genes may influence life span or quality at advanced ages. Using data from the population-based cardiovascular health study (CHS) cohort, we examined the associations between promoter polymorphisms of several inflammation and thrombosis genes with longevity. We ascertained genotypes for interleukin (IL)-6 -174 G/C, beta-fibrinogen -455 G/A, plasminogen activator inhibitor (PAI)-1 -675 4G/5G, and thrombin-activatable fibrinolysis inhibitor (TAFI) -438 G/A in 2224 men and women > or = 65 years old at baseline. During 10 years of follow-up, men with the TAFI -438 A/A genotype had decreased mortality due to all causes, and lived, on average, 0.9 more years of life, or 1.1 more years of healthy life, than men with the -438 G allele. The effects of TAFI -438 G/A in women were smaller and not statistically significant. PAI-1 4G/4G genotype appeared to be associated with lower non-cardiovascular mortality in men, but with greater cardiovascular mortality in women. In exploratory analyses, we observed a possible interaction among anti-inflammatory drugs, interleukin-6 -174 C/C genotype, and longevity. These findings suggest that modulators of fibrinolytic activity may have a generalized influence on aging, and merit further investigation in studies of genetic determinants of human longevity.
Keywords: Aged; Aging; Carboxypeptidase B2; Cause of Death; Cohort Studies; Female; Genotype; Health Status; Humans; Inflammation; Longevity; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Prospective Studies; Risk Factors; Thrombosis

The course of functional decline in older people with persistently elevated depressive symptoms: longitudinal findings from the Cardiovascular Health Study. - Lenze, Eric J; Schulz, Richard; Martire, Lynn M; Zdaniuk, Bozena; Glass, Thomas; Kop, Willem J; Jackson, Sharon A; Reynolds, Charles F (J Am Geriatr Soc, 2005)
OBJECTIVES: To examine the relationship between persistently high depressive symptoms and long-term changes in functional disability in elderly persons. DESIGN: A community-based, prospective, observational study. SETTING: Participant data from the Cardiovascular Health Study. PARTICIPANTS: From the overall sample of 5,888 subjects, three types of participants were identified for this study: (1) persistently depressed individuals, who experienced an onset of depressive symptoms that persisted over 4 years (n=119); (2) temporarily depressed individuals, who experienced an onset of depressive symptoms that resolved over time (n=259); and (3) nondepressed individuals, with persistently low depressive symptoms throughout the follow-up period who were matched on baseline activity of daily living (ADL) scores, sex, and age to the previous two groups combined (n=378). MEASUREMENTS: Four consecutive years of data were assessed: validated measures of depression (10-item CES-D), functional disability (10-item ADL/instrumental ADL measure), physical performance, medical illness, and cognition. RESULTS: The persistently depressed group showed a greater linear increase in functional disability ratings than the temporarily depressed and nondepressed groups. This association between persistent depression and functional disability was robust even when controlling for baseline demographic and clinical/performance measures, including cognition. The persistently depressed group had an adjusted odds ratio (OR) of 5.27 (95% confidence interval (CI) 3.03-9.16) for increased functional disability compared with the nondepressed group over 3 years of follow-up, whereas the temporarily depressed group had an adjusted OR of 2.39 (95% CI=1.55-3.69) compared with the nondepressed group. CONCLUSION: Persistently elevated depressive symptoms in elderly persons are associated with a steep trajectory of worsening functional disability, generating the hypothesis that treatments for late-life depression need to be assessed on their efficacy in maintaining long-term functional status as well as remission of depressive symptoms. These results also demonstrate the need for studies to differentiate between persistent and temporary depressive symptoms when examining their relationship to disability.
Keywords: Activities of Daily Living; Aged; Case-Control Studies; Depressive Disorder; Disabled Persons; Female; Humans; Longitudinal Studies; Male; Multivariate Analysis; Risk; United States

Cystatin C concentration as a risk factor for heart failure in older adults. - Sarnak, Mark J; Katz, Ronit; Stehman-Breen, Catherine O; Fried, Linda F; Jenny, Nancy Swords; Psaty, Bruce M; Newman, Anne B; Siscovick, David; Shlipak, Michael G (Ann Intern Med, 2005)
BACKGROUND: Previous studies that evaluated the association of kidney function with incident heart failure may be limited by the insensitivity of serum creatinine concentration for detecting abnormal kidney function. OBJECTIVE: To compare serum concentrations of cystatin C (a novel marker of kidney function) and creatinine as predictors of incident heart failure. DESIGN: Observational study based on measurement of serum cystatin C from frozen sera obtained at the 1992-1993 visit of the Cardiovascular Health Study. Follow-up occurred every 6 months. SETTING: Adults 65 years of age or older from 4 communities in the United States. PARTICIPANTS: 4384 persons without previous heart failure who had measurements of serum cystatin C and serum creatinine. MEASUREMENTS: Incident heart failure. RESULTS: The mean (+/-SD) serum concentrations of cystatin C and creatinine were 82 +/- 25 nmol/L (1.10 +/- 0.33 mg/L) and 89 +/- 34 micromol/L (1.01 +/- 0.39 mg/dL), respectively. During a median follow-up of 8.3 years (maximum, 9.1 years), 763 (17%) participants developed heart failure. After adjustment for demographic factors, traditional and novel cardiovascular risk factors, cardiovascular disease status, and medication use, sequential quintiles of cystatin C concentration were associated with a stepwise increased risk for heart failure in Cox proportional hazards models (hazard ratios, 1.0 [reference], 1.30 [95% CI, 0.96 to 1.75], 1.44 [CI, 1.07 to 1.94], 1.58 [CI, 1.18 to 2.12], and 2.16 [CI, 1.61 to 2.91]). In contrast, quintiles of serum creatinine concentration were not associated with risk for heart failure in adjusted analysis (hazard ratios, 1.0 [reference], 0.77 [CI, 0.59 to 1.01], 0.85 [CI, 0.64 to 1.13], 0.97 [CI, 0.72 to 1.29], and 1.14 [CI, 0.87 to 1.49]). LIMITATIONS: The mechanism by which cystatin C concentration predicts risk for heart failure remains unclear. CONCLUSIONS: The cystatin C concentration is an independent risk factor for heart failure in older adults and appears to provide a better measure of risk assessment than the serum creatinine concentration. *For a full list of participating Cardiovascular Health Study investigators and institutions, see http://www.chs-nhlbi.org.
Keywords: Aged; Biomarkers; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Incidence; Kidney; Kidney Function Tests; Male; Risk Factors; United States

Cystatin-C and mortality in elderly persons with heart failure. - Shlipak, Michael G; Katz, Ronit; Fried, Linda F; Jenny, Nancy Swords; Stehman-Breen, Catherine O; Newman, Anne B; Siscovick, David; Psaty, Bruce M; Sarnak, Mark J (J Am Coll Cardiol, 2005)
OBJECTIVES: We sought to evaluate cystatin-C, a novel measure of renal function, as a predictor of mortality in elderly persons with heart failure (HF) and to compare it with creatinine. BACKGROUND: Renal function is an important prognostic factor in patients with HF, but creatinine levels, which partly reflect muscle mass, may be insensitive for detecting renal insufficiency. METHODS: A total of 279 Cardiovascular Health Study participants with prevalent HF and measures of serum cystatin-C and creatinine were followed for mortality outcomes over a median of 6.5 years. RESULTS: Median creatinine and cystatin-C levels were 1.05 mg/dl and 1.26 mg/l. Each standard deviation increase in cystatin-C (0.35 mg/l) was associated with a 31% greater adjusted mortality risk (95% confidence interval [CI] 20% to 43%, p < 0.001), whereas each standard deviation increase in creatinine (0.39 mg/dl) was associated with a 17% greater adjusted mortality risk (95% CI 1% to 36%, p = 0.04). When both measures were combined in a single adjusted model, cystatin-C remained associated with elevated mortality risk (hazard ratio 1.60, 95% CI 1.32 to 1.94), whereas creatinine levels appeared associated with lower risk (hazard ratio 0.73, 95% CI 0.57 to 0.95). CONCLUSIONS: Cystatin-C is a stronger predictor of mortality than creatinine in elderly persons with HF. If confirmed in future studies, this new marker of renal function could improve risk stratification in patients with HF.
Keywords: Age Factors; Aged; Aged, 80 and over; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Male; Pilot Projects; Predictive Value of Tests; Risk Assessment; Survival Analysis

Dementia and Alzheimer's disease incidence in relationship to cardiovascular disease in the Cardiovascular Health Study cohort. - Newman, Anne B; Fitzpatrick, Annette L; Lopez, Oscar; Jackson, Sharon; Lyketsos, Constantine; Jagust, William; Ives, Diane; DeKosky, Steven T; Kuller, Lewis H (J Am Geriatr Soc, 2005)
OBJECTIVES: To determine whether coronary artery disease, peripheral arterial disease (PAD), or noninvasive markers of cardiovascular disease (CVD) predict the onset of dementia and Alzheimer's disease (AD). DESIGN: Longitudinal cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Men and women (N=3,602) with a brain magnetic resonance imaging (MRI) scan but no dementia were followed for 5.4 years. Participants with stroke were excluded. MEASUREMENTS: Neurologists and psychiatrists classified incident cases of dementia and subtype using neuropsychological tests, examination, medical records and informant interviews. CVD was defined at the time of the MRI scan. Noninvasive tests of CVD were assessed within 1 year of the MRI. Apolipoprotein E allele status, age, race, sex, education, Mini-Mental State Examination score, and income were assessed as potential confounders. RESULTS: The incidence of dementia was higher in those with prevalent CVD, particularly in the subgroup with PAD. The rate of AD was 34.4 per 1,000 person-years for those with a history of CVD, versus 22.2 per 1,000 person-years without a history of CVD (adjusted hazard ratio (HR)=1.3, 95% confidence interval (CI)=1.0-1.7). Rates of AD were highest in those with PAD (57.4 vs 23.7 per 100 person-years, adjusted HR=2.4, 95% CI=1.4-4.2). Results were similar with further exclusion of those with vascular dementia from the AD group. A gradient of increasing risk was noted with the extent of vascular disease. CONCLUSION: Older adults with CVD other than stroke had a higher risk of dementia and AD than did those without CVD. The risk was highest in people with PAD, suggesting that extensive peripheral atherosclerosis is a risk factor for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Dementia; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Peripheral Vascular Diseases; Risk Factors

Determinants of vascular dementia in the Cardiovascular Health Cognition Study. - Kuller, L H; Lopez, O L; Jagust, W J; Becker, J T; DeKosky, S T; Lyketsos, C; Kawas, C; Breitner, J C S; Fitzpatrick, A; Dulberg, C (Neurology, 2005)
OBJECTIVE: The authors evaluated 3,375 participants without dementia at the time of MRI in 1991 to 1994 over 5.7 years for incident dementia and type of dementia. METHODS: Incidence of and risk factors for vascular dementia (VaD) were measured using both pre-MRI and modified State of California Alzheimer's Disease Diagnostic and Treatment Centers (ADDTC) post-MRI review and further classified Alzheimer disease (AD) by the National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association (NINCDS-ADRDA) criteria. RESULTS: Approximately 44% (213) of 480 incident dementia cases were classified as possible or probable VaD by ADDTC. The incidence of VaD increased with age and was greater in blacks than whites. Risk factors for VaD included age, Modified Mini-Mental State Examination, high white matter grade, number of MRI infarcts, ventricular size, and history of stroke. CONCLUSIONS: Vascular disease in the brain is prevalent among incident dementia cases. There is a substantial overlap between cases classified as Alzheimer disease by Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association and vascular dementia (VaD) by modified State of California Alzheimer's Disease Diagnostic and Treatment Centers criteria. The substantial contribution of vascular disease would be missed without inclusion of MRI. Treatment of risk factors for VaD could have an important impact on incidence of dementia.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Brain; Cardiovascular Diseases; Cerebral Arteries; Cerebral Infarction; Cohort Studies; Comorbidity; Continental Population Groups; Dementia, Vascular; Female; Humans; Lateral Ventricles; Magnetic Resonance Imaging; Male; Nerve Fibers, Myelinated; Neuropsychological Tests; Risk Factors; Sex Factors

Incidence, manifestations, and predictors of worsening white matter on serial cranial magnetic resonance imaging in the elderly: the Cardiovascular Health Study. - Longstreth, W T; Arnold, Alice M; Beauchamp, Norman J; Manolio, Teri A; Lefkowitz, David; Jungreis, Charles; Hirsch, Calvin H; O'Leary, Daniel H; Furberg, Curt D (Stroke, 2005)
BACKGROUND AND PURPOSE: Magnetic resonance imaging (MRI) scans in the elderly commonly show white matter findings that may raise concerns. We sought to document incidence, manifestations, and predictors of worsening white matter grade on serial imaging. METHODS: The Cardiovascular Health Study is a population-based, longitudinal study of 5888 people aged 65 years and older, of whom 1919 have had extensive initial and follow-up evaluations, including 2 MRI scans separated by 5 years. Scans were read without clinical information in standard side-by-side fashion to determine worsening white matter grade. RESULTS: Worsening was evident in 538 participants (28%), mostly (85%) by 1 grade. Although similar at initial scan, participants with worsening white matter grade, compared with those without, experienced greater decline on modified Mini-Mental State examination and Digit-Symbol Substitution test (both P< or =0.001) after controlling for potential confounding factors, including occurrence of transient ischemic attack or stroke between scans. Independent predictors of worsening white matter grade included cigarette smoking before initial scan and infarct on initial scan. Otherwise, predictors differed according to white matter grade on initial scan. For low initial grade, increased age, increased diastolic blood pressure, increased high-density lipoprotein cholesterol, and decreased low-density lipoprotein cholesterol were associated with increased risk of worsening. For high initial grade, any cardiovascular disease and low ankle-arm index were associated with decreased risk of worsening, whereas use of diuretics and statins were associated with increased risk. CONCLUSIONS: Worsening white matter grade on serial MRI scans in elderly is common, is associated with cognitive decline, and has complex relations with cardiovascular risk factors.
Keywords: Aged; Brain; Cardiovascular Diseases; Cognition Disorders; Female; Humans; Incidence; Leukoaraiosis; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Stroke

Kidney function as a predictor of noncardiovascular mortality. - Fried, Linda F; Katz, Ronit; Sarnak, Mark J; Shlipak, Michael G; Chaves, Paulo H M; Jenny, Nancy Swords; Stehman-Breen, Catherine; Gillen, Dan; Bleyer, Anthony J; Hirsch, Calvin; Siscovick, David; Newman, Anne B (J Am Soc Nephrol, 2005)
Chronic kidney disease is associated with a higher risk for cardiovascular mortality, as well as all-cause mortality. Whether chronic kidney disease is a predictor of noncardiovascular mortality is less clear. To further explore the latter, the association of kidney function with total noncardiovascular mortality and cause-specific mortality was assessed in the Cardiovascular Health Study, a community-based cohort of older individuals. Kidney disease was assessed using cystatin C and estimated GFR in 4637 participants in 1992 to 1993. Participants were followed until June 30, 2001. Deaths were adjudicated as cardiovascular or noncardiovascular disease by committee, and an underlying cause of death was assigned. The associations of kidney function with total noncardiovascular mortality and cause-specific mortality were analyzed by proportional hazards regression. Noncardiovascular mortality rates increased with higher cystatin C quartiles (16.8, 17.1, 21.6, and 50.0 per 1000 person-years). The association of cystatin C with noncardiovascular mortality persisted after adjustment for demographic factors; the presence of diabetes, C-reactive protein, hemoglobin, and prevalent cardiovascular disease; and measures of atherosclerosis (hazard ratio 1.69; 95% confidence interval 1.33 to 2.15, for the fourth quartile versus the first quartile). Results for estimated GFR were similar. The risk for noncardiac deaths attributed to pulmonary disease, infection, cancer, and other causes was similarly associated with cystatin C levels. Kidney function predicts noncardiovascular mortality from multiple causes in the elderly. Further research is needed to understand the mechanisms and evaluate interventions to reduce the high mortality rate in chronic kidney disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Cardiovascular Diseases; Cause of Death; Cohort Studies; Confidence Intervals; Creatinine; Cystatin C; Cystatins; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Kidney Function Tests; Longitudinal Studies; Male; Probability; Proportional Hazards Models; Risk Assessment; Severity of Illness Index; Survival Analysis; United States

Methods for incorporating death into health-related variables in longitudinal studies. - Diehr, Paula; Johnson, Laura Lee; Patrick, Donald L; Psaty, Bruce (J Clin Epidemiol, 2005)
BACKGROUND AND OBJECTIVES: Longitudinal studies of health over time may be misleading if some people die. Self-rated health (excellent to poor) and the SF-36 profile scores have been transformed to incorporate death. We applied the same approaches to incorporate death into activities of daily living difficulties (ADLs), IADLs, mini-mental state examination, depressive symptoms, blocks walked per week, bed days, the timed walk, body mass index and blood pressure. STUDY DESIGN AND SETTING: The Cardiovascular Health Study of 5,888 older adults, was followed up to 9 years. Mean age was 73 at baseline, and 658 had an incident stroke during follow-up. METHODS: We recoded each variable as the probability of being healthy 1 year in the future (PHF), conditional on the current value of the variable. This was done for 11 health variables, using three definitions of healthy, and two estimation models. Deaths were set to zero, and mean PHF was plotted in the 3 years before and after an incident stroke. RESULTS: Analyses without the deaths were too optimistic. The effect of stroke was greatest on hospitalization, self-rated health, and IADLs. Alternative transformation approaches had slightly different results. CONCLUSION: These methods provide an additional approach for handling death in longitudinal studies.
Keywords: Activities of Daily Living; Death; Health Status Indicators; Humans; Longitudinal Studies; Proportional Hazards Models

Survival following dementia onset: Alzheimer's disease and vascular dementia. - Fitzpatrick, Annette L; Kuller, Lewis H; Lopez, Oscar L; Kawas, Claudia H; Jagust, William (J Neurol Sci, 2005)
Survival following the onset of dementia has been reported to vary from 3 to over 9 years. We examined mortality in 3602 participants of the Cardiovascular Health (CHS) Cognition Study in four US communities evaluated for dementia incidence between 1992 and 1999 and followed for 6.5 years. By June 2000, 33 of 62 (53.2%) participants who developed vascular dementia (VaD) had died compared to 79 of 245 (32.2%) with Alzheimer's disease (AD), 66 of 151 (43.7%) with both AD and VaD, and 429 of 2318 (18.5%) with normal cognition. Using Cox proportional hazards regression with a time-dependent covariate for dementia status adjusted for age, gender and race, individuals with VaD were more than four times as likely to die during follow-up than those with normal cognition (HR: 4.4, 95% CI: 3.1-6.3). The hazard ratios were 2.1 (95% CI: 1.6-2.7) for AD and 2.5 (95% CI: 1.9-3.3) for both types. Adjusted accelerated life models estimated median survival from dementia onset to death as 3.9 years for those with VaD, 7.1 years for AD, 5.4 years for mixed dementia, and 11.0 years for matched controls with normal cognition. While persons with VaD died primarily from cerebrovascular disease, those with AD/mixed dementia died more frequently from dementia/failure to thrive.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Capillaries; Cerebral Amyloid Angiopathy; Cerebrovascular Circulation; Cerebrovascular Disorders; Female; Frontal Lobe; Humans; Male; Middle Aged; Prospective Studies

Alcohol consumption and risk of coronary heart disease in older adults: the Cardiovascular Health Study. - Mukamal, Kenneth J; Chung, Hyoju; Jenny, Nancy S; Kuller, Lewis H; Longstreth, W T; Mittleman, Murray A; Burke, Gregory L; Cushman, Mary; Psaty, Bruce M; Siscovick, David S (J Am Geriatr Soc, 2006)
OBJECTIVES: To evaluate several aspects of the relationship between alcohol use and coronary heart disease in older adults, including beverage type, mediating factors, and type of outcome. DESIGN: Prospective cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Four thousand four hundred ten adults aged 65 and older free of cardiovascular disease at baseline. MEASUREMENTS: Risk of incident myocardial infarction or coronary death according to self-reported consumption of beer, wine, and spirits ascertained yearly. RESULTS: During an average follow-up period of 9.2 years, 675 cases of incident myocardial infarction or coronary death occurred. Compared with long-term abstainers, multivariate relative risks of 0.90 (95% confidence interval (CI)=0.71-1.14), 0.93 (95% CI=0.73-1.20), 0.76 (95% CI=0.53-1.10), and 0.58 (95% CI=0.39-0.86) were found in consumers of less than one, one to six, seven to 13, and 14 or more drinks per week, respectively (P for trend=.007). Associations were similar for secondary coronary outcomes, including nonfatal and fatal events. No strong mediators of the association were identified, although fibrinogen appeared to account for 9% to 10% of the relationship. The associations were statistically similar for intake of wine, beer, and liquor and generally similar in subgroups, including those with and without an apolipoprotein E4 allele. CONCLUSION: In this population, consumption of 14 or more drinks per week was associated with the lowest risk of coronary heart disease, although clinicians should not recommend moderate drinking to prevent coronary heart disease based on this evidence alone, because current National Institute on Alcohol Abuse and Alcoholism guidelines suggest that older adults limit alcohol intake to one drink per day.
Keywords: Aged; Alcohol Drinking; Apolipoproteins E; Beer; Cohort Studies; Coronary Disease; Female; Genotype; Health Behavior; Humans; Incidence; Male; Residence Characteristics; Risk Assessment; Socioeconomic Factors; United States; Wine

The association of race with frailty: the cardiovascular health study. - Hirsch, Calvin; Anderson, Melissa L; Newman, Anne; Kop, Willem; Jackson, Sharon; Gottdiener, John; Tracy, Russell; Fried, Linda P (Ann Epidemiol, 2006)
PURPOSE: Frailty, which has been conceptualized as a state of decreased physiologic reserve contributing to functional decline, has a prevalence among older African Americans that is twice that in older whites. This study assesses the independent contribution of race to frailty. METHODS: We evaluated 786 African-American and 4491 white participants of the Cardiovascular Health Study (CHS). Frailty is defined as meeting three or more of five criteria derived from CHS measures: lowest quintile for grip strength, self-reported exhaustion, unintentional weight loss of 10 lbs or greater in 1 year, slowest quintile for gait speed, and lowest quintile for physical activity. Controlling for age, sex, comorbidity, socioeconomic factors, and race, multinomial logistic regression estimated the odds ratio (OR) of prefrail (one or two criteria) to not frail and frail to not frail. RESULTS: Among African Americans, 8.7% of men and 15.0% of women were frail compared with 4.6% and 6.8% of white men and women, respectively. In adjusted models, nonobese African Americans had a fourfold greater odds of frailty compared with whites. The increased OR of frailty associated with African-American race was less pronounced among those who were obese or disabled. CONCLUSION: African-American race is associated independently with frailty.
Keywords: African Americans; Aged; Asthenia; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; European Continental Ancestry Group; Female; Frail Elderly; Health Status; Humans; Male; Middle Aged; Motor Activity; Odds Ratio; United States; Weight Loss

CFH, ELOVL4, PLEKHA1 and LOC387715 genes and susceptibility to age-related maculopathy: AREDS and CHS cohorts and meta-analyses. - Conley, Yvette P; Jakobsdottir, Johanna; Mah, Tammy; Weeks, Daniel E; Klein, Ronald; Kuller, Lewis; Ferrell, Robert E; Gorin, Michael B (Hum Mol Genet, 2006)
Age-related maculopathy (ARM) is an important cause of visual impairment in the elderly population. It is of crucial importance to identify genetic factors and their interactions with environmental exposures for this disorder. This study was aimed at investigating the CFH, ELOVL4, PLEKHA1 and LOC387715 genes in independent cohorts collected using different ascertainment schemes. The study used a case-control design with subjects originally recruited through the Cardiovascular Health Study (CHS) and the Age-Related Eye Disease Study (AREDS). CFH was significantly associated with ARM in both cohorts (P</=0.00001). A meta-analysis confirmed that the risk allele in the heterozygous or homozygous state (OR, 2.4 and 6.2; 95% CI, 2.2-2.7 and 5.4-7.2, respectively) confers susceptibility. LOC387715 was also significantly associated with ARM in both cohorts (P</=0.00001) and a meta-analysis confirmed that the risk allele in the heterozygous and homozygous state (OR, 2.5 and 7.3; 95% CI, 2.2-2.9 and 5.7-9.4, respectively) confers susceptibility. Both CFH and LOC387715 showed an allele-dose effect on the ARM risk, individuals homozygous at either locus were at more than two-fold risk compared to those heterozygous. PLEKHA1, which is closely linked to LOC387715, was significantly associated with ARM status in the AREDS cohort, but not the CHS cohort and ELOVL4 was not significantly associated with ARM in either cohort. Joint action of CFH and LOC387715 was best described by independent multiplicative effect without significant interaction in both cohorts. Interaction of both genes with cigarette smoking was insignificant in both cohorts. This study provides additional support for the CFH and LOC387715 genes in ARM susceptibility via the evaluation of cohorts that had different ascertainment schemes regarding ARM status and through the meta-analyses.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cohort Studies; Complement Factor H; Eye Proteins; Female; Genetic Predisposition to Disease; Humans; Intracellular Signaling Peptides and Proteins; Macular Degeneration; Male; Membrane Proteins; Proteins

Costs for heart failure with normal vs reduced ejection fraction. - Liao, Lawrence; Jollis, James G; Anstrom, Kevin J; Whellan, David J; Kitzman, Dalane W; Aurigemma, Gerard P; Mark, Daniel B; Schulman, Kevin A; Gottdiener, John S (Arch Intern Med, 2006)
BACKGROUND: Among the elderly population, heart failure (HF) with normal ejection fraction (EF) is more common than classic HF with low EF. However, there are few data regarding the costs of HF with normal EF. In a prospective, population-based cohort of elderly participants, we compared the costs and resource use of patients with HF and normal and reduced EF. METHODS: A total of 4549 participants (84.5% white; 40.6% male) in the National Heart, Lung, and Blood Institute Cardiovascular Health Study were linked to Medicare claims from 1992 through 1998. By protocol echo examinations or clinical EF assessments, 881 participants with HF were characterized as having abnormal or normal EF. We applied semiparametric estimators to calculate mean costs per subject for a 5-year period. RESULTS: There were 495 HF participants with normal EF (186 prevalent at study entry and 309 incident during the study period) and 386 participants with abnormal EF (166 prevalent and 220 incident). Participants with abnormal EF had more cardiology encounters and cardiac procedures. However, compared with abnormal EF participants, the 5-year costs for normal EF participants were similar in both the prevalent ($33,023 with abnormal EF and $32,580 with normal EF; P=.93) and incident ($49,128 with abnormal EF and $45,604 with normal EF; P=.55) groups. In models accounting for comorbid conditions, the costs with normal and abnormal EF remained similar. CONCLUSIONS: Over a 5-year period, patients with HF and normal EF consume as many health care resources as those with reduced EF. These data highlight the substantial financial burden of HF with normal EF among the elderly population.
Keywords: Aged; Aged, 80 and over; Comorbidity; Echocardiography; Health Care Costs; Heart Failure; Humans; Incidence; Medicare; Prevalence; Prospective Studies; Regression Analysis; Statistics, Nonparametric; Stroke Volume; Systole; United States; Ventricular Function, Left

Education and the cognitive decline associated with MRI-defined brain infarct. - Elkins, J S; Longstreth, W T; Manolio, T A; Newman, A B; Bhadelia, R A; Johnston, S C (Neurology, 2006)
OBJECTIVE: To assess whether educational attainment, a correlate of cognitive reserve, predicts the amount of cognitive decline associated with a new brain infarct. METHODS: The Cardiovascular Health Study is a population-based, longitudinal study of people aged 65 years and older. Cognitive function was measured annually using the Modified Mini-Mental State Examination (3MS) and the Digit-Symbol Substitution Test (DSST). The authors tested whether education level modified 1) the cross-sectional association between cognitive performance and MRI-defined infarct and 2) the change in cognitive function associated with an incident infarct at a follow-up MRI. RESULTS: In cross-sectional analysis (n = 3,660), MRI-defined infarct was associated with a greater impact on 3MS performance in the lowest education quartile when compared with others (p for heterogeneity = 0.012). Among those with a follow-up MRI who had no infarct on initial MRI (n = 1,433), education level was not associated with the incidence, size, or location of new brain infarct. However, a new MRI-defined infarct predicted substantially greater decline in 3MS scores in the lowest education group compared with the others (6.3, 95% CI 4.4- to 8.2-point decline vs 1.7, 95% CI 0.7- to 2.7-point decline; p for heterogeneity < 0.001). Higher education was not associated with smaller declines in DSST performance in the setting of MRI-defined infarct. CONCLUSIONS: Education seems to modify an individual's decline on a test of general cognitive function when there is incident brain infarct. These findings are consistent with the hypothesis that cognitive reserve influences the impact of vascular injury in the brain.
Keywords: Cerebral Infarction; Cognition Disorders; Cross-Sectional Studies; Educational Status; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Neuropsychological Tests

Education, cognitive test scores, and black-white differences in dementia risk. - Shadlen, Marie-Florence; Siscovick, David; Fitzpatrick, Annette L; Dulberg, Corinne; Kuller, Lewis H; Jackson, Sharon (J Am Geriatr Soc, 2006)
OBJECTIVES: To compare dementia risks of elderly black and white subjects and to determine whether differences in education and cognitive test scores contribute to the inconsistency in reported differences between these groups. DESIGN: Longitudinal, 6-year follow-up. PARTICIPANTS: Two thousand seven hundred eighty-six older black and white subjects in the Cardiovascular Health Study. MEASUREMENTS: Age, education (>10 years vs < or =10 years), Modified Mini-Mental State Examination score (3MS, < or =85 vs >85). Potential confounders were sex, depression, apolipoprotein E4 genotype, vascular disease, and baseline magnetic resonance imaging changes. RESULTS: White subjects with low education and black subjects with high education had twice the risk of dementia of white subjects with high education (95% confidence interval (CI)=1.5-2.4 and 95% CI=1.4-2.7); black subjects with low education had five times the risk of dementia (95% CI=3.4-7.7). Likewise, for subjects with low 3MSE scores, black subjects had 6.7 times the risk of dementia (95% CI=4.7-9.7) and white subjects had 2.7 times the risk of dementia (95% CI=2.2-3.5) as white subjects with high 3MSE scores. Finally, in Cox models, there was no significant black-white difference in dementia risk after adjustment for all confounders and baseline 3MSE. CONCLUSION: Black race was associated with greater dementia risk even after adjustment for education and other potential confounders. This black-white difference in dementia risk was markedly attenuated after adjustment for baseline cognitive screening scores. The apparent race effect may reflect gaps in the quality of education or differences in the trajectory of impaired cognitive function experienced by the two groups. Future investigations might take these findings into consideration for the design of studies evaluating black-white differences in dementia risk.
Keywords: African Continental Ancestry Group; Aged; Cognition; Dementia; Educational Status; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Psychological Tests; Retrospective Studies; Risk Factors; United States

Metabolic syndrome and cardiovascular disease in older people: The cardiovascular health study. - McNeill, Ann Marie; Katz, Ronit; Girman, Cynthia J; Rosamond, Wayne D; Wagenknecht, Lynne E; Barzilay, Joshua I; Tracy, Russell P; Savage, Peter J; Jackson, Sharon A (J Am Geriatr Soc, 2006)
OBJECTIVES: To assess the prospective association between metabolic syndrome (MetS) and cardiovascular disease (CVD) in older people and to evaluate the effect of lowering the threshold for impaired fasting glucose (IFG) on the prevalence of IFG and MetS and the risk of CVD. DESIGN: Prospective cohort study. SETTING: Four field centers in U.S. communities. PARTICIPANTS: Three thousand five hundred eighty-five subjects in the Cardiovascular Health Study free of diabetes mellitus and CVD at baseline (mean age 72, 62% female, 14% black). MEASUREMENTS: Baseline measures of MetS components and adjudicated incident CVD events. MetS (2001) was defined first using the original criteria from the Third Adult Treatment Panel Report of the National Cholesterol Education Program (> or =3 of the following: large waist circumference (women >88 cm, men >102 cm), elevated triglycerides (> or =1.70 mmol/L), low high-density lipoprotein cholesterol (men <1.04 mmol/L, women <1.30 mmol/L), elevated fasting glucose (6.1-6.9 mmol/L), and high blood pressure (> or =130/85 mmHg or self-reported use of medications for hypertension). Subjects were also classified according to the revised definition of the MetS (2005) that applies the lower threshold for fasting glucose (5.6-6.9 mmol/L). RESULTS: During follow-up (median 11 years), 818 coronary heart disease (CHD), 401 stroke, and 554 congestive heart failure (CHF) events occurred. Age- and race-adjusted hazard ratios (HRs) for CHD, stroke, and CHF were 1.30 (95% confidence interval (CI) = 1.07-1.57), 0.94 (95% CI = 0.73-1.21), and 1.40 (95% CI = 1.12-1.76) for women and 1.35 (95% CI = 1.10-1.66), 1.51 (95% CI = 1.08-2.12), and 1.47 (95% CI = 1.14-1.90) for men, respectively. Overall, women and men with MetS (2005) were 20% to 30% more likely to experience any CVD event than subjects without MetS (2005). Using the lower cut-point for IFG resulted in a near tripling in IFG prevalence (16% to 46%) and an additional 9% classified with MetS (2005) but HRs similar to those estimated from the original MetS (2001) criteria. High blood pressure was the component most strongly associated with incident CHD. CONCLUSION: Results from this study of an elderly, population-based cohort provide support for earlier investigations in primarily middle-aged populations that link the presence of MetS with the development of CVD and further underscore the importance of recognizing and treating its individual components, particularly high blood pressure.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Blood Glucose; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Fasting; Female; Humans; Incidence; Male; Metabolic Syndrome; Risk Factors; Sex Factors

Neuropsychological characteristics of mild cognitive impairment subgroups. - Lopez, O L; Becker, J T; Jagust, W J; Fitzpatrick, A; Carlson, M C; DeKosky, S T; Breitner, J; Lyketsos, C G; Jones, B; Kawas, C; Kuller, L H (J Neurol Neurosurg Psychiatry, 2006)
OBJECTIVE: To describe the neuropsychological characteristics of mild cognitive impairment (MCI) subgroups identified in the Cardiovascular Health Study (CHS) cognition study. METHODS: MCI was classified as MCI-amnestic type (MCI-AT): patients with documented memory deficits but otherwise normal cognitive function; and MCI-multiple cognitive deficits type (MCI-MCDT): impairment of at least one cognitive domain (not including memory), or one abnormal test in at least two other domains, but who had not crossed the dementia threshold. The MCI subjects did not have systemic, neurological, or psychiatric disorders likely to affect cognition. RESULTS: MCI-AT (n = 10) had worse verbal and non-verbal memory performance than MCI-MCDT (n = 28) or normal controls (n = 374). By contrast, MCI-MCDT had worse language, psychomotor speed, fine motor control, and visuoconstructional function than MCI-AT or normal controls. MCI-MCDT subjects had memory deficits, though they were less pronounced than in MCI-AT. Of the MCI-MCDT cases, 22 (78.5%) had memory deficits, and 6 (21.5%) did not. MCI-MCDT with memory disorders had more language deficits than MCI-MCDT without memory disorders. By contrast, MCI-MCDT without memory deficits had more fine motor control deficits than MCI-MCDT with memory deficits. CONCLUSIONS: The most frequent form of MCI was the MCI-MCDT with memory deficits. However, the identification of memory impaired MCI groups did not reflect the true prevalence of MCI in a population, as 16% of all MCI cases and 21.5% of the MCI-MCDT cases did not have memory impairment. Study of idiopathic amnestic and non-amnestic forms of MCI is essential for an understanding of the aetiology of MCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amnesia; Cognition Disorders; Female; Humans; Male; Neuropsychological Tests; Psychometrics; Reference Values

The sensitivity and specificity of markers for event times. - Cai, Tianxi; Pepe, Margaret Sullivan; Zheng, Yingye; Lumley, Thomas; Jenny, Nancy Swords (Biostatistics, 2006)
The statistical literature on assessing the accuracy of risk factors or disease markers as diagnostic tests deals almost exclusively with settings where the test, Y, is measured concurrently with disease status D. In practice, however, disease status may vary over time and there is often a time lag between when the marker is measured and the occurrence of disease. One example concerns the Framingham risk score (FR-score) as a marker for the future risk of cardiovascular events, events that occur after the score is ascertained. To evaluate such a marker, one needs to take the time lag into account since the predictive accuracy may be higher when the marker is measured closer to the time of disease occurrence. We therefore consider inference for sensitivity and specificity functions that are defined as functions of time. Semiparametric regression models are proposed. Data from a cohort study are used to estimate model parameters. One issue that arises in practice is that event times may be censored. In this research, we extend in several respects the work by Leisenring et al. (1997) that dealt only with parametric models for binary tests and uncensored data. We propose semiparametric models that accommodate continuous tests and censoring. Asymptotic distribution theory for parameter estimates is developed and procedures for making statistical inference are evaluated with simulation studies. We illustrate our methods with data from the Cardiovascular Health Study, relating the FR-score measured at enrollment to subsequent risk of cardiovascular events.
Keywords: Aged; Aged, 80 and over; Biomarkers; Biometry; Cardiovascular Diseases; Female; Humans; Male; Models, Statistical; Risk Factors; ROC Curve; Sensitivity and Specificity; Time Factors

Soluble intracellular adhesion molecule-1 is associated with cardiovascular disease risk and mortality in older adults. - Jenny, N S; Arnold, A M; Kuller, L H; Sharrett, A R; Fried, L P; Psaty, B M; Tracy, R P (J Thromb Haemost, 2006)
BACKGROUND: Intracellular adhesion molecule-1 (ICAM-1) regulates leukocyte-endothelial attachment, a process crucial to atherosclerosis. Circulating soluble ICAM-1 (sICAM-1) may serve as a marker of cardiovascular disease (CVD) progression. OBJECTIVES: We examined the association of sICAM-1 with measures of subclinical CVD and risk of incident CVD events and death in older men and women (age > or = 65 years) from the Cardiovascular Health Study. METHODS: Selected participants were free of clinical CVD at baseline. Non-exclusive incident case groups were angina (n = 534), myocardial infarction (n = 304), stroke (n = 327), and death (n = 842; CVD death = 310). A total 643 subjects were free of events during follow-up. RESULTS: sICAM-1 was positively associated with C-reactive protein, interleukin-6 and fibrinogen and measures of subclinical CVD in these older men and women. In Cox regression models adjusted for age, gender, and race, increasing levels of sICAM-1 were associated with increased risk of all cause mortality in men and women. Hazard ratios (95% confidence intervals) for a one standard deviation increase in sICAM-1 (89.7 ng mL(-1)) were 1.3 (1.1-1.4) in men and 1.2 (1.1-1.3) in women. sICAM-1 was associated with increased risk of CVD death in women (1.2; 1.0-1.5), but not men (1.1; 0.9-1.3). There were no associations of sICAM-1 with non-fatal CVD events. CONCLUSIONS: While sICAM-1 was associated with death in older men and women, there was a more marked association between sICAM-1 and CVD death in women.
Keywords: Aged; Aged, 80 and over; Angina Pectoris; Biomarkers; Cardiovascular Diseases; Female; Humans; Incidence; Intercellular Adhesion Molecule-1; Male; Mortality; Myocardial Infarction; Regression Analysis; Risk Factors; Sex Factors; Solubility; Stroke

Subclinical atherosclerosis and the risk of future venous thrombosis in the Cardiovascular Health Study. - van der Hagen, P B; Folsom, A R; Jenny, N S; Heckbert, S R; O'Meara, E S; Reich, L M; Rosendaal, F R; Cushman, M (J Thromb Haemost, 2006)
BACKGROUND: Recent reports have suggested an association of atherosclerosis with risk of venous thrombosis. OBJECTIVE: To confirm whether subclinical atherosclerosis is a risk factor for venous thrombosis (VT) among men and women age 65 and older. METHODS: Participants of the Cardiovascular Health Study (n = 4,108) without baseline clinical cardiovascular disease, anticoagulant use or previous VT were followed for a median of 11.7 years after non-invasive assessment of subclinical atherosclerosis using carotid ultrasound (intima-media thickness and presence of plaques), ankle-brachial blood pressure index and electrocardiogram. Each event was classified as idiopathic or secondary. We used Cox proportional hazards regression to estimate the relative risk of overall and idiopathic VT for individuals with and without baseline subclinical atherosclerosis. RESULTS: There were 133 first time VT events. No subclinical atherosclerosis measures were associated with increased risk of overall or idiopathic VT. The adjusted relative risks of overall and idiopathic VT for presence of any type of subclinical disease were 0.60 (95% confidence interval 0.39-0.91) and 0.32 (0.18-0.59), respectively. Most of this association was explained by an inverse association of high-risk carotid plaques (prevalent in 54% of those at risk) with VT. CONCLUSION: Non-invasively measured subclinical atherosclerosis was not associated with increased risk of overall or idiopathic VT in this observational study. Carotid plaques and arterial events during follow up were inversely associated, a finding that requires further study.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Carotid Artery Thrombosis; Cohort Studies; Female; Humans; Male; Proportional Hazards Models; Risk Factors; Ultrasonography; Venous Thrombosis

Transthyretin V122I in African Americans with congestive heart failure. - Buxbaum, Joel; Jacobson, Daniel R; Tagoe, Clement; Alexander, Alice; Kitzman, Dalane W; Greenberg, Barry; Thaneemit-Chen, Surai; Lavori, Philip (J Am Coll Cardiol, 2006)
Keywords: African Americans; Gene Frequency; Heart Failure; Heterozygote; Humans; Isoleucine; Mutation; Prealbumin; Valine

Usefulness of aortic root dimension in persons > or = 65 years of age in predicting heart failure, stroke, cardiovascular mortality, all-cause mortality and acute myocardial infarction (from the Cardiovascular Health Study). - Gardin, Julius M; Arnold, Alice M; Polak, Joseph; Jackson, Sharon; Smith, Vivienne; Gottdiener, John (Am J Cardiol, 2006)
Echocardiographic measures of left ventricular (LV) function and structure as well as left atrial size have been reported to predict adverse cardiovascular disease (CVD) outcomes. Although anatomic changes of the aortic root are likely to reflect effects of hypertension and atherosclerosis, few data are available on the predictive value of aortic root dimension (ARD) for outcome in free-living populations. The purpose of this investigation was to determine whether in a cohort of patients aged > or = 65 years ARD was associated with traditional coronary heart disease (CHD) risk factors and with 10-year incident CVD outcomes. In the National Heart, Lung, and Blood Institute-sponsored Cardiovascular Health Study, 3,933 free-living black and white men and women > or = 65 years of age without prevalent CVD had 2-dimensional directed M-mode echocardiographic measurements of ARD as part of a comprehensive evaluation. ARD was associated with age and gender (greater in men) but not race. ARD was also positively associated with diastolic blood pressure, LV hypertrophy, major electrocardiographic abnormalities, and other echocardiographic measures, including LV mass, ventricular septal and posterior wall thickness, and LV dimension. After adjustment for other known risk factors, high ARD was associated with an increased risk for incident congestive heart failure (CHF) in men (hazard ratio for upper compared with all other quintiles 1.47, p = 0.014), stroke in men and women (hazard ratio 1.39 per cm, p = 0.015), CVD mortality in men and women (hazard ratio 1.48 per cm, p = 0.007), and total mortality in men and women taking antihypertensive medications (hazard ratio 1.46 per cm, p = 0.007), but not with incident myocardial infarction (MI) (hazard ratio 0.89, p = 0.39). In conclusion, in a cohort of patients aged > or = 65 years without clinical CVD at baseline, ARD was associated with several CHD risk factors and measures of subclinical disease and was predictive of incident CHF, stroke, CVD mortality, and all-cause mortality, but not of incident MI.
Keywords: Age Factors; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography, Doppler; Female; Heart Failure; Humans; Hypertrophy, Left Ventricular; Male; Multicenter Studies as Topic; Myocardial Infarction; Predictive Value of Tests; Risk Factors; Sex Factors; Stroke

Alcohol consumption, interleukin-6 and apolipoprotein E genotypes, and concentrations of interleukin-6 and serum amyloid P in older adults. - Mukamal, Kenneth J; Jenny, Nancy S; Tracy, Russell P; Siscovick, David S (Am J Clin Nutr, 2007)
BACKGROUND: Whether alcohol intake is associated with concentrations of interleukin-6 (IL-6) and serum amyloid P (SAP) is uncertain. OBJECTIVE: We determined how alcohol intake and apolipoprotein E (apo E) and IL-6 promoter (IL-6 -174G-->C) polymorphisms interact for concentrations of IL-6 and SAP. DESIGN: In the Cardiovascular Health Study, 2454 older adults reported their intake of beer, wine, and liquor and underwent measurements of circulating IL-6 and SAP. RESULTS: Alcohol intake was not associated with IL-6 concentrations among apo E4-negative or IL-6C-positive participants but was positively associated among both apo E4-positive and IL-6C-negative participants (P for trend = 0.02 for both). The corresponding interactions on SAP were not significant for alcohol overall but were similar for liquor intake. CONCLUSIONS: Among older adults free of clinical cardiovascular disease, specific IL-6 promoter and apo E alleles appeared to confer positive associations of alcohol consumption with IL-6 concentrations. Genetic heterogeneity should be considered in understanding the cardiovascular effects of alcohol intake.
Keywords: Aged; Alcohol Drinking; Apolipoprotein E4; Apolipoproteins E; Blood Glucose; C-Reactive Protein; Cohort Studies; Female; Genotype; Humans; Interleukin-6; Male; Promoter Regions, Genetic; Serum Amyloid P-Component

Collaborative meta-analysis of individual participant data from observational studies of Lp-PLA2 and cardiovascular diseases. - Ballantyne, C; Cushman, M; Psaty, B; Furberg, C; Khaw, K T; Sandhu, M; Oldgren, J; Rossi, G P; Maiolino, G; Cesari, M; Lenzini, L; James, S K; et al. (Eur J Cardiovasc Prev Rehabil, 2007)
BACKGROUND: A large number of observational epidemiological studies have reported generally positive associations between circulating mass and activity levels of lipoprotein-associated phospholipase A2 (Lp-PLA2) and the risk of cardiovascular diseases. Few studies have been large enough to provide reliable estimates in different circumstances, such as in different subgroups (e.g., by age group, sex, or smoking status) or at different Lp-PLA2 levels. Moreover, most published studies have related disease risk only to baseline values of Lp-PLA2 markers (which can lead to substantial underestimation of any risk relationships because of within-person variability over time) and have used different approaches to adjustment for possible confounding factors. OBJECTIVES: By combination of data from individual participants from all relevant observational studies in a systematic 'meta-analysis', with correction for regression dilution (using available data on serial measurements of Lp-PLA2), the Lp-PLA2 Studies Collaboration will aim to characterize more precisely than has previously been possible the strength and shape of the age and sex-specific associations of plasma Lp-PLA2 with coronary heart disease (and, where data are sufficient, with other vascular diseases, such as ischaemic stroke). It will also help to determine to what extent such associations are independent of possible confounding factors and to explore potential sources of heterogeneity among studies, such as those related to assay methods and study design. It is anticipated that the present collaboration will serve as a framework to investigate related questions on Lp-PLA2 and cardiovascular outcomes. METHODS: A central database is being established containing data on circulating Lp-PLA2 values, sex and other potential confounding factors, age at baseline Lp-PLA2 measurement, age at event or at last follow-up, major vascular morbidity and cause-specific mortality. Information about any repeat measurements of Lp-PLA2 and potential confounding factors has been sought to allow adjustment for possible confounding and correction for regression dilution. The analyses will involve age-specific regression models. Synthesis of the available observational studies of Lp-PLA2 will yield information on a total of about 15 000 cardiovascular disease endpoints.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Cardiovascular Diseases; Humans; Phospholipases A2

The Emerging Risk Factors Collaboration: analysis of individual data on lipid, inflammatory and other markers in over 1.1 million participants in 104 prospective studies of cardiovascular diseases. - Danesh, J; Erqou, S; Walker, M; Thompson, S G; Tipping, R; Ford, C; Pressel, S; Walldius, G; Jungner, I; Folsom, A R; Chambless, L E; Knuiman, M; et al. (Eur J Epidemiol, 2007)
Many long-term prospective studies have reported on associations of cardiovascular diseases with circulating lipid markers and/or inflammatory markers. Studies have not, however, generally been designed to provide reliable estimates under different circumstances and to correct for within-person variability. The Emerging Risk Factors Collaboration has established a central database on over 1.1 million participants from 104 prospective population-based studies, in which subsets have information on lipid and inflammatory markers, other characteristics, as well as major cardiovascular morbidity and cause-specific mortality. Information on repeat measurements on relevant characteristics has been collected in approximately 340,000 participants to enable estimation of and correction for within-person variability. Re-analysis of individual data will yield up to approximately 69,000 incident fatal or nonfatal first ever major cardiovascular outcomes recorded during about 11.7 million person years at risk. The primary analyses will involve age-specific regression models in people without known baseline cardiovascular disease in relation to fatal or nonfatal first ever coronary heart disease outcomes. This initiative will characterize more precisely and in greater detail than has previously been possible the shape and strength of the age- and sex-specific associations of several lipid and inflammatory markers with incident coronary heart disease outcomes (and, secondarily, with other incident cardiovascular outcomes) under a wide range of circumstances. It will, therefore, help to determine to what extent such associations are independent from possible confounding factors and to what extent such markers (separately and in combination) provide incremental predictive value.
Keywords: Albumins; Biomarkers; Cardiovascular Diseases; Databases, Factual; Far East; Humans; Inflammation; Leukocyte Count; Lipids; Lipoproteins, HDL; Prospective Studies; Risk Factors; Triglycerides

IL-6 gene variation is associated with IL-6 and C-reactive protein levels but not cardiovascular outcomes in the Cardiovascular Health Study. - Walston, Jeremy D; Fallin, M Daniele; Cushman, Mary; Lange, Leslie; Psaty, Bruce; Jenny, Nancy; Browner, Warren; Tracy, Russell; Durda, Peter; Reiner, Alex (Hum Genet, 2007)
Interleukin-6 (IL-6) and C-reactive protein (CRP) levels increase with age and likely play a role in adverse health outcomes in older adults. The relationship between IL-6 gene tag single nucleotide polymorphisms (SNPs) and circulating IL-6 and CRP levels, cardiovascular disease (CVD) outcomes, and mortality in Caucasian (CA) and African American (AA) participants of the Cardiovascular Health Study (CHS) was evaluated using ANCOVA and Cox proportional hazards models. The minor allele of the promoter SNP 1510 and intronic SNP 3572 associates with significantly higher serum IL-6 and CRP levels in CA but not AA. The CRP association persisted after CA and AA populations were combined and after accounting for multiple comparisons. These associations did not carry through to cardiovascular disease outcomes. Decreased risk of stroke was identified in CA, with the minor allele of SNP 1111 (HRR 0.71, 95% CI 0.52, 0.95), P = 0.02, and increased risk of CVD and all-cause mortality (HRR 1.31, 95% CI 1.05-1.64) in AAs heterozygote for SNP 2989. While genetic variation in the IL-6 gene was associated with circulating IL-6 and especially with CRP concentrations in this study, there is little evidence for association between common IL-6 gene variation and adverse health outcomes in this population of older adults.
Keywords: African Americans; Aged; Alleles; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; Interleukin-6; Introns; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Promoter Regions, Genetic

Individual and neighborhood socioeconomic status and progressive chronic kidney disease in an elderly population: The Cardiovascular Health Study. - Merkin, Sharon Stein; Diez Roux, Ana V; Coresh, Josef; Fried, Linda F; Jackson, Sharon A; Powe, Neil R (Soc Sci Med, 2007)
Few studies have focused on the association between socioeconomic status (SES) and progressive chronic kidney disease (pCKD) in an elderly population. We conducted a cohort study of 4735 Cardiovascular Health Study participants, ages 65 and older and living in 4 US communities, to examine the independent risk of pCKD associated with income, education and living in a low SES area. pCKD was defined as creatinine elevation 0.4 mg/dL (35 micromol/L) over a 4-7 year follow-up or CKD hospitalization. Area SES was characterized using measures of income, wealth, education and occupation for 1990 (corresponding to time of enrollment) US Census block groups of residence. Age and study site-adjusted incidence rates (per 1000 person years) of pCKD by quartiles of area-level SES score, income and education showed decreasing rates with increasing SES. Cox proportional hazards models showed that living in the lowest SES area quartile, as opposed to the highest, was associated with 50% greater risk of pCKD, after adjusting for age, gender, study site, baseline creatinine, and individual-level SES. This increased risk and trend persisted after adjusting for lifestyle risk factors, diabetes and hypertension. We found no significant independent associations between pCKD and individual-level income or education (after adjusting for all other SES factors). As such, living in a low SES area is associated with greater risk of pCKD in an elderly US population.
Keywords: Age Factors; Aged; Cohort Studies; Female; Humans; Incidence; Kidney Failure, Chronic; Male; Proportional Hazards Models; Residence Characteristics; Risk Factors; Sex Factors; Social Class; United States

Inflammation and hemostasis biomarkers and cardiovascular risk in the elderly: the Cardiovascular Health Study. - Zakai, N A; Katz, R; Jenny, N S; Psaty, B M; Reiner, A P; Schwartz, S M; Cushman, M (J Thromb Haemost, 2007)
BACKGROUND: There are few studies of inflammation and hemostasis biomarkers and cardiovascular disease risk (CVD) in older adults. OBJECTIVES: To assess multiple biomarkers simultaneously and in combinations for CVD risk assessment in older individuals. PATIENTS/METHODS: Thirteen biomarkers, interleukin-6 (IL-6), C-reactive protein (CRP), D-dimer, fibrinogen, factor VII, factor VIII, leukocyte count (WBC), platelet count, lipoprotein(a), soluble intercellular adhesion molecule-1 (sICAM-1), albumin, homocysteine and uric acid, were correlated with incident CVD in 4510 individuals in the Cardiovascular Health Study. Baseline biomarkers were analyzed as gender-specific SD increments and quintiles in proportional hazards models adjusted for demographics, CVD risk factors and medications. RESULTS: Over 9 years with 1700 CVD events, seven biomarkers were associated with CVD. Adjusted hazard ratios (HRs, 95% CI) per SD increment were 1.16 (1.09, 1.23) for IL-6, 1.16 (1.09, 1.23) for CRP, 1.13 (1.05, 1.21) for D-dimer, 1.17 (1.09, 1.25) for homocysteine, 1.06 (1.00, 1.12) for WBC, 1.06 (1.00, 1.12) for factor VIII, and 1.07 (1.00, 1.13) for lipoprotein(a). Fibrinogen was associated with CVD in men only (HR 1.12, 95% CI 1.04, 1.22) and sICAM-1 in women only (HR 1.16, 95% CI 1.05, 1.27). IL-6 and CRP remained associated with CVD when modeled with WBC. Participants were classified by all combinations of two biomarkers being high or low (IL-6, CRP, WBC, factor VIII, cholesterol/HDL). All were associated with CVD when cholesterol/HDL was low and none when CRP was low. CONCLUSIONS: Seven biomarkers were associated with CVD in older adults, with CRP having some advantages compared with others. Even larger studies are needed to better characterize these associations.
Keywords: Aged; Aging; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cholesterol; Cohort Studies; Factor VIII; Female; Fibrinogen; Hemostasis; Homocysteine; Humans; Inflammation Mediators; Interleukin-6; Leukocyte Count; Lipoprotein(a); Male; Prospective Studies; Risk Factors

Inflammation biomarkers and near-term death in older men. - Jenny, Nancy Swords; Yanez, N David; Psaty, Bruce M; Kuller, Lewis H; Hirsch, Calvin H; Tracy, Russell P (Am J Epidemiol, 2007)
Associations of C-reactive protein (CRP) and fibrinogen with death may weaken over time. Combining both markers may improve prediction of death in older adults. In 5,828 Cardiovascular Health Study participants (United States, 1989-2000), 383 deaths (183 cardiovascular disease (CVD)) in years 1-3 (early) and 914 deaths (396 CVD) in years 4-8 (late) occurred. For men, when comparing highest to lowest quartiles, hazard ratios for early death were 4.1 (95% confidence interval (CI): 2.7, 6.3) for CRP and 4.1 (95% CI: 2.7, 6.4) for fibrinogen in models adjusted for CVD risk. For early CVD death, hazard ratios were 4.3 (95% CI: 2.2, 8.4) and 3.4 (95% CI: 1.8, 6.3), respectively. When comparing men in the highest quartiles of both biomarkers with those in the lowest, hazard ratios were 9.6 (95% CI: 4.3, 21.1) for early death and 13.5 (95% CI: 3.2, 56.5) for early CVD death. Associations were weaker for late deaths. For women, CRP (hazard ratio = 2.3, 95% CI: 1.4, 3.9), but not fibrinogen (hazard ratio = 1.3, 95% CI: 0.8, 2.2), was associated with early death. Results were similar for CVD death. Neither was associated with late deaths. CRP and fibrinogen were more strongly associated with death in older men than women and more strongly associated with early than late death. Combining both markers may identify older men at greatest risk of near-term death.
Keywords: Age Distribution; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Diabetes Complications; Epidemiologic Studies; Female; Fibrinogen; Follow-Up Studies; Humans; Hypercholesterolemia; Hypertension; Inflammation; Male; Middle Aged; Obesity; Population Surveillance; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Factors; Sex Distribution; Smoking; Time Factors; United States

Leukocyte telomere length and cardiovascular disease in the cardiovascular health study. - Fitzpatrick, Annette L; Kronmal, Richard A; Gardner, Jeffrey P; Psaty, Bruce M; Jenny, Nancy S; Tracy, Russell P; Walston, Jeremy; Kimura, Masyuki; Aviv, Abraham (Am J Epidemiol, 2007)
The telomere length of replicating somatic cells is inversely correlated with age and has been reported to be associated cross-sectionally with cardiovascular disease (CVD). Leukocyte telomere length, as expressed by mean terminal restriction fragment (TRF) length, was measured in 419 randomly selected participants from the Cardiovascular Health Study, comprising a community-dwelling cohort recruited in four US communities. The authors investigated associations between TRF length and selected measures of subclinical CVD/risk factors for CVD (data were collected at the 1992/1993 clinic visit) and incident CVD (ascertained through June 2002). In these participants (average age = 74.2 years (standard deviation, 5.2)), mean TRF length was 6.3 kilobase pairs (standard deviation, 0.62). Significant or borderline inverse associations were found between TRF length and diabetes, glucose, insulin, diastolic blood pressure, carotid intima-media thickness, and interleukin-6. Associations with body size and C-reactive protein were modified by gender and age, occurring only in men and in participants aged 73 years or younger. In younger (but not older) participants, each shortened kilobase pair of TRF corresponded with a threefold increased risk of myocardial infarction (hazard ratio = 3.08, 95% confidence interval: 1.22, 7.73) and stroke (hazard ratio = 3.22, 95% confidence interval: 1.29, 8.02). These results support the hypotheses that telomere attrition may be related to diseases of aging through mechanisms involving oxidative stress, inflammation, and progression to CVD.
Keywords: Aged; Cardiovascular Diseases; DNA; Female; Humans; Inflammation; Leukocytes; Male; Myocardial Infarction; Oxidative Stress; Pilot Projects; Polymorphism, Restriction Fragment Length; Risk; Risk Assessment; Risk Factors; Telomere

Long-term costs and resource use in elderly participants with congestive heart failure in the Cardiovascular Health Study. - Liao, Lawrence; Anstrom, Kevin J; Gottdiener, John S; Pappas, Paul A; Whellan, David J; Kitzman, Dalane W; Aurigemma, Gerard P; Mark, Daniel B; Schulman, Kevin A; Jollis, James G (Am Heart J, 2007)
BACKGROUND: Although heart failure (HF) afflicts nearly 5 million Americans, the long-term cost of HF care has not been described previously. In a prospective, longitudinal cohort of community-dwelling elderly from 4 regions, we examined the long-term costs and resource use of elderly patients with HF. METHODS: We linked 4860 elderly participants in the National Heart, Lung, and Blood Institute Cardiovascular Health Study to Medicare part A and part B claims from 1992 to 2003. Costs were calculated from Medicare payments and discounted at 3% annually. We applied nonparametric estimators to calculate mean costs and resource use per patient for a 10-year period. To describe the relationship between patient characteristics and long-term costs, we constructed censoring-adjusted regression models. RESULTS: There were 343 participants (84.8% white; 50.1% men; mean age, 78.2 years) with prevalent HF and 4517 participants without HF at study entry. Mean follow-up was 6.7 years (median, 6.4 years). The 10-year survival rates were 33% and 63% for the prevalent HF and nonprevalent HF groups (P < .001), respectively. The mean 10-year medical costs were significantly higher for the prevalent HF cohort (54,704 dollars vs 41 dollars,780, P < .001). The higher costs associated with HF were also reflected in greater resource use with more hospitalizations (P < .05) and more intensive care unit days (P < .05). Participants with HF had more physician visits (P < .05), with most of these encounters involving noncardiology physicians. However, in multivariate models, prevalent HF was not an independent predictor of higher costs. CONCLUSION: Patients with HF consume substantially more health care resources than their elderly peers, and these higher costs persist through 10 years of follow-up. Many of these costs may be related to other comorbid conditions.
Keywords: Aged; Costs and Cost Analysis; Female; Health Resources; Heart Failure; Humans; Male; Medicare; Prospective Studies; Time Factors

Serum amyloid P and cardiovascular disease in older men and women: results from the Cardiovascular Health Study. - Jenny, Nancy Swords; Arnold, Alice M; Kuller, Lewis H; Tracy, Russell P; Psaty, Bruce M (Arterioscler Thromb Vasc Biol, 2007)
OBJECTIVE: Serum amyloid P (SAP), a pentraxin like C-reactive protein (CRP), functions in innate immunity. However, associations of SAP with cardiovascular disease (CVD) are unknown. METHODS AND RESULTS: We examined these associations in the Cardiovascular Health Study using a case-cohort design. Nonexclusive case groups were incident angina (n=523), myocardial infarction (MI; n=308), stroke (n=323), and CVD death (n=288). 786 participants had no events. SAP was correlated with CRP, CVD risk factors (obesity, blood pressure, lipids), common and internal carotid wall thickness, and ankle-brachial index (all P<0.02). In Cox regression models adjusted for age, sex, and ethnicity, a standard deviation increase in SAP (9.8 mg/L) was associated with angina (hazard ratio; 95% confidence interval 1.3; 1.2 to 1.5) and MI (1.3; 1.1 to 1.5), but not stroke (1.1; 0.9 to 1.3) or CVD death (1.1; 0.9 to 1.3). Adding CRP to the models had no significant effect on associations. Adjusting for CVD risk factors slightly attenuated SAP associations with CVD events; however, associations with angina and MI remained significant. CONCLUSIONS: Although both are pentraxins, SAP and CRP may represent different facets of inflammation. The association of SAP with CVD in these older adults further supports the role of innate immunity in atherosclerosis.
Keywords: Aged; Aged, 80 and over; Aging; Angina, Unstable; Atherosclerosis; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Humans; Hypertension; Immunity, Innate; Male; Myocardial Infarction; Obesity; Prevalence; Proportional Hazards Models; Risk Factors; Serum Amyloid P-Component

Socioeconomic position and incident mobility impairment in the Cardiovascular Health Study. - Nordstrom, Cheryl K; Diez Roux, Ana V; Schulz, Richard; Haan, Mary N; Jackson, Sharon A; Balfour, Jennifer L (BMC Geriatr, 2007)
BACKGROUND: We investigated if personal socioeconomic position (SEP) factors and neighborhood characteristics were associated with incident mobility impairment in the elderly. METHODS: We used data from the Cardiovascular Health Study, a longitudinal, population-based examination of coronary heart disease and stroke among persons aged 65 and older in the United States. RESULTS: Among 3,684 persons without baseline mobility impairment, lower baseline SEP was associated with increased risk of incident mobility disability during the 10-year follow-up period, although the strengths of these associations varied by socioeconomic indicator and race/sex group. CONCLUSION: Among independent-living elderly, SEP affected development of mobility impairment into later life. Particular effort should be made to prevent or delay its onset among the elderly with low income, education, and/or who live in economically disadvantaged neighborhoods.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Disabled Persons; Education; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Mobility Limitation; Residence Characteristics; Social Class; Stroke; United States

USF1 gene variants, cardiovascular risk, and mortality in European Americans: analysis of two US cohort studies. - Reiner, Alexander P; Carlson, Christopher S; Jenny, Nancy S; Durda, J Peter; Siscovick, David S; Nickerson, Deborah A; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2007)
OBJECTIVE: A common haplotype of the upstream transcription factor 1 gene (USF1) has been associated with decreased susceptibility to familial combined hyperlipidemia (FCHL) and, paradoxically, with increased risk of cardiovascular disease (CVD) and all-cause mortality. METHODS AND RESULTS: We assessed associations between USF1 tagSNPs, CVD risk factors, and aging-related phenotypes using data from 2 large population-based cohorts, Coronary Artery Risk Development in Young Adults (CARDIA) and the Cardiovascular Health Study (CHS), comprising younger and older adults, respectively. In CARDIA, each additional copy of the FCHL low-risk allele was associated with 2.4 mg/dL lower levels of LDL cholesterol (P=0.01) and decreased risk of subclinical atherosclerosis as assessed by coronary artery calcium (odds ratio 0.79; 95%CI 0.63 to 0.98). Whereas there was little association between USF1 genotype and metabolic or CVD traits in older adults from CHS, the USF1 low-risk dyslipidemia allele was associated with higher plasma C-reactive protein and interleukin (IL)-6 levels and with increased risk of mortality, particularly attributable to noncardiovascular causes. CONCLUSIONS: There appears to be a complex and possibly age-dependent relationship between USF1 genotype, atherosclerosis phenotypes, and CVD risk. USF1 may influence mortality through pathways distinct from atherosclerosis. Alternatively, linkage disequilibrium with neighboring polymorphisms in other genes such as F11R may be responsible for the observed USF1 genotype-phenotype associations in older adults.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Aging; Blood Glucose; C-Reactive Protein; Calcium; Cardiovascular Diseases; Carotid Artery, Common; Cohort Studies; Coronary Artery Disease; Coronary Vessels; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Humans; Hyperlipidemia, Familial Combined; Insulin; Interleukin-6; Linkage Disequilibrium; Lipids; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Upstream Stimulatory Factors

Albuminuria and dementia in the elderly: a community study. - Barzilay, Joshua I; Fitzpatrick, Annette L; Luchsinger, Jose; Yasar, Sevil; Bernick, Charles; Jenny, Nancy S; Kuller, Lewis H (Am J Kidney Dis, 2008)
BACKGROUND: Dementia is associated with microvascular disease of the retina. In this study, we examine whether cognitive status (normal cognition, mild cognitive impairment, and dementia) is associated with albuminuria, a microvascular disorder of the kidney. STUDY DESIGN: Cross-sectional analysis. SETTING & PARTICIPANTS: 2,316 participants from the Cardiovascular Health Cognition Study who underwent brain magnetic resonance imaging and testing for albuminuria. PREDICTOR: Doubling of albuminuria. OUTCOME: Dementia defined according to neuropsychological and clinical evaluation. MEASUREMENTS: Multinomial logistic modeling was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) of dementia and mild cognitive impairment with doubling of albuminuria compared with the odds with normal cognition. RESULTS: 283 participants (12.2%) had dementia, 344 (14.9%) had mild cognitive impairment, and 1,689 (72.9%) had normal cognition. Compared with participants with normal cognition, doubling of albuminuria was associated with increased odds of dementia (OR, 1.22; 95% CI, 1.15 to 1.29). Adjustment for prevalent cardiovascular disease and cardiovascular risk factors, lipid levels, C-reactive protein level, estimated glomerular filtration rate, and apolipoprotein E-4 genotype attenuated this association, but it remained statistically significant (OR, 1.12; 95% CI, 1.03 to 1.22). Mild cognitive impairment was associated with albuminuria on unadjusted analysis, but not with adjustment for other factors. LIMITATIONS: Results are cross-sectional; causality cannot be imputed. CONCLUSIONS: The odds of dementia increased in the presence of albuminuria. These findings suggest a role of shared susceptibility for microvascular disease in the brain and kidney in older adults.
Keywords: Age Factors; Aged; Aged, 80 and over; Albuminuria; Brain; Cognition; Cross-Sectional Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Odds Ratio; Population Surveillance; Prognosis; Retrospective Studies; Risk Factors

Ankle brachial index combined with Framingham Risk Score to predict cardiovascular events and mortality: a meta-analysis. - Fowkes, F G R; Murray, G D; Butcher, I; Heald, C L; Lee, R J; Chambless, L E; Folsom, A R; Hirsch, A T; Dramaix, M; deBacker, G; Wautrecht, J-C; Kornitzer, M; et al. (JAMA, 2008)
CONTEXT: Prediction models to identify healthy individuals at high risk of cardiovascular disease have limited accuracy. A low ankle brachial index (ABI) is an indicator of atherosclerosis and has the potential to improve prediction. OBJECTIVE: To determine if the ABI provides information on the risk of cardiovascular events and mortality independently of the Framingham risk score (FRS) and can improve risk prediction. DATA SOURCES: Relevant studies were identified. A search of MEDLINE (1950 to February 2008) and EMBASE (1980 to February 2008) was conducted using common text words for the term ankle brachial index combined with text words and Medical Subject Headings to capture prospective cohort designs. Review of reference lists and conference proceedings, and correspondence with experts was conducted to identify additional published and unpublished studies. STUDY SELECTION: Studies were included if participants were derived from a general population, ABI was measured at baseline, and individuals were followed up to detect total and cardiovascular mortality. DATA EXTRACTION: Prespecified data on individuals in each selected study were extracted into a combined data set and an individual participant data meta-analysis was conducted on individuals who had no previous history of coronary heart disease. RESULTS: Sixteen population cohort studies fulfilling the inclusion criteria were included. During 480,325 person-years of follow-up of 24,955 men and 23,339 women, the risk of death by ABI had a reverse J-shaped distribution with a normal (low risk) ABI of 1.11 to 1.40. The 10-year cardiovascular mortality in men with a low ABI (< or = 0.90) was 18.7% (95% confidence interval [CI], 13.3%-24.1%) and with normal ABI (1.11-1.40) was 4.4% (95% CI, 3.2%-5.7%) (hazard ratio [HR], 4.2; 95% CI, 3.3-5.4). Corresponding mortalities in women were 12.6% (95% CI, 6.2%-19.0%) and 4.1% (95% CI, 2.2%-6.1%) (HR, 3.5; 95% CI, 2.4-5.1). The HRs remained elevated after adjusting for FRS (2.9 [95% CI, 2.3-3.7] for men vs 3.0 [95% CI, 2.0-4.4] for women). A low ABI (< or = 0.90) was associated with approximately twice the 10-year total mortality, cardiovascular mortality, and major coronary event rate compared with the overall rate in each FRS category. Inclusion of the ABI in cardiovascular risk stratification using the FRS would result in reclassification of the risk category and modification of treatment recommendations in approximately 19% of men and 36% of women. CONCLUSION: Measurement of the ABI may improve the accuracy of cardiovascular risk prediction beyond the FRS.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Ankle; Atherosclerosis; Blood Pressure; Brachial Artery; Cardiovascular Diseases; Cohort Studies; Confidence Intervals; Female; Global Health; Humans; Male; Middle Aged; Odds Ratio; Predictive Value of Tests; Risk Assessment; Risk Factors; Severity of Illness Index

Associations between common fibrinogen gene polymorphisms and cardiovascular disease in older adults. The Cardiovascular Health Study. - Carty, Cara L; Cushman, Mary; Jones, Daniel; Lange, Leslie A; Hindorff, Lucia A; Rice, Kenneth; Jenny, Nancy S; Durda, J Peter; Walston, Jeremy; Carlson, Christopher S; Nickerson, Debbie; Tracy, Russell P; et al. (Thromb Haemost, 2008)
Elevated plasma fibrinogen is a risk factor for cardiovascular disease (CVD), but associations between fibrinogen single nucleotide polymorphisms (SNPs) and disease risk are inconsistent. We investigated whether common (> or = 5% minor allele frequency) variation in the fibrinogen genes (FGA, FGB, FGG) is associated with fibrinogen concentration, carotid artery intima-medial thickness (IMT) and risk of incident myocardial infarction (MI), ischemic stroke and CVD mortality in European- (EA) and African-descent (AA) adults (> or = 65 years) from the Cardiovascular Health Study. TagSNPs were genotyped in 3,969 EA and 719 AA free of MI or stroke at baseline. Race-specific models included multiple testing correction and adjustment for sex, age and site. Among EA, minor alleles of FGA3807, FGB1437 and FGG902 were associated with higher fibrinogen levels; whereas FGA251, FGA2224, FGA6534 and FGG10034 were associated with lower levels, p<0.004 for each. Strongest associations were seen for FGB1437; each additional copy of the minor allele was associated with 13 mg/dl (95%CI: 9-16) higher fibrinogen level. Similar trends in AA were not significant. Fibrinogen haplotypes were not significantly associated with internal or common carotid IMT. No associations with MI or CVD mortality were seen in EA, though FGB1038 and FGG902 were significantly associated with increased and decreased risk of stroke in men, respectively, as were related haplotypes. FGB1038 was also associated with CVD mortality in AA, HR = 1.9 (95%CI: 1.3-2.7). In conclusion, while fibrinogen genetic variation was strongly associated with fibrinogen levels, there was less evidence of association with the more complex outcomes of IMT and CVD events.
Keywords: African Americans; Age Factors; Aged; Brain Ischemia; Cardiovascular Diseases; Carotid Artery Diseases; European Continental Ancestry Group; Female; Fibrinogen; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Population Surveillance; Proportional Hazards Models; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke; United States

Common genetic variants associated with plasma fibrin D-dimer concentration in older European- and African-American adults. - Lange, L A; Reiner, A P; Carty, C L; Jenny, N S; Cushman, M; Lange, E M (J Thromb Haemost, 2008)
BACKGROUND AND OBJECTIVES: D-dimer is a hemostasis marker that reflects ongoing fibrin formation and degradation. There is significant inter-individual and inter-population variability in D-dimer concentration, but whether genetic factors underlie these differences is largely unknown. We hypothesized that common coagulation gene variants contribute to differences in circulating D-dimer concentration. METHODS: The setting was European-American (EA; n = 1858) and African-American (AA; n = 327) unrelated older adults from the Cardiovascular Health Study (CHS), in which we genotyped SNPs in 42 genes related to blood coagulation and fibrinolysis. RESULTS: Several fibrinogen gene polymorphisms, including the Thr312Ala Aalpha chain variant and the FGG-10034 C/T variant, were associated with approximately 20% higher plasma D-dimer levels in EA (false discovery rate < 5% for covariate-adjusted model). There was also some evidence that a Pro41Leu variant of the PLAU gene encoding urinary plasminogen activator and non-coding polymorphism of the plasminogen activator inhibitor type 1 gene (SERPINE1) were associated with higher plasma D-dimer in EA. There were no significant associations between the studied coagulation or fibrinolysis gene SNPs and plasma D-dimer levels in the smaller AA sample. However, each standard deviation increase in European ancestry assessed by ancestry-informative gene markers was associated with approximately 10% lower mean D-dimer levels in AA. CONCLUSIONS: Together, common coagulation/fibrinolysis gene SNPs explained only approximately 2% of the variance in plasma D-dimer levels in EA. These findings suggest that the association of D-dimer with risk of vascular outcomes may be mediated largely by environmental factors, other genes, and/or genetic interactions.
Keywords: Africa; African Americans; Aged; Aged, 80 and over; Blood Coagulation; Europe; European Continental Ancestry Group; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Fibrinolysis; Genotype; Humans; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; Prospective Studies; United States; Urokinase-Type Plasminogen Activator

Distribution and correlates of lipoprotein-associated phospholipase A2 in an elderly cohort: the Cardiovascular Health Study. - Furberg, Curt D; Nelson, Jeanenne J; Solomon, Cam; Cushman, Mary; Jenny, Nancy Swords; Psaty, Bruce M (J Am Geriatr Soc, 2008)
OBJECTIVES: To determine whether high levels of lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) are associated with prevalent cardiovascular disease (CVD) and to evaluate factors most influencing Lp-PLA(2) levels in a community-based cohort of older adults. DESIGN: Cross-sectional. SETTING: The Cardiovascular Health Study (CHS), a population-based cohort study of men and women aged 65 and older. PARTICIPANTS: Five thousand five hundred thirty-one CHS participants. MEASUREMENTS: Levels of Lp-PLA(2) activity were determined using stored blood samples from the baseline examination. RESULTS: Mean Lp-PLA(2) was higher in participants with electrocardiographically determined ventricular conduction defect and major Q-wave abnormality and was positively correlated with left ventricular (LV) mass. It was high in those with echocardiographically determined abnormal LV ejection fraction, which persisted after adjustment. Mean Lp-PLA(2) was also higher in participants with mild renal insufficiency and kidney disease. After multivariable adjustment, there was a modest but significant 27% greater risk of prevalent CHF per standard deviation increment of Lp-PLA(2) and a modest but significant 12% greater risk of prevalent myocardial infarction. Lp-PLA(2) was weakly but mainly most strongly correlated with cholesterol and lipoproteins, but those correlations were not especially strong. Lp-PLA(2) was weakly positively correlated with soluble intercellular adhesion molecule-1 but not interleukin-6. In total, all factors considered could explain only 29% of Lp-PLA(2) activity. CONCLUSION: Novel findings in the study are the associations, in those aged 65 and older, between Lp-PLA(2) activity and LV dysfunction, CHF, and renal disease. CVD risk factors only minimally explain levels of Lp-PLA(2).
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Atherosclerosis; Body Mass Index; Cardiac Output, Low; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Cross-Sectional Studies; Electrocardiography; Female; Heart Failure; Humans; Hypertrophy, Left Ventricular; Long QT Syndrome; Male; Reference Values; Renal Insufficiency; Risk Factors; Statistics as Topic; Triglycerides

Incident physical disability in people with lower extremity peripheral arterial disease: the role of cardiovascular disease. - Brach, Jennifer S; Solomon, Cam; Naydeck, Barbara L; Sutton-Tyrrell, Kim; Enright, Paul L; Jenny, Nancy Swords; Chaves, Paulo M; Newman, Anne B (J Am Geriatr Soc, 2008)
OBJECTIVES: To evaluate the risk of incident physical disability and the decline in gait speed over a 6-year follow-up associated with a low ankle-arm index (AAI) in older adults. DESIGN: Observational cohort study. SETTING: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania. PARTICIPANTS: Four thousand seven hundred five older adults, 58% women and 17.6% black, participating in the Cardiovascular Health Study. MEASUREMENTS: AAI was measured in 1992/93 (baseline). Self-reported mobility, activity of daily living (ADL), and instrumental activity of daily living (IADL) disability and gait speed were recorded at baseline and at 1-year intervals over 6 years of follow-up. Mobility disability was defined as any difficulty walking half a mile and ADL and IADL disability was defined as any difficulty with 11 specific ADL and IADL tasks. Individuals with mobility, ADL, or IADL disability at baseline were excluded from the respective incident disability analyses. RESULTS: Lower baseline AAI values were associated with increased risk of mobility disability and ADL/IADL disability. Clinical cardiovascular disease (CVD), diabetes mellitus, and interim CVD events partially explained these associations for mobility disability and clinical CVD and diabetes mellitus partially explained these associations for ADL and IADL disability. Individuals with an AAI less than 0.9 had on average a mean decrease in gait speed of 0.02 m/s per year, or a decline of 0.12 m/s over the 6-year follow-up. Prevalent CVD partly explained this decrease but interim CVD events did not further attenuate it. CONCLUSION: Low AAI serves as marker of future disability risk. Reduction of disability risk in patients with a low AAI should consider cardiovascular comorbidity and the prevention of additional disabling CVD events.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Cohort Studies; Comorbidity; Disability Evaluation; Female; Gait; Geriatric Assessment; Humans; Lower Extremity; Male; Mobility Limitation; Peripheral Vascular Diseases; Proportional Hazards Models; Risk Assessment; Risk Factors; United States

Inflammatory markers and longitudinal lung function decline in the elderly. - Jiang, Rui; Burke, Gregory L; Enright, Paul L; Newman, Anne B; Margolis, Helene G; Cushman, Mary; Tracy, Russell P; Wang, Yuanjia; Kronmal, Richard A; Barr, R Graham (Am J Epidemiol, 2008)
Longitudinal studies examining associations of the inflammatory markers fibrinogen and C-reactive protein (CRP) with lung function decline are sparse. The authors examined whether elevated fibrinogen and CRP levels were associated with greater longitudinal lung function decline in the elderly. The Cardiovascular Health Study measured fibrinogen and CRP in 5,790 Whites and African Americans from four US communities aged 65 years or older in 1989-1990 or 1992-1993. Spirometry was performed in 1989-1990 and 4, 7, and 16 years later. Fibrinogen and CRP were inversely associated with lung function at baseline after adjustment for multiple potential confounders. In mixed models, the rate of decline in forced expiratory volume in 1 second (FEV(1))/forced vital capacity (FVC) ratio with increasing age was faster among those with higher baseline fibrinogen (-0.032%/year per standard deviation higher fibrinogen (95% confidence interval: -0.057, -0.0074)) but not among those with higher CRP (-0.0037%/year per standard deviation higher CRP (95% confidence interval: -0.013, 0.0056)). Longitudinal analyses for FEV(1) and FVC yielded results in the direction opposite of that hypothesized, possibly because of the high mortality rate and strong inverse association of FEV(1) and FVC but not FEV(1)/FVC with mortality. An alternative approach to missing data yielded similar results. In conclusion, higher levels of fibrinogen, but not CRP, independently predicted greater FEV(1)/FVC decline in the elderly.
Keywords: Aged; C-Reactive Protein; Cross-Sectional Studies; Female; Fibrinogen; Forced Expiratory Volume; Geriatric Assessment; Humans; Logistic Models; Longitudinal Studies; Lung Volume Measurements; Male; Multicenter Studies as Topic; Pulmonary Disease, Chronic Obstructive; Spirometry

Insulin-like growth factors, their binding proteins, and prostate cancer risk: analysis of individual patient data from 12 prospective studies. - Roddam, Andrew W; Allen, Naomi E; Appleby, Paul; Key, Timothy J; Ferrucci, Luigi; Carter, H Ballentine; Metter, E Jeffrey; Chen, Chu; Weiss, Noel S; Fitzpatrick, Annette; Hsing, Ann W; Lacey, James V; et al. (Ann Intern Med, 2008)
BACKGROUND: Some, but not all, published results have shown an association between circulating blood levels of some insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) and the subsequent risk for prostate cancer. PURPOSE: To assess the association between levels of IGFs and IGFBPs and the subsequent risk for prostate cancer. DATA SOURCES: Studies identified in PubMed, Web of Science, and CancerLit. STUDY SELECTION: The principal investigators of all studies that published data on circulating concentrations of sex steroids, IGFs, or IGFBPs and prostate cancer risk using prospectively collected blood samples were invited to collaborate. DATA EXTRACTION: Investigators provided individual participant data on circulating concentrations of IGF-I, IGF-II, IGFBP-II, and IGFBP-III and participant characteristics to a central data set in Oxford, United Kingdom. DATA SYNTHESIS: The study included data on 3700 men with prostate cancer and 5200 control participants. On average, case patients were 61.5 years of age at blood collection and received a diagnosis of prostate cancer 5 years after blood collection. The greater the serum IGF-I concentration, the greater the subsequent risk for prostate cancer (odds ratio [OR] in the highest vs. lowest quintile, 1.38 [95% CI, 1.19 to 1.60]; P < 0.001 for trend). Neither IGF-II nor IGFBP-II concentrations were associated with prostate cancer risk, but statistical power was limited. Insulin-like growth factor I and IGFBP-III were correlated (r = 0.58), and although IGFBP-III concentration seemed to be associated with prostate cancer risk, this was secondary to its association with IGF-I levels. Insulin-like growth factor I concentrations seemed to be more positively associated with low-grade than high-grade disease; otherwise, the association between IGFs and IGFBPs and prostate cancer risk had no statistically significant heterogeneity related to stage or grade of disease, time between blood collection and diagnosis, age and year of diagnosis, prostate-specific antigen level at recruitment, body mass index, smoking, or alcohol intake. LIMITATIONS: Insulin-like growth factor concentrations were measured in only 1 sample for each participant, and the laboratory methods to measure IGFs differed in each study. Not all patients had disease stage or grade information, and the diagnosis of prostate cancer may differ among the studies. CONCLUSION: High circulating IGF-I concentrations are associated with a moderately increased risk for prostate cancer.
Keywords: Aged; Humans; Insulin-Like Growth Factor Binding Protein 2; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor Binding Proteins; Insulin-Like Growth Factor I; Insulin-Like Growth Factor II; Male; Middle Aged; Prospective Studies; Prostatic Neoplasms; Risk Factors; Somatomedins

Lipoprotein-associated phospholipase A2 and risk of venous thrombosis in older adults. - Olson, Nels; O'Meara, Ellen S; Jenny, Nancy S; Folsom, Aaron R; Bovill, Edwin G; Furberg, Curt D; Heckbert, Susan R; Psaty, Bruce M; Cushman, Mary (Am J Hematol, 2008)
Lipoprotein-associated phospholipase A2 (Lp-PLA2) is an enzyme involved in inflammation and platelet function. Inherited deficiency and elevated levels are associated with atherosclerosis. Given potential common etiologies of atherosclerosis and venous thrombosis (VT), we hypothesized that low and high Lp-PLA2 would be associated with VT risk. Lp-PLA(2) mass and activity were measured in baseline samples of Cardiovascular Health Study participants (5,888 men and women age > or =65), excluding 354 reporting pre-baseline VT. The study endpoint was VT unrelated to cancer after 11.6 years follow-up. Hazard ratios were estimated using Cox proportional hazard models, adjusting for age, race, sex, and body-mass index. With 129 cases of VT, there was no association of Lp-PLA2 activity with risk. Adjusted hazard ratios were 1.19 (CI 0.62, 2.29) and 0.87 (CI 0.43, 1.76) for the lowest and highest decile, respectively, compared to the 10-25th percentile. Corresponding hazard ratios for Lp-PLA2 mass were 1.63 (CI 0.79, 3.34) and 1.33 (CI 0.61, 2.87). Results were robust to several definitions of low or high Lp-PLA2. While the association of Lp-PLA(2) levels with arterial disease events implies a role for this enzyme in atherogenesis, our findings suggest that it is not prothrombotic.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Female; Humans; Male; Risk Factors; Venous Thrombosis

Metabolic syndrome, endothelial dysfunction, and risk of cardiovascular events: the Northern Manhattan Study (NOMAS). - Suzuki, Takeki; Hirata, Kumiko; Elkind, Mitchell S V; Jin, Zhezhen; Rundek, Tanja; Miyake, Yumiko; Boden-Albala, Bernadette; Di Tullio, Marco R; Sacco, Ralph; Homma, Shunichi (Am Heart J, 2008)
BACKGROUND: Metabolic syndrome (MetS) predisposes to cardiovascular disease. Endothelial dysfunction is thought to be an important factor in the pathogenesis of atherosclerosis. We tested the hypothesis that both MetS and endothelial dysfunction are vascular risk factors and provide additive prognostic values in predicting cardiovascular events in a multiethnic community sample. METHODS: The study population consisted of 819 subjects (467 female, mean age 66.5 +/- 8.8 years, 66% Hispanic) enrolled in the NOMAS. Metabolic syndrome was defined using the revised Adult Treatment Panel III criteria. Brachial artery flow-mediated dilation (FMD) was measured using high-resolution ultrasound. Endothelial dysfunction was defined as FMD <8.44% (lower 3 quartiles). Cox proportional hazards models were used to assess the effect of MetS and endothelial dysfunction on risk of cardiovascular events. RESULTS: During 81 +/- 21 months of follow-up, events occurred in 84 subjects. Metabolic syndrome was independently associated with cardiovascular events in a multivariate model, including cardiovascular risk factors (adjusted hazard ratio 2.08, 95% CI 1.27-3.40). Subjects with both MetS and endothelial dysfunction were at higher risk for cardiovascular events than those with either one of them alone (adjusted hazard ratio 2.60, 95% CI 1.14-5.92). CONCLUSIONS: Metabolic syndrome is associated with incident cardiovascular events. Combined use of MetS and FMD identifies those who are at higher risk of cardiovascular events. Metabolic syndrome and noninvasive FMD testing can be used concurrently for cardiovascular risk prediction.
Keywords: Adult; Aged; Brachial Artery; Endothelium, Vascular; Female; Humans; Kaplan-Meier Estimate; Male; Metabolic Syndrome; Middle Aged; Prognosis; Prospective Studies; Risk Factors; Stroke; Vascular Diseases

Polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha are associated with C-reactive protein. - Reiner, Alexander P; Barber, Mathew J; Guan, Yongtao; Ridker, Paul M; Lange, Leslie A; Chasman, Daniel I; Walston, Jeremy D; Cooper, Gregory M; Jenny, Nancy S; Rieder, Mark J; Durda, J Peter; Smith, Joshua D; et al. (Am J Hum Genet, 2008)
Data from the Pharmacogenomics and Risk of Cardiovascular Disease (PARC) study and the Cardiovascular Health Study (CHS) provide independent and confirmatory evidence for association between common polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha and plasma C-reactive protein (CRP) concentration. Analyses with the use of imputation-based methods to combine genotype data from both studies and to test untyped SNPs from the HapMap database identified several SNPs within a 5 kb region of HNF1A intron 1 with the strongest evidence of association with CRP phenotype.
Keywords: Aged; Bayes Theorem; C-Reactive Protein; Female; Hepatocyte Nuclear Factor 1-alpha; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Pravastatin; Simvastatin

PROC, PROCR and PROS1 polymorphisms, plasma anticoagulant phenotypes, and risk of cardiovascular disease and mortality in older adults: the Cardiovascular Health Study. - Reiner, A P; Carty, C L; Jenny, N S; Nievergelt, C; Cushman, M; Stearns-Kurosawa, D J; Kurosawa, S; Kuller, L H; Lange, L A (J Thromb Haemost, 2008)
BACKGROUND AND OBJECTIVES: Genes encoding protein C anticoagulant pathways are candidates for atherothrombotic and other aging-related disorders. METHODS: Using a tagSNP approach, and data from the Cardiovascular Health Study (CHS), we assessed associations of common polymorphisms of PROC, PROS1 and PROCR with: (i) plasma protein C, soluble protein C endothelial receptor (sEPCR) and protein S levels measured in a subsample of 336 participants at study entry; and (ii) risk of incident clinical outcomes [coronary heart disease (CHD), stroke, and mortality] in 4547 participants during follow-up. Secondarily, we explored associations between plasma protein C, protein S and sEPCR levels and other candidate genes involved in thrombosis, inflammation, and aging. RESULTS: The PROCR Ser219Gly polymorphism (rs867186) was strongly associated with higher sEPCR levels, explaining 75% of the phenotypic variation. The PROCR Ser219Gly variant was also associated with higher levels of circulating protein C antigen. An IL10 polymorphism was associated with higher free protein S levels. The minor alleles of PROC rs2069901 and PROS1 rs4857343 were weakly associated with lower protein C and free protein S levels, respectively. There was no association between PROCR Ser219Gly and risk of CHD, stroke, or mortality. The minor allele of another common PROCR tagSNP, rs2069948, was associated with lymphoid PROCR mRNA expression and with increased risk of incident stroke and all-cause mortality, and decreased healthy survival during follow-up. CONCLUSIONS: A common PROCR variant may be associated with decreased healthy survival in older adults. Additional studies are warranted to establish the role of PROCR variants in ischemic and aging-related disorders.
Keywords: Aged; Aged, 80 and over; Aging; Antigens, CD; Blood Coagulation Factor Inhibitors; Cardiovascular Diseases; Coronary Disease; Endothelial Protein C Receptor; Female; Humans; Inflammation; Male; Middle Aged; Mortality; Polymorphism, Genetic; Protein C; Protein S; Receptors, Cell Surface; Risk; Stroke; Thrombosis

Association of common genetic variation in the insulin/IGF1 signaling pathway with human longevity. - Pawlikowska, Ludmila; Hu, Donglei; Huntsman, Scott; Sung, Andrew; Chu, Catherine; Chen, Justin; Joyner, Alexander H; Schork, Nicholas J; Hsueh, Wen-Chi; Reiner, Alexander P; Psaty, Bruce M; Atzmon, Gil; et al. (Aging Cell, 2009)
The insulin/IGF1 signaling pathways affect lifespan in several model organisms, including worms, flies and mice. To investigate whether common genetic variation in this pathway influences lifespan in humans, we genotyped 291 common variants in 30 genes encoding proteins in the insulin/IGF1 signaling pathway in a cohort of elderly Caucasian women selected from the Study of Osteoporotic Fractures (SOF). The cohort included 293 long-lived cases (lifespan > or = 92 years (y), mean +/- standard deviation (SD) = 95.3 +/- 2.2y) and 603 average-lifespan controls (lifespan < or = 79y, mean = 75.7 +/- 2.6y). Variants were selected for genotyping using a haplotype-tagging approach. We found a modest excess of variants nominally associated with longevity. Nominally significant variants were then replicated in two additional Caucasian cohorts including both males and females: the Cardiovascular Health Study and Ashkenazi Jewish Centenarians. An intronic single nucleotide polymorphism in AKT1, rs3803304, was significantly associated with lifespan in a meta-analysis across the three cohorts (OR = 0.78 95%CI = 0.68-0.89, adjusted P = 0.043); two intronic single nucleotide polymorphisms in FOXO3A demonstrated a significant lifespan association among women only (rs1935949, OR = 1.35, 95%CI = 1.15-1.57, adjusted P = 0.0093). These results demonstrate that common variants in several genes in the insulin/IGF1 pathway are associated with human lifespan.
Keywords: Aged; Aged, 80 and over; Female; Follow-Up Studies; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome, Human; Genotype; Humans; Insulin; Insulin-Like Growth Factor I; Longevity; Male; Osteoporosis; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins c-akt; Signal Transduction

Association of genetic variation in serum amyloid-A with cardiovascular disease and interactions with IL6, IL1RN, IL1beta and TNF genes in the Cardiovascular Health Study. - Carty, Cara L; Heagerty, Patrick; Heckbert, Susan R; Enquobahrie, Daniel A; Jarvik, Gail P; Davis, Scott; Tracy, Russell P; Reiner, Alexander P (J Atheroscler Thromb, 2009)
AIM: Since inflammation is an important contributor to atherosclerosis, gene variants mediating inflammation are of interest. We investigated gene variants in acute phase serum amyloid-A (SAA), a sensitive indicator of inflammatory activity, and their associations with cardiovascular disease (CVD) and HDL cholesterol. Interaction of the SAA genes with genetic variants of their regulators, IL-1, IL-6 and TNF-alpha in influencing CVD was also explored. METHODS: SNPs characterizing common variation in the SAA1 and SAA2 genes were genotyped in European-(EA) and African-American (AA) participants (n=3969 and n=719) of the Cardiovascular Health Study. Using linear and Cox proportional hazards regression, we assessed associations of SNPs with baseline carotid artery intima-media thickness (cIMT) and risk of incident myocardial infarction, ischemic stroke, total CVD events or mortality during 14 years of follow-up. RESULTS: No associations between SAA SNPs and outcomes were observed in EA, with the exception of total CVD events; each rs4638289 minor allele was associated with an increased risk in obese individuals, HR=1.2 (95%CI: 0.981.4; p=0.086) and decreased risk among non-obese, HR=0.9 (95%CI: 0.80.99; p=0.026). In AA, we observed modest associations between SAA SNPs and cIMT, potentially modified by HDL. SAA SNPs were also associated with lower HDL in EA and AA. Suggestive gene-gene interaction findings for cIMT in AA and CVD mortality in EA were not significant in subsequent model selection tests. CONCLUSION: Associations of SAA SNPs with cIMT, HDL and total CVD events were identified, unadjusted for multiple testing. These findings should be regarded as hypothesis-generating until confirmed by other studies.
Keywords: Aged; Cardiovascular Diseases; Cholesterol, HDL; Cytokines; Female; Gene Regulatory Networks; Humans; Inflammation Mediators; Interleukin 1 Receptor Antagonist Protein; Interleukin-1beta; Interleukin-6; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; Serum Amyloid A Protein; Tumor Necrosis Factor-alpha; Tunica Intima

Association of novel genetic Loci with circulating fibrinogen levels: a genome-wide association study in 6 population-based cohorts. - Dehghan, Abbas; Yang, Qiong; Peters, Annette; Basu, Saonli; Bis, Joshua C; Rudnicka, Alicja R; Kavousi, Maryam; Chen, Ming-Huei; Baumert, Jens; Lowe, Gordon D O; McKnight, Barbara; Tang, Weihong; et al. (Circ Cardiovasc Genet, 2009)
BACKGROUND: Fibrinogen is both central to blood coagulation and an acute-phase reactant. We aimed to identify common variants influencing circulation fibrinogen levels. METHODS AND RESULTS: We conducted a genome-wide association analysis on 6 population-based studies, the Rotterdam Study, the Framingham Heart Study, the Cardiovascular Health Study, the Atherosclerosis Risk in Communities Study, the Monitoring of Trends and Determinants in Cardiovascular Disease/KORA Augsburg Study, and the British 1958 Birth Cohort Study, including 22 096 participants of European ancestry. Four loci were marked by 1 or more single-nucleotide polymorphisms that demonstrated genome-wide significance (P<5.0 x 10(-8)). These included a single-nucleotide polymorphism located in the fibrinogen beta chain (FGB) gene and 3 single-nucleotide polymorphisms representing newly identified loci. The high-signal single-nucleotide polymorphisms were rs1800789 in exon 7 of FGB (P=1.8 x 10(-30)), rs2522056 downstream from the interferon regulatory factor 1 (IRF1) gene (P=1.3 x 10(-15)), rs511154 within intron 1 of the propionyl coenzyme A carboxylase (PCCB) gene (P=5.9 x 10(-10)), and rs1539019 on the NLR family pyrin domain containing 3 isoforms (NLRP3) gene (P=1.04 x 10(-8)). CONCLUSIONS: Our findings highlight biological pathways that may be important in regulation of inflammation underlying cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Associations of pentraxin 3 with cardiovascular disease and all-cause death: the Cardiovascular Health Study. - Jenny, Nancy Swords; Arnold, Alice M; Kuller, Lewis H; Tracy, Russell P; Psaty, Bruce M (Arterioscler Thromb Vasc Biol, 2009)
OBJECTIVE: We examined associations of pentraxin 3 (PTX3), a vascular inflammation marker, with incident cardiovascular disease (CVD) and all-cause death. METHODS AND RESULTS: 1583 Cardiovascular Health Study participants free of prevalent CVD were included. Nonexclusive case groups were angina (n=476), myocardial infarction (MI; n=237), stroke (n=310), CVD death (n=282), and all-cause death (n=772). 535 participants had no events. PTX3 levels were higher in those with subclinical CVD (1.90+/-1.89 ng/mL) than those without (1.71+/-1.88 ng/mL; P=0.001). Using Cox regression adjusted for age, sex, and ethnicity, a standard deviation increase in PTX3 (1.89 ng/mL) was associated with CVD death (hazard ratio 1.11; 95% confidence interval 1.02 to 1.21) and all-cause death (1.08; 1.02 to 1.15). PTX3 was not associated with angina (1.09; 0.98 to 1.20), MI (0.96; 0.81 to 1.12), or stroke (1.06; 0.95 to 1.18). Adding C-reactive protein (CRP) or CVD risk factors to the models had no significant effects on associations. CONCLUSIONS: In these older adults, PTX3 was associated with CVD and all-cause death independent of CRP and CVD risk factors. PTX3 likely reflects different aspects of inflammation than CRP and may provide insight into vascular health in aging and chronic diseases of aging that lead to death.
Keywords: Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Health Surveys; Humans; Inflammation Mediators; Linear Models; Male; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Serum Amyloid P-Component; Time Factors; United States; Up-Regulation

Common coding variants of the HNF1A gene are associated with multiple cardiovascular risk phenotypes in community-based samples of younger and older European-American adults: the Coronary Artery Risk Development in Young Adults Study and The Cardiovascula - Reiner, Alexander P; Gross, Myron D; Carlson, Christopher S; Bielinski, Suzette J; Lange, Leslie A; Fornage, Myriam; Jenny, Nancy S; Walston, Jeremy; Tracy, Russell P; Williams, O Dale; Jacobs, David R; Nickerson, Deborah A (Circ Cardiovasc Genet, 2009)
BACKGROUND: The transcription factor hepatocyte nuclear factor (HNF)-1 alpha regulates the activity of a number of genes involved in innate immunity, blood coagulation, lipid and glucose transport and metabolism, and cellular detoxification. Common polymorphisms of the HNF-1 alpha gene (HNF1A) were recently associated with plasma C-reactive protein and gamma-glutamyl transferase concentration in middle-aged to older European Americans (EA). METHODS AND RESULTS: We assessed whether common variants of HNF1A are associated with C-reactive protein, gamma-glutamyl transferase, and other atherosclerotic and metabolic risk factors, in the large, population-based Coronary Artery Risk Development in Young Adults Study of healthy young EA (n=2154) and African American (AA; n=2083) adults. The minor alleles of Ile27Leu (rs1169288) and Ser486Asn (rs2464196) were associated with 0.10 to 0.15 standard deviation units lower C-reactive protein and gamma-glutamyl transferase levels in EA. The same HNF1A coding variants were associated with higher low-density lipoprotein cholesterol, apolipoprotein B, creatinine, and fibrinogen in EA. We replicated the associations between HNF1A coding variants and C-reactive protein, fibrinogen, low-density lipoprotein cholesterol, and renal function in a second population-based sample of EA adults 65 years and older from the Cardiovascular Health Study. The HNF1A Ser486Asn and/or Ile27Leu variants were also associated with increased risk of subclinical coronary atherosclerosis in Coronary Artery Risk Development in Young Adults and with incident coronary heart disease in Cardiovascular Health Study. The Ile27Leu and Ser486Asn variants were 3-fold less common in AA than in EA. There was little evidence of association between HNF1A genotype and atherosclerosis-related phenotypes in AA. CONCLUSIONS: Common polymorphisms of HNF1A seem to influence multiple phenotypes related to cardiovascular risk in the general population of younger and older EA adults.
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; gamma-Glutamyltransferase; Genetic Predisposition to Disease; Genotype; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Genome-wide association study of blood pressure and hypertension. - Levy, Daniel; Ehret, Georg B; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Dehghan, Abbas; Glazer, Nicole L; Morrison, Alanna C; Johnson, Andrew D; Aspelund, Thor; Aulchenko, Yurii; Lumley, Thomas; et al. (Nat Genet, 2009)
Blood pressure is a major cardiovascular disease risk factor. To date, few variants associated with interindividual blood pressure variation have been identified and replicated. Here we report results of a genome-wide association study of systolic (SBP) and diastolic (DBP) blood pressure and hypertension in the CHARGE Consortium (n = 29,136), identifying 13 SNPs for SBP, 20 for DBP and 10 for hypertension at P < 4 × 10(-7). The top ten loci for SBP and DBP were incorporated into a risk score; mean BP and prevalence of hypertension increased in relation to the number of risk alleles carried. When ten CHARGE SNPs for each trait were included in a joint meta-analysis with the Global BPgen Consortium (n = 34,433), four CHARGE loci attained genome-wide significance (P < 5 × 10(-8)) for SBP (ATP2B1, CYP17A1, PLEKHA7, SH2B3), six for DBP (ATP2B1, CACNB2, CSK-ULK3, SH2B3, TBX3-TBX5, ULK4) and one for hypertension (ATP2B1). Identifying genes associated with blood pressure advances our understanding of blood pressure regulation and highlights potential drug targets for the prevention or treatment of hypertension.
Keywords: Blood Pressure; Cell Line; Chromosome Mapping; Chromosomes, Human; Diastole; Gene Expression Regulation; Genetic Association Studies; Genome-Wide Association Study; Humans; Hypertension; Liver; Lymphocytes; Meta-Analysis as Topic; Odds Ratio; Phenotype; Prevalence; Risk Assessment; Systole

High frequency of and factors associated with thyroid hormone over-replacement and under-replacement in men and women aged 65 and over. - Somwaru, Lily L; Arnold, Alice M; Joshi, Neha; Fried, Linda P; Cappola, Anne R (J Clin Endocrinol Metab, 2009)
CONTEXT: Thyroid hormone use is common in older populations, but the frequency of over- or under-replacement is debated. OBJECTIVE: We sought to describe the frequency of and factors associated with thyroid hormone over- or under-replacement in a population of older men and women. DESIGN: Participants were 3678 U.S. community dwelling individuals aged 65 yr or older enrolled in the Cardiovascular Health Study who had thyroid function tests in 1989-1990. Thyroid hormone users (n = 339) were identified and classified into low TSH (<0.45 mU/liter), euthyroid (0.45-4.5 mU/liter), and high TSH (>4.5 mU/liter). RESULTS: Of the 339 thyroid hormone users, 41% had a low TSH, 16% had a high TSH, and 43% were in the euthyroid range. In multivariable analyses, lower weight (P < 0.001) was independently associated with low TSH status. For every 10 kg lower weight, the likelihood of having low TSH increased by 65% [odd ratio (OR) 1.65; 95% confidence interval (CI) 1.31-2.07]. Those with renal insufficiency were less likely to have low TSH levels (P = 0.02). The presence of diabetes was independently associated with having low (OR 3.35; 95% CI 1.46-7.65) and high TSH levels (OR 2.66; 95% CI 1.14-6.21). CONCLUSIONS: There is a very high prevalence of thyroid function testing abnormalities in older people taking thyroid hormone preparations, particularly in those of low weight or with diabetes. Because of potential adverse cardiovascular and skeletal effects from over-replacement, older people represent a key population for increased TSH monitoring on therapy.
Keywords: Aged; Body Mass Index; Body Weight; Diabetes Mellitus; Dose-Response Relationship, Drug; Drug Therapy, Combination; Female; Hormone Replacement Therapy; Humans; Male; Multivariate Analysis; Renal Insufficiency; Risk Factors; Thyroid Diseases; Thyroid Hormones; Thyrotropin; Thyroxine; Triiodothyronine

Insulin-like growth factors and leukocyte telomere length: the cardiovascular health study. - Kaplan, Robert C; Fitzpatrick, Annette L; Pollak, Michael N; Gardner, Jeffrey P; Jenny, Nancy S; McGinn, Aileen P; Kuller, Lewis H; Strickler, Howard D; Kimura, Masayuki; Psaty, Bruce M; Aviv, Abraham (J Gerontol A Biol Sci Med Sci, 2009)
The insulin-like growth factor (IGF) axis may affect immune cell replicative potential and telomere dynamics. Among 551 adults 65 years and older, leukocyte telomere length (LTL), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor-binding proteins 1 and 3 (IGFBP-1, IGFBP-3) were measured. Multivariate linear regression was used to model the association of LTL with IGF-1 and IGFBPs, while controlling for confounding and increasing precision by adjusting for covariates. We observed a significant association between higher IGF-1 and longer LTL after adjustment for age, sex, race, smoking status, body mass index, hypertension, diabetes, and serum lipids. The results suggested an increase of .08 kb in LTL for each standard deviation increase of IGF-1 (p = .04). IGFBP-1 and IGFBP-3 were not significantly associated with LTL. High IGF-1 may be an independent predictor of longer LTL, consistent with prior evidence suggesting a role for IGF-1 in mechanisms relating to telomere maintenance.
Keywords: Aged; Aging; Cross-Sectional Studies; Female; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor Binding Proteins; Insulin-Like Growth Factor I; Leukocytes; Linear Models; Male; Sex Characteristics; Telomere

Lipoprotein-associated phospholipase A(2) and risk of congestive heart failure in older adults: the Cardiovascular Health Study. - Suzuki, Takeki; Solomon, Cam; Jenny, Nancy Swords; Tracy, Russell; Nelson, Jeanenne J; Psaty, Bruce M; Furberg, Curt; Cushman, Mary (Circ Heart Fail, 2009)
BACKGROUND: Inflammation may be a causative factor in congestive heart failure (CHF). Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) is an inflammation marker associated with vascular risk. One previous study showed an association of Lp-PLA(2) activity with CHF risk, but there were only 94 CHF cases and Lp-PLA(2) antigen, which is available clinically in the United States, was not measured. METHODS AND RESULTS: We measured baseline Lp-PLA(2) antigen and activity in 3991 men and women without baseline CHF or cardiovascular disease who were participating in the Cardiovascular Health Study, a prospective observational study of adults 65 years or older. Cox proportional hazards models adjusted for age, sex, clinic site, race, low-density and high-density lipoprotein cholesterol, body mass index, systolic and diastolic blood pressure, hypertension, smoking status, pack-years, and diabetes were used to calculate hazard ratios and 95% CIs for incident CHF. Further models adjusted for coronary disease events during follow-up and C-reactive protein. Eight hundred twenty-nine participants developed CHF during 12.1 years. Adjusted hazard ratios for CHF with Lp-PLA(2) in the fourth compared with the first quartile were 1.44 (95% CI, 1.16 to 1.79) for Lp-PLA(2) antigen and 1.06 (95% CI, 0.84 to 1.32) for activity. Adjustment for incident coronary disease attenuated the hazard ratio for Lp-PLA(2) antigen to 1.26 (95% CI, 1.02 to 1.57), adjustment for C-reactive protein had minimal impact. CONCLUSIONS: Lp-PLA(2) antigen was associated with risk of future CHF in older people, independent of CHF and coronary risk factors, and partly mediated by coronary disease events. Further clinical and basic research is needed to better understand the role of Lp-PLA(2) in CHF.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Biomarkers; C-Reactive Protein; Female; Fibrinogen; Heart Failure; Humans; Incidence; Inflammation Mediators; Interleukin-6; Kaplan-Meier Estimate; Male; Population Surveillance; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Longitudinal Data with Follow-up Truncated by Death: Match the Analysis Method to Research Aims. - Kurland, Brenda F; Johnson, Laura L; Egleston, Brian L; Diehr, Paula H (Stat Sci, 2009)
Diverse analysis approaches have been proposed to distinguish data missing due to death from nonresponse, and to summarize trajectories of longitudinal data truncated by death. We demonstrate how these analysis approaches arise from factorizations of the distribution of longitudinal data and survival information. Models are illustrated using cognitive functioning data for older adults. For unconditional models, deaths do not occur, deaths are independent of the longitudinal response, or the unconditional longitudinal response is averaged over the survival distribution. Unconditional models, such as random effects models fit to unbalanced data, may implicitly impute data beyond the time of death. Fully conditional models stratify the longitudinal response trajectory by time of death. Fully conditional models are effective for describing individual trajectories, in terms of either aging (age, or years from baseline) or dying (years from death). Causal models (principal stratification) as currently applied are fully conditional models, since group differences at one timepoint are described for a cohort that will survive past a later timepoint. Partly conditional models summarize the longitudinal response in the dynamic cohort of survivors. Partly conditional models are serial cross-sectional snapshots of the response, reflecting the average response in survivors at a given timepoint rather than individual trajectories. Joint models of survival and longitudinal response describe the evolving health status of the entire cohort. Researchers using longitudinal data should consider which method of accommodating deaths is consistent with research aims, and use analysis methods accordingly.

Metabolic syndrome and risk of venous thromboembolism: Longitudinal Investigation of Thromboembolism Etiology. - Steffen, L M; Cushman, M; Peacock, J M; Heckbert, S R; Jacobs, D R; Rosamond, W D; Folsom, A R (J Thromb Haemost, 2009)
SUMMARY BACKGROUND: In a recent case-control study, the odds of metabolic syndrome (MetSyn) among deep vein thrombosis cases were almost twice those among controls. We tested the hypothesis that the incidence of non-cancer-related venous thromboembolism (VTE) is higher among adults with MetSyn and further, that associations are stronger for idiopathic than secondary VTE. METHODS: A total of 20 374 middle-aged and elderly adults were followed for over 12 years for incident VTE in the Longitudinal Investigation of Thromboembolism Etiology (LITE). All hospitalizations were identified and VTEs validated by chart review. Baseline MetSyn was defined using ATP III guidelines, including >or=3 of the following components: abdominal obesity, elevated blood pressure, low HDL-cholesterol, high triglycerides and high glucose. Because sex modified the relation between MetSyn and VTE (p(interaction) = 0.001), proportional hazards regression analyses were stratified by sex to assess the associations of MetSyn and its components with risk of incident non-cancer-related VTE, adjusting for potential confounders. RESULTS: Incident VTE (n = 358) included 196 idiopathic events. Baseline MetSyn was associated with risk of total VTE (hazard ratio (HR) = 1.84, 95% CI = 1.30, 2.59) and idiopathic VTE (HR = 1.59, 95% CI = 1.02, 2.47) among men, but not women. The association was largely attributable to abdominal obesity (HR of VTE = 2.10, 95% CI = 1.51, 2.93, in men; HR of VTE = 1.70, 95% CI = 1.24, 2.34, in women), with no additional contribution by the other MetSyn components. CONCLUSION: Although abdominal obesity was associated with increased risk of VTE in both men and women, MetSyn and its other components do not seem important in VTE etiology.
Keywords: Blood Coagulation Factors; Blood Glucose; Blood Pressure; Body Mass Index; Cohort Studies; Female; Fibrinogen; Humans; Lipids; Longitudinal Studies; Male; Metabolic Syndrome; Proportional Hazards Models; Risk Factors; Venous Thromboembolism

Multiple loci influence erythrocyte phenotypes in the CHARGE Consortium. - Ganesh, Santhi K; Zakai, Neil A; van Rooij, Frank J A; Soranzo, Nicole; Smith, Albert V; Nalls, Michael A; Chen, Ming-Huei; Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Kuhnel, Brigitte; Aspelund, Thor; et al. (Nat Genet, 2009)
Measurements of erythrocytes within the blood are important clinical traits and can indicate various hematological disorders. We report here genome-wide association studies (GWAS) for six erythrocyte traits, including hemoglobin concentration (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red blood cell count (RBC). We performed an initial GWAS in cohorts of the CHARGE Consortium totaling 24,167 individuals of European ancestry and replication in additional independent cohorts of the HaemGen Consortium totaling 9,456 individuals. We identified 23 loci significantly associated with these traits in a meta-analysis of the discovery and replication cohorts (combined P values ranging from 5 x 10(-8) to 7 x 10(-86)). Our findings include loci previously associated with these traits (HBS1L-MYB, HFE, TMPRSS6, TFR2, SPTA1) as well as new associations (EPO, TFRC, SH2B3 and 15 other loci). This study has identified new determinants of erythrocyte traits, offering insight into common variants underlying variation in erythrocyte measures.
Keywords: Blood Pressure; Cell Line; Cohort Studies; Endothelial Cells; Erythrocytes; Gene Expression; Genome, Human; Genome-Wide Association Study; Humans; Hypertension; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

NRXN3 is a novel locus for waist circumference: a genome-wide association study from the CHARGE Consortium. - Heard-Costa, Nancy L; Zillikens, M Carola; Monda, Keri L; Johansson, Asa; Harris, Tamara B; Fu, Mao; Haritunians, Talin; Feitosa, Mary F; Aspelund, Thor; Eiriksdottir, Gudny; Garcia, Melissa; Launer, Lenore J; et al. (PLoS Genet, 2009)
Central abdominal fat is a strong risk factor for diabetes and cardiovascular disease. To identify common variants influencing central abdominal fat, we conducted a two-stage genome-wide association analysis for waist circumference (WC). In total, three loci reached genome-wide significance. In stage 1, 31,373 individuals of Caucasian descent from eight cohort studies confirmed the role of FTO and MC4R and identified one novel locus associated with WC in the neurexin 3 gene [NRXN3 (rs10146997, p = 6.4x10(-7))]. The association with NRXN3 was confirmed in stage 2 by combining stage 1 results with those from 38,641 participants in the GIANT consortium (p = 0.009 in GIANT only, p = 5.3x10(-8) for combined analysis, n = 70,014). Mean WC increase per copy of the G allele was 0.0498 z-score units (0.65 cm). This SNP was also associated with body mass index (BMI) [p = 7.4x10(-6), 0.024 z-score units (0.10 kg/m(2)) per copy of the G allele] and the risk of obesity (odds ratio 1.13, 95% CI 1.07-1.19; p = 3.2x10(-5) per copy of the G allele). The NRXN3 gene has been previously implicated in addiction and reward behavior, lending further evidence that common forms of obesity may be a central nervous system-mediated disorder. Our findings establish that common variants in NRXN3 are associated with WC, BMI, and obesity.
Keywords: Aged; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Obesity; Polymorphism, Single Nucleotide; Waist Circumference

Systematically missing confounders in individual participant data meta-analysis of observational cohort studies. - Jackson, Dan; White, Ian; Kostis, J B; Wilson, A C; Folsom, A R; Wu, K; Chambless, L; Benderly, M; Goldbourt, U; Willeit, J; Kiechl, S; Yarnell, J W G; et al. (Stat Med, 2009)
One difficulty in performing meta-analyses of observational cohort studies is that the availability of confounders may vary between cohorts, so that some cohorts provide fully adjusted analyses while others only provide partially adjusted analyses. Commonly, analyses of the association between an exposure and disease either are restricted to cohorts with full confounder information, or use all cohorts but do not fully adjust for confounding. We propose using a bivariate random-effects meta-analysis model to use information from all available cohorts while still adjusting for all the potential confounders. Our method uses both the fully adjusted and the partially adjusted estimated effects in the cohorts with full confounder information, together with an estimate of their within-cohort correlation. The method is applied to estimate the association between fibrinogen level and coronary heart disease incidence using data from 154,012 participants in 31 cohorts
Keywords: Cohort Studies; Computer Simulation; Coronary Disease; Data Interpretation, Statistical; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Models, Statistical

Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index. - Speliotes, Elizabeth K; Willer, Cristen J; Berndt, Sonja I; Monda, Keri L; Thorleifsson, Gudmar; Jackson, Anne U; Lango Allen, Hana; Lindgren, Cecilia M; Luan, Jian'an; Mägi, Reedik; Randall, Joshua C; Vedantam, Sailaja; et al. (Nat Genet, 2010)
Obesity is globally prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined associations between body mass index and ∼ 2.8 million SNPs in up to 123,865 individuals with targeted follow up of 42 SNPs in up to 125,931 additional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci associated with body mass index (P < 5 × 10⁻⁸), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly associated loci may provide new insights into human body weight regulation.
Keywords: Body Height; Body Mass Index; Body Size; Body Weight; Chromosome Mapping; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Obesity; Polymorphism, Single Nucleotide

Association between baseline kidney function and change in CRP: an analysis of the cardiovascular health study. - Rifkin, Dena E; Katz, Ronit; Fried, Linda F; Kestenbaum, Bryan; Jenny, Nancy Swords; Newman, Anne B; Siscovick, David S; Shlipak, Michael G; Sarnak, Mark J (Nephron Clin Pract, 2010)
BACKGROUND: In cross-sectional analyses, C-reactive protein (CRP) levels are inversely related to levels of kidney function. The relationship between kidney function and subsequent changes in CRP is unknown. METHODS: We studied 4,364 individuals from the Cardiovascular Health Study, a longitudinal cohort of community-dwelling older adults. Baseline eGFRcys was estimated using cystatin C. CRP was measured at baseline and after 3 and 7 years of follow-up; slopes of change in CRP were calculated. RESULTS: The mean (SD) age of the cohort was 72 (5.2) years; mean (SD) eGFRcys was 78.9 (18.4) ml/min/1.73 m(2). The median (interquartile range IQR) baseline CRP was 2.39 (1.22, 4.33) mg/l; the median (IQR) yearly change in CRP was -0.0051 (-0.020 to 0.27) mg/l/year. After adjustment for demographic characteristics and the initial level of CRP, each standard deviation lower baseline eGFR was associated with a small and non-significant yearly increase in CRP (0.032 mg/l/year; 95% CI: -0.005 to 0.070, p = 0.094). CONCLUSIONS: We did not find a relationship between eGFR and subsequent changes in CRP. The association between kidney function and CRP in cross-sectional analyses may reflect unmeasured confounding by atherosclerosis; alternatively, the burden of comorbidity and interval mortality in this population may have masked a stronger longitudinal association between kidney function and change in CRP. Further study in younger populations may clarify whether impaired kidney function leads to change in inflammation over time.
Keywords: Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Female; Follow-Up Studies; Glomerular Filtration Rate; Humans; Kidney Function Tests; Longitudinal Studies; Male; Residence Characteristics

Association between depressive symptoms and fibrosis markers: the Cardiovascular Health Study. - Kop, Willem J; Kuhl, Emily A; Barasch, Eddy; Jenny, Nancy S; Gottlieb, Stephen S; Gottdiener, John S (Brain Behav Immun, 2010)
OBJECTIVE: Fibrosis plays an important role in heart failure (HF) and other diseases that occur more frequently with increasing age. Depression is associated with an increased risk of heart failure and other age-related diseases. This study examined the association between depressive symptoms and fibrosis markers in adults aged 65 years and above. METHODS: Fibrosis markers and depressive symptoms were assessed in 870 participants (age=80.9+/-5.9 yrs, 49% women) using a case-control design based on heart failure status (307 HF patients and 563 age- and sex-matched controls, of whom 284 with CVD risk factors (hypertension, diabetes mellitus, or hypercholesterolemia) and 279 controls without these CVD risk factors). Fibrosis markers were procollagen type I (PIP), type I collagen (CITP), and procollagen type III (PIIINP). Inflammation markers included C-reactive protein, white blood cell counts and fibrinogen. Depression was assessed using the Center for Epidemiological Studies-Depression (CES-D) scale using a previously validated cut-off point for depression (CES-D > or = 8). Covariates included demographic and clinical variables. RESULTS: Depression was associated with higher levels of PIP (median=411.0, inter-quartile range (IQR)=324.4-472.7 ng/mL vs. 387.6, IQR=342.0-512.5 ng/mL, p=0.006) and CITP (4.99, IQR=3.53-6.85 vs. 4.53, IQR=3.26-6.22 microg/L, p=0.024), but not PIIIINP (4.07, IQR=2.75-5.54 microg/L vs. 3.58, IQR=2.71-5.01 microg/L, p=0.29) compared to individuals without depression. Inflammation markers were also elevated in depressed participants (CRP, p=0.014; WBC, p=0.075; fibrinogen, p=0.074), but these inflammation markers did not account for the relationship between depression and fibrosis markers. CONCLUSIONS: Depression is associated with elevated fibrosis markers and may therefore adversely affect heart failure and other age-related diseases in which extra-cellular matrix formation plays a pathophysiological role.
Keywords: Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Collagen Type I; Depression; Electrocardiography; Endomyocardial Fibrosis; Fatigue; Female; Fibrosis; Health Surveys; Heart Failure; Humans; Inflammation Mediators; Male; Multivariate Analysis; Peptide Fragments; Procollagen; Psychiatric Status Rating Scales; Risk Factors; Socioeconomic Factors

Bayesian methods for meta-analysis of causal relationships estimated using genetic instrumental variables. - Burgess, Stephen; Thompson, Simon G; Burgess, S; Thompson, S G; Andrews, G; Samani, N J; Hall, A; Whincup, P; Morris, R; Lawlor, D A; Davey Smith, G; Timpson, N; et al. (Stat Med, 2010)
Genetic markers can be used as instrumental variables, in an analogous way to randomization in a clinical trial, to estimate the causal relationship between a phenotype and an outcome variable. Our purpose is to extend the existing methods for such Mendelian randomization studies to the context of multiple genetic markers measured in multiple studies, based on the analysis of individual participant data. First, for a single genetic marker in one study, we show that the usual ratio of coefficients approach can be reformulated as a regression with heterogeneous error in the explanatory variable. This can be implemented using a Bayesian approach, which is next extended to include multiple genetic markers. We then propose a hierarchical model for undertaking a meta-analysis of multiple studies, in which it is not necessary that the same genetic markers are measured in each study. This provides an overall estimate of the causal relationship between the phenotype and the outcome, and an assessment of its heterogeneity across studies. As an example, we estimate the causal relationship of blood concentrations of C-reactive protein on fibrinogen levels using data from 11 studies. These methods provide a flexible framework for efficient estimation of causal relationships derived from multiple studies. Issues discussed include weak instrument bias, analysis of binary outcome data such as disease risk, missing genetic data, and the use of haplotypes.
Keywords: Bayes Theorem; Biostatistics; C-Reactive Protein; Fibrinogen; Genetic Markers; Humans; Meta-Analysis as Topic; Models, Statistical; Phenotype; Polymorphism, Single Nucleotide

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Common genetic determinants of vitamin D insufficiency: a genome-wide association study. - Wang, Thomas J; Zhang, Feng; Richards, J Brent; Kestenbaum, Bryan; van Meurs, Joyce B; Berry, Diane; Kiel, Douglas P; Streeten, Elizabeth A; Ohlsson, Claes; Koller, Daniel L; Peltonen, Leena; Cooper, Jason D; et al. (Lancet, 2010)
BACKGROUND: Vitamin D is crucial for maintenance of musculoskeletal health, and might also have a role in extraskeletal tissues. Determinants of circulating 25-hydroxyvitamin D concentrations include sun exposure and diet, but high heritability suggests that genetic factors could also play a part. We aimed to identify common genetic variants affecting vitamin D concentrations and risk of insufficiency. METHODS: We undertook a genome-wide association study of 25-hydroxyvitamin D concentrations in 33 996 individuals of European descent from 15 cohorts. Five epidemiological cohorts were designated as discovery cohorts (n=16 125), five as in-silico replication cohorts (n=9367), and five as de-novo replication cohorts (n=8504). 25-hydroxyvitamin D concentrations were measured by radioimmunoassay, chemiluminescent assay, ELISA, or mass spectrometry. Vitamin D insufficiency was defined as concentrations lower than 75 nmol/L or 50 nmol/L. We combined results of genome-wide analyses across cohorts using Z-score-weighted meta-analysis. Genotype scores were constructed for confirmed variants. FINDINGS: Variants at three loci reached genome-wide significance in discovery cohorts for association with 25-hydroxyvitamin D concentrations, and were confirmed in replication cohorts: 4p12 (overall p=1.9x10(-109) for rs2282679, in GC); 11q12 (p=2.1x10(-27) for rs12785878, near DHCR7); and 11p15 (p=3.3x10(-20) for rs10741657, near CYP2R1). Variants at an additional locus (20q13, CYP24A1) were genome-wide significant in the pooled sample (p=6.0x10(-10) for rs6013897). Participants with a genotype score (combining the three confirmed variants) in the highest quartile were at increased risk of having 25-hydroxyvitamin D concentrations lower than 75 nmol/L (OR 2.47, 95% CI 2.20-2.78, p=2.3x10(-48)) or lower than 50 nmol/L (1.92, 1.70-2.16, p=1.0x10(-26)) compared with those in the lowest quartile. INTERPRETATION: Variants near genes involved in cholesterol synthesis, hydroxylation, and vitamin D transport affect vitamin D status. Genetic variation at these loci identifies individuals who have substantially raised risk of vitamin D insufficiency. FUNDING: Full funding sources listed at end of paper (see Acknowledgments).
Keywords: Canada; Chromosomes, Human, Pair 11; Chromosomes, Human, Pair 4; Cohort Studies; Dietary Supplements; Europe; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Immunoassay; International Cooperation; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Seasons; United States; Vitamin D; Vitamin D Deficiency

Common variants in 22 loci are associated with QRS duration and cardiac ventricular conduction. - Sotoodehnia, Nona; Isaacs, Aaron; de Bakker, Paul I W; Dörr, Marcus; Newton-Cheh, Christopher; Nolte, Ilja M; van der Harst, Pim; Müller, Martina; Eijgelsheim, Mark; Alonso, Alvaro; Hicks, Andrew A; Padmanabhan, Sandosh; et al. (Nat Genet, 2010)
The QRS interval, from the beginning of the Q wave to the end of the S wave on an electrocardiogram, reflects ventricular depolarization and conduction time and is a risk factor for mortality, sudden death and heart failure. We performed a genome-wide association meta-analysis in 40,407 individuals of European descent from 14 studies, with further genotyping in 7,170 additional Europeans, and we identified 22 loci associated with QRS duration (P < 5 × 10(-8)). These loci map in or near genes in pathways with established roles in ventricular conduction such as sodium channels, transcription factors and calcium-handling proteins, but also point to previously unidentified biologic processes, such as kinase inhibitors and genes related to tumorigenesis. We demonstrate that SCN10A, a candidate gene at the most significantly associated locus in this study, is expressed in the mouse ventricular conduction system, and treatment with a selective SCN10A blocker prolongs QRS duration. These findings extend our current knowledge of ventricular depolarization and conduction.
Keywords: Animals; Animals, Newborn; Chromosomes, Human; Computational Biology; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Mice; Mice, Transgenic; Models, Animal; Myocytes, Cardiac; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sodium Channels

Common variants in the calcium-sensing receptor gene are associated with total serum calcium levels. - O'Seaghdha, Conall M; Yang, Qiong; Glazer, Nicole L; Leak, Tennille S; Dehghan, Abbas; Smith, Albert V; Kao, W H Linda; Lohman, Kurt; Hwang, Shih-Jen; Johnson, Andrew D; Hofman, Albert; Uitterlinden, André G; et al. (Hum Mol Genet, 2010)
Serum calcium levels are tightly regulated. We performed genome-wide association studies (GWAS) in population-based studies participating in the CHARGE Consortium to uncover common genetic variations associated with total serum calcium levels. GWAS of serum calcium concentrations was performed in 20 611 individuals of European ancestry for ∼2.5 million genotyped and imputed single-nucleotide polymorphisms (SNPs). The SNP with the lowest P-value was rs17251221 (P = 2.4 * 10(-22), minor allele frequency 14%) in the calcium-sensing receptor gene (CASR). This lead SNP was associated with higher serum calcium levels [0.06 mg/dl (0.015 mmol/l) per copy of the minor G allele] and accounted for 0.54% of the variance in serum calcium concentrations. The identification of variation in CASR that influences serum calcium concentration confirms the results of earlier candidate gene studies. The G allele of rs17251221 was also associated with higher serum magnesium levels (P = 1.2 * 10(-3)), lower serum phosphate levels (P = 2.8 * 10(-7)) and lower bone mineral density at the lumbar spine (P = 0.038), but not the femoral neck. No additional genomic loci contained SNPs associated at genome-wide significance (P < 5 * 10(-8)). These associations resemble clinical characteristics of patients with familial hypocalciuric hypercalcemia, an autosomal-dominant disease arising from rare inactivating mutations in the CASR gene. We conclude that common genetic variation in the CASR gene is associated with similar but milder features in the general population.
Keywords: Adult; Calcium; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing

Differential white blood cell count and type 2 diabetes: systematic review and meta-analysis of cross-sectional and prospective studies. - Gkrania-Klotsas, Effrossyni; Ye, Zheng; Cooper, Andrew J; Sharp, Stephen J; Luben, Robert; Biggs, Mary L; Chen, Liang-Kung; Gokulakrishnan, Kuppan; Hanefeld, Markolf; Ingelsson, Erik; Lai, Wen-An; Lin, Shih-Yi; et al. (PLoS One, 2010)
OBJECTIVE: Biological evidence suggests that inflammation might induce type 2 diabetes (T2D), and epidemiological studies have shown an association between higher white blood cell count (WBC) and T2D. However, the association has not been systematically investigated. RESEARCH DESIGN AND METHODS: Studies were identified through computer-based and manual searches. Previously unreported studies were sought through correspondence. 20 studies were identified (8,647 T2D cases and 85,040 non-cases). Estimates of the association of WBC with T2D were combined using random effects meta-analysis; sources of heterogeneity as well as presence of publication bias were explored. RESULTS: The combined relative risk (RR) comparing the top to bottom tertile of the WBC count was 1.61 (95% CI: 1.45; 1.79, p = 1.5*10(-18)). Substantial heterogeneity was present (I(2) = 83%). For granulocytes the RR was 1.38 (95% CI: 1.17; 1.64, p = 1.5*10(-4)), for lymphocytes 1.26 (95% CI: 1.02; 1.56, p = 0.029), and for monocytes 0.93 (95% CI: 0.68; 1.28, p = 0.67) comparing top to bottom tertile. In cross-sectional studies, RR was 1.74 (95% CI: 1.49; 2.02, p = 7.7*10(-13)), while in cohort studies it was 1.48 (95% CI: 1.22; 1.79, p = 7.7*10(-5)). We assessed the impact of confounding in EPIC-Norfolk study and found that the age and sex adjusted HR of 2.19 (95% CI: 1.74; 2.75) was attenuated to 1.82 (95% CI: 1.45; 2.29) after further accounting for smoking, T2D family history, physical activity, education, BMI and waist circumference. CONCLUSIONS: A raised WBC is associated with higher risk of T2D. The presence of publication bias and failure to control for all potential confounders in all studies means the observed association is likely an overestimate.
Keywords: Adult; Aged; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Leukocyte Count; Male; Middle Aged; Prospective Studies

Four novel Loci (19q13, 6q24, 12q24, and 5q14) influence the microcirculation in vivo. - Ikram, M Kamran; Sim, Xueling; Xueling, Sim; Jensen, Richard A; Cotch, Mary Frances; Hewitt, Alex W; Ikram, M Arfan; Wang, Jie Jin; Klein, Ronald; Klein, Barbara E K; Breteler, Monique M B; Cheung, Ning; et al. (PLoS Genet, 2010)
There is increasing evidence that the microcirculation plays an important role in the pathogenesis of cardiovascular diseases. Changes in retinal vascular caliber reflect early microvascular disease and predict incident cardiovascular events. We performed a genome-wide association study to identify genetic variants associated with retinal vascular caliber. We analyzed data from four population-based discovery cohorts with 15,358 unrelated Caucasian individuals, who are members of the Cohort for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and replicated findings in four independent Caucasian cohorts (n  =  6,652). All participants had retinal photography and retinal arteriolar and venular caliber measured from computer software. In the discovery cohorts, 179 single nucleotide polymorphisms (SNP) spread across five loci were significantly associated (p<5.0×10(-8)) with retinal venular caliber, but none showed association with arteriolar caliber. Collectively, these five loci explain 1.0%-3.2% of the variation in retinal venular caliber. Four out of these five loci were confirmed in independent replication samples. In the combined analyses, the top SNPs at each locus were: rs2287921 (19q13; p  =  1.61×10(-25), within the RASIP1 locus), rs225717 (6q24; p = 1.25×10(-16), adjacent to the VTA1 and NMBR loci), rs10774625 (12q24; p  =  2.15×10(-13), in the region of ATXN2,SH2B3 and PTPN11 loci), and rs17421627 (5q14; p = 7.32×10(-16), adjacent to the MEF2C locus). In two independent samples, locus 12q24 was also associated with coronary heart disease and hypertension. Our population-based genome-wide association study demonstrates four novel loci associated with retinal venular caliber, an endophenotype of the microcirculation associated with clinical cardiovascular disease. These data provide further insights into the contribution and biological mechanisms of microcirculatory changes that underlie cardiovascular disease.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Child; Child, Preschool; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; Cohort Studies; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Microcirculation; Middle Aged; Polymorphism, Single Nucleotide; Retinal Vessels; Young Adult

Fucosyltransferase 2 (FUT2) non-secretor status is associated with Crohn's disease. - McGovern, Dermot P B; Jones, Michelle R; Taylor, Kent D; Marciante, Kristin; Yan, Xiaofei; Dubinsky, Marla; Ippoliti, Andy; Vasiliauskas, Eric; Berel, Dror; Derkowski, Carrie; Dutridge, Deb; Fleshner, Phil; et al. (Hum Mol Genet, 2010)
Genetic variation in both innate and adaptive immune systems is associated with Crohn's disease (CD) susceptibility, but much of the heritability to CD remains unknown. We performed a genome-wide association study (GWAS) in 896 CD cases and 3204 healthy controls all of Caucasian origin as defined by multidimensional scaling. We found supportive evidence for 21 out of 40 CD loci identified in a recent CD GWAS meta-analysis, including two loci which had only nominally achieved replication (rs4807569, 19p13; rs991804, CCL2/CCL7). In addition, we identified associations with genes involved in tight junctions/epithelial integrity (ASHL, ARPC1A), innate immunity (EXOC2), dendritic cell biology [CADM1 (IGSF4)], macrophage development (MMD2), TGF-beta signaling (MAP3K7IP1) and FUT2 (a physiological trait that regulates gastrointestinal mucosal expression of blood group A and B antigens) (rs602662, P=3.4x10(-5)). Twenty percent of Caucasians are 'non-secretors' who do not express ABO antigens in saliva as a result of the FUT2 W134X allele. We demonstrated replication in an independent cohort of 1174 CD cases and 357 controls between the four primary FUT2 single nucleotide polymorphisms (SNPs) and CD (rs602662, combined P-value 4.90x10(-8)) and also association with FUT2 W143X (P=2.6x10(-5)). Further evidence of the relevance of this locus to CD pathogenesis was demonstrated by the association of the original four SNPs and CD in the recently published CD GWAS meta-analysis (rs602662, P=0.001). These findings strongly implicate this locus in CD susceptibility and highlight the role of the mucus layer in the development of CD.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Cohort Studies; Crohn Disease; Female; Fucosyltransferases; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Genome-wide analysis of genetic loci associated with Alzheimer disease. - Seshadri, Sudha; Fitzpatrick, Annette L; Ikram, M Arfan; DeStefano, Anita L; Gudnason, Vilmundur; Boada, Merce; Bis, Joshua C; Smith, Albert V; Carassquillo, Minerva M; Lambert, Jean Charles; Harold, Denise; Schrijvers, Elisabeth M C; et al. (JAMA, 2010)
CONTEXT: Genome-wide association studies (GWAS) have recently identified CLU, PICALM, and CR1 as novel genes for late-onset Alzheimer disease (AD). OBJECTIVES: To identify and strengthen additional loci associated with AD and confirm these in an independent sample and to examine the contribution of recently identified genes to AD risk prediction in a 3-stage analysis of new and previously published GWAS on more than 35,000 persons (8371 AD cases). DESIGN, SETTING, AND PARTICIPANTS: In stage 1, we identified strong genetic associations (P < 10(-3)) in a sample of 3006 AD cases and 14,642 controls by combining new data from the population-based Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (1367 AD cases [973 incident]) with previously reported results from the Translational Genomics Research Institute and the Mayo AD GWAS. We identified 2708 single-nucleotide polymorphisms (SNPs) with P < 10(-3). In stage 2, we pooled results for these SNPs with the European AD Initiative (2032 cases and 5328 controls) to identify 38 SNPs (10 loci) with P < 10(-5). In stage 3, we combined data for these 10 loci with data from the Genetic and Environmental Risk in AD consortium (3333 cases and 6995 controls) to identify 4 SNPs with P < 1.7x10(-8). These 4 SNPs were replicated in an independent Spanish sample (1140 AD cases and 1209 controls). Genome-wide association analyses were completed in 2007-2008 and the meta-analyses and replication in 2009. MAIN OUTCOME MEASURE: Presence of Alzheimer disease. RESULTS: Two loci were identified to have genome-wide significance for the first time: rs744373 near BIN1 (odds ratio [OR],1.13; 95% confidence interval [CI],1.06-1.21 per copy of the minor allele; P = 1.59x10(-11)) and rs597668 near EXOC3L2/BLOC1S3/MARK4 (OR, 1.18; 95% CI, 1.07-1.29; P = 6.45x10(-9)). Associations of these 2 loci plus the previously identified loci CLU and PICALM with AD were confirmed in the Spanish sample (P < .05). However, although CLU and PICALM were confirmed to be associated with AD in this independent sample, they did not improve the ability of a model that included age, sex, and APOE to predict incident AD (improvement in area under the receiver operating characteristic curve from 0.847 to 0.849 in the Rotterdam Study and 0.702 to 0.705 in the Cardiovascular Health Study). CONCLUSIONS: Two genetic loci for AD were found for the first time to reach genome-wide statistical significance. These findings were replicated in an independent population. Two recently reported associations were also confirmed. These loci did not improve AD risk prediction. While not clinically useful, they may implicate biological pathways useful for future research.
Keywords: Age of Onset; Aged; Alzheimer Disease; Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Odds Ratio; Polymorphism, Single Nucleotide

Genome-wide association analysis identifies multiple loci related to resting heart rate. - Eijgelsheim, Mark; Newton-Cheh, Christopher; Sotoodehnia, Nona; de Bakker, Paul I W; Müller, Martina; Morrison, Alanna C; Smith, Albert V; Isaacs, Aaron; Sanna, Serena; Dörr, Marcus; Navarro, Pau; Fuchsberger, Christian; et al. (Hum Mol Genet, 2010)
Higher resting heart rate is associated with increased cardiovascular disease and mortality risk. Though heritable factors play a substantial role in population variation, little is known about specific genetic determinants. This knowledge can impact clinical care by identifying novel factors that influence pathologic heart rate states, modulate heart rate through cardiac structure and function or by improving our understanding of the physiology of heart rate regulation. To identify common genetic variants associated with heart rate, we performed a meta-analysis of 15 genome-wide association studies (GWAS), including 38,991 subjects of European ancestry, estimating the association between age-, sex- and body mass-adjusted RR interval (inverse heart rate) and approximately 2.5 million markers. Results with P < 5 × 10(-8) were considered genome-wide significant. We constructed regression models with multiple markers to assess whether results at less stringent thresholds were likely to be truly associated with RR interval. We identified six novel associations with resting heart rate at six loci: 6q22 near GJA1; 14q12 near MYH7; 12p12 near SOX5, c12orf67, BCAT1, LRMP and CASC1; 6q22 near SLC35F1, PLN and c6orf204; 7q22 near SLC12A9 and UfSp1; and 11q12 near FADS1. Associations at 6q22 400 kb away from GJA1, at 14q12 MYH6 and at 1q32 near CD34 identified in previously published GWAS were confirmed. In aggregate, these variants explain approximately 0.7% of RR interval variance. A multivariant regression model including 20 variants with P < 10(-5) increased the explained variance to 1.6%, suggesting that some loci falling short of genome-wide significance are likely truly associated. Future research is warranted to elucidate underlying mechanisms that may impact clinical care.
Keywords: Adult; Aged; Base Pairing; Cohort Studies; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Heart Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Rest

Genome-wide association identifies OBFC1 as a locus involved in human leukocyte telomere biology. - Levy, Daniel; Neuhausen, Susan L; Hunt, Steven C; Kimura, Masayuki; Hwang, Shih-Jen; Chen, Wei; Bis, Joshua C; Fitzpatrick, Annette L; Smith, Erin; Johnson, Andrew D; Gardner, Jeffrey P; Srinivasan, Sathanur R; et al. (Proc Natl Acad Sci U S A, 2010)
Telomeres are engaged in a host of cellular functions, and their length is regulated by multiple genes. Telomere shortening, in the course of somatic cell replication, ultimately leads to replicative senescence. In humans, rare mutations in genes that regulate telomere length have been identified in monogenic diseases such as dyskeratosis congenita and idiopathic pulmonary fibrosis, which are associated with shortened leukocyte telomere length (LTL) and increased risk for aplastic anemia. Shortened LTL is observed in a host of aging-related complex genetic diseases and is associated with diminished survival in the elderly. We report results of a genome-wide association study of LTL in a consortium of four observational studies (n = 3,417 participants with LTL and genome-wide genotyping). SNPs in the regions of the oligonucleotide/oligosaccharide-binding folds containing one gene (OBFC1; rs4387287; P = 3.9 x 10(-9)) and chemokine (C-X-C motif) receptor 4 gene (CXCR4; rs4452212; P = 2.9 x 10(-8)) were associated with LTL at a genome-wide significance level (P < 5 x 10(-8)). We attempted replication of the top SNPs at these loci through de novo genotyping of 1,893 additional individuals and in silico lookup in another observational study (n = 2,876), and we confirmed the association findings for OBFC1 but not CXCR4. In addition, we confirmed the telomerase RNA component (TERC) as a gene associated with LTL (P = 1.1 x 10(-5)). The identification of OBFC1 through genome-wide association as a locus for interindividual variation in LTL in the general population advances the understanding of telomere biology in humans and may provide insights into aging-related disorders linked to altered LTL dynamics.
Keywords: Cohort Studies; Genome-Wide Association Study; Genotype; Humans; Leukocytes; Polymorphism, Single Nucleotide; Receptors, CXCR4; Telomere; Telomere-Binding Proteins

Genome-wide association study identifies GPC5 as a novel genetic locus protective against sudden cardiac arrest. - Arking, Dan E; Reinier, Kyndaron; Post, Wendy; Jui, Jonathan; Hilton, Gina; O'Connor, Ashley; Prineas, Ronald J; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Rea, Thomas; Sotoodehnia, Nona; et al. (PLoS One, 2010)
BACKGROUND: Existing studies indicate a significant genetic component for sudden cardiac arrest (SCA) and genome-wide association studies (GWAS) provide an unbiased approach for identification of novel genes. We performed a GWAS to identify genetic determinants of SCA. METHODOLOGY/PRINCIPAL FINDINGS: We used a case-control design within the ongoing Oregon Sudden Unexpected Death Study (Oregon-SUDS). Cases (n = 424) were SCAs with coronary artery disease (CAD) among residents of Portland, OR (2002-07, population approximately 1,000,000) and controls (n = 226) were residents with CAD, but no history of SCA. All subjects were of White-European ancestry and GWAS was performed using Affymetrix 500K/5.0 and 6.0 arrays. High signal markers were genotyped in SCA cases (n = 521) identified from the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS) (combined n = 19,611). No SNPs reached genome-wide significance (p<5x10(-8)). SNPs at 6 loci were prioritized for follow-up primarily based on significance of p<10(-4) and proximity to a known gene (CSMD2, GPR37L1, LIN9, B4GALNT3, GPC5, and ZNF592). The minor allele of GPC5 (GLYPICAN 5, rs3864180) was associated with a lower risk of SCA in Oregon-SUDS, an effect that was also observed in ARIC/CHS whites (p<0.05) and blacks (p<0.04). In a combined Cox proportional hazards model analysis that adjusted for race, the minor allele exhibited a hazard ratio of 0.85 (95% CI 0.74 to 0.98; p<0.01). CONCLUSIONS/SIGNIFICANCE: A novel genetic locus for SCA, GPC5, was identified from Oregon-SUDS and successfully validated in the ARIC and CHS cohorts. Three other members of the Glypican family have been previously implicated in human disease, including cardiac conditions. The mechanism of this specific association requires further study.
Keywords: Aged; Alleles; Case-Control Studies; Cohort Studies; Death, Sudden, Cardiac; Ethnic Groups; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glypicans; Heart Diseases; Humans; Male; Middle Aged; Models, Genetic; Oligonucleotide Array Sequence Analysis; Oregon; Polymorphism, Single Nucleotide

Genome-wide meta-analysis increases to 71 the number of confirmed Crohn's disease susceptibility loci. - Franke, Andre; McGovern, Dermot P B; Barrett, Jeffrey C; Wang, Kai; Radford-Smith, Graham L; Ahmad, Tariq; Lees, Charlie W; Balschun, Tobias; Lee, James; Roberts, Rebecca; Anderson, Carl A; Bis, Joshua C; et al. (Nat Genet, 2010)
We undertook a meta-analysis of six Crohn's disease genome-wide association studies (GWAS) comprising 6,333 affected individuals (cases) and 15,056 controls and followed up the top association signals in 15,694 cases, 14,026 controls and 414 parent-offspring trios. We identified 30 new susceptibility loci meeting genome-wide significance (P < 5 × 10⁻⁸). A series of in silico analyses highlighted particular genes within these loci and, together with manual curation, implicated functionally interesting candidate genes including SMAD3, ERAP2, IL10, IL2RA, TYK2, FUT2, DNMT3A, DENND1B, BACH2 and TAGAP. Combined with previously confirmed loci, these results identify 71 distinct loci with genome-wide significant evidence for association with Crohn's disease.
Keywords: Computational Biology; Crohn Disease; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Reproducibility of Results

Hundreds of variants clustered in genomic loci and biological pathways affect human height. - Lango Allen, Hana; Estrada, Karol; Lettre, Guillaume; Berndt, Sonja I; Weedon, Michael N; Rivadeneira, Fernando; Willer, Cristen J; Jackson, Anne U; Vedantam, Sailaja; Raychaudhuri, Soumya; Ferreira, Teresa; Wood, Andrew R; et al. (Nature, 2010)
Most common human traits and diseases have a polygenic pattern of inheritance: DNA sequence variants at many genetic loci influence the phenotype. Genome-wide association (GWA) studies have identified more than 600 variants associated with human traits, but these typically explain small fractions of phenotypic variation, raising questions about the use of further studies. Here, using 183,727 individuals, we show that hundreds of genetic variants, in at least 180 loci, influence adult height, a highly heritable and classic polygenic trait. The large number of loci reveals patterns with important implications for genetic studies of common human diseases and traits. First, the 180 loci are not random, but instead are enriched for genes that are connected in biological pathways (P = 0.016) and that underlie skeletal growth defects (P < 0.001). Second, the likely causal gene is often located near the most strongly associated variant: in 13 of 21 loci containing a known skeletal growth gene, that gene was closest to the associated variant. Third, at least 19 loci have multiple independently associated variants, suggesting that allelic heterogeneity is a frequent feature of polygenic traits, that comprehensive explorations of already-discovered loci should discover additional variants and that an appreciable fraction of associated loci may have been identified. Fourth, associated variants are enriched for likely functional effects on genes, being over-represented among variants that alter amino-acid structure of proteins and expression levels of nearby genes. Our data explain approximately 10% of the phenotypic variation in height, and we estimate that unidentified common variants of similar effect sizes would increase this figure to approximately 16% of phenotypic variation (approximately 20% of heritable variation). Although additional approaches are needed to dissect the genetic architecture of polygenic human traits fully, our findings indicate that GWA studies can identify large numbers of loci that implicate biologically relevant genes and pathways.
Keywords: Body Height; Chromosomes, Human, Pair 3; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Metabolic Networks and Pathways; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Interaction between fibrinogen and IL-6 genetic variants and associations with cardiovascular disease risk in the Cardiovascular Health Study. - Carty, Cara L; Heagerty, Patrick; Heckbert, Susan R; Jarvik, Gail P; Lange, Leslie A; Cushman, Mary; Tracy, Russell P; Reiner, Alexander P (Ann Hum Genet, 2010)
The inflammatory cytokine interleukin-6 (IL-6) is a main regulator of fibrinogen synthesis, though its interaction with fibrinogen genes (FGA, FGB, FGG) and subsequent impact on cardiovascular disease (CVD) risk is not well-studied. We investigated joint associations of fibrinogen and IL6 tagSNPs with fibrinogen concentrations, carotid intima-media thickness, and myocardial infarction or ischemic stroke in 3900 European-American Cardiovascular Health Study participants. To identify combinations of genetic main effects and interactions associated with outcomes, we used logic regression. We also evaluated whether the relationship between fibrinogen SNPs and fibrinogen level varied by IL-6 level using linear regression models with multiplicative interaction terms. Combinations of fibrinogen and IL6 SNPs were significantly associated with fibrinogen level (p < 0.005), but not with other outcomes. Fibrinogen levels were higher in individuals having FGB1437 (rs1800790) and lacking FGA6534 (rs6050) minor alleles; these SNPs interacted with IL6 rs1800796 to influence fibrinogen level. Marginally significant (p= 0.03) interactions between IL-6 level and FGA and FGG promoter SNPs associated with fibrinogen levels were detected. We identified potential gene-gene interactions influencing fibrinogen levels. Although IL-6 responsive binding sites are present in fibrinogen gene promoter regions, we did not find strong evidence of interaction between fibrinogen SNPs and IL6 SNPs or levels influencing CVD.
Keywords: Aged; Cardiovascular Diseases; Carotid Arteries; Female; Fibrinogen; Genetic Predisposition to Disease; Genetic Variation; Humans; Interleukin-6; Male; Models, Biological; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk; Stroke

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; European Continental Ancestry Group; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide

Large-scale genomic studies reveal central role of ABO in sP-selectin and sICAM-1 levels. - Barbalic, Maja; Dupuis, Josée; Dehghan, Abbas; Bis, Joshua C; Hoogeveen, Ron C; Schnabel, Renate B; Nambi, Vijay; Bretler, Monique; Smith, Nicholas L; Peters, Annette; Lu, Chen; Tracy, Russell P; et al. (Hum Mol Genet, 2010)
P-selectin and intercellular adhesion molecule-1 (ICAM-1) participate in inflammatory processes by promoting adhesion of leukocytes to vascular wall endothelium. Their soluble levels have been associated with adverse cardiovascular events. To identify loci affecting soluble levels of P-selectin (sP-selectin) and ICAM-1 (sICAM-1), we performed a genome-wide association study in a sample of 4115 (sP-selectin) and 9813 (sICAM-1) individuals of European ancestry as a part of The Cohorts for Heart and Aging Research in Genome Epidemiology consortium. The most significant SNP association for sP-selectin was within the SELP gene (rs6136, P = 4.05 x 10(-61)) and for sICAM-1 levels within the ICAM-1 gene (rs3093030, P = 3.53 x 10(-23)). Both sP-selectin and sICAM-1 were associated with ABO gene variants (rs579459, P = 1.86 x 10(-41) and rs649129, P = 1.22 x 10(-15), respectively) and in both cases the observed associations could be accounted for by the A1 allele of the ABO blood group. The absence of an association between ABO blood group and platelet-bound P-selectin levels in an independent subsample (N = 1088) from the ARIC study, suggests that the ABO blood group may influence cleavage of the P-selectin protein from the cell surface or clearance from the circulation, rather than its production and cellular presentation. These results provide new insights into adhesion molecule biology.
Keywords: ABO Blood-Group System; Blood Platelets; Enzyme-Linked Immunosorbent Assay; European Continental Ancestry Group; Fluorescence; Genome-Wide Association Study; Humans; Intercellular Adhesion Molecule-1; P-Selectin

Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) and risk of cardiovascular disease in older adults: results from the Cardiovascular Health Study. - Jenny, Nancy Swords; Solomon, Cam; Cushman, Mary; Tracy, Russell P; Nelson, Jeanenne J; Psaty, Bruce M; Furberg, Curt D (Atherosclerosis, 2010)
OBJECTIVE: To examine associations between lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) antigen level (mass) and enzymatic activity (activity) and cardiovascular disease (CVD) in older adults. METHODS: We examined associations of Lp-PLA(2) mass and activity with incident myocardial infarction (MI; n=508), stroke (n=565) and CVD death (n=665) using Cox regressions adjusted for age, sex, ethnicity and CVD risk factors in 3949 older adults, aged > or =65 years at baseline, from the Cardiovascular Health Study (CHS). RESULTS: Lp-PLA(2) was associated with incident CVD events in these older adults. Hazard ratios (95% confidence intervals) for highest versus lowest tertiles of Lp-PLA(2) mass were 1.49 (1.19-1.85) for MI, 1.21 (0.98-1.49) for stroke and 1.11 (0.92-1.33) for CVD death. The highest tertile of Lp-PLA(2) activity was associated with MI (1.36; 1.09-1.70) and CVD death (1.23; 1.02-1.50). Combined Lp-PLA(2) tertile 3 and CRP>3mg/l, compared to Lp-PLA(2) tertile 1 and CRP<1mg/l, was associated with MI (2.29; 1.49-3.52) for Lp-PLA(2) mass and MI (1.66; 1.10-2.51) and CVD death (1.57; 1.08-2.26) for activity. For MI, both mass and activity added excess risk to elevated CRP alone ( approximately 20% excess risk) and activity added excess risk for CVD death ( approximately 12%). CONCLUSION: Lp-PLA(2) mass and activity were associated with incident CVD events in older adults in CHS. Lp-PLA(2) and CRP were independent and additive in prediction of events. While associations were modest, these results support further exploration of Lp-PLA(2) to identify older individuals at risk for CVD.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; C-Reactive Protein; Cardiovascular Diseases; Female; Humans; Myocardial Infarction; Population Surveillance; Prospective Studies; Risk; Stroke

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

New loci associated with kidney function and chronic kidney disease. - Köttgen, Anna; Pattaro, Cristian; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Glazer, Nicole L; Parsa, Afshin; Gao, Xiaoyi; Yang, Qiong; Smith, Albert V; O'Connell, Jeffrey R; Li, Man; et al. (Nat Genet, 2010)
Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 individuals of European ancestry from 20 predominantly population-based studies in order to identify new susceptibility loci for reduced renal function as estimated by serum creatinine (eGFRcrea), serum cystatin c (eGFRcys) and CKD (eGFRcrea < 60 ml/min/1.73 m(2); n = 5,807 individuals with CKD (cases)). Follow-up of the 23 new genome-wide-significant loci (P < 5 x 10(-8)) in 22,982 replication samples identified 13 new loci affecting renal function and CKD (in or near LASS2, GCKR, ALMS1, TFDP2, DAB2, SLC34A1, VEGFA, PRKAG2, PIP5K1B, ATXN2, DACH1, UBE2Q2 and SLC7A9) and 7 loci suspected to affect creatinine production and secretion (CPS1, SLC22A2, TMEM60, WDR37, SLC6A13, WDR72 and BCAS3). These results further our understanding of the biologic mechanisms of kidney function by identifying loci that potentially influence nephrogenesis, podocyte function, angiogenesis, solute transport and metabolic functions of the kidney.
Keywords: Cohort Studies; Creatinine; Cystatin C; Diet; Europe; Genetic Markers; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Models, Genetic; Risk Factors

Novel associations of multiple genetic loci with plasma levels of factor VII, factor VIII, and von Willebrand factor: The CHARGE (Cohorts for Heart and Aging Research in Genome Epidemiology) Consortium. - Smith, Nicholas L; Chen, Ming-Huei; Dehghan, Abbas; Strachan, David P; Basu, Saonli; Soranzo, Nicole; Hayward, Caroline; Rudan, Igor; Sabater-Lleal, Maria; Bis, Joshua C; de Maat, Moniek P M; Rumley, Ann; et al. (Circulation, 2010)
BACKGROUND: Plasma levels of coagulation factors VII (FVII), VIII (FVIII), and von Willebrand factor (vWF) influence risk of hemorrhage and thrombosis. We conducted genome-wide association studies to identify new loci associated with plasma levels. METHODS AND RESULTS: The setting of the study included 5 community-based studies for discovery comprising 23 608 European-ancestry participants: Atherosclerosis Risk In Communities Study, Cardiovascular Health Study, British 1958 Birth Cohort, Framingham Heart Study, and Rotterdam Study. All subjects had genome-wide single-nucleotide polymorphism (SNP) scans and at least 1 phenotype measured: FVII activity/antigen, FVIII activity, and vWF antigen. Each study used its genotype data to impute to HapMap SNPs and independently conducted association analyses of hemostasis measures using an additive genetic model. Study findings were combined by meta-analysis. Replication was conducted in 7604 participants not in the discovery cohort. For FVII, 305 SNPs exceeded the genome-wide significance threshold of 5.0x10(-8) and comprised 5 loci on 5 chromosomes: 2p23 (smallest P value 6.2x10(-24)), 4q25 (3.6x10(-12)), 11q12 (2.0x10(-10)), 13q34 (9.0x10(-259)), and 20q11.2 (5.7x10(-37)). Loci were within or near genes, including 4 new candidate genes and F7 (13q34). For vWF, 400 SNPs exceeded the threshold and marked 8 loci on 6 chromosomes: 6q24 (1.2x10(-22)), 8p21 (1.3x10(-16)), 9q34 (<5.0x10(-324)), 12p13 (1.7x10(-32)), 12q23 (7.3x10(-10)), 12q24.3 (3.8x10(-11)), 14q32 (2.3x10(-10)), and 19p13.2 (1.3x10(-9)). All loci were within genes, including 6 new candidate genes, as well as ABO (9q34) and VWF (12p13). For FVIII, 5 loci were identified and overlapped vWF findings. Nine of the 10 new findings were replicated. CONCLUSIONS: New genetic associations were discovered outside previously known biological pathways and may point to novel prevention and treatment targets of hemostasis disorders.
Keywords: Adult; Factor VII; Factor VIII; Female; Genome-Wide Association Study; Hemostasis; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Thrombosis; von Willebrand Factor

Obesity is linked with lower brain volume in 700 AD and MCI patients. - Ho, April J; Raji, Cyrus A; Becker, James T; Lopez, Oscar L; Kuller, Lewis H; Hua, Xue; Lee, Suh; Hibar, Derrek; Dinov, Ivo D; Stein, Jason L; Jack, Clifford R; Weiner, Michael W; et al. (Neurobiol Aging, 2010)
Obesity is associated with lower brain volumes in cognitively normal elderly subjects, but no study has yet investigated the effects of obesity on brain structure in patients with mild cognitive impairment (MCI) or Alzheimer's disease (AD). To determine if higher body mass index (BMI) is associated with brain volume deficits in cognitively impaired elderly subjects, we analyzed brain magnetic resonance imaging (MRI) scans of 700 MCI or AD patients from 2 different cohorts: the Alzheimer's Disease Neuroimaging Initiative (ADNI) and the Cardiovascular Health Study-Cognition Study (CHS-CS). Tensor-based morphometry (TBM) was used to create 3-dimensional maps of regional tissue excess or deficits in subjects with MCI (ADNI, n = 399; CHS-CS, n = 77) and AD (ADNI, n = 188; CHS, n = 36). In both AD and MCI groups, higher body mass index was associated with brain volume deficits in frontal, temporal, parietal, and occipital lobes; the atrophic pattern was consistent in both ADNI and CHS populations. Cardiovascular risk factors, especially obesity, should be considered as influencing brain structure in those already afflicted by cognitive impairment and dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Body Mass Index; Brain; Cognition Disorders; Cohort Studies; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Obesity; Organ Size; Prospective Studies; Risk Factors

Physical activity and years of healthy life in older adults: results from the cardiovascular health study. - Hirsch, Calvin H; Diehr, Paula; Newman, Anne B; Gerrior, Shirley A; Pratt, Charlotte; Lebowitz, Michael D; Jackson, Sharon A (J Aging Phys Act, 2010)
Little is known about how many years of life and disability-free years seniors can gain through exercise. Using data from the Cardiovascular Health Study, the authors estimated the extra years of life and self-reported healthy life (over 11 years) and years without impairment in activities of daily living (over 6 years) associated with quintiles of physical activity (PA) in older adults from different age groups. They estimated PA from the Minnesota Leisure Time Activities Questionnaire. Multivariable linear regression adjusted for health-related covariates. The relative gains in survival and years of healthy life (YHL) generally were proportionate to the amount of PA, greater among those 75+, and higher in men. Compared with being sedentary, the most active men 75+ had 1.49 more YHL (95% CI: 0.79, 2.19), and the most active women 75+ had 1.06 more YHL (95% CI: 0.44, 1.68). Seniors over age 74 experience the largest relative gains in survival and healthy life from physical activity.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Exercise; Female; Health Behavior; Health Status; Humans; Leisure Activities; Life Style; Male; Quality-Adjusted Life Years; Sex Factors

Post hoc Parkinson's disease: identifying an uncommon disease in the Cardiovascular Health Study. - Ton, T G; Jain, S; Boudreau, R; Thacker, E L; Strotmeyer, E S; Newman, A B; Longstreth, W T; Checkoway, H (Neuroepidemiology, 2010)
BACKGROUND: Although ongoing cohort studies offer a unique opportunity to apply existing information collected prospectively to further the scientific understanding of Parkinson's disease (PD), they typically have limited information for clinical diagnosis. METHODS: We used combinations of self-report, International Classification of Diseases - 9th edition codes and antiparkinsonian medications to identify PD in the Cardiovascular Health Study. To determine whether the expected inverse association between smoking and PD is evident using our outcome definitions, we assessed baseline smoking characteristics for various definitions of PD. RESULTS: We identified 60 cases with prevalent PD (1.0%; 95% confidence interval, CI = 0.8-1.3%) and 154 with incident PD by year 14. Clear associations were observed for current smokers (odds ratio, OR = 0.50; 95% CI = 0.26-0.95) and for those who smoked ≥50 pack-years (OR = 0.53; 95% CI = 0.29-0.96). Estimates for smoking were similar when ≥2 data sources were required. Estimates for self-report alone were attenuated towards null. CONCLUSIONS: Using multiple data sources to identify PD represents an alternative method of outcome identification in a cohort that would otherwise not be possible for PD research. Ongoing cohort studies can provide settings in which rapid replication and explorations of new hypotheses for PD are possible.
Keywords: Aged; Aged, 80 and over; Cardiovascular System; Cohort Studies; Female; Health Status; Humans; Incidence; Male; Odds Ratio; Parkinson Disease; Prevalence; Prospective Studies; Risk Factors; Smoking; Surveys and Questionnaires; United States

Study of the relationship between the interleukin-6 gene and obstructive sleep apnea. - Larkin, Emma K; Patel, Sanjay R; Zhu, Xiaofeng; Tracy, Russell P; Jenny, Nancy S; Reiner, Alex P; Walston, Jeremy; Redline, Susan (Clin Transl Sci, 2010)
Keywords: Adult; African Americans; Alleles; Female; Humans; Interleukin-6; Male; Middle Aged; Polymorphism, Single Nucleotide; Sleep Apnea, Obstructive

Association of genetic variants and incident coronary heart disease in multiethnic cohorts: the PAGE study. - Franceschini, Nora; Carty, Cara; Bůzková, Petra; Reiner, Alex P; Garrett, Tiana; Lin, Yi; Vöckler, Jens-S; Hindorff, Lucia A; Cole, Shelley A; Boerwinkle, Eric; Lin, Dan-Yu; Bookman, Ebony; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: Genome-wide association studies identified several single nucleotide polymorphisms (SNP) associated with prevalent coronary heart disease (CHD), but less is known of associations with incident CHD. The association of 13 published CHD SNPs was examined in 5 ancestry groups of 4 large US prospective cohorts. METHODS AND RESULTS: The analyses included incident coronary events over an average 9.1 to 15.7 follow-up person-years in up to 26 617 white individuals (6626 events), 8018 black individuals (914 events), 1903 Hispanic individuals (113 events), 3669 American Indian individuals (595 events), and 885 Asian/Pacific Islander individuals (66 events). We used Cox proportional hazards models (with additive mode of inheritance) adjusted for age, sex, and ancestry (as needed). Nine loci were statistically associated with incident CHD events in white participants: 9p21 (rs10757278; P=4.7 × 10(-41)), 16q23.1 (rs2549513; P=0.0004), 6p24.1 (rs499818; P=0.0002), 2q36.3 (rs2943634; P=6.7 × 10(-6)), MTHFD1L (rs6922269, P=5.1 × 10(-10)), APOE (rs429358; P=2.7×10(-18)), ZNF627 (rs4804611; P=5.0 × 10(-8)), CXCL12 (rs501120; P=1.4 × 10(-6)) and LPL (rs268; P=2.7 × 10(-17)). The 9p21 region showed significant between-study heterogeneity, with larger effects in individuals age 55 years or younger and in women. Inclusion of coronary revascularization procedures among the incident CHD events introduced heterogeneity. The SNPs were not associated with CHD in black participants, and associations varied in other US minorities. CONCLUSIONS: Prospective analyses of white participants replicated several reported cross-sectional CHD-SNP associations.
Keywords: Aged; Aged, 80 and over; Continental Population Groups; Coronary Disease; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Association of genetic variation with systolic and diastolic blood pressure among African Americans: the Candidate Gene Association Resource study. - Fox, Ervin R; Young, J Hunter; Li, Yali; Dreisbach, Albert W; Keating, Brendan J; Musani, Solomon K; Liu, Kiang; Morrison, Alanna C; Ganesh, Santhi; Kutlar, Abdullah; Ramachandran, Vasan S; Polak, Josef F; et al. (Hum Mol Genet, 2011)
The prevalence of hypertension in African Americans (AAs) is higher than in other US groups; yet, few have performed genome-wide association studies (GWASs) in AA. Among people of European descent, GWASs have identified genetic variants at 13 loci that are associated with blood pressure. It is unknown if these variants confer susceptibility in people of African ancestry. Here, we examined genome-wide and candidate gene associations with systolic blood pressure (SBP) and diastolic blood pressure (DBP) using the Candidate Gene Association Resource (CARe) consortium consisting of 8591 AAs. Genotypes included genome-wide single-nucleotide polymorphism (SNP) data utilizing the Affymetrix 6.0 array with imputation to 2.5 million HapMap SNPs and candidate gene SNP data utilizing a 50K cardiovascular gene-centric array (ITMAT-Broad-CARe [IBC] array). For Affymetrix data, the strongest signal for DBP was rs10474346 (P= 3.6 × 10(-8)) located near GPR98 and ARRDC3. For SBP, the strongest signal was rs2258119 in C21orf91 (P= 4.7 × 10(-8)). The top IBC association for SBP was rs2012318 (P= 6.4 × 10(-6)) near SLC25A42 and for DBP was rs2523586 (P= 1.3 × 10(-6)) near HLA-B. None of the top variants replicated in additional AA (n = 11 882) or European-American (n = 69 899) cohorts. We replicated previously reported European-American blood pressure SNPs in our AA samples (SH2B3, P= 0.009; TBX3-TBX5, P= 0.03; and CSK-ULK3, P= 0.0004). These genetic loci represent the best evidence of genetic influences on SBP and DBP in AAs to date. More broadly, this work supports that notion that blood pressure among AAs is a trait with genetic underpinnings but also with significant complexity.
Keywords: Adult; African Americans; Aged; Blood Pressure; Cohort Studies; Diastole; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

Association of genomic loci from a cardiovascular gene SNP array with fibrinogen levels in European Americans and African-Americans from six cohort studies: the Candidate Gene Association Resource (CARe). - Wassel, Christina L; Lange, Leslie A; Keating, Brendan J; Taylor, Kira C; Johnson, Andrew D; Palmer, Cameron; Ho, Lindsey A; Smith, Nicholas L; Lange, Ethan M; Li, Yun; Yang, Qiong; Delaney, Joseph A; et al. (Blood, 2011)
Several common genomic loci, involving various immunity- and metabolism-related genes, have been associated with plasma fibrinogen in European Americans (EAs). The genetic determinants of fibrinogen in African Americans (AAs) are poorly characterized. Using a vascular gene-centric array in 23,634 EA and 6657 AA participants from 6 studies comprising the Candidate Gene Association Resource project, we examined the association of 47,539 common and lower frequency variants with fibrinogen concentration. We identified a rare Pro265Leu variant in FGB (rs6054) associated with lower fibrinogen. Common fibrinogen gene single nucleotide polymorphisms (FGB rs1800787 and FGG rs2066861) significantly associated with fibrinogen in EAs were prevalent in AAs and showed consistent associations. Several fibrinogen locus single nucleotide polymorphism associated with lower fibrinogen were exclusive to AAs; these include a newly reported association with FGA rs10050257. For IL6R, IL1RN, and NLRP3 inflammatory gene loci, associations with fibrinogen were concordant between EAs and AAs, but not at other loci (CPS1, PCCB, and SCL22A5-IRF1). The association of FGG rs2066861 with fibrinogen differed according to assay type used to measure fibrinogen. Further characterization of common and lower-frequency genetic variants that contribute to interpopulation differences in fibrinogen phenotype may help refine our understanding of the contribution of hemostasis and inflammation to atherothrombotic risk.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Association of hypertension drug target genes with blood pressure and hypertension in 86,588 individuals. - Johnson, Andrew D; Newton-Cheh, Christopher; Chasman, Daniel I; Ehret, Georg B; Johnson, Toby; Rose, Lynda; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Gudnason, Vilmundur; Larson, Martin G; Chakravarti, Aravinda; et al. (Hypertension, 2011)
We previously conducted genome-wide association meta-analysis of systolic blood pressure, diastolic blood pressure, and hypertension in 29,136 people from 6 cohort studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Here we examine associations of these traits with 30 gene regions encoding known antihypertensive drug targets. We find nominal evidence of association of ADRB1, ADRB2, AGT, CACNA1A, CACNA1C, and SLC12A3 polymorphisms with 1 or more BP traits in the Cohorts for Heart and Aging Research in Genomic Epidemiology genome-wide association meta-analysis. We attempted replication of the top meta-analysis single nucleotide polymorphisms for these genes in the Global BPgen Consortium (n=34,433) and the Women's Genome Health Study (n=23,019) and found significant results for rs1801253 in ADRB1 (Arg389Gly), with the Gly allele associated with a lower mean systolic blood pressure (β: 0.57 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=4.7×10(-10)), diastolic blood pressure (β: 0.36 mm Hg; SE: 0.06 mm Hg; meta-analysis: P=9.5×10(-10)), and prevalence of hypertension (β: 0.06 mm Hg; SE: 0.02 mm Hg; meta-analysis: P=3.3×10(-4)). Variation in AGT (rs2004776) was associated with systolic blood pressure (β: 0.42 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=3.8×10(-6)), as well as diastolic blood pressure (P=5.0×10(-8)) and hypertension (P=3.7×10(-7)). A polymorphism in ACE (rs4305) showed modest replication of association with increased hypertension (β: 0.06 mm Hg; SE: 0.01 mm Hg; meta-analysis: P=3.0×10(-5)). Two loci, ADRB1 and AGT, contain single nucleotide polymorphisms that reached a genome-wide significance threshold in meta-analysis for the first time. Our findings suggest that these genes warrant further studies of their genetic effects on blood pressure, including pharmacogenetic interactions.
Keywords: Alleles; Angiotensinogen; Antihypertensive Agents; Blood Pressure; Female; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Male; Pharmacogenetics; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-1

Association of polymorphisms in the hepatocyte growth factor gene promoter with keratoconus. - Burdon, Kathryn P; Macgregor, Stuart; Bykhovskaya, Yelena; Javadiyan, Sharhbanou; Li, Xiaohui; Laurie, Kate J; Muszynska, Dorota; Lindsay, Richard; Lechner, Judith; Haritunians, Talin; Henders, Anjali K; Dash, Durga; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: Keratoconus is a progressive disorder of the cornea that can lead to severe visual impairment or blindness. Although several genomic regions have been linked to rare familial forms of keratoconus, no genes have yet been definitively identified for common forms of the disease. METHODS: Two genome-wide association scans were undertaken in parallel. The first used pooled DNA from an Australian cohort, followed by typing of top-ranked single-nucleotide polymorphisms (SNPs) in individual DNA samples. The second was conducted in individually genotyped patients, and controls from the USA. Tag SNPs around the hepatocyte growth factor (HGF) gene were typed in three additional replication cohorts. Serum levels of HGF protein in normal individuals were assessed with ELISA and correlated with genotype. RESULTS: The only SNP observed to be associated in both the pooled discovery and primary replication cohort was rs1014091, located upstream of the HGF gene. The nearby SNP rs3735520 was found to be associated in the individually typed discovery cohort (P = 6.1 × 10(-7)). Genotyping of tag SNPs around HGF revealed association at rs3735520 and rs17501108/rs1014091 in four of the five cohorts. Meta-analysis of all five datasets together yielded suggestive P values for rs3735520 (P = 9.9 × 10(-7)) and rs17501108 (P = 9.9 × 10(-5)). In addition, SNP rs3735520 was found to be associated with serum HGF level in normal individuals (P = 0.036). CONCLUSIONS: Taken together, these results implicate genetic variation at the HGF locus with keratoconus susceptibility.
Keywords: Adult; Aged; Chromosomes, Human, Pair 7; Corneal Topography; Enzyme-Linked Immunosorbent Assay; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Hepatocyte Growth Factor; Humans; Keratoconus; Middle Aged; Nucleic Acid Hybridization; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Tagged Sites

Association of serum phosphate levels with aortic valve sclerosis and annular calcification: the cardiovascular health study. - Linefsky, Jason P; O'Brien, Kevin D; Katz, Ronit; de Boer, Ian H; Barasch, Eddy; Jenny, Nancy S; Siscovick, David S; Kestenbaum, Bryan (J Am Coll Cardiol, 2011)
OBJECTIVES: This study was conducted to evaluate mineral metabolism markers as potential risk factors for calcific aortic valve disease. BACKGROUND: Mineral metabolism disturbances are common among older people and may contribute to cardiac valvular calcification. Associations of serum mineral metabolism markers with cardiac valvular calcification have not been evaluated in a well-characterized general population of older adults. METHODS: We measured serum levels of phosphate, calcium, parathyroid hormone, and 25-hydroxyvitamin D in 1,938 Cardiovascular Health Study participants who were free of clinical cardiovascular disease and who underwent echocardiographic measurements of aortic valve sclerosis (AVS), mitral annular calcification (MAC), and aortic annular calcification (AAC). We used logistic regression models to estimate associations of mineral metabolism markers with AVS, MAC, and AAC after adjustment for relevant confounding variables, including kidney function. RESULTS: The respective prevalences of AVS, MAC, and AAC were 54%, 39%, and 44%. Each 0.5 mg/dl higher serum phosphate concentration was associated with greater adjusted odds of AVS (odds ratio [OR]: 1.17, 95% confidence interval [CI]: 1.04 to 1.31, p = 0.01), MAC (OR: 1.12, 95% CI: 1.00 to 1.26, p = 0.05), and AAC (OR: 1.12, 95% CI: 0.99 to 1.25, p = 0.05). In contrast, serum calcium, parathyroid hormone, and 25-hydroxyvitamin D concentrations were not associated with aortic or mitral calcification. CONCLUSIONS: Higher serum phosphate levels within the normal range were associated with valvular and annular calcification in a community-based cohort of older adults. Phosphate may be a novel risk factor for calcific aortic valve disease and warrants further study.
Keywords: Aged; Aortic Valve; Calcinosis; Calcium; Female; Heart Valve Diseases; Humans; Male; Mitral Valve; Parathyroid Hormone; Phosphates; Risk Factors; Sclerosis; Vitamin D

A bivariate genome-wide approach to metabolic syndrome: STAMPEED consortium. - Kraja, Aldi T; Vaidya, Dhananjay; Pankow, James S; Goodarzi, Mark O; Assimes, Themistocles L; Kullo, Iftikhar J; Sovio, Ulla; Mathias, Rasika A; Sun, Yan V; Franceschini, Nora; Absher, Devin; Li, Guo; et al. (Diabetes, 2011)
OBJECTIVE The metabolic syndrome (MetS) is defined as concomitant disorders of lipid and glucose metabolism, central obesity, and high blood pressure, with an increased risk of type 2 diabetes and cardiovascular disease. This study tests whether common genetic variants with pleiotropic effects account for some of the correlated architecture among five metabolic phenotypes that define MetS. RESEARCH DESIGN AND METHODS Seven studies of the STAMPEED consortium, comprising 22,161 participants of European ancestry, underwent genome-wide association analyses of metabolic traits using a panel of ∼2.5 million imputed single nucleotide polymorphisms (SNPs). Phenotypes were defined by the National Cholesterol Education Program (NCEP) criteria for MetS in pairwise combinations. Individuals exceeding the NCEP thresholds for both traits of a pair were considered affected. RESULTS Twenty-nine common variants were associated with MetS or a pair of traits. Variants in the genes LPL, CETP, APOA5 (and its cluster), GCKR (and its cluster), LIPC, TRIB1, LOC100128354/MTNR1B, ABCB11, and LOC100129150 were further tested for their association with individual qualitative and quantitative traits. None of the 16 top SNPs (one per gene) associated simultaneously with more than two individual traits. Of them 11 variants showed nominal associations with MetS per se. The effects of 16 top SNPs on the quantitative traits were relatively small, together explaining from ∼9% of the variance in triglycerides, 5.8% of high-density lipoprotein cholesterol, 3.6% of fasting glucose, and 1.4% of systolic blood pressure. CONCLUSIONS Qualitative and quantitative pleiotropic tests on pairs of traits indicate that a small portion of the covariation in these traits can be explained by the reported common genetic variants.
Keywords: Adult; Aged; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Meta-Analysis as Topic; Metabolic Syndrome; Middle Aged; Phenotype; Polymorphism, Single Nucleotide

Candidate gene association study for diabetic retinopathy in persons with type 2 diabetes: the Candidate gene Association Resource (CARe). - Sobrin, Lucia; Green, Todd; Sim, Xueling; Jensen, Richard A; Tai, E Shyong; Tay, Wan Ting; Wang, Jie Jin; Mitchell, Paul; Sandholm, Niina; Liu, Yiyuan; Hietala, Kustaa; Iyengar, Sudha K; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: To investigate whether variants in cardiovascular candidate genes, some of which have been previously associated with type 2 diabetes (T2D), diabetic retinopathy (DR), and diabetic nephropathy (DN), are associated with DR in the Candidate gene Association Resource (CARe). METHODS: Persons with T2D who were enrolled in the study (n = 2691) had fundus photography and genotyping of single nucleotide polymorphisms (SNPs) in 2000 candidate genes. Two case definitions were investigated: Early Treatment Diabetic Retinopathy Study (ETDRS) grades ≥ 14 and ≥ 30. The χ² analyses for each CARe cohort were combined by Cochran-Mantel-Haenszel (CMH) pooling of odds ratios (ORs) and corrected for multiple hypothesis testing. Logistic regression was performed with adjustment for other DR risk factors. Results from replication in independent cohorts were analyzed with CMH meta-analysis methods. RESULTS: Among 39 genes previously associated with DR, DN, or T2D, three SNPs in P-selectin (SELP) were associated with DR. The strongest association was to rs6128 (OR = 0.43, P = 0.0001, after Bonferroni correction). These associations remained significant after adjustment for DR risk factors. Among other genes examined, several variants were associated with DR with significant P values, including rs6856425 tagging α-l-iduronidase (IDUA) (P = 2.1 × 10(-5), after Bonferroni correction). However, replication in independent cohorts did not reveal study-wide significant effects. The P values after replication were 0.55 and 0.10 for rs6128 and rs6856425, respectively. CONCLUSIONS: Genes associated with DN, T2D, and vascular diseases do not appear to be consistently associated with DR. A few genetic variants associated with DR, particularly those in SELP and near IDUA, should be investigated in additional DR cohorts.
Keywords: Cardiovascular Diseases; Diabetes Mellitus, Type 2; Diabetic Nephropathies; Diabetic Retinopathy; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Iduronidase; Odds Ratio; P-Selectin; Polymorphism, Single Nucleotide; Risk Factors

Cerivastatin, genetic variants, and the risk of rhabdomyolysis. - Marciante, Kristin D; Durda, Jon P; Heckbert, Susan R; Lumley, Thomas; Rice, Ken; McKnight, Barbara; Totah, Rheem A; Tamraz, Bani; Kroetz, Deanna L; Fukushima, Hisayo; Kaspera, Rüdiger; Bis, Joshua C; et al. (Pharmacogenet Genomics, 2011)
OBJECTIVE: The withdrawal of cerivastatin involved an uncommon but serious adverse reaction, rhabdomyolysis. The bimodal response, rhabdomyolysis in a small proportion of users, points to genetic factors as a potential cause. We conducted a case-control study to evaluate genetic markers for cerivastatin-associated rhabdomyolysis. METHODS: This study had two components: a candidate gene study to evaluate variants in CYP2C8, UGT1A1, UGT1A3, and SLCO1B1; and a genome-wide association study to identify risk factors in other regions of the genome. A total of 185 rhabdomyolysis cases were frequency matched to statin-using controls from the Cardiovascular Health Study (n=374) and the Heart and Vascular Health Study (n=358). Validation relied on functional studies. RESULTS: Permutation test results suggested an association between cerivastatin-associated rhabdomyolysis and variants in SLCO1B1 (P=0.002), but not variants in CYP2C8 (P=0.073) or UGTs (P=0.523). An additional copy of the minor allele of SLCO1B1 rs4149056 (p.Val174Ala) was associated with the risk of rhabdomyolysis (odds ratio: 1.89; 95% confidence interval: 1.40-2.56). In transfected cells, this variant reduced cerivastatin transport by 40% compared with the reference transporter (P<0.001). The genome-wide association study identified an intronic variant (rs2819742) in the ryanodine receptor 2 gene (RYR2) as significant (P=1.74E-07). An additional copy of the minor allele of the RYR2 variant was associated with a reduced risk of rhabdomyolysis (odds ratio: 0.48; 95% confidence interval: 0.36-0.63). CONCLUSION: We identified modest genetic risk factors for an extreme response to cerivastatin. Disabling genetic variants in the candidate genes were not responsible for the bimodal response to cerivastatin.
Keywords: Adult; Aged; Aged, 80 and over; Aryl Hydrocarbon Hydroxylases; Case-Control Studies; Cytochrome P-450 CYP2C8; Female; Genetic Variation; Genome-Wide Association Study; Glucuronosyltransferase; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Organic Anion Transporters; Polymorphism, Single Nucleotide; Pyridines; Rhabdomyolysis; Risk; Ryanodine Receptor Calcium Release Channel; Solute Carrier Organic Anion Transporter Family Member 1b1

CUBN is a gene locus for albuminuria. - Böger, Carsten A; Chen, Ming-Huei; Tin, Adrienne; Olden, Matthias; Köttgen, Anna; de Boer, Ian H; Fuchsberger, Christian; O'Seaghdha, Conall M; Pattaro, Cristian; Teumer, Alexander; Liu, Ching-Ti; Glazer, Nicole L; et al. (J Am Soc Nephrol, 2011)
Identification of genetic risk factors for albuminuria may alter strategies for early prevention of CKD progression, particularly among patients with diabetes. Little is known about the influence of common genetic variants on albuminuria in both general and diabetic populations. We performed a meta-analysis of data from 63,153 individuals of European ancestry with genotype information from genome-wide association studies (CKDGen Consortium) and from a large candidate gene study (CARe Consortium) to identify susceptibility loci for the quantitative trait urinary albumin-to-creatinine ratio (UACR) and the clinical diagnosis microalbuminuria. We identified an association between a missense variant (I2984V) in the CUBN gene, which encodes cubilin, and both UACR (P = 1.1 × 10(-11)) and microalbuminuria (P = 0.001). We observed similar associations among 6981 African Americans in the CARe Consortium. The associations between this variant and both UACR and microalbuminuria were significant in individuals of European ancestry regardless of diabetes status. Finally, this variant associated with a 41% increased risk for the development of persistent microalbuminuria during 20 years of follow-up among 1304 participants with type 1 diabetes in the prospective DCCT/EDIC Study. In summary, we identified a missense CUBN variant that associates with levels of albuminuria in both the general population and in individuals with diabetes.
Keywords: African Continental Ancestry Group; Albuminuria; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Humans; Mutation, Missense; Receptors, Cell Surface

Enhanced statistical tests for GWAS in admixed populations: assessment using African Americans from CARe and a Breast Cancer Consortium. - Pasaniuc, Bogdan; Zaitlen, Noah; Lettre, Guillaume; Chen, Gary K; Tandon, Arti; Kao, W H Linda; Ruczinski, Ingo; Fornage, Myriam; Siscovick, David S; Zhu, Xiaofeng; Larkin, Emma; Lange, Leslie A; et al. (PLoS Genet, 2011)
While genome-wide association studies (GWAS) have primarily examined populations of European ancestry, more recent studies often involve additional populations, including admixed populations such as African Americans and Latinos. In admixed populations, linkage disequilibrium (LD) exists both at a fine scale in ancestral populations and at a coarse scale (admixture-LD) due to chromosomal segments of distinct ancestry. Disease association statistics in admixed populations have previously considered SNP association (LD mapping) or admixture association (mapping by admixture-LD), but not both. Here, we introduce a new statistical framework for combining SNP and admixture association in case-control studies, as well as methods for local ancestry-aware imputation. We illustrate the gain in statistical power achieved by these methods by analyzing data of 6,209 unrelated African Americans from the CARe project genotyped on the Affymetrix 6.0 chip, in conjunction with both simulated and real phenotypes, as well as by analyzing the FGFR2 locus using breast cancer GWAS data from 5,761 African-American women. We show that, at typed SNPs, our method yields an 8% increase in statistical power for finding disease risk loci compared to the power achieved by standard methods in case-control studies. At imputed SNPs, we observe an 11% increase in statistical power for mapping disease loci when our local ancestry-aware imputation framework and the new scoring statistic are jointly employed. Finally, we show that our method increases statistical power in regions harboring the causal SNP in the case when the causal SNP is untyped and cannot be imputed. Our methods and our publicly available software are broadly applicable to GWAS in admixed populations.
Keywords: African Americans; Algorithms; Breast Neoplasms; Chromosome Mapping; Coronary Disease; Diabetes Mellitus, Type 2; Female; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Receptor, Fibroblast Growth Factor, Type 2; Software

Genetic determinants of lipid traits in diverse populations from the population architecture using genomics and epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Taylor, Kira; Schumacher, Fredrick R; Hindorff, Lucia A; Ambite, José L; Anderson, Garnet; Best, Lyle G; Brown-Gentry, Kristin; Bůzková, Petra; Carlson, Christopher S; Cochran, Barbara; et al. (PLoS Genet, 2011)
For the past five years, genome-wide association studies (GWAS) have identified hundreds of common variants associated with human diseases and traits, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels. Approximately 95 loci associated with lipid levels have been identified primarily among populations of European ancestry. The Population Architecture using Genomics and Epidemiology (PAGE) study was established in 2008 to characterize GWAS-identified variants in diverse population-based studies. We genotyped 49 GWAS-identified SNPs associated with one or more lipid traits in at least two PAGE studies and across six racial/ethnic groups. We performed a meta-analysis testing for SNP associations with fasting HDL-C, LDL-C, and ln(TG) levels in self-identified European American (~20,000), African American (~9,000), American Indian (~6,000), Mexican American/Hispanic (~2,500), Japanese/East Asian (~690), and Pacific Islander/Native Hawaiian (~175) adults, regardless of lipid-lowering medication use. We replicated 55 of 60 (92%) SNP associations tested in European Americans at p<0.05. Despite sufficient power, we were unable to replicate ABCA1 rs4149268 and rs1883025, CETP rs1864163, and TTC39B rs471364 previously associated with HDL-C and MAFB rs6102059 previously associated with LDL-C. Based on significance (p<0.05) and consistent direction of effect, a majority of replicated genotype-phentoype associations for HDL-C, LDL-C, and ln(TG) in European Americans generalized to African Americans (48%, 61%, and 57%), American Indians (45%, 64%, and 77%), and Mexican Americans/Hispanics (57%, 56%, and 86%). Overall, 16 associations generalized across all three populations. For the associations that did not generalize, differences in effect sizes, allele frequencies, and linkage disequilibrium offer clues to the next generation of association studies for these traits.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Continental Population Groups; Female; Gene Frequency; Genetics, Population; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Lipid Metabolism; Lipoproteins, HDL; Lipoproteins, LDL; Male; Middle Aged; Molecular Epidemiology; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Triglycerides; Young Adult

Genetic loci associated with plasma phospholipid n-3 fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Lemaitre, Rozenn N; Tanaka, Toshiko; Tang, Weihong; Manichaikul, Ani; Foy, Millennia; Kabagambe, Edmond K; Nettleton, Jennifer A; King, Irena B; Weng, Lu-Chen; Bhattacharya, Sayanti; Bandinelli, Stefania; Bis, Joshua C; et al. (PLoS Genet, 2011)
Long-chain n-3 polyunsaturated fatty acids (PUFAs) can derive from diet or from α-linolenic acid (ALA) by elongation and desaturation. We investigated the association of common genetic variation with plasma phospholipid levels of the four major n-3 PUFAs by performing genome-wide association studies in five population-based cohorts comprising 8,866 subjects of European ancestry. Minor alleles of SNPs in FADS1 and FADS2 (desaturases) were associated with higher levels of ALA (p = 3 x 10⁻⁶⁴) and lower levels of eicosapentaenoic acid (EPA, p = 5 x 10⁻⁵⁸) and docosapentaenoic acid (DPA, p = 4 x 10⁻¹⁵⁴). Minor alleles of SNPs in ELOVL2 (elongase) were associated with higher EPA (p = 2 x 10⁻¹²) and DPA (p = 1 x 10⁻⁴³) and lower docosahexaenoic acid (DHA, p = 1 x 10⁻¹⁵). In addition to genes in the n-3 pathway, we identified a novel association of DPA with several SNPs in GCKR (glucokinase regulator, p = 1 x 10⁻⁸). We observed a weaker association between ALA and EPA among carriers of the minor allele of a representative SNP in FADS2 (rs1535), suggesting a lower rate of ALA-to-EPA conversion in these subjects. In samples of African, Chinese, and Hispanic ancestry, associations of n-3 PUFAs were similar with a representative SNP in FADS1 but less consistent with a representative SNP in ELOVL2. Our findings show that common variation in n-3 metabolic pathway genes and in GCKR influences plasma phospholipid levels of n-3 PUFAs in populations of European ancestry and, for FADS1, in other ancestries.
Keywords: Alleles; Continental Population Groups; Fatty Acids, Omega-3; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide

Genetic predictors of fibrin D-dimer levels in healthy adults. - Smith, Nicholas L; Huffman, Jennifer E; Strachan, David P; Huang, Jie; Dehghan, Abbas; Trompet, Stella; Lopez, Lorna M; Shin, So-Youn; Baumert, Jens; Vitart, Veronique; Bis, Joshua C; Wild, Sarah H; et al. (Circulation, 2011)
BACKGROUND: Fibrin fragment D-dimer, one of several peptides produced when crosslinked fibrin is degraded by plasmin, is the most widely used clinical marker of activated blood coagulation. To identity genetic loci influencing D-dimer levels, we performed the first large-scale, genome-wide association search. METHODS AND RESULTS: A genome-wide investigation of the genomic correlates of plasma D-dimer levels was conducted among 21 052 European-ancestry adults. Plasma levels of D-dimer were measured independently in each of 13 cohorts. Each study analyzed the association between ≈2.6 million genotyped and imputed variants across the 22 autosomal chromosomes and natural-log–transformed D-dimer levels using linear regression in additive genetic models adjusted for age and sex. Among all variants, 74 exceeded the genome-wide significance threshold and marked 3 regions. At 1p22, rs12029080 (P=6.4×10(-52)) was 46.0 kb upstream from F3, coagulation factor III (tissue factor). At 1q24, rs6687813 (P=2.4×10(-14)) was 79.7 kb downstream of F5, coagulation factor V. At 4q32, rs13109457 (P=2.9×10(-18)) was located between 2 fibrinogen genes: 10.4 kb downstream from FGG and 3.0 kb upstream from FGA. Variants were associated with a 0.099-, 0.096-, and 0.061-unit difference, respectively, in natural-log–transformed D-dimer and together accounted for 1.8% of the total variance. When adjusted for nonsynonymous substitutions in F5 and FGA loci known to be associated with D-dimer levels, there was no evidence of an additional association at either locus. CONCLUSIONS: Three genes were associated with fibrin D-dimer levels. Of these 3, the F3 association was the strongest, and has not been previously reported.
Keywords: Adult; Aged; Blood Coagulation; European Continental Ancestry Group; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Testing; Genome-Wide Association Study; Humans; Male; Middle Aged; Reference Values; Thromboplastin

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genetic variation near IRS1 associates with reduced adiposity and an impaired metabolic profile. - Kilpeläinen, Tuomas O; Zillikens, M Carola; Stančáková, Alena; Finucane, Francis M; Ried, Janina S; Langenberg, Claudia; Zhang, Weihua; Beckmann, Jacques S; Luan, Jian'an; Vandenput, Liesbeth; Styrkarsdottir, Unnur; Zhou, Yanhua; et al. (Nat Genet, 2011)
Genome-wide association studies have identified 32 loci influencing body mass index, but this measure does not distinguish lean from fat mass. To identify adiposity loci, we meta-analyzed associations between ∼2.5 million SNPs and body fat percentage from 36,626 individuals and followed up the 14 most significant (P < 10(-6)) independent loci in 39,576 individuals. We confirmed a previously established adiposity locus in FTO (P = 3 × 10(-26)) and identified two new loci associated with body fat percentage, one near IRS1 (P = 4 × 10(-11)) and one near SPRY2 (P = 3 × 10(-8)). Both loci contain genes with potential links to adipocyte physiology. Notably, the body-fat-decreasing allele near IRS1 is associated with decreased IRS1 expression and with an impaired metabolic profile, including an increased visceral to subcutaneous fat ratio, insulin resistance, dyslipidemia, risk of diabetes and coronary artery disease and decreased adiponectin levels. Our findings provide new insights into adiposity and insulin resistance.
Keywords: Adiponectin; Adiposity; Alleles; Body Fat Distribution; Body Mass Index; Body Weight; Female; Genetic Variation; Genome-Wide Association Study; Humans; Insulin Receptor Substrate Proteins; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Meta-Analysis as Topic; Metabolome; Obesity; Polymorphism, Single Nucleotide; Subcutaneous Fat

Genome-wide association and large-scale follow up identifies 16 new loci influencing lung function. - Soler Artigas, Maria; Loth, Daan W; Wain, Louise V; Gharib, Sina A; Obeidat, Ma'en; Tang, Wenbo; Zhai, Guangju; Zhao, Jing Hua; Smith, Albert Vernon; Huffman, Jennifer E; Albrecht, Eva; Jackson, Catherine M; et al. (Nat Genet, 2011)
Pulmonary function measures reflect respiratory health and are used in the diagnosis of chronic obstructive pulmonary disease. We tested genome-wide association with forced expiratory volume in 1 second and the ratio of forced expiratory volume in 1 second to forced vital capacity in 48,201 individuals of European ancestry with follow up of the top associations in up to an additional 46,411 individuals. We identified new regions showing association (combined P < 5 × 10(-8)) with pulmonary function in or near MFAP2, TGFB2, HDAC4, RARB, MECOM (also known as EVI1), SPATA9, ARMC2, NCR3, ZKSCAN3, CDC123, C10orf11, LRP1, CCDC38, MMP15, CFDP1 and KCNE2. Identification of these 16 new loci may provide insight into the molecular mechanisms regulating pulmonary function and into molecular targets for future therapy to alleviate reduced lung function.
Keywords: Child; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Identification of a sudden cardiac death susceptibility locus at 2q24.2 through genome-wide association in European ancestry individuals. - Arking, Dan E; Junttila, M Juhani; Goyette, Philippe; Huertas-Vazquez, Adriana; Eijgelsheim, Mark; Blom, Marieke T; Newton-Cheh, Christopher; Reinier, Kyndaron; Teodorescu, Carmen; Uy-Evanado, Audrey; Carter-Monroe, Naima; Kaikkonen, Kari S; et al. (PLoS Genet, 2011)
Sudden cardiac death (SCD) continues to be one of the leading causes of mortality worldwide, with an annual incidence estimated at 250,000-300,000 in the United States and with the vast majority occurring in the setting of coronary disease. We performed a genome-wide association meta-analysis in 1,283 SCD cases and >20,000 control individuals of European ancestry from 5 studies, with follow-up genotyping in up to 3,119 SCD cases and 11,146 controls from 11 European ancestry studies, and identify the BAZ2B locus as associated with SCD (P = 1.8×10(-10)). The risk allele, while ancestral, has a frequency of ~1.4%, suggesting strong negative selection and increases risk for SCD by 1.92-fold per allele (95% CI 1.57-2.34). We also tested the role of 49 SNPs previously implicated in modulating electrocardiographic traits (QRS, QT, and RR intervals). Consistent with epidemiological studies showing increased risk of SCD with prolonged QRS/QT intervals, the interval-prolonging alleles are in aggregate associated with increased risk for SCD (P = 0.006).
Keywords: Adult; Aged; Alleles; Chromosomes, Human, Pair 2; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Contraction; Polymorphism, Single Nucleotide

Kidney function decline in the elderly: impact of lipoprotein-associated phospholipase A(2). - Peralta, Carmen A; Katz, Ronit; Shlipak, Michael; Dubin, Ruth; DeBoer, Ian; Jenny, Nancy; Fitzpatrick, Annette; Koro, Carol; Kestenbaum, Bryan; Ix, Joachim; Sarnak, Mark; Cushman, Mary (Am J Nephrol, 2011)
BACKGROUND: Whether lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) levels are associated with kidney function decline has not been well studied. METHODS: We investigated associations of Lp-PLA(2) antigen and activity with kidney function decline and rapid decline over 5.7 years in the Cardiovascular Health Study (n = 4,359). We estimated kidney function by cystatin C (eGFRcys) in repeated measures, and defined rapid decline as ≥3 ml/min/1.73 m(2) per year. We stratified by baseline preserved GFR (≥60 ml/min/1.73 m(2)). RESULTS: Mean age was 72 ± 5 years. Average eGFRcys decline was -1.79 ml/min/1.73 m(2) (SD = 2.60) per year. Among persons with preserved GFR, compared to the lowest quartile of Lp-PLA(2) antigen, eGFRcys decline was faster among persons in the second, β -0.31 (95% CI -0.52, -0.10), third -0.19 (-0.41, 0.02) and fourth quartiles -0.26 (-0.48, -0.04) after full adjustment. Persons in the highest quartile of Lp-PLA(2) antigen had increased odds of rapid decline 1.34 (1.03, 1.75), compared to the lowest. There was no significant association between levels of Lp-PLA(2) activity and eGFRcys decline or rapid decline. Associations were not statistically significant among persons with low eGFR (<60 ml/min/1.73 m(2)) at baseline. CONCLUSION: Higher levels of Lp-PLA(2) antigen but not activity were significantly associated with faster rates of kidney function decline. These findings may suggest a novel vascular pathway for kidney disease progression.
Keywords: Aged; Cardiovascular Diseases; Creatinine; Cystatin C; Disease Progression; Female; Geriatrics; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Male; Middle Aged; Phospholipases A2; Risk Factors; Treatment Outcome

Leukocyte telomere length and mortality in the Cardiovascular Health Study. - Fitzpatrick, Annette L; Kronmal, Richard A; Kimura, Masayuki; Gardner, Jeffrey P; Psaty, Bruce M; Jenny, Nancy S; Tracy, Russell P; Hardikar, Sheetal; Aviv, Abraham (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Leukocyte telomere length (LTL) is related to diseases of aging, but studies of mortality have been inconsistent. METHODS: We evaluated LTL in relation to total mortality and specific cause of death in 1,136 participants of the Cardiovascular Health Study who provided blood samples in 1992-1993 and survived through 1997-1998. LTL was measured by Southern blots of the terminal restriction fragments. Cause of death was classified by a committee of physicians reviewing death certificates, medical records, and informant interviews. RESULTS: A total of 468 (41.2%) deaths occurred over 6.1 years of follow-up in participants with mean age of 73.9 years (SD 4.7), 65.4% female, and 14.8% African American. Although increased age and male gender were associated with shorter LTLs, African Americans had significantly longer LTLs independent of age and sex (p < .001). Adjusted for age, sex, and race, persons with the shortest quartile of LTL were 60% more likely to die during follow-up than those within the longest quartile (hazard ratio: 1.61, 95% confidence interval: 1.22-2.12, p = .001). The association remained after adjustment for cardiovascular disease risk factors. Evaluations of cause of death found LTL to be related to deaths due to an infectious disease etiology (hazard ratio: 2.80, 95% confidence interval: 1.32-5.94, p = .007), whereas a borderline association was found for cardiac deaths (hazard ratio: 1.82, 95% confidence interval: 0.95-3.49, p = .07) in adjusted models. Risk estimates for deaths due to cancer, dementia, and ischemic stroke were not significant. CONCLUSION: These data weakly corroborate prior findings of associations between LTL and mortality in the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Body Mass Index; Cardiovascular Diseases; Cause of Death; Comorbidity; Coronary Disease; Diabetes Mellitus; Female; Humans; Hypertension; Leukocytes; Longitudinal Studies; Male; Prospective Studies; Smoking; Stroke; Telomere

Lipoprotein-associated phospholipase A(2) and future risk of subclinical disease and cardiovascular events in individuals with type 2 diabetes: the Cardiovascular Health Study. - Nelson, T L; Kamineni, A; Psaty, B; Cushman, M; Jenny, N S; Hokanson, J; Furberg, C; Mukamal, K J (Diabetologia, 2011)
AIMS/HYPOTHESIS: Type 2 diabetes is an established risk factor for cardiovascular disease (CVD). This increased risk may be due in part to the increased levels of inflammatory factors associated with diabetes. Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) is a risk marker for CVD and has pro-inflammatory effects in atherosclerotic plaques. We therefore sought to determine whether Lp-PLA(2) levels partially explain the greater prevalence of subclinical CVD and greater incidence of CVD outcomes associated with type 2 diabetes in the Cardiovascular Health Study. METHODS: We conducted a cross-sectional and prospective study of 4,062 men and women without previous CVD from the Cardiovascular Health Study (1989 to 2007). Lp-PLA(2) mass and activity were measured in baseline plasma. Subclinical disease was determined at baseline and incident CVD was ascertained annually. We used logistic regression for cross-sectional analyses and Cox proportional hazards models for incident analyses. RESULTS: At baseline, Lp-PLA(2) mass did not differ significantly by type 2 diabetes status; however, Lp-PLA(2) activity was significantly higher among type 2 diabetic individuals. Baseline subclinical disease was significantly associated with baseline diabetes and this association was similar in models unadjusted or adjusted for Lp-PLA(2) (OR 1.68 [95% CI 1.31-2.15] vs OR 1.67 [95% CI 1.30-2.13]). Baseline type 2 diabetes was also significantly associated with incident CVD events, including fatal CHD, fatal myocardial infarction (MI) and non-fatal MI in multivariable analyses. There were no differences in these estimates after further adjustment for Lp-PLA(2) activity. CONCLUSIONS/INTERPRETATION: In this older cohort, differences in Lp-PLA(2) activity did not explain any of the excess risk for subclinical disease or CVD outcomes related to diabetes.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Cardiovascular Diseases; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Male; Proportional Hazards Models; Prospective Studies; Risk Factors

Longitudinal changes in adiponectin and inflammatory markers and relation to survival in the oldest old: the Cardiovascular Health Study All Stars study. - Kizer, Jorge R; Arnold, Alice M; Jenny, Nancy S; Cushman, Mary; Strotmeyer, Elsa S; Ives, Diane G; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Hirsch, Calvin H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Adiponectin has anti-inflammatory properties, and its production is suppressed by inflammatory factors. Although elevated levels of adiponectin and inflammatory markers each predict mortality in older adults, the implications of their interdependent actions have not been examined. METHODS: We investigated the joint associations of levels and interval changes in adiponectin, C-reactive protein (CRP), and interleukin 6 (IL-6) with risk of death in 840 older adults participating in a population-based study. Adiponectin, CRP, and IL-6 were measured in samples collected 8.9 (8.2-9.8) years apart, and all-cause mortality was subsequently ascertained (n = 176). RESULTS: Interval changes and end levels of adiponectin, CRP, and IL-6 showed mostly positive, independent associations with mortality, without evidence of multiplicative interaction. Joint models, however, showed an U-shaped relationship between end level of adiponectin and outcome (hazard ratio [HR] [95% CI] = 0.72 [0.52-0.99] per standard deviation [SD] for levels <20.0 mg/L; HR = 1.91 [1.61-3.44] per SD for levels ≥20.0 mg/L). Participants with the greatest longitudinal increases (upper quartile) in both adiponectin and inflammatory markers had a higher risk of death (HR = 2.85 [1.78-4.58]) than those with large increases in adiponectin alone (HR = 1.87 [1.20-2.92]) (p = .043), but not inflammatory markers alone (HR = 2.48 [1.67-3.67]) (p = .55), as compared with smaller changes for both. CONCLUSION: Higher levels or interval change in adiponectin and inflammatory markers predict increased mortality in older persons independent of each other, although for adiponectin, the association appears inverse below 20 mg/L. These findings suggest that inflammatory and noninflammatory mechanisms governing aging-related decline operate in parallel and provide a potential explanation for paradoxical adiponectin-outcome associations reported previously.
Keywords: Adiponectin; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Chi-Square Distribution; Enzyme-Linked Immunosorbent Assay; Female; Humans; Inflammation; Interleukin-6; Male; Mortality; Predictive Value of Tests; Risk Factors; Sensitivity and Specificity; Survival Analysis; United States

Meta-analysis of genome-wide association studies in >80 000 subjects identifies multiple loci for C-reactive protein levels. - Dehghan, Abbas; Dupuis, Josée; Barbalic, Maja; Bis, Joshua C; Eiriksdottir, Gudny; Lu, Chen; Pellikka, Niina; Wallaschofski, Henri; Kettunen, Johannes; Henneman, Peter; Baumert, Jens; Strachan, David P; et al. (Circulation, 2011)
BACKGROUND: C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We sought to identify genetic variants that are associated with CRP levels. METHODS AND RESULTS: We performed a genome-wide association analysis of CRP in 66 185 participants from 15 population-based studies. We sought replication for the genome-wide significant and suggestive loci in a replication panel comprising 16 540 individuals from 10 independent studies. We found 18 genome-wide significant loci, and we provided evidence of replication for 8 of them. Our results confirm 7 previously known loci and introduce 11 novel loci that are implicated in pathways related to the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) or the immune system (CRP, IL6R, NLRP3, IL1F10, and IRF1) or that reside in regions previously not known to play a role in chronic inflammation (PPP1R3B, SALL1, PABPC4, ASCL1, RORA, and BCL7B). We found a significant interaction of body mass index with LEPR (P<2.9×10(-6)). A weighted genetic risk score that was developed to summarize the effect of risk alleles was strongly associated with CRP levels and explained ≈5% of the trait variance; however, there was no evidence for these genetic variants explaining the association of CRP with coronary heart disease. CONCLUSIONS: We identified 18 loci that were associated with CRP levels. Our study highlights immune response and metabolic regulatory pathways involved in the regulation of chronic inflammation.
Keywords: Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Vasculitis

New gene functions in megakaryopoiesis and platelet formation. - Gieger, Christian; Radhakrishnan, Aparna; Cvejic, Ana; Tang, Weihong; Porcu, Eleonora; Pistis, Giorgio; Serbanovic-Canic, Jovana; Elling, Ulrich; Goodall, Alison H; Labrune, Yann; Lopez, Lorna M; Mägi, Reedik; et al. (Nature, 2011)
Platelets are the second most abundant cell type in blood and are essential for maintaining haemostasis. Their count and volume are tightly controlled within narrow physiological ranges, but there is only limited understanding of the molecular processes controlling both traits. Here we carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in up to 66,867 individuals of European ancestry, followed by extensive biological and functional assessment. We identified 68 genomic loci reliably associated with platelet count and volume mapping to established and putative novel regulators of megakaryopoiesis and platelet formation. These genes show megakaryocyte-specific gene expression patterns and extensive network connectivity. Using gene silencing in Danio rerio and Drosophila melanogaster, we identified 11 of the genes as novel regulators of blood cell formation. Taken together, our findings advance understanding of novel gene functions controlling fate-determining events during megakaryopoiesis and platelet formation, providing a new example of successful translation of GWAS to function.
Keywords: Animals; Blood Platelets; Cell Size; Drosophila melanogaster; Drosophila Proteins; Europe; Gene Expression Profiling; Gene Silencing; Genome, Human; Genome-Wide Association Study; Hematopoiesis; Humans; Megakaryocytes; Platelet Count; Protein Interaction Maps; Transcription, Genetic; Zebrafish; Zebrafish Proteins

The risk of Parkinson disease associated with urate in a community-based cohort of older adults. - Jain, S; Ton, T G; Boudreau, R M; Yang, M; Thacker, E L; Studenski, S; Longstreth, W T; Strotmeyer, E S; Newman, A B (Neuroepidemiology, 2011)
BACKGROUND/AIMS: Studies suggest an inverse association between urate concentration and the risk of Parkinson disease (PD). We investigated this in the Cardiovascular Health Study in an elderly community-based cohort of adults. METHODS: The association of baseline urate (µmol/l) and incident PD over 14 years was assessed with locally weighted scatterplot smoothing (LOESS) regression from which categories of low (<300 µmol/l), middle (300-500 µmol/l), and high (>500 µmol/l) urate ranges were derived. Multivariate logistic regression models assessed the risk of PD for each urate range. Linear and quadratic terms were tested when modeling the association between urate and the risk of PD. RESULTS: Women had significantly lower urate concentrations than did men [316.8 µmol/l (SD 88.0) vs. 367.4 µmol/l (SD 87.7), p < 0.0001] and in women no associations between urate and PD risk were observed. In men, LOESS curves suggested a U-shaped or threshold effect between urate and PD risk. With the middle range as reference, the risk of developing PD was significantly increased for urate <300 µmol/l (OR 1.69, 95% CI 1.03-2.78) but not for urate >500 µmol/l (OR 1.55, 95% CI 0.72-3.32) in men. A negative linear term was significant for urate <500 µmol/l, and across the entire range a convex quadratic term was significant. CONCLUSIONS: Results suggest a more complex relationship than previously reported between urate levels and the risk of PD in men. Low urate concentrations were associated with a higher PD risk and high urate concentrations were not associated with a further decrease in PD risk.
Keywords: Aged; California; Cohort Studies; Female; Humans; Male; Maryland; North Carolina; Parkinson Disease; Pennsylvania; Prospective Studies; Risk Factors; Sex Distribution; Sex Factors; Uric Acid

Total zinc intake may modify the glucose-raising effect of a zinc transporter (SLC30A8) variant: a 14-cohort meta-analysis. - Kanoni, Stavroula; Nettleton, Jennifer A; Hivert, Marie-France; Ye, Zheng; van Rooij, Frank J A; Shungin, Dmitry; Sonestedt, Emily; Ngwa, Julius S; Wojczynski, Mary K; Lemaitre, Rozenn N; Gustafsson, Stefan; Anderson, Jennifer S; et al. (Diabetes, 2011)
OBJECTIVE: Many genetic variants have been associated with glucose homeostasis and type 2 diabetes in genome-wide association studies. Zinc is an essential micronutrient that is important for β-cell function and glucose homeostasis. We tested the hypothesis that zinc intake could influence the glucose-raising effect of specific variants. RESEARCH DESIGN AND METHODS: We conducted a 14-cohort meta-analysis to assess the interaction of 20 genetic variants known to be related to glycemic traits and zinc metabolism with dietary zinc intake (food sources) and a 5-cohort meta-analysis to assess the interaction with total zinc intake (food sources and supplements) on fasting glucose levels among individuals of European ancestry without diabetes. RESULTS: We observed a significant association of total zinc intake with lower fasting glucose levels (β-coefficient ± SE per 1 mg/day of zinc intake: -0.0012 ± 0.0003 mmol/L, summary P value = 0.0003), while the association of dietary zinc intake was not significant. We identified a nominally significant interaction between total zinc intake and the SLC30A8 rs11558471 variant on fasting glucose levels (β-coefficient ± SE per A allele for 1 mg/day of greater total zinc intake: -0.0017 ± 0.0006 mmol/L, summary interaction P value = 0.005); this result suggests a stronger inverse association between total zinc intake and fasting glucose in individuals carrying the glucose-raising A allele compared with individuals who do not carry it. None of the other interaction tests were statistically significant. CONCLUSIONS: Our results suggest that higher total zinc intake may attenuate the glucose-raising effect of the rs11558471 SLC30A8 (zinc transporter) variant. Our findings also support evidence for the association of higher total zinc intake with lower fasting glucose levels.
Keywords: Blood Glucose; Cation Transport Proteins; Cohort Studies; Humans; Polymorphism, Single Nucleotide; Zinc; Zinc Transporter 8

Vitamin D, parathyroid hormone, and cardiovascular events among older adults. - Kestenbaum, Bryan; Katz, Ronit; de Boer, Ian; Hoofnagle, Andy; Sarnak, Mark J; Shlipak, Michael G; Jenny, Nancy S; Siscovick, David S (J Am Coll Cardiol, 2011)
OBJECTIVES: The aim of this study was to evaluate associations of 25-hydroxyvitamin D (25-OHD) and parathyroid hormone (PTH) concentrations separately and in combination with incident cardiovascular events and mortality during 14 years of follow-up in the CHS (Cardiovascular Health Study). BACKGROUND: Vitamin D deficiency and PTH excess are common in older adults and may adversely affect cardiovascular health. METHODS: A total of 2,312 participants who were free of cardiovascular disease at baseline were studied. Vitamin D and intact PTH were measured from previously frozen serum using mass spectrometry and a 2-site immunoassay. Outcomes were adjudicated cases of myocardial infarction, heart failure, cardiovascular death, and all-cause mortality. RESULTS: There were 384 participants (17%) with serum 25-OHD concentrations <15 ng/ml and 570 (25%) with serum PTH concentrations ≥ 65 pg/ml. After adjustment, each 10 ng/ml lower 25-OHD concentration was associated with a 9% greater (95% confidence interval [CI]: 2% to 17% greater) relative hazard of mortality and a 25% greater (95% CI: 8% to 44% greater) relative hazard of myocardial infarction. Serum 25-OHD concentrations <15 ng/ml were associated with a 29% greater (95% CI: 5% to 55% greater) risk for mortality. Serum PTH concentrations ≥ 65 pg/ml were associated with a 30% greater risk for heart failure (95% CI: 6% to 61% greater) but not other outcomes. There was no evidence of an interaction between serum 25-OHD and PTH concentrations and cardiovascular events. CONCLUSIONS: Among older adults, 25-OHD deficiency is associated with myocardial infarction and mortality; PTH excess is associated with heart failure. Vitamin D and PTH might influence cardiovascular risk through divergent pathways.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cohort Studies; Female; Follow-Up Studies; Humans; Male; Parathyroid Hormone; Prospective Studies; Vitamin D

Association of fetuin-a with incident diabetes mellitus in community-living older adults: the cardiovascular health study. - Ix, Joachim H; Biggs, Mary L; Mukamal, Kenneth J; Kizer, Jorge R; Zieman, Susan J; Siscovick, David S; Mozzaffarian, Dariush; Jensen, Majken K; Nelson, Lauren; Ruderman, Neil; Djoussé, Luc (Circulation, 2012)
BACKGROUND: The liver-secreted protein fetuin-A induces peripheral insulin resistance in vitro. In a pilot study, we observed that higher fetuin-A levels were associated with diabetes mellitus in older persons. However, this finding has not been confirmed in large cohorts. We sought to confirm the association of fetuin-A with incident diabetes mellitus in older persons and to determine whether the association differs by age, sex, and race and among persons with cardiovascular disease (CVD). METHODS AND RESULTS: Among 3710 community-living individuals ≥ 65 years of age without diabetes mellitus at baseline, fetuin-A was measured in serum collected in 1992 to 1993. Participants were followed up for 10.6 years (median) for incident diabetes mellitus. Cox regression models evaluated the association of fetuin-A with incident diabetes mellitus. Interaction terms evaluated heterogeneity by age, sex, race, and CVD. Mean age was 75 years; 60 were female; 15 were black; and 16 had CVD. Mean fetuin-A concentrations were 0.47 ± 0.10 g/L. During follow-up, 305 incident diabetes cases occurred. Each 0.10-g/L (SD)-greater fetuin-A was associated with 19 higher risk of diabetes mellitus (hazard ratio, 1.19; 95 confidence interval, 1.06-1.33) after adjustment for demographics, lifestyle factors, albumin, kidney function, and CVD. Further adjustment for potential mediators (body mass index, waist circumference, hypertension, lipids, and C-reactive protein) moderately attenuated the association (hazard ratio, 1.13; 95 confidence interval, 1.00-1.28). Results were similar by sex, race, and CVD status but were stronger in persons <75 years old (P for interaction=0.01). CONCLUSIONS: Higher fetuin-A is associated with incident diabetes mellitus in older persons regardless of sex, race, or prevalent CVD status. The association may be attenuated in those ≥ 75 years of age.
Keywords: African Continental Ancestry Group; Age Distribution; Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Humans; Incidence; Life Style; Lipids; Male; Pilot Projects; Prevalence; Proportional Hazards Models; Residence Characteristics; Risk Factors; Sex Distribution

Cardiac microinjury measured by troponin T predicts collagen metabolism in adults aged >=65 years with heart failure. - Kop, Willem J; Gottdiener, John S; deFilippi, Christopher R; Barasch, Eddy; Seliger, Stephen L; Jenny, Nancy S; Christenson, Robert H (Circ Heart Fail, 2012)
BACKGROUND: Repeated myocardial microinjuries lead to collagen deposition and fibrosis, thereby increasing the risk of clinical heart failure. Little is known about the longitudinal association between increases in myocardial injury and the biology of collagen synthesis and deposition. METHODS AND RESULTS: Repeated measures of highly sensitive cardiac troponin T (cTnT) were obtained in participants of the Cardiovascular Health Study (N=353; mean age, 74±6 years; 52% women) at baseline and at 3 years follow-up. Biomarkers of collagen metabolism were obtained at follow-up and included carboxyterminal propeptide of procollagen type I, carboxyterminal telopeptide of type I collagen, and aminoterminal propeptide of procollagen III. Multivariable linear regression analyses were used to examine the association between baseline cTnT and changes in cTnT with collagen metabolism markers at follow-up adjusting for demographics, heart failure status, and cardiovascular risk factors. Results indicated that cTnT increases over 3-years were significantly associated with higher levels of carboxyterminal telopeptide of type I collagen (β=0.22, P<0.001) and aminoterminal propeptide of procollagen III (β=0.12, P=0.035) at follow-up when adjusting for demographic, clinical, and biochemical covariates including baseline cTnT. These associations were stronger in patients with heart failure than in control subjects. Conclusions- Increases in myocardial microinjury measured by changes in cTnT adversely affect markers of collagen metabolism. These findings are important to the biology of myocardial fibrosis and tissue repair. Serial evaluation of cTnT combined with collagen metabolism markers may further elucidate the pathophysiology of heart failure.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Case-Control Studies; Chi-Square Distribution; Collagen; Collagen Type I; Female; Fibrosis; Heart Failure; Humans; Linear Models; Longitudinal Studies; Male; Multivariate Analysis; Myocardium; Peptide Fragments; Peptides; Predictive Value of Tests; Procollagen; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; Troponin T; Up-Regulation

Cardiovascular physiology in premotor Parkinson's disease: a neuroepidemiologic study. - Jain, Samay; Ton, Thanh G; Perera, Subashan; Zheng, Yan; Stein, Phyllis K; Thacker, Evan; Strotmeyer, Elsa S; Newman, Anne B; Longstreth, Will T (Mov Disord, 2012)
Changes in cardiovascular physiology in Parkinson's disease (PD) are common and may occur prior to diagnostic parkinsonian motor signs. We investigated associations of electrocardiographic (ECG) abnormalities, orthostasis, heart rate variability, and carotid stenosis with the risk of PD diagnosis in the Cardiovascular Health Study, a community-based cohort of older adults. ECG abnormality, orthostasis (symptomatic or asymptomatic), heart rate variability (24-hour Holter monitoring), and any carotid stenosis (≥1%) by ultrasound were modeled as primary predictors of incident PD diagnosis using multivariable logistic regression. Incident PD cases were identified by at least 1 of the following: self-report, antiparkinsonian medication use, and ICD-9. If unadjusted models were significant, they were adjusted or stratified by age, sex, and smoking status, and those in which predictors were still significant (P ≤ .05) were also adjusted for race, diabetes, total cholesterol, low-density lipoprotein, blood pressure, body mass index, physical activity, education level, stroke, and C-reactive protein. Of 5888 participants, 154 incident PD cases were identified over 14 years of follow-up. After adjusting models with all covariates, those with any ECG abnormality (odds ratio [OR], 1.45; 95% CI, 1.02-2.07; P = .04) or any carotid stenosis (OR, 2.40; 95% CI, 1.40-4.09; P = .001) at baseline had a higher risk of incident PD diagnosis. Orthostasis and heart rate variability were not significant predictors. This exploratory study suggests that carotid stenosis and ECG abnormalities occur prior to motor signs in PD, thus serving as potential premotor features or risk factors for PD diagnosis. Replication is needed in a population with more thorough ascertainment of PD onset.
Keywords: Aged; Antiparkinson Agents; Cardiovascular Physiological Phenomena; Carotid Stenosis; Cohort Studies; Data Interpretation, Statistical; Dizziness; Electrocardiography; Female; Heart Rate; Hospitalization; Humans; Longitudinal Studies; Male; Movement Disorders; Neurologic Examination; Parkinson Disease; Risk; Ultrasonography

Common folate gene variant, MTHFR C677T, is associated with brain structure in two independent cohorts of people with mild cognitive impairment. - Rajagopalan, Priya; Jahanshad, Neda; Stein, Jason L; Hua, Xue; Madsen, Sarah K; Kohannim, Omid; Hibar, Derrek P; Toga, Arthur W; Jack, Clifford R; Saykin, Andrew J; Green, Robert C; Weiner, Michael W; et al. (Neuroimage Clin, 2012)
A commonly carried C677T polymorphism in a folate-related gene, MTHFR, is associated with higher plasma homocysteine, a well-known mediator of neuronal damage and brain atrophy. As homocysteine promotes brain atrophy, we set out to discover whether people carrying the C677T MTHFR polymorphism which increases homocysteine, might also show systematic differences in brain structure. Using tensor-based morphometry, we tested this association in 359 elderly Caucasian subjects with mild cognitive impairment (MCI) (mean age: 75 ± 7.1 years) scanned with brain MRI and genotyped as part of Alzheimer's Disease Neuroimaging Initiative. We carried out a replication study in an independent, non-overlapping sample of 51 elderly Caucasian subjects with MCI (mean age: 76 ± 5.5 years), scanned with brain MRI and genotyped for MTHFR, as part of the Cardiovascular Health Study. At each voxel in the brain, we tested to see where regional volume differences were associated with carrying one or more MTHFR 'T' alleles. In ADNI subjects, carriers of the MTHFR risk allele had detectable brain volume deficits, in the white matter, of up to 2-8% per risk T allele locally at baseline and showed accelerated brain atrophy of 0.5-1.5% per T allele at 1 year follow-up, after adjusting for age and sex. We replicated these brain volume deficits of up to 5-12% per MTHFR T allele in the independent cohort of CHS subjects. As expected, the associations weakened after controlling for homocysteine levels, which the risk gene affects. The MTHFR risk variant may thus promote brain atrophy by elevating homocysteine levels. This study aims to investigate the spatially detailed effects of this MTHFR polymorphism on brain structure in 3D, pointing to a causal pathway that may promote homocysteine-mediated brain atrophy in elderly people with MCI.

Comparison of risk prediction using the CKD-EPI equation and the MDRD study equation for estimated glomerular filtration rate. - Matsushita, Kunihiro; Mahmoodi, Bakhtawar K; Woodward, Mark; Emberson, Jonathan R; Jafar, Tazeen H; Jee, Sun Ha; Polkinghorne, Kevan R; Shankar, Anoop; Smith, David H; Tonelli, Marcello; Warnock, David G; Wen, Chi-Pang; et al. (JAMA, 2012)
CONTEXT: The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation more accurately estimates glomerular filtration rate (GFR) than the Modification of Diet in Renal Disease (MDRD) Study equation using the same variables, especially at higher GFR, but definitive evidence of its risk implications in diverse settings is lacking. OBJECTIVE: To evaluate risk implications of estimated GFR using the CKD-EPI equation compared with the MDRD Study equation in populations with a broad range of demographic and clinical characteristics. DESIGN, SETTING, AND PARTICIPANTS: A meta-analysis of data from 1.1 million adults (aged ≥ 18 years) from 25 general population cohorts, 7 high-risk cohorts (of vascular disease), and 13 CKD cohorts. Data transfer and analyses were conducted between March 2011 and March 2012. MAIN OUTCOME MEASURES: All-cause mortality (84,482 deaths from 40 cohorts), cardiovascular mortality (22,176 events from 28 cohorts), and end-stage renal disease (ESRD) (7644 events from 21 cohorts) during 9.4 million person-years of follow-up; the median of mean follow-up time across cohorts was 7.4 years (interquartile range, 4.2-10.5 years). RESULTS: Estimated GFR was classified into 6 categories (≥90, 60-89, 45-59, 30-44, 15-29, and <15 mL/min/1.73 m(2)) by both equations. Compared with the MDRD Study equation, 24.4% and 0.6% of participants from general population cohorts were reclassified to a higher and lower estimated GFR category, respectively, by the CKD-EPI equation, and the prevalence of CKD stages 3 to 5 (estimated GFR <60 mL/min/1.73 m(2)) was reduced from 8.7% to 6.3%. In estimated GFR of 45 to 59 mL/min/1.73 m(2) by the MDRD Study equation, 34.7% of participants were reclassified to estimated GFR of 60 to 89 mL/min/1.73 m(2) by the CKD-EPI equation and had lower incidence rates (per 1000 person-years) for the outcomes of interest (9.9 vs 34.5 for all-cause mortality, 2.7 vs 13.0 for cardiovascular mortality, and 0.5 vs 0.8 for ESRD) compared with those not reclassified. The corresponding adjusted hazard ratios were 0.80 (95% CI, 0.74-0.86) for all-cause mortality, 0.73 (95% CI, 0.65-0.82) for cardiovascular mortality, and 0.49 (95% CI, 0.27-0.88) for ESRD. Similar findings were observed in other estimated GFR categories by the MDRD Study equation. Net reclassification improvement based on estimated GFR categories was significantly positive for all outcomes (range, 0.06-0.13; all P < .001). Net reclassification improvement was similarly positive in most subgroups defined by age (<65 years and ≥65 years), sex, race/ethnicity (white, Asian, and black), and presence or absence of diabetes and hypertension. The results in the high-risk and CKD cohorts were largely consistent with the general population cohorts. CONCLUSION: The CKD-EPI equation classified fewer individuals as having CKD and more accurately categorized the risk for mortality and ESRD than did the MDRD Study equation across a broad range of populations.
Keywords: African Continental Ancestry Group; Aged; Algorithms; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Decision Support Techniques; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Models, Theoretical; Risk Assessment; Sex Factors

Consistent directions of effect for established type 2 diabetes risk variants across populations: the population architecture using Genomics and Epidemiology (PAGE) Consortium. - Haiman, Christopher A; Fesinmeyer, Megan D; Spencer, Kylee L; Bůzková, Petra; Voruganti, V Saroja; Wan, Peggy; Haessler, Jeff; Franceschini, Nora; Monroe, Kristine R; Howard, Barbara V; Jackson, Rebecca D; Florez, Jose C; et al. (Diabetes, 2012)
Common genetic risk variants for type 2 diabetes (T2D) have primarily been identified in populations of European and Asian ancestry. We tested whether the direction of association with 20 T2D risk variants generalizes across six major racial/ethnic groups in the U.S. as part of the Population Architecture using Genomics and Epidemiology Consortium (16,235 diabetes case and 46,122 control subjects of European American, African American, Hispanic, East Asian, American Indian, and Native Hawaiian ancestry). The percentage of positive (odds ratio [OR] >1 for putative risk allele) associations ranged from 69% in American Indians to 100% in European Americans. Of the nine variants where we observed significant heterogeneity of effect by racial/ethnic group (P(heterogeneity) < 0.05), eight were positively associated with risk (OR >1) in at least five groups. The marked directional consistency of association observed for most genetic variants across populations implies a shared functional common variant in each region. Fine-mapping of all loci will be required to reveal markers of risk that are important within and across populations.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Metagenomics; Middle Aged; Population Groups; Risk; Risk Factors

Evaluation of the metabochip genotyping array in African Americans and implications for fine mapping of GWAS-identified loci: the PAGE study. - Buyske, Steven; Wu, Ying; Carty, Cara L; Cheng, Iona; Assimes, Themistocles L; Dumitrescu, Logan; Hindorff, Lucia A; Mitchell, Sabrina; Ambite, Jose Luis; Boerwinkle, Eric; Bůzková, Petra; Carlson, Chris S; et al. (PLoS One, 2012)
The Metabochip is a custom genotyping array designed for replication and fine mapping of metabolic, cardiovascular, and anthropometric trait loci and includes low frequency variation content identified from the 1000 Genomes Project. It has 196,725 SNPs concentrated in 257 genomic regions. We evaluated the Metabochip in 5,863 African Americans; 89% of all SNPs passed rigorous quality control with a call rate of 99.9%. Two examples illustrate the value of fine mapping with the Metabochip in African-ancestry populations. At CELSR2/PSRC1/SORT1, we found the strongest associated SNP for LDL-C to be rs12740374 (p = 3.5 × 10(-11)), a SNP indistinguishable from multiple SNPs in European ancestry samples due to high correlation. Its distinct signal supports functional studies elsewhere suggesting a causal role in LDL-C. At CETP we found rs17231520, with risk allele frequency 0.07 in African Americans, to be associated with HDL-C (p = 7.2 × 10(-36)). This variant is very rare in Europeans and not tagged in common GWAS arrays, but was identified as associated with HDL-C in African Americans in a single-gene study. Our results, one narrowing the risk interval and the other revealing an associated variant not found in Europeans, demonstrate the advantages of high-density genotyping of common and rare variation for fine mapping of trait loci in African American samples.
Keywords: African Americans; Cardiovascular Diseases; Cholesterol Ester Transfer Proteins; Cholesterol, HDL; Cholesterol, LDL; Chromosomes, Human; Cohort Studies; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; Metabolic Diseases; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Evolution and functional impact of rare coding variation from deep sequencing of human exomes. - Tennessen, Jacob A; Bigham, Abigail W; O'Connor, Timothy D; Fu, Wenqing; Kenny, Eimear E; Gravel, Simon; McGee, Sean; Do, Ron; Liu, Xiaoming; Jun, Goo; Kang, Hyun Min; Jordan, Daniel; et al. (Science, 2012)
As a first step toward understanding how rare variants contribute to risk for complex diseases, we sequenced 15,585 human protein-coding genes to an average median depth of 111× in 2440 individuals of European (n = 1351) and African (n = 1088) ancestry. We identified over 500,000 single-nucleotide variants (SNVs), the majority of which were rare (86% with a minor allele frequency less than 0.5%), previously unknown (82%), and population-specific (82%). On average, 2.3% of the 13,595 SNVs each person carried were predicted to affect protein function of ~313 genes per genome, and ~95.7% of SNVs predicted to be functionally important were rare. This excess of rare functional variants is due to the combined effects of explosive, recent accelerated population growth and weak purifying selection. Furthermore, we show that large sample sizes will be required to associate rare variants with complex traits.
Keywords: African Americans; Disease; European Continental Ancestry Group; Evolution, Molecular; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Polymorphism, Single Nucleotide; Population Growth; Selection, Genetic

Fine-mapping and initial characterization of QT interval loci in African Americans. - Avery, Christy L; Sethupathy, Praveen; Buyske, Steven; He, Qianchuan; Lin, Dan-Yu; Arking, Dan E; Carty, Cara L; Duggan, David; Fesinmeyer, Megan D; Hindorff, Lucia A; Jeff, Janina M; Klein, Liviu; et al. (PLoS Genet, 2012)
The QT interval (QT) is heritable and its prolongation is a risk factor for ventricular tachyarrhythmias and sudden death. Most genetic studies of QT have examined European ancestral populations; however, the increased genetic diversity in African Americans provides opportunities to narrow association signals and identify population-specific variants. We therefore evaluated 6,670 SNPs spanning eleven previously identified QT loci in 8,644 African American participants from two Population Architecture using Genomics and Epidemiology (PAGE) studies: the Atherosclerosis Risk in Communities study and Women's Health Initiative Clinical Trial. Of the fifteen known independent QT variants at the eleven previously identified loci, six were significantly associated with QT in African American populations (P≤1.20×10(-4)): ATP1B1, PLN1, KCNQ1, NDRG4, and two NOS1AP independent signals. We also identified three population-specific signals significantly associated with QT in African Americans (P≤1.37×10(-5)): one at NOS1AP and two at ATP1B1. Linkage disequilibrium (LD) patterns in African Americans assisted in narrowing the region likely to contain the functional variants for several loci. For example, African American LD patterns showed that 0 SNPs were in LD with NOS1AP signal rs12143842, compared with European LD patterns that indicated 87 SNPs, which spanned 114.2 Kb, were in LD with rs12143842. Finally, bioinformatic-based characterization of the nine African American signals pointed to functional candidates located exclusively within non-coding regions, including predicted binding sites for transcription factors such as TBX5, which has been implicated in cardiac structure and conductance. In this detailed evaluation of QT loci, we identified several African Americans SNPs that better define the association with QT and successfully narrowed intervals surrounding established loci. These results demonstrate that the same loci influence variation in QT across multiple populations, that novel signals exist in African Americans, and that the SNPs identified as strong candidates for functional evaluation implicate gene regulatory dysfunction in QT prolongation.
Keywords: African Americans; Aged; Computational Biology; Electrocardiography; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors; Tachycardia; United States

FTO genotype is associated with phenotypic variability of body mass index. - Yang, Jian; Loos, Ruth J F; Powell, Joseph E; Medland, Sarah E; Speliotes, Elizabeth K; Chasman, Daniel I; Rose, Lynda M; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Mägi, Reedik; Waite, Lindsay; Smith, Albert Vernon; et al. (Nature, 2012)
There is evidence across several species for genetic control of phenotypic variation of complex traits, such that the variance among phenotypes is genotype dependent. Understanding genetic control of variability is important in evolutionary biology, agricultural selection programmes and human medicine, yet for complex traits, no individual genetic variants associated with variance, as opposed to the mean, have been identified. Here we perform a meta-analysis of genome-wide association studies of phenotypic variation using ∼170,000 samples on height and body mass index (BMI) in human populations. We report evidence that the single nucleotide polymorphism (SNP) rs7202116 at the FTO gene locus, which is known to be associated with obesity (as measured by mean BMI for each rs7202116 genotype), is also associated with phenotypic variability. We show that the results are not due to scale effects or other artefacts, and find no other experiment-wise significant evidence for effects on variability, either at loci other than FTO for BMI or at any locus for height. The difference in variance for BMI among individuals with opposite homozygous genotypes at the FTO locus is approximately 7%, corresponding to a difference of ∼0.5 kilograms in the standard deviation of weight. Our results indicate that genetic variants can be discovered that are associated with variability, and that between-person variability in obesity can partly be explained by the genotype at the FTO locus. The results are consistent with reported FTO by environment interactions for BMI, possibly mediated by DNA methylation. Our BMI results for other SNPs and our height results for all SNPs suggest that most genetic variants, including those that influence mean height or mean BMI, are not associated with phenotypic variance, or that their effects on variability are too small to detect even with samples sizes greater than 100,000.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Height; Body Mass Index; Co-Repressor Proteins; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteins; Repressor Proteins

Genetic determinants of the ankle-brachial index: a meta-analysis of a cardiovascular candidate gene 50K SNP panel in the candidate gene association resource (CARe) consortium. - Wassel, Christina L; Lamina, Claudia; Nambi, Vijay; Coassin, Stefan; Mukamal, Kenneth J; Ganesh, Santhi K; Jacobs, David R; Franceschini, Nora; Papanicolaou, George J; Gibson, Quince; Yanek, Lisa R; van der Harst, Pim; et al. (Atherosclerosis, 2012)
BACKGROUND: Candidate gene association studies for peripheral artery disease (PAD), including subclinical disease assessed with the ankle-brachial index (ABI), have been limited by the modest number of genes examined. We conducted a two stage meta-analysis of ∼50,000 SNPs across ∼2100 candidate genes to identify genetic variants for ABI. METHODS AND RESULTS: We studied subjects of European ancestry from 8 studies (n=21,547, 55% women, mean age 44-73 years) and African American ancestry from 5 studies (n=7267, 60% women, mean age 41-73 years) involved in the candidate gene association resource (CARe) consortium. In each ethnic group, additive genetic models were used (with each additional copy of the minor allele corresponding to the given beta) to test each SNP for association with continuous ABI (excluding ABI>1.40) and PAD (defined as ABI<0.90) using linear or logistic regression with adjustment for known PAD risk factors and population stratification. We then conducted a fixed-effects inverse-variance weighted meta-analyses considering a p<2×10(-6) to denote statistical significance. RESULTS: In the European ancestry discovery meta-analyses, rs2171209 in SYTL3 (β=-0.007, p=6.02×10(-7)) and rs290481 in TCF7L2 (β=-0.008, p=7.01×10(-7)) were significantly associated with ABI. None of the SNP associations for PAD were significant, though a SNP in CYP2B6 (p=4.99×10(-5)) was among the strongest associations. These 3 genes are linked to key PAD risk factors (lipoprotein(a), type 2 diabetes, and smoking behavior, respectively). We sought replication in 6 population-based and 3 clinical samples (n=15,440) for rs290481 and rs2171209. However, in the replication stage (rs2171209, p=0.75; rs290481, p=0.19) and in the combined discovery and replication analysis the SNP-ABI associations were no longer significant (rs2171209, p=1.14×10(-3); rs290481, p=8.88×10(-5)). In African Americans, none of the SNP associations for ABI or PAD achieved an experiment-wide level of significance. CONCLUSIONS: Genetic determinants of ABI and PAD remain elusive. Follow-up of these preliminary findings may uncover important biology given the known gene-risk factor associations. New and more powerful approaches to PAD gene discovery are warranted.
Keywords: Adult; African Americans; Aged; Ankle Brachial Index; Aryl Hydrocarbon Hydroxylases; Cytochrome P-450 CYP2B6; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Oxidoreductases, N-Demethylating; Peripheral Arterial Disease; Polymorphism, Single Nucleotide; Risk Factors; Transcription Factor 7-Like 2 Protein

Genetic variants in Arhgef11 are associated with kidney injury in the Dahl salt-sensitive rat. - Williams, Jan M; Johnson, Ashley C; Stelloh, Cary; Dreisbach, Albert W; Franceschini, Nora; Regner, Kevin R; Townsend, Raymond R; Roman, Richard J; Garrett, Michael R (Hypertension, 2012)
A previous genetic analysis comparing the Dahl salt-sensitive (S) rat with the spontaneously hypertensive rat identified a major locus on chromosome 2 that influences proteinuria in the S rat. In the present study, blood pressure, proteinuria, and renal hemodynamics were evaluated in congenic strains with small segments of the protective spontaneously hypertensive rat genome on the S background. Proteinuria and renal function were significantly improved in the congenic strains compared with the S. The causative locus interval was narrowed to <375 kb on the basis of congenic strains, haplotype data, comparative mapping, and concordance with human genetic studies. Sequencing of the coding region of genes in this region identified 36 single nucleotide polymorphisms (13 nonsynonymous and 23 synonymous). Gene expression profiling indicated that only a few genes exhibited differential expression. Arhgef11, Pear1, and Sh2d2 were identified as important candidate genes that may be linked to kidney injury in the S rat. In particular, Arhgef11 plays an important role in the activation of the Rho-ROCK signaling pathway. Inhibition of this pathway using fasudil resulted in a significant reduction of proteinuria in treated S rats (compared with untreated S). However, no difference was observed between treated or untreated spontaneously hypertensive rat or congenic strains. The homologous region in humans was found to be associated with estimated glomerular filtration rate in the Candidate Gene Association Resource population. In summary, these findings demonstrate that allelic variants in Arhgef11, acting through the Rho-ROCK pathway, could influence kidney injury in the S as well as provide insight into human kidney disease.
Keywords: 1-(5-Isoquinolinesulfonyl)-2-Methylpiperazine; Animals; Animals, Congenic; Blood Pressure; Blotting, Western; Chromosome Mapping; Gene Expression Profiling; Genetic Predisposition to Disease; Guanine Nucleotide Exchange Factors; Humans; Kidney; Kidney Diseases; Male; Polymorphism, Single Nucleotide; Protein Kinase Inhibitors; Proteinuria; Quantitative Trait Loci; Rats; Rats, Inbred Dahl; Rats, Inbred SHR; Renal Circulation; Reverse Transcriptase Polymerase Chain Reaction; rho-Associated Kinases; rhoA GTP-Binding Protein; Signal Transduction

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genome-wide association studies identify CHRNA5/3 and HTR4 in the development of airflow obstruction. - Wilk, Jemma B; Shrine, Nick R G; Loehr, Laura R; Zhao, Jing Hua; Manichaikul, Ani; Lopez, Lorna M; Smith, Albert Vernon; Heckbert, Susan R; Smolonska, Joanna; Tang, Wenbo; Loth, Daan W; Curjuric, Ivan; et al. (Am J Respir Crit Care Med, 2012)
RATIONALE: Genome-wide association studies (GWAS) have identified loci influencing lung function, but fewer genes influencing chronic obstructive pulmonary disease (COPD) are known. OBJECTIVES: Perform meta-analyses of GWAS for airflow obstruction, a key pathophysiologic characteristic of COPD assessed by spirometry, in population-based cohorts examining all participants, ever smokers, never smokers, asthma-free participants, and more severe cases. METHODS: Fifteen cohorts were studied for discovery (3,368 affected; 29,507 unaffected), and a population-based family study and a meta-analysis of case-control studies were used for replication and regional follow-up (3,837 cases; 4,479 control subjects). Airflow obstruction was defined as FEV(1) and its ratio to FVC (FEV(1)/FVC) both less than their respective lower limits of normal as determined by published reference equations. MEASUREMENTS AND MAIN RESULTS: The discovery meta-analyses identified one region on chromosome 15q25.1 meeting genome-wide significance in ever smokers that includes AGPHD1, IREB2, and CHRNA5/CHRNA3 genes. The region was also modestly associated among never smokers. Gene expression studies confirmed the presence of CHRNA5/3 in lung, airway smooth muscle, and bronchial epithelial cells. A single-nucleotide polymorphism in HTR4, a gene previously related to FEV(1)/FVC, achieved genome-wide statistical significance in combined meta-analysis. Top single-nucleotide polymorphisms in ADAM19, RARB, PPAP2B, and ADAMTS19 were nominally replicated in the COPD meta-analysis. CONCLUSIONS: These results suggest an important role for the CHRNA5/3 region as a genetic risk factor for airflow obstruction that may be independent of smoking and implicate the HTR4 gene in the etiology of airflow obstruction.
Keywords: Aged; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Receptors, Nicotinic; Receptors, Serotonin, 5-HT4; Smoking; Vital Capacity

Genome-wide association study for circulating levels of PAI-1 provides novel insights into its regulation. - Huang, Jie; Sabater-Lleal, Maria; Asselbergs, Folkert W; Tregouet, David; Shin, So-Youn; Ding, Jingzhong; Baumert, Jens; Oudot-Mellakh, Tiphaine; Folkersen, Lasse; Johnson, Andrew D; Smith, Nicholas L; Williams, Scott M; et al. (Blood, 2012)
We conducted a genome-wide association study to identify novel associations between genetic variants and circulating plasminogen activator inhibitor-1 (PAI-1) concentration, and examined functional implications of variants and genes that were discovered. A discovery meta-analysis was performed in 19 599 subjects, followed by replication analysis of genome-wide significant (P < 5 × 10(-8)) single nucleotide polymorphisms (SNPs) in 10 796 independent samples. We further examined associations with type 2 diabetes and coronary artery disease, assessed the functional significance of the SNPs for gene expression in human tissues, and conducted RNA-silencing experiments for one novel association. We confirmed the association of the 4G/5G proxy SNP rs2227631 in the promoter region of SERPINE1 (7q22.1) and discovered genome-wide significant associations at 3 additional loci: chromosome 7q22.1 close to SERPINE1 (rs6976053, discovery P = 3.4 × 10(-10)); chromosome 11p15.2 within ARNTL (rs6486122, discovery P = 3.0 × 10(-8)); and chromosome 3p25.2 within PPARG (rs11128603, discovery P = 2.9 × 10(-8)). Replication was achieved for the 7q22.1 and 11p15.2 loci. There was nominal association with type 2 diabetes and coronary artery disease at ARNTL (P < .05). Functional studies identified MUC3 as a candidate gene for the second association signal on 7q22.1. In summary, SNPs in SERPINE1 and ARNTL and an SNP associated with the expression of MUC3 were robustly associated with circulating levels of PAI-1.
Keywords: Adaptor Proteins, Signal Transducing; ARNTL Transcription Factors; ATPases Associated with Diverse Cellular Activities; Cell Line; Cell Line, Tumor; Cohort Studies; Coronary Artery Disease; Diabetes Mellitus, Type 2; Gene Expression Profiling; Gene Expression Regulation; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; LIM Domain Proteins; Meta-Analysis as Topic; Monocytes; Mucin-3; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; PPAR gamma; Proteasome Endopeptidase Complex; RNA Interference; Transcription Factors

Genome-wide joint meta-analysis of SNP and SNP-by-smoking interaction identifies novel loci for pulmonary function. - Hancock, Dana B; Soler Artigas, Maria; Gharib, Sina A; Henry, Amanda; Manichaikul, Ani; Ramasamy, Adaikalavan; Loth, Daan W; Imboden, Medea; Koch, Beate; McArdle, Wendy L; Smith, Albert V; Smolonska, Joanna; et al. (PLoS Genet, 2012)
Genome-wide association studies have identified numerous genetic loci for spirometic measures of pulmonary function, forced expiratory volume in one second (FEV(1)), and its ratio to forced vital capacity (FEV(1)/FVC). Given that cigarette smoking adversely affects pulmonary function, we conducted genome-wide joint meta-analyses (JMA) of single nucleotide polymorphism (SNP) and SNP-by-smoking (ever-smoking or pack-years) associations on FEV(1) and FEV(1)/FVC across 19 studies (total N = 50,047). We identified three novel loci not previously associated with pulmonary function. SNPs in or near DNER (smallest P(JMA = )5.00×10(-11)), HLA-DQB1 and HLA-DQA2 (smallest P(JMA = )4.35×10(-9)), and KCNJ2 and SOX9 (smallest P(JMA = )1.28×10(-8)) were associated with FEV(1)/FVC or FEV(1) in meta-analysis models including SNP main effects, smoking main effects, and SNP-by-smoking (ever-smoking or pack-years) interaction. The HLA region has been widely implicated for autoimmune and lung phenotypes, unlike the other novel loci, which have not been widely implicated. We evaluated DNER, KCNJ2, and SOX9 and found them to be expressed in human lung tissue. DNER and SOX9 further showed evidence of differential expression in human airway epithelium in smokers compared to non-smokers. Our findings demonstrated that joint testing of SNP and SNP-by-environment interaction identified novel loci associated with complex traits that are missed when considering only the genetic main effects.
Keywords: Forced Expiratory Volume; Gene Expression; Genome, Human; Genome-Wide Association Study; HLA-DQ Antigens; HLA-DQ beta-Chains; Humans; Lung; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels, Inwardly Rectifying; Pulmonary Disease, Chronic Obstructive; Receptors, Cell Surface; Smoking; SOX9 Transcription Factor; Vital Capacity

Genome-wide meta-analyses of smoking behaviors in African Americans. - David, S P; Hamidovic, A; Chen, G K; Bergen, A W; Wessel, J; Kasberger, J L; Brown, W M; Petruzella, S; Thacker, E L; Kim, Y; Nalls, M A; Tranah, G J; et al. (Transl Psychiatry, 2012)
The identification and exploration of genetic loci that influence smoking behaviors have been conducted primarily in populations of the European ancestry. Here we report results of the first genome-wide association study meta-analysis of smoking behavior in African Americans in the Study of Tobacco in Minority Populations Genetics Consortium (n = 32,389). We identified one non-coding single-nucleotide polymorphism (SNP; rs2036527[A]) on chromosome 15q25.1 associated with smoking quantity (cigarettes per day), which exceeded genome-wide significance (β = 0.040, s.e. = 0.007, P = 1.84 × 10(-8)). This variant is present in the 5'-distal enhancer region of the CHRNA5 gene and defines the primary index signal reported in studies of the European ancestry. No other SNP reached genome-wide significance for smoking initiation (SI, ever vs never smoking), age of SI, or smoking cessation (SC, former vs current smoking). Informative associations that approached genome-wide significance included three modestly correlated variants, at 15q25.1 within PSMA4, CHRNA5 and CHRNA3 for smoking quantity, which are associated with a second signal previously reported in studies in European ancestry populations, and a signal represented by three SNPs in the SPOCK2 gene on chr10q22.1. The association at 15q25.1 confirms this region as an important susceptibility locus for smoking quantity in men and women of African ancestry. Larger studies will be needed to validate the suggestive loci that did not reach genome-wide significance and further elucidate the contribution of genetic variation to disparities in cigarette consumption, SC and smoking-attributable disease between African Americans and European Americans.
Keywords: Adult; African Americans; Aged; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 15; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteoglycans; Receptors, Nicotinic; Smoking; Statistics as Topic

Genome-wide meta-analysis identifies 56 bone mineral density loci and reveals 14 loci associated with risk of fracture. - Estrada, Karol; Styrkarsdottir, Unnur; Evangelou, Evangelos; Hsu, Yi-Hsiang; Duncan, Emma L; Ntzani, Evangelia E; Oei, Ling; Albagha, Omar M E; Amin, Najaf; Kemp, John P; Koller, Daniel L; Li, Guo; et al. (Nat Genet, 2012)
Bone mineral density (BMD) is the most widely used predictor of fracture risk. We performed the largest meta-analysis to date on lumbar spine and femoral neck BMD, including 17 genome-wide association studies and 32,961 individuals of European and east Asian ancestry. We tested the top BMD-associated markers for replication in 50,933 independent subjects and for association with risk of low-trauma fracture in 31,016 individuals with a history of fracture (cases) and 102,444 controls. We identified 56 loci (32 new) associated with BMD at genome-wide significance (P < 5 × 10(-8)). Several of these factors cluster within the RANK-RANKL-OPG, mesenchymal stem cell differentiation, endochondral ossification and Wnt signaling pathways. However, we also discovered loci that were localized to genes not known to have a role in bone biology. Fourteen BMD-associated loci were also associated with fracture risk (P < 5 × 10(-4), Bonferroni corrected), of which six reached P < 5 × 10(-8), including at 18p11.21 (FAM210A), 7q21.3 (SLC25A13), 11q13.2 (LRP5), 4q22.1 (MEPE), 2p16.2 (SPTBN1) and 10q21.1 (DKK1). These findings shed light on the genetic architecture and pathophysiological mechanisms underlying BMD variation and fracture susceptibility.
Keywords: Bone Density; Computational Biology; European Continental Ancestry Group; Extracellular Matrix Proteins; Female; Femur Neck; Fractures, Bone; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Glycoproteins; Humans; Intercellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-5; Lumbar Vertebrae; Male; Mitochondrial Membrane Transport Proteins; Osteoporosis; Phosphoproteins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Spectrin

Large-scale association analyses identify new loci influencing glycemic traits and provide insight into the underlying biological pathways. - Scott, Robert A; Lagou, Vasiliki; Welch, Ryan P; Wheeler, Eleanor; Montasser, May E; Luan, Jian'an; Mägi, Reedik; Strawbridge, Rona J; Rehnberg, Emil; Gustafsson, Stefan; Kanoni, Stavroula; Rasmussen-Torvik, Laura J; et al. (Nat Genet, 2012)
Through genome-wide association meta-analyses of up to 133,010 individuals of European ancestry without diabetes, including individuals newly genotyped using the Metabochip, we have increased the number of confirmed loci influencing glycemic traits to 53, of which 33 also increase type 2 diabetes risk (q < 0.05). Loci influencing fasting insulin concentration showed association with lipid levels and fat distribution, suggesting impact on insulin resistance. Gene-based analyses identified further biologically plausible loci, suggesting that additional loci beyond those reaching genome-wide significance are likely to represent real associations. This conclusion is supported by an excess of directionally consistent and nominally significant signals between discovery and follow-up studies. Functional analysis of these newly discovered loci will further improve our understanding of glycemic control.
Keywords: Adult; Animals; Blood Glucose; Fasting; Female; Gene Frequency; Genome-Wide Association Study; Humans; Insulin; Male; Metabolic Networks and Pathways; Mice; Osmolar Concentration; Quantitative Trait Loci

Lipid-related markers and cardiovascular disease prediction. - Di Angelantonio, Emanuele; Gao, Pei; Pennells, Lisa; Kaptoge, Stephen; Caslake, Muriel; Thompson, Alexander; Butterworth, Adam S; Sarwar, Nadeem; Wormser, David; Saleheen, Danish; Ballantyne, Christie M; Psaty, Bruce M; et al. (JAMA, 2012)
CONTEXT: The value of assessing various emerging lipid-related markers for prediction of first cardiovascular events is debated. OBJECTIVE: To determine whether adding information on apolipoprotein B and apolipoprotein A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 to total cholesterol and high-density lipoprotein cholesterol (HDL-C) improves cardiovascular disease (CVD) risk prediction. DESIGN, SETTING, AND PARTICIPANTS: Individual records were available for 165,544 participants without baseline CVD in 37 prospective cohorts (calendar years of recruitment: 1968-2007) with up to 15,126 incident fatal or nonfatal CVD outcomes (10,132 CHD and 4994 stroke outcomes) during a median follow-up of 10.4 years (interquartile range, 7.6-14 years). MAIN OUTCOME MEASURES: Discrimination of CVD outcomes and reclassification of participants across predicted 10-year risk categories of low (<10%), intermediate (10%-<20%), and high (≥20%) risk. RESULTS: The addition of information on various lipid-related markers to total cholesterol, HDL-C, and other conventional risk factors yielded improvement in the model's discrimination: C-index change, 0.0006 (95% CI, 0.0002-0.0009) for the combination of apolipoprotein B and A-I; 0.0016 (95% CI, 0.0009-0.0023) for lipoprotein(a); and 0.0018 (95% CI, 0.0010-0.0026) for lipoprotein-associated phospholipase A2 mass. Net reclassification improvements were less than 1% with the addition of each of these markers to risk scores containing conventional risk factors. We estimated that for 100,000 adults aged 40 years or older, 15,436 would be initially classified at intermediate risk using conventional risk factors alone. Additional testing with a combination of apolipoprotein B and A-I would reclassify 1.1%; lipoprotein(a), 4.1%; and lipoprotein-associated phospholipase A2 mass, 2.7% of people to a 20% or higher predicted CVD risk category and, therefore, in need of statin treatment under Adult Treatment Panel III guidelines. CONCLUSION: In a study of individuals without known CVD, the addition of information on the combination of apolipoprotein B and A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 mass to risk scores containing total cholesterol and HDL-C led to slight improvement in CVD prediction.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cholesterol, HDL; Cohort Studies; Female; Humans; Lipoproteins; Male; Middle Aged; Risk Assessment

Long-term assessment of inflammation and healthy aging in late life: the Cardiovascular Health Study All Stars. - Jenny, Nancy S; French, Benjamin; Arnold, Alice M; Strotmeyer, Elsa S; Cushman, Mary; Chaves, Paulo H M; Ding, Jingzhong; Fried, Linda P; Kritchevsky, Stephen B; Rifkin, Dena E; Sarnak, Mark J; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2012)
BACKGROUND: Associations of inflammation with age-related pathologies are documented; however, it is not understood how changes in inflammation over time impact healthy aging. METHODS: We examined associations of long-term change in C-reactive protein (CRP) and interleukin-6 (IL-6) with concurrent onset of physical and cognitive impairment, subsequent cardiovascular disease (CVD), and mortality in 1,051 participants in the Cardiovascular Health Study All Stars Study. Biomarkers were measured in 1996-1997 and 2005-2006. RESULTS: In 2005-2006, median age was 84.9 years, 63% were women and 17% non-white; 21% had at least a doubling in CRP over time and 23% had at least a doubling in IL-6. Adjusting for demographics, CVD risk factors, and 1996-1997 CRP level, each doubling in CRP change over 9 years was associated with higher risk of physical or cognitive impairment (odds ratio 1.29; 95% confidence interval 1.15, 1.45). Results were similar for IL-6 (1.45; 1.20, 1.76). A doubling in IL-6 change over time, but not CRP, was associated with incident CVD events; hazard ratio (95% confidence interval) 1.34 (1.03, 1.75). Doubling in change in each biomarker was individually associated with mortality (CRP: 1.12 [1.03, 1.22]; IL-6 1.39 [1.16, 1.65]). In models containing both change and 2005-2006 level, only level was associated with CVD events and mortality. CONCLUSIONS: Although increases in inflammation markers over 9 years were associated with higher concurrent risk of functional impairment and subsequent CVD events and mortality, final levels of each biomarker appeared to be more important in determining risk of subsequent events than change over time.
Keywords: Aged; Aged, 80 and over; Aging; C-Reactive Protein; Cardiovascular Diseases; Cognition; Cohort Studies; Cross-Sectional Studies; Female; Humans; Inflammation; Inflammation Mediators; Interleukin-6; Longitudinal Studies; Male; Risk Factors; Vermont

Markers of inflammation in prevalent and incident Parkinson's disease in the Cardiovascular Health Study. - Ton, Thanh G N; Jain, Samay; Biggs, Mary L; Thacker, Evan L; Strotmeyer, Elsa S; Boudreau, Robert; Newman, Anne B; Longstreth, W T; Checkoway, Harvey (Parkinsonism Relat Disord, 2012)
BACKGROUND: Studies demonstrate existence of inflammation in prevalent Parkinson's disease (PD). We assessed associations of baseline levels of inflammatory markers with prevalent PD at baseline (1989) and incident PD identified over 13 years of follow-up of the Cardiovascular Health Study. METHODS: Blood samples at baseline were measured for fibrinogen, interleukin-6, tumor necrosis factor-α, C-reactive protein, albumin, and white blood cells. The analysis included 60 prevalent and 154 incident PD cases. RESULTS: Risk of prevalent PD was significantly higher per doubling of IL-6 among women (odds ratio [OR]=1.5, 95% confidence interval [CI]: 1.0, 2.4) and WBC among men (OR: 2.4, 95% CI: 1.2, 4.9) in multivariate models. Risk of incident PD was not associated with higher levels of any biomarker after adjusting for age, smoking, African American race, and history of diabetes. Inverse associations with incident PD were observed per doubling of C-reactive protein (OR=0.9; 95% CI: 0.8, 1.0) and of fibrinogen among women (OR=0.4; 95% CI: 0.2, 0.8). CONCLUSIONS: Although inflammation exists in PD, it may not represent an etiologic factor. Our findings suggest the need for larger studies that measure inflammatory markers before PD onset.
Keywords: Aged; Aged, 80 and over; Albumins; Biomarkers; C-Reactive Protein; Enzyme-Linked Immunosorbent Assay; Female; Fibrinogen; Humans; Incidence; Inflammation; Interleukin-6; Leukocyte Count; Male; Parkinson Disease; Prevalence; Risk Factors; Tumor Necrosis Factor-alpha

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Subclinical thyroid dysfunction and the risk of heart failure events: an individual participant data analysis from 6 prospective cohorts. - Gencer, Bariş; Collet, Tinh-Hai; Virgini, Vanessa; Bauer, Douglas C; Gussekloo, Jacobijn; Cappola, Anne R; Nanchen, David; den Elzen, Wendy P J; Balmer, Philippe; Luben, Robert N; Iacoviello, Massimo; Triggiani, Vincenzo; et al. (Circulation, 2012)
BACKGROUND: American College of Cardiology/American Heart Association guidelines for the diagnosis and management of heart failure recommend investigating exacerbating conditions such as thyroid dysfunction, but without specifying the impact of different thyroid-stimulation hormone (TSH) levels. Limited prospective data exist on the association between subclinical thyroid dysfunction and heart failure events. METHODS AND RESULTS: We performed a pooled analysis of individual participant data using all available prospective cohorts with thyroid function tests and subsequent follow-up of heart failure events. Individual data on 25 390 participants with 216 248 person-years of follow-up were supplied from 6 prospective cohorts in the United States and Europe. Euthyroidism was defined as TSH of 0.45 to 4.49 mIU/L, subclinical hypothyroidism as TSH of 4.5 to 19.9 mIU/L, and subclinical hyperthyroidism as TSH <0.45 mIU/L, the last two with normal free thyroxine levels. Among 25 390 participants, 2068 (8.1%) had subclinical hypothyroidism and 648 (2.6%) had subclinical hyperthyroidism. In age- and sex-adjusted analyses, risks of heart failure events were increased with both higher and lower TSH levels (P for quadratic pattern <0.01); the hazard ratio was 1.01 (95% confidence interval, 0.81-1.26) for TSH of 4.5 to 6.9 mIU/L, 1.65 (95% confidence interval, 0.84-3.23) for TSH of 7.0 to 9.9 mIU/L, 1.86 (95% confidence interval, 1.27-2.72) for TSH of 10.0 to 19.9 mIU/L (P for trend <0.01) and 1.31 (95% confidence interval, 0.88-1.95) for TSH of 0.10 to 0.44 mIU/L and 1.94 (95% confidence interval, 1.01-3.72) for TSH <0.10 mIU/L (P for trend=0.047). Risks remained similar after adjustment for cardiovascular risk factors. CONCLUSION: Risks of heart failure events were increased with both higher and lower TSH levels, particularly for TSH ≥10 and <0.10 mIU/L.
Keywords: Adult; Aged; Aged, 80 and over; Comorbidity; Female; Follow-Up Studies; Heart Failure; Humans; Hypothyroidism; Male; Middle Aged; Prospective Studies; Risk; Risk Factors; Sensitivity and Specificity; Thyrotropin; Thyroxine

Telomere-associated polymorphisms correlate with cardiovascular disease mortality in Caucasian women: the Cardiovascular Health Study. - Burnett-Hartman, Andrea N; Fitzpatrick, Annette L; Kronmal, Richard A; Psaty, Bruce M; Jenny, Nancy S; Bis, Josh C; Tracy, Russ P; Kimura, Masayuki; Aviv, Abraham (Mech Ageing Dev, 2012)
Leukocyte telomere length (LTL) is linked to cardiovascular disease (CVD); however, it is unclear if LTL has an etiologic role in CVD. To gain insight into the LTL and CVD relationship, a cohort study of CVD mortality and single nucleotide polymorphisms (SNPs) in OBFC1 and TERC, genes related to LTL, was conducted among 3271 Caucasian participants ages ≥65 years enrolled 1989-1990 in the Cardiovascular Health Study. Leukocyte DNA was genotyped for SNPs in OBFC1 (rs4387287 and rs9419958) and TERC (rs3772190) that were previously associated with LTL through genome-wide association studies. Cox regression was used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs). The OBFC1 SNPs were in linkage disequilibrium (r(2)=0.99), and both SNPs were similarly associated with CVD mortality in women. For women, there was a decreased risk of CVD death associated with the minor allele (rs4387287), HR=0.7; 95% CI: 0.5-0.9 (CC vs. AC) and HR=0.5; 95% CI: 0.20-1.4 (CC vs. AA) (P-trend <0.01). For men there was no association, HR=1.0; 95% CI: 0.7-1.3 (CC vs. AC) and HR=1.7; 95% CI: 0.8-3.6 (CC vs. AA) (P-trend=0.64). These findings support the hypothesis that telomere biology and associated genes may play a role in CVD-related death, particularly among women.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Humans; Leukocytes; Male; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Risk; RNA; Sex Factors; Telomerase; Telomere

Ultraconserved elements in the human genome: association and transmission analyses of highly constrained single-nucleotide polymorphisms. - Chiang, Charleston W K; Liu, Ching-Ti; Lettre, Guillaume; Lange, Leslie A; Jorgensen, Neal W; Keating, Brendan J; Vedantam, Sailaja; Nock, Nora L; Franceschini, Nora; Reiner, Alex P; Demerath, Ellen W; Boerwinkle, Eric; et al. (Genetics, 2012)
Ultraconserved elements in the human genome likely harbor important biological functions as they are dosage sensitive and are able to direct tissue-specific expression. Because they are under purifying selection, variants in these elements may have a lower frequency in the population but a higher likelihood of association with complex traits. We tested a set of highly constrained SNPs (hcSNPs) distributed genome-wide among ultraconserved and nearly ultraconserved elements for association with seven traits related to reproductive (age at natural menopause, number of children, age at first child, and age at last child) and overall [longevity, body mass index (BMI), and height] fitness. Using up to 24,047 European-American samples from the National Heart, Lung, and Blood Institute Candidate Gene Association Resource (CARe), we observed an excess of associations with BMI and height. In an independent replication panel the most strongly associated SNPs showed an 8.4-fold enrichment of associations at the nominal level, including three variants in previously identified loci and one in a locus (DENND1A) previously shown to be associated with polycystic ovary syndrome. Finally, using 1430 family trios, we showed that the transmissions from heterozygous parents to offspring of the derived alleles of rare (frequency ≤ 0.5%) hcSNPs are not biased, particularly after adjusting for the rates of genotype missingness and error in the data. The lack of transmission bias ruled out an immediately and strongly deleterious effect due to the rare derived alleles, consistent with the observation that mice homozygous for the deletion of ultraconserved elements showed no overt phenotype. Our study also illustrated the importance of carefully modeling potential technical confounders when analyzing genotype data of rare variants.
Keywords: Alleles; Animals; Body Height; Body Mass Index; Child; Conserved Sequence; Dogs; Evolution, Molecular; Female; Genetic Fitness; Genetic Variation; Genome, Human; Genotype; Humans; Inheritance Patterns; Male; Mice; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Rats; Reproduction; Young Adult

Association of functional polymorphism rs2231142 (Q141K) in the ABCG2 gene with serum uric acid and gout in 4 US populations: the PAGE Study. - Zhang, Lili; Spencer, Kylee L; Voruganti, V Saroja; Jorgensen, Neal W; Fornage, Myriam; Best, Lyle G; Brown-Gentry, Kristin D; Cole, Shelley A; Crawford, Dana C; Deelman, Ewa; Franceschini, Nora; Gaffo, Angelo L; et al. (Am J Epidemiol, 2013)
A loss-of-function mutation (Q141K, rs2231142) in the ATP-binding cassette, subfamily G, member 2 gene (ABCG2) has been shown to be associated with serum uric acid levels and gout in Asians, Europeans, and European and African Americans; however, less is known about these associations in other populations. Rs2231142 was genotyped in 22,734 European Americans, 9,720 African Americans, 3,849 Mexican Americans, and 3,550 American Indians in the Population Architecture using Genomics and Epidemiology (PAGE) Study (2008-2012). Rs2231142 was significantly associated with serum uric acid levels (P = 2.37 × 10(-67), P = 3.98 × 10(-5), P = 6.97 × 10(-9), and P = 5.33 × 10(-4) in European Americans, African Americans, Mexican Americans, and American Indians, respectively) and gout (P = 2.83 × 10(-10), P = 0.01, and P = 0.01 in European Americans, African Americans, and Mexican Americans, respectively). Overall, the T allele was associated with a 0.24-mg/dL increase in serum uric acid level (P = 1.37 × 10(-80)) and a 1.75-fold increase in the odds of gout (P = 1.09 × 10(-12)). The association between rs2231142 and serum uric acid was significantly stronger in men, postmenopausal women, and hormone therapy users compared with their counterparts. The association with gout was also significantly stronger in men than in women. These results highlight a possible role of sex hormones in the regulation of ABCG2 urate transporter and its potential implications for the prevention, diagnosis, and treatment of hyperuricemia and gout.
Keywords: Adult; African Americans; Age Distribution; ATP-Binding Cassette Transporters; Comorbidity; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Gout; Hormone Replacement Therapy; Humans; Indians, North American; Male; Mexican Americans; Middle Aged; Neoplasm Proteins; Polymorphism, Genetic; Postmenopause; Sex Distribution; United States; Uric Acid

Common FABP4 genetic variants and plasma levels of fatty acid binding protein 4 in older adults. - Mukamal, Kenneth J; Wilk, Jemma B; Biggs, Mary L; Jensen, Majken K; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Mozaffarian, Dariush; Psaty, Bruce M; Siscovick, David S; Djoussé, Luc (Lipids, 2013)
We examined common variants in the fatty acid binding protein 4 gene (FABP4) and plasma levels of FABP4 in adults aged 65 and older from the Cardiovascular Health Study. We genotyped rs16909187, rs1054135, rs16909192, rs10808846, rs7018409, rs2290201, and rs6992708 and measured circulating FABP4 levels among 3190 European Americans and 660 African Americans. Among European Americans, the minor alleles of six single nucleotide polymorphisms (SNP) were associated with lower FABP4 levels (all p ≤ 0.01). Among African Americans, the SNP with the lowest minor allele frequency was associated with lower FABP4 levels (p = 0.015). The C-A haplotype of rs16909192 and rs2290201 was associated with lower FABP4 levels in both European Americans (frequency = 16 %; p = 0.001) and African Americans (frequency = 8 %; p = 0.04). The haplotype combined a SNP in the first intron with one in the 3'untranslated region. However, the alleles associated with lower FABP4 levels were associated with higher fasting glucose in meta-analyses from the MAGIC consortium. These results demonstrate associations of common SNP and haplotypes in the FABP4 gene with lower plasma FABP4 but higher fasting glucose levels.
Keywords: African Americans; Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Fatty Acid-Binding Proteins; Female; Gene Frequency; Genetic Association Studies; Haplotypes; Humans; Insulin; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide

Common genetic loci influencing plasma homocysteine concentrations and their effect on risk of coronary artery disease. - van Meurs, Joyce B J; Paré, Guillaume; Schwartz, Stephen M; Hazra, Aditi; Tanaka, Toshiko; Vermeulen, Sita H; Cotlarciuc, Ioana; Yuan, Xin; Mälarstig, Anders; Bandinelli, Stefania; Bis, Joshua C; Blom, Henk; et al. (Am J Clin Nutr, 2013)
BACKGROUND: The strong observational association between total homocysteine (tHcy) concentrations and risk of coronary artery disease (CAD) and the null associations in the homocysteine-lowering trials have prompted the need to identify genetic variants associated with homocysteine concentrations and risk of CAD. OBJECTIVE: We tested whether common genetic polymorphisms associated with variation in tHcy are also associated with CAD. DESIGN: We conducted a meta-analysis of genome-wide association studies (GWAS) on tHcy concentrations in 44,147 individuals of European descent. Polymorphisms associated with tHcy (P < 10(⁻⁸) were tested for association with CAD in 31,400 cases and 92,927 controls. RESULTS: Common variants at 13 loci, explaining 5.9% of the variation in tHcy, were associated with tHcy concentrations, including 6 novel loci in or near MMACHC (2.1 × 10⁻⁹), SLC17A3 (1.0 × 10⁻⁸), GTPB10 (1.7 × 10⁻⁸), CUBN (7.5 × 10⁻¹⁰), HNF1A (1.2 × 10⁻¹²)), and FUT2 (6.6 × 10⁻⁹), and variants previously reported at or near the MTHFR, MTR, CPS1, MUT, NOX4, DPEP1, and CBS genes. Individuals within the highest 10% of the genotype risk score (GRS) had 3-μmol/L higher mean tHcy concentrations than did those within the lowest 10% of the GRS (P = 1 × 10⁻³⁶). The GRS was not associated with risk of CAD (OR: 1.01; 95% CI: 0.98, 1.04; P = 0.49). CONCLUSIONS: We identified several novel loci that influence plasma tHcy concentrations. Overall, common genetic variants that influence plasma tHcy concentrations are not associated with risk of CAD in white populations, which further refutes the causal relevance of moderately elevated tHcy concentrations and tHcy-related pathways for CAD.
Keywords: Coronary Artery Disease; Genes; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homocysteine; Humans; Polymorphism, Genetic; Risk Factors

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Common variants in Mendelian kidney disease genes and their association with renal function. - Parsa, Afshin; Fuchsberger, Christian; Köttgen, Anna; O'Seaghdha, Conall M; Pattaro, Cristian; de Andrade, Mariza; Chasman, Daniel I; Teumer, Alexander; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; et al. (J Am Soc Nephrol, 2013)
Many common genetic variants identified by genome-wide association studies for complex traits map to genes previously linked to rare inherited Mendelian disorders. A systematic analysis of common single-nucleotide polymorphisms (SNPs) in genes responsible for Mendelian diseases with kidney phenotypes has not been performed. We thus developed a comprehensive database of genes for Mendelian kidney conditions and evaluated the association between common genetic variants within these genes and kidney function in the general population. Using the Online Mendelian Inheritance in Man database, we identified 731 unique disease entries related to specific renal search terms and confirmed a kidney phenotype in 218 of these entries, corresponding to mutations in 258 genes. We interrogated common SNPs (minor allele frequency >5%) within these genes for association with the estimated GFR in 74,354 European-ancestry participants from the CKDGen Consortium. However, the top four candidate SNPs (rs6433115 at LRP2, rs1050700 at TSC1, rs249942 at PALB2, and rs9827843 at ROBO2) did not achieve significance in a stage 2 meta-analysis performed in 56,246 additional independent individuals, indicating that these common SNPs are not associated with estimated GFR. The effect of less common or rare variants in these genes on kidney function in the general population and disease-specific cohorts requires further research.
Keywords: Databases, Genetic; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Mendelian Randomization Analysis; Phenotype; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic

Discovery and refinement of loci associated with lipid levels. - Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; Beckmann, Jacques S; Bragg-Gresham, Jennifer L; et al. (Nat Genet, 2013)
Levels of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and total cholesterol are heritable, modifiable risk factors for coronary artery disease. To identify new loci and refine known loci influencing these lipids, we examined 188,577 individuals using genome-wide and custom genotyping arrays. We identify and annotate 157 loci associated with lipid levels at P < 5 × 10(-8), including 62 loci not previously associated with lipid levels in humans. Using dense genotyping in individuals of European, East Asian, South Asian and African ancestry, we narrow association signals in 12 loci. We find that loci associated with blood lipid levels are often associated with cardiovascular and metabolic traits, including coronary artery disease, type 2 diabetes, blood pressure, waist-hip ratio and body mass index. Our results demonstrate the value of using genetic data from individuals of diverse ancestry and provide insights into the biological mechanisms regulating blood lipids to guide future genetic, biological and therapeutic research.
Keywords: African Continental Ancestry Group; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Lipids; Triglycerides

Fetuin-A, type 2 diabetes, and risk of cardiovascular disease in older adults: the cardiovascular health study. - Jensen, Majken K; Bartz, Traci M; Mukamal, Kenneth J; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Rimm, Eric B; Siscovick, David S; Shlipak, Michael; Ix, Joachim H (Diabetes Care, 2013)
OBJECTIVE: Fetuin-A, a hepatic secretory protein that simultaneously inhibits arterial calcification and insulin action, is associated with type 2 diabetes, but its association with cardiovascular disease (CVD) is uncertain. Preliminary studies suggest that the association of fetuin-A with CVD might differ among individuals with or without type 2 diabetes. RESEARCH DESIGN AND METHODS: This was a prospective study of 3,810 community-living individuals older than 65 years (511 with type 2 diabetes) and free of CVD in 1992 when fetuin-A levels were measured. Participants were followed-up for incident CVD through June 2008. RESULTS: Mean age was 75 years, and 61% were women; 1,456 participants had an incident CVD event (248 among individuals with type 2 diabetes). The association of fetuin-A with CVD was modified by type 2 diabetes (P interaction = 0.02). Higher fetuin-A was associated with lower CVD risk among persons without type 2 diabetes [hazard ratio per SD 0.1 g/L higher fetuin-A, 0.93 (95% CI, 0.88-0.99)], whereas a trend in the opposite direction was observed among individuals with type 2 diabetes, although it was not statistically significant [1.07 (0.93-1.22)]. Among individuals without type 2 diabetes, similar effect modification was observed by obesity and insulin resistance. Consistently, higher fetuin-A was associated with lower CVD risk only in the subgroups without obesity or with HOMA-IR below the median [0.91 (0.85-0.97) and 0.87 (0.79-0.95), respectively]. CONCLUSIONS: The association of fetuin-A with risk of CVD differs among elderly individuals with and without insulin resistance or type 2 diabetes.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Female; Fetuins; Humans; Incidence; Longitudinal Studies; Male; Risk Factors

Fibroblast growth factor 23, bone mineral density, and risk of hip fracture among older adults: the cardiovascular health study. - Jovanovich, Anna; Bůzková, Petra; Chonchol, Michel; Robbins, John; Fink, Howard A; de Boer, Ian H; Kestenbaum, Bryan; Katz, Ronit; Carbone, Laura; Lee, Jennifer; Laughlin, Gail A; Mukamal, Kenneth J; et al. (J Clin Endocrinol Metab, 2013)
CONTEXT: Fibroblast growth factor 23 (FGF23) is a phosphaturic hormone that also inhibits calcitriol synthesis. OBJECTIVE: Our objective was to evaluate the relationships of plasma FGF23 concentrations with bone mineral density (BMD) and hip fracture in community-dwelling older adults. DESIGN AND SETTING: Linear regression and Cox proportional hazard models were used to examine the associations of plasma FGF23 concentrations with BMD and incident hip fracture, respectively. Analyses were also stratified by chronic kidney disease. PARTICIPANTS: Participants included 2008 women and 1329 men ≥65 years from the 1996 to 1997 Cardiovascular Health Study visit. MAIN OUTCOME MEASURES: Dual x-ray absorptiometry measured total hip (TH) and lumbar spine (LS) BMD in 1291 participants. Hip fracture incidence was assessed prospectively through June 30, 2008 by hospitalization records in all participants. RESULTS: Women had higher plasma FGF23 concentrations than men (75 [56-107] vs 66 [interquartile range = 52-92] relative units/mL; P < .001). After adjustment, higher FGF23 concentrations were associated with greater total hip and lumbar spine BMD in men only (β per doubling of FGF23 = 0.02, with 95% confidence interval [CI] = 0.001-0.04 g/cm(2), and 0.03 with 95% CI = 0.01-0.06 g/cm(2)). During 9.6 ± 5.1-11.0 years of follow-up, 328 hip fractures occurred. Higher FGF23 concentrations were not associated with hip fracture risk in women or men (adjusted hazard ratio = 0.95, with 95% CI = 0.78-1.15, and 1.09 with 95% CI = 0.82-1.46 per doubling of FGF23). Results did not differ by chronic kidney disease status (P > .4 for interactions). CONCLUSIONS: In this large prospective cohort of community-dwelling older adults, higher FGF23 concentrations were weakly associated with greater lumbar spine and total hip BMD but not with hip fracture risk.
Keywords: Aged; Aged, 80 and over; Bone Density; Female; Fibroblast Growth Factors; Hip Fractures; Humans; Longitudinal Studies; Male; Middle Aged; Prospective Studies; Risk; Spinal Fractures

Fibroblast growth factor 23, left ventricular mass, and left ventricular hypertrophy in community-dwelling older adults. - Jovanovich, Anna; Ix, Joachim H; Gottdiener, John; McFann, Kim; Katz, Ronit; Kestenbaum, Bryan; de Boer, Ian H; Sarnak, Mark; Shlipak, Michael G; Mukamal, Kenneth J; Siscovick, David; Chonchol, Michel (Atherosclerosis, 2013)
OBJECTIVES: In chronic kidney disease (CKD), high FGF23 concentrations are associated with left ventricular hypertrophy (LVH), cardiovascular events, and death. The associations of FGF23 with left ventricular mass (LVM) and LVH in the general population and the influence of CKD remains uncertain. METHODS: C-terminal plasma FGF23 concentrations were measured, and LVM and LVH evaluated by echocardiogram among 2255 individuals ≥65 years in the Cardiovascular Health Study. Linear regression analysis adjusting for demographics, cardiovascular, and kidney related risk factors examined the associations of FGF23 concentrations with LVM. Analyses were stratified by CKD status and adjusted linear and logistic regression analysis explored the associations of FGF23 with LVM and LVH. RESULTS: Among the entire cohort, higher FGF23 concentrations were associated with greater LVM in adjusted analyses (β = 6.71 [95% CI 4.35-9.01] g per doubling of FGF23). 32% (n = 624) had CKD (eGFR <60 mL/min/1.73 m(2) and/or urine albumin-to-creatinine ratio >30 mg/g). Associations were stronger among participants with CKD (p interaction = 0.006): LVM β = 9.71 [95% CI 5.86-13.56] g per doubling of FGF23 compared to those without CKD (β = 3.44 [95% CI 0.77, 6.11] g per doubling of FGF23). While there was no significant interaction between FGF23 and CKD for LVH (p interaction = 0.25), the OR (1.46 95% CI [1.20-1.77]) in the CKD group was statistically significant and of larger magnitude than the OR for in the no CKD group (1.12 [95% CI 0.97-1.48]). CONCLUSION: In a large cohort of older community-dwelling adults, higher FGF23 concentrations were associated with greater LVM and LVH with stronger relationships in participants with CKD.
Keywords: Aged; Female; Fibroblast Growth Factors; Heart Ventricles; Humans; Hypertrophy, Left Ventricular; Longitudinal Studies; Male; Renal Insufficiency, Chronic; Risk Factors; Ultrasonography

Fine Mapping and Identification of BMI Loci in African Americans. - Gong, Jian; Schumacher, Fredrick; Lim, Unhee; Hindorff, Lucia A; Haessler, Jeff; Buyske, Steven; Carlson, Christopher S; Rosse, Stephanie; Bůzková, Petra; Fornage, Myriam; Gross, Myron; Pankratz, Nathan; et al. (Am J Hum Genet, 2013)
Genome-wide association studies (GWASs) primarily performed in European-ancestry (EA) populations have identified numerous loci associated with body mass index (BMI). However, it is still unclear whether these GWAS loci can be generalized to other ethnic groups, such as African Americans (AAs). Furthermore, the putative functional variant or variants in these loci mostly remain under investigation. The overall lower linkage disequilibrium in AA compared to EA populations provides the opportunity to narrow in or fine-map these BMI-related loci. Therefore, we used the Metabochip to densely genotype and evaluate 21 BMI GWAS loci identified in EA studies in 29,151 AAs from the Population Architecture using Genomics and Epidemiology (PAGE) study. Eight of the 21 loci (SEC16B, TMEM18, ETV5, GNPDA2, TFAP2B, BDNF, FTO, and MC4R) were found to be associated with BMI in AAs at 5.8 × 10(-5). Within seven out of these eight loci, we found that, on average, a substantially smaller number of variants was correlated (r(2) > 0.5) with the most significant SNP in AA than in EA populations (16 versus 55). Conditional analyses revealed GNPDA2 harboring a potential additional independent signal. Moreover, Metabochip-wide discovery analyses revealed two BMI-related loci, BRE (rs116612809, p = 3.6 × 10(-8)) and DHX34 (rs4802349, p = 1.2 × 10(-7)), which were significant when adjustment was made for the total number of SNPs tested across the chip. These results demonstrate that fine mapping in AAs is a powerful approach for both narrowing in on the underlying causal variants in known loci and discovering BMI-related loci.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Body Mass Index; Female; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Young Adult

Genetic analysis of a population heavy drinking phenotype identifies risk variants in whites. - Hamidovic, Ajna; Goodloe, Robert J; Young, Taylor R; Styn, Mindi A; Mukamal, Kenneth J; Choquet, Helene; Kasberger, Jay L; Buxbaum, Sarah G; Papanicolaou, George J; White, Wendy; Volcik, Kelly; Spring, Bonnie; et al. (J Clin Psychopharmacol, 2013)
Genetic association studies thus far have used detailed diagnoses of alcoholism to identify loci associated with risk. This proof-of-concept analysis examined whether population data of lifetime heaviest alcohol consumption may be used to identify genetic loci that modulate risk. We conducted a genetic association study in European Americans between variants in approximately 2100 genes and alcohol consumption as part of the Candidate gene Association Resource project. We defined cases as individuals with a history of drinking 5 or more drinks per day almost every day of the week and controls as current light drinkers (1-5 drinks per week). We cross-validated identified single nucleotide polymorphisms in a meta-analysis of 2 cohorts of unrelated individuals--Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health Study (CHS)--and in a separate cohort of related individuals--Framingham Heart Study (FHS). The most significant variant in the meta-analysis of ARIC and CHS was rs6933598 in methylenetetrahydrofolate dehydrogenase (P = 7.46 × 10(-05)) with a P value in FHS of 0.042. The top variants in FHS were rs12249562 in cubulin (P = 3.03 × 10(-05)) and rs9839267 near cholecystokinin (P = 3.05 × 10(-05)) with a P value of 0.019 for rs9839267 in CHS. We have here shown feasibility in evaluating lifetime incidence of heavy alcohol drinking from population-based studies for the purpose of conducting genetic association analyses.
Keywords: Aged; Alcohol Drinking; Alcoholism; Case-Control Studies; European Continental Ancestry Group; Feasibility Studies; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Humans; Incidence; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk

Genetic loci for retinal arteriolar microcirculation. - Sim, Xueling; Jensen, Richard A; Ikram, M Kamran; Cotch, Mary Frances; Li, Xiaohui; Macgregor, Stuart; Xie, Jing; Smith, Albert Vernon; Boerwinkle, Eric; Mitchell, Paul; Klein, Ronald; Klein, Barbara E K; et al. (PLoS One, 2013)
Narrow arterioles in the retina have been shown to predict hypertension as well as other vascular diseases, likely through an increase in the peripheral resistance of the microcirculatory flow. In this study, we performed a genome-wide association study in 18,722 unrelated individuals of European ancestry from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium and the Blue Mountain Eye Study, to identify genetic determinants associated with variations in retinal arteriolar caliber. Retinal vascular calibers were measured on digitized retinal photographs using a standardized protocol. One variant (rs2194025 on chromosome 5q14 near the myocyte enhancer factor 2C MEF2C gene) was associated with retinal arteriolar caliber in the meta-analysis of the discovery cohorts at genome-wide significance of P-value <5×10(-8). This variant was replicated in an additional 3,939 individuals of European ancestry from the Australian Twins Study and Multi-Ethnic Study of Atherosclerosis (rs2194025, P-value = 2.11×10(-12) in combined meta-analysis of discovery and replication cohorts). In independent studies of modest sample sizes, no significant association was found between this variant and clinical outcomes including coronary artery disease, stroke, myocardial infarction or hypertension. In conclusion, we found one novel loci which underlie genetic variation in microvasculature which may be relevant to vascular disease. The relevance of these findings to clinical outcomes remains to be determined.
Keywords: Aged; Aged, 80 and over; Arterioles; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Male; MEF2 Transcription Factors; Microcirculation; Middle Aged; Models, Genetic; Retinal Vessels

Genetic variants associated with fasting glucose and insulin concentrations in an ethnically diverse population: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Fesinmeyer, Megan D; Meigs, James B; North, Kari E; Schumacher, Fredrick R; Bůzková, Petra; Franceschini, Nora; Haessler, Jeffrey; Goodloe, Robert; Spencer, Kylee L; Voruganti, Venkata Saroja; Howard, Barbara V; Jackson, Rebecca; et al. (BMC Med Genet, 2013)
BACKGROUND: Multiple genome-wide association studies (GWAS) within European populations have implicated common genetic variants associated with insulin and glucose concentrations. In contrast, few studies have been conducted within minority groups, which carry the highest burden of impaired glucose homeostasis and type 2 diabetes in the U.S. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we investigated the association of up to 10 GWAS-identified single nucleotide polymorphisms (SNPs) in 8 genetic regions with glucose or insulin concentrations in up to 36,579 non-diabetic subjects including 23,323 European Americans (EA) and 7,526 African Americans (AA), 3,140 Hispanics, 1,779 American Indians (AI), and 811 Asians. We estimated the association between each SNP and fasting glucose or log-transformed fasting insulin, followed by meta-analysis to combine results across PAGE sites. RESULTS: Overall, our results show that 9/9 GWAS SNPs are associated with glucose in EA (p = 0.04 to 9 × 10-15), versus 3/9 in AA (p= 0.03 to 6 × 10-5), 3/4 SNPs in Hispanics, 2/4 SNPs in AI, and 1/2 SNPs in Asians. For insulin we observed a significant association with rs780094/GCKR in EA, Hispanics and AI only. CONCLUSIONS: Generalization of results across multiple racial/ethnic groups helps confirm the relevance of some of these loci for glucose and insulin metabolism. Lack of association in non-EA groups may be due to insufficient power, or to unique patterns of linkage disequilibrium.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Genomics; Hispanic Americans; Humans; Indians, North American; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Genetically elevated fetuin-A levels, fasting glucose levels, and risk of type 2 diabetes: the cardiovascular health study. - Jensen, Majken K; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Zieman, Susan J; Rimm, Eric B; Siscovick, David S; Psaty, Bruce M; Ix, Joachim H; Mukamal, Kenneth J (Diabetes Care, 2013)
OBJECTIVE: Fetuin-A levels are associated with higher risk of type 2 diabetes, but it is unknown if the association is causal. We investigated common (>5%) genetic variants in the fetuin-A gene (AHSG) fetuin-A levels, fasting glucose, and risk of type 2 diabetes. RESEARCH DESIGN AND METHODS: Genetic variation, fetuin-A levels, and fasting glucose were assessed in 2,893 Caucasian and 542 African American community-living individuals 65 years of age or older in 1992-1993. RESULTS: Common AHSG variants (rs4917 and rs2248690) were strongly associated with fetuin-A concentrations (P<0.0001). In analyses of 259 incident cases of type 2 diabetes, the single nucleotide polymorphisms (SNPs) were not associated with diabetes risk during follow-up and similar null associations were observed when 579 prevalent cases were included. As expected, higher fetuin-A levels were associated with higher fasting glucose concentrations (1.9 mg/dL [95% CI, 1.2-2.7] higher per SD in Caucasians), but Mendelian randomization analyses using both SNPs as unbiased proxies for measured fetuin-A did not support an association between genetically predicted fetuin-A levels and fasting glucose (-0.3 mg/dL [95% CI, -1.9 to 1.3] lower per SD in Caucasians). The difference between the associations of fasting glucose with actual and genetically predicted fetuin-A level was statistically significant (P=0.001). Results among the smaller sample of African Americans trended in similar directions but were statistically insignificant. CONCLUSIONS: Common variants in the AHSG gene are strongly associated with plasma fetuin-A concentrations, but not with risk of type 2 diabetes or glucose concentrations, raising the possibility that the association between fetuin-A and type 2 diabetes may not be causal.
Keywords: alpha-2-HS-Glycoprotein; Blood Glucose; Diabetes Mellitus, Type 2; Fasting; Female; Genotype; Humans; Male; Polymorphism, Single Nucleotide

Genome-wide and gene-centric analyses of circulating myeloperoxidase levels in the charge and care consortia. - Reiner, Alexander P; Hartiala, Jaana; Zeller, Tanja; Bis, Joshua C; Dupuis, Josée; Fornage, Myriam; Baumert, Jens; Kleber, Marcus E; Wild, Philipp S; Baldus, Stephan; Bielinski, Suzette J; Fontes, João D; et al. (Hum Mol Genet, 2013)
Increased systemic levels of myeloperoxidase (MPO) are associated with the risk of coronary artery disease (CAD). To identify the genetic factors that are associated with circulating MPO levels, we carried out a genome-wide association study (GWAS) and a gene-centric analysis in subjects of European ancestry and African Americans (AAs). A locus on chromosome 1q31.1 containing the complement factor H (CFH) gene was strongly associated with serum MPO levels in 9305 subjects of European ancestry (lead SNP rs800292; P = 4.89 × 10(-41)) and in 1690 AA subjects (rs505102; P = 1.05 × 10(-8)). Gene-centric analyses in 8335 subjects of European ancestry additionally identified two rare MPO coding sequence variants that were associated with serum MPO levels (rs28730837, P = 5.21 × 10(-12); rs35897051, P = 3.32 × 10(-8)). A GWAS for plasma MPO levels in 9260 European ancestry subjects identified a chromosome 17q22 region near MPO that was significantly associated (lead SNP rs6503905; P = 2.94 × 10(-12)), but the CFH locus did not exhibit evidence of association with plasma MPO levels. Functional analyses revealed that rs800292 was associated with levels of complement proteins in serum. Variants at chromosome 17q22 also had pleiotropic cis effects on gene expression. In a case-control analysis of ∼80 000 subjects from CARDIoGRAM, none of the identified single-nucleotide polymorphisms (SNPs) were associated with CAD. These results suggest that distinct genetic factors regulate serum and plasma MPO levels, which may have relevance for various acute and chronic inflammatory disorders. The clinical implications for CAD and a better understanding of the functional basis for the association of CFH and MPO variants with circulating MPO levels require further study.
Keywords: Adult; African Americans; Aged; Case-Control Studies; Complement Factor H; Coronary Artery Disease; European Continental Ancestry Group; Female; Gene Expression Regulation, Enzymologic; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Peroxidase; Polymorphism, Single Nucleotide; Young Adult

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genome-wide association of body fat distribution in African ancestry populations suggests new loci. - Liu, Ching-Ti; Monda, Keri L; Taylor, Kira C; Lange, Leslie; Demerath, Ellen W; Palmas, Walter; Wojczynski, Mary K; Ellis, Jaclyn C; Vitolins, Mara Z; Liu, Simin; Papanicolaou, George J; Irvin, Marguerite R; et al. (PLoS Genet, 2013)
Central obesity, measured by waist circumference (WC) or waist-hip ratio (WHR), is a marker of body fat distribution. Although obesity disproportionately affects minority populations, few studies have conducted genome-wide association study (GWAS) of fat distribution among those of predominantly African ancestry (AA). We performed GWAS of WC and WHR, adjusted and unadjusted for BMI, in up to 33,591 and 27,350 AA individuals, respectively. We identified loci associated with fat distribution in AA individuals using meta-analyses of GWA results for WC and WHR (stage 1). Overall, 25 SNPs with single genomic control (GC)-corrected p-values<5.0 × 10(-6) were followed-up (stage 2) in AA with WC and with WHR. Additionally, we interrogated genomic regions of previously identified European ancestry (EA) WHR loci among AA. In joint analysis of association results including both Stage 1 and 2 cohorts, 2 SNPs demonstrated association, rs2075064 at LHX2, p = 2.24×10(-8) for WC-adjusted-for-BMI, and rs6931262 at RREB1, p = 2.48×10(-8) for WHR-adjusted-for-BMI. However, neither signal was genome-wide significant after double GC-correction (LHX2: p = 6.5 × 10(-8); RREB1: p = 5.7 × 10(-8)). Six of fourteen previously reported loci for waist in EA populations were significant (p<0.05 divided by the number of independent SNPs within the region) in AA studied here (TBX15-WARS2, GRB14, ADAMTS9, LY86, RSPO3, ITPR2-SSPN). Further, we observed associations with metabolic traits: rs13389219 at GRB14 associated with HDL-cholesterol, triglycerides, and fasting insulin, and rs13060013 at ADAMTS9 with HDL-cholesterol and fasting insulin. Finally, we observed nominal evidence for sexual dimorphism, with stronger results in AA women at the GRB14 locus (p for interaction = 0.02). In conclusion, we identified two suggestive loci associated with fat distribution in AA populations in addition to confirming 6 loci previously identified in populations of EA. These findings reinforce the concept that there are fat distribution loci that are independent of generalized adiposity.
Keywords: Adiposity; African Continental Ancestry Group; Body Fat Distribution; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Genome-wide association study identifies novel loci associated with concentrations of four plasma phospholipid fatty acids in the de novo lipogenesis pathway: results from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortiu - Wu, Jason H Y; Lemaitre, Rozenn N; Manichaikul, Ani; Guan, Weihua; Tanaka, Toshiko; Foy, Millennia; Kabagambe, Edmond K; Djoussé, Luc; Siscovick, David; Fretts, Amanda M; Johnson, Catherine; King, Irena B; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND- Palmitic acid (16:0), stearic acid (18:0), palmitoleic acid (16:1n-7), and oleic acid (18:1n-9) are major saturated and monounsaturated fatty acids that affect cellular signaling and metabolic pathways. They are synthesized via de novo lipogenesis and are the main saturated and monounsaturated fatty acids in the diet. Levels of these fatty acids have been linked to diseases including type 2 diabetes mellitus and coronary heart disease. METHODS AND RESULTS- Genome-wide association studies were conducted in 5 population-based cohorts comprising 8961 participants of European ancestry to investigate the association of common genetic variation with plasma levels of these 4 fatty acids. We identified polymorphisms in 7 novel loci associated with circulating levels of ≥1 of these fatty acids. ALG14 (asparagine-linked glycosylation 14 homolog) polymorphisms were associated with higher 16:0 (P=2.7×10(-11)) and lower 18:0 (P=2.2×10(-18)). FADS1 and FADS2 (desaturases) polymorphisms were associated with higher 16:1n-7 (P=6.6×10(-13)) and 18:1n-9 (P=2.2×10(-32)) and lower 18:0 (P=1.3×10(-20)). LPGAT1 (lysophosphatidylglycerol acyltransferase) polymorphisms were associated with lower 18:0 (P=2.8×10(-9)). GCKR (glucokinase regulator; P=9.8×10(-10)) and HIF1AN (factor inhibiting hypoxia-inducible factor-1; P=5.7×10(-9)) polymorphisms were associated with higher 16:1n-7, whereas PKD2L1 (polycystic kidney disease 2-like 1; P=5.7×10(-15)) and a locus on chromosome 2 (not near known genes) were associated with lower 16:1n-7 (P=4.1×10(-8)). CONCLUSIONS- Our findings provide novel evidence that common variations in genes with diverse functions, including protein-glycosylation, polyunsaturated fatty acid metabolism, phospholipid modeling, and glucose- and oxygen-sensing pathways, are associated with circulating levels of 4 fatty acids in the de novo lipogenesis pathway. These results expand our knowledge of genetic factors relevant to de novo lipogenesis and fatty acid biology.
Keywords: Adult; Aged; Chromosomes, Human, Pair 2; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Fatty Acids, Monounsaturated; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Lipogenesis; Male; Middle Aged; Oleic Acid; Palmitic Acid; Polymorphism, Single Nucleotide; Stearic Acids

A genome-wide association study of depressive symptoms. - Hek, Karin; Demirkan, Ayse; Lahti, Jari; Terracciano, Antonio; Teumer, Alexander; Cornelis, Marilyn C; Amin, Najaf; Bakshis, Erin; Baumert, Jens; Ding, Jingzhong; Liu, Yongmei; Marciante, Kristin; et al. (Biol Psychiatry, 2013)
BACKGROUND: Depression is a heritable trait that exists on a continuum of varying severity and duration. Yet, the search for genetic variants associated with depression has had few successes. We exploit the entire continuum of depression to find common variants for depressive symptoms. METHODS: In this genome-wide association study, we combined the results of 17 population-based studies assessing depressive symptoms with the Center for Epidemiological Studies Depression Scale. Replication of the independent top hits (p<1×10(-5)) was performed in five studies assessing depressive symptoms with other instruments. In addition, we performed a combined meta-analysis of all 22 discovery and replication studies. RESULTS: The discovery sample comprised 34,549 individuals (mean age of 66.5) and no loci reached genome-wide significance (lowest p = 1.05×10(-7)). Seven independent single nucleotide polymorphisms were considered for replication. In the replication set (n = 16,709), we found suggestive association of one single nucleotide polymorphism with depressive symptoms (rs161645, 5q21, p = 9.19×10(-3)). This 5q21 region reached genome-wide significance (p = 4.78×10(-8)) in the overall meta-analysis combining discovery and replication studies (n = 51,258). CONCLUSIONS: The results suggest that only a large sample comprising more than 50,000 subjects may be sufficiently powered to detect genes for depressive symptoms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human, Pair 5; Depression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

A genome-wide association study of early menopause and the combined impact of identified variants. - Perry, John R B; Corre, Tanguy; Esko, Tõnu; Chasman, Daniel I; Fischer, Krista; Franceschini, Nora; He, Chunyan; Kutalik, Zoltán; Mangino, Massimo; Rose, Lynda M; Vernon Smith, Albert; Stolk, Lisette; et al. (Hum Mol Genet, 2013)
Early menopause (EM) affects up to 10% of the female population, reducing reproductive lifespan considerably. Currently, it constitutes the leading cause of infertility in the western world, affecting mainly those women who postpone their first pregnancy beyond the age of 30 years. The genetic aetiology of EM is largely unknown in the majority of cases. We have undertaken a meta-analysis of genome-wide association studies (GWASs) in 3493 EM cases and 13 598 controls from 10 independent studies. No novel genetic variants were discovered, but the 17 variants previously associated with normal age at natural menopause as a quantitative trait (QT) were also associated with EM and primary ovarian insufficiency (POI). Thus, EM has a genetic aetiology which overlaps variation in normal age at menopause and is at least partly explained by the additive effects of the same polygenic variants. The combined effect of the common variants captured by the single nucleotide polymorphism arrays was estimated to account for ∼30% of the variance in EM. The association between the combined 17 variants and the risk of EM was greater than the best validated non-genetic risk factor, smoking.
Keywords: Case-Control Studies; Female; Gene Frequency; Genome-Wide Association Study; Humans; Menopause, Premature; Polymorphism, Single Nucleotide; Primary Ovarian Insufficiency; Quantitative Trait Loci; Risk

Genome-wide association study of retinopathy in individuals without diabetes. - Jensen, Richard A; Sim, Xueling; Li, Xiaohui; Cotch, Mary Frances; Ikram, M Kamran; Holliday, Elizabeth G; Eiriksdottir, Gudny; Harris, Tamara B; Jonasson, Fridbert; Klein, Barbara E K; Launer, Lenore J; Smith, Albert Vernon; et al. (PLoS One, 2013)
BACKGROUND: Mild retinopathy (microaneurysms or dot-blot hemorrhages) is observed in persons without diabetes or hypertension and may reflect microvascular disease in other organs. We conducted a genome-wide association study (GWAS) of mild retinopathy in persons without diabetes. METHODS: A working group agreed on phenotype harmonization, covariate selection and analytic plans for within-cohort GWAS. An inverse-variance weighted fixed effects meta-analysis was performed with GWAS results from six cohorts of 19,411 Caucasians. The primary analysis included individuals without diabetes and secondary analyses were stratified by hypertension status. We also singled out the results from single nucleotide polymorphisms (SNPs) previously shown to be associated with diabetes and hypertension, the two most common causes of retinopathy. RESULTS: No SNPs reached genome-wide significance in the primary analysis or the secondary analysis of participants with hypertension. SNP, rs12155400, in the histone deacetylase 9 gene (HDAC9) on chromosome 7, was associated with retinopathy in analysis of participants without hypertension, -1.3±0.23 (beta ± standard error), p = 6.6×10(-9). Evidence suggests this was a false positive finding. The minor allele frequency was low (∼2%), the quality of the imputation was moderate (r(2) ∼0.7), and no other common variants in the HDAC9 gene were associated with the outcome. SNPs found to be associated with diabetes and hypertension in other GWAS were not associated with retinopathy in persons without diabetes or in subgroups with or without hypertension. CONCLUSIONS: This GWAS of retinopathy in individuals without diabetes showed little evidence of genetic associations. Further studies are needed to identify genes associated with these signs in order to help unravel novel pathways and determinants of microvascular diseases.
Keywords: Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Histone Deacetylases; Humans; Hypertension; Male; Polymorphism, Single Nucleotide; Repressor Proteins; Retinal Diseases

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Genome-wide meta-analysis of observational studies shows common genetic variants associated with macronutrient intake. - Tanaka, Toshiko; Ngwa, Julius S; van Rooij, Frank J A; Zillikens, M Carola; Wojczynski, Mary K; Frazier-Wood, Alexis C; Houston, Denise K; Kanoni, Stavroula; Lemaitre, Rozenn N; Luan, Jian'an; Mikkilä, Vera; Renstrom, Frida; et al. (Am J Clin Nutr, 2013)
BACKGROUND: Macronutrient intake varies substantially between individuals, and there is evidence that this variation is partly accounted for by genetic variants. OBJECTIVE: The objective of the study was to identify common genetic variants that are associated with macronutrient intake. DESIGN: We performed 2-stage genome-wide association (GWA) meta-analysis of macronutrient intake in populations of European descent. Macronutrients were assessed by using food-frequency questionnaires and analyzed as percentages of total energy consumption from total fat, protein, and carbohydrate. From the discovery GWA (n = 38,360), 35 independent loci associated with macronutrient intake at P < 5 × 10(-6) were identified and taken forward to replication in 3 additional cohorts (n = 33,533) from the DietGen Consortium. For one locus, fat mass obesity-associated protein (FTO), cohorts with Illumina MetaboChip genotype data (n = 7724) provided additional replication data. RESULTS: A variant in the chromosome 19 locus (rs838145) was associated with higher carbohydrate (β ± SE: 0.25 ± 0.04%; P = 1.68 × 10(-8)) and lower fat (β ± SE: -0.21 ± 0.04%; P = 1.57 × 10(-9)) consumption. A candidate gene in this region, fibroblast growth factor 21 (FGF21), encodes a fibroblast growth factor involved in glucose and lipid metabolism. The variants in this locus were associated with circulating FGF21 protein concentrations (P < 0.05) but not mRNA concentrations in blood or brain. The body mass index (BMI)-increasing allele of the FTO variant (rs1421085) was associated with higher protein intake (β ± SE: 0.10 ± 0.02%; P = 9.96 × 10(-10)), independent of BMI (after adjustment for BMI, β ± SE: 0.08 ± 0.02%; P = 3.15 × 10(-7)). CONCLUSION: Our results indicate that variants in genes involved in nutrient metabolism and obesity are associated with macronutrient consumption in humans. Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetic and Environmental Determinants of Triglycerides), NCT01331512 (InCHIANTI Study), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Alleles; Atherosclerosis; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fibroblast Growth Factors; Follow-Up Studies; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Life Style; Obesity; Polymorphism, Single Nucleotide; Prospective Studies; Quantitative Trait Loci; Surveys and Questionnaires

Higher magnesium intake is associated with lower fasting glucose and insulin, with no evidence of interaction with select genetic loci, in a meta-analysis of 15 CHARGE Consortium Studies. - Hruby, Adela; Ngwa, Julius S; Renstrom, Frida; Wojczynski, Mary K; Ganna, Andrea; Hallmans, Göran; Houston, Denise K; Jacques, Paul F; Kanoni, Stavroula; Lehtimäki, Terho; Lemaitre, Rozenn N; Manichaikul, Ani; et al. (J Nutr, 2013)
Favorable associations between magnesium intake and glycemic traits, such as fasting glucose and insulin, are observed in observational and clinical studies, but whether genetic variation affects these associations is largely unknown. We hypothesized that single nucleotide polymorphisms (SNPs) associated with either glycemic traits or magnesium metabolism affect the association between magnesium intake and fasting glucose and insulin. Fifteen studies from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided data from up to 52,684 participants of European descent without known diabetes. In fixed-effects meta-analyses, we quantified 1) cross-sectional associations of dietary magnesium intake with fasting glucose (mmol/L) and insulin (ln-pmol/L) and 2) interactions between magnesium intake and SNPs related to fasting glucose (16 SNPs), insulin (2 SNPs), or magnesium (8 SNPs) on fasting glucose and insulin. After adjustment for age, sex, energy intake, BMI, and behavioral risk factors, magnesium (per 50-mg/d increment) was inversely associated with fasting glucose [β = -0.009 mmol/L (95% CI: -0.013, -0.005), P < 0.0001] and insulin [-0.020 ln-pmol/L (95% CI: -0.024, -0.017), P < 0.0001]. No magnesium-related SNP or interaction between any SNP and magnesium reached significance after correction for multiple testing. However, rs2274924 in magnesium transporter-encoding TRPM6 showed a nominal association (uncorrected P = 0.03) with glucose, and rs11558471 in SLC30A8 and rs3740393 near CNNM2 showed a nominal interaction (uncorrected, both P = 0.02) with magnesium on glucose. Consistent with other studies, a higher magnesium intake was associated with lower fasting glucose and insulin. Nominal evidence of TRPM6 influence and magnesium interaction with select loci suggests that further investigation is warranted.
Keywords: Blood Glucose; Female; Genetic Loci; Humans; Insulin; Magnesium; Male; Polymorphism, Single Nucleotide; Trace Elements; TRPM Cation Channels

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Insights into the genetic architecture of early stage age-related macular degeneration: a genome-wide association study meta-analysis. - Holliday, Elizabeth G; Smith, Albert V; Cornes, Belinda K; Buitendijk, Gabriëlle H S; Jensen, Richard A; Sim, Xueling; Aspelund, Thor; Aung, Tin; Baird, Paul N; Boerwinkle, Eric; Cheng, Ching Yu; van Duijn, Cornelia M; et al. (PLoS One, 2013)
Genetic factors explain a majority of risk variance for age-related macular degeneration (AMD). While genome-wide association studies (GWAS) for late AMD implicate genes in complement, inflammatory and lipid pathways, the genetic architecture of early AMD has been relatively under studied. We conducted a GWAS meta-analysis of early AMD, including 4,089 individuals with prevalent signs of early AMD (soft drusen and/or retinal pigment epithelial changes) and 20,453 individuals without these signs. For various published late AMD risk loci, we also compared effect sizes between early and late AMD using an additional 484 individuals with prevalent late AMD. GWAS meta-analysis confirmed previously reported association of variants at the complement factor H (CFH) (peak P = 1.5×10(-31)) and age-related maculopathy susceptibility 2 (ARMS2) (P = 4.3×10(-24)) loci, and suggested Apolipoprotein E (ApoE) polymorphisms (rs2075650; P = 1.1×10(-6)) associated with early AMD. Other possible loci that did not reach GWAS significance included variants in the zinc finger protein gene GLI3 (rs2049622; P = 8.9×10(-6)) and upstream of GLI2 (rs6721654; P = 6.5×10(-6)), encoding retinal Sonic hedgehog signalling regulators, and in the tyrosinase (TYR) gene (rs621313; P = 3.5×10(-6)), involved in melanin biosynthesis. For a range of published, late AMD risk loci, estimated effect sizes were significantly lower for early than late AMD. This study confirms the involvement of multiple established AMD risk variants in early AMD, but suggests weaker genetic effects on the risk of early AMD relative to late AMD. Several biological processes were suggested to be potentially specific for early AMD, including pathways regulating RPE cell melanin content and signalling pathways potentially involved in retinal regeneration, generating hypotheses for further investigation.
Keywords: Apolipoproteins E; Complement Factor H; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Kruppel-Like Transcription Factors; Macular Degeneration; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Zinc Finger Protein Gli3

Investigation of gene-by-sex interactions for lipid traits in diverse populations from the population architecture using genomics and epidemiology study. - Taylor, Kira C; Carty, Cara L; Dumitrescu, Logan; Bůzková, Petra; Cole, Shelley A; Hindorff, Lucia; Schumacher, Fred R; Wilkens, Lynne R; Shohet, Ralph V; Quibrera, P Miguel; Johnson, Karen C; Henderson, Brian E; et al. (BMC Genet, 2013)
BACKGROUND: High-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels are influenced by both genes and the environment. Genome-wide association studies (GWAS) have identified ~100 common genetic variants associated with HDL-C, LDL-C, and/or TG levels, mostly in populations of European descent, but little is known about the modifiers of these associations. Here, we investigated whether GWAS-identified SNPs for lipid traits exhibited heterogeneity by sex in the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: A sex-stratified meta-analysis was performed for 49 GWAS-identified SNPs for fasting HDL-C, LDL-C, and ln(TG) levels among adults self-identified as European American (25,013). Heterogeneity by sex was established when phet < 0.001. There was evidence for heterogeneity by sex for two SNPs for ln(TG) in the APOA1/C3/A4/A5/BUD13 gene cluster: rs28927680 (p(het) = 7.4 x 10(-7)) and rs3135506 (p(het) = 4.3 x 10(-4)one SNP in PLTP for HDL levels (rs7679; p(het) = 9.9 x 10(-4)), and one in HMGCR for LDL levels (rs12654264; p(het) = 3.1 x 10(-5)). We replicated heterogeneity by sex in five of seventeen loci previously reported by genome-wide studies (binomial p = 0.0009). We also present results for other racial/ethnic groups in the supplementary materials, to provide a resource for future meta-analyses. CONCLUSIONS: We provide further evidence for sex-specific effects of SNPs in the APOA1/C3/A4/A5/BUD13 gene cluster, PLTP, and HMGCR on fasting triglyceride levels in European Americans from the PAGE study. Our findings emphasize the need for considering context-specific effects when interpreting genetic associations emerging from GWAS, and also highlight the difficulties in replicating interaction effects across studies and across racial/ethnic groups.
Keywords: Female; Genetic Heterogeneity; Genome, Human; Genome-Wide Association Study; Humans; Lipids; Male; Polymorphism, Single Nucleotide; Population Groups

Lack of associations of ten candidate coronary heart disease risk genetic variants and subclinical atherosclerosis in four US populations: the Population Architecture using Genomics and Epidemiology (PAGE) study. - Zhang, Lili; Bůzková, Petra; Wassel, Christina L; Roman, Mary J; North, Kari E; Crawford, Dana C; Boston, Jonathan; Brown-Gentry, Kristin D; Cole, Shelley A; Deelman, Ewa; Goodloe, Robert; Wilson, Sarah; et al. (Atherosclerosis, 2013)
BACKGROUND: A number of genetic variants have been discovered by recent genome-wide association studies for their associations with clinical coronary heart disease (CHD). However, it is unclear whether these variants are also associated with the development of CHD as measured by subclinical atherosclerosis phenotypes, ankle brachial index (ABI), carotid artery intima-media thickness (cIMT) and carotid plaque. METHODS: Ten CHD risk single nucleotide polymorphisms (SNPs) were genotyped in individuals of European American (EA), African American (AA), American Indian (AI), and Mexican American (MA) ancestry in the Population Architecture using Genomics and Epidemiology (PAGE) study. In each individual study, we performed linear or logistic regression to examine population-specific associations between SNPs and ABI, common and internal cIMT, and plaque. The results from individual studies were meta-analyzed using a fixed effect inverse variance weighted model. RESULTS: None of the ten SNPs was significantly associated with ABI and common or internal cIMT, after Bonferroni correction. In the sample of 13,337 EA, 3809 AA, and 5353 AI individuals with carotid plaque measurement, the GCKR SNP rs780094 was significantly associated with the presence of plaque in AI only (OR = 1.32, 95% confidence interval: 1.17, 1.49, P = 1.08 × 10(-5)), but not in the other populations (P = 0.90 in EA and P = 0.99 in AA). A 9p21 region SNP, rs1333049, was nominally associated with plaque in EA (OR = 1.07, P = 0.02) and in AI (OR = 1.10, P = 0.05). CONCLUSIONS: We identified a significant association between rs780094 and plaque in AI populations, which needs to be replicated in future studies. There was little evidence that the index CHD risk variants identified through genome-wide association studies in EA influence the development of CHD through subclinical atherosclerosis as assessed by cIMT and ABI across ancestries.
Keywords: African Americans; Aged; Ankle Brachial Index; Asymptomatic Diseases; Carotid Artery Diseases; Carotid Intima-Media Thickness; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Indians, North American; Linear Models; Logistic Models; Male; Mexican Americans; Middle Aged; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

A meta-analysis identifies new loci associated with body mass index in individuals of African ancestry. - Monda, Keri L; Chen, Gary K; Taylor, Kira C; Palmer, Cameron; Edwards, Todd L; Lange, Leslie A; Ng, Maggie C Y; Adeyemo, Adebowale A; Allison, Matthew A; Bielak, Lawrence F; Chen, Guanjie; Graff, Mariaelisa; et al. (Nat Genet, 2013)
Genome-wide association studies (GWAS) have identified 36 loci associated with body mass index (BMI), predominantly in populations of European ancestry. We conducted a meta-analysis to examine the association of >3.2 million SNPs with BMI in 39,144 men and women of African ancestry and followed up the most significant associations in an additional 32,268 individuals of African ancestry. We identified one new locus at 5q33 (GALNT10, rs7708584, P = 3.4 × 10(-11)) and another at 7p15 when we included data from the GIANT consortium (MIR148A-NFE2L3, rs10261878, P = 1.2 × 10(-10)). We also found suggestive evidence of an association at a third locus at 6q16 in the African-ancestry sample (KLHL32, rs974417, P = 6.9 × 10(-8)). Thirty-two of the 36 previously established BMI variants showed directionally consistent effect estimates in our GWAS (binomial P = 9.7 × 10(-7)), five of which reached genome-wide significance. These findings provide strong support for shared BMI loci across populations, as well as for the utility of studying ancestrally diverse populations.
Keywords: African Americans; Body Mass Index; Case-Control Studies; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

A meta-analysis of thyroid-related traits reveals novel loci and gender-specific differences in the regulation of thyroid function. - Porcu, Eleonora; Medici, Marco; Pistis, Giorgio; Volpato, Claudia B; Wilson, Scott G; Cappola, Anne R; Bos, Steffan D; Deelen, Joris; den Heijer, Martin; Freathy, Rachel M; Lahti, Jari; Liu, Chunyu; et al. (PLoS Genet, 2013)
Thyroid hormone is essential for normal metabolism and development, and overt abnormalities in thyroid function lead to common endocrine disorders affecting approximately 10% of individuals over their life span. In addition, even mild alterations in thyroid function are associated with weight changes, atrial fibrillation, osteoporosis, and psychiatric disorders. To identify novel variants underlying thyroid function, we performed a large meta-analysis of genome-wide association studies for serum levels of the highly heritable thyroid function markers TSH and FT4, in up to 26,420 and 17,520 euthyroid subjects, respectively. Here we report 26 independent associations, including several novel loci for TSH (PDE10A, VEGFA, IGFBP5, NFIA, SOX9, PRDM11, FGF7, INSR, ABO, MIR1179, NRG1, MBIP, ITPK1, SASH1, GLIS3) and FT4 (LHX3, FOXE1, AADAT, NETO1/FBXO15, LPCAT2/CAPNS2). Notably, only limited overlap was detected between TSH and FT4 associated signals, in spite of the feedback regulation of their circulating levels by the hypothalamic-pituitary-thyroid axis. Five of the reported loci (PDE8B, PDE10A, MAF/LOC440389, NETO1/FBXO15, and LPCAT2/CAPNS2) show strong gender-specific differences, which offer clues for the known sexual dimorphism in thyroid function and related pathologies. Importantly, the TSH-associated loci contribute not only to variation within the normal range, but also to TSH values outside the reference range, suggesting that they may be involved in thyroid dysfunction. Overall, our findings explain, respectively, 5.64% and 2.30% of total TSH and FT4 trait variance, and they improve the current knowledge of the regulation of hypothalamic-pituitary-thyroid axis function and the consequences of genetic variation for hypo- or hyperthyroidism.
Keywords: Female; Genome-Wide Association Study; Humans; Hyperthyroidism; Hypothyroidism; Male; Phenotype; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Sex Characteristics; Signal Transduction; Thyroid Gland; Thyrotropin; Thyroxine

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Hum Genet, 2013)
Genome-wide association studies (GWAS) have identified many variants that influence high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and/or triglycerides. However, environmental modifiers, such as smoking, of these known genotype-phenotype associations are just recently emerging in the literature. We have tested for interactions between smoking and 49 GWAS-identified variants in over 41,000 racially/ethnically diverse samples with lipid levels from the Population Architecture Using Genomics and Epidemiology (PAGE) study. Despite their biological plausibility, we were unable to detect significant SNP × smoking interactions.
Keywords: Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Ethnic Groups; Female; Gene Frequency; Gene-Environment Interaction; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide; Prevalence; Smoking; Triglycerides; Young Adult

Obesity is associated with a lower resting oxygen saturation in the ambulatory elderly: results from the cardiovascular health study. - Kapur, Vishesh K; Wilsdon, Anthony G; Au, David; Avdalovic, Mark; Enright, Paul; Fan, Vincent S; Hansel, Nadia N; Heckbert, Susan R; Jiang, Rui; Krishnan, Jerry A; Mukamal, Kenneth; Yende, Sachin; et al. (Respir Care, 2013)
BACKGROUND: The contribution of obesity to hypoxemia has not been reported in a community-based study. Our hypothesis was that increasing obesity would be independently associated with lower SpO2 in an ambulatory elderly population. METHODS: The Cardiovascular Health Study ascertained resting SpO2 in 2,252 subjects over age 64. We used multiple linear regression to estimate the association of body mass index (BMI) with SpO2 and to adjust for potentially confounding factors. Covariates including age, sex, race, smoking, airway obstruction (based on spirometry), self reported diagnosis of emphysema, asthma, heart failure, and left ventricular function (by echocardiography) were evaluated. RESULTS: Among 2,252 subjects the mean and median SpO2 were 97.6% and 98.0% respectively; 5% of subjects had SpO2 values below 95%. BMI was negatively correlated with SpO2 (Spearman R = -0.27, P < .001). The mean difference in SpO2 between the lowest and highest BMI categories (< 25 kg/m(2) and ≥ 35 kg/m(2)) was 1.33% (95% CI 0.89-1.78%). In multivariable linear regression analysis, SpO2 was significantly inversely associated with BMI (1.4% per 10 units of BMI, 95% CI 1.2-1.6, for whites/others, and 0.87% per 10 units of BMI, 95% CI 0.47-1.27, for African Americans). CONCLUSIONS: We found a narrow distribution of SpO2 values in a community-based sample of ambulatory elderly. Obesity was a strong independent contributor to a low SpO2, with effects comparable to or greater than other factors clinically associated with lower SpO2.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Humans; Male; Obesity; Oximetry; Oxygen; Smoking; Waist Circumference

Post-genome-wide association study challenges for lipid traits: describing age as a modifier of gene-lipid associations in the Population Architecture using Genomics and Epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Ann Hum Genet, 2013)
Numerous common genetic variants that influence plasma high-density lipoprotein cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride distributions have been identified via genome-wide association studies (GWAS). However, whether or not these associations are age-dependent has largely been overlooked. We conducted an association study and meta-analysis in more than 22,000 European Americans between 49 previously identified GWAS variants and the three lipid traits, stratified by age (males: <50 or ≥50 years of age; females: pre- or postmenopausal). For each variant, a test of heterogeneity was performed between the two age strata and significant Phet values were used as evidence of age-specific genetic effects. We identified seven associations in females and eight in males that displayed suggestive heterogeneity by age (Phet < 0.05). The association between rs174547 (FADS1) and LDL-C in males displayed the most evidence for heterogeneity between age groups (Phet = 1.74E-03, I(2) = 89.8), with a significant association in older males (P = 1.39E-06) but not younger males (P = 0.99). However, none of the suggestive modifying effects survived adjustment for multiple testing, highlighting the challenges of identifying modifiers of modest SNP-trait associations despite large sample sizes.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

Racial differences in the incidence of and risk factors for atrial fibrillation in older adults: the cardiovascular health study. - Jensen, Paul N; Thacker, Evan L; Dublin, Sascha; Psaty, Bruce M; Heckbert, Susan R (J Am Geriatr Soc, 2013)
This study examined whether different associations between risk factors and atrial fibrillation (AF) according to race could explain the lower incidence of AF in blacks. Baseline risk factor information was obtained from interviews, clinical examinations, and echocardiography in 4,774 white and 911 black Cardiovascular Health Study participants aged 65 and older without a history of AF at baseline in 1989/90 or 1992/93. Incident AF was determined according to hospital discharge diagnosis or annual study electrocardiogram. Cox regression was used to assess associations between risk factors and race and incident AF. During a mean 11.2 years of follow-up, 1,403 whites and 182 blacks had incident AF. Associations between all examined risk factors were similar in both races, except left ventricular posterior wall thickness, which was more strongly associated with AF in blacks (per 0.2 cm, blacks: hazard ratio (HR) = 1.72, 95% confidence interval (CI) = 1.44-2.06; whites: HR = 1.30, 95% CI = 1.18-1.43). Overall, the relative risk of AF was 25% lower in blacks than whites after adjustment for age and sex (HR = 0.75, 95% CI = 0.64-0.87) and 45% lower after adjustment for all considered risk factors (HR = 0.55, 95% CI = 0.35-0.88). Different associations of the considered risk factors and incident AF by race do not explain the lower incidence of AF in blacks.
Keywords: Aged; Atrial Fibrillation; Continental Population Groups; Female; Follow-Up Studies; Humans; Incidence; Male; Prevalence; Risk Assessment; Risk Factors; Stroke; United States

Replication of genetic loci for ages at menarche and menopause in the multi-ethnic Population Architecture using Genomics and Epidemiology (PAGE) study. - Carty, C L; Spencer, K L; Setiawan, V W; Fernandez-Rhodes, L; Malinowski, J; Buyske, S; Young, A; Jorgensen, N W; Cheng, I; Carlson, C S; Brown-Gentry, K; Goodloe, R; et al. (Hum Reprod, 2013)
STUDY QUESTION: Do genetic associations identified in genome-wide association studies (GWAS) of age at menarche (AM) and age at natural menopause (ANM) replicate in women of diverse race/ancestry from the Population Architecture using Genomics and Epidemiology (PAGE) Study? SUMMARY ANSWER: We replicated GWAS reproductive trait single nucleotide polymorphisms (SNPs) in our European descent population and found that many SNPs were also associated with AM and ANM in populations of diverse ancestry. WHAT IS KNOWN ALREADY: Menarche and menopause mark the reproductive lifespan in women and are important risk factors for chronic diseases including obesity, cardiovascular disease and cancer. Both events are believed to be influenced by environmental and genetic factors, and vary in populations differing by genetic ancestry and geography. Most genetic variants associated with these traits have been identified in GWAS of European-descent populations. STUDY DESIGN, SIZE, DURATION: A total of 42 251 women of diverse ancestry from PAGE were included in cross-sectional analyses of AM and ANM. MATERIALS, SETTING, METHODS: SNPs previously associated with ANM (n = 5 SNPs) and AM (n = 3 SNPs) in GWAS were genotyped in American Indians, African Americans, Asians, European Americans, Hispanics and Native Hawaiians. To test SNP associations with ANM or AM, we used linear regression models stratified by race/ethnicity and PAGE sub-study. Results were then combined in race-specific fixed effect meta-analyses for each outcome. For replication and generalization analyses, significance was defined at P < 0.01 for ANM analyses and P < 0.017 for AM analyses. MAIN RESULTS AND THE ROLE OF CHANCE: We replicated findings for AM SNPs in the LIN28B locus and an intergenic region on 9q31 in European Americans. The LIN28B SNPs (rs314277 and rs314280) were also significantly associated with AM in Asians, but not in other race/ethnicity groups. Linkage disequilibrium (LD) patterns at this locus varied widely among the ancestral groups. With the exception of an intergenic SNP at 13q34, all ANM SNPs replicated in European Americans. Three were significantly associated with ANM in other race/ethnicity populations: rs2153157 (6p24.2/SYCP2L), rs365132 (5q35/UIMC1) and rs16991615 (20p12.3/MCM8). While rs1172822 (19q13/BRSK1) was not significant in the populations of non-European descent, effect sizes showed similar trends. LIMITATIONS, REASONS FOR CAUTION: Lack of association for the GWAS SNPs in the non-European American groups may be due to differences in locus LD patterns between these groups and the European-descent populations included in the GWAS discovery studies; and in some cases, lower power may also contribute to non-significant findings. WIDER IMPLICATIONS OF THE FINDINGS: The discovery of genetic variants associated with the reproductive traits provides an important opportunity to elucidate the biological mechanisms involved with normal variation and disorders of menarche and menopause. In this study we replicated most, but not all reported SNPs in European descent populations and examined the epidemiologic architecture of these early reported variants, describing their generalizability and effect size across differing ancestral populations. Such data will be increasingly important for prioritizing GWAS SNPs for follow-up in fine-mapping and resequencing studies, as well as in translational research.
Keywords: Age Factors; Cross-Sectional Studies; Female; Genome-Wide Association Study; Genotype; Humans; Menarche; Menopause; Polymorphism, Single Nucleotide

Resequencing and clinical associations of the 9p21.3 region: a comprehensive investigation in the Framingham heart study. - Johnson, Andrew D; Hwang, Shih-Jen; Voorman, Arend; Morrison, Alanna; Peloso, Gina M; Hsu, Yi-Hsiang; Thanassoulis, George; Newton-Cheh, Christopher; Rogers, Ian S; Hoffmann, Udo; Freedman, Jane E; Fox, Caroline S; et al. (Circulation, 2013)
BACKGROUND: 9p21.3 is among the most strongly replicated regions for cardiovascular disease. There are few reports of sequencing the associated 9p21.3 interval. We set out to sequence the 9p21.3 region followed by a comprehensive study of genetic associations with clinical and subclinical cardiovascular disease and its risk factors, as well as with copy number variation and gene expression, in the Framingham Heart Study (FHS). METHODS AND RESULTS: We sequenced 281 individuals (94 with myocardial infarction, 94 with high coronary artery calcium levels, and 93 control subjects free of elevated coronary artery calcium or myocardial infarction), followed by genotyping and association in >7000 additional FHS individuals. We assessed genetic associations with clinical and subclinical cardiovascular disease, risk factor phenotypes, and gene expression levels of the protein-coding genes CDKN2A and CDKN2B and the noncoding gene ANRIL in freshly harvested leukocytes and platelets. Within this large sample, we found strong associations of 9p21.3 variants with increased risk for myocardial infarction, higher coronary artery calcium levels, and larger abdominal aorta diameters and no evidence for association with traditional cardiovascular disease risk factors. No common protein-coding variation, variants in splice donor or acceptor sites, or copy number variation events were observed. By contrast, strong associations were observed between genetic variants and gene expression, particularly for a short isoform of ANRIL and for CDKN2B. CONCLUSIONS: Our thorough genomic characterization of 9p21.3 suggests common variants likely account for observed disease associations and provides further support for the hypothesis that complex regulatory variation affecting ANRIL and CDKN2B gene expression may contribute to increased risk for clinically apparent and subclinical coronary artery disease and aortic disease.
Keywords: Calcinosis; Chromosomes, Human, Pair 9; Coronary Artery Disease; Cyclin-Dependent Kinase Inhibitor p15; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Longitudinal Studies; Male; Massachusetts; Middle Aged; Myocardial Infarction; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; RNA, Long Noncoding; Sequence Analysis, DNA

Sex-stratified genome-wide association studies including 270,000 individuals show sexual dimorphism in genetic loci for anthropometric traits. - Randall, Joshua C; Winkler, Thomas W; Kutalik, Zoltán; Berndt, Sonja I; Jackson, Anne U; Monda, Keri L; Kilpeläinen, Tuomas O; Esko, Tõnu; Mägi, Reedik; Li, Shengxu; Workalemahu, Tsegaselassie; Feitosa, Mary F; et al. (PLoS Genet, 2013)
Given the anthropometric differences between men and women and previous evidence of sex-difference in genetic effects, we conducted a genome-wide search for sexually dimorphic associations with height, weight, body mass index, waist circumference, hip circumference, and waist-to-hip-ratio (133,723 individuals) and took forward 348 SNPs into follow-up (additional 137,052 individuals) in a total of 94 studies. Seven loci displayed significant sex-difference (FDR<5%), including four previously established (near GRB14/COBLL1, LYPLAL1/SLC30A10, VEGFA, ADAMTS9) and three novel anthropometric trait loci (near MAP3K1, HSD17B4, PPARG), all of which were genome-wide significant in women (P<5×10(-8)), but not in men. Sex-differences were apparent only for waist phenotypes, not for height, weight, BMI, or hip circumference. Moreover, we found no evidence for genetic effects with opposite directions in men versus women. The PPARG locus is of specific interest due to its role in diabetes genetics and therapy. Our results demonstrate the value of sex-specific GWAS to unravel the sexually dimorphic genetic underpinning of complex traits.
Keywords: Anthropometry; Body Height; Body Mass Index; Body Weight; Body Weights and Measures; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; Waist Circumference; Waist-Hip Ratio

Simple risk model predicts incidence of atrial fibrillation in a racially and geographically diverse population: the CHARGE-AF consortium. - Alonso, Alvaro; Krijthe, Bouwe P; Aspelund, Thor; Stepas, Katherine A; Pencina, Michael J; Moser, Carlee B; Sinner, Moritz F; Sotoodehnia, Nona; Fontes, João D; Janssens, A Cecile J W; Kronmal, Richard A; Magnani, Jared W; et al. (J Am Heart Assoc, 2013)
BACKGROUND: Tools for the prediction of atrial fibrillation (AF) may identify high-risk individuals more likely to benefit from preventive interventions and serve as a benchmark to test novel putative risk factors. METHODS AND RESULTS: Individual-level data from 3 large cohorts in the United States (Atherosclerosis Risk in Communities [ARIC] study, the Cardiovascular Health Study [CHS], and the Framingham Heart Study [FHS]), including 18 556 men and women aged 46 to 94 years (19% African Americans, 81% whites) were pooled to derive predictive models for AF using clinical variables. Validation of the derived models was performed in 7672 participants from the Age, Gene and Environment-Reykjavik study (AGES) and the Rotterdam Study (RS). The analysis included 1186 incident AF cases in the derivation cohorts and 585 in the validation cohorts. A simple 5-year predictive model including the variables age, race, height, weight, systolic and diastolic blood pressure, current smoking, use of antihypertensive medication, diabetes, and history of myocardial infarction and heart failure had good discrimination (C-statistic, 0.765; 95% CI, 0.748 to 0.781). Addition of variables from the electrocardiogram did not improve the overall model discrimination (C-statistic, 0.767; 95% CI, 0.750 to 0.783; categorical net reclassification improvement, -0.0032; 95% CI, -0.0178 to 0.0113). In the validation cohorts, discrimination was acceptable (AGES C-statistic, 0.664; 95% CI, 0.632 to 0.697 and RS C-statistic, 0.705; 95% CI, 0.664 to 0.747) and calibration was adequate. CONCLUSION: A risk model including variables readily available in primary care settings adequately predicted AF in diverse populations from the United States and Europe.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Atrial Fibrillation; Cohort Studies; Diabetes Mellitus; European Continental Ancestry Group; Female; Heart Failure; Humans; Hypertension; Iceland; Incidence; Male; Middle Aged; Myocardial Infarction; Netherlands; Proportional Hazards Models; Risk Assessment; Smoking; United States

Soluble CD14: genomewide association analysis and relationship to cardiovascular risk and mortality in older adults. - Reiner, Alex P; Lange, Ethan M; Jenny, Nancy S; Chaves, Paulo H M; Ellis, Jaclyn; Li, Jin; Walston, Jeremy; Lange, Leslie A; Cushman, Mary; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2013)
OBJECTIVE: CD14 is a glycosylphosphotidylinositol-anchored membrane glycoprotein expressed on neutrophils and monocytes/macrophages that also circulates as a soluble form (sCD14). Despite the well-recognized role of CD14 in inflammation, relatively little is known about the genetic determinants of sCD14 or the relationship of sCD14 to vascular- and aging-related phenotypes. METHODS AND RESULTS: We measured baseline levels of sCD14 in >5000 European-American and black adults aged 65 years and older from the Cardiovascular Health Study, who were well characterized at baseline for atherosclerotic risk factors and subclinical cardiovascular disease, and who have been followed for clinical cardiovascular disease and mortality outcomes up to 20 years. At baseline, sCD14 generally showed strong positive correlations with traditional cardio-metabolic risk factors and with subclinical measures of vascular disease such as carotid wall thickness and ankle-brachial index (independently of traditional cardiovascular disease risk factors), and was also inversely correlated with body mass index. In genomewide association analyses of sCD14, we (1) confirmed the importance of the CD14 locus on chromosome 5q21 in European-American; (2) identified a novel African ancestry-specific allele of CD14 associated with lower sCD14 in blacks; and (3) identified a putative novel association in European-American of a nonsynonymous variant of PIGC, which encodes an enzyme required for the first step in glycosylphosphotidylinositol anchor biosynthesis. Finally, we show that, like other acute phase inflammatory biomarkers, sCD14 predicts incident cardiovascular disease, and strongly and independently predicts all-cause mortality in older adults. CONCLUSIONS: CD14 independently predicts risk mortality in older adults.
Keywords: African Americans; Age Factors; Aged; Biomarkers; Cardiovascular Diseases; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Haplotypes; Hexosyltransferases; Humans; Incidence; Inflammation Mediators; Linear Models; Lipopolysaccharide Receptors; Logistic Models; Male; Membrane Proteins; Multivariate Analysis; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

A systematic mapping approach of 16q12.2/FTO and BMI in more than 20,000 African Americans narrows in on the underlying functional variation: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Peters, Ulrike; North, Kari E; Sethupathy, Praveen; Buyske, Steve; Haessler, Jeff; Jiao, Shuo; Fesinmeyer, Megan D; Jackson, Rebecca D; Kuller, Lew H; Rajkovic, Aleksandar; Lim, Unhee; Cheng, Iona; et al. (PLoS Genet, 2013)
Genetic variants in intron 1 of the fat mass- and obesity-associated (FTO) gene have been consistently associated with body mass index (BMI) in Europeans. However, follow-up studies in African Americans (AA) have shown no support for some of the most consistently BMI-associated FTO index single nucleotide polymorphisms (SNPs). This is most likely explained by different race-specific linkage disequilibrium (LD) patterns and lower correlation overall in AA, which provides the opportunity to fine-map this region and narrow in on the functional variant. To comprehensively explore the 16q12.2/FTO locus and to search for second independent signals in the broader region, we fine-mapped a 646-kb region, encompassing the large FTO gene and the flanking gene RPGRIP1L by investigating a total of 3,756 variants (1,529 genotyped and 2,227 imputed variants) in 20,488 AAs across five studies. We observed associations between BMI and variants in the known FTO intron 1 locus: the SNP with the most significant p-value, rs56137030 (8.3 × 10(-6)) had not been highlighted in previous studies. While rs56137030was correlated at r(2)>0.5 with 103 SNPs in Europeans (including the GWAS index SNPs), this number was reduced to 28 SNPs in AA. Among rs56137030 and the 28 correlated SNPs, six were located within candidate intronic regulatory elements, including rs1421085, for which we predicted allele-specific binding affinity for the transcription factor CUX1, which has recently been implicated in the regulation of FTO. We did not find strong evidence for a second independent signal in the broader region. In summary, this large fine-mapping study in AA has substantially reduced the number of common alleles that are likely to be functional candidates of the known FTO locus. Importantly our study demonstrated that comprehensive fine-mapping in AA provides a powerful approach to narrow in on the functional candidate(s) underlying the initial GWAS findings in European populations.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Aged, 80 and over; Alleles; Body Mass Index; Chromosome Mapping; Continental Population Groups; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Obesity; Proteins

Trans-ethnic fine-mapping of lipid loci identifies population-specific signals and allelic heterogeneity that increases the trait variance explained. - Wu, Ying; Waite, Lindsay L; Jackson, Anne U; Sheu, Wayne H-H; Buyske, Steven; Absher, Devin; Arnett, Donna K; Boerwinkle, Eric; Bonnycastle, Lori L; Carty, Cara L; Cheng, Iona; Cochran, Barbara; et al. (PLoS Genet, 2013)
Genome-wide association studies (GWAS) have identified ~100 loci associated with blood lipid levels, but much of the trait heritability remains unexplained, and at most loci the identities of the trait-influencing variants remain unknown. We conducted a trans-ethnic fine-mapping study at 18, 22, and 18 GWAS loci on the Metabochip for their association with triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), respectively, in individuals of African American (n = 6,832), East Asian (n = 9,449), and European (n = 10,829) ancestry. We aimed to identify the variants with strongest association at each locus, identify additional and population-specific signals, refine association signals, and assess the relative significance of previously described functional variants. Among the 58 loci, 33 exhibited evidence of association at P<1 × 10(-4) in at least one ancestry group. Sequential conditional analyses revealed that ten, nine, and four loci in African Americans, Europeans, and East Asians, respectively, exhibited two or more signals. At these loci, accounting for all signals led to a 1.3- to 1.8-fold increase in the explained phenotypic variance compared to the strongest signals. Distinct signals across ancestry groups were identified at PCSK9 and APOA5. Trans-ethnic analyses narrowed the signals to smaller sets of variants at GCKR, PPP1R3B, ABO, LCAT, and ABCA1. Of 27 variants reported previously to have functional effects, 74% exhibited the strongest association at the respective signal. In conclusion, trans-ethnic high-density genotyping and analysis confirm the presence of allelic heterogeneity, allow the identification of population-specific variants, and limit the number of candidate SNPs for functional studies.
Keywords: African Americans; Apolipoproteins A; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Lipoproteins, HDL; Lipoproteins, LDL; Proprotein Convertases; Serine Endopeptidases; Triglycerides

Whole-genome sequence-based analysis of high-density lipoprotein cholesterol. - Morrison, Alanna C; Voorman, Arend; Johnson, Andrew D; Liu, Xiaoming; Yu, Jin; Li, Alexander; Muzny, Donna; Yu, Fuli; Rice, Kenneth; Zhu, Chengsong; Bis, Joshua; Heiss, Gerardo; et al. (Nat Genet, 2013)
We describe initial steps for interrogating whole-genome sequence data to characterize the genetic architecture of a complex trait, levels of high-density lipoprotein cholesterol (HDL-C). We report whole-genome sequencing and analysis of 962 individuals from the Cohorts for Heart and Aging Research in Genetic Epidemiology (CHARGE) studies. From this analysis, we estimate that common variation contributes more to heritability of HDL-C levels than rare variation, and screening for mendelian variants for dyslipidemia identified individuals with extreme HDL-C levels. Whole-genome sequencing analyses highlight the value of regulatory and non-protein-coding regions of the genome in addition to protein-coding regions.
Keywords: Cholesterol, HDL; Computational Biology; Databases, Genetic; Genetic Variation; Genome, Human; Genome-Wide Association Study; Genomics; Heterozygote; Humans; Open Reading Frames

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Association between the metabolic syndrome, its individual components, and unprovoked venous thromboembolism: results of a patient-level meta-analysis. - Ageno, Walter; Di Minno, Matteo N D; Ay, Cihan; Jang, Moon Ju; Hansen, John-Bjarne; Steffen, Lyn M; Vaya, Amparo; Rattazzi, Marcello; Pabinger, Ingrid; Oh, Doyeun; Di Minno, Giovanni; Braekkan, Sigrid K; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: The metabolic syndrome (MetS) may contribute to the pathogenesis of venous thromboembolism (VTE), but this association requires additional investigation. APPROACH AND RESULTS: We performed a patient-level meta-analysis of case-control and cohort studies that evaluated the role of MetS and risk of unprovoked VTE. For case-control studies, odds ratios and 95% confidence intervals were calculated using logistic regression analysis to estimate the influence of individual variables on the risk of VTE; χ(2) tests for trend were used to investigate the effect of increasing number of components of MetS on the risk of VTE and to explore the influence of abdominal obesity on this relationship. For cohort studies, hazard ratios and 95% confidence interval were calculated using multivariable Cox regression analysis. Six case-control studies were included (908 cases with unprovoked VTE and 1794 controls): in multivariate analysis, MetS was independently associated with VTE (odds ratio, 1.91; 95% confidence interval, 1.57-2.33), and both MetS and abdominal obesity were better predictors of unprovoked VTE than obesity defined by the body mass index. Two prospective cohort studies were included (26,531 subjects and 289 unprovoked VTE events): age, obesity, and abdominal obesity, but not MetS were associated with VTE. CONCLUSIONS: Case-control but not prospective cohort studies support an association between MetS and VTE. Abdominal adiposity is a strong risk factor for VTE.
Keywords: Adult; Aged; Case-Control Studies; Cohort Studies; Female; Humans; Logistic Models; Male; Metabolic Syndrome; Middle Aged; Obesity, Abdominal; Risk Factors; Venous Thromboembolism

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; African Continental Ancestry Group; Aged; Alleles; Animals; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides

Association of sick sinus syndrome with incident cardiovascular disease and mortality: the Atherosclerosis Risk in Communities study and Cardiovascular Health Study. - Alonso, Alvaro; Jensen, Paul N; Lopez, Faye L; Chen, Lin Y; Psaty, Bruce M; Folsom, Aaron R; Heckbert, Susan R (PLoS One, 2014)
BACKGROUND: Sick sinus syndrome (SSS) is a common indication for pacemaker implantation. Limited information exists on the association of sick sinus syndrome (SSS) with mortality and cardiovascular disease (CVD) in the general population. METHODS: We studied 19,893 men and women age 45 and older in the Atherosclerosis Risk in Communities (ARIC) study and the Cardiovascular Health Study (CHS), two community-based cohorts, who were without a pacemaker or atrial fibrillation (AF) at baseline. Incident SSS cases were validated by review of medical charts. Incident CVD and mortality were ascertained using standardized protocols. Multivariable Cox models were used to estimate the association of incident SSS with selected outcomes. RESULTS: During a mean follow-up of 17 years, 213 incident SSS events were identified and validated (incidence, 0.6 events per 1,000 person-years). After adjustment for confounders, SSS incidence was associated with increased mortality (hazard ratio [HR] 1.39, 95% confidence interval [CI] 1.14-1.70), coronary heart disease (HR 1.72, 95%CI 1.11-2.66), heart failure (HR 2.87, 95%CI 2.17-3.80), stroke (HR 1.56, 95%CI 0.99-2.46), AF (HR 5.75, 95%CI 4.43-7.46), and pacemaker implantation (HR 53.7, 95%CI 42.9-67.2). After additional adjustment for other incident CVD during follow-up, SSS was no longer associated with increased mortality, coronary heart disease, or stroke, but remained associated with higher risk of heart failure (HR 2.00, 95%CI 1.51-2.66), AF (HR 4.25, 95%CI 3.28-5.51), and pacemaker implantation (HR 25.2, 95%CI 19.8-32.1). CONCLUSION: Individuals who develop SSS are at increased risk of death and CVD. The mechanisms underlying these associations warrant further investigation.
Keywords: Age Distribution; Atherosclerosis; Cohort Studies; Continental Population Groups; Female; Humans; Incidence; Male; Middle Aged; Residence Characteristics; Risk; Sex Distribution; Sick Sinus Syndrome

B-type natriuretic peptide and C-reactive protein in the prediction of atrial fibrillation risk: the CHARGE-AF Consortium of community-based cohort studies. - Sinner, Moritz F; Stepas, Katherine A; Moser, Carlee B; Krijthe, Bouwe P; Aspelund, Thor; Sotoodehnia, Nona; Fontes, João D; Janssens, A Cecile J W; Kronmal, Richard A; Magnani, Jared W; Witteman, Jacqueline C; Chamberlain, Alanna M; et al. (Europace, 2014)
AIMS: B-type natriuretic peptide (BNP) and C-reactive protein (CRP) predict atrial fibrillation (AF) risk. However, their risk stratification abilities in the broad community remain uncertain. We sought to improve risk stratification for AF using biomarker information. METHODS AND RESULTS: We ascertained AF incidence in 18 556 Whites and African Americans from the Atherosclerosis Risk in Communities Study (ARIC, n=10 675), Cardiovascular Health Study (CHS, n = 5043), and Framingham Heart Study (FHS, n = 2838), followed for 5 years (prediction horizon). We added BNP (ARIC/CHS: N-terminal pro-B-type natriuretic peptide; FHS: BNP), CRP, or both to a previously reported AF risk score, and assessed model calibration and predictive ability [C-statistic, integrated discrimination improvement (IDI), and net reclassification improvement (NRI)]. We replicated models in two independent European cohorts: Age, Gene/Environment Susceptibility Reykjavik Study (AGES), n = 4467; Rotterdam Study (RS), n = 3203. B-type natriuretic peptide and CRP were significantly associated with AF incidence (n = 1186): hazard ratio per 1-SD ln-transformed biomarker 1.66 [95% confidence interval (CI), 1.56-1.76], P < 0.0001 and 1.18 (95% CI, 1.11-1.25), P < 0.0001, respectively. Model calibration was sufficient (BNP, χ(2) = 17.0; CRP, χ(2) = 10.5; BNP and CRP, χ(2) = 13.1). B-type natriuretic peptide improved the C-statistic from 0.765 to 0.790, yielded an IDI of 0.027 (95% CI, 0.022-0.032), a relative IDI of 41.5%, and a continuous NRI of 0.389 (95% CI, 0.322-0.455). The predictive ability of CRP was limited (C-statistic increment 0.003). B-type natriuretic peptide consistently improved prediction in AGES and RS. CONCLUSION: B-type natriuretic peptide, not CRP, substantially improved AF risk prediction beyond clinical factors in an independently replicated, heterogeneous population. B-type natriuretic peptide may serve as a benchmark to evaluate novel putative AF risk biomarkers.
Keywords: Aged; Atrial Fibrillation; Biomarkers; C-Reactive Protein; Europe; Female; Humans; Incidence; Male; Natriuretic Peptide, Brain; Peptide Fragments; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

The challenges of genome-wide interaction studies: lessons to learn from the analysis of HDL blood levels. - van Leeuwen, Elisabeth M; Smouter, Françoise A S; Kam-Thong, Tony; Karbalai, Nazanin; Smith, Albert V; Harris, Tamara B; Launer, Lenore J; Sitlani, Colleen M; Li, Guo; Brody, Jennifer A; Bis, Joshua C; White, Charles C; et al. (PLoS One, 2014)
Genome-wide association studies (GWAS) have revealed 74 single nucleotide polymorphisms (SNPs) associated with high-density lipoprotein cholesterol (HDL) blood levels. This study is, to our knowledge, the first genome-wide interaction study (GWIS) to identify SNP×SNP interactions associated with HDL levels. We performed a GWIS in the Rotterdam Study (RS) cohort I (RS-I) using the GLIDE tool which leverages the massively parallel computing power of Graphics Processing Units (GPUs) to perform linear regression on all genome-wide pairs of SNPs. By performing a meta-analysis together with Rotterdam Study cohorts II and III (RS-II and RS-III), we were able to filter 181 interaction terms with a p-value<1 · 10-8 that replicated in the two independent cohorts. We were not able to replicate any of these interaction term in the AGES, ARIC, CHS, ERF, FHS and NFBC-66 cohorts (Ntotal = 30,011) when adjusting for multiple testing. Our GWIS resulted in the consistent finding of a possible interaction between rs774801 in ARMC8 (ENSG00000114098) and rs12442098 in SPATA8 (ENSG00000185594) being associated with HDL levels. However, p-values do not reach the preset Bonferroni correction of the p-values. Our study suggest that even for highly genetically determined traits such as HDL the sample sizes needed to detect SNP×SNP interactions are large and the 2-step filtering approaches do not yield a solution. Here we present our analysis plan and our reservations concerning GWIS.
Keywords: Cholesterol, HDL; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Common variation in fatty acid metabolic genes and risk of incident sudden cardiac arrest. - Lemaitre, Rozenn N; Johnson, Catherine O; Hesselson, Stephanie; Sotoodehnia, Nona; Sotoodhenia, Nona; McKnight, Barbara; Sitlani, Colleen M; Rea, Thomas D; King, Irena B; Kwok, Pui-Yan; Mak, Angel; Li, Guo; et al. (Heart Rhythm, 2014)
BACKGROUND: There is limited information on genetic factors associated with sudden cardiac arrest (SCA). OBJECTIVE: To assess the association of common variation in genes in fatty acid pathways with SCA risk. METHODS: We selected 85 candidate genes and 1155 single nucleotide polymorphisms (SNPs) tagging common variation in each gene. We investigated the SNP associations with SCA in a population-based case-control study. Cases (n = 2160) were from a repository of SCA in the greater Seattle area. Controls (n = 2615), frequency-matched on age and sex, were from the same area. We used linear logistic regression to examine SNP associations with SCA. We performed permutation-based p-min tests to account for multiple comparisons within each gene. The SNP associations with a corrected P value of <.05 were then examined in a meta-analysis of these SNP associations in 9 replication studies totaling 2129 SCA cases and 23,833 noncases. RESULTS: Eight SNPs in or near 8 genes were associated with SCA risk in the discovery study, one of which was nominally significant in the replication phase (rs7737692, minor allele frequency 36%, near the LPCAT1 gene). For each copy of the minor allele, rs7737692 was associated with 13% lower SCA risk (95% confidence interval -21% to -5%) in the discovery phase and 9% lower SCA risk (95% confidence interval -16% to -1%) in the replication phase. CONCLUSIONS: While none of the associations reached significance with Bonferroni correction, a common genetic variant near LPCAT1, a gene involved in the remodeling of phospholipids, was nominally associated with incident SCA risk. Further study is needed to validate this observation.
Keywords: 1-Acylglycerophosphocholine O-Acyltransferase; Aged; Algorithms; Alleles; Case-Control Studies; Death, Sudden, Cardiac; Fatty Acids; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Polymorphism, Single Nucleotide; Risk Factors

Drug-gene interactions and the search for missing heritability: a cross-sectional pharmacogenomics study of the QT interval. - Avery, C L; Sitlani, C M; Arking, D E; Arnett, D K; Bis, J C; Boerwinkle, E; Buckley, B M; Ida Chen, Y-D; de Craen, A J M; Eijgelsheim, M; Enquobahrie, D; Evans, D S; et al. (Pharmacogenomics J, 2014)
Variability in response to drug use is common and heritable, suggesting that genome-wide pharmacogenomics studies may help explain the 'missing heritability' of complex traits. Here, we describe four independent analyses in 33 781 participants of European ancestry from 10 cohorts that were designed to identify genetic variants modifying the effects of drugs on QT interval duration (QT). Each analysis cross-sectionally examined four therapeutic classes: thiazide diuretics (prevalence of use=13.0%), tri/tetracyclic antidepressants (2.6%), sulfonylurea hypoglycemic agents (2.9%) and QT-prolonging drugs as classified by the University of Arizona Center for Education and Research on Therapeutics (4.4%). Drug-gene interactions were estimated using covariable-adjusted linear regression and results were combined with fixed-effects meta-analysis. Although drug-single-nucleotide polymorphism (SNP) interactions were biologically plausible and variables were well-measured, findings from the four cross-sectional meta-analyses were null (Pinteraction>5.0 × 10(-8)). Simulations suggested that additional efforts, including longitudinal modeling to increase statistical power, are likely needed to identify potentially important pharmacogenomic effects.
Keywords: Computer Simulation; Cross-Sectional Studies; Drug-Related Side Effects and Adverse Reactions; Electrocardiography; European Continental Ancestry Group; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Linear Models; Long QT Syndrome; Markov Chains; Pharmacogenetics; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Effects of long-term averaging of quantitative blood pressure traits on the detection of genetic associations. - Ganesh, Santhi K; Chasman, Daniel I; Larson, Martin G; Guo, Xiuqing; Verwoert, Germain; Bis, Joshua C; Gu, Xiangjun; Smith, Albert V; Yang, Min-Lee; Zhang, Yan; Ehret, Georg; Rose, Lynda M; et al. (Am J Hum Genet, 2014)
Blood pressure (BP) is a heritable, quantitative trait with intraindividual variability and susceptibility to measurement error. Genetic studies of BP generally use single-visit measurements and thus cannot remove variability occurring over months or years. We leveraged the idea that averaging BP measured across time would improve phenotypic accuracy and thereby increase statistical power to detect genetic associations. We studied systolic BP (SBP), diastolic BP (DBP), mean arterial pressure (MAP), and pulse pressure (PP) averaged over multiple years in 46,629 individuals of European ancestry. We identified 39 trait-variant associations across 19 independent loci (p < 5 × 10(-8)); five associations (in four loci) uniquely identified by our LTA analyses included those of SBP and MAP at 2p23 (rs1275988, near KCNK3), DBP at 2q11.2 (rs7599598, in FER1L5), and PP at 6p21 (rs10948071, near CRIP3) and 7p13 (rs2949837, near IGFBP3). Replication analyses conducted in cohorts with single-visit BP data showed positive replication of associations and a nominal association (p < 0.05). We estimated a 20% gain in statistical power with long-term average (LTA) as compared to single-visit BP association studies. Using LTA analysis, we identified genetic loci influencing BP. LTA might be one way of increasing the power of genetic associations for continuous traits in extant samples for other phenotypes that are measured serially over time.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Longitudinal Studies; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Enhancing case ascertainment of Parkinson's disease using Medicare claims data in a population-based cohort: the Cardiovascular Health Study. - Ton, Thanh G N; Biggs, Mary Lou; Comer, Diane; Curtis, Lesley; Hu, Shu-Ching; Thacker, Evan L; Searles Nielsen, Susan; Delaney, Joseph A; Landsittel, Douglas; Longstreth, William T; Checkoway, Harvey; Jain, Samay (Pharmacoepidemiol Drug Saf, 2014)
PURPOSE: We sought to improve a previous algorithm to ascertain Parkinson's disease (PD) in the Cardiovascular Health Study by incorporating additional data from Medicare outpatient claims. We compared our results to the previous algorithm in terms of baseline prevalence and incidence of PD, as well as associations with baseline smoking characteristics. METHODS: Our original case ascertainment used self-reported diagnosis, antiparkinsonian medication, and hospitalization discharge International Classification of Diseases-Ninth version code. In this study, we incorporated additional data from fee-for-service Medicare claims, extended follow-up time, review of hospitalization records, and adjudicated cause of death. Two movement disorders specialists adjudicated final PD status. We used logistic regression models and controlled for age, sex, African American race, and education. RESULTS: We identified 75 additional cases but reclassified 80 previously identified cases as not having PD. We observed significant inverse association with smoking status (odds ratio = 0.42; 95% confidence interval (CI) = 0.22, 0.79), and inverse linear trends with pack-years (p = 0.005), and cigarettes per day (p = 0.019) with incident PD. All estimates were stronger than those from the previous algorithm. CONCLUSIONS: Our enhanced method did not alter prevalence and incidence estimates compared with our previous algorithm. However, our enhanced method provided stronger estimates of association, potentially due to reduced level of disease misclassification.
Keywords: Aged; Aged, 80 and over; Algorithms; Antiparkinson Agents; Cohort Studies; Databases, Factual; Female; Hospitalization; Humans; Incidence; Logistic Models; Male; Medicare; Parkinson Disease; Prevalence; Prospective Studies; Smoking; Time Factors; United States

Evidence of heterogeneity by race/ethnicity in genetic determinants of QT interval. - Seyerle, Amanda A; Young, Alicia M; Jeff, Janina M; Melton, Phillip E; Jorgensen, Neal W; Lin, Yi; Carty, Cara L; Deelman, Ewa; Heckbert, Susan R; Hindorff, Lucia A; Jackson, Rebecca D; Martin, Lisa W; et al. (Epidemiology, 2014)
BACKGROUND: QT interval (QT) prolongation is an established risk factor for ventricular tachyarrhythmia and sudden cardiac death. Previous genome-wide association studies in populations of the European descent have identified multiple genetic loci that influence QT, but few have examined these loci in ethnically diverse populations. METHODS: Here, we examine the direction, magnitude, and precision of effect sizes for 21 previously reported SNPs from 12 QT loci, in populations of European (n = 16,398), African (n = 5,437), American Indian (n = 5,032), Hispanic (n = 1,143), and Asian (n = 932) descent as part of the Population Architecture using Genomics and Epidemiology (PAGE) study. Estimates obtained from linear regression models stratified by race/ethnicity were combined using inverse-variance weighted meta-analysis. Heterogeneity was evaluated using Cochran's Q test. RESULTS: Of 21 SNPs, 7 showed consistent direction of effect across all 5 populations, and an additional 9 had estimated effects that were consistent across 4 populations. Despite consistent direction of effect, 9 of 16 SNPs had evidence (P < 0.05) of heterogeneity by race/ethnicity. For these 9 SNPs, linkage disequilibrium plots often indicated substantial variation in linkage disequilibrium patterns among the various racial/ethnic groups, as well as possible allelic heterogeneity. CONCLUSIONS: These results emphasize the importance of analyzing racial/ethnic groups separately in genetic studies. Furthermore, they underscore the possible utility of trans-ethnic studies to pinpoint underlying casual variants influencing heritable traits such as QT.
Keywords: Aged; Continental Population Groups; Electrocardiography; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Long QT Syndrome; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

FTO genetic variants, dietary intake and body mass index: insights from 177,330 individuals. - Qi, Qibin; Kilpeläinen, Tuomas O; Downer, Mary K; Tanaka, Toshiko; Smith, Caren E; Sluijs, Ivonne; Sonestedt, Emily; Chu, Audrey Y; Renstrom, Frida; Lin, Xiaochen; Ängquist, Lars H; Huang, Jinyan; et al. (Hum Mol Genet, 2014)
FTO is the strongest known genetic susceptibility locus for obesity. Experimental studies in animals suggest the potential roles of FTO in regulating food intake. The interactive relation among FTO variants, dietary intake and body mass index (BMI) is complex and results from previous often small-scale studies in humans are highly inconsistent. We performed large-scale analyses based on data from 177,330 adults (154 439 Whites, 5776 African Americans and 17 115 Asians) from 40 studies to examine: (i) the association between the FTO-rs9939609 variant (or a proxy single-nucleotide polymorphism) and total energy and macronutrient intake and (ii) the interaction between the FTO variant and dietary intake on BMI. The minor allele (A-allele) of the FTO-rs9939609 variant was associated with higher BMI in Whites (effect per allele = 0.34 [0.31, 0.37] kg/m(2), P = 1.9 × 10(-105)), and all participants (0.30 [0.30, 0.35] kg/m(2), P = 3.6 × 10(-107)). The BMI-increasing allele of the FTO variant showed a significant association with higher dietary protein intake (effect per allele = 0.08 [0.06, 0.10] %, P = 2.4 × 10(-16)), and relative weak associations with lower total energy intake (-6.4 [-10.1, -2.6] kcal/day, P = 0.001) and lower dietary carbohydrate intake (-0.07 [-0.11, -0.02] %, P = 0.004). The associations with protein (P = 7.5 × 10(-9)) and total energy (P = 0.002) were attenuated but remained significant after adjustment for BMI. We did not find significant interactions between the FTO variant and dietary intake of total energy, protein, carbohydrate or fat on BMI. Our findings suggest a positive association between the BMI-increasing allele of FTO variant and higher dietary protein intake and offer insight into potential link between FTO, dietary protein intake and adiposity.
Keywords: Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Female; Gene Frequency; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins

Gender and telomere length: systematic review and meta-analysis. - Gardner, Michael; Bann, David; Wiley, Laura; Cooper, Rachel; Hardy, Rebecca; Nitsch, Dorothea; Martin-Ruiz, Carmen; Shiels, Paul; Sayer, Avan Aihie; Barbieri, Michelangela; Bekaert, Sofie; Bischoff, Claus; et al. (Exp Gerontol, 2014)
BACKGROUND: It is widely believed that females have longer telomeres than males, although results from studies have been contradictory. METHODS: We carried out a systematic review and meta-analyses to test the hypothesis that in humans, females have longer telomeres than males and that this association becomes stronger with increasing age. Searches were conducted in EMBASE and MEDLINE (by November 2009) and additional datasets were obtained from study investigators. Eligible observational studies measured telomeres for both females and males of any age, had a minimum sample size of 100 and included participants not part of a diseased group. We calculated summary estimates using random-effects meta-analyses. Heterogeneity between studies was investigated using sub-group analysis and meta-regression. RESULTS: Meta-analyses from 36 cohorts (36,230 participants) showed that on average females had longer telomeres than males (standardised difference in telomere length between females and males 0.090, 95% CI 0.015, 0.166; age-adjusted). There was little evidence that these associations varied by age group (p=1.00) or cell type (p=0.29). However, the size of this difference did vary by measurement methods, with only Southern blot but neither real-time PCR nor Flow-FISH showing a significant difference. This difference was not associated with random measurement error. CONCLUSIONS: Telomere length is longer in females than males, although this difference was not universally found in studies that did not use Southern blot methods. Further research on explanations for the methodological differences is required.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Female; Humans; Male; Middle Aged; Sex Factors; Telomere

Gene-age interactions in blood pressure regulation: a large-scale investigation with the CHARGE, Global BPgen, and ICBP Consortia. - Simino, Jeannette; Shi, Gang; Bis, Joshua C; Chasman, Daniel I; Ehret, Georg B; Gu, Xiangjun; Guo, Xiuqing; Hwang, Shih-Jen; Sijbrands, Eric; Smith, Albert V; Verwoert, Germaine C; Bragg-Gresham, Jennifer L; et al. (Am J Hum Genet, 2014)
Although age-dependent effects on blood pressure (BP) have been reported, they have not been systematically investigated in large-scale genome-wide association studies (GWASs). We leveraged the infrastructure of three well-established consortia (CHARGE, GBPgen, and ICBP) and a nonstandard approach (age stratification and metaregression) to conduct a genome-wide search of common variants with age-dependent effects on systolic (SBP), diastolic (DBP), mean arterial (MAP), and pulse (PP) pressure. In a two-staged design using 99,241 individuals of European ancestry, we identified 20 genome-wide significant (p ≤ 5 × 10(-8)) loci by using joint tests of the SNP main effect and SNP-age interaction. Nine of the significant loci demonstrated nominal evidence of age-dependent effects on BP by tests of the interactions alone. Index SNPs in the EHBP1L1 (DBP and MAP), CASZ1 (SBP and MAP), and GOSR2 (PP) loci exhibited the largest age interactions, with opposite directions of effect in the young versus the old. The changes in the genetic effects over time were small but nonnegligible (up to 1.58 mm Hg over 60 years). The EHBP1L1 locus was discovered through gene-age interactions only in whites but had DBP main effects replicated (p = 8.3 × 10(-4)) in 8,682 Asians from Singapore, indicating potential interethnic heterogeneity. A secondary analysis revealed 22 loci with evidence of age-specific effects (e.g., only in 20 to 29-year-olds). Age can be used to select samples with larger genetic effect sizes and more homogenous phenotypes, which may increase statistical power. Age-dependent effects identified through novel statistical approaches can provide insight into the biology and temporal regulation underlying BP associations.
Keywords: Adolescent; Adult; Age Factors; Aged; Blood Pressure; Cohort Studies; Humans; Middle Aged; Young Adult

Gene-centric meta-analyses for central adiposity traits in up to 57 412 individuals of European descent confirm known loci and reveal several novel associations. - Yoneyama, Sachiko; Guo, Yiran; Lanktree, Matthew B; Barnes, Michael R; Elbers, Clara C; Karczewski, Konrad J; Padmanabhan, Sandosh; Bauer, Florianne; Baumert, Jens; Beitelshees, Amber; Berenson, Gerald S; Boer, Jolanda M A; et al. (Hum Mol Genet, 2014)
Waist circumference (WC) and waist-to-hip ratio (WHR) are surrogate measures of central adiposity that are associated with adverse cardiovascular events, type 2 diabetes and cancer independent of body mass index (BMI). WC and WHR are highly heritable with multiple susceptibility loci identified to date. We assessed the association between SNPs and BMI-adjusted WC and WHR and unadjusted WC in up to 57 412 individuals of European descent from 22 cohorts collaborating with the NHLBI's Candidate Gene Association Resource (CARe) project. The study population consisted of women and men aged 20-80 years. Study participants were genotyped using the ITMAT/Broad/CARE array, which includes ∼50 000 cosmopolitan tagged SNPs across ∼2100 cardiovascular-related genes. Each trait was modeled as a function of age, study site and principal components to control for population stratification, and we conducted a fixed-effects meta-analysis. No new loci for WC were observed. For WHR analyses, three novel loci were significantly associated (P < 2.4 × 10(-6)). Previously unreported rs2811337-G near TMCC1 was associated with increased WHR (β ± SE, 0.048 ± 0.008, P = 7.7 × 10(-9)) as was rs7302703-G in HOXC10 (β = 0.044 ± 0.008, P = 2.9 × 10(-7)) and rs936108-C in PEMT (β = 0.035 ± 0.007, P = 1.9 × 10(-6)). Sex-stratified analyses revealed two additional novel signals among females only, rs12076073-A in SHC1 (β = 0.10 ± 0.02, P = 1.9 × 10(-6)) and rs1037575-A in ATBDB4 (β = 0.046 ± 0.01, P = 2.2 × 10(-6)), supporting an already established sexual dimorphism of central adiposity-related genetic variants. Functional analysis using ENCODE and eQTL databases revealed that several of these loci are in regulatory regions or regions with differential expression in adipose tissue.
Keywords: Adiposity; Adult; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Waist Circumference; Waist-Hip Ratio; Young Adult

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic determinants of age-related macular degeneration in diverse populations from the PAGE study. - Restrepo, Nicole A; Spencer, Kylee L; Goodloe, Robert; Garrett, Tiana A; Heiss, Gerardo; Bůzková, Petra; Jorgensen, Neal; Jensen, Richard A; Matise, Tara C; Hindorff, Lucia A; Klein, Barbara E K; Klein, Ronald; et al. (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Substantial progress has been made in identifying susceptibility variants for AMD in European populations; however, few studies have been conducted to understand the role these variants play in AMD risk in diverse populations. The present study aims to examine AMD risk across diverse populations in known and suspected AMD complement factor and lipid-related loci. METHODS: Targeted genotyping was performed across study sites for AMD and lipid trait-associated single nucleotide polymorphism (SNPs). Genetic association tests were performed at individual sites and then meta-analyzed using logistic regression assuming an additive genetic model stratified by self-described race/ethnicity. Participants included cases with early or late AMD and controls with no signs of AMD as determined by fundus photography. Populations included in this study were European Americans, African Americans, Mexican Americans, and Singaporeans from the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: Index variants of AMD, rs1061170 (CFH) and rs10490924 (ARMS2), were associated with AMD at P=3.05×10(-8) and P=6.36×10(-6), respectively, in European Americans. In general, none of the major AMD index variants generalized to our non-European populations with the exception of rs10490924 in Mexican Americans at an uncorrected P value<0.05. Four lipid-associated SNPS (LPL rs328, TRIB1 rs6987702, CETP rs1800775, and KCTD10/MVK rs2338104) were associated with AMD in African Americans and Mexican Americans (P<0.05), but these associations did not survive strict corrections for multiple testing. CONCLUSIONS: While most associations did not generalize in the non-European populations, variants within lipid-related genes were found to be associated with AMD. This study highlights the need for larger well-powered studies in non-European populations.
Keywords: Adult; Aged; Aged, 80 and over; Complement Factor H; DNA; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Macular Degeneration; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Prevalence; Prospective Studies; Proteins; Risk Factors; United States

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analysis identifies six new loci associated with forced vital capacity. - Loth, Daan W; Soler Artigas, Maria; Gharib, Sina A; Wain, Louise V; Franceschini, Nora; Koch, Beate; Pottinger, Tess D; Smith, Albert Vernon; Duan, Qing; Oldmeadow, Chris; Lee, Mi Kyeong; Strachan, David P; et al. (Nat Genet, 2014)
Forced vital capacity (FVC), a spirometric measure of pulmonary function, reflects lung volume and is used to diagnose and monitor lung diseases. We performed genome-wide association study meta-analysis of FVC in 52,253 individuals from 26 studies and followed up the top associations in 32,917 additional individuals of European ancestry. We found six new regions associated at genome-wide significance (P < 5 × 10(-8)) with FVC in or near EFEMP1, BMP6, MIR129-2-HSD17B12, PRDM11, WWOX and KCNJ2. Two loci previously associated with spirometric measures (GSTCD and PTCH1) were related to FVC. Newly implicated regions were followed up in samples from African-American, Korean, Chinese and Hispanic individuals. We detected transcripts for all six newly implicated genes in human lung tissue. The new loci may inform mechanisms involved in lung development and the pathogenesis of restrictive lung disease.
Keywords: Cohort Studies; Databases, Genetic; Follow-Up Studies; Forced Expiratory Volume; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung Diseases; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Prognosis; Quantitative Trait Loci; Respiratory Function Tests; Spirometry; Vital Capacity

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Glycated hemoglobin measurement and prediction of cardiovascular disease. - Di Angelantonio, Emanuele; Gao, Pei; Khan, Hassan; Butterworth, Adam S; Wormser, David; Kaptoge, Stephen; Kondapally Seshasai, Sreenivasa Rao; Thompson, Alex; Sarwar, Nadeem; Willeit, Peter; Ridker, Paul M; Barr, Elizabeth L M; et al. (JAMA, 2014)
IMPORTANCE: The value of measuring levels of glycated hemoglobin (HbA1c) for the prediction of first cardiovascular events is uncertain. OBJECTIVE: To determine whether adding information on HbA1c values to conventional cardiovascular risk factors is associated with improvement in prediction of cardiovascular disease (CVD) risk. DESIGN, SETTING, AND PARTICIPANTS: Analysis of individual-participant data available from 73 prospective studies involving 294,998 participants without a known history of diabetes mellitus or CVD at the baseline assessment. MAIN OUTCOMES AND MEASURES: Measures of risk discrimination for CVD outcomes (eg, C-index) and reclassification (eg, net reclassification improvement) of participants across predicted 10-year risk categories of low (<5%), intermediate (5% to <7.5%), and high (≥ 7.5%) risk. RESULTS: During a median follow-up of 9.9 (interquartile range, 7.6-13.2) years, 20,840 incident fatal and nonfatal CVD outcomes (13,237 coronary heart disease and 7603 stroke outcomes) were recorded. In analyses adjusted for several conventional cardiovascular risk factors, there was an approximately J-shaped association between HbA1c values and CVD risk. The association between HbA1c values and CVD risk changed only slightly after adjustment for total cholesterol and triglyceride concentrations or estimated glomerular filtration rate, but this association attenuated somewhat after adjustment for concentrations of high-density lipoprotein cholesterol and C-reactive protein. The C-index for a CVD risk prediction model containing conventional cardiovascular risk factors alone was 0.7434 (95% CI, 0.7350 to 0.7517). The addition of information on HbA1c was associated with a C-index change of 0.0018 (0.0003 to 0.0033) and a net reclassification improvement of 0.42 (-0.63 to 1.48) for the categories of predicted 10-year CVD risk. The improvement provided by HbA1c assessment in prediction of CVD risk was equal to or better than estimated improvements for measurement of fasting, random, or postload plasma glucose levels. CONCLUSIONS AND RELEVANCE: In a study of individuals without known CVD or diabetes, additional assessment of HbA1c values in the context of CVD risk assessment provided little incremental benefit for prediction of CVD risk.
Keywords: Aged; C-Reactive Protein; Cholesterol, HDL; Coronary Disease; Diabetes Mellitus; Female; Glycated Hemoglobin A; Humans; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Risk Assessment; Stroke

Identification of novel genetic Loci associated with thyroid peroxidase antibodies and clinical thyroid disease. - Medici, Marco; Porcu, Eleonora; Pistis, Giorgio; Teumer, Alexander; Brown, Suzanne J; Jensen, Richard A; Rawal, Rajesh; Roef, Greet L; Plantinga, Theo S; Vermeulen, Sita H; Lahti, Jari; Simmonds, Matthew J; et al. (PLoS Genet, 2014)
Autoimmune thyroid diseases (AITD) are common, affecting 2-5% of the general population. Individuals with positive thyroid peroxidase antibodies (TPOAbs) have an increased risk of autoimmune hypothyroidism (Hashimoto's thyroiditis), as well as autoimmune hyperthyroidism (Graves' disease). As the possible causative genes of TPOAbs and AITD remain largely unknown, we performed GWAS meta-analyses in 18,297 individuals for TPOAb-positivity (1769 TPOAb-positives and 16,528 TPOAb-negatives) and in 12,353 individuals for TPOAb serum levels, with replication in 8,990 individuals. Significant associations (P<5×10(-8)) were detected at TPO-rs11675434, ATXN2-rs653178, and BACH2-rs10944479 for TPOAb-positivity, and at TPO-rs11675434, MAGI3-rs1230666, and KALRN-rs2010099 for TPOAb levels. Individual and combined effects (genetic risk scores) of these variants on (subclinical) hypo- and hyperthyroidism, goiter and thyroid cancer were studied. Individuals with a high genetic risk score had, besides an increased risk of TPOAb-positivity (OR: 2.18, 95% CI 1.68-2.81, P = 8.1×10(-8)), a higher risk of increased thyroid-stimulating hormone levels (OR: 1.51, 95% CI 1.26-1.82, P = 2.9×10(-6)), as well as a decreased risk of goiter (OR: 0.77, 95% CI 0.66-0.89, P = 6.5×10(-4)). The MAGI3 and BACH2 variants were associated with an increased risk of hyperthyroidism, which was replicated in an independent cohort of patients with Graves' disease (OR: 1.37, 95% CI 1.22-1.54, P = 1.2×10(-7) and OR: 1.25, 95% CI 1.12-1.39, P = 6.2×10(-5)). The MAGI3 variant was also associated with an increased risk of hypothyroidism (OR: 1.57, 95% CI 1.18-2.10, P = 1.9×10(-3)). This first GWAS meta-analysis for TPOAbs identified five newly associated loci, three of which were also associated with clinical thyroid disease. With these markers we identified a large subgroup in the general population with a substantially increased risk of TPOAbs. The results provide insight into why individuals with thyroid autoimmunity do or do not eventually develop thyroid disease, and these markers may therefore predict which TPOAb-positives are particularly at risk of developing clinical thyroid dysfunction.
Keywords: Autoantibodies; Genetic Loci; Genome-Wide Association Study; Graves Disease; Hashimoto Disease; Humans; Iodide Peroxidase; Risk Factors; Thyroiditis, Autoimmune; Thyrotropin

Incidence of and risk factors for sick sinus syndrome in the general population. - Jensen, Paul N; Gronroos, Noelle N; Chen, Lin Y; Folsom, Aaron R; deFilippi, Chris; Heckbert, Susan R; Alonso, Alvaro (J Am Coll Cardiol, 2014)
BACKGROUND: Little is known about the incidence of and risk factors for sick sinus syndrome (SSS), a common indication for pacemaker implantation. OBJECTIVES: This study sought to describe the epidemiology of SSS. METHODS: This analysis included 20,572 participants (mean baseline age 59 years, 43% male) in the ARIC (Atherosclerosis Risk In Communities) study and the CHS (Cardiovascular Health Study), who at baseline were free of prevalent atrial fibrillation and pacemaker therapy, had a heart rate of ≥ 50 beats/min unless using beta blockers, and were identified as of white or black race. Incident SSS cases were identified by hospital discharge International Classification of Disease-revision 9-Clinical Modification code 427.81 and validated by medical record review. RESULTS: During an average 17 years of follow-up, 291 incident SSS cases were identified (unadjusted rate 0.8 per 1,000 person-years). Incidence increased with age (hazard ratio [HR]: 1.73; 95% confidence interval [CI]: 1.47 to 2.05 per 5-year increment), and blacks had a 41% lower risk of SSS than whites (HR: 0.59; 95% CI: 0.37 to 0.98). Incident SSS was associated with greater baseline body mass index, height, N-terminal pro-B-type natriuretic peptide, and cystatin C, with longer QRS interval, with lower heart rate, and with prevalent hypertension, right bundle branch block, and cardiovascular disease. We project that the annual number of new SSS cases in the United States will increase from 78,000 in 2012 to 172,000 in 2060. CONCLUSIONS: Blacks have a lower risk of SSS than whites, and several cardiovascular risk factors were associated with incident SSS. With the aging of the population, the number of Americans with SSS will increase dramatically over the next 50 years.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Population Surveillance; Prospective Studies; Risk Factors; Sick Sinus Syndrome

Integrating genetic, transcriptional, and functional analyses to identify 5 novel genes for atrial fibrillation. - Sinner, Moritz F; Tucker, Nathan R; Lunetta, Kathryn L; Ozaki, Kouichi; Smith, J Gustav; Trompet, Stella; Bis, Joshua C; Lin, Honghuang; Chung, Mina K; Nielsen, Jonas B; Lubitz, Steven A; Krijthe, Bouwe P; et al. (Circulation, 2014)
BACKGROUND: Atrial fibrillation (AF) affects >30 million individuals worldwide and is associated with an increased risk of stroke, heart failure, and death. AF is highly heritable, yet the genetic basis for the arrhythmia remains incompletely understood. METHODS AND RESULTS: To identify new AF-related genes, we used a multifaceted approach, combining large-scale genotyping in 2 ethnically distinct populations, cis-eQTL (expression quantitative trait loci) mapping, and functional validation. Four novel loci were identified in individuals of European descent near the genes NEURL (rs12415501; relative risk [RR]=1.18; 95% confidence interval [CI], 1.13-1.23; P=6.5×10(-16)), GJA1 (rs13216675; RR=1.10; 95% CI, 1.06-1.14; P=2.2×10(-8)), TBX5 (rs10507248; RR=1.12; 95% CI, 1.08-1.16; P=5.7×10(-11)), and CAND2 (rs4642101; RR=1.10; 95% CI, 1.06-1.14; P=9.8×10(-9)). In Japanese, novel loci were identified near NEURL (rs6584555; RR=1.32; 95% CI, 1.26-1.39; P=2.0×10(-25)) and CUX2 (rs6490029; RR=1.12; 95% CI, 1.08-1.16; P=3.9×10(-9)). The top single-nucleotide polymorphisms or their proxies were identified as cis-eQTLs for the genes CAND2 (P=2.6×10(-19)), GJA1 (P=2.66×10(-6)), and TBX5 (P=1.36×10(-5)). Knockdown of the zebrafish orthologs of NEURL and CAND2 resulted in prolongation of the atrial action potential duration (17% and 45%, respectively). CONCLUSIONS: We have identified 5 novel loci for AF. Our results expand the diversity of genetic pathways implicated in AF and provide novel molecular targets for future biological and pharmacological investigation.
Keywords: Aged; Animals; Atrial Fibrillation; Chromosome Mapping; Connexin 43; Europe; Female; Gene Knockdown Techniques; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Muscle Proteins; Nuclear Proteins; Quantitative Trait Loci; Repressor Proteins; T-Box Domain Proteins; Transcription Factors; Ubiquitin-Protein Ligases; Zebrafish; Zebrafish Proteins

Large-scale genome-wide association studies and meta-analyses of longitudinal change in adult lung function. - Tang, Wenbo; Kowgier, Matthew; Loth, Daan W; Soler Artigas, Maria; Joubert, Bonnie R; Hodge, Emily; Gharib, Sina A; Smith, Albert V; Ruczinski, Ingo; Gudnason, Vilmundur; Mathias, Rasika A; Harris, Tamara B; et al. (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified numerous loci influencing cross-sectional lung function, but less is known about genes influencing longitudinal change in lung function. METHODS: We performed GWAS of the rate of change in forced expiratory volume in the first second (FEV1) in 14 longitudinal, population-based cohort studies comprising 27,249 adults of European ancestry using linear mixed effects model and combined cohort-specific results using fixed effect meta-analysis to identify novel genetic loci associated with longitudinal change in lung function. Gene expression analyses were subsequently performed for identified genetic loci. As a secondary aim, we estimated the mean rate of decline in FEV1 by smoking pattern, irrespective of genotypes, across these 14 studies using meta-analysis. RESULTS: The overall meta-analysis produced suggestive evidence for association at the novel IL16/STARD5/TMC3 locus on chromosome 15 (P  =  5.71 × 10(-7)). In addition, meta-analysis using the five cohorts with ≥3 FEV1 measurements per participant identified the novel ME3 locus on chromosome 11 (P  =  2.18 × 10(-8)) at genome-wide significance. Neither locus was associated with FEV1 decline in two additional cohort studies. We confirmed gene expression of IL16, STARD5, and ME3 in multiple lung tissues. Publicly available microarray data confirmed differential expression of all three genes in lung samples from COPD patients compared with controls. Irrespective of genotypes, the combined estimate for FEV1 decline was 26.9, 29.2 and 35.7 mL/year in never, former, and persistent smokers, respectively. CONCLUSIONS: In this large-scale GWAS, we identified two novel genetic loci in association with the rate of change in FEV1 that harbor candidate genes with biologically plausible functional links to lung function.
Keywords: Adult; Chromosomes, Human, Pair 11; Female; Gene Expression Regulation; Genetic Loci; Genome-Wide Association Study; Humans; Longitudinal Studies; Male; Respiration

Lipoprotein-associated phospholipase A2 and risk of dementia in the Cardiovascular Health Study. - Fitzpatrick, Annette L; Irizarry, Michael C; Cushman, Mary; Jenny, Nancy S; Chi, Gloria C; Koro, Carol (Atherosclerosis, 2014)
OBJECTIVE: To evaluate associations between Lipoprotein-associated phospholipase A2 (Lp-PLA2) mass and activity with risk of dementia and its subtypes. METHODS: Analysis were completed on 3320 participants of the Cardiovascular Health Study (CHS), a population-based longitudinal study of community-dwelling adults age ≥65 years followed for an average of 5.4 years. Baseline serum Lp-PLA2 mass was measured using a sandwich enzyme immunoassay and Lp-PLA2 activity utilized a tritiated-platelet activating factor activity assay. Cox proportional hazards regression assessed the relative risk of incident dementia with higher baseline Lp-PLA2 adjusting for demographics, cardiovascular disease (CVD) and risk factors, inflammation markers and apolipoprotein E (APOE) genotype. RESULTS: Each standard deviation higher Lp-PLA2 mass and activity were related to increased risk of dementia (fully adjusted HR: 1.11 per SD, 95% CI: 1.00-1.24 for mass; HR: 1.12 per SD, 95% CI: 1.00-1.26 for activity). Persons in the highest quartile of Lp-PLA2 mass were 50% more likely to develop dementia than those in the lowest quartile in adjusted models (HR: 1.49; 95% CI: 1.08-2.06). Among dementia subtypes, the risk of AD was increased two-fold in the highest compared to lowest quartile of Lp-PLA2 mass (adjusted HR: 1.98, 95% CI: 1.22-3.21). Results were attenuated in models of mixed dementia and VaD. Lp-PLA2 activity also doubled the risk of mixed dementia in the highest compared to lowest quartile (HR: 2.21, 95% CI: 1.12-4.373). INTERPRETATION: These data support Lp-PLA2 as a risk factor for dementia independent of CVD and its risk factors. Further study is required to clarify the role of Lp-PLA2-related mechanisms in dementia subtypes.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Alzheimer Disease; Dementia; Female; Humans; Male; Risk; Risk Factors

Loss-of-function mutations in APOC3, triglycerides, and coronary disease. - Crosby, Jacy; Peloso, Gina M; Auer, Paul L; Crosslin, David R; Stitziel, Nathan O; Lange, Leslie A; Lu, Yingchang; Tang, Zheng-Zheng; Zhang, He; Hindy, George; Masca, Nicholas; Stirrups, Kathleen; et al. (N Engl J Med, 2014)
BACKGROUND: Plasma triglyceride levels are heritable and are correlated with the risk of coronary heart disease. Sequencing of the protein-coding regions of the human genome (the exome) has the potential to identify rare mutations that have a large effect on phenotype. METHODS: We sequenced the protein-coding regions of 18,666 genes in each of 3734 participants of European or African ancestry in the Exome Sequencing Project. We conducted tests to determine whether rare mutations in coding sequence, individually or in aggregate within a gene, were associated with plasma triglyceride levels. For mutations associated with triglyceride levels, we subsequently evaluated their association with the risk of coronary heart disease in 110,970 persons. RESULTS: An aggregate of rare mutations in the gene encoding apolipoprotein C3 (APOC3) was associated with lower plasma triglyceride levels. Among the four mutations that drove this result, three were loss-of-function mutations: a nonsense mutation (R19X) and two splice-site mutations (IVS2+1G→A and IVS3+1G→T). The fourth was a missense mutation (A43T). Approximately 1 in 150 persons in the study was a heterozygous carrier of at least one of these four mutations. Triglyceride levels in the carriers were 39% lower than levels in noncarriers (P<1×10(-20)), and circulating levels of APOC3 in carriers were 46% lower than levels in noncarriers (P=8×10(-10)). The risk of coronary heart disease among 498 carriers of any rare APOC3 mutation was 40% lower than the risk among 110,472 noncarriers (odds ratio, 0.60; 95% confidence interval, 0.47 to 0.75; P=4×10(-6)). CONCLUSIONS: Rare mutations that disrupt APOC3 function were associated with lower levels of plasma triglycerides and APOC3. Carriers of these mutations were found to have a reduced risk of coronary heart disease. (Funded by the National Heart, Lung, and Blood Institute and others.).
Keywords: African Continental Ancestry Group; Apolipoprotein C-III; Coronary Disease; European Continental Ancestry Group; Exome; Genotype; Heterozygote; Humans; Liver; Mutation; Risk Factors; Sequence Analysis, DNA; Triglycerides

Meta-analysis of genome-wide association studies in African Americans provides insights into the genetic architecture of type 2 diabetes. - Ng, Maggie C Y; Shriner, Daniel; Chen, Brian H; Li, Jiang; Chen, Wei-Min; Guo, Xiuqing; Liu, Jiankang; Bielinski, Suzette J; Yanek, Lisa R; Nalls, Michael A; Comeau, Mary E; Rasmussen-Torvik, Laura J; et al. (PLoS Genet, 2014)
Type 2 diabetes (T2D) is more prevalent in African Americans than in Europeans. However, little is known about the genetic risk in African Americans despite the recent identification of more than 70 T2D loci primarily by genome-wide association studies (GWAS) in individuals of European ancestry. In order to investigate the genetic architecture of T2D in African Americans, the MEta-analysis of type 2 DIabetes in African Americans (MEDIA) Consortium examined 17 GWAS on T2D comprising 8,284 cases and 15,543 controls in African Americans in stage 1 analysis. Single nucleotide polymorphisms (SNPs) association analysis was conducted in each study under the additive model after adjustment for age, sex, study site, and principal components. Meta-analysis of approximately 2.6 million genotyped and imputed SNPs in all studies was conducted using an inverse variance-weighted fixed effect model. Replications were performed to follow up 21 loci in up to 6,061 cases and 5,483 controls in African Americans, and 8,130 cases and 38,987 controls of European ancestry. We identified three known loci (TCF7L2, HMGA2 and KCNQ1) and two novel loci (HLA-B and INS-IGF2) at genome-wide significance (4.15 × 10(-94)<P<5 × 10(-8), odds ratio (OR)  = 1.09 to 1.36). Fine-mapping revealed that 88 of 158 previously identified T2D or glucose homeostasis loci demonstrated nominal to highly significant association (2.2 × 10(-23) < locus-wide P<0.05). These novel and previously identified loci yielded a sibling relative risk of 1.19, explaining 17.5% of the phenotypic variance of T2D on the liability scale in African Americans. Overall, this study identified two novel susceptibility loci for T2D in African Americans. A substantial number of previously reported loci are transferable to African Americans after accounting for linkage disequilibrium, enabling fine mapping of causal variants in trans-ethnic meta-analysis studies.
Keywords: African Americans; Diabetes Mellitus, Type 2; Genome-Wide Association Study; HLA-B27 Antigen; HMGA2 Protein; Humans; KCNQ1 Potassium Channel; Mutant Chimeric Proteins; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Meta-analysis of loci associated with age at natural menopause in African-American women. - Chen, Christina T L; Liu, Ching-Ti; Chen, Gary K; Andrews, Jeanette S; Arnold, Alice M; Dreyfus, Jill; Franceschini, Nora; Garcia, Melissa E; Kerr, Kathleen F; Li, Guo; Lohman, Kurt K; Musani, Solomon K; et al. (Hum Mol Genet, 2014)
Age at menopause marks the end of a woman's reproductive life and its timing associates with risks for cancer, cardiovascular and bone disorders. GWAS and candidate gene studies conducted in women of European ancestry have identified 27 loci associated with age at menopause. The relevance of these loci to women of African ancestry has not been previously studied. We therefore sought to uncover additional menopause loci and investigate the relevance of European menopause loci by performing a GWAS meta-analysis in 6510 women with African ancestry derived from 11 studies across the USA. We did not identify any additional loci significantly associated with age at menopause in African Americans. We replicated the associations between six loci and age at menopause (P-value < 0.05): AMHR2, RHBLD2, PRIM1, HK3/UMC1, BRSK1/TMEM150B and MCM8. In addition, associations of 14 loci are directionally consistent with previous reports. We provide evidence that genetic variants influencing reproductive traits identified in European populations are also important in women of African ancestry residing in USA.
Keywords: African Americans; Age Factors; Chromosomes, Human; European Continental Ancestry Group; Female; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Menopause; United States

Multiancestral analysis of inflammation-related genetic variants and C-reactive protein in the population architecture using genomics and epidemiology study. - Kocarnik, Jonathan M; Pendergrass, Sarah A; Carty, Cara L; Pankow, James S; Schumacher, Fredrick R; Cheng, Iona; Durda, Peter; Ambite, Jose Luis; Deelman, Ewa; Cook, Nancy R; Liu, Simin; Wactawski-Wende, Jean; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: C-reactive protein (CRP) is a biomarker of inflammation. Genome-wide association studies (GWAS) have identified single-nucleotide polymorphisms (SNPs) associated with CRP concentrations and inflammation-related traits such as cardiovascular disease, type 2 diabetes mellitus, and obesity. We aimed to replicate previous CRP-SNP associations, assess whether these associations generalize to additional race/ethnicity groups, and evaluate inflammation-related SNPs for a potentially pleiotropic association with CRP. METHODS AND RESULTS: We selected and analyzed 16 CRP-associated and 250 inflammation-related GWAS SNPs among 40 473 African American, American Indian, Asian/Pacific Islander, European American, and Hispanic participants from 7 studies collaborating in the Population Architecture using Genomics and Epidemiology (PAGE) study. Fixed-effect meta-analyses combined study-specific race/ethnicity-stratified linear regression estimates to evaluate the association between each SNP and high-sensitivity CRP. Overall, 18 SNPs in 8 loci were significantly associated with CRP (Bonferroni-corrected P<3.1×10(-3) for replication, P<2.0×10(-4) for pleiotropy): Seven of these were specific to European Americans, while 9 additionally generalized to African Americans (1), Hispanics (5), or both (3); 1 SNP was seen only in African Americans and Hispanics. Two SNPs in the CELSR2/PSRC1/SORT1 locus showed a potentially novel association with CRP: rs599839 (P=2.0×10(-6)) and rs646776 (P=3.1×10(-5)). CONCLUSIONS: We replicated 16 SNP-CRP associations, 10 of which generalized to African Americans and/or Hispanics. We also identified potentially novel pleiotropic associations with CRP for two SNPs previously associated with coronary artery disease and/or low-density lipoprotein-cholesterol. These findings demonstrate the benefit of evaluating genotype-phenotype associations in multiple race/ethnicity groups and looking for pleiotropic relationships among SNPs previously associated with related phenotypes.
Keywords: Adult; African Continental Ancestry Group; Aged; Asian Continental Ancestry Group; C-Reactive Protein; Female; Genetic Variation; Genome-Wide Association Study; Hispanic Americans; Humans; Indians, North American; Inflammation; Male; Middle Aged; Polymorphism, Single Nucleotide; United States; Young Adult

Multilocus genetic risk score associates with ischemic stroke in case-control and prospective cohort studies. - Malik, Rainer; Bevan, Steve; Nalls, Michael A; Holliday, Elizabeth G; Devan, William J; Cheng, Yu-Ching; Ibrahim-Verbaas, Carla A; Verhaaren, Benjamin F J; Bis, Joshua C; Joon, Aron Y; de Stefano, Anita L; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Genome-wide association studies have revealed multiple common variants associated with known risk factors for ischemic stroke (IS). However, their aggregate effect on risk is uncertain. We aimed to generate a multilocus genetic risk score (GRS) for IS based on genome-wide association studies data from clinical-based samples and to establish its external validity in prospective population-based cohorts. METHODS: Three thousand five hundred forty-eight clinic-based IS cases and 6399 controls from the Wellcome Trust Case Control Consortium 2 were used for derivation of the GRS. Subjects from the METASTROKE consortium served as a replication sample. The validation sample consisted of 22 751 participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. We selected variants that had reached genome-wide significance in previous association studies on established risk factors for IS. RESULTS: A combined GRS for atrial fibrillation, coronary artery disease, hypertension, and systolic blood pressure significantly associated with IS both in the case-control samples and in the prospective population-based studies. Subjects in the top quintile of the combined GRS had >2-fold increased risk of IS compared with subjects in the lowest quintile. Addition of the combined GRS to a simple model based on sex significantly improved the prediction of IS in the combined clinic-based samples but not in the population-based studies, and there was no significant improvement in net reclassification. CONCLUSIONS: A multilocus GRS based on common variants for established cardiovascular risk factors was significantly associated with IS both in clinic-based samples and in the general population. However, the improvement in clinical risk prediction was found to be small.
Keywords: Adult; Aged; Aged, 80 and over; Atrial Fibrillation; Blood Pressure; Brain Ischemia; Case-Control Studies; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Multilocus Sequence Typing; Polymorphism, Single Nucleotide; Population; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke

No evidence for genome-wide interactions on plasma fibrinogen by smoking, alcohol consumption and body mass index: results from meta-analyses of 80,607 subjects. - Baumert, Jens; Huang, Jie; McKnight, Barbara; Sabater-Lleal, Maria; Steri, Maristella; Chu, Audrey Y; Trompet, Stella; Lopez, Lorna M; Fornage, Myriam; Teumer, Alexander; Tang, Weihong; Rudnicka, Alicja R; et al. (PLoS One, 2014)
Plasma fibrinogen is an acute phase protein playing an important role in the blood coagulation cascade having strong associations with smoking, alcohol consumption and body mass index (BMI). Genome-wide association studies (GWAS) have identified a variety of gene regions associated with elevated plasma fibrinogen concentrations. However, little is yet known about how associations between environmental factors and fibrinogen might be modified by genetic variation. Therefore, we conducted large-scale meta-analyses of genome-wide interaction studies to identify possible interactions of genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentration. The present study included 80,607 subjects of European ancestry from 22 studies. Genome-wide interaction analyses were performed separately in each study for about 2.6 million single nucleotide polymorphisms (SNPs) across the 22 autosomal chromosomes. For each SNP and risk factor, we performed a linear regression under an additive genetic model including an interaction term between SNP and risk factor. Interaction estimates were meta-analysed using a fixed-effects model. No genome-wide significant interaction with smoking status, alcohol consumption or BMI was observed in the meta-analyses. The most suggestive interaction was found for smoking and rs10519203, located in the LOC123688 region on chromosome 15, with a p value of 6.2 × 10(-8). This large genome-wide interaction study including 80,607 participants found no strong evidence of interaction between genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentrations. Further studies are needed to yield deeper insight in the interplay between environmental factors and gene variants on the regulation of fibrinogen concentrations.
Keywords: Alcohol Drinking; Body Mass Index; Fibrinogen; Gene-Environment Interaction; Genomics; Humans; Smoking

Novel genetic markers associate with atrial fibrillation risk in Europeans and Japanese. - Lubitz, Steven A; Lunetta, Kathryn L; Lin, Honghuang; Arking, Dan E; Trompet, Stella; Li, Guo; Krijthe, Bouwe P; Chasman, Daniel I; Barnard, John; Kleber, Marcus E; Dörr, Marcus; Ozaki, Kouichi; et al. (J Am Coll Cardiol, 2014)
OBJECTIVES: This study sought to identify nonredundant atrial fibrillation (AF) genetic susceptibility signals and examine their cumulative relations with AF risk. BACKGROUND: AF-associated loci span broad genomic regions that may contain multiple susceptibility signals. Whether multiple signals exist at AF loci has not been systematically explored. METHODS: We performed association testing conditioned on the most significant, independently associated genetic markers at 9 established AF loci using 2 complementary techniques in 64,683 individuals of European ancestry (3,869 incident and 3,302 prevalent AF cases). Genetic risk scores were created and tested for association with AF in Europeans and an independent sample of 11,309 individuals of Japanese ancestry (7,916 prevalent AF cases). RESULTS: We observed at least 4 distinct AF susceptibility signals on chromosome 4q25 upstream of PITX2, but not at the remaining 8 AF loci. A multilocus score comprised 12 genetic markers demonstrated an estimated 5-fold gradient in AF risk. We observed a similar spectrum of risk associated with these markers in Japanese. Regions containing AF signals on chromosome 4q25 displayed a greater degree of evolutionary conservation than the remainder of the locus, suggesting that they may tag regulatory elements. CONCLUSIONS: The chromosome 4q25 AF locus is architecturally complex and harbors at least 4 AF susceptibility signals in individuals of European ancestry. Similar polygenic AF susceptibility exists between Europeans and Japanese. Future work is necessary to identify causal variants, determine mechanisms by which associated loci predispose to AF, and explore whether AF susceptibility signals classify individuals at risk for AF and related morbidity.
Keywords: Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; Europe; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factors

Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins. - Postmus, Iris; Trompet, Stella; Deshmukh, Harshal A; Barnes, Michael R; Li, Xiaohui; Warren, Helen R; Chasman, Daniel I; Zhou, Kaixin; Arsenault, Benoit J; Donnelly, Louise A; Wiggins, Kerri L; Avery, Christy L; et al. (Nat Commun, 2014)
Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previously identified in GWAS. Moreover, we confirm the previously described associations with APOE and LPA. Our findings advance the understanding of the pharmacogenetic architecture of statin response.
Keywords: Cholesterol, LDL; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide

Quantifying rare, deleterious variation in 12 human cytochrome P450 drug-metabolism genes in a large-scale exome dataset. - Gordon, Adam S; Tabor, Holly K; Johnson, Andrew D; Snively, Beverly M; Assimes, Themistocles L; Auer, Paul L; Ioannidis, John P A; Peters, Ulrike; Robinson, Jennifer G; Sucheston, Lara E; Wang, Danxin; Sotoodehnia, Nona; et al. (Hum Mol Genet, 2014)
The study of genetic influences on drug response and efficacy ('pharmacogenetics') has existed for over 50 years. Yet, we still lack a complete picture of how genetic variation, both common and rare, affects each individual's responses to medications. Exome sequencing is a promising alternative method for pharmacogenetic discovery as it provides information on both common and rare variation in large numbers of individuals. Using exome data from 2203 AA and 4300 Caucasian individuals through the NHLBI Exome Sequencing Project, we conducted a survey of coding variation within 12 Cytochrome P450 (CYP) genes that are collectively responsible for catalyzing nearly 75% of all known Phase I drug oxidation reactions. In addition to identifying many polymorphisms with known pharmacogenetic effects, we discovered over 730 novel nonsynonymous alleles across the 12 CYP genes of interest. These alleles include many with diverse functional effects such as premature stop codons, aberrant splicesites and mutations at conserved active site residues. Our analysis considering both novel, predicted functional alleles as well as known, actionable CYP alleles reveals that rare, deleterious variation contributes markedly to the overall burden of pharmacogenetic alleles within the populations considered, and that the contribution of rare variation to this burden is over three times greater in AA individuals as compared with Caucasians. While most of these impactful alleles are individually rare, 7.6-11.7% of individuals interrogated in the study carry at least one newly described potentially deleterious alleles in a major drug-metabolizing CYP.
Keywords: Cytochrome P-450 Enzyme System; Databases, Genetic; European Continental Ancestry Group; Exome; Humans; Pharmaceutical Preparations; Pharmacogenetics; Polymorphism, Genetic

Racial and regional differences in venous thromboembolism in the United States in 3 cohorts. - Zakai, Neil A; McClure, Leslie A; Judd, Suzanne E; Safford, Monika M; Folsom, Aaron R; Lutsey, Pamela L; Cushman, Mary (Circulation, 2014)
BACKGROUND: Blacks are thought to have a higher risk of venous thromboembolism (VTE) than whites. However, prior studies are limited to administrative databases that lack specific information on VTE risk factors or have limited geographic scope. METHODS AND RESULTS: We ascertained VTE from 3 prospective studies: the Atherosclerosis Risk in Communities Study (ARIC), the Cardiovascular Health Study (CHS), and the Reasons for Geographic and Racial Differences in Stroke study (REGARDS). We tested the association of race with VTE using Cox proportional hazard models adjusted for VTE risk factors. Over 438 090 person-years, 916 incident VTE events (302 in blacks) occurred in 51 149 individuals (17 318 blacks) who were followed up. In risk factor-adjusted models, blacks had a higher rate of VTE than whites in the CHS (hazard ratio, 1.81; 95% confidence interval, 1.20-2.73) but not ARIC (hazard ratio, 1.21; 95% confidence interval, 0.96-1.54). In REGARDS, there was a significant region-by-race interaction (P=0.01): Blacks in the Southeast had a significantly higher rate of VTE than blacks in the rest of the United States (hazard ratio, 1.63; 95% confidence interval, 1.08-2.48) that was not seen in whites (hazard ratio, 0.83; 95% confidence interval, 0.61-1.14). CONCLUSIONS: The association of race with VTE differed in each cohort, which may reflect the different time periods of the studies or different regional rates of VTE. Further studies of environmental and genetic risk factors for VTE are needed to determine which underlie racial and perhaps regional differences in VTE.
Keywords: African Continental Ancestry Group; Aged; Cohort Studies; European Continental Ancestry Group; Female; Humans; Longitudinal Studies; Male; Middle Aged; Prevalence; Proportional Hazards Models; Prospective Studies; Residence Characteristics; Risk Factors; United States; Venous Thromboembolism

Sequencing of SCN5A identifies rare and common variants associated with cardiac conduction: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Magnani, Jared W; Brody, Jennifer A; Prins, Bram P; Arking, Dan E; Lin, Honghuang; Yin, Xiaoyan; Liu, Ching-Ti; Morrison, Alanna C; Zhang, Feng; Spector, Tim D; Alonso, Alvaro; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The cardiac sodium channel SCN5A regulates atrioventricular and ventricular conduction. Genetic variants in this gene are associated with PR and QRS intervals. We sought to characterize further the contribution of rare and common coding variation in SCN5A to cardiac conduction. METHODS AND RESULTS: In Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study, we performed targeted exonic sequencing of SCN5A (n=3699, European ancestry individuals) and identified 4 common (minor allele frequency >1%) and 157 rare variants. Common and rare SCN5A coding variants were examined for association with PR and QRS intervals through meta-analysis of European ancestry participants from CHARGE, National Heart, Lung, and Blood Institute's Exome Sequencing Project (n=607), and the UK10K (n=1275) and by examining Exome Sequencing Project African ancestry participants (n=972). Rare coding SCN5A variants in aggregate were associated with PR interval in European and African ancestry participants (P=1.3×10(-3)). Three common variants were associated with PR and QRS interval duration among European ancestry participants and one among African ancestry participants. These included 2 well-known missense variants: rs1805124 (H558R) was associated with PR and QRS shortening in European ancestry participants (P=6.25×10(-4) and P=5.2×10(-3), respectively) and rs7626962 (S1102Y) was associated with PR shortening in those of African ancestry (P=2.82×10(-3)). Among European ancestry participants, 2 novel synonymous variants, rs1805126 and rs6599230, were associated with cardiac conduction. Our top signal, rs1805126 was associated with PR and QRS lengthening (P=3.35×10(-7) and P=2.69×10(-4), respectively) and rs6599230 was associated with PR shortening (P=2.67×10(-5)). CONCLUSIONS: By sequencing SCN5A, we identified novel common and rare coding variants associated with cardiac conduction.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Conduction System; Heart Diseases; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Simple biologically informed inflammatory index of two serum cytokines predicts 10 year all-cause mortality in older adults. - Varadhan, Ravi; Yao, Wenliang; Matteini, Amy; Beamer, Brock A; Xue, Qian-Li; Yang, Huanle; Manwani, Bhavish; Reiner, Alexander; Jenny, Nancy; Parekh, Neel; Fallin, M Daniele; Newman, Anne; et al. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Individual measurements of inflammation have been utilized to assess adverse outcomes risk in older adults with varying degrees of success. This study was designed to identify biologically informed, aggregate measures of inflammation for optimal risk assessment and to inform further biological study of inflammatory pathways. METHODS: In total, 15 nuclear factor-kappa B-mediated pathway markers of inflammation were first measured in baseline serum samples of 1,155 older participants in the InCHIANTI population. Of these, C-reactive protein, interleukin-1-receptor antagonist, interleukin-6, interleukin-18, and soluble tumor necrosis factor-α receptor-1 were independent predictors of 5-year mortality. These five inflammatory markers were measured in baseline serum samples of 5,600 Cardiovascular Health Study participants. A weighted summary score, the first principal component summary score, and an inflammation index score were developed from these five log-transformed inflammatory markers, and their prediction of 10-year all-cause mortality was evaluated in Cardiovascular Health Study and then validated in InCHIANTI. RESULTS: The inflammation index score that included interleukin-6 and soluble tumor necrosis factor-α receptor-1 was the best predictor of 10-year all-cause mortality in Cardiovascular Health Study, after adjusting for age, sex, education, race, smoking, and body mass index (hazards ratio = 1.62; 95% CI: 1.54, 1.70) compared with all other single and combined measures. The inflammation index score was also the best predictor of mortality in the InCHIANTI validation study (hazards ratio 1.33; 95% CI: 1.17-1.52). Stratification by sex and CVD status further strengthened the association of inflammation index score with mortality. CONCLUSION: A simple additive index of serum interleukin-6 and soluble tumor necrosis factor-α receptor-1 best captures the effect of chronic inflammation on mortality in older adults among the 15 biomarkers measured.
Keywords: Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cohort Studies; Female; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-18; Interleukin-6; Longevity; Male; Receptors, Tumor Necrosis Factor, Type I; Risk Factors

Strategies to design and analyze targeted sequencing data: cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Lin, Honghuang; Wang, Min; Brody, Jennifer A; Bis, Joshua C; Dupuis, Josée; Lumley, Thomas; McKnight, Barbara; Rice, Kenneth M; Sitlani, Colleen M; Reid, Jeffrey G; Bressler, Jan; Liu, Xiaoming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies have identified thousands of genetic variants that influence a variety of diseases and health-related quantitative traits. However, the causal variants underlying the majority of genetic associations remain unknown. Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study aims to follow up genome-wide association study signals and identify novel associations of the allelic spectrum of identified variants with cardiovascular-related traits. METHODS AND RESULTS: The study included 4231 participants from 3 CHARGE cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, and the Framingham Heart Study. We used a case-cohort design in which we selected both a random sample of participants and participants with extreme phenotypes for each of 14 traits. We sequenced and analyzed 77 genomic loci, which had previously been associated with ≥1 of 14 phenotypes. A total of 52 736 variants were characterized by sequencing and passed our stringent quality control criteria. For common variants (minor allele frequency ≥1%), we performed unweighted regression analyses to obtain P values for associations and weighted regression analyses to obtain effect estimates that accounted for the sampling design. For rare variants, we applied 2 approaches: collapsed aggregate statistics and joint analysis of variants using the sequence kernel association test. CONCLUSIONS: We sequenced 77 genomic loci in participants from 3 cohorts. We established a set of filters to identify high-quality variants and implemented statistical and bioinformatics strategies to analyze the sequence data and identify potentially functional variants within genome-wide association study loci.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Research Design; Sequence Analysis, DNA

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Whole-exome sequencing identifies rare and low-frequency coding variants associated with LDL cholesterol. - Lange, Leslie A; Hu, Youna; Zhang, He; Xue, Chenyi; Schmidt, Ellen M; Tang, Zheng-Zheng; Bizon, Chris; Lange, Ethan M; Smith, Joshua D; Turner, Emily H; Jun, Goo; Kang, Hyun Min; et al. (Am J Hum Genet, 2014)
Elevated low-density lipoprotein cholesterol (LDL-C) is a treatable, heritable risk factor for cardiovascular disease. Genome-wide association studies (GWASs) have identified 157 variants associated with lipid levels but are not well suited to assess the impact of rare and low-frequency variants. To determine whether rare or low-frequency coding variants are associated with LDL-C, we exome sequenced 2,005 individuals, including 554 individuals selected for extreme LDL-C (>98(th) or <2(nd) percentile). Follow-up analyses included sequencing of 1,302 additional individuals and genotype-based analysis of 52,221 individuals. We observed significant evidence of association between LDL-C and the burden of rare or low-frequency variants in PNPLA5, encoding a phospholipase-domain-containing protein, and both known and previously unidentified variants in PCSK9, LDLR and APOB, three known lipid-related genes. The effect sizes for the burden of rare variants for each associated gene were substantially higher than those observed for individual SNPs identified from GWASs. We replicated the PNPLA5 signal in an independent large-scale sequencing study of 2,084 individuals. In conclusion, this large whole-exome-sequencing study for LDL-C identified a gene not known to be implicated in LDL-C and provides unique insight into the design and analysis of similar experiments.
Keywords: Adult; Aged; Apolipoproteins E; Cholesterol, LDL; Cohort Studies; Dyslipidemias; Exome; Female; Follow-Up Studies; Gene Frequency; Genetic Code; Genome-Wide Association Study; Genotype; Humans; Lipase; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Proprotein Convertases; Receptors, LDL; Sequence Analysis, DNA; Serine Endopeptidases

Association of Alzheimer's disease GWAS loci with MRI markers of brain aging. - Chauhan, Ganesh; Adams, Hieab H H; Bis, Joshua C; Weinstein, Galit; Yu, Lei; Töglhofer, Anna Maria; Smith, Albert Vernon; van der Lee, Sven J; Gottesman, Rebecca F; Thomson, Russell; Wang, Jing; Yang, Qiong; et al. (Neurobiol Aging, 2015)
Whether novel risk variants of Alzheimer's disease (AD) identified through genome-wide association studies also influence magnetic resonance imaging-based intermediate phenotypes of AD in the general population is unclear. We studied association of 24 AD risk loci with intracranial volume, total brain volume, hippocampal volume (HV), white matter hyperintensity burden, and brain infarcts in a meta-analysis of genetic association studies from large population-based samples (N = 8175-11,550). In single-SNP based tests, AD risk allele of APOE (rs2075650) was associated with smaller HV (p = 0.0054) and CD33 (rs3865444) with smaller intracranial volume (p = 0.0058). In gene-based tests, there was associations of HLA-DRB1 with total brain volume (p = 0.0006) and BIN1 with HV (p = 0.00089). A weighted AD genetic risk score was associated with smaller HV (beta ± SE = -0.047 ± 0.013, p = 0.00041), even after excluding the APOE locus (p = 0.029). However, only association of AD genetic risk score with HV, including APOE, was significant after multiple testing correction (including number of independent phenotypes tested). These results suggest that novel AD genetic risk variants may contribute to structural brain aging in nondemented older community persons.
Keywords: Aging; Alleles; Alzheimer Disease; Apolipoproteins E; Brain; Female; Genome-Wide Association Study; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Organ Size; Polymorphism, Single Nucleotide; Risk; Sialic Acid Binding Ig-like Lectin 3

Association of Cardiometabolic Multimorbidity With Mortality. - Di Angelantonio, Emanuele; Kaptoge, Stephen; Wormser, David; Willeit, Peter; Butterworth, Adam S; Bansal, Narinder; O'Keeffe, Linda M; Gao, Pei; Wood, Angela M; Burgess, Stephen; Freitag, Daniel F; Pennells, Lisa; et al. (JAMA, 2015)
IMPORTANCE: The prevalence of cardiometabolic multimorbidity is increasing. OBJECTIVE: To estimate reductions in life expectancy associated with cardiometabolic multimorbidity. DESIGN, SETTING, AND PARTICIPANTS: Age- and sex-adjusted mortality rates and hazard ratios (HRs) were calculated using individual participant data from the Emerging Risk Factors Collaboration (689,300 participants; 91 cohorts; years of baseline surveys: 1960-2007; latest mortality follow-up: April 2013; 128,843 deaths). The HRs from the Emerging Risk Factors Collaboration were compared with those from the UK Biobank (499,808 participants; years of baseline surveys: 2006-2010; latest mortality follow-up: November 2013; 7995 deaths). Cumulative survival was estimated by applying calculated age-specific HRs for mortality to contemporary US age-specific death rates. EXPOSURES: A history of 2 or more of the following: diabetes mellitus, stroke, myocardial infarction (MI). MAIN OUTCOMES AND MEASURES: All-cause mortality and estimated reductions in life expectancy. RESULTS: In participants in the Emerging Risk Factors Collaboration without a history of diabetes, stroke, or MI at baseline (reference group), the all-cause mortality rate adjusted to the age of 60 years was 6.8 per 1000 person-years. Mortality rates per 1000 person-years were 15.6 in participants with a history of diabetes, 16.1 in those with stroke, 16.8 in those with MI, 32.0 in those with both diabetes and MI, 32.5 in those with both diabetes and stroke, 32.8 in those with both stroke and MI, and 59.5 in those with diabetes, stroke, and MI. Compared with the reference group, the HRs for all-cause mortality were 1.9 (95% CI, 1.8-2.0) in participants with a history of diabetes, 2.1 (95% CI, 2.0-2.2) in those with stroke, 2.0 (95% CI, 1.9-2.2) in those with MI, 3.7 (95% CI, 3.3-4.1) in those with both diabetes and MI, 3.8 (95% CI, 3.5-4.2) in those with both diabetes and stroke, 3.5 (95% CI, 3.1-4.0) in those with both stroke and MI, and 6.9 (95% CI, 5.7-8.3) in those with diabetes, stroke, and MI. The HRs from the Emerging Risk Factors Collaboration were similar to those from the more recently recruited UK Biobank. The HRs were little changed after further adjustment for markers of established intermediate pathways (eg, levels of lipids and blood pressure) and lifestyle factors (eg, smoking, diet). At the age of 60 years, a history of any 2 of these conditions was associated with 12 years of reduced life expectancy and a history of all 3 of these conditions was associated with 15 years of reduced life expectancy. CONCLUSIONS AND RELEVANCE: Mortality associated with a history of diabetes, stroke, or MI was similar for each condition. Because any combination of these conditions was associated with multiplicative mortality risk, life expectancy was substantially lower in people with multimorbidity.
Keywords: Adult; Aged; Comorbidity; Diabetes Mellitus; Female; Humans; Life Expectancy; Male; Middle Aged; Mortality; Myocardial Infarction; Risk Factors; Stroke

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; African Americans; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors

Association of Fetuin-A With Incident Fractures in Community-Dwelling Older Adults: The Cardiovascular Health Study. - Fink, Howard A; Bůzková, Petra; Garimella, Pranav S; Mukamal, Kenneth J; Cauley, Jane A; Kizer, Jorge R; Barzilay, Joshua I; Jalal, Diana I; Ix, Joachim H (J Bone Miner Res, 2015)
Fetuin-A, a serum protein that regulates calcium mineralization, has been associated with bone mineral density (BMD) in several cross-sectional human studies, suggesting a possible beneficial effect on clinically important measures of bone health. Fetuin-A and incidence of subsequent fracture was assessed in 4714 men and women ≥65 years of age. Proportional hazards models were used to estimate risk of incident hip (hospital discharge ICD-9 codes) and composite fracture (hip, pelvis, humerus, or proximal forearm; hospital discharge ICD-9 codes and Medicare claims data). A total of 576 participants had an incident hip fracture (median follow-up 11.2 years) and 768 had an incident composite fracture (median follow-up 6.9 years). In unadjusted analyses, there was no association between fetuin-A (per SD increase) and risk of hip fracture (hazard ratio [HR], 0.96; 95% CI, 0.88 to 1.05) or composite fracture (HR, 0.99; 95% CI, 0.92 to 1.06). Results were not significantly changed after adjustment for potential confounding variables. Analyses modeling fetuin-A in quartiles or within a subset with available BMD measures also showed no statistically significant association with risk of hip or composite fracture. Though fetuin-A was positively associated with areal BMD in partially adjusted models (total hip: β, 0.013 g/cm(2) ; 95% CI, 0.005 to 0.021; femoral neck: β, 0.011 g/cm(2) ; 95% CI, 0.004 to 0.018; and lumbar spine: β, 0.007 g/cm(2) ; 95% CI, 0.001 to 0.028), these associations were no longer significant after further adjustment for BMI and in final multivariate models. In this large sample of community-dwelling older adults, a small positive association between fetuin-A and areal BMD appeared attributable to confounding variables and we found no evidence of an association between fetuin-A and risk of clinical fracture.
Keywords: Adult; Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Bone Density; Cross-Sectional Studies; Female; Follow-Up Studies; Fractures, Bone; Humans; Incidence; Male; Models, Biological

Coagulation factor XII genetic variation, ex vivo thrombin generation, and stroke risk in the elderly: results from the Cardiovascular Health Study. - Olson, N C; Butenas, S; Lange, L A; Lange, E M; Cushman, M; Jenny, N S; Walston, J; Souto, J C; Soria, J M; Chauhan, G; Debette, S; Longstreth, W T; et al. (J Thromb Haemost, 2015)
BACKGROUND: The relationships of thrombin generation (TG) with cardiovascular disease risk are underevaluated in population-based cohorts. OBJECTIVES: To evaluate the relationships of TG influenced by the contact and tissue factor coagulation pathways ex vivo with common single-nucleotide polymorphisms (SNPs) and incident cardiovascular disease and stroke. PATIENTS/METHODS: We measured peak TG (pTG) in baseline plasma samples of Cardiovascular Health Study participants (n = 5411), both with and without inhibitory anti-factor XIa antibody (pTG/FXIa(-) ). We evaluated their associations with ~ 50 000 SNPs by using the IBCv2 genotyping array, and with incident cardiovascular disease and stroke events over a median follow-up of 13.2 years. RESULTS: The minor allele for an SNP in the FXII gene (F12), rs1801020, was associated with lower pTG in European-Americans (β = - 34.2 ± 3.5 nm; P = 3.3 × 10(-22) ; minor allele frequency [MAF] = 0.23) and African-Americans (β = - 31.1 ± 7.9 nm; P = 9.0 × 10(-5) ; MAF = 0.42). Lower FXIa-independent pTG (pTG/FXIa(-) ) was associated with the F12 rs1801020 minor allele, and higher pTG/FXIa(-) was associated with the ABO SNP rs657152 minor allele (β = 16.3 nm; P = 4.3 × 10(-9) ; MAF = 0.37). The risk factor-adjusted ischemic stroke hazard ratios were 1.09 (95% confidence interval CI 1.01-1.17; P = 0.03) for pTG, 1.06 (95% CI 0.98-1.15; P = 0.17) for pTG/FXIa(-) , and 1.11 (95% CI 1.02-1.21; P = 0.02) for FXIa-dependent pTG (pTG/FXIa(+) ), per one standard deviation increment (n = 834 ischemic strokes). In a multicohort candidate gene analysis, rs1801020 was not associated with incident ischemic stroke (β = - 0.02; standard error = 0.08; P = 0.81). CONCLUSIONS: These results support the importance of contact activation pathway-dependent TG as a risk factor for ischemic stroke, and indicate the importance of F12 SNPs for TG ex vivo and in vivo.
Keywords: African Americans; Age Factors; Aged; Blood Coagulation; Brain Ischemia; European Continental Ancestry Group; Factor XII; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Incidence; Male; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Thrombin; Time Factors; United States

Common variation in COL4A1/COL4A2 is associated with sporadic cerebral small vessel disease. - Rannikmae, Kristiina; Davies, Gail; Thomson, Pippa A; Bevan, Steve; Devan, William J; Falcone, Guido J; Traylor, Matthew; Anderson, Christopher D; Battey, Thomas W K; Radmanesh, Farid; Deka, Ranjan; Woo, Jessica G; et al. (Neurology, 2015)
OBJECTIVES: We hypothesized that common variants in the collagen genes COL4A1/COL4A2 are associated with sporadic forms of cerebral small vessel disease. METHODS: We conducted meta-analyses of existing genotype data among individuals of European ancestry to determine associations of 1,070 common single nucleotide polymorphisms (SNPs) in the COL4A1/COL4A2 genomic region with the following: intracerebral hemorrhage and its subtypes (deep, lobar) (1,545 cases, 1,485 controls); ischemic stroke and its subtypes (cardioembolic, large vessel disease, lacunar) (12,389 cases, 62,004 controls); and white matter hyperintensities (2,733 individuals with ischemic stroke and 9,361 from population-based cohorts with brain MRI data). We calculated a statistical significance threshold that accounted for multiple testing and linkage disequilibrium between SNPs (p < 0.000084). RESULTS: Three intronic SNPs in COL4A2 were significantly associated with deep intracerebral hemorrhage (lead SNP odds ratio [OR] 1.29, 95% confidence interval [CI] 1.14-1.46, p = 0.00003; r(2) > 0.9 between SNPs). Although SNPs associated with deep intracerebral hemorrhage did not reach our significance threshold for association with lacunar ischemic stroke (lead SNP OR 1.10, 95% CI 1.03-1.18, p = 0.0073), and with white matter hyperintensity volume in symptomatic ischemic stroke patients (lead SNP OR 1.07, 95% CI 1.01-1.13, p = 0.016), the direction of association was the same. There was no convincing evidence of association with white matter hyperintensities in population-based studies or with non-small vessel disease cerebrovascular phenotypes. CONCLUSIONS: Our results indicate an association between common variation in the COL4A2 gene and symptomatic small vessel disease, particularly deep intracerebral hemorrhage. These findings merit replication studies, including in ethnic groups of non-European ancestry.
Keywords: Cerebral Small Vessel Diseases; Collagen Type IV; Genetic Association Studies; Genetic Variation; Humans; Polymorphism, Single Nucleotide

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Drug-Gene Interactions of Antihypertensive Medications and Risk of Incident Cardiovascular Disease: A Pharmacogenomics Study from the CHARGE Consortium. - Bis, Joshua C; Sitlani, Colleen; Irvin, Ryan; Avery, Christy L; Smith, Albert Vernon; Sun, Fangui; Evans, Daniel S; Musani, Solomon K; Li, Xiaohui; Trompet, Stella; Krijthe, Bouwe P; Harris, Tamara B; et al. (PLoS One, 2015)
BACKGROUND: Hypertension is a major risk factor for a spectrum of cardiovascular diseases (CVD), including myocardial infarction, sudden death, and stroke. In the US, over 65 million people have high blood pressure and a large proportion of these individuals are prescribed antihypertensive medications. Although large long-term clinical trials conducted in the last several decades have identified a number of effective antihypertensive treatments that reduce the risk of future clinical complications, responses to therapy and protection from cardiovascular events vary among individuals. METHODS: Using a genome-wide association study among 21,267 participants with pharmaceutically treated hypertension, we explored the hypothesis that genetic variants might influence or modify the effectiveness of common antihypertensive therapies on the risk of major cardiovascular outcomes. The classes of drug treatments included angiotensin-converting enzyme inhibitors, beta-blockers, calcium channel blockers, and diuretics. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, each study performed array-based genome-wide genotyping, imputed to HapMap Phase II reference panels, and used additive genetic models in proportional hazards or logistic regression models to evaluate drug-gene interactions for each of four therapeutic drug classes. We used meta-analysis to combine study-specific interaction estimates for approximately 2 million single nucleotide polymorphisms (SNPs) in a discovery analysis among 15,375 European Ancestry participants (3,527 CVD cases) with targeted follow-up in a case-only study of 1,751 European Ancestry GenHAT participants as well as among 4,141 African-Americans (1,267 CVD cases). RESULTS: Although drug-SNP interactions were biologically plausible, exposures and outcomes were well measured, and power was sufficient to detect modest interactions, we did not identify any statistically significant interactions from the four antihypertensive therapy meta-analyses (Pinteraction > 5.0×10-8). Similarly, findings were null for meta-analyses restricted to 66 SNPs with significant main effects on coronary artery disease or blood pressure from large published genome-wide association studies (Pinteraction ≥ 0.01). Our results suggest that there are no major pharmacogenetic influences of common SNPs on the relationship between blood pressure medications and the risk of incident CVD.
Keywords: African Americans; Aged; Antihypertensive Agents; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Treatment Outcome

Empirically Derived Trajectories to Dementia Over 15 Years of Follow-up Identified by Using Mixed Membership Models. - Lecci, Fabrizio; Junker, Brian; Kuller, Lewis H; Lopez, Oscar L; Becker, James T (Am J Epidemiol, 2015)
Alzheimer disease is the most common form of dementia in the elderly, and the complex relationships among risk factors produce highly variable natural histories from normal cognition through the prodromal stage of mild cognitive impairment (MCI) to clinical dementia. We used a novel statistical approach, mixed membership trajectory models, to capture the variety of such pathways in 652 participants in the Cardiovascular Health Study Cognition Study over 22 years of follow-up (1992-2014). We identified 3 trajectories: a "healthy" profile with a peak probability of MCI between 95 and 100 years of age and only a 50% probability of dementia by age 100; an "intermediate" profile with a peak probability of MCI between 85 and 90 years of age and progression to dementia between 90 and 95 years; and an "unhealthy" profile with a peak probability of progressing to MCI between ages 75 and 80 years and to dementia between the ages of 80 and 85 years. Hypertension, education, race, and the ϵ4 allele of the apolipoprotein E gene all affected the closeness of an individual to 1 or more of the canonical trajectories. These results provide new insights into the natural history of Alzheimer disease and evidence for a potential difference in the pathophysiology of the development of dementia.
Keywords: Age Distribution; Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Cardiovascular Diseases; Comorbidity; Dementia; Diabetes Mellitus; Disease Progression; Female; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Mild Cognitive Impairment; Neuroimaging; Prevalence; Proportional Hazards Models; Risk Factors; Sex Distribution

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Fetuin-A and risk of coronary heart disease: A Mendelian randomization analysis and a pooled analysis of AHSG genetic variants in 7 prospective studies. - Laugsand, Lars E; Ix, Joachim H; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Dehghan, Abbas; Rexrode, Kathryn; Lopez, Oscar L; Rimm, Eric B; Siscovick, David S; O'Donnell, Christopher J; et al. (Atherosclerosis, 2015)
BACKGROUND AND AIMS: Fetuin-A has a plausible role in the inhibition of arterial calcification, but its association with risk of coronary heart disease (CHD) in the general population is unclear. We used two common genetic variants in the fetuin-A gene (AHSG) that are strongly associated with circulating fetuin-A levels to investigate the associations with risk of CHD and subclinical cardiovascular measures (intima-media thickness, ankle-arm index, and coronary artery calcification). METHODS: Genetic variation and fetuin-A levels were assessed in 3299 community-living individuals (2733 Caucasians and 566 African Americans) 65 years of age or older, free of previous cardiovascular disease, who participated in the Cardiovascular Health Study (CHS) in 1992-1993. RESULTS: Among Caucasians, both rs2248690 and rs4917 were associated with 12% lower fetuin-A concentrations per minor allele (P < 0.0001). The hazard ratios (HRs) per minor allele for incident CHD were 1.12 (95% CI: 1.00-1.26) for rs2248690 and 1.02 (0.91-1.14) for rs4917. Using both genotypes as an instrumental variable for measured fetuin-A, the HRs for one standard deviation increase in genetically determined fetuin-A levels on CHD risk were 0.84 (95% CI: 0.70-1.00) for rs2248690 and 0.97 (95% CI: 0.82-1.14) for rs4917, respectively. However, in CHS neither of the genotypes were associated with subclinical cardiovascular measures and when CHS data were meta-analyzed with data from six other prospective studies (totaling 26,702 Caucasian participants and 3295 CHD cases), the meta-analyzed HRs for incident CHD were 1.12 (0.93-1.34) and 1.06 (0.93-1.20) for rs2248690 and rs4917, respectively (p heterogeneity 0.005 and 0.0048). CONCLUSION: Common variants in the AHSG gene are strongly associated with fetuin-A levels, but their concurrent association with CHD risk in current prospective studies is inconsistent. Further investigation in studies with measured fetuin-A and AHSG variants is needed to clarify the potential causal association of fetuin-A with CHD risk.
Keywords: Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Carotid Intima-Media Thickness; Coronary Vessels; Female; Genetic Variation; Genotype; Heart Diseases; Humans; Insulin Resistance; Longitudinal Studies; Male; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Vascular Calcification

Fibrosis-related biomarkers and large and small vessel disease: the Cardiovascular Health Study. - Agarwal, Isha; Arnold, Alice; Glazer, Nicole L; Barasch, Eddy; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Jensen, Richard A; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; et al. (Atherosclerosis, 2015)
OBJECTIVE: Fibrosis has been implicated in a number of pathological, organ-based conditions of the liver, kidney, heart, and lungs. The objective of this study was to determine whether biomarkers of fibrosis are associated with vascular disease in the large and/or small vessels. METHODS: We evaluated the associations of two circulating biomarkers of fibrosis, transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with incident peripheral artery disease (PAD) and subclinical macrovascular (carotid intima-media thickness, flow-mediated vasodilation, ankle-brachial index, retinal vein diameter), and microvascular (retinal artery diameter and retinopathy) disease among older adults in the Cardiovascular Health Study. We measured TGF-β and PIIINP from samples collected in 1996 and ascertained clinical PAD through 2011. Measurements of large and small vessels were collected between 1996 and 1998. RESULTS: After adjustment for sociodemographic, clinical, and biochemical risk factors, TGF-β was associated with incident PAD (hazard ratio [HR] = 1.36 per doubling of TGF-β, 95% confidence interval [CI] = 1.04, 1.78) and retinal venular diameter (1.63 μm per doubling of TGF-β, CI = 0.23, 3.02). PIIINP was not associated with incident PAD, but was associated with carotid intima-media thickness (0.102 mm per doubling of PIIINP, CI = 0.029, 0.174) and impaired brachial artery reactivity (-0.20% change per doubling of PIIINP, CI = -0.39, -0.02). Neither TGF-β nor PIIINP were associated with retinal arteriolar diameter or retinopathy. CONCLUSIONS: Serum concentrations of fibrosis-related biomarkers were associated with several measures of large vessel disease, including incident PAD, but not with small vessel disease. Fibrosis may contribute to large vessel atherosclerosis in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Brachial Artery; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cross-Sectional Studies; Female; Fibrosis; Humans; Incidence; Male; Peptide Fragments; Peripheral Arterial Disease; Predictive Value of Tests; Procollagen; Prognosis; Prospective Studies; Retinal Diseases; Risk Factors; Transforming Growth Factor beta; United States; Vasodilation

Gene × dietary pattern interactions in obesity: analysis of up to 68 317 adults of European ancestry. - Nettleton, Jennifer A; Follis, Jack L; Ngwa, Julius S; Smith, Caren E; Ahmad, Shafqat; Tanaka, Toshiko; Wojczynski, Mary K; Voortman, Trudy; Lemaitre, Rozenn N; Kristiansson, Kati; Nuotio, Marja-Liisa; Houston, Denise K; et al. (Hum Mol Genet, 2015)
Obesity is highly heritable. Genetic variants showing robust associations with obesity traits have been identified through genome-wide association studies. We investigated whether a composite score representing healthy diet modifies associations of these variants with obesity traits. Totally, 32 body mass index (BMI)- and 14 waist-hip ratio (WHR)-associated single nucleotide polymorphisms were genotyped, and genetic risk scores (GRS) were calculated in 18 cohorts of European ancestry (n = 68 317). Diet score was calculated based on self-reported intakes of whole grains, fish, fruits, vegetables, nuts/seeds (favorable) and red/processed meats, sweets, sugar-sweetened beverages and fried potatoes (unfavorable). Multivariable adjusted, linear regression within each cohort followed by inverse variance-weighted, fixed-effects meta-analysis was used to characterize: (a) associations of each GRS with BMI and BMI-adjusted WHR and (b) diet score modification of genetic associations with BMI and BMI-adjusted WHR. Nominally significant interactions (P = 0.006-0.04) were observed between the diet score and WHR-GRS (but not BMI-GRS), two WHR loci (GRB14 rs10195252; LYPLAL1 rs4846567) and two BMI loci (LRRN6C rs10968576; MTIF3 rs4771122), for the respective BMI-adjusted WHR or BMI outcomes. Although the magnitudes of these select interactions were small, our data indicated that associations between genetic predisposition and obesity traits were stronger with a healthier diet. Our findings generate interesting hypotheses; however, experimental and functional studies are needed to determine their clinical relevance.
Keywords: Adult; Body Mass Index; Case-Control Studies; Diet, Western; Epistasis, Genetic; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide

Gene-centric approach identifies new and known loci for FVIII activity and VWF antigen levels in European Americans and African Americans. - Tang, Weihong; Cushman, Mary; Green, David; Rich, Stephen S; Lange, Leslie A; Yang, Qiong; Tracy, Russell P; Tofler, Geoffrey H; Basu, Saonli; Wilson, James G; Keating, Brendan J; Weng, Lu-Chen; et al. (Am J Hematol, 2015)
Coagulation factor VIII and von Willebrand factor (VWF) are key proteins in procoagulant activation. Higher FVIII coagulant activity (FVIII :C) and VWF antigen (VWF :Ag) are risk factors for cardiovascular disease and venous thromboembolism. Beyond associations with ABO blood group, genetic determinants of FVIII and VWF are not well understood, especially in non European-American populations. We performed a genetic association study of FVIII :C and VWF:Ag that assessed 50,000 gene-centric single nucleotide polymorphisms (SNPs) in 18,556 European Americans (EAs) and 5,047 African Americans (AAs) from five population-based cohorts. Previously unreported associations for FVIII :C were identified in both AAs and EAs with KNG1 (most significantly associated SNP rs710446, Ile581Thr, Ile581Thr, P = 5.10 × 10(-7) in EAs and P = 3.88 × 10(-3) in AAs) and VWF rs7962217 (Gly2705Arg,P = 6.30 × 10(-9) in EAs and P = 2.98 × 10(-2) in AAs. Significant associations for FVIII :C were also observed with F8/TMLHE region SNP rs12557310 in EAs (P = 8.02 × 10(-10) ), with VWF rs1800380 in AAs (P = 5.62 × 10(-11) ), and with MAT1A rs2236568 in AAs (P51.69 × 10(-6) ). We replicated previously reported associations of FVIII :C and VWF :Ag with the ABO blood group, VWF rs1063856(Thr789Ala), rs216321 (Ala852Gln), and VWF rs2229446 (Arg2185Gln). Findings from this study expand our understanding of genetic influences for FVIII :C and VWF :Ag in both EAs and AAs.
Keywords: Adult; African Americans; Aged; European Continental Ancestry Group; Factor VIII; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Methionine Adenosyltransferase; Middle Aged; Polymorphism, Single Nucleotide; Venous Thromboembolism; von Willebrand Factor

Gene-Environment Interactions of Circadian-Related Genes for Cardiometabolic Traits. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Garaulet, Marta; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Kiefte-de Jong, Jessica C; Lamon-Fava, Stefania; Scheer, Frank A J L; Bartz, Traci M; et al. (Diabetes Care, 2015)
OBJECTIVE: Common circadian-related gene variants associate with increased risk for metabolic alterations including type 2 diabetes. However, little is known about whether diet and sleep could modify associations between circadian-related variants (CLOCK-rs1801260, CRY2-rs11605924, MTNR1B-rs1387153, MTNR1B-rs10830963, NR1D1-rs2314339) and cardiometabolic traits (fasting glucose [FG], HOMA-insulin resistance, BMI, waist circumference, and HDL-cholesterol) to facilitate personalized recommendations. RESEARCH DESIGN AND METHODS: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations and interactions between dietary intake/sleep duration and selected variants on cardiometabolic traits from 15 cohort studies including up to 28,190 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. RESULTS: We observed significant associations between relative macronutrient intakes and glycemic traits and short sleep duration (<7 h) and higher FG and replicated known MTNR1B associations with glycemic traits. No interactions were evident after accounting for multiple comparisons. However, we observed nominally significant interactions (all P < 0.01) between carbohydrate intake and MTNR1B-rs1387153 for FG with a 0.003 mmol/L higher FG with each additional 1% carbohydrate intake in the presence of the T allele, between sleep duration and CRY2-rs11605924 for HDL-cholesterol with a 0.010 mmol/L higher HDL-cholesterol with each additional hour of sleep in the presence of the A allele, and between long sleep duration (≥9 h) and MTNR1B-rs1387153 for BMI with a 0.60 kg/m(2) higher BMI with long sleep duration in the presence of the T allele relative to normal sleep duration (≥7 to <9 h). CONCLUSIONS: Our results suggest that lower carbohydrate intake and normal sleep duration may ameliorate cardiometabolic abnormalities conferred by common circadian-related genetic variants. Until further mechanistic examination of the nominally significant interactions is conducted, recommendations applicable to the general population regarding diet—specifically higher carbohydrate and lower fat composition—and normal sleep duration should continue to be emphasized among individuals with the investigated circadian-related gene variants.
Keywords: Adult; Alleles; Blood Glucose; Circadian Rhythm Signaling Peptides and Proteins; Cohort Studies; Diabetes Mellitus, Type 2; Diet, Fat-Restricted; European Continental Ancestry Group; Fasting; Female; Gene-Environment Interaction; Humans; Insulin Resistance; Male; Middle Aged; Multicenter Studies as Topic; Observational Studies as Topic; Phenotype; Polymorphism, Single Nucleotide; Sleep; Waist Circumference

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic loci associated with circulating levels of very long-chain saturated fatty acids. - Lemaitre, Rozenn N; King, Irena B; Kabagambe, Edmond K; Wu, Jason H Y; McKnight, Barbara; Manichaikul, Ani; Guan, Weihua; Sun, Qi; Chasman, Daniel I; Foy, Millennia; Wang, Lu; Zhu, Jingwen; et al. (J Lipid Res, 2015)
Very long-chain saturated fatty acids (VLSFAs) are saturated fatty acids with 20 or more carbons. In contrast to the more abundant saturated fatty acids, such as palmitic acid, there is growing evidence that circulating VLSFAs may have beneficial biological properties. Whether genetic factors influence circulating levels of VLSFAs is not known. We investigated the association of common genetic variation with plasma phospholipid/erythrocyte levels of three VLSFAs by performing genome-wide association studies in seven population-based cohorts comprising 10,129 subjects of European ancestry. We observed associations of circulating VLSFA concentrations with common variants in two genes, serine palmitoyl-transferase long-chain base subunit 3 (SPTLC3), a gene involved in the rate-limiting step of de novo sphingolipid synthesis, and ceramide synthase 4 (CERS4). The SPTLC3 variant at rs680379 was associated with higher arachidic acid (20:0 , P = 5.81 × 10(-13)). The CERS4 variant at rs2100944 was associated with higher levels of 20:0 (P = 2.65 × 10(-40)) and in analyses that adjusted for 20:0, with lower levels of behenic acid (P = 4.22 × 10(-26)) and lignoceric acid (P = 3.20 × 10(-21)). These novel associations suggest an inter-relationship of circulating VLSFAs and sphingolipid synthesis.
Keywords: Cohort Studies; Fatty Acids; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans

Genetic loci associated with circulating phospholipid trans fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Mozaffarian, Dariush; Kabagambe, Edmond K; Johnson, Catherine O; Lemaitre, Rozenn N; Manichaikul, Ani; Sun, Qi; Foy, Millennia; Wang, Lu; Wiener, Howard; Irvin, Marguerite R; Rich, Stephen S; Wu, Hongyu; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Circulating trans fatty acids (TFAs), which cannot be synthesized by humans, are linked to adverse health outcomes. Although TFAs are obtained from diet, little is known about subsequent influences (e.g., relating to incorporation, metabolism, or intercompetition with other fatty acids) that could alter circulating concentrations and possibly modulate or mediate impacts on health. OBJECTIVE: The objective was to elucidate novel biologic pathways that may influence circulating TFAs by evaluating associations between common genetic variation and TFA biomarkers. DESIGN: We performed meta-analyses using 7 cohorts of European-ancestry participants (n = 8013) having measured genome-wide variation in single-nucleotide polymorphisms (SNPs) and circulating TFA biomarkers (erythrocyte or plasma phospholipids), including trans-16:1n-7, total trans-18:1, trans/cis-18:2, cis/trans-18:2, and trans/trans-18:2. We further evaluated SNPs with genome-wide significant associations among African Americans (n = 1082), Chinese Americans (n = 669), and Hispanic Americans (n = 657) from 2 of these cohorts. RESULTS: Among European-ancestry participants, 31 SNPs in or near the fatty acid desaturase (FADS) 1 and 2 cluster were associated with cis/trans-18:2; a top hit was rs174548 (β = 0.0035, P = 4.90 × 10(-15)), an SNP previously associated with circulating n-3 and n-6 polyunsaturated fatty acid concentrations. No significant association was identified for other TFAs. rs174548 in FADS1/2 was also associated with cis/trans-18:2 in Hispanic Americans (β = 0.0053, P = 1.05 × 10(-6)) and Chinese Americans (β = 0.0028, P = 0.002) but not African Americans (β = 0.0009, P = 0.34); however, in African Americans, fine mapping identified a top hit in FADS2 associated with cis/trans-18:2 (rs174579: β = 0.0118, P = 4.05 × 10(-5)). The association between rs174548 and cis/trans-18:2 remained significant after further adjustment for individual circulating n-3 and n-6 fatty acids, except arachidonic acid. After adjustment for arachidonic acid concentrations, the association between rs174548 and cis/trans-18:2 was nearly eliminated in European-ancestry participants (β-coefficient reduced by 86%), with similar reductions in Hispanic Americans and Chinese Americans. CONCLUSIONS: Our findings provide novel evidence for genetic regulation of cis/trans-18:2 by the FADS1/2 cluster and suggest that this regulation may be influenced/mediated by concentrations of arachidonic acid, an n-6 polyunsaturated fat.
Keywords: African Americans; Arachidonic Acid; Asian Americans; Biomarkers; European Continental Ancestry Group; Fatty Acids, Omega-6; Gene Frequency; Genetic Association Studies; Genetic Loci; Genotyping Techniques; Humans; Phospholipids; Polymorphism, Single Nucleotide; Trans Fatty Acids

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

Genome of The Netherlands population-specific imputations identify an ABCA6 variant associated with cholesterol levels. - van Leeuwen, Elisabeth M; Karssen, Lennart C; Deelen, Joris; Isaacs, Aaron; Medina-Gómez, Carolina; Mbarek, Hamdi; Kanterakis, Alexandros; Trompet, Stella; Postmus, Iris; Verweij, Niek; van Enckevort, David J; Huffman, Jennifer E; et al. (Nat Commun, 2015)
Variants associated with blood lipid levels may be population-specific. To identify low-frequency variants associated with this phenotype, population-specific reference panels may be used. Here we impute nine large Dutch biobanks (~35,000 samples) with the population-specific reference panel created by the Genome of The Netherlands Project and perform association testing with blood lipid levels. We report the discovery of five novel associations at four loci (P value <6.61 × 10(-4)), including a rare missense variant in ABCA6 (rs77542162, p.Cys1359Arg, frequency 0.034), which is predicted to be deleterious. The frequency of this ABCA6 variant is 3.65-fold increased in the Dutch and its effect (βLDL-C=0.135, βTC=0.140) is estimated to be very similar to those observed for single variants in well-known lipid genes, such as LDLR.
Keywords: ATP-Binding Cassette Transporters; Cholesterol; Gene Frequency; Genetic Association Studies; Humans; Mutation, Missense; Netherlands

Genome-wide meta-analysis identifies six novel loci associated with habitual coffee consumption. - Cornelis, M C; Byrne, E M; Esko, T; Nalls, M A; Ganna, A; Paynter, N; Monda, K L; Amin, N; Fischer, K; Renstrom, F; Ngwa, J S; Huikari, V; et al. (Mol Psychiatry, 2015)
Coffee, a major dietary source of caffeine, is among the most widely consumed beverages in the world and has received considerable attention regarding health risks and benefits. We conducted a genome-wide (GW) meta-analysis of predominately regular-type coffee consumption (cups per day) among up to 91,462 coffee consumers of European ancestry with top single-nucleotide polymorphisms (SNPs) followed-up in ~30 062 and 7964 coffee consumers of European and African-American ancestry, respectively. Studies from both stages were combined in a trans-ethnic meta-analysis. Confirmed loci were examined for putative functional and biological relevance. Eight loci, including six novel loci, met GW significance (log10Bayes factor (BF)>5.64) with per-allele effect sizes of 0.03-0.14 cups per day. Six are located in or near genes potentially involved in pharmacokinetics (ABCG2, AHR, POR and CYP1A2) and pharmacodynamics (BDNF and SLC6A4) of caffeine. Two map to GCKR and MLXIPL genes related to metabolic traits but lacking known roles in coffee consumption. Enhancer and promoter histone marks populate the regions of many confirmed loci and several potential regulatory SNPs are highly correlated with the lead SNP of each. SNP alleles near GCKR, MLXIPL, BDNF and CYP1A2 that were associated with higher coffee consumption have previously been associated with smoking initiation, higher adiposity and fasting insulin and glucose but lower blood pressure and favorable lipid, inflammatory and liver enzyme profiles (P<5 × 10(-8)).Our genetic findings among European and African-American adults reinforce the role of caffeine in mediating habitual coffee consumption and may point to molecular mechanisms underlying inter-individual variability in pharmacological and health effects of coffee.
Keywords: Adaptor Proteins, Signal Transducing; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Brain-Derived Neurotrophic Factor; Coffea; Cytochrome P-450 CYP1A2; Food Habits; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

Habitual sleep duration is associated with BMI and macronutrient intake and may be modified by CLOCK genetic variants. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Cade, Brian E; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Lamon-Fava, Stefania; Richardson, Kris; Saxena, Richa; Scheer, Frank A J L; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Short sleep duration has been associated with greater risks of obesity, hypertension, diabetes, and cardiovascular disease. Also, common genetic variants in the human Circadian Locomotor Output Cycles Kaput (CLOCK) show associations with ghrelin and total energy intake. OBJECTIVES: We examined associations between habitual sleep duration, body mass index (BMI), and macronutrient intake and assessed whether CLOCK variants modify these associations. DESIGN: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations of sleep duration and BMI and macronutrient intake as percentages of total energy as well as interactions with CLOCK variants from 9 cohort studies including up to 14,906 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. RESULTS: We observed a significant association between sleep duration and lower BMI (β ± SE = 0.16 ± 0.04, P < 0.0001) in the overall sample; however, associations between sleep duration and relative macronutrient intake were evident in age- and sex-stratified analyses only. We observed a significant association between sleep duration and lower saturated fatty acid intake in younger (aged 20-64 y) adults (men: 0.11 ± 0.06%, P = 0.03; women: 0.10 ± 0.05%, P = 0.04) and with lower carbohydrate (-0.31 ± 0.12%, P < 0.01), higher total fat (0.18 ± 0.09%, P = 0.05), and higher PUFA (0.05 ± 0.02%, P = 0.02) intakes in older (aged 65-80 y) women. In addition, the following 2 nominally significant interactions were observed: between sleep duration and rs12649507 on PUFA intake and between sleep duration and rs6858749 on protein intake. CONCLUSIONS: Our results indicate that longer habitual sleep duration is associated with lower BMI and age- and sex-specific favorable dietary behaviors. Differences in the relative intake of specific macronutrients associated with short sleep duration could, at least in part, explain previously reported associations between short sleep duration and chronic metabolic abnormalities. In addition, the influence of obesity-associated CLOCK variants on the association between sleep duration and macronutrient intake suggests that longer habitual sleep duration could ameliorate the genetic predisposition to obesity via a favorable dietary profile.
Keywords: Adult; Body Mass Index; CLOCK Proteins; Cohort Studies; Cross-Sectional Studies; Diet; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fatty Acids, Unsaturated; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Sleep; Young Adult

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Integrative pathway genomics of lung function and airflow obstruction. - Gharib, Sina A; Loth, Daan W; Soler Artigas, Maria; Birkland, Timothy P; Wilk, Jemma B; Wain, Louise V; Brody, Jennifer A; Obeidat, Ma'en; Hancock, Dana B; Tang, Wenbo; Rawal, Rajesh; Boezen, H Marike; et al. (Hum Mol Genet, 2015)
Chronic respiratory disorders are important contributors to the global burden of disease. Genome-wide association studies (GWASs) of lung function measures have identified several trait-associated loci, but explain only a modest portion of the phenotypic variability. We postulated that integrating pathway-based methods with GWASs of pulmonary function and airflow obstruction would identify a broader repertoire of genes and processes influencing these traits. We performed two independent GWASs of lung function and applied gene set enrichment analysis to one of the studies and validated the results using the second GWAS. We identified 131 significantly enriched gene sets associated with lung function and clustered them into larger biological modules involved in diverse processes including development, immunity, cell signaling, proliferation and arachidonic acid. We found that enrichment of gene sets was not driven by GWAS-significant variants or loci, but instead by those with less stringent association P-values. Next, we applied pathway enrichment analysis to a meta-analyzed GWAS of airflow obstruction. We identified several biologic modules that functionally overlapped with those associated with pulmonary function. However, differences were also noted, including enrichment of extracellular matrix (ECM) processes specifically in the airflow obstruction study. Network analysis of the ECM module implicated a candidate gene, matrix metalloproteinase 10 (MMP10), as a putative disease target. We used a knockout mouse model to functionally validate MMP10's role in influencing lung's susceptibility to cigarette smoke-induced emphysema. By integrating pathway analysis with population-based genomics, we unraveled biologic processes underlying pulmonary function traits and identified a candidate gene for obstructive lung disease.
Keywords: Airway Obstruction; Animals; Cell Proliferation; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Immune System; Lung; Male; Metabolic Networks and Pathways; Mice; Phenotype; Polymorphism, Single Nucleotide; Signal Transduction

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

A Meta-analysis of the Association of Estimated GFR, Albuminuria, Diabetes Mellitus, and Hypertension With Acute Kidney Injury. - James, Matthew T; Grams, Morgan E; Woodward, Mark; Elley, C Raina; Green, Jamie A; Wheeler, David C; de Jong, Paul; Gansevoort, Ron T; Levey, Andrew S; Warnock, David G; Sarnak, Mark J (Am J Kidney Dis, 2015)
BACKGROUND: Diabetes mellitus and hypertension are risk factors for acute kidney injury (AKI). Whether estimated glomerular filtration rate (eGFR) and urine albumin-creatinine ratio (ACR) remain risk factors for AKI in the presence and absence of these conditions is uncertain. STUDY DESIGN: Meta-analysis of cohort studies. SETTING & POPULATION: 8 general-population (1,285,045 participants) and 5 chronic kidney disease (CKD; 79,519 participants) cohorts. SELECTION CRITERIA FOR STUDIES: Cohorts participating in the CKD Prognosis Consortium. PREDICTORS: Diabetes and hypertension status, eGFR by the 2009 CKD Epidemiology Collaboration creatinine equation, urine ACR, and interactions. OUTCOME: Hospitalization with AKI, using Cox proportional hazards models to estimate HRs of AKI and random-effects meta-analysis to pool results. RESULTS: During a mean follow-up of 4 years, there were 16,480 episodes of AKI in the general-population and 2,087 episodes in the CKD cohorts. Low eGFRs and high ACRs were associated with higher risks of AKI in individuals with or without diabetes and with or without hypertension. When compared to a common reference of eGFR of 80mL/min/1.73m(2) in nondiabetic patients, HRs for AKI were generally higher in diabetic patients at any level of eGFR. The same was true for diabetic patients at all levels of ACR compared with nondiabetic patients. The risk gradient for AKI with lower eGFRs was greater in those without diabetes than with diabetes, but similar with higher ACRs in those without versus with diabetes. Those with hypertension had a higher risk of AKI at eGFRs>60mL/min/1.73m(2) than those without hypertension. However, risk gradients for AKI with both lower eGFRs and higher ACRs were greater for those without than with hypertension. LIMITATIONS: AKI identified by diagnostic code. CONCLUSIONS: Lower eGFRs and higher ACRs are associated with higher risks of AKI among individuals with or without either diabetes or hypertension.
Keywords: Acute Kidney Injury; Adult; Aged; Comorbidity; Diabetes Mellitus; Disease Progression; Female; Glomerular Filtration Rate; Humans; Hypertension; Incidence; Kidney Failure, Chronic; Male; Middle Aged; Prognosis; Renal Insufficiency, Chronic

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Continental Population Groups; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Stroke; White Matter

Novel loci associated with usual sleep duration: the CHARGE Consortium Genome-Wide Association Study. - Gottlieb, D J; Hek, K; Chen, T-H; Watson, N F; Eiriksdottir, G; Byrne, E M; Cornelis, M; Warby, S C; Bandinelli, S; Cherkas, L; Evans, D S; Grabe, H J; et al. (Mol Psychiatry, 2015)
Usual sleep duration is a heritable trait correlated with psychiatric morbidity, cardiometabolic disease and mortality, although little is known about the genetic variants influencing this trait. A genome-wide association study (GWAS) of usual sleep duration was conducted using 18 population-based cohorts totaling 47 180 individuals of European ancestry. Genome-wide significant association was identified at two loci. The strongest is located on chromosome 2, in an intergenic region 35- to 80-kb upstream from the thyroid-specific transcription factor PAX8 (lowest P=1.1 × 10(-9)). This finding was replicated in an African-American sample of 4771 individuals (lowest P=9.3 × 10(-4)). The strongest combined association was at rs1823125 (P=1.5 × 10(-10), minor allele frequency 0.26 in the discovery sample, 0.12 in the replication sample), with each copy of the minor allele associated with a sleep duration 3.1 min longer per night. The alleles associated with longer sleep duration were associated in previous GWAS with a more favorable metabolic profile and a lower risk of attention deficit hyperactivity disorder. Understanding the mechanisms underlying these associations may help elucidate biological mechanisms influencing sleep duration and its association with psychiatric, metabolic and cardiovascular disease.
Keywords: Adult; African Americans; Aged; Dyssomnias; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Self Report; Sleep

Physical Activity, Physical Fitness, and Leukocyte Telomere Length: The Cardiovascular Health Study. - Soares-Miranda, Luisa; Imamura, Fumiaki; Siscovick, David; Jenny, Nancy Swords; Fitzpatrick, Annette L; Mozaffarian, Dariush (Med Sci Sports Exerc, 2015)
INTRODUCTION: The influence of physical activity (PA) and physical fitness (PF) at older ages on changes in telomere length (TL)--repetitive DNA sequences that may mark biologic aging--is not well-established. Few prior studies (mainly cross-sectional) have been conducted in older adults, and few studies have evaluated PF. METHODS: We investigated cross-sectional and prospective associations of PA and PF with leukocyte TL among 582 older adults (mean ± SD age, 73 ± 5 yr at baseline) in the Cardiovascular Health Study, with serial TL measures and PA and PF assessed multiple times. Cross-sectional associations were assessed using multivariable repeated-measures regression, in which cumulatively averaged PA and PF measures were related to TL. Longitudinal analyses assessed cumulatively averaged PA and PF against later changes in TL, and changes in cumulatively averaged PA and PF against changes in TL. RESULTS: Cross-sectionally, greater walking distance and chair test performance, but not other PA and PF measures, were each associated with longer TL (P trend = 0.007 and 0.04, respectively). In longitudinal analyses, no significant associations of baseline PA and PF with change in TL were observed. In contrast, changes in leisure-time activity and chair test performance were each inversely associated with changes in TL. CONCLUSIONS: Cross-sectional analyses suggest that greater PA and PF are associated with longer TL. Prospective analyses show that changes in PA and PF are associated with differences in changes in TL. Even later in life, changes in certain PA and PF measures are associated with changes in TL, suggesting that leisure-time activity and fitness could reduce leukocyte telomere attrition among older adults.
Keywords: Aged; Aging; Cross-Sectional Studies; Exercise Test; Female; Hand Strength; Humans; Leukocytes; Male; Motor Activity; Physical Fitness; Prospective Studies; Telomere Homeostasis; Walking

Plasma Levels of Soluble Interleukin-2 Receptor α: Associations With Clinical Cardiovascular Events and Genome-Wide Association Scan. - Durda, Peter; Sabourin, Jeremy; Lange, Ethan M; Nalls, Mike A; Mychaleckyj, Josyf C; Jenny, Nancy Swords; Li, Jin; Walston, Jeremy; Harris, Tamara B; Psaty, Bruce M; Valdar, William; Liu, Yongmei; et al. (Arterioscler Thromb Vasc Biol, 2015)
OBJECTIVE: Interleukin (IL) -2 receptor subunit α regulates lymphocyte activation, which plays an important role in atherosclerosis. Associations between soluble IL-2Rα (sIL-2Rα) and cardiovascular disease (CVD) have not been widely studied and little is known about the genetic determinants of sIL-2Rα levels. APPROACH AND RESULTS: We measured baseline levels of sIL-2Rα in 4408 European American (EA) and 766 African American (AA) adults from the Cardiovascular Health Study (CHS) and examined associations with baseline CVD risk factors, subclinical CVD, and incident CVD events. We also performed a genome-wide association study for sIL-2Rα in CHS (2964 EAs and 683 AAs) and further combined CHS EA results with those from two other EA cohorts in a meta-analysis (n=4464 EAs). In age, sex- and race- adjusted models, sIL-2Rα was positively associated with current smoking, type 2 diabetes mellitus, hypertension, insulin, waist circumference, C-reactive protein, IL-6, fibrinogen, internal carotid wall thickness, all-cause mortality, CVD mortality, and incident CVD, stroke, and heart failure. When adjusted for baseline CVD risk factors and subclinical CVD, associations with all-cause mortality, CVD mortality, and heart failure remained significant in both EAs and AAs. In the EA genome-wide association study analysis, we observed 52 single-nucleotide polymorphisms in the chromosome 10p15-14 region, which contains IL2RA, IL15RA, and RMB17, that reached genome-wide significance (P<5×10(-8)). The most significant single-nucleotide polymorphism was rs7911500 (P=1.31×10(-75)). The EA meta-analysis results were highly consistent with CHS-only results. No single-nucleotide polymorphisms reached statistical significance in the AAs. CONCLUSIONS: These results support a role for sIL-2Rα in atherosclerosis and provide evidence for multiple-associated single-nucleotide polymorphisms at chromosome 10p15-14.
Keywords: Adult; African Americans; Age Distribution; Aged; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Incidence; Interleukin-2 Receptor alpha Subunit; Kaplan-Meier Estimate; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Distribution; Survival Analysis

Population genomic analysis of 962 whole genome sequences of humans reveals natural selection in non-coding regions. - Yu, Fuli; Lu, Jian; Liu, Xiaoming; Gazave, Elodie; Chang, Diana; Raj, Srilakshmi; Hunter-Zinck, Haley; Blekhman, Ran; Arbiza, Leonardo; Van Hout, Cris; Morrison, Alanna; Johnson, Andrew D; et al. (PLoS One, 2015)
Whole genome analysis in large samples from a single population is needed to provide adequate power to assess relative strengths of natural selection across different functional components of the genome. In this study, we analyzed next-generation sequencing data from 962 European Americans, and found that as expected approximately 60% of the top 1% of positive selection signals lie in intergenic regions, 33% in intronic regions, and slightly over 1% in coding regions. Several detailed functional annotation categories in intergenic regions showed statistically significant enrichment in positively selected loci when compared to the null distribution of the genomic span of ENCODE categories. There was a significant enrichment of purifying selection signals detected in enhancers, transcription factor binding sites, microRNAs and target sites, but not on lincRNA or piRNAs, suggesting different evolutionary constraints for these domains. Loci in "repressed or low activity regions" and loci near or overlapping the transcription start site were the most significantly over-represented annotations among the top 1% of signals for positive selection.
Keywords: DNA, Intergenic; Genetic Loci; Humans; Metagenomics; Open Reading Frames; Polymorphism, Single Nucleotide

Positive association of tomato consumption with serum urate: support for tomato consumption as an anecdotal trigger of gout flares. - Flynn, Tanya J; Cadzow, Murray; Dalbeth, Nicola; Jones, Peter B; Stamp, Lisa K; Hindmarsh, Jennie Harré; Todd, Alwyn S; Walker, Robert J; Topless, Ruth; Merriman, Tony R (BMC Musculoskelet Disord, 2015)
BACKGROUND: Gout is a consequence of an innate immune reaction to monosodium urate crystals deposited in joints. Acute gout attacks can be triggered by dietary factors that are themselves associated with serum urate levels. Tomato consumption is an anecdotal trigger of gout flares. This study aimed to measure the frequency of tomato consumption as a self-reported trigger of gout attacks in a large New Zealand sample set, and to test the hypothesis that tomato consumption is associated with serum urate levels. METHODS: Two thousand fifty one New Zealanders (of Māori, Pacific Island, European or other ancestry) with clinically-ascertained gout were asked about gout trigger foods. European individuals from the Atherosclerosis Risk In Communities (ARIC; n = 7517) Study, Cardiovascular Health Study (CHS; n = 2151) and Framingham Heart Study (FHS; n = 3052) were used to test, in multivariate-adjusted analyses, for association between serum urate and tomato intake. RESULTS: Seventy one percent of people with gout reported having ≥1 gout trigger food. Of these 20% specifically mentioned tomatoes, the 4(th) most commonly reported trigger food. There was association between tomato intake and serum urate levels in the ARIC, CHS and FHS combined cohort (β = 0.66 μmolL(-1) increase in serum urate per additional serve per week; P = 0.006) - evident in both sexes (men: β = 0.84 μmolL(-1), P = 0.035; women: β = 0.59 μmolL (-1), P = 0.041). CONCLUSIONS: While our descriptive and observational data are unable to support the claim that tomato consumption is a trigger of gout attacks, the positive association between tomato consumption and serum urate levels suggests that the self-reporting of tomatoes as a dietary trigger by people with gout has a biological basis.
Keywords: Adolescent; Adult; Aged; European Continental Ancestry Group; Female; Gout; Humans; Hyperuricemia; Lycopersicon esculentum; Male; Middle Aged; New Zealand; Oceanic Ancestry Group; Surveys and Questionnaires; Uric Acid; Young Adult

Predicting Future Years of Life, Health, and Functional Ability: A Healthy Life Calculator for Older Adults. - Diehr, Paula; Diehr, Michael; Arnold, Alice; Yee, Laura M; Odden, Michelle C; Hirsch, Calvin H; Thielke, Stephen; Psaty, Bruce M; Johnson, W Craig; Kizer Md, Jorge R; Newman, Anne (Gerontol Geriatr Med, 2015)
To create personalized estimates of future health and ability status for older adults.Data came from the Cardiovascular Health Study (CHS), a large longitudinal study. Outcomes included years of life, years of healthy life (based on self-rated health), years of able life (based on activities of daily living), and years of healthy and able life. We developed regression estimates using the demographic and health characteristics that best predicted the four outcomes. Internal and external validity were assessed.A prediction equation based on 11 variables accounted for about 40% of the variability for each outcome. Internal validity was excellent, and external validity was satisfactory. The resulting CHS Healthy Life Calculator (CHSHLC) is available at http://healthylifecalculator.org.CHSHLC provides a well-documented estimate of future years of healthy and able life for older adults, who may use it in planning for the future.

Rare and Coding Region Genetic Variants Associated With Risk of Ischemic Stroke: The NHLBI Exome Sequence Project. - Auer, Paul L; Nalls, Mike; Meschia, James F; Worrall, Bradford B; Longstreth, W T; Seshadri, Sudha; Kooperberg, Charles; Burger, Kathleen M; Carlson, Christopher S; Carty, Cara L; Chen, Wei-Min; Cupples, L Adrienne; et al. (JAMA Neurol, 2015)
IMPORTANCE: Stroke is the second leading cause of death and the third leading cause of years of life lost. Genetic factors contribute to stroke prevalence, and candidate gene and genome-wide association studies (GWAS) have identified variants associated with ischemic stroke risk. These variants often have small effects without obvious biological significance. Exome sequencing may discover predicted protein-altering variants with a potentially large effect on ischemic stroke risk. OBJECTIVE: To investigate the contribution of rare and common genetic variants to ischemic stroke risk by targeting the protein-coding regions of the human genome. DESIGN, SETTING, AND PARTICIPANTS: The National Heart, Lung, and Blood Institute (NHLBI) Exome Sequencing Project (ESP) analyzed approximately 6000 participants from numerous cohorts of European and African ancestry. For discovery, 365 cases of ischemic stroke (small-vessel and large-vessel subtypes) and 809 European ancestry controls were sequenced; for replication, 47 affected sibpairs concordant for stroke subtype and an African American case-control series were sequenced, with 1672 cases and 4509 European ancestry controls genotyped. The ESP's exome sequencing and genotyping started on January 1, 2010, and continued through June 30, 2012. Analyses were conducted on the full data set between July 12, 2012, and July 13, 2013. MAIN OUTCOMES AND MEASURES: Discovery of new variants or genes contributing to ischemic stroke risk and subtype (primary analysis) and determination of support for protein-coding variants contributing to risk in previously published candidate genes (secondary analysis). RESULTS: We identified 2 novel genes associated with an increased risk of ischemic stroke: a protein-coding variant in PDE4DIP (rs1778155; odds ratio, 2.15; P = 2.63 × 10(-8)) with an intracellular signal transduction mechanism and in ACOT4 (rs35724886; odds ratio, 2.04; P = 1.24 × 10(-7)) with a fatty acid metabolism; confirmation of PDE4DIP was observed in affected sibpair families with large-vessel stroke subtype and in African Americans. Replication of protein-coding variants in candidate genes was observed for 2 previously reported GWAS associations: ZFHX3 (cardioembolic stroke) and ABCA1 (large-vessel stroke). CONCLUSIONS AND RELEVANCE: Exome sequencing discovered 2 novel genes and mechanisms, PDE4DIP and ACOT4, associated with increased risk for ischemic stroke. In addition, ZFHX3 and ABCA1 were discovered to have protein-coding variants associated with ischemic stroke. These results suggest that genetic variation in novel pathways contributes to ischemic stroke risk and serves as a target for prediction, prevention, and therapy.
Keywords: Aged; Brain Ischemia; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Muscle Proteins; National Heart, Lung, and Blood Institute (U.S.); Nuclear Proteins; Open Reading Frames; Palmitoyl-CoA Hydrolase; Stroke; United States

Serum urate levels and the risk of hip fractures: data from the Cardiovascular Health Study. - Mehta, Tapan; Bůzková, Petra; Sarnak, Mark J; Chonchol, Michel; Cauley, Jane A; Wallace, Erin; Fink, Howard A; Robbins, John; Jalal, Diana (Metabolism, 2015)
PURPOSE: Uric acid inhibits vitamin D activation experimentally and higher serum urate levels are associated with higher parathyroid hormone levels in humans suggesting a link between uric acid and bone health. We hypothesized that hyperuricemia may increase the risk of fractures in older adults. METHODS: 1963 men and 2729 women ≥65 years of age who participated in the Cardiovascular Health Study and had baseline serum urate levels were included in the study. The primary outcome was incident hip fracture, assessed prospectively through June, 2008 by inpatient and outpatient records. The analysis was stratified by sex a priori. RESULTS: There was a U-shaped relationship between serum urate levels and hip fractures in men. Men in the lowest and the highest urate quartiles (<4.88 and ≥6.88 mg/dL respectively) had a significantly higher rate of fractures in unadjusted analysis. However, upon multivariate adjustment, only the HR for hip fracture in highest quartile versus the reference remained significant (HR 1.9; 95% C.I. 1.1, 3.1; p value 0.02). High serum urate levels were not associated with hip fractures in women. CONCLUSION: In this large prospective cohort of community-dwelling older adults, increased serum urate levels were associated with an increased risk of hip fractures in men. Further studies are needed to confirm these findings and to understand the mechanisms that underlie them.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Estrogen Replacement Therapy; Female; Health Surveys; Hip Fractures; Humans; Kaplan-Meier Estimate; Male; Prospective Studies; Risk; Sex Factors; United States; Uric Acid

Sex, Race, and Age Differences in Observed Years of Life, Healthy Life, and Able Life among Older Adults in The Cardiovascular Health Study. - Thielke, Stephen M; Diehr, Paula H; Yee, Laura M; Arnold, Alice M; Quiñones, Ana R; Whitson, Heather E; Jacob, Mini E; Newman, Anne B (J Pers Med, 2015)
OBJECTIVE: Longevity fails to account for health and functional status during aging. We sought to quantify differences in years of total life, years of healthy life, and years of able life among groups defined by age, sex, and race. DESIGN: Primary analysis of a cohort study. SETTING: 18 years of annual evaluations in four U.S. communities. PARTICIPANTS: 5888 men and women aged 65 and older. MEASUREMENTS: Years of life were calculated as the time from enrollment to death or 18 years. Years of total, healthy, and able life were determined from self-report during annual or semi-annual contacts. Cumulative years were summed across each of the age and sex groups. RESULTS: White women had the best outcomes for all three measures, followed by white men, non-white women, and non-white men. For example, at the mean age of 73, a white female participant could expect 12.9 years of life, 8.9 of healthy life and 9.5 of able life, while a non-white female could expect 12.6, 7.0, and 8.0 years, respectively. A white male could expect 11.2, 8.1, and 8.9 years of life, healthy life, and able life, and a non-white male 10.3, 6.2, and 7.9 years. Regardless of starting age, individuals of the same race and sex groups spent similar amounts (not proportions) of time in an unhealthy or unable state. CONCLUSION: Gender had a greater effect on longevity than did race, but race had a greater effect on years spent healthy or able. The mean number of years spent in an unable or sick state was surprisingly independent of the lifespan.

Sleep Disturbances and Glucose Metabolism in Older Adults: The Cardiovascular Health Study. - Strand, Linn Beate; Carnethon, Mercedes; Biggs, Mary Lou; Djoussé, Luc; Kaplan, Robert C; Siscovick, David S; Robbins, John A; Redline, Susan; Patel, Sanjay R; Janszky, Imre; Mukamal, Kenneth J (Diabetes Care, 2015)
OBJECTIVE: We examined the associations of symptoms of sleep-disordered breathing (SDB), which was defined as loud snoring, stopping breathing for a while during sleep, and daytime sleepiness, and insomnia with glucose metabolism and incident type 2 diabetes in older adults. RESEARCH DESIGN AND METHODS: Between 1989 and 1993, the Cardiovascular Health Study recruited 5,888 participants ≥65 years of age from four U.S. communities. Participants reported SDB and insomnia symptoms yearly through 1989-1994. In 1989-1990, participants underwent an oral glucose tolerance test, from which insulin secretion and insulin sensitivity were estimated. Fasting glucose levels were measured in 1989-1990 and again in 1992-1993, 1994-1995, 1996-1997, and 1998-1999, and medication use was ascertained yearly. We determined the cross-sectional associations of sleep symptoms with fasting glucose levels, 2-h glucose levels, insulin sensitivity, and insulin secretion using generalized estimated equations and linear regression models. We determined the associations of updated and averaged sleep symptoms with incident diabetes in Cox proportional hazards models. We adjusted for sociodemographics, lifestyle factors, and medical history. RESULTS: Observed apnea, snoring, and daytime sleepiness were associated with higher fasting glucose levels, higher 2-h glucose levels, lower insulin sensitivity, and higher insulin secretion. The risk of the development of type 2 diabetes was positively associated with observed apnea (hazard ratio [HR] 1.84 [95% CI 1.19-2.86]), snoring (HR 1.27 [95% CI 0.95-1.71]), and daytime sleepiness (HR 1.54 [95% CI 1.13-2.12]). In contrast, we did not find consistent associations between insomnia symptoms and glucose metabolism or incident type 2 diabetes. CONCLUSIONS: Easily collected symptoms of SDB are strongly associated with insulin resistance and the incidence of type 2 diabetes in older adults. Monitoring glucose metabolism in such patients may prove useful in identifying candidates for lifestyle or pharmacological therapy. Further studies are needed to determine whether insomnia symptoms affect the risk of diabetes in younger adults.
Keywords: Adult; Aged; Blood Glucose; Cardiovascular System; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Fasting; Female; Glucose Tolerance Test; Humans; Incidence; Insulin; Insulin Resistance; Male; Middle Aged; Sleep Apnea Syndromes; Sleep Initiation and Maintenance Disorders; Snoring; United States

Subclinical Hypothyroidism and the Risk of Stroke Events and Fatal Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Ikram, M Arfan; Blum, Manuel R; Collet, Tinh-Hai; Bakker, Stephan J L; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Hofman, Albert; Portegies, Marileen L P; et al. (J Clin Endocrinol Metab, 2015)
OBJECTIVE: The objective was to determine the risk of stroke associated with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: Published prospective cohort studies were identified through a systematic search through November 2013 without restrictions in several databases. Unpublished studies were identified through the Thyroid Studies Collaboration. We collected individual participant data on thyroid function and stroke outcome. Euthyroidism was defined as TSH levels of 0.45-4.49 mIU/L, and subclinical hypothyroidism was defined as TSH levels of 4.5-19.9 mIU/L with normal T4 levels. DATA EXTRACTION AND SYNTHESIS: We collected individual participant data on 47 573 adults (3451 subclinical hypothyroidism) from 17 cohorts and followed up from 1972-2014 (489 192 person-years). Age- and sex-adjusted pooled hazard ratios (HRs) for participants with subclinical hypothyroidism compared to euthyroidism were 1.05 (95% confidence interval [CI], 0.91-1.21) for stroke events (combined fatal and nonfatal stroke) and 1.07 (95% CI, 0.80-1.42) for fatal stroke. Stratified by age, the HR for stroke events was 3.32 (95% CI, 1.25-8.80) for individuals aged 18-49 years. There was an increased risk of fatal stroke in the age groups 18-49 and 50-64 years, with a HR of 4.22 (95% CI, 1.08-16.55) and 2.86 (95% CI, 1.31-6.26), respectively (p trend 0.04). We found no increased risk for those 65-79 years old (HR, 1.00; 95% CI, 0.86-1.18) or ≥ 80 years old (HR, 1.31; 95% CI, 0.79-2.18). There was a pattern of increased risk of fatal stroke with higher TSH concentrations. CONCLUSIONS: Although no overall effect of subclinical hypothyroidism on stroke could be demonstrated, an increased risk in subjects younger than 65 years and those with higher TSH concentrations was observed.
Keywords: Adult; Asymptomatic Diseases; Female; Humans; Hypothyroidism; Incidence; Male; Risk Factors; Stroke; Thyrotropin

Subclinical thyroid dysfunction and fracture risk: a meta-analysis. - Blum, Manuel R; Bauer, Douglas C; Collet, Tinh-Hai; Fink, Howard A; Cappola, Anne R; da Costa, Bruno R; Wirth, Christina D; Peeters, Robin P; Asvold, Bjørn O; den Elzen, Wendy P J; Luben, Robert N; Imaizumi, Misa; et al. (JAMA, 2015)
IMPORTANCE: Associations between subclinical thyroid dysfunction and fractures are unclear and clinical trials are lacking. OBJECTIVE: To assess the association of subclinical thyroid dysfunction with hip, nonspine, spine, or any fractures. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (inception to March 26, 2015) were searched without language restrictions for prospective cohort studies with thyroid function data and subsequent fractures. DATA EXTRACTION: Individual participant data were obtained from 13 prospective cohorts in the United States, Europe, Australia, and Japan. Levels of thyroid function were defined as euthyroidism (thyroid-stimulating hormone [TSH], 0.45-4.49 mIU/L), subclinical hyperthyroidism (TSH <0.45 mIU/L), and subclinical hypothyroidism (TSH ≥4.50-19.99 mIU/L) with normal thyroxine concentrations. MAIN OUTCOME AND MEASURES: The primary outcome was hip fracture. Any fractures, nonspine fractures, and clinical spine fractures were secondary outcomes. RESULTS: Among 70,298 participants, 4092 (5.8%) had subclinical hypothyroidism and 2219 (3.2%) had subclinical hyperthyroidism. During 762,401 person-years of follow-up, hip fracture occurred in 2975 participants (4.6%; 12 studies), any fracture in 2528 participants (9.0%; 8 studies), nonspine fracture in 2018 participants (8.4%; 8 studies), and spine fracture in 296 participants (1.3%; 6 studies). In age- and sex-adjusted analyses, the hazard ratio (HR) for subclinical hyperthyroidism vs euthyroidism was 1.36 for hip fracture (95% CI, 1.13-1.64; 146 events in 2082 participants vs 2534 in 56,471); for any fracture, HR was 1.28 (95% CI, 1.06-1.53; 121 events in 888 participants vs 2203 in 25,901); for nonspine fracture, HR was 1.16 (95% CI, 0.95-1.41; 107 events in 946 participants vs 1745 in 21,722); and for spine fracture, HR was 1.51 (95% CI, 0.93-2.45; 17 events in 732 participants vs 255 in 20,328). Lower TSH was associated with higher fracture rates: for TSH of less than 0.10 mIU/L, HR was 1.61 for hip fracture (95% CI, 1.21-2.15; 47 events in 510 participants); for any fracture, HR was 1.98 (95% CI, 1.41-2.78; 44 events in 212 participants); for nonspine fracture, HR was 1.61 (95% CI, 0.96-2.71; 32 events in 185 participants); and for spine fracture, HR was 3.57 (95% CI, 1.88-6.78; 8 events in 162 participants). Risks were similar after adjustment for other fracture risk factors. Endogenous subclinical hyperthyroidism (excluding thyroid medication users) was associated with HRs of 1.52 (95% CI, 1.19-1.93) for hip fracture, 1.42 (95% CI, 1.16-1.74) for any fracture, and 1.74 (95% CI, 1.01-2.99) for spine fracture. No association was found between subclinical hypothyroidism and fracture risk. CONCLUSIONS AND RELEVANCE: Subclinical hyperthyroidism was associated with an increased risk of hip and other fractures, particularly among those with TSH levels of less than 0.10 mIU/L and those with endogenous subclinical hyperthyroidism. Further study is needed to determine whether treating subclinical hyperthyroidism can prevent fractures.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Fractures, Bone; Hip Fractures; Humans; Hyperthyroidism; Hypothyroidism; Male; Middle Aged; Risk Factors; Spinal Fractures; Thyrotropin; Young Adult

Urinary uromodulin, kidney function, and cardiovascular disease in elderly adults. - Garimella, Pranav S; Biggs, Mary L; Katz, Ronit; Ix, Joachim H; Bennett, Michael R; Devarajan, Prasad; Kestenbaum, Bryan R; Siscovick, David S; Jensen, Majken K; Shlipak, Michael G; Chaves, Paulo H M; Sarnak, Mark J (Kidney Int, 2015)
Urinary uromodulin (uUMOD) is the most common secreted tubular protein in healthy adults. However, the relationship between uUMOD and clinical outcomes is still unclear. Here we measured uUMOD in 192 participants of the Cardiovascular Health Study with over a 30% decline in estimated glomerular filtration rate (eGFR) over 9 years, 54 with incident end-stage renal disease (ESRD), and in a random subcohort of 958 participants. The association of uUMOD with eGFR decline was evaluated using logistic regression and with incident ESRD, cardiovascular disease, heart failure, and mortality using Cox proportional regression. Mean age was 78 years and median uUMOD was 25.8 μg/ml. In a case-control study evaluating eGFR decline (192 cases and 231 controls), each 1-s.d. higher uUMOD was associated with a 23% lower odds of eGFR decline (odds ratio 0.77 (95% CI 0.62-0.96)) and a 10% lower risk of mortality (hazard ratio 0.90 (95% CI 0.83-0.98)) after adjusting for demographics, eGFR, albumin/creatinine ratio, and other risk factors. There was no risk association of uUMOD with ESRD, cardiovascular disease, or heart failure after multivariable adjustment. Thus, low uUMOD levels may identify persons at risk of progressive kidney disease and mortality above and beyond established markers of kidney disease, namely eGFR and the albumin/creatinine ratio. Future studies need to confirm these results and evaluate whether uUMOD is a marker of tubular health and/or whether it plays a causal role in preserving kidney function.
Keywords: Aged; Aged, 80 and over; Albuminuria; Biomarkers; Cardiovascular Diseases; Case-Control Studies; Creatinine; Disease Progression; Female; Glomerular Filtration Rate; Heart Failure; Humans; Incidence; Kidney Failure, Chronic; Male; Proportional Hazards Models; Uromodulin

White Matter Lesion Progression: Genome-Wide Search for Genetic Influences. - Hofer, Edith; Cavalieri, Margherita; Bis, Joshua C; DeCarli, Charles; Fornage, Myriam; Sigurdsson, Sigurdur; Srikanth, Velandai; Trompet, Stella; Verhaaren, Benjamin F J; Wolf, Christiane; Yang, Qiong; Adams, Hieab H H; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter lesion (WML) progression on magnetic resonance imaging is related to cognitive decline and stroke, but its determinants besides baseline WML burden are largely unknown. Here, we estimated heritability of WML progression, and sought common genetic variants associated with WML progression in elderly participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Heritability of WML progression was calculated in the Framingham Heart Study. The genome-wide association study included 7773 elderly participants from 10 cohorts. To assess the relative contribution of genetic factors to progression of WML, we compared in 7 cohorts risk models including demographics, vascular risk factors plus single-nucleotide polymorphisms that have been shown to be associated cross-sectionally with WML in the current and previous association studies. RESULTS: A total of 1085 subjects showed WML progression. The heritability estimate for WML progression was low at 6.5%, and no single-nucleotide polymorphisms achieved genome-wide significance (P<5×10(-8)). Four loci were suggestive (P<1×10(-5)) of an association with WML progression: 10q24.32 (rs10883817, P=1.46×10(-6)); 12q13.13 (rs4761974, P=8.71×10(-7)); 20p12.1 (rs6135309, P=3.69×10(-6)); and 4p15.31 (rs7664442, P=2.26×10(-6)). Variants that have been previously related to WML explained only 0.8% to 11.7% more of the variance in WML progression than age, vascular risk factors, and baseline WML burden. CONCLUSIONS: Common genetic factors contribute little to the progression of age-related WML in middle-aged and older adults. Future research on determinants of WML progression should focus more on environmental, lifestyle, or host-related biological factors.
Keywords: Adult; Aged; Cohort Studies; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Middle Aged; Prospective Studies; White Matter

-3 Polyunsaturated Fatty Acid Biomarkers and Coronary Heart Disease: Pooling Project of 19 Cohort Studies - Del Gobbo, L. C.; Imamura, F.; Aslibekyan, S.; Marklund, M.; Virtanen, J. K.; Wennberg, M.; Yakoob, M. Y.; Chiuve, S. E.; Dela Cruz, L.; Frazier-Wood, A. C.; Fretts, A. M.; Guallar, E.; et al. (JAMA Intern Med, 2016)
-3 polyunsaturated fatty acids for primary prevention of coronary heart disease (CHD) remains controversial. Most prior longitudinal studies evaluated self-reported consumption rather than biomarkers.\ -3) for incident CHD.\ A global consortium of 19 studies identified by November 2014.\ -3 biomarkers and ascertained CHD.\ -6 levels, and FADS desaturase genes.\ Incident total CHD, fatal CHD, and nonfatal myocardial infarction (MI).\ -3 biomarkers ALA, DPA, and DHA were associated with a lower risk of fatal CHD, with relative risks (RRs) of 0.91 (95% CI, 0.84-0.98) for ALA, 0.90 (95% CI, 0.85-0.96) for DPA, and 0.90 (95% CI, 0.84-0.96) for DHA. Although DPA was associated with a lower risk of total CHD (RR, 0.94; 95% CI, 0.90-0.99), ALA (RR, 1.00; 95% CI, 0.95-1.05), EPA (RR, 0.94; 95% CI, 0.87-1.02), and DHA (RR, 0.95; 95% CI, 0.91-1.00) were not. Significant associations with nonfatal MI were not evident. Associations appeared generally stronger in phospholipids and total plasma. Restricted cubic splines did not identify evidence of nonlinearity in dose responses.\ -3 fatty acids are associated with a modestly lower incidence of fatal CHD.

52 Genetic Loci Influencing Myocardial Mass. - van der Harst, Pim; van Setten, Jessica; Verweij, Niek; Vogler, Georg; Franke, Lude; Maurano, Matthew T; Wang, Xinchen; Mateo Leach, Irene; Eijgelsheim, Mark; Sotoodehnia, Nona; Hayward, Caroline; Sorice, Rossella; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Myocardial mass is a key determinant of cardiac muscle function and hypertrophy. Myocardial depolarization leading to cardiac muscle contraction is reflected by the amplitude and duration of the QRS complex on the electrocardiogram (ECG). Abnormal QRS amplitude or duration reflect changes in myocardial mass and conduction, and are associated with increased risk of heart failure and death. OBJECTIVES: This meta-analysis sought to gain insights into the genetic determinants of myocardial mass. METHODS: We carried out a genome-wide association meta-analysis of 4 QRS traits in up to 73,518 individuals of European ancestry, followed by extensive biological and functional assessment. RESULTS: We identified 52 genomic loci, of which 32 are novel, that are reliably associated with 1 or more QRS phenotypes at p < 1 × 10(-8). These loci are enriched in regions of open chromatin, histone modifications, and transcription factor binding, suggesting that they represent regions of the genome that are actively transcribed in the human heart. Pathway analyses provided evidence that these loci play a role in cardiac hypertrophy. We further highlighted 67 candidate genes at the identified loci that are preferentially expressed in cardiac tissue and associated with cardiac abnormalities in Drosophila melanogaster and Mus musculus. We validated the regulatory function of a novel variant in the SCN5A/SCN10A locus in vitro and in vivo. CONCLUSIONS: Taken together, our findings provide new insights into genes and biological pathways controlling myocardial mass and may help identify novel therapeutic targets.

Association of Smoking, Alcohol, and Obesity with Cardiovascular Death and Ischemic Stroke in Atrial Fibrillation: The Atherosclerosis Risk in Communities (ARIC) Study and Cardiovascular Health Study (CHS). - Kwon, Younghoon; Norby, Faye L; Jensen, Paul N; Agarwal, Sunil K; Soliman, Elsayed Z; Lip, Gregory Y H; Longstreth, W T; Alonso, Alvaro; Heckbert, Susan R; Chen, Lin Y (PLoS One, 2016)
Atrial fibrillation (AF) is associated with an increased risk of ischemic stroke and cardiovascular (CV) death. Whether modifiable lifestyle risk factors are associated with these CV outcomes in AF is unknown. Among Atherosclerosis Risk in Communities (ARIC) study and Cardiovascular Health Study (CHS) participants with incident AF, we estimated the risk of composite endpoint of ischemic stroke or CV death associated with candidate modifiable risk factor (smoking, heavy alcohol consumption, or high body mass index [BMI]), and computed the C-statistic, net reclassification improvement (NRI), and integrated discrimination improvement (IDI) of incorporating each factor into the CHA2DS2-VASc. Among 1222 ARIC (mean age: 63.4) and 756 CHS (mean age: 79.1) participants with incident AF, during mean follow-up of 6.9 years and 5.7 years, there were 332 and 335 composite events respectively. Compared with never smokers, current smokers had a higher incidence of the composite endpoint in ARIC [HR: 1.65 (1.21-2.26)] but not in CHS [HR: 1.05 (0.69-1.61)]. In ARIC, the addition of current smoking did not improve risk prediction over and above the CHA2DS2-VASc. No significant associations were observed with alcohol consumption or BMI with CVD outcomes in AF patients from either cohort. Smoking is associated with an increased risk of ischemic stroke or CV death in ARIC, which comprised mostly middle-aged to young-old (65-74 years), but not in CHS, which comprised mostly middle-old or oldest-old (≥75 years) adults with AF. However, addition of smoking to the CHA2DS2-VASc score did not improve risk prediction of these outcomes.
Keywords: Aged; Alcohol Drinking; Atrial Fibrillation; Cardiovascular Diseases; Female; Humans; Male; Middle Aged; Obesity; Smoking; Stroke

Associations of insulin resistance, inflammation and liver synthetic function with very low-density lipoprotein: The Cardiovascular Health Study. - Jiang, Z Gordon; de Boer, Ian H; Mackey, Rachel H; Jensen, Majken K; Lai, Michelle; Robson, Simon C; Tracy, Russell; Kuller, Lewis H; Mukamal, Kenneth J (Metabolism, 2016)
INTRODUCTION: Production of very low-density lipoprotein (VLDL) is increased in states of metabolic syndrome, leading to hypertriglyceridemia. However, metabolic syndrome is often associated with non-alcoholic fatty liver disease, which leads to liver fibrosis and inflammation that may decrease VLDL production. In this study, we aim to determine the interactive impact on VLDL profiles from insulin resistance, impairment in liver synthetic function and inflammation. METHODS: We examined cross-sectional associations of insulin sensitivity, inflammation, and liver synthetic function with VLDL particle (VLDL-P) concentration and size among 1,850 older adults in the Cardiovascular Health Study. RESULTS: Indices for high insulin sensitivity and low liver synthetic function were associated with lower concentrations of VLDL-P. In addition, insulin resistance preferentially increased concentration of large VLDL and was associated with mean VLDL size. Indices for inflammation however demonstrated a nonlinear relationship with both VLDL-P concentration and VLDL size. When mutually adjusted, one standard deviation (SD) increment in Matsuda index and C-reactive protein (CRP) were associated with 4.9 nmol/L (-8.2 to -1.5, p=0.005) and 6.3 nmol/L (-11.0 to -1.6, p=0.009) lower VLDL-P concentration respectively. In contrast, one-SD increment in factor VII, a marker for liver synthetic function, was associated with 16.9 nmol/L (12.6-21.2, p<0.001) higher VLDL-P concentration. Furthermore, a one-SD increment in the Matsuda index was associated with 1.1 nm (-2.0 to -0.3, p=0.006) smaller mean VLDL size, whereas CRP and factor VII were not associated with VLDL size. CONCLUSION: Insulin sensitivity, inflammation and markers for liver synthetic function differentially impact VLDL-P concentration and VLDL size. These results underscore the complex effects of insulin resistance and its complications on VLDL production.
Keywords: Aged; Aged, 80 and over; C-Reactive Protein; Cross-Sectional Studies; Factor VII; Female; Humans; Inflammation; Insulin Resistance; Lipoproteins, VLDL; Liver; Liver Function Tests; Male; Risk Factors; Socioeconomic Factors

Can a Healthy Lifestyle Compress the Disabled Period in Older Adults? - Jacob, Mini E; Yee, Laura M; Diehr, Paula H; Arnold, Alice M; Thielke, Stephen M; Chaves, Paulo H M; Gobbo, Liana Del; Hirsch, Calvin; Siscovick, David; Newman, Anne B (J Am Geriatr Soc, 2016)
OBJECTIVES: To determine whether lifestyle factors, measured late in life, could compress the disabled period toward the end of life. DESIGN: Community-based cohort study of older adults followed from 1989 to 2015. SETTING: Four U.S. communities. PARTICIPANTS: Community-living men and women aged 65 and older (N = 5,248, mean age 72.7 ± 5.5, 57% female, 15.2% minority) who were not wheelchair dependent and were able to give informed consent at baseline. MEASUREMENTS: Multiple lifestyle factors, including smoking, alcohol consumption, physical activity, diet, body mass index (BMI), social networks, and social support, were measured at baseline. Activities of daily living (ADLs) were assessed at baseline and throughout follow-up. Years of life (YoL) was defined as years until death. Years of able life (YAL) was defined as years without any ADL difficulty. YAL/YoL%, the proportion of life lived able, was used to indicate the relative compression or expansion of the disabled period. RESULTS: The average duration of disabled years was 4.5 (out of 15.4 mean YoL) for women and 2.9 (out of 12.4 mean YoL) for men. In a multivariable model, obesity was associated with 7.3 percentage points (95% confidence interval (CI) = 5.4-9.2) lower YAL/YoL% than normal weight. Scores in the lowest quintile of the Alternate Healthy Eating Index were associated with a 3.7% (95% CI = 1.6-5.9) lower YAL/YoL% than scores in the highest quintile. Every 25 blocks walked in a week was associated with 0.5 percentage points (95% CI = 0.3-0.8) higher YAL/YoL%. CONCLUSION: The effects of healthy lifestyle factors on the proportion of future life lived free of disability indicate that the disabled period can be compressed, given the right combination of these factors.

Common variants in DRD2 are associated with sleep duration: the CARe consortium. - Cade, Brian E; Gottlieb, Daniel J; Lauderdale, Diane S; Bennett, David A; Buchman, Aron S; Buxbaum, Sarah G; De Jager, Philip L; Evans, Daniel S; Fulop, Tibor; Gharib, Sina A; Johnson, W Craig; Kim, Hyun; et al. (Hum Mol Genet, 2016)
Sleep duration is implicated in the etiologies of chronic diseases and premature mortality. However, the genetic basis for sleep duration is poorly defined. We sought to identify novel genetic components influencing sleep duration in a multi-ethnic sample. Meta-analyses were conducted of genetic associations with self-reported, habitual sleep duration from seven Candidate Gene Association Resource (CARe) cohorts of over 25 000 individuals of African, Asian, European and Hispanic American ancestry. All individuals were genotyped for ∼50 000 SNPs from 2000 candidate heart, lung, blood and sleep genes. African-Americans had additional genome-wide genotypes. Four cohorts provided replication. A SNP (rs17601612) in the dopamine D2 receptor gene (DRD2) was significantly associated with sleep duration (P = 9.8 × 10(-7)). Conditional analysis identified a second DRD2 signal with opposite effects on sleep duration. In exploratory analysis, suggestive association was observed for rs17601612 with polysomnographically determined sleep latency (P = 0.002). The lead DRD2 signal was recently identified in a schizophrenia GWAS, and a genetic risk score of 11 additional schizophrenia GWAS loci genotyped on the IBC array was also associated with longer sleep duration (P = 0.03). These findings support a role for DRD2 in influencing sleep duration. Our work motivates future pharmocogenetics research on alerting agents such as caffeine and modafinil that interact with the dopaminergic pathway and further investigation of genetic overlap between sleep and neuro-psychiatric traits.
Keywords: Cohort Studies; Ethnic Groups; Humans; Polymorphism, Single Nucleotide; Polysomnography; Receptors, Dopamine D2; Sleep; Time Factors

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.

A DNA methylation biomarker of alcohol consumption. - Liu, C; Marioni, R E; Hedman, Å K; Pfeiffer, L; Tsai, P-C; Reynolds, L M; Just, A C; Duan, Q; Boer, C G; Tanaka, T; Elks, C E; Aslibekyan, S; et al. (Mol Psychiatry, 2016)
The lack of reliable measures of alcohol intake is a major obstacle to the diagnosis and treatment of alcohol-related diseases. Epigenetic modifications such as DNA methylation may provide novel biomarkers of alcohol use. To examine this possibility, we performed an epigenome-wide association study of methylation of cytosine-phosphate-guanine dinucleotide (CpG) sites in relation to alcohol intake in 13 population-based cohorts (ntotal=13 317; 54% women; mean age across cohorts 42-76 years) using whole blood (9643 European and 2423 African ancestries) or monocyte-derived DNA (588 European, 263 African and 400 Hispanic ancestry) samples. We performed meta-analysis and variable selection in whole-blood samples of people of European ancestry (n=6926) and identified 144 CpGs that provided substantial discrimination (area under the curve=0.90-0.99) for current heavy alcohol intake (⩾42 g per day in men and ⩾28 g per day in women) in four replication cohorts. The ancestry-stratified meta-analysis in whole blood identified 328 (9643 European ancestry samples) and 165 (2423 African ancestry samples) alcohol-related CpGs at Bonferroni-adjusted P<1 × 10(-7). Analysis of the monocyte-derived DNA (n=1251) identified 62 alcohol-related CpGs at P<1 × 10(-7). In whole-blood samples of people of European ancestry, we detected differential methylation in two neurotransmitter receptor genes, the γ-Aminobutyric acid-A receptor delta and γ-aminobutyric acid B receptor subunit 1; their differential methylation was associated with expression levels of a number of genes involved in immune function. In conclusion, we have identified a robust alcohol-related DNA methylation signature and shown the potential utility of DNA methylation as a clinically useful diagnostic test to detect current heavy alcohol consumption.Molecular Psychiatry advance online publication, 15 November 2016; doi:10.1038/mp.2016.192.

DNA methylation signatures of chronic low-grade inflammation are associated with complex diseases. - Ligthart, Symen; Marzi, Carola; Aslibekyan, Stella; Mendelson, Michael M; Conneely, Karen N; Tanaka, Toshiko; Colicino, Elena; Waite, Lindsay L; Joehanes, Roby; Guan, Weihua; Brody, Jennifer A; Elks, Cathy; et al. (Genome Biol, 2016)
BACKGROUND: Chronic low-grade inflammation reflects a subclinical immune response implicated in the pathogenesis of complex diseases. Identifying genetic loci where DNA methylation is associated with chronic low-grade inflammation may reveal novel pathways or therapeutic targets for inflammation. RESULTS: We performed a meta-analysis of epigenome-wide association studies (EWAS) of serum C-reactive protein (CRP), which is a sensitive marker of low-grade inflammation, in a large European population (n = 8863) and trans-ethnic replication in African Americans (n = 4111). We found differential methylation at 218 CpG sites to be associated with CRP (P < 1.15 × 10(-7)) in the discovery panel of European ancestry and replicated (P < 2.29 × 10(-4)) 58 CpG sites (45 unique loci) among African Americans. To further characterize the molecular and clinical relevance of the findings, we examined the association with gene expression, genetic sequence variants, and clinical outcomes. DNA methylation at nine (16%) CpG sites was associated with whole blood gene expression in cis (P < 8.47 × 10(-5)), ten (17%) CpG sites were associated with a nearby genetic variant (P < 2.50 × 10(-3)), and 51 (88%) were also associated with at least one related cardiometabolic entity (P < 9.58 × 10(-5)). An additive weighted score of replicated CpG sites accounted for up to 6% inter-individual variation (R2) of age-adjusted and sex-adjusted CRP, independent of known CRP-related genetic variants. CONCLUSION: We have completed an EWAS of chronic low-grade inflammation and identified many novel genetic loci underlying inflammation that may serve as targets for the development of novel therapeutic interventions for inflammation.

Epigenetic Signatures of Cigarette Smoking. - Joehanes, Roby; Just, Allan C; Marioni, Riccardo E; Pilling, Luke C; Reynolds, Lindsay M; Mandaviya, Pooja R; Guan, Weihua; Xu, Tao; Elks, Cathy E; Aslibekyan, Stella; Moreno-Macias, Hortensia; Smith, Jennifer A; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: DNA methylation leaves a long-term signature of smoking exposure and is one potential mechanism by which tobacco exposure predisposes to adverse health outcomes, such as cancers, osteoporosis, lung, and cardiovascular disorders. METHODS AND RESULTS: To comprehensively determine the association between cigarette smoking and DNA methylation, we conducted a meta-analysis of genome-wide DNA methylation assessed using the Illumina BeadChip 450K array on 15 907 blood-derived DNA samples from participants in 16 cohorts (including 2433 current, 6518 former, and 6956 never smokers). Comparing current versus never smokers, 2623 cytosine-phosphate-guanine sites (CpGs), annotated to 1405 genes, were statistically significantly differentially methylated at Bonferroni threshold of P<1×10(-7) (18 760 CpGs at false discovery rate <0.05). Genes annotated to these CpGs were enriched for associations with several smoking-related traits in genome-wide studies including pulmonary function, cancers, inflammatory diseases, and heart disease. Comparing former versus never smokers, 185 of the CpGs that differed between current and never smokers were significant P<1×10(-7) (2623 CpGs at false discovery rate <0.05), indicating a pattern of persistent altered methylation, with attenuation, after smoking cessation. Transcriptomic integration identified effects on gene expression at many differentially methylated CpGs. CONCLUSIONS: Cigarette smoking has a broad impact on genome-wide methylation that, at many loci, persists many years after smoking cessation. Many of the differentially methylated genes were novel genes with respect to biological effects of smoking and might represent therapeutic targets for prevention or treatment of tobacco-related diseases. Methylation at these sites could also serve as sensitive and stable biomarkers of lifetime exposure to tobacco smoke.

Evaluation of a Genetic Risk Score to Improve Risk Prediction for Alzheimer's Disease. - Chouraki, Vincent; Reitz, Christiane; Maury, Fleur; Bis, Joshua C; Bellenguez, Céline; Yu, Lei; Jakobsdottir, Johanna; Mukherjee, Shubhabrata; Adams, Hieab H; Choi, Seung Hoan; Larson, Eric B; Fitzpatrick, Annette; et al. (J Alzheimers Dis, 2016)
Effective prevention of Alzheimer's disease (AD) requires the development of risk prediction tools permitting preclinical intervention. We constructed a genetic risk score (GRS) comprising common genetic variants associated with AD, evaluated its association with incident AD and assessed its capacity to improve risk prediction over traditional models based on age, sex, education, and APOEɛ4. In eight prospective cohorts included in the International Genomics of Alzheimer's Project (IGAP), we derived weighted sum of risk alleles from the 19 top SNPs reported by the IGAP GWAS in participants aged 65 and older without prevalent dementia. Hazard ratios (HR) of incident AD were estimated in Cox models. Improvement in risk prediction was measured by the difference in C-index (Δ-C), the integrated discrimination improvement (IDI) and continuous net reclassification improvement (NRI>0). Overall, 19,687 participants at risk were included, of whom 2,782 developed AD. The GRS was associated with a 17% increase in AD risk (pooled HR = 1.17; 95% CI =   [1.13-1.21] per standard deviation increase in GRS; p-value =  2.86×10-16). This association was stronger among persons with at least one APOEɛ4 allele (HRGRS = 1.24; 95% CI =   [1.15-1.34]) than in others (HRGRS = 1.13; 95% CI =   [1.08-1.18]; pinteraction = 3.45×10-2). Risk prediction after seven years of follow-up showed a small improvement when adding the GRS to age, sex, APOEɛ4, and education (Δ-Cindex =  0.0043 [0.0019-0.0067]). Similar patterns were observed for IDI and NRI>0. In conclusion, a risk score incorporating common genetic variation outside the APOEɛ4 locus improved AD risk prediction and may facilitate risk stratification for prevention trials.

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.

Fine-mapping, novel loci identification, and SNP association transferability in a genome-wide association study of QRS duration in African Americans. - Evans, Daniel S; Avery, Christy L; Nalls, Mike A; Li, Guo; Barnard, John; Smith, Erin N; Tanaka, Toshiko; Butler, Anne M; Buxbaum, Sarah G; Alonso, Alvaro; Arking, Dan E; Berenson, Gerald S; et al. (Hum Mol Genet, 2016)
The electrocardiographic QRS duration, a measure of ventricular depolarization and conduction, is associated with cardiovascular mortality. While single nucleotide polymorphisms (SNPs) associated with QRS duration have been identified at 22 loci in populations of European descent, the genetic architecture of QRS duration in non-European populations is largely unknown. We therefore performed a genome-wide association study (GWAS) meta-analysis of QRS duration in 13,031 African Americans from ten cohorts and a transethnic GWAS meta-analysis with additional results from populations of European descent. In the African American GWAS, a single genome-wide significant SNP association was identified (rs3922844, P = 4 × 10(-14)) in intron 16 of SCN5A, a voltage-gated cardiac sodium channel gene. The QRS-prolonging rs3922844 C allele was also associated with decreased SCN5A RNA expression in human atrial tissue (P = 1.1 × 10(-4)). High density genotyping revealed that the SCN5A association region in African Americans was confined to intron 16. Transethnic GWAS meta-analysis identified novel SNP associations on chromosome 18 in MYL12A (rs1662342, P = 4.9 × 10(-8)) and chromosome 1 near CD1E and SPTA1 (rs7547997, P = 7.9 × 10(-9)). The 22 QRS loci previously identified in populations of European descent were enriched for significant SNP associations with QRS duration in African Americans (P = 9.9 × 10(-7)), and index SNP associations in or near SCN5A, SCN10A, CDKN1A, NFIA, HAND1, TBX5 and SETBP1 replicated in African Americans. In summary, rs3922844 was associated with QRS duration and SCN5A expression, two novel QRS loci were identified using transethnic meta-analysis, and a significant proportion of QRS-SNP associations discovered in populations of European descent were transferable to African Americans when adequate power was achieved.

{Gene-gene Interaction Analyses for Atrial Fibrillation - Lin, H.; Mueller-Nurasyid, M.; Smith, A. V.; Arking, D. E.; Barnard, J.; Bartz, T. M.; Lunetta, K. L.; Lohman, K.; Kleber, M. E.; Lubitz, S. A.; Geelhoed, B.; Trompet, S.; et al. (Sci Rep, 2016)
{Atrial fibrillation (AF) is a heritable disease that affects more than thirty million individuals worldwide. Extensive efforts have been devoted to the study of genetic determinants of AF. The objective of our study is to examine the effect of gene-gene interaction on AF susceptibility. We performed a large-scale association analysis of gene-gene interactions with AF in 8,173 AF cases, and 65,237 AF-free referents collected from 15 studies for discovery. We examined putative interactions between genome-wide SNPs and 17 known AF-related SNPs. The top interactions were then tested for association in an independent cohort for replication, which included more than 2,363 AF cases and 114,746 AF-free referents. One interaction, between rs7164883 at the HCN4 locus and rs4980345 at the SLC28A1 locus, was found to be significantly associated with AF in the discovery cohorts (interaction OR = 1.44, 95% CI: 1.27-1.65

General Framework for Meta-Analysis of Haplotype Association Tests. - Wang, Shuai; Zhao, Jing Hua; An, Ping; Guo, Xiuqing; Jensen, Richard A; Marten, Jonathan; Huffman, Jennifer E; Meidtner, Karina; Boeing, Heiner; Campbell, Archie; Rice, Kenneth M; Scott, Robert A; et al. (Genet Epidemiol, 2016)
For complex traits, most associated single nucleotide variants (SNV) discovered to date have a small effect, and detection of association is only possible with large sample sizes. Because of patient confidentiality concerns, it is often not possible to pool genetic data from multiple cohorts, and meta-analysis has emerged as the method of choice to combine results from multiple studies. Many meta-analysis methods are available for single SNV analyses. As new approaches allow the capture of low frequency and rare genetic variation, it is of interest to jointly consider multiple variants to improve power. However, for the analysis of haplotypes formed by multiple SNVs, meta-analysis remains a challenge, because different haplotypes may be observed across studies. We propose a two-stage meta-analysis approach to combine haplotype analysis results. In the first stage, each cohort estimate haplotype effect sizes in a regression framework, accounting for relatedness among observations if appropriate. For the second stage, we use a multivariate generalized least square meta-analysis approach to combine haplotype effect estimates from multiple cohorts. Haplotype-specific association tests and a global test of independence between haplotypes and traits are obtained within our framework. We demonstrate through simulation studies that we control the type-I error rate, and our approach is more powerful than inverse variance weighted meta-analysis of single SNV analysis when haplotype effects are present. We replicate a published haplotype association between fasting glucose-associated locus (G6PC2) and fasting glucose in seven studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and we provide more precise haplotype effect estimates.

{Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function - Pattaro, C.; Teumer, A.; Gorski, M.; Chu, A. Y.; Li, M.; Mijatovic, V.; Garnaas, M.; Tin, A.; Sorice, R.; Li, Y.; Taliun, D.; Olden, M.; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.

{The genetics of blood pressure regulation and its target organs from association studies in 342,415 individuals - Ehret, G. B.; Ferreira, T.; Chasman, D. I.; Jackson, A. U.; Schmidt, E. M.; Johnson, T.; Thorleifsson, G.; Luan, J.; Donnelly, L. A.; Kanoni, S.; Petersen, A. K.; Pihur, V.; et al. (Nat Genet, 2016)
To dissect the genetic architecture of blood pressure and assess effects on target organ damage, we analyzed 128,272 SNPs from targeted and genome-wide arrays in 201,529 individuals of European ancestry, and genotypes from an additional 140,886 individuals were used for validation. We identified 66 blood pressure-associated loci, of which 17 were new; 15 harbored multiple distinct association signals. The 66 index SNPs were enriched for cis-regulatory elements, particularly in vascular endothelial cells, consistent with a primary role in blood pressure control through modulation of vascular tone across multiple tissues. The 66 index SNPs combined in a risk score showed comparable effects in 64,421 individuals of non-European descent. The 66-SNP blood pressure risk score was significantly associated with target organ damage in multiple tissues but with minor effects in the kidney. Our findings expand current knowledge of blood pressure-related pathways and highlight tissues beyond the classical renal system in blood pressure regulation.

Genome-Wide Association Analysis of Young-Onset Stroke Identifies a Locus on Chromosome 10q25 Near HABP2. - Cheng, Yu-Ching; Stanne, Tara M; Giese, Anne-Katrin; Ho, Weang Kee; Traylor, Matthew; Amouyel, Philippe; Holliday, Elizabeth G; Malik, Rainer; Xu, Huichun; Kittner, Steven J; Cole, John W; O'Connell, Jeffrey R; et al. (Stroke, 2016)
BACKGROUND AND PURPOSE: Although a genetic contribution to ischemic stroke is well recognized, only a handful of stroke loci have been identified by large-scale genetic association studies to date. Hypothesizing that genetic effects might be stronger for early- versus late-onset stroke, we conducted a 2-stage meta-analysis of genome-wide association studies, focusing on stroke cases with an age of onset <60 years. METHODS: The discovery stage of our genome-wide association studies included 4505 cases and 21 968 controls of European, South-Asian, and African ancestry, drawn from 6 studies. In Stage 2, we selected the lead genetic variants at loci with association P<5×10(-6) and performed in silico association analyses in an independent sample of ≤1003 cases and 7745 controls. RESULTS: One stroke susceptibility locus at 10q25 reached genome-wide significance in the combined analysis of all samples from the discovery and follow-up stages (rs11196288; odds ratio =1.41; P=9.5×10(-9)). The associated locus is in an intergenic region between TCF7L2 and HABP2. In a further analysis in an independent sample, we found that 2 single nucleotide polymorphisms in high linkage disequilibrium with rs11196288 were significantly associated with total plasma factor VII-activating protease levels, a product of HABP2. CONCLUSIONS: HABP2, which encodes an extracellular serine protease involved in coagulation, fibrinolysis, and inflammatory pathways, may be a genetic susceptibility locus for early-onset stroke.
Keywords: Adult; African Continental Ancestry Group; Age of Onset; Aged; Asian Continental Ancestry Group; Brain Ischemia; Chromosomes, Human, Pair 10; Computer Simulation; DNA, Intergenic; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Serine Endopeptidases; Stroke

Genome-Wide Association Study for Incident Myocardial Infarction and Coronary Heart Disease in Prospective Cohort Studies: The CHARGE Consortium. - Dehghan, Abbas; Bis, Joshua C; White, Charles C; Smith, Albert Vernon; Morrison, Alanna C; Cupples, L Adrienne; Trompet, Stella; Chasman, Daniel I; Lumley, Thomas; Völker, Uwe; Buckley, Brendan M; Ding, Jingzhong; et al. (PLoS One, 2016)
BACKGROUND: Data are limited on genome-wide association studies (GWAS) for incident coronary heart disease (CHD). Moreover, it is not known whether genetic variants identified to date also associate with risk of CHD in a prospective setting. METHODS: We performed a two-stage GWAS analysis of incident myocardial infarction (MI) and CHD in a total of 64,297 individuals (including 3898 MI cases, 5465 CHD cases). SNPs that passed an arbitrary threshold of 5×10-6 in Stage I were taken to Stage II for further discovery. Furthermore, in an analysis of prognosis, we studied whether known SNPs from former GWAS were associated with total mortality in individuals who experienced MI during follow-up. RESULTS: In Stage I 15 loci passed the threshold of 5×10-6; 8 loci for MI and 8 loci for CHD, for which one locus overlapped and none were reported in previous GWAS meta-analyses. We took 60 SNPs representing these 15 loci to Stage II of discovery. Four SNPs near QKI showed nominally significant association with MI (p-value<8.8×10-3) and three exceeded the genome-wide significance threshold when Stage I and Stage II results were combined (top SNP rs6941513: p = 6.2×10-9). Despite excellent power, the 9p21 locus SNP (rs1333049) was only modestly associated with MI (HR = 1.09, p-value = 0.02) and marginally with CHD (HR = 1.06, p-value = 0.08). Among an inception cohort of those who experienced MI during follow-up, the risk allele of rs1333049 was associated with a decreased risk of subsequent mortality (HR = 0.90, p-value = 3.2×10-3). CONCLUSIONS: QKI represents a novel locus that may serve as a predictor of incident CHD in prospective studies. The association of the 9p21 locus both with increased risk of first myocardial infarction and longer survival after MI highlights the importance of study design in investigating genetic determinants of complex disorders.
Keywords: Aged; Cohort Studies; Cooperative Behavior; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

A genome-wide association study meta-analysis of clinical fracture in 10,012 African American women. - Taylor, Kira C; Evans, Daniel S; Edwards, Digna R Velez; Edwards, Todd L; Sofer, Tamar; Li, Guo; Liu, Youfang; Franceschini, Nora; Jackson, Rebecca D; Giri, Ayush; Donneyong, Macarius; Psaty, Bruce; et al. (Bone Rep, 2016)
BACKGROUND: Osteoporosis is a major public health problem associated with excess disability and mortality. It is estimated that 50-70% of the variation in osteoporotic fracture risk is attributable to genetic factors. The purpose of this hypothesis-generating study was to identify possible genetic determinants of fracture among African American (AA) women in a GWAS meta-analysis. METHODS: Data on clinical fractures (all fractures except fingers, toes, face, skull or sternum) were analyzed among AA female participants in the Women's Health Initiative (WHI) (N = 8155), Cardiovascular Health Study (CHS) (N = 504), BioVU (N = 704), Health ABC (N = 651), and the Johnston County Osteoarthritis Project (JoCoOA) (N = 291). Affymetrix (WHI) and Illumina (Health ABC, JoCoOA, BioVU, CHS) GWAS panels were used for genotyping, and a 1:1 ratio of YRI:CEU HapMap haplotypes was used as an imputation reference panel. We used Cox proportional hazard models or logistic regression to evaluate the association of ~ 2.5 million SNPs with fracture risk, adjusting for ancestry, age, and geographic region where applicable. We conducted a fixed-effects, inverse variance-weighted meta-analysis. Genome-wide significance was set at P < 5 × 10- 8. RESULTS: One SNP, rs12775980 in an intron of SVIL on chromosome 10p11.2, reached genome-wide significance (P = 4.0 × 10- 8). Although this SNP has a low minor allele frequency (0.03), there was no evidence for heterogeneity of effects across the studies (I2 = 0). This locus was not reported in any previous osteoporosis-related GWA studies. We also interrogated previously reported GWA-significant loci associated with fracture or bone mineral density in our data. One locus (SMOC1) generalized, but overall there was not substantial evidence of generalization. Possible reasons for the lack of generalization are discussed. CONCLUSION: This GWAS meta-analysis of fractures in African American women identified a potentially novel locus in the supervillin gene, which encodes a platelet-associated factor and was previously associated with platelet thrombus formation in African Americans. If validated in other populations of African descent, these findings suggest potential new mechanisms involved in fracture that may be particularly important among African Americans.

Genome-Wide Association Study of the Modified Stumvoll Insulin Sensitivity Index Identifies BCL2 and FAM19A2 as Novel Insulin Sensitivity Loci. - Walford, Geoffrey A; Gustafsson, Stefan; Rybin, Denis; Stančáková, Alena; Chen, Han; Liu, Ching-Ti; Hong, Jaeyoung; Jensen, Richard A; Rice, Ken; Morris, Andrew P; Mägi, Reedik; Tönjes, Anke; et al. (Diabetes, 2016)
Genome-wide association studies (GWAS) have found few common variants that influence fasting measures of insulin sensitivity. We hypothesized that a GWAS of an integrated assessment of fasting and dynamic measures of insulin sensitivity would detect novel common variants. We performed a GWAS of the modified Stumvoll Insulin Sensitivity Index (ISI) within the Meta-Analyses of Glucose and Insulin-Related Traits Consortium. Discovery for genetic association was performed in 16,753 individuals, and replication was attempted for the 23 most significant novel loci in 13,354 independent individuals. Association with ISI was tested in models adjusted for age, sex, and BMI and in a model analyzing the combined influence of the genotype effect adjusted for BMI and the interaction effect between the genotype and BMI on ISI (model 3). In model 3, three variants reached genome-wide significance: rs13422522 (NYAP2; P = 8.87 × 10(-11)), rs12454712 (BCL2; P = 2.7 × 10(-8)), and rs10506418 (FAM19A2; P = 1.9 × 10(-8)). The association at NYAP2 was eliminated by conditioning on the known IRS1 insulin sensitivity locus; the BCL2 and FAM19A2 associations were independent of known cardiometabolic loci. In conclusion, we identified two novel loci and replicated known variants associated with insulin sensitivity. Further studies are needed to clarify the causal variant and function at the BCL2 and FAM19A2 loci.

Genomewide meta-analysis identifies loci associated with IGF-I and IGFBP-3 levels with impact on age-related traits. - Teumer, Alexander; Qi, Qibin; Nethander, Maria; Aschard, Hugues; Bandinelli, Stefania; Beekman, Marian; Berndt, Sonja I; Bidlingmaier, Martin; Broer, Linda; Cappola, Anne; Ceda, Gian Paolo; Chanock, Stephen; et al. (Aging Cell, 2016)
The growth hormone/insulin-like growth factor (IGF) axis can be manipulated in animal models to promote longevity, and IGF-related proteins including IGF-I and IGF-binding protein-3 (IGFBP-3) have also been implicated in risk of human diseases including cardiovascular diseases, diabetes, and cancer. Through genomewide association study of up to 30 884 adults of European ancestry from 21 studies, we confirmed and extended the list of previously identified loci associated with circulating IGF-I and IGFBP-3 concentrations (IGF1, IGFBP3, GCKR, TNS3, GHSR, FOXO3, ASXL2, NUBP2/IGFALS, SORCS2, and CELSR2). Significant sex interactions, which were characterized by different genotype-phenotype associations between men and women, were found only for associations of IGFBP-3 concentrations with SNPs at the loci IGFBP3 and SORCS2. Analyses of SNPs, gene expression, and protein levels suggested that interplay between IGFBP3 and genes within the NUBP2 locus (IGFALS and HAGH) may affect circulating IGF-I and IGFBP-3 concentrations. The IGF-I-decreasing allele of SNP rs934073, which is an eQTL of ASXL2, was associated with lower adiposity and higher likelihood of survival beyond 90 years. The known longevity-associated variant rs2153960 (FOXO3) was observed to be a genomewide significant SNP for IGF-I concentrations. Bioinformatics analysis suggested enrichment of putative regulatory elements among these IGF-I- and IGFBP-3-associated loci, particularly of rs646776 at CELSR2. In conclusion, this study identified several loci associated with circulating IGF-I and IGFBP-3 concentrations and provides clues to the potential role of the IGF axis in mediating effects of known (FOXO3) and novel (ASXL2) longevity-associated loci.

Global Electric Heterogeneity Risk Score for Prediction of Sudden Cardiac Death in the General Population: The Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health (CHS) Studies. - Waks, Jonathan W; Sitlani, Colleen M; Soliman, Elsayed Z; Kabir, Muammar; Ghafoori, Elyar; Biggs, Mary L; Henrikson, Charles A; Sotoodehnia, Nona; Biering-Sørensen, Tor; Agarwal, Sunil K; Siscovick, David S; Post, Wendy S; et al. (Circulation, 2016)
BACKGROUND: Asymptomatic individuals account for the majority of sudden cardiac deaths (SCDs). Development of effective, low-cost, and noninvasive SCD risk stratification tools is necessary. METHODS AND RESULTS: Participants from the Atherosclerosis Risk in Communities study and Cardiovascular Health Study (n=20 177; age, 59.3±10.1 years; age range, 44-100 years; 56% female; 77% white) were followed up for 14.0 years (median). Five ECG markers of global electric heterogeneity (GEH; sum absolute QRST integral, spatial QRST angle, spatial ventricular gradient [SVG] magnitude, SVG elevation, and SVG azimuth) were measured on standard 12-lead ECGs. Cox proportional hazards and competing risks models evaluated associations between GEH electrocardiographic parameters and SCD. An SCD competing risks score was derived from demographics, comorbidities, and GEH parameters. SCD incidence was 1.86 per 1000 person-years. After multivariable adjustment, baseline GEH parameters and large increases in GEH parameters over time were independently associated with SCD. Final SCD risk scores included age, sex, race, diabetes mellitus, hypertension, coronary heart disease, stroke, and GEH parameters as continuous variables. When GEH parameters were added to clinical/demographic factors, the C statistic increased from 0.777 to 0.790 (P=0.008), the risk score classified 10-year SCD risk as high (>5%) in 7.2% of participants, 10% of SCD victims were appropriately reclassified into a high-risk category, and only 1.4% of SCD victims were inappropriately reclassified from high to intermediate risk. The net reclassification index was 18.3%. CONCLUSIONS: Abnormal electrophysiological substrate quantified by GEH parameters is independently associated with SCD in the general population. The addition of GEH parameters to clinical characteristics improves SCD risk prediction.

GWAS analysis of handgrip and lower body strength in older adults in the CHARGE consortium. - Matteini, Amy M; Tanaka, Toshiko; Karasik, David; Atzmon, Gil; Chou, Wen-Chi; Eicher, John D; Johnson, Andrew D; Arnold, Alice M; Callisaya, Michele L; Davies, Gail; Evans, Daniel S; Holtfreter, Birte; et al. (Aging Cell, 2016)
Decline in muscle strength with aging is an important predictor of health trajectory in the elderly. Several factors, including genetics, are proposed contributors to variability in muscle strength. To identify genetic contributors to muscle strength, a meta-analysis of genomewide association studies of handgrip was conducted. Grip strength was measured using a handheld dynamometer in 27 581 individuals of European descent over 65 years of age from 14 cohort studies. Genomewide association analysis was conducted on ~2.7 million imputed and genotyped variants (SNPs). Replication of the most significant findings was conducted using data from 6393 individuals from three cohorts. GWAS of lower body strength was also characterized in a subset of cohorts. Two genomewide significant (P-value< 5 × 10(-8) ) and 39 suggestive (P-value< 5 × 10(-5) ) associations were observed from meta-analysis of the discovery cohorts. After meta-analysis with replication cohorts, genomewide significant association was observed for rs752045 on chromosome 8 (β = 0.47, SE = 0.08, P-value = 5.20 × 10(-10) ). This SNP is mapped to an intergenic region and is located within an accessible chromatin region (DNase hypersensitivity site) in skeletal muscle myotubes differentiated from the human skeletal muscle myoblasts cell line. This locus alters a binding motif of the CCAAT/enhancer-binding protein-β (CEBPB) that is implicated in muscle repair mechanisms. GWAS of lower body strength did not yield significant results. A common genetic variant in a chromosomal region that regulates myotube differentiation and muscle repair may contribute to variability in grip strength in the elderly. Further studies are needed to uncover the mechanisms that link this genetic variant with muscle strength.

GWAS for executive function and processing speed suggests involvement of the CADM2 gene. - Ibrahim-Verbaas, C A; Bressler, J; Debette, S; Schuur, M; Smith, A V; Bis, J C; Davies, G; Trompet, S; Smith, J A; Wolf, C; Chibnik, L B; Liu, Y; et al. (Mol Psychiatry, 2016)
To identify common variants contributing to normal variation in two specific domains of cognitive functioning, we conducted a genome-wide association study (GWAS) of executive functioning and information processing speed in non-demented older adults from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium. Neuropsychological testing was available for 5429-32,070 subjects of European ancestry aged 45 years or older, free of dementia and clinical stroke at the time of cognitive testing from 20 cohorts in the discovery phase. We analyzed performance on the Trail Making Test parts A and B, the Letter Digit Substitution Test (LDST), the Digit Symbol Substitution Task (DSST), semantic and phonemic fluency tests, and the Stroop Color and Word Test. Replication was sought in 1311-21860 subjects from 20 independent cohorts. A significant association was observed in the discovery cohorts for the single-nucleotide polymorphism (SNP) rs17518584 (discovery P-value=3.12 × 10(-8)) and in the joint discovery and replication meta-analysis (P-value=3.28 × 10(-9) after adjustment for age, gender and education) in an intron of the gene cell adhesion molecule 2 (CADM2) for performance on the LDST/DSST. Rs17518584 is located about 170 kb upstream of the transcription start site of the major transcript for the CADM2 gene, but is within an intron of a variant transcript that includes an alternative first exon. The variant is associated with expression of CADM2 in the cingulate cortex (P-value=4 × 10(-4)). The protein encoded by CADM2 is involved in glutamate signaling (P-value=7.22 × 10(-15)), gamma-aminobutyric acid (GABA) transport (P-value=1.36 × 10(-11)) and neuron cell-cell adhesion (P-value=1.48 × 10(-13)). Our findings suggest that genetic variation in the CADM2 gene is associated with individual differences in information processing speed.

Inflammatory markers and extent and progression of early atherosclerosis: Meta-analysis of individual-participant-data from 20 prospective studies of the PROG-IMT collaboration. - Willeit, Peter; Thompson, Simon G; Agewall, Stefan; Bergström, Göran; Bickel, Horst; Catapano, Alberico L; Chien, Kuo-Liong; de Groot, Eric; Empana, Jean-Philippe; Etgen, Thorleif; Franco, Oscar H; Iglseder, Bernhard; et al. (Eur J Prev Cardiol, 2016)
BACKGROUND: Large-scale epidemiological evidence on the role of inflammation in early atherosclerosis, assessed by carotid ultrasound, is lacking. We aimed to quantify cross-sectional and longitudinal associations of inflammatory markers with common-carotid-artery intima-media thickness (CCA-IMT) in the general population. METHODS: Information on high-sensitivity C-reactive protein, fibrinogen, leucocyte count and CCA-IMT was available in 20 prospective cohort studies of the PROG-IMT collaboration involving 49,097 participants free of pre-existing cardiovascular disease. Estimates of associations were calculated within each study and then combined using random-effects meta-analyses. RESULTS: Mean baseline CCA-IMT amounted to 0.74 mm (SD = 0.18) and mean CCA-IMT progression over a mean of 3.9 years to 0.011 mm/year (SD = 0.039). Cross-sectional analyses showed positive linear associations between inflammatory markers and baseline CCA-IMT. After adjustment for traditional cardiovascular risk factors, mean differences in baseline CCA-IMT per one-SD higher inflammatory marker were: 0.0082 mm for high-sensitivity C-reactive protein (p < 0.001); 0.0072 mm for fibrinogen (p < 0.001); and 0.0025 mm for leucocyte count (p = 0.033). 'Inflammatory load', defined as the number of elevated inflammatory markers (i.e. in upper two quintiles), showed a positive linear association with baseline CCA-IMT (p < 0.001). Longitudinal associations of baseline inflammatory markers and changes therein with CCA-IMT progression were null or at most weak. Participants with the highest 'inflammatory load' had a greater CCA-IMT progression (p = 0.015). CONCLUSION: Inflammation was independently associated with CCA-IMT cross-sectionally. The lack of clear associations with CCA-IMT progression may be explained by imprecision in its assessment within a limited time period. Our findings for 'inflammatory load' suggest important combined effects of the three inflammatory markers on early atherosclerosis.

KLB is associated with alcohol drinking, and its gene product β-Klotho is necessary for FGF21 regulation of alcohol preference. - Schumann, Gunter; Liu, Chunyu; O'Reilly, Paul; Gao, He; Song, Parkyong; Xu, Bing; Ruggeri, Barbara; Amin, Najaf; Jia, Tianye; Preis, Sarah; Segura Lepe, Marcelo; Akira, Shizuo; et al. (Proc Natl Acad Sci U S A, 2016)
Excessive alcohol consumption is a major public health problem worldwide. Although drinking habits are known to be inherited, few genes have been identified that are robustly linked to alcohol drinking. We conducted a genome-wide association metaanalysis and replication study among >105,000 individuals of European ancestry and identified β-Klotho (KLB) as a locus associated with alcohol consumption (rs11940694; P = 9.2 × 10(-12)). β-Klotho is an obligate coreceptor for the hormone FGF21, which is secreted from the liver and implicated in macronutrient preference in humans. We show that brain-specific β-Klotho KO mice have an increased alcohol preference and that FGF21 inhibits alcohol drinking by acting on the brain. These data suggest that a liver-brain endocrine axis may play an important role in the regulation of alcohol drinking behavior and provide a unique pharmacologic target for reducing alcohol consumption.

Large-Scale Exome-wide Association Analysis Identifies Loci for White Blood Cell Traits and Pleiotropy with Immune-Mediated Diseases. - Tajuddin, Salman M; Schick, Ursula M; Eicher, John D; Chami, Nathalie; Giri, Ayush; Brody, Jennifer A; Hill, W David; Kacprowski, Tim; Li, Jin; Lyytikäinen, Leo-Pekka; Manichaikul, Ani; Mihailov, Evelin; et al. (Am J Hum Genet, 2016)
White blood cells play diverse roles in innate and adaptive immunity. Genetic association analyses of phenotypic variation in circulating white blood cell (WBC) counts from large samples of otherwise healthy individuals can provide insights into genes and biologic pathways involved in production, differentiation, or clearance of particular WBC lineages (myeloid, lymphoid) and also potentially inform the genetic basis of autoimmune, allergic, and blood diseases. We performed an exome array-based meta-analysis of total WBC and subtype counts (neutrophils, monocytes, lymphocytes, basophils, and eosinophils) in a multi-ancestry discovery and replication sample of ∼157,622 individuals from 25 studies. We identified 16 common variants (8 of which were coding variants) associated with one or more WBC traits, the majority of which are pleiotropically associated with autoimmune diseases. Based on functional annotation, these loci included genes encoding surface markers of myeloid, lymphoid, or hematopoietic stem cell differentiation (CD69, CD33, CD87), transcription factors regulating lineage specification during hematopoiesis (ASXL1, IRF8, IKZF1, JMJD1C, ETS2-PSMG1), and molecules involved in neutrophil clearance/apoptosis (C10orf54, LTA), adhesion (TNXB), or centrosome and microtubule structure/function (KIF9, TUBD1). Together with recent reports of somatic ASXL1 mutations among individuals with idiopathic cytopenias or clonal hematopoiesis of undetermined significance, the identification of a common regulatory 3' UTR variant of ASXL1 suggests that both germline and somatic ASXL1 mutations contribute to lower blood counts in otherwise asymptomatic individuals. These association results shed light on genetic mechanisms that regulate circulating WBC counts and suggest a prominent shared genetic architecture with inflammatory and autoimmune diseases.

Large-scale pharmacogenomic study of sulfonylureas and the QT, JT and QRS intervals: CHARGE Pharmacogenomics Working Group. - Floyd, J S; Sitlani, C M; Avery, C L; Noordam, R; Li, X; Smith, A V; Gogarten, S M; Li, J; Broer, L; Evans, D S; Trompet, S; Brody, J A; et al. (Pharmacogenomics J, 2016)
Sulfonylureas, a commonly used class of medication used to treat type 2 diabetes, have been associated with an increased risk of cardiovascular disease. Their effects on QT interval duration and related electrocardiographic phenotypes are potential mechanisms for this adverse effect. In 11 ethnically diverse cohorts that included 71 857 European, African-American and Hispanic/Latino ancestry individuals with repeated measures of medication use and electrocardiogram (ECG) measurements, we conducted a pharmacogenomic genome-wide association study of sulfonylurea use and three ECG phenotypes: QT, JT and QRS intervals. In ancestry-specific meta-analyses, eight novel pharmacogenomic loci met the threshold for genome-wide significance (P<5 × 10(-8)), and a pharmacokinetic variant in CYP2C9 (rs1057910) that has been associated with sulfonylurea-related treatment effects and other adverse drug reactions in previous studies was replicated. Additional research is needed to replicate the novel findings and to understand their biological basis.The Pharmacogenomics Journal advance online publication, 13 December 2016; doi:10.1038/tpj.2016.90.

Lipoprotein-Associated Phospholipase A2 and Incident Peripheral Arterial Disease in Older Adults: The Cardiovascular Health Study. - Garg, Parveen K; Arnold, Alice M; Hinckley Stukovsky, Karen D; Koro, Carol; Jenny, Nancy S; Mukamal, Kenneth J; Criqui, Michael H; Furberg, Curt D; Newman, Anne B; Cushman, Mary (Arterioscler Thromb Vasc Biol, 2016)
OBJECTIVE: Although prior studies report a relationship between elevated lipoprotein-associated phospholipase A2 (Lp-PLA2) and incident cardiovascular disease, the prospective association of Lp-PLA2 with incident peripheral arterial disease (PAD) has not been studied. We investigated the association between Lp-PLA2 mass and activity and the risk of developing clinical PAD and low ankle-brachial index (ABI). APPROACH AND RESULTS: Among Cardiovascular Health Study participants, a population-based cohort of 5888 adults aged ≥65 years enrolled in 1989 to 1990, Lp-PLA2 mass and activity were measured in 4537 individuals without baseline PAD. Clinical PAD, defined as leg artery revascularization or diagnosed claudication, was ascertained through 2011. Incident low ABI, defined as ABI <0.9 and decline of ≥0.15, was assessed among 3537 individuals who had an ABI >0.9 at baseline and a second ABI measurement 3 or 6 years later. Analyses were adjusted for demographics, cholesterol, smoking, comorbidities, and C-reactive protein. Each standard deviation increment in Lp-PLA2 mass (117 ng/mL) was associated with a higher risk of developing clinical PAD (hazard ratio 1.28; 95% confidence interval 1.13, 1.45) and incident low ABI (odds ratio 1.16; 95% confidence interval 1.00, 1.33). Results per standard deviation increment in Lp-PLA2 activity (13 nmol/min per mL) were similar for clinical PAD (hazard ratio 1.24; 95% confidence interval 1.07, 1.44) and low ABI (odds ratio 1.28; 95% confidence interval 1.09, 1.50). CONCLUSIONS: Higher Lp-PLA2 mass and activity were associated with development of both incident clinical PAD and low ABI. Future studies are needed to determine whether pharmacological inhibition of Lp-PLA2 reduces the incidence of PAD.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Age Factors; Aged; Aging; Ankle Brachial Index; Biomarkers; Chi-Square Distribution; Female; Humans; Incidence; Inflammation Mediators; Logistic Models; Male; Odds Ratio; Peripheral Arterial Disease; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

Longitudinal Relationship Between Loneliness and Social Isolation in Older Adults: Results From the Cardiovascular Health Study. - Petersen, Johanna; Kaye, Jeffrey; Jacobs, Peter G; Quinones, Ana; Dodge, Hiroko; Arnold, Alice; Thielke, Stephen (J Aging Health, 2016)
OBJECTIVE: To understand the longitudinal relationship between loneliness and isolation. METHOD: Participants included 5,870 adults 65 years and older (M = 72.89 ± 5.59 years) from the first 5 years of the Cardiovascular Health Study. Loneliness was assessed using a dichotomized loneliness question. Social isolation was assessed using six items from the Lubben Social Network Scale. Yearly life events were included to assess abrupt social network changes. Mixed effects logistic regression was employed to analyze the relationship between isolation and loneliness. RESULTS: Higher levels of social isolation were associated with higher odds of loneliness, as was an increase (from median) in level of social isolation. Life events such as a friend dying were also associated with increased odds of loneliness. DISCUSSION: These results suggest that average level of isolation and increases in the level of isolation are closely tied to loneliness, which has implications for future assessment or monitoring of loneliness in older adult populations.

Meta-analysis identifies common and rare variants influencing blood pressure and overlapping with metabolic trait loci. - Liu, Chunyu; Kraja, Aldi T; Smith, Jennifer A; Brody, Jennifer A; Franceschini, Nora; Bis, Joshua C; Rice, Kenneth; Morrison, Alanna C; Lu, Yingchang; Weiss, Stefan; Guo, Xiuqing; Palmas, Walter; et al. (Nat Genet, 2016)
Meta-analyses of association results for blood pressure using exome-centric single-variant and gene-based tests identified 31 new loci in a discovery stage among 146,562 individuals, with follow-up and meta-analysis in 180,726 additional individuals (total n = 327,288). These blood pressure-associated loci are enriched for known variants for cardiometabolic traits. Associations were also observed for the aggregation of rare and low-frequency missense variants in three genes, NPR1, DBH, and PTPMT1. In addition, blood pressure associations at 39 previously reported loci were confirmed. The identified variants implicate biological pathways related to cardiometabolic traits, vascular function, and development. Several new variants are inferred to have roles in transcription or as hubs in protein-protein interaction networks. Genetic risk scores constructed from the identified variants were strongly associated with coronary disease and myocardial infarction. This large collection of blood pressure-associated loci suggests new therapeutic strategies for hypertension, emphasizing a link with cardiometabolic risk.

A meta-analysis of 120 246 individuals identifies 18 new loci for fibrinogen concentration. - de Vries, Paul S; Chasman, Daniel I; Sabater-Lleal, Maria; Chen, Ming-Huei; Huffman, Jennifer E; Steri, Maristella; Tang, Weihong; Teumer, Alexander; Marioni, Riccardo E; Grossmann, Vera; Hottenga, Jouke J; Trompet, Stella; et al. (Hum Mol Genet, 2016)
Genome-wide association studies have previously identified 23 genetic loci associated with circulating fibrinogen concentration. These studies used HapMap imputation and did not examine the X-chromosome. 1000 Genomes imputation provides better coverage of uncommon variants, and includes indels. We conducted a genome-wide association analysis of 34 studies imputed to the 1000 Genomes Project reference panel and including ∼120 000 participants of European ancestry (95 806 participants with data on the X-chromosome). Approximately 10.7 million single-nucleotide polymorphisms and 1.2 million indels were examined. We identified 41 genome-wide significant fibrinogen loci; of which, 18 were newly identified. There were no genome-wide significant signals on the X-chromosome. The lead variants of five significant loci were indels. We further identified six additional independent signals, including three rare variants, at two previously characterized loci: FGB and IRF1. Together the 41 loci explain 3% of the variance in plasma fibrinogen concentration.

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.

Meta-analysis of genome-wide association studies of HDL cholesterol response to statins. - Postmus, Iris; Warren, Helen R; Trompet, Stella; Arsenault, Benoit J; Avery, Christy L; Bis, Joshua C; Chasman, Daniel I; de Keyser, Catherine E; Deshmukh, Harshal A; Evans, Daniel S; Feng, QiPing; Li, Xiaohui; et al. (J Med Genet, 2016)
BACKGROUND: In addition to lowering low density lipoprotein cholesterol (LDL-C), statin therapy also raises high density lipoprotein cholesterol (HDL-C) levels. Inter-individual variation in HDL-C response to statins may be partially explained by genetic variation. METHODS AND RESULTS: We performed a meta-analysis of genome-wide association studies (GWAS) to identify variants with an effect on statin-induced high density lipoprotein cholesterol (HDL-C) changes. The 123 most promising signals with p<1×10(-4) from the 16 769 statin-treated participants in the first analysis stage were followed up in an independent group of 10 951 statin-treated individuals, providing a total sample size of 27 720 individuals. The only associations of genome-wide significance (p<5×10(-8)) were between minor alleles at the CETP locus and greater HDL-C response to statin treatment. CONCLUSIONS: Based on results from this study that included a relatively large sample size, we suggest that CETP may be the only detectable locus with common genetic variants that influence HDL-C response to statins substantially in individuals of European descent. Although CETP is known to be associated with HDL-C, we provide evidence that this pharmacogenetic effect is independent of its association with baseline HDL-C levels.

Multiethnic Exome-Wide Association Study of Subclinical Atherosclerosis. - Natarajan, Pradeep; Bis, Joshua C; Bielak, Lawrence F; Cox, Amanda J; Dörr, Marcus; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; Isaacs, Aaron; Jhun, Min A; Kavousi, Maryam; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: -The burden of subclinical atherosclerosis in asymptomatic individuals is heritable and associated with elevated risk of developing clinical coronary heart disease (CHD). We sought to identify genetic variants in protein-coding regions associated with subclinical atherosclerosis and the risk of subsequent CHD. METHODS AND RESULTS: -We studied a total of 25,109 European ancestry and African-American participants with coronary artery calcification (CAC) measured by cardiac computed tomography and 52,869 with common carotid intima media thickness (CIMT) measured by ultrasonography within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Participants were genotyped for 247,870 DNA sequence variants (231,539 in exons) across the genome. A meta-analysis of exome-wide association studies was performed across cohorts for CAC and CIMT. APOB p.Arg3527Gln was associated with four-fold excess CAC (P = 3×10(-10)). The APOE ε2 allele (p.Arg176Cys) was associated with both 22.3% reduced CAC (P = 1×10(-12)) and 1.4% reduced CIMT (P = 4×10(-14)) in carriers compared with non-carriers. In secondary analyses conditioning on LDL cholesterol concentration, the ε2 protective association with CAC, although attenuated, remained strongly significant. Additionally, the presence of ε2 was associated with reduced risk for CHD (OR 0.77; P = 1×10(-11)). CONCLUSIONS: -Exome-wide association meta-analysis demonstrates that protein-coding variants in APOB and APOE associate with subclinical atherosclerosis. APOE ε2 represents the first significant association for multiple subclinical atherosclerosis traits across multiple ethnicities as well as clinical CHD.

Natriuretic peptides and integrated risk assessment for cardiovascular disease: an individual-participant-data meta-analysis. - Willeit, Peter; Kaptoge, Stephen; Welsh, Paul; Butterworth, Adam; Chowdhury, Rajiv; Spackman, Sarah; Pennells, Lisa; Gao, Pei; Burgess, Stephen; Freitag, Daniel; Sweeting, Michael; Wood, Angela; et al. (Lancet Diabetes Endocrinol, 2016)
BACKGROUND: Guidelines for primary prevention of cardiovascular diseases focus on prediction of coronary heart disease and stroke. We assessed whether or not measurement of N-terminal-pro-B-type natriuretic peptide (NT-proBNP) concentration could enable a more integrated approach than at present by predicting heart failure and enhancing coronary heart disease and stroke risk assessment. METHODS: In this individual-participant-data meta-analysis, we generated and harmonised individual-participant data from relevant prospective studies via both de-novo NT-proBNP concentration measurement of stored samples and collection of data from studies identified through a systematic search of the literature (PubMed, Scientific Citation Index Expanded, and Embase) for articles published up to Sept 4, 2014, using search terms related to natriuretic peptide family members and the primary outcomes, with no language restrictions. We calculated risk ratios and measures of risk discrimination and reclassification across predicted 10 year risk categories (ie, <5%, 5% to <7·5%, and ≥7·5%), adding assessment of NT-proBNP concentration to that of conventional risk factors (ie, age, sex, smoking status, systolic blood pressure, history of diabetes, and total and HDL cholesterol concentrations). Primary outcomes were the combination of coronary heart disease and stroke, and the combination of coronary heart disease, stroke, and heart failure. FINDINGS: We recorded 5500 coronary heart disease, 4002 stroke, and 2212 heart failure outcomes among 95 617 participants without a history of cardiovascular disease in 40 prospective studies. Risk ratios (for a comparison of the top third vs bottom third of NT-proBNP concentrations, adjusted for conventional risk factors) were 1·76 (95% CI 1·56-1·98) for the combination of coronary heart disease and stroke and 2·00 (1·77-2·26) for the combination of coronary heart disease, stroke, and heart failure. Addition of information about NT-proBNP concentration to a model containing conventional risk factors was associated with a C-index increase of 0·012 (0·010-0·014) and a net reclassification improvement of 0·027 (0·019-0·036) for the combination of coronary heart disease and stroke and a C-index increase of 0·019 (0·016-0·022) and a net reclassification improvement of 0·028 (0·019-0·038) for the combination of coronary heart disease, stroke, and heart failure. INTERPRETATION: In people without baseline cardiovascular disease, NT-proBNP concentration assessment strongly predicted first-onset heart failure and augmented coronary heart disease and stroke prediction, suggesting that NT-proBNP concentration assessment could be used to integrate heart failure into cardiovascular disease primary prevention. FUNDING: British Heart Foundation, Austrian Science Fund, UK Medical Research Council, National Institute for Health Research, European Research Council, and European Commission Framework Programme 7.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Female; Humans; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Assessment

A novel Alzheimer disease locus located near the gene encoding tau protein. - Jun, G; Ibrahim-Verbaas, C A; Vronskaya, M; Lambert, J-C; Chung, J; Naj, A C; Kunkle, B W; Wang, L-S; Bis, J C; Bellenguez, C; Harold, D; Lunetta, K L; et al. (Mol Psychiatry, 2016)
APOE ɛ4, the most significant genetic risk factor for Alzheimer disease (AD), may mask effects of other loci. We re-analyzed genome-wide association study (GWAS) data from the International Genomics of Alzheimer's Project (IGAP) Consortium in APOE ɛ4+ (10 352 cases and 9207 controls) and APOE ɛ4- (7184 cases and 26 968 controls) subgroups as well as in the total sample testing for interaction between a single-nucleotide polymorphism (SNP) and APOE ɛ4 status. Suggestive associations (P<1 × 10(-4)) in stage 1 were evaluated in an independent sample (stage 2) containing 4203 subjects (APOE ɛ4+: 1250 cases and 536 controls; APOE ɛ4-: 718 cases and 1699 controls). Among APOE ɛ4- subjects, novel genome-wide significant (GWS) association was observed with 17 SNPs (all between KANSL1 and LRRC37A on chromosome 17 near MAPT) in a meta-analysis of the stage 1 and stage 2 data sets (best SNP, rs2732703, P=5·8 × 10(-9)). Conditional analysis revealed that rs2732703 accounted for association signals in the entire 100-kilobase region that includes MAPT. Except for previously identified AD loci showing stronger association in APOE ɛ4+ subjects (CR1 and CLU) or APOE ɛ4- subjects (MS4A6A/MS4A4A/MS4A6E), no other SNPs were significantly associated with AD in a specific APOE genotype subgroup. In addition, the finding in the stage 1 sample that AD risk is significantly influenced by the interaction of APOE with rs1595014 in TMEM106B (P=1·6 × 10(-7)) is noteworthy, because TMEM106B variants have previously been associated with risk of frontotemporal dementia. Expression quantitative trait locus analysis revealed that rs113986870, one of the GWS SNPs near rs2732703, is significantly associated with four KANSL1 probes that target transcription of the first translated exon and an untranslated exon in hippocampus (P ⩽ 1.3 × 10(-8)), frontal cortex (P ⩽ 1.3 × 10(-9)) and temporal cortex (P⩽1.2 × 10(-11)). Rs113986870 is also strongly associated with a MAPT probe that targets transcription of alternatively spliced exon 3 in frontal cortex (P=9.2 × 10(-6)) and temporal cortex (P=2.6 × 10(-6)). Our APOE-stratified GWAS is the first to show GWS association for AD with SNPs in the chromosome 17q21.31 region. Replication of this finding in independent samples is needed to verify that SNPs in this region have significantly stronger effects on AD risk in persons lacking APOE ɛ4 compared with persons carrying this allele, and if this is found to hold, further examination of this region and studies aimed at deciphering the mechanism(s) are warranted.
Keywords: Alzheimer Disease; Apolipoprotein E4; Chromosomes, Human, Pair 17; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; tau Proteins

Novel Genetic Loci Associated With Retinal Microvascular Diameter. - Jensen, Richard A; Sim, Xueling; Smith, Albert Vernon; Li, Xiaohui; Jakobsdottir, Johanna; Cheng, Ching-Yu; Brody, Jennifer A; Cotch, Mary Frances; McKnight, Barbara; Klein, Ronald; Wang, Jie Jin; Kifley, Annette; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: There is increasing evidence that retinal microvascular diameters are associated with cardiovascular and cerebrovascular conditions. The shared genetic effects of these associations are currently unknown. The aim of this study was to increase our understanding of the genetic factors that mediate retinal vessel size. METHODS AND RESULTS: This study extends previous genome-wide association study results using 24 000+ multiethnic participants from 7 discovery cohorts and 5000+ subjects of European ancestry from 2 replication cohorts. Using the Illumina HumanExome BeadChip, we investigate the association of single-nucleotide polymorphisms and variants collectively across genes with summary measures of retinal vessel diameters, referred to as the central retinal venule equivalent and the central retinal arteriole equivalent. We report 4 new loci associated with central retinal venule equivalent, one of which is also associated with central retinal arteriole equivalent. The 4 single-nucleotide polymorphisms are rs7926971 in TEAD1 (P=3.1×10(-) (11); minor allele frequency=0.43), rs201259422 in TSPAN10 (P=4.4×10(-9); minor allele frequency=0.27), rs5442 in GNB3 (P=7.0×10(-10); minor allele frequency=0.05), and rs1800407 in OCA2 (P=3.4×10(-8); minor allele frequency=0.05). The latter single-nucleotide polymorphism, rs1800407, was also associated with central retinal arteriole equivalent (P=6.5×10(-12)). Results from the gene-based burden tests were null. In phenotype look-ups, single-nucleotide polymorphism rs201255422 was associated with both systolic (P=0.001) and diastolic blood pressures (P=8.3×10(-04)). CONCLUSIONS: Our study expands the understanding of genetic factors influencing the size of the retinal microvasculature. These findings may also provide insight into the relationship between retinal and systemic microvascular disease.

{Novel genetic loci underlying human intracranial volume identified through genome-wide association - Adams, H. H.; Hibar, D. P.; Chouraki, V.; Stein, J. L.; Nyquist, P. A.; Renter?a, M. E.; Trompet, S.; Arias-Vasquez, A.; Seshadri, S.; Desrivi?res, S.; Beecham, A. H.; Jahanshad, N.; et al. (Nat Neurosci, 2016)
Intracranial volume reflects the maximally attained brain size during development, and remains stable with loss of tissue in late life. It is highly heritable, but the underlying genes remain largely undetermined. In a genome-wide association study of 32,438 adults, we discovered five previously unknown loci for intracranial volume and confirmed two known signals. Four of the loci were also associated with adult human stature, but these remained associated with intracranial volume after adjusting for height. We found a high genetic correlation with child head circumference (Ïgenetic = 0.748), which indicates a similar genetic background and allowed us to identify four additional loci through meta-analysis (Ncombined = 37,345). Variants for intracranial volume were also related to childhood and adult cognitive function, and Parkinson's disease, and were enriched near genes involved in growth pathways, including PI3K-AKT signaling. These findings identify the biological underpinnings of intracranial volume and their link to physiological and pathological traits.

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.

A principal component meta-analysis on multiple anthropometric traits identifies novel loci for body shape. - Ried, Janina S; Jeff M, Janina; Chu, Audrey Y; Bragg-Gresham, Jennifer L; van Dongen, Jenny; Huffman, Jennifer E; Ahluwalia, Tarunveer S; Cadby, Gemma; Eklund, Niina; Eriksson, Joel; Esko, Tõnu; Feitosa, Mary F; et al. (Nat Commun, 2016)
Large consortia have revealed hundreds of genetic loci associated with anthropometric traits, one trait at a time. We examined whether genetic variants affect body shape as a composite phenotype that is represented by a combination of anthropometric traits. We developed an approach that calculates averaged PCs (AvPCs) representing body shape derived from six anthropometric traits (body mass index, height, weight, waist and hip circumference, waist-to-hip ratio). The first four AvPCs explain >99% of the variability, are heritable, and associate with cardiometabolic outcomes. We performed genome-wide association analyses for each body shape composite phenotype across 65 studies and meta-analysed summary statistics. We identify six novel loci: LEMD2 and CD47 for AvPC1, RPS6KA5/C14orf159 and GANAB for AvPC3, and ARL15 and ANP32 for AvPC4. Our findings highlight the value of using multiple traits to define complex phenotypes for discovery, which are not captured by single-trait analyses, and may shed light onto new pathways.
Keywords: Anthropometry; Body Size; Genome-Wide Association Study; Genotype; Humans; Models, Genetic; Principal Component Analysis

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.

Rare, low frequency and common coding variants in CHRNA5 and their contribution to nicotine dependence in European and African Americans. - Olfson, E; Saccone, N L; Johnson, E O; Chen, L-S; Culverhouse, R; Doheny, K; Foltz, S M; Fox, L; Gogarten, S M; Hartz, S; Hetrick, K; Laurie, C C; et al. (Mol Psychiatry, 2016)
The common nonsynonymous variant rs16969968 in the α5 nicotinic receptor subunit gene (CHRNA5) is the strongest genetic risk factor for nicotine dependence in European Americans and contributes to risk in African Americans. To comprehensively examine whether other CHRNA5 coding variation influences nicotine dependence risk, we performed targeted sequencing on 1582 nicotine-dependent cases (Fagerström Test for Nicotine Dependence score⩾4) and 1238 non-dependent controls, with independent replication of common and low frequency variants using 12 studies with exome chip data. Nicotine dependence was examined using logistic regression with individual common variants (minor allele frequency (MAF)⩾0.05), aggregate low frequency variants (0.05>MAF⩾0.005) and aggregate rare variants (MAF<0.005). Meta-analysis of primary results was performed with replication studies containing 12 174 heavy and 11 290 light smokers. Next-generation sequencing with 180 × coverage identified 24 nonsynonymous variants and 2 frameshift deletions in CHRNA5, including 9 novel variants in the 2820 subjects. Meta-analysis confirmed the risk effect of the only common variant (rs16969968, European ancestry: odds ratio (OR)=1.3, P=3.5 × 10(-11); African ancestry: OR=1.3, P=0.01) and demonstrated that three low frequency variants contributed an independent risk (aggregate term, European ancestry: OR=1.3, P=0.005; African ancestry: OR=1.4, P=0.0006). The remaining 22 rare coding variants were associated with increased risk of nicotine dependence in the European American primary sample (OR=12.9, P=0.01) and in the same risk direction in African Americans (OR=1.5, P=0.37). Our results indicate that common, low frequency and rare CHRNA5 coding variants are independently associated with nicotine dependence risk. These newly identified variants likely influence the risk for smoking-related diseases such as lung cancer.

Rooted in risk: genetic predisposition for low-density lipoprotein cholesterol level associates with diminished low-density lipoprotein cholesterol response to statin treatment. - Smit, Roelof Aj; Postmus, Iris; Trompet, Stella; Barnes, Michael R; Warren, Helen; Arsenault, Benoit J; Chasman, Daniel I; Cupples, L Adrienne; Hitman, Graham A; Krauss, Ronald M; Li, Xiaohui; Psaty, Bruce M; et al. (Pharmacogenomics, 2016)
AIMS: To utilize previously reported lead SNPs for low-density lipoprotein cholesterol (LDL-c) levels to find additional loci of importance to statin response, and examine whether genetic predisposition to LDL-c levels associates with differential statin response. METHODS: We investigated effects on statin response of 59 LDL-c SNPs, by combining summary level statistics from the Global Lipids Genetics and Genomic Investigation of Statin Therapy consortia. RESULTS: Lead SNPs for APOE, SORT1 and NPC1L1 were associated with a decreased LDL-c response to statin treatment, as was overall genetic predisposition for increased LDL-c levels as quantified with 59 SNPs, with a 5.4% smaller statin response per standard deviation increase in genetically raised LDL-c levels. CONCLUSION: Genetic predisposition for increased LDL-c level may decrease efficacy of statin therapy.
Keywords: Cholesterol, LDL; Genetic Predisposition to Disease; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide; Triglycerides

Soluble CD14 and fracture risk. - Bethel, M; Bůžková, P; Fink, H A; Robbins, J A; Cauley, J A; Lee, J; Barzilay, J I; Jalal, D I; Carbone, L D (Osteoporos Int, 2016)
UNLABELLED: Soluble CD14 (sCD14) is an inflammatory marker associated with osteoclasts. Using Cox proportional hazards models, we found a positive association between plasma levels of sCD14 and risk of incident fracture among participants in the Cardiovascular Health Study. sCD14 may be useful in identifying those at risk for fracture. INTRODUCTION: Soluble CD14, a proinflammatory cytokine, is primarily derived from macrophages/monocytes that can differentiate into osteoclasts. The purpose of this study was to examine the relationship between sCD14 levels and osteoporotic fractures. METHODS: In the Cardiovascular Health Study, 5462 men and women had sCD14 levels measured at baseline. Incident hip fractures (median follow-up time 12.5 years) and incident composite fractures (defined as the first hip, pelvis, humerus, or distal radius fracture, median follow-up 8.6 years) were identified from hospital discharge summaries and/or Medicare claims data. Cox proportional hazards models were used to model the association between sCD14 levels and time to incident hip or composite fracture, overall and as a function of race and gender. RESULTS: In unadjusted models, there was a positive association between sCD14 levels (per 1 standard deviation increase, i.e., 361.6 ng/mL) and incident hip (HR, 1.26; 95 % CI, 1.17, 1.36) and composite (HR, 1.20; 95 % CI, 1.12, 1.28) fractures. When models were fully adjusted for demographics, lifestyle factors, and medication use, these associations were no longer significant. However, in whites, the association of sCD14 levels with hip fractures remained significant in fully adjusted models (HR, 1.11; 95 % CI, 1.01-1.23). Associations of sCD14 levels with hip and composite fracture did not differ between men and women. CONCLUSIONS: In this large cohort of community-dwelling older adults, higher sCD14 levels were associated with an increased risk of incident hip fractures in whites.

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2016)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (nStage1: 111,666; nStage2: 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (PPM1J, EDEM3, ACP1, SPEG, EYA4, CYP1A1, and ATXN2L; PStage1<3.7×10(-7)), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, SOS2 (P=5.4×10(-8) by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of acp1- and sos2-knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.

Systemic markers of microvascular disease and bone mineral density in older adults : The cardiovascular health study. - Barzilay, J I; Bůžková, P; Fink, H A; Cauley, J A; Robbins, J A; Garimella, P S; Jalal, D I; Mukamal, K J (Osteoporos Int, 2016)
Here we report that abnormal brain white matter and, to a lesser extent, albuminuria are associated with reduced bone mineral density in the hip, spine, and total body in men and women. These findings may explain the increased hip fracture risk reported in some studies in association with microvascular disorders. INTRODUCTION: Markers of microvascular disease have been individually associated with increased risk of osteoporotic fractures in some studies. Here, we examine whether these markers are associated with reduced bone mineral density (BMD) individually and together. METHODS: BMD testing using dual x-ray absorptiometry of the hip, lumbar spine, and total body was performed in 1473 participants from the Cardiovascular Health Study (mean age ~ 78 years): 1215 were assessed for urinary albumin-creatinine ratio, 944 for abnormal white matter disease (AWMD) by brain MRI, and 541 for retinal vascular disease with fundus photographs. Linear regression models were used to evaluate the cross-sectional association of each marker with BMD accounting for potentially confounding factors. RESULTS: AWMD was associated with lower hip, spine, and total body BMD in women (β -3.08 to -4.53; p < 0.01 for all) and lower hip and total body BMD in men (β -2.90 to -4.24; p = 0.01-0.03). Albuminuria was associated with lower hip (β -3.37; p = .05) and total body (β -3.21; p = .02) BMD in men, but not in women. The associations of AWMD and albuminuria with BMD persisted with mutual adjustment and appeared to be additive to each other. Retinal vascular disease was not associated with BMD in men or women. CONCLUSION: AWMD and, to a lesser extent, albuminuria were independently associated with lower BMD, suggesting that microvascular disease may play a role in the pathogenesis of reduced BMD. These findings need to be confirmed by longitudinal studies.

Testosterone, Dihydrotestosterone, Sex Hormone Binding Globulin and Incident Diabetes among Older Men: the Cardiovascular Health Study. - Joyce, Katherine E; Biggs, Mary L; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Siscovick, David S; Shores, Molly M; Matsumoto, Alvin M; Mukamal, Kenneth J (J Clin Endocrinol Metab, 2016)
CONTEXT: Although sex hormone binding globulin (SHBG) and testosterone (T) have been inversely associated with risk of diabetes, few studies have examined dihydrotestosterone (DHT), a more potent androgen than T, or older adults, whose glycemic pathophysiology differs from younger adults. OBJECTIVE: To determine the associations of SHBG, T, and DHT with insulin resistance and incident diabetes in older adult men. DESIGN: In a prospective cohort study, we evaluated baseline levels of SHBG, T, and DHT using liquid chromatography-tandem mass spectrometry among 852 men in the Cardiovascular Health Study free of diabetes and cardiovascular disease in 1994. MAIN OUTCOME: Insulin resistance estimated by HOMA-IR and insulin sensitivity estimated by the Gutt index in 1996, and incident diabetes (n=112) ascertained over a mean follow-up of 9.8 years. RESULTS: In linear regression models adjusted for demographics, alcohol consumption, current smoking, body-mass index, and other androgens, SHBG (HOMA-IR 0.30 units lower per doubling; 95% confidence interval [CI], 0.08-0.52; p=0.01) and total DHT (HOMA-IR 0.18 units lower per doubling; 95% CI 0.06-0.30; p=0.01), but not free T (p=0.33) were inversely associated with insulin resistance. In corresponding Cox proportional hazards models, total DHT was again inversely associated with risk of diabetes (adjusted hazard ratio per doubling 0.69; 95% CI, 0.52-0.92; p=0.01), but SHBG (hazard ratio 1.09; 95% CI, 0.74-1.59; p=0.66) and free T (hazard ratio 1.15; 95% CI, 0.92-1.43; p=0.23) were not. CONCLUSIONS: Among older men, higher levels of DHT are inversely associated with insulin resistance and risk of diabetes over the ensuing 10 years, while levels of T are not. Future studies are still needed to clarify the role of SHBG in risk of diabetes in this population.

Thyroid Function Within the Reference Range and the Risk of Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Collet, Tinh-Hai; Ikram, M Arfan; Blum, Manuel R; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Portegies, Marileen L P; Iervasi, Giorgio; Medici, Marco; et al. (J Clin Endocrinol Metab, 2016)
CONTEXT: The currently applied reference ranges for thyroid function are under debate. Despite evidence that thyroid function within the reference range is related with several cardiovascular disorders, its association with the risk of stroke has not been evaluated previously. DESIGN AND SETTING: We identified studies through a systematic literature search and the Thyroid Studies Collaboration, a collaboration of prospective cohort studies. Studies measuring baseline TSH, free T4, and stroke outcomes were included, and we collected individual participant data from each study, including thyroid function measurements and incident all stroke (combined fatal and nonfatal) and fatal stroke. The applied reference range for TSH levels was between 0.45 and 4.49 mIU/L. RESULTS: We collected individual participant data on 43 598 adults with TSH within the reference range from 17 cohorts, with a median follow-up of 11.6 years (interquartile range 5.1-13.9), including 449 908 person-years. Age- and sex-adjusted pooled hazard ratio for TSH was 0.78 (95% confidence interval [CI] 0.65-0.95 across the reference range of TSH) for all stroke and 0.83 (95% CI 0.62-1.09) for fatal stroke. For the free T4 analyses, the hazard ratio was 1.08 (95% CI 0.99-1.15 per SD increase) for all stroke and 1.10 (95% CI 1.04-1.19) for fatal stroke. This was independent of cardiovascular risk factors including systolic blood pressure, total cholesterol, smoking, and prevalent diabetes. CONCLUSION: Higher levels of TSH within the reference range may decrease the risk of stroke, highlighting the need for further research focusing on the clinical consequences associated with differences within the reference range of thyroid function.

Trans-ethnic Meta-analysis and Functional Annotation Illuminates the Genetic Architecture of Fasting Glucose and Insulin. - Liu, Ching-Ti; Raghavan, Sridharan; Maruthur, Nisa; Kabagambe, Edmond Kato; Hong, Jaeyoung; Ng, Maggie C Y; Hivert, Marie-France; Lu, Yingchang; An, Ping; Bentley, Amy R; Drolet, Anne M; Gaulton, Kyle J; et al. (Am J Hum Genet, 2016)
Knowledge of the genetic basis of the type 2 diabetes (T2D)-related quantitative traits fasting glucose (FG) and insulin (FI) in African ancestry (AA) individuals has been limited. In non-diabetic subjects of AA (n = 20,209) and European ancestry (EA; n = 57,292), we performed trans-ethnic (AA+EA) fine-mapping of 54 established EA FG or FI loci with detailed functional annotation, assessed their relevance in AA individuals, and sought previously undescribed loci through trans-ethnic (AA+EA) meta-analysis. We narrowed credible sets of variants driving association signals for 22/54 EA-associated loci; 18/22 credible sets overlapped with active islet-specific enhancers or transcription factor (TF) binding sites, and 21/22 contained at least one TF motif. Of the 54 EA-associated loci, 23 were shared between EA and AA. Replication with an additional 10,096 AA individuals identified two previously undescribed FI loci, chrX FAM133A (rs213676) and chr5 PELO (rs6450057). Trans-ethnic analyses with regulatory annotation illuminate the genetic architecture of glycemic traits and suggest gene regulation as a target to advance precision medicine for T2D. Our approach to utilize state-of-the-art functional annotation and implement trans-ethnic association analysis for discovery and fine-mapping offers a framework for further follow-up and characterization of GWAS signals of complex trait loci.

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)

Age, Race and Gender Factors in Incident Disability. - Jacob, Mini E; Marron, Megan M; Boudreau, Robert; Odden, Michelle C; Arnold, Alice M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2017)
Background: Incident disability rates enable the comparison of risk across populations. Understanding these by age, sex and race is important for planning for the care of older adults and targeting prevention. Methods: We calculated incident disability rates among older adults in the Cardiovascular Health Study, a study of 5,888 older adults aged ≥ 65 years over 6 years of follow-up. Disability was defined in 2 ways: 1) self-report of disability (severe difficulty or inability) in any of 6 ADLs, and 2) mobility difficulty (any difficulty walking half a mile or climbing 10 steps). Incident disability rates were calculated as events per 100 person years for age, gender and race groups. Results: The incidence of ADL disability, and mobility difficulty were 2.7 (2.5-2.8), and 9.8 (9.4 -10.3) events per 100 person years. Women, older participants and blacks had higher rates in both domains. Conclusion: Incidence rates are considerably different based on the domain examined as well as age, race and gender composition of the population. Prevention efforts should focus on high risk populations and attempt to ameliorate factors that increase risk in these groups.

Analysis commons, a team approach to discovery in a big-data environment for genetic epidemiology. - Brody, Jennifer A; Morrison, Alanna C; Bis, Joshua C; O'Connell, Jeffrey R; Brown, Michael R; Huffman, Jennifer E; Ames, Darren C; Carroll, Andrew; Conomos, Matthew P; Gabriel, Stacey; Gibbs, Richard A; Gogarten, Stephanie M; et al. (Nat Genet, 2017)

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study. - Haycock, Philip C; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J; Evans, David M; Willeit, Peter; Aviv, Abraham; Gaunt, Tom R; et al. (JAMA Oncol, 2017)
Importance: The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. Objective: To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases. Data Sources: Genomewide association studies (GWAS) published up to January 15, 2015. Study Selection: GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available. Data Extraction and Synthesis: Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population. Main Outcomes and Measures: Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation. Results: Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]). Conclusions and Relevance: It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Germ-Line Mutation; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neoplasms; Polymorphism, Single Nucleotide; Risk Assessment; Telomere; Telomere Homeostasis

Association of Coronary Artery Calcium Score vs Age With Cardiovascular Risk in Older Adults: An Analysis of Pooled Population-Based Studies. - Yano, Yuichiro; O'Donnell, Christopher J; Kuller, Lewis; Kavousi, Maryam; Erbel, Raimund; Ning, Hongyan; D'Agostino, Ralph; Newman, Anne B; Nasir, Khurram; Hofman, Albert; Lehmann, Nils; Dhana, Klodian; et al. (JAMA Cardiol, 2017)
Importance: Besides age, other discriminators of atherosclerotic cardiovascular disease (ASCVD) risk are needed in older adults. Objectives: To examine the predictive ability of coronary artery calcium (CAC) score vs age for incident ASCVD and how risk prediction changes by adding CAC score and removing only age from prediction models. Design, Setting, and Participants: We conducted an analysis of pooled US population-based studies, including the Framingham Heart Study, the Multi-Ethnic Study of Atherosclerosis, and the Cardiovascular Health Study. Results were compared with 2 European cohorts, the Rotterdam Study and the Heinz Nixdorf Recall Study. Participants underwent CAC scoring between 1998 and 2006 using cardiac computed tomography. The participants included adults older than 60 years without known ASCVD at baseline. Exposures: Coronary artery calcium scores. Main Outcomes and Measures: Incident ASCVD events including coronary heart disease (CHD) and stroke. Results: The study included 4778 participants from 3 US cohorts, with a mean age of 70.1 years; 2582 (54.0%) were women, and 2431 (50.9%) were nonwhite. Over 11 years of follow-up (44 152 person-years), 405 CHD and 228 stroke events occurred. Coronary artery calcium score (vs age) had a greater association with incident CHD (C statistic, 0.733 vs 0.690; C statistics difference, 0.043; 95% CI of difference, 0.009-0.075) and modestly improved prediction of incident stroke (C statistic, 0.695 vs 0.670; C statistics difference, 0.025; 95% CI of difference, -0.015 to 0.064). Adding CAC score to models including traditional cardiovascular risk factors, with only age being removed, provided improved discrimination for incident CHD (C statistic, 0.735 vs 0.703; C statistics difference, 0.032; 95% CI of difference, 0.002-0.062) but not for stroke. Coronary artery calcium score was more likely than age to provide higher category-free net reclassification improvement among participants who experienced an ASCVD event (0.390; 95% CI, 0.312-0.467 vs 0.08; 95% CI -0.001 to 0.181) and to result in more accurate reclassification of risk for ASCVD events among these individuals. The findings were similar in the 2 European cohorts (n = 4990). Conclusions and Relevance: Coronary artery calcium may be an alternative marker besides age to better discriminate between lower and higher CHD risk in older adults. Whether CAC score can assist in guiding the decision to initiate statin treatment for primary prevention in older adults requires further investigation.

Comparison of HapMap and 1000 Genomes Reference Panels in a Large-Scale Genome-Wide Association Study. - de Vries, Paul S; Sabater-Lleal, Maria; Chasman, Daniel I; Trompet, Stella; Ahluwalia, Tarunveer S; Teumer, Alexander; Kleber, Marcus E; Chen, Ming-Huei; Wang, Jie Jin; Attia, John R; Marioni, Riccardo E; Steri, Maristella; et al. (PLoS One, 2017)
An increasing number of genome-wide association (GWA) studies are now using the higher resolution 1000 Genomes Project reference panel (1000G) for imputation, with the expectation that 1000G imputation will lead to the discovery of additional associated loci when compared to HapMap imputation. In order to assess the improvement of 1000G over HapMap imputation in identifying associated loci, we compared the results of GWA studies of circulating fibrinogen based on the two reference panels. Using both HapMap and 1000G imputation we performed a meta-analysis of 22 studies comprising the same 91,953 individuals. We identified six additional signals using 1000G imputation, while 29 loci were associated using both HapMap and 1000G imputation. One locus identified using HapMap imputation was not significant using 1000G imputation. The genome-wide significance threshold of 5×10-8 is based on the number of independent statistical tests using HapMap imputation, and 1000G imputation may lead to further independent tests that should be corrected for. When using a stricter Bonferroni correction for the 1000G GWA study (P-value < 2.5×10-8), the number of loci significant only using HapMap imputation increased to 4 while the number of loci significant only using 1000G decreased to 5. In conclusion, 1000G imputation enabled the identification of 20% more loci than HapMap imputation, although the advantage of 1000G imputation became less clear when a stricter Bonferroni correction was used. More generally, our results provide insights that are applicable to the implementation of other dense reference panels that are under development.

The complex genetics of gait speed: genome-wide meta-analysis approach. - Ben-Avraham, Dan; Karasik, David; Verghese, Joe; Lunetta, Kathryn L; Smith, Jennifer A; Eicher, John D; Vered, Rotem; Deelen, Joris; Arnold, Alice M; Buchman, Aron S; Tanaka, Toshiko; Faul, Jessica D; et al. (Aging (Albany NY), 2017)
Emerging evidence suggests that the basis for variation in late-life mobility is attributable, in part, to genetic factors, which may become increasingly important with age. Our objective was to systematically assess the contribution of genetic variation to gait speed in older individuals. We conducted a meta-analysis of gait speed GWASs in 31,478 older adults from 17 cohorts of the CHARGE consortium, and validated our results in 2,588 older adults from 4 independent studies. We followed our initial discoveries with network and eQTL analysis of candidate signals in tissues. The meta-analysis resulted in a list of 536 suggestive genome wide significant SNPs in or near 69 genes. Further interrogation with Pathway Analysis placed gait speed as a polygenic complex trait in five major networks. Subsequent eQTL analysis revealed several SNPs significantly associated with the expression of PRSS16, WDSUB1 and PTPRT, which in addition to the meta-analysis and pathway suggested that genetic effects on gait speed may occur through synaptic function and neuronal development pathways. No genome-wide significant signals for gait speed were identified from this moderately large sample of older adults, suggesting that more refined physical function phenotypes will be needed to identify the genetic basis of gait speed in aging.

Detection of genetic loci associated with plasma fetuin-A: A meta-analysis of genome-wide association studies from the CHARGE Consortium. - Jensen, Majken K; Jensen, Richard A; Mukamal, Kenneth J; Guo, Xiuqing; Yao, Jie; Sun, Qi; Cornelis, Marilyn; Liu, Yongmei; Chen, Ming-Huei; Kizer, Jorge R; Djoussé, Luc; Siscovick, David S; et al. (Hum Mol Genet, 2017)
Plasma fetuin-A is associated with type 2 diabetes, and AHSG, the gene encoding fetuin-A, has been identified as a susceptibility locus for diabetes and metabolic syndrome. Thus far, unbiased investigations of the genetic determinants of plasma fetuin-A concentrations have not been conducted. We searched for single nucleotide polymorphisms (SNPs) related to fetuin-A concentrations by a genome-wide association study in six population-based studies.We examined the association of fetuin-A levels with ∼ 2.5 million genotyped and imputed SNPs in 9,055 participants of European descent and 2,119 African Americans. In both ethnicities, strongest associations were centered in a region with a high degree of LD near the AHSG locus. Among 136 genome-wide significant (p < 0.05x10-8) SNPs near the AHSG locus, the top SNP was rs4917 (p = 1.27x10-303), a known coding SNP in exon 6 that is associated with a 0.06 g/L (∼13%) lower fetuin-A level. This variant alone explained 14% of the variation in fetuin-A levels. Analyses conditioned on rs4917 indicated that the strong association with the AHSG locus stems from additional independent associations of multiple variants among European Americans. In conclusion, levels of fetuin-A in plasma are strongly associated with SNPs in its encoding gene, AHSG, but not elsewhere in the genome. Given the strength of the associations observed for multiple independent SNPs, the AHSG gene is an example of a candidate locus suitable for additional investigations including fine mapping to elucidate the biological basis of the findings and further functional experiments to clarify AHSG as a potential therapeutic target.

Discovery and fine-mapping of adiposity loci using high density imputation of genome-wide association studies in individuals of African ancestry: African ancestry anthropometry genetics consortium. - Ng, Maggie C Y; Graff, Mariaelisa; Lu, Yingchang; Justice, Anne E; Mudgal, Poorva; Liu, Ching-Ti; Young, Kristin; Yanek, Lisa R; Feitosa, Mary F; Wojczynski, Mary K; Rand, Kristin; Brody, Jennifer A; et al. (PLoS Genet, 2017)
Genome-wide association studies (GWAS) have identified >300 loci associated with measures of adiposity including body mass index (BMI) and waist-to-hip ratio (adjusted for BMI, WHRadjBMI), but few have been identified through screening of the African ancestry genomes. We performed large scale meta-analyses and replications in up to 52,895 individuals for BMI and up to 23,095 individuals for WHRadjBMI from the African Ancestry Anthropometry Genetics Consortium (AAAGC) using 1000 Genomes phase 1 imputed GWAS to improve coverage of both common and low frequency variants in the low linkage disequilibrium African ancestry genomes. In the sex-combined analyses, we identified one novel locus (TCF7L2/HABP2) for WHRadjBMI and eight previously established loci at P < 5×10-8: seven for BMI, and one for WHRadjBMI in African ancestry individuals. An additional novel locus (SPRYD7/DLEU2) was identified for WHRadjBMI when combined with European GWAS. In the sex-stratified analyses, we identified three novel loci for BMI (INTS10/LPL and MLC1 in men, IRX4/IRX2 in women) and four for WHRadjBMI (SSX2IP, CASC8, PDE3B and ZDHHC1/HSD11B2 in women) in individuals of African ancestry or both African and European ancestry. For four of the novel variants, the minor allele frequency was low (<5%). In the trans-ethnic fine mapping of 47 BMI loci and 27 WHRadjBMI loci that were locus-wide significant (P < 0.05 adjusted for effective number of variants per locus) from the African ancestry sex-combined and sex-stratified analyses, 26 BMI loci and 17 WHRadjBMI loci contained ≤ 20 variants in the credible sets that jointly account for 99% posterior probability of driving the associations. The lead variants in 13 of these loci had a high probability of being causal. As compared to our previous HapMap imputed GWAS for BMI and WHRadjBMI including up to 71,412 and 27,350 African ancestry individuals, respectively, our results suggest that 1000 Genomes imputation showed modest improvement in identifying GWAS loci including low frequency variants. Trans-ethnic meta-analyses further improved fine mapping of putative causal variants in loci shared between the African and European ancestry populations.

Discovery and fine-mapping of loci associated with monounsaturated fatty acids through trans-ethnic meta-analysis in Chinese and European populations. - Hu, Yao; Tanaka, Toshiko; Zhu, Jingwen; Guan, Weihua; Wu, Jason H Y; Psaty, Bruce M; McKnight, Barbara; King, Irena B; Sun, Qi; Richard, Melissa; Manichaikul, Ani; Frazier-Wood, Alexis C; et al. (J Lipid Res, 2017)
Monounsaturated fatty acids (MUFAs) are unsaturated fatty acids with one double bond and are derived from endogenous synthesis and dietary intake. Accumulating evidence has suggested that plasma and erythrocyte MUFA levels were associated with cardiometabolic disorders including cardiovascular disease (CVD), type 2 diabetes (T2D) and metabolic syndrome (MS). Previous genome-wide association studies (GWAS) have identified seven loci for plasma and erythrocyte palmitoleic acid and oleic acid levels in populations of European origin. To identify additional MUFA-associated loci and the potential causal variant at each locus, we performed ethnic-specific GWAS meta-analyses and trans-ethnic meta-analyses in over 15,000 participants of Chinese- and European-ancestry. We identified novel genome-wide significant associations for vaccenic acid at FADS1/2 and PKD2L1 [log10(Bayes factor)>=8.07] and for gondoic acid at FADS1/2 and GCKR [log10(Bayes factor)>=61619;6.22], and also observed improved fine-mapping resolutions at FADS1/2 and GCKR loci. The greatest improvement was observed at GCKR, where the number of variants in the 99% credible set was reduced from 16 (covering ~95kb) to five (covering ~20kb, including a missense variant rs1260326) after trans-ethnic meta-analysis. We also confirmed the previously reported associations of PKD2L1, FADS1/2, GCKR and HIF1AN with palmitoleic acid and of FADS1/2 and LPCAT3 with oleic acid in the Chinese-specific GWAS and trans-ethnic meta-analyses. Pathway-based analyses suggested that the identified loci were enriched in unsaturated fatty acids metabolism and signaling pathways. Our findings provided novel insight into the genetic basis relevant to MUFA metabolism and biology.

Discovery and replication of SNP-SNP interactions for quantitative lipid traits in over 60,000 individuals. - Holzinger, Emily R; Verma, Shefali S; Moore, Carrie B; Hall, Molly; De, Rishika; Gilbert-Diamond, Diane; Lanktree, Matthew B; Pankratz, Nathan; Amuzu, Antoinette; Burt, Amber; Dale, Caroline; Dudek, Scott; et al. (BioData Min, 2017)
BACKGROUND: The genetic etiology of human lipid quantitative traits is not fully elucidated, and interactions between variants may play a role. We performed a gene-centric interaction study for four different lipid traits: low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglycerides (TG). RESULTS: Our analysis consisted of a discovery phase using a merged dataset of five different cohorts (n = 12,853 to n = 16,849 depending on lipid phenotype) and a replication phase with ten independent cohorts totaling up to 36,938 additional samples. Filters are often applied before interaction testing to correct for the burden of testing all pairwise interactions. We used two different filters: 1. A filter that tested only single nucleotide polymorphisms (SNPs) with a main effect of p < 0.001 in a previous association study. 2. A filter that only tested interactions identified by Biofilter 2.0. Pairwise models that reached an interaction significance level of p < 0.001 in the discovery dataset were tested for replication. We identified thirteen SNP-SNP models that were significant in more than one replication cohort after accounting for multiple testing. CONCLUSIONS: These results may reveal novel insights into the genetic etiology of lipid levels. Furthermore, we developed a pipeline to perform a computationally efficient interaction analysis with multi-cohort replication.

Discovery of novel heart rate-associated loci using the Exome Chip. - van den Berg, Marten E; Warren, Helen R; Cabrera, Claudia P; Verweij, Niek; Mifsud, Borbala; Haessler, Jeffrey; Bihlmeyer, Nathan A; Fu, Yi-Ping; Weiss, Stefan; Lin, Henry J; Grarup, Niels; Li-Gao, Ruifang; et al. (Hum Mol Genet, 2017)
Background Resting heart rate is a heritable trait, and an increase in heart rate is associated with increased mortality risk. GWAS analyses have found loci associated with resting heart rate, at the time of our study these loci explained 0.9% of the variation.Aim To discover new genetic loci associated with heart rate from Exome Chip meta-analyses.Methods Heart rate was measured from either elecrtrocardiograms or pulse recordings. We meta-analysed heart rate association results from 104,452 European-ancestry individuals from 30 cohorts, genotyped using the Exome Chip. Twenty-four variants were selected for follow-up in an independent dataset (UK Biobank, N = 134,251). Conditional and gene-based testing was undertaken, and variants were investigated with bioinformatics methods.Results We discovered five novel heart rate loci, and one new independent low-frequency non-synonymous variant in an established heart rate locus (KIAA1755). Lead variants in four of the novel loci are non-synonymous variants in the genes C10orf71, DALDR3, TESK2, SEC31B. The variant at SEC31B is significantly associated with SEC31B expression in heart and tibial nerve tissue. Further candidate genes were detected from long range regulatory chromatin interactions in heart tissue (SCD, SLF2, MAPK8). We observed significant enrichment in DNase I hypersensitive sites in fetal heart and lung. Moreover, enrichment was seen for the first time in human neuronal progenitor cells (derived from embryonic stem cells) and fetal muscle samples by including our novel variants.Conclusion Our findings advance the knowledge of the genetic architecture of heart rate, and indicate new candidate genes for follow-up functional studies.

DNA Methylation Analysis Identifies Loci for Blood Pressure Regulation. - Richard, Melissa A; Huan, Tianxiao; Ligthart, Symen; Gondalia, Rahul; Jhun, Min A; Brody, Jennifer A; Irvin, Marguerite R; Marioni, Riccardo; Shen, Jincheng; Tsai, Pei-Chien; Montasser, May E; Jia, Yucheng; et al. (Am J Hum Genet, 2017)
Genome-wide association studies have identified hundreds of genetic variants associated with blood pressure (BP), but sequence variation accounts for a small fraction of the phenotypic variance. Epigenetic changes may alter the expression of genes involved in BP regulation and explain part of the missing heritability. We therefore conducted a two-stage meta-analysis of the cross-sectional associations of systolic and diastolic BP with blood-derived genome-wide DNA methylation measured on the Infinium HumanMethylation450 BeadChip in 17,010 individuals of European, African American, and Hispanic ancestry. Of 31 discovery-stage cytosine-phosphate-guanine (CpG) dinucleotides, 13 replicated after Bonferroni correction (discovery: N = 9,828, p < 1.0 × 10-7; replication: N = 7,182, p < 1.6 × 10-3). The replicated methylation sites are heritable (h2 > 30%) and independent of known BP genetic variants, explaining an additional 1.4% and 2.0% of the interindividual variation in systolic and diastolic BP, respectively. Bidirectional Mendelian randomization among up to 4,513 individuals of European ancestry from 4 cohorts suggested that methylation at cg08035323 (TAF1B-YWHAQ) influences BP, while BP influences methylation at cg00533891 (ZMIZ1), cg00574958 (CPT1A), and cg02711608 (SLC1A5). Gene expression analyses further identified six genes (TSPAN2, SLC7A11, UNC93B1, CPT1A, PTMS, and LPCAT3) with evidence of triangular associations between methylation, gene expression, and BP. Additional integrative Mendelian randomization analyses of gene expression and DNA methylation suggested that the expression of TSPAN2 is a putative mediator of association between DNA methylation at cg23999170 and BP. These findings suggest that heritable DNA methylation plays a role in regulating BP independently of previously known genetic variants.
Keywords: Aged; Blood Pressure; CpG Islands; Cross-Sectional Studies; DNA Methylation; Epigenesis, Genetic; Genetic Variation; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Middle Aged; Nerve Tissue Proteins; Quantitative Trait Loci; Tetraspanins

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

Fine mapping of QT interval regions in global populations refines previously identified QT interval loci and identifies signals unique to African and Hispanic descent populations. - Avery, Christy L; Wassel, Christina L; Richard, Melissa A; Highland, Heather M; Bien, Stephanie; Zubair, Niha; Soliman, Elsayed Z; Fornage, Myriam; Bielinski, Suzette J; Tao, Ran; Seyerle, Amanda A; Shah, Sanjiv J; et al. (Heart Rhythm, 2017)
BACKGROUND: The electrocardiographically measured QT interval (QT) is heritable and its prolongation is an established risk factor for several cardiovascular diseases. Yet, most QT genetic studies have been performed in European ancestral populations, possibly reducing their global relevance. OBJECTIVE: To leverage diversity and improve biological insight, we fine mapped 16 of the 35 previously identified QT loci (46%) in populations of African American (n = 12,410) and Hispanic/Latino (n = 14,837) ancestry. METHODS: Racial/ethnic-specific multiple linear regression analyses adjusted for heart rate and clinical covariates were examined separately and in combination after inverse-variance weighted trans-ethnic meta-analysis. RESULTS: The 16 fine-mapped QT loci included on the Illumina Metabochip represented 21 independent signals, of which 16 (76%) were significantly (P-value≤9.1×10(-5)) associated with QT. Through sequential conditional analysis we also identified three trans-ethnic novel SNPs at ATP1B1, SCN5A-SCN10A, and KCNQ1 and three Hispanic/Latino-specific novel SNPs at NOS1AP and SCN5A-SCN10A (two novel SNPs) with evidence of associations with QT independent of previous identified GWAS lead SNPs. Linkage disequilibrium patterns helped to narrow the region likely to contain the functional variants at several loci, including NOS1AP, USP50-TRPM7, and PRKCA, although intervals surrounding SLC35F1-PLN and CNOT1 remained broad in size (>100 kb). Finally, bioinformatics-based functional characterization suggested a regulatory function in cardiac tissues for the majority of independent signals that generalized and the novel SNPs. CONCLUSION: Our findings suggest that a majority of identified SNPs implicate gene regulatory dysfunction in QT prolongation, that the same loci influence variation in QT across global populations, and that additional, novel, population-specific QT signals exist.

Galectin-3 and Venous Thromboembolism Incidence: the Atherosclerosis Risk in Communities (ARIC) Study. - Fashanu, Oluwaseun E; Heckbert, Susan R; Aguilar, David; Jensen, Paul N; Ballantyne, Christie M; Basu, Saonli; Hoogeveen, Ron C; DeFilippi, Christopher; Cushman, Mary; Folsom, Aaron R (Res Pract Thromb Haemost, 2017)
Background: The inflammatory biomarker galectin-3 contributes to pathologic conditions such as heart failure and stimulates murine thrombogenesis. Its association with venous thromboembolism (VTE) has been sparsely studied. Objectives: To assess the prospective association of plasma galectin-3 and the LGALS3 rs4644 SNP with VTE incidence. Methods: We measured plasma galectin-3 in 9,916 participants in the Atherosclerosis Risk in Communities (ARIC) study cohort in 1996 - 1998 and identified VTEs through 2013. Using Cox regression, we estimated the hazard ratio associating galectin-3 with incident VTE over a median of 13.9 years. Replication was sought in the Cardiovascular Health Study (CHS). Results: ARIC included 21.8% blacks and 56.2% females with mean baseline age of 62.7 years. The incidence rate of VTE (n=389 events) increased across quintiles of galectin-3, with hazard ratios (95% CI) of 1 (reference), 1.13 (0.80 - 1.61), 1.00 (0.70 - 1.43), 1.36 (0.96 - 1.91), and 1.55 (1.09 - 2.19) (p-trend = 0.005), adjusted for age, sex, race, body mass index, diabetes status, and renal function. Results did not replicate in the CHS (124 VTE), but meta-analysis of both studies yielded a pooled hazard ratio (95% CI) for 1 SD increment in log galectin-3 of 1.10 (1.00 - 1.22). In ARIC, the C allele of rs4644 in the LGALS3 gene was associated with higher galectin-3 level, and in whites, with an increased rate of VTE. Conclusion: Galectin-3 levels were associated positively with VTE incidence.

Generalization and fine mapping of European ancestry-based central adiposity variants in African ancestry populations. - Yoneyama, S; Yao, J; Guo, X; Fernandez-Rhodes, L; Lim, U; Boston, J; Bůžková, P; Carlson, C S; Cheng, I; Cochran, B; Cooper, R; Ehret, G; et al. (Int J Obes (Lond), 2017)
BACKGROUND/OBJECTIVES: Central adiposity measures such as waist circumference (WC) and waist-to-hip ratio (WHR) are associated with cardiometabolic disorders independently of body mass index (BMI) and are gaining clinically utility. Several studies report genetic variants associated with central adiposity, but most utilize only European ancestry populations. Understanding whether the genetic associations discovered among mainly European descendants are shared with African ancestry populations will help elucidate the biological underpinnings of abdominal fat deposition. SUBJECTS/METHODS: To identify the underlying functional genetic determinants of body fat distribution, we conducted an array-wide association meta-analysis among persons of African ancestry across seven studies/consortia participating in the Population Architecture using Genomics and Epidemiology (PAGE) consortium. We used the Metabochip array, designed for fine-mapping cardiovascular-associated loci, to explore novel array-wide associations with WC and WHR among 15 945 African descendants using all and sex-stratified groups. We further interrogated 17 known WHR regions for African ancestry-specific variants. RESULTS: Of the 17 WHR loci, eight single-nucleotide polymorphisms (SNPs) located in four loci were replicated in the sex-combined or sex-stratified meta-analyses. Two of these eight independently associated with WHR after conditioning on the known variant in European descendants (rs12096179 in TBX15-WARS2 and rs2059092 in ADAMTS9). In the fine-mapping assessment, the putative functional region was reduced across all four loci but to varying degrees (average 40% drop in number of putative SNPs and 20% drop in genomic region). Similar to previous studies, the significant SNPs in the female-stratified analysis were stronger than the significant SNPs from the sex-combined analysis. No novel associations were detected in the array-wide analyses. CONCLUSIONS: Of 17 previously identified loci, four loci replicated in the African ancestry populations of this study. Utilizing different linkage disequilibrium patterns observed between European and African ancestries, we narrowed the suggestive region containing causative variants for all four loci.

Genetic Interactions with Age, Sex, Body Mass Index, and Hypertension in Relation to Atrial Fibrillation: The AFGen Consortium. - Weng, Lu-Chen; Lunetta, Kathryn L; Müller-Nurasyid, Martina; Smith, Albert Vernon; Thériault, Sébastien; Weeke, Peter E; Barnard, John; Bis, Joshua C; Lyytikäinen, Leo-Pekka; Kleber, Marcus E; Martinsson, Andreas; Lin, Henry J; et al. (Sci Rep, 2017)
It is unclear whether genetic markers interact with risk factors to influence atrial fibrillation (AF) risk. We performed genome-wide interaction analyses between genetic variants and age, sex, hypertension, and body mass index in the AFGen Consortium. Study-specific results were combined using meta-analysis (88,383 individuals of European descent, including 7,292 with AF). Variants with nominal interaction associations in the discovery analysis were tested for association in four independent studies (131,441 individuals, including 5,722 with AF). In the discovery analysis, the AF risk associated with the minor rs6817105 allele (at the PITX2 locus) was greater among subjects ≤ 65 years of age than among those > 65 years (interaction p-value = 4.0 × 10-5). The interaction p-value exceeded genome-wide significance in combined discovery and replication analyses (interaction p-value = 1.7 × 10-8). We observed one genome-wide significant interaction with body mass index and several suggestive interactions with age, sex, and body mass index in the discovery analysis. However, none was replicated in the independent sample. Our findings suggest that the pathogenesis of AF may differ according to age in individuals of European descent, but we did not observe evidence of statistically significant genetic interactions with sex, body mass index, or hypertension on AF risk.

Genetic loci associated with chronic obstructive pulmonary disease overlap with loci for lung function and pulmonary fibrosis. - Hobbs, Brian D; de Jong, Kim; Lamontagne, Maxime; Bossé, Yohan; Shrine, Nick; Artigas, Maria Soler; Wain, Louise V; Hall, Ian P; Jackson, Victoria E; Wyss, Annah B; London, Stephanie J; North, Kari E; et al. (Nat Genet, 2017)
Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality worldwide. We performed a genetic association study in 15,256 cases and 47,936 controls, with replication of select top results (P < 5 × 10(-6)) in 9,498 cases and 9,748 controls. In the combined meta-analysis, we identified 22 loci associated at genome-wide significance, including 13 new associations with COPD. Nine of these 13 loci have been associated with lung function in general population samples, while 4 (EEFSEC, DSP, MTCL1, and SFTPD) are new. We noted two loci shared with pulmonary fibrosis (FAM13A and DSP) but that had opposite risk alleles for COPD. None of our loci overlapped with genome-wide associations for asthma, although one locus has been implicated in joint susceptibility to asthma and obesity. We also identified genetic correlation between COPD and asthma. Our findings highlight new loci associated with COPD, demonstrate the importance of specific loci associated with lung function to COPD, and identify potential regions of genetic overlap between COPD and other respiratory diseases.

Genetic loci associated with heart rate variability and their effects on cardiac disease risk. - Nolte, Ilja M; Munoz, M Loretto; Tragante, Vinicius; Amare, Azmeraw T; Jansen, Rick; Vaez, Ahmad; von der Heyde, Benedikt; Avery, Christy L; Bis, Joshua C; Dierckx, Bram; van Dongen, Jenny; Gogarten, Stephanie M; et al. (Nat Commun, 2017)
Reduced cardiac vagal control reflected in low heart rate variability (HRV) is associated with greater risks for cardiac morbidity and mortality. In two-stage meta-analyses of genome-wide association studies for three HRV traits in up to 53,174 individuals of European ancestry, we detect 17 genome-wide significant SNPs in eight loci. HRV SNPs tag non-synonymous SNPs (in NDUFA11 and KIAA1755), expression quantitative trait loci (eQTLs) (influencing GNG11, RGS6 and NEO1), or are located in genes preferentially expressed in the sinoatrial node (GNG11, RGS6 and HCN4). Genetic risk scores account for 0.9 to 2.6% of the HRV variance. Significant genetic correlation is found for HRV with heart rate (-0.74<rg<-0.55) and blood pressure (-0.35<rg<-0.20). These findings provide clinically relevant biological insight into heritable variation in vagal heart rhythm regulation, with a key role for genetic variants (GNG11, RGS6) that influence G-protein heterotrimer action in GIRK-channel induced pacemaker membrane hyperpolarization.

{Genetic Risk Prediction of Atrial Fibrillation - Lubitz, S. A.; Yin, X.; Lin, H. J.; Kolek, M.; Smith, J. G.; Trompet, S.; Rienstra, M.; Rost, N. S.; Teixeira, P. L.; Almgren, P.; Anderson, C. D.; Chen, L. Y.; et al. (Circulation, 2017)
Atrial fibrillation (AF) has a substantial genetic basis. Identification of individuals at greatest AF risk could minimize the incidence of cardioembolic stroke.\ To determine whether genetic data can stratify risk for development of AF, we examined associations between AF genetic risk scores and incident AF in 5 prospective studies comprising 18 919 individuals of European ancestry. We examined associations between AF genetic risk scores and ischemic stroke in a separate study of 509 ischemic stroke cases (202 cardioembolic [40%]) and 3028 referents. Scores were based on 11 to 719 common variants (≥5%) associated with AF at P values ranging from <1×10-3 to <1×10-8 in a prior independent genetic association study.\ Incident AF occurred in 1032 individuals (5.5%). AF genetic risk scores were associated with new-onset AF after adjustment for clinical risk factors. The pooled hazard ratio for incident AF for the highest versus lowest quartile of genetic risk scores ranged from 1.28 (719 variants; 95% confidence interval, 1.13-1.46; P=1.5×10-4) to 1.67 (25 variants; 95% confidence interval, 1.47-1.90; P=9.3×10-15). Discrimination of combined clinical and genetic risk scores varied across studies and scores (maximum C statistic, 0.629-0.811; maximum ΔC statistic from clinical score alone, 0.009-0.017). AF genetic risk was associated with stroke in age- and sex-adjusted models. For example, individuals in the highest versus lowest quartile of a 127-variant score had a 2.49-fold increased odds of cardioembolic stroke (95% confidence interval, 1.39-4.58; P=2.7×10-3). The effect persisted after the exclusion of individuals (n=70) with known AF (odds ratio, 2.25; 95% confidence interval, 1.20-4.40; P=0.01).\ Comprehensive AF genetic risk scores were associated with incident AF beyond associations for clinical AF risk factors but offered small improvements in discrimination. AF genetic risk was also associated with cardioembolic stroke in age- and sex-adjusted analyses. Efforts are warranted to determine whether AF genetic risk may improve identification of subclinical AF or help distinguish between stroke mechanisms.

Genetically Determined Plasma Lipid Levels and Risk of Diabetic Retinopathy: A Mendelian Randomization Study. - Sobrin, Lucia; Chong, Yong He; Fan, Qiao; Gan, Alfred; Stanwyck, Lynn K; Kaidonis, Georgia; Craig, Jamie E; Kim, Jihye; Liao, Wen-Ling; Huang, Yu-Chuen; Lee, Wen-Jane; Hung, Yi-Jen; et al. (Diabetes, 2017)
Results from observational studies examining dyslipidemia as a risk factor for diabetic retinopathy (DR) have been inconsistent. We evaluated the causal relationship between plasma lipids and DR using a Mendelian randomization approach. We pooled genome-wide association studies summary statistics from 18 studies for two DR phenotypes: any DR (N = 2,969 case and 4,096 control subjects) and severe DR (N = 1,277 case and 3,980 control subjects). Previously identified lipid-associated single nucleotide polymorphisms served as instrumental variables. Meta-analysis to combine the Mendelian randomization estimates from different cohorts was conducted. There was no statistically significant change in odds ratios of having any DR or severe DR for any of the lipid fractions in the primary analysis that used single nucleotide polymorphisms that did not have a pleiotropic effect on another lipid fraction. Similarly, there was no significant association in the Caucasian and Chinese subgroup analyses. This study did not show evidence of a causal role of the four lipid fractions on DR. However, the study had limited power to detect odds ratios less than 1.23 per SD in genetically induced increase in plasma lipid levels, thus we cannot exclude that causal relationships with more modest effect sizes exist.
Keywords: Aged; Diabetic Retinopathy; Female; Genome-Wide Association Study; Humans; Lipids; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk

{Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk - Warren, H. R.; Evangelou, E.; Cabrera, C. P.; Gao, H.; Ren, M.; Mifsud, B.; Ntalla, I.; Surendran, P.; Liu, C.; Cook, J. P.; Kraja, A. T.; Drenos, F.; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.

Genome-wide association meta-analysis of fish and EPA+DHA consumption in 17 US and European cohorts. - Mozaffarian, Dariush; Dashti, Hassan S; Wojczynski, Mary K; Chu, Audrey Y; Nettleton, Jennifer A; Männistö, Satu; Kristiansson, Kati; Reedik, Mägi; Lahti, Jari; Houston, Denise K; Cornelis, Marilyn C; van Rooij, Frank J A; et al. (PLoS One, 2017)
BACKGROUND: Regular fish and omega-3 consumption may have several health benefits and are recommended by major dietary guidelines. Yet, their intakes remain remarkably variable both within and across populations, which could partly owe to genetic influences. OBJECTIVE: To identify common genetic variants that influence fish and dietary eicosapentaenoic acid plus docosahexaenoic acid (EPA+DHA) consumption. DESIGN: We conducted genome-wide association (GWA) meta-analysis of fish (n = 86,467) and EPA+DHA (n = 62,265) consumption in 17 cohorts of European descent from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium Nutrition Working Group. Results from cohort-specific GWA analyses (additive model) for fish and EPA+DHA consumption were adjusted for age, sex, energy intake, and population stratification, and meta-analyzed separately using fixed-effect meta-analysis with inverse variance weights (METAL software). Additionally, heritability was estimated in 2 cohorts. RESULTS: Heritability estimates for fish and EPA+DHA consumption ranged from 0.13-0.24 and 0.12-0.22, respectively. A significant GWA for fish intake was observed for rs9502823 on chromosome 6: each copy of the minor allele (FreqA = 0.015) was associated with 0.029 servings/day (~1 serving/month) lower fish consumption (P = 1.96x10-8). No significant association was observed for EPA+DHA, although rs7206790 in the obesity-associated FTO gene was among top hits (P = 8.18x10-7). Post-hoc calculations demonstrated 95% statistical power to detect a genetic variant associated with effect size of 0.05% for fish and 0.08% for EPA+DHA. CONCLUSIONS: These novel findings suggest that non-genetic personal and environmental factors are principal determinants of the remarkable variation in fish consumption, representing modifiable targets for increasing intakes among all individuals. Genes underlying the signal at rs72838923 and mechanisms for the association warrant further investigation.
Keywords: Adult; Aged; Cohort Studies; Docosahexaenoic Acids; Eicosapentaenoic Acid; Europe; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Seafood; United States

A genome-wide interaction analysis of tricyclic/tetracyclic antidepressants and RR and QT intervals: a pharmacogenomics study from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. - Noordam, Raymond; Sitlani, Colleen M; Avery, Christy L; Stewart, James D; Gogarten, Stephanie M; Wiggins, Kerri L; Trompet, Stella; Warren, Helen R; Sun, Fangui; Evans, Daniel S; Li, Xiaohui; Li, Jin; et al. (J Med Genet, 2017)
BACKGROUND: Increased heart rate and a prolonged QT interval are important risk factors for cardiovascular morbidity and mortality, and can be influenced by the use of various medications, including tricyclic/tetracyclic antidepressants (TCAs). We aim to identify genetic loci that modify the association between TCA use and RR and QT intervals. METHODS AND RESULTS: We conducted race/ethnic-specific genome-wide interaction analyses (with HapMap phase II imputed reference panel imputation) of TCAs and resting RR and QT intervals in cohorts of European (n=45 706; n=1417 TCA users), African (n=10 235; n=296 TCA users) and Hispanic/Latino (n=13 808; n=147 TCA users) ancestry, adjusted for clinical covariates. Among the populations of European ancestry, two genome-wide significant loci were identified for RR interval: rs6737205 in BRE (β=56.3, pinteraction=3.9e(-9)) and rs9830388 in UBE2E2 (β=25.2, pinteraction=1.7e(-8)). In Hispanic/Latino cohorts, rs2291477 in TGFBR3 significantly modified the association between TCAs and QT intervals (β=9.3, pinteraction=2.55e(-8)). In the meta-analyses of the other ethnicities, these loci either were excluded from the meta-analyses (as part of quality control), or their effects did not reach the level of nominal statistical significance (pinteraction>0.05). No new variants were identified in these ethnicities. No additional loci were identified after inverse-variance-weighted meta-analysis of the three ancestries. CONCLUSIONS: Among Europeans, TCA interactions with variants in BRE and UBE2E2 were identified in relation to RR intervals. Among Hispanic/Latinos, variants in TGFBR3 modified the relation between TCAs and QT intervals. Future studies are required to confirm our results.

Genome-Wide Interactions with Dairy Intake for Body Mass Index in Adults of European Descent. - Smith, Caren E; Follis, Jack L; Dashti, Hassan S; Tanaka, Toshiko; Graff, Mariaelisa; Fretts, Amanda M; Kilpeläinen, Tuomas O; Wojczynski, Mary K; Richardson, Kris; Nalls, Mike A; Schulz, Christina-Alexandra; Liu, Yongmei; et al. (Mol Nutr Food Res, 2017)
SCOPE: Body weight responds variably to the intake of dairy foods. Genetic variation may contribute to inter-individual variability in associations between body weight and dairy consumption. METHODS AND RESULTS: A genome-wide interaction study to discover genetic variants that account for variation in BMI in the context of low-fat, high-fat and total dairy intake in cross-sectional analysis was conducted. Data from nine discovery studies (up to 25 513 European descent individuals) were meta-analyzed. Twenty-six genetic variants reached the selected significance threshold (p-interaction <10-7) , and six independent variants (LINC01512-rs7751666, PALM2/AKAP2-rs914359, ACTA2-rs1388, PPP1R12A-rs7961195, LINC00333-rs9635058, AC098847.1-rs1791355) were evaluated meta-analytically for replication of interaction in up to 17 675 individuals. Variant rs9635058 (128 kb 3' of LINC00333) was replicated (p-interaction = 0.004). In the discovery cohorts, rs9635058 interacted with dairy (p-interaction = 7.36 × 10-8) such that each serving of low-fat dairy was associated with 0.225 kg m-2 lower BMI per each additional copy of the effect allele (A). A second genetic variant (ACTA2-rs1388) approached interaction replication significance for low-fat dairy exposure. CONCLUSION: Body weight responses to dairy intake may be modified by genotype, in that greater dairy intake may protect a genetic subgroup from higher body weight.

Genome-wide meta-analysis associates HLA-DQA1/DRB1 and LPA and lifestyle factors with human longevity. - Joshi, Peter K; Pirastu, Nicola; Kentistou, Katherine A; Fischer, Krista; Hofer, Edith; Schraut, Katharina E; Clark, David W; Nutile, Teresa; Barnes, Catriona L K; Timmers, Paul R H J; Shen, Xia; Gandin, Ilaria; et al. (Nat Commun, 2017)
Genomic analysis of longevity offers the potential to illuminate the biology of human aging. Here, using genome-wide association meta-analysis of 606,059 parents' survival, we discover two regions associated with longevity (HLA-DQA1/DRB1 and LPA). We also validate previous suggestions that APOE, CHRNA3/5, CDKN2A/B, SH2B3 and FOXO3A influence longevity. Next we show that giving up smoking, educational attainment, openness to new experience and high-density lipoprotein (HDL) cholesterol levels are most positively genetically correlated with lifespan while susceptibility to coronary artery disease (CAD), cigarettes smoked per day, lung cancer, insulin resistance and body fat are most negatively correlated. We suggest that the effect of education on lifespan is principally mediated through smoking while the effect of obesity appears to act via CAD. Using instrumental variables, we suggest that an increase of one body mass index unit reduces lifespan by 7 months while 1 year of education adds 11 months to expected lifespan.Variability in human longevity is genetically influenced. Using genetic data of parental lifespan, the authors identify associations at HLA-DQA/DRB1 and LPA and find that genetic variants that increase educational attainment have a positive effect on lifespan whereas increasing BMI negatively affects lifespan.

{Genome-wide meta-analysis of 241,258 adults accounting for smoking behaviour identifies novel loci for obesity traits - Justice, A. E.; Winkler, T. W.; Feitosa, M. F.; Graff, M.; Fisher, V. A.; Young, K.; Barata, L.; Deng, X.; Czajkowski, J.; Hadley, D.; Ngwa, J. S.; Ahluwalia, T. S.; et al. (Nat Commun, 2017)
Few genome-wide association studies (GWAS) account for environmental exposures, like smoking, potentially impacting the overall trait variance when investigating the genetic contribution to obesity-related traits. Here, we use GWAS data from 51,080 current smokers and 190,178 nonsmokers (87% European descent) to identify loci influencing BMI and central adiposity, measured as waist circumference and waist-to-hip ratio both adjusted for BMI. We identify 23 novel genetic loci, and 9 loci with convincing evidence of gene-smoking interaction (GxSMK) on obesity-related traits. We show consistent direction of effect for all identified loci and significance for 18 novel and for 5 interaction loci in an independent study sample. These loci highlight novel biological functions, including response to oxidative stress, addictive behaviour, and regulatory functions emphasizing the importance of accounting for environment in genetic analyses. Our results suggest that tobacco smoking may alter the genetic susceptibility to overall adiposity and body fat distribution.

Genome-wide Trans-ethnic Meta-analysis Identifies Seven Genetic Loci Influencing Erythrocyte Traits and a Role for RBPMS in Erythropoiesis. - van Rooij, Frank J A; Qayyum, Rehan; Smith, Albert V; Zhou, Yi; Trompet, Stella; Tanaka, Toshiko; Keller, Margaux F; Chang, Li-Ching; Schmidt, Helena; Yang, Min-Lee; Chen, Ming-Huei; Hayes, James; et al. (Am J Hum Genet, 2017)
Genome-wide association studies (GWASs) have identified loci for erythrocyte traits in primarily European ancestry populations. We conducted GWAS meta-analyses of six erythrocyte traits in 71,638 individuals from European, East Asian, and African ancestries using a Bayesian approach to account for heterogeneity in allelic effects and variation in the structure of linkage disequilibrium between ethnicities. We identified seven loci for erythrocyte traits including a locus (RBPMS/GTF2E2) associated with mean corpuscular hemoglobin and mean corpuscular volume. Statistical fine-mapping at this locus pointed to RBPMS at this locus and excluded nearby GTF2E2. Using zebrafish morpholino to evaluate loss of function, we observed a strong in vivo erythropoietic effect for RBPMS but not for GTF2E2, supporting the statistical fine-mapping at this locus and demonstrating that RBPMS is a regulator of erythropoiesis. Our findings show the utility of trans-ethnic GWASs for discovery and characterization of genetic loci influencing hematologic traits.

Higher plasma transforming growth factor (TGF)-β is associated with kidney disease in older community dwelling adults. - Mehta, Tapan; Bůzková, Petra; Kizer, Jorge R; Djoussé, Luc; Chonchol, Michel; Mukamal, Kenneth J; Shlipak, Michael; Ix, Joachim H; Jalal, Diana (BMC Nephrol, 2017)
BACKGROUND: TGF-β is induced in the vasculature with aging suggesting that high plasma TGF-β levels may be a risk factor for chronic kidney disease (CKD) in older adults. METHODS: We conducted a cross-sectional analysis of the association between plasma TGF-β levels and CKD including data for 1722 older adults who had participated in the 1996/97 visit of the Cardiovascular Health Study (CHS). Prevalent CKD was defined as eGFR < 60 mL/min/1.73 m(2) or urinary albumin/creatinine ratio (ACR) ≥30 mg/g. We also evaluated whether baseline TGF-β levels predicted change in eGFR, cardiovascular (CV) events, or mortality in longitudinal analysis. RESULTS: Plasma TGF-β levels were significantly and independently associated with lower eGFR in cross-sectional analysis. Doubling of TGF-β was significantly associated with lower eGFR (β estimate after adjusting for CV risk factors = -1.18, 95% CI -2.03, -0.32). We observed no association with albuminuria. There was no association between baseline TGF-β and change in eGFR, but each doubling of TGF-β at baseline was associated with increased risk of a composite outcome of CV events and mortality, adjusted HR 1.10 (95% C.I. 1.02- 1.20, p = 0.006). CONCLUSION: In this large cohort of community-dwelling older individuals, high plasma TGF-β levels are modestly, but independently associated with lower eGFR but not with albuminuria in cross-sectional analysis. In addition, TGF-β levels are associated with increased risk of CV events and mortality. Further research is needed to determine the direction of association between plasma TGF-β and the risk of CKD and CKD-associated morbidities in older adults.

Impact of common genetic determinants of Hemoglobin A1c on type 2 diabetes risk and diagnosis in ancestrally diverse populations: A transethnic genome-wide meta-analysis. - Wheeler, Eleanor; Leong, Aaron; Liu, Ching-Ti; Hivert, Marie-France; Strawbridge, Rona J; Podmore, Clara; Li, Man; Yao, Jie; Sim, Xueling; Hong, Jaeyoung; Chu, Audrey Y; Zhang, Weihua; et al. (PLoS Med, 2017)
BACKGROUND: Glycated hemoglobin (HbA1c) is used to diagnose type 2 diabetes (T2D) and assess glycemic control in patients with diabetes. Previous genome-wide association studies (GWAS) have identified 18 HbA1c-associated genetic variants. These variants proved to be classifiable by their likely biological action as erythrocytic (also associated with erythrocyte traits) or glycemic (associated with other glucose-related traits). In this study, we tested the hypotheses that, in a very large scale GWAS, we would identify more genetic variants associated with HbA1c and that HbA1c variants implicated in erythrocytic biology would affect the diagnostic accuracy of HbA1c. We therefore expanded the number of HbA1c-associated loci and tested the effect of genetic risk-scores comprised of erythrocytic or glycemic variants on incident diabetes prediction and on prevalent diabetes screening performance. Throughout this multiancestry study, we kept a focus on interancestry differences in HbA1c genetics performance that might influence race-ancestry differences in health outcomes. METHODS & FINDINGS: Using genome-wide association meta-analyses in up to 159,940 individuals from 82 cohorts of European, African, East Asian, and South Asian ancestry, we identified 60 common genetic variants associated with HbA1c. We classified variants as implicated in glycemic, erythrocytic, or unclassified biology and tested whether additive genetic scores of erythrocytic variants (GS-E) or glycemic variants (GS-G) were associated with higher T2D incidence in multiethnic longitudinal cohorts (N = 33,241). Nineteen glycemic and 22 erythrocytic variants were associated with HbA1c at genome-wide significance. GS-G was associated with higher T2D risk (incidence OR = 1.05, 95% CI 1.04-1.06, per HbA1c-raising allele, p = 3 × 10-29); whereas GS-E was not (OR = 1.00, 95% CI 0.99-1.01, p = 0.60). In Europeans and Asians, erythrocytic variants in aggregate had only modest effects on the diagnostic accuracy of HbA1c. Yet, in African Americans, the X-linked G6PD G202A variant (T-allele frequency 11%) was associated with an absolute decrease in HbA1c of 0.81%-units (95% CI 0.66-0.96) per allele in hemizygous men, and 0.68%-units (95% CI 0.38-0.97) in homozygous women. The G6PD variant may cause approximately 2% (N = 0.65 million, 95% CI 0.55-0.74) of African American adults with T2D to remain undiagnosed when screened with HbA1c. Limitations include the smaller sample sizes for non-European ancestries and the inability to classify approximately one-third of the variants. Further studies in large multiethnic cohorts with HbA1c, glycemic, and erythrocytic traits are required to better determine the biological action of the unclassified variants. CONCLUSIONS: As G6PD deficiency can be clinically silent until illness strikes, we recommend investigation of the possible benefits of screening for the G6PD genotype along with using HbA1c to diagnose T2D in populations of African ancestry or groups where G6PD deficiency is common. Screening with direct glucose measurements, or genetically-informed HbA1c diagnostic thresholds in people with G6PD deficiency, may be required to avoid missed or delayed diagnoses.
Keywords: Diabetes Mellitus, Type 2; Genetic Variation; Genome-Wide Association Study; Glycated Hemoglobin A; Humans; Phenotype; Risk

Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. - Zillikens, M Carola; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura M; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel L; Kutalik, Zoltán; Luan, Jian'an; et al. (Nat Commun, 2017)
Lean body mass, consisting mostly of skeletal muscle, is important for healthy aging. We performed a genome-wide association study for whole body (20 cohorts of European ancestry with n = 38,292) and appendicular (arms and legs) lean body mass (n = 28,330) measured using dual energy X-ray absorptiometry or bioelectrical impedance analysis, adjusted for sex, age, height, and fat mass. Twenty-one single-nucleotide polymorphisms were significantly associated with lean body mass either genome wide (p < 5 × 10-8) or suggestively genome wide (p < 2.3 × 10-6). Replication in 63,475 (47,227 of European ancestry) individuals from 33 cohorts for whole body lean body mass and in 45,090 (42,360 of European ancestry) subjects from 25 cohorts for appendicular lean body mass was successful for five single-nucleotide polymorphisms in/near HSD17B11, VCAN, ADAMTSL3, IRS1, and FTO for total lean body mass and for three single-nucleotide polymorphisms in/near VCAN, ADAMTSL3, and IRS1 for appendicular lean body mass. Our findings provide new insight into the genetics of lean body mass.Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.

Large-scale genome-wide analysis identifies genetic variants associated with cardiac structure and function. - Wild, Philipp S; Felix, Janine F; Schillert, Arne; Teumer, Alexander; Chen, Ming-Huei; Leening, Maarten J G; Völker, Uwe; Großmann, Vera; Brody, Jennifer A; Irvin, Marguerite R; Shah, Sanjiv J; Pramana, Setia; et al. (J Clin Invest, 2017)
BACKGROUND: Understanding the genetic architecture of cardiac structure and function may help to prevent and treat heart disease. This investigation sought to identify common genetic variations associated with inter-individual variability in cardiac structure and function. METHODS: A GWAS meta-analysis of echocardiographic traits was performed, including 46,533 individuals from 30 studies (EchoGen consortium). The analysis included 16 traits of left ventricular (LV) structure, and systolic and diastolic function. RESULTS: The discovery analysis included 21 cohorts for structural and systolic function traits (n = 32,212) and 17 cohorts for diastolic function traits (n = 21,852). Replication was performed in 5 cohorts (n = 14,321) and 6 cohorts (n = 16,308), respectively. Besides 5 previously reported loci, the combined meta-analysis identified 10 additional genome-wide significant SNPs: rs12541595 near MTSS1 and rs10774625 in ATXN2 for LV end-diastolic internal dimension; rs806322 near KCNRG, rs4765663 in CACNA1C, rs6702619 near PALMD, rs7127129 in TMEM16A, rs11207426 near FGGY, rs17608766 in GOSR2, and rs17696696 in CFDP1 for aortic root diameter; and rs12440869 in IQCH for Doppler transmitral A-wave peak velocity. Findings were in part validated in other cohorts and in GWAS of related disease traits. The genetic loci showed associations with putative signaling pathways, and with gene expression in whole blood, monocytes, and myocardial tissue. CONCLUSION: The additional genetic loci identified in this large meta-analysis of cardiac structure and function provide insights into the underlying genetic architecture of cardiac structure and warrant follow-up in future functional studies. FUNDING: For detailed information per study, see Acknowledgments.

Large-scale GWAS identifies multiple loci for hand grip strength providing biological insights into muscular fitness. - Willems, Sara M; Wright, Daniel J; Day, Felix R; Trajanoska, Katerina; Joshi, Peter K; Morris, John A; Matteini, Amy M; Garton, Fleur C; Grarup, Niels; Oskolkov, Nikolay; Thalamuthu, Anbupalam; Mangino, Massimo; et al. (Nat Commun, 2017)
Hand grip strength is a widely used proxy of muscular fitness, a marker of frailty, and predictor of a range of morbidities and all-cause mortality. To investigate the genetic determinants of variation in grip strength, we perform a large-scale genetic discovery analysis in a combined sample of 195,180 individuals and identify 16 loci associated with grip strength (P<5 × 10) in combined analyses. A number of these loci contain genes implicated in structure and function of skeletal muscle fibres (ACTG1), neuronal maintenance and signal transduction (PEX14, TGFA, SYT1), or monogenic syndromes with involvement of psychomotor impairment (PEX14, LRPPRC and KANSL1). Mendelian randomization analyses are consistent with a causal effect of higher genetically predicted grip strength on lower fracture risk. In conclusion, our findings provide new biological insight into the mechanistic underpinnings of grip strength and the causal role of muscular strength in age-related morbidities and mortality.

Leisure-time physical activity and leukocyte telomere length among older women. - Shadyab, Aladdin H; Lamonte, Michael J; Kooperberg, Charles; Reiner, Alexander P; Carty, Cara L; Manini, Todd M; Hou, Lifang; Di, Chongzhi; Macera, Caroline A; Gallo, Linda C; Shaffer, Richard A; Jain, Sonia; et al. (Exp Gerontol, 2017)
BACKGROUND: Shortened leukocyte telomere length (LTL), a purported marker of cellular aging, is associated with morbidity and mortality. However, the association of physical activity, a modifiable lifestyle behavior, with LTL has not been adequately studied among older adults. METHODS: In this cross-sectional study, we examined associations of various intensity levels of leisure-time physical activity with LTL among 1476 older white and African American women from the Women's Health Initiative Objective Physical Activity and Cardiovascular Health study. Self-reported physical activity was assessed by questionnaire, and LTL was measured by Southern blot. The association between physical activity and LTL was evaluated using multiple linear regression models adjusted for demographic characteristics, lifestyle behaviors, and health-related variables. RESULTS: Women were on average aged 79.2 (standard deviation 6.7) years old. In the final model adjusted for age, race/ethnicity, education, marital status, smoking, alcohol, body mass index, a history of chronic diseases, and hormone therapy use, LTL was on average 110 (95% confidence interval, 20-190) base pairs longer among women in the highest (≥17.00MET-hours/week) compared with the lowest (<1.25MET-hours/week) level of total leisure-time physical activity (P for trend=0.02). Higher levels of moderate-to-vigorous physical activity (P for trend=0.04) and faster walking speed (P for trend=0.03) were also associated with longer LTL in the fully-adjusted models. CONCLUSION: Older women participating in greater amounts of total leisure-time physical activity and moderate-to-vigorous physical activity had longer LTL.

Low-Frequency Synonymous Coding Variation in CYP2R1 Has Large Effects on Vitamin D Levels and Risk of Multiple Sclerosis. - Manousaki, Despoina; Dudding, Tom; Haworth, Simon; Hsu, Yi-Hsiang; Liu, Ching-Ti; Medina-Gómez, Carolina; Voortman, Trudy; van der Velde, Nathalie; Melhus, Håkan; Robinson-Cohen, Cassianne; Cousminer, Diana L; Nethander, Maria; et al. (Am J Hum Genet, 2017)
Vitamin D insufficiency is common, correctable, and influenced by genetic factors, and it has been associated with risk of several diseases. We sought to identify low-frequency genetic variants that strongly increase the risk of vitamin D insufficiency and tested their effect on risk of multiple sclerosis, a disease influenced by low vitamin D concentrations. We used whole-genome sequencing data from 2,619 individuals through the UK10K program and deep-imputation data from 39,655 individuals genotyped genome-wide. Meta-analysis of the summary statistics from 19 cohorts identified in CYP2R1 the low-frequency (minor allele frequency = 2.5%) synonymous coding variant g.14900931G>A (p.Asp120Asp) (rs117913124[A]), which conferred a large effect on 25-hydroxyvitamin D (25OHD) levels (-0.43 SD of standardized natural log-transformed 25OHD per A allele; p value = 1.5 × 10(-88)). The effect on 25OHD was four times larger and independent of the effect of a previously described common variant near CYP2R1. By analyzing 8,711 individuals, we showed that heterozygote carriers of this low-frequency variant have an increased risk of vitamin D insufficiency (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.78-2.78, p = 1.26 × 10(-12)). Individuals carrying one copy of this variant also had increased odds of multiple sclerosis (OR = 1.4, 95% CI = 1.19-1.64, p = 2.63 × 10(-5)) in a sample of 5,927 case and 5,599 control subjects. In conclusion, we describe a low-frequency CYP2R1 coding variant that exerts the largest effect upon 25OHD levels identified to date in the general European population and implicates vitamin D in the etiology of multiple sclerosis.
Keywords: Cholestanetriol 26-Monooxygenase; Cytochrome P450 Family 2; Gene Frequency; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Multiple Sclerosis; Polymorphism, Single Nucleotide; Risk Factors; Vitamin D; Vitamin D Deficiency

New Blood Pressure-Associated Loci Identified in Meta-Analyses of 475 000 Individuals. - Kraja, Aldi T; Cook, James P; Warren, Helen R; Surendran, Praveen; Liu, Chunyu; Evangelou, Evangelos; Manning, Alisa K; Grarup, Niels; Drenos, Fotios; Sim, Xueling; Smith, Albert Vernon; Amin, Najaf; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide association studies have recently identified >400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier studies identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of exome chip genotype data. An additional 100 variants yielded suggestive evidence of association. METHODS AND RESULTS: Here, we augment the sample with 140 886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs were available for association analysis with systolic BP or diastolic BP or pulse pressure. We performed 2 meta-analyses, one in individuals of European, South Asian, African, and Hispanic descent (pan-ancestry, ≈475 000), and the other in the subset of individuals of European descent (≈423 000). Twenty-one SNVs were genome-wide significant (P<5×10-8) for BP, of which 4 are new BP loci: rs9678851 (missense, SLC4A1AP), rs7437940 (AFAP1), rs13303 (missense, STAB1), and rs1055144 (7p15.2). In addition, we identified a potentially independent novel BP-associated SNV, rs3416322 (missense, SYNPO2L) at a known locus, uncorrelated with the previously reported SNVs. Two SNVs are associated with expression levels of nearby genes, and SNVs at 3 loci are associated with other traits. One SNV with a minor allele frequency <0.01, (rs3025380 at DBH) was genome-wide significant. CONCLUSIONS: We report 4 novel loci associated with BP regulation, and 1 independent variant at an established BP locus. This analysis highlights several candidate genes with variation that alter protein function or gene expression for potential follow-up.

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near HSPB7, TNXB, LRP12, LOC283335, SEPT9, and AKT2, and provide new replication evidence for a further 2 signals in EBF2 and NFKBIA Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

{Novel genetic loci associated with hippocampal volume - Hibar, D. P.; Adams, H. H. H.; Jahanshad, N.; Chauhan, G.; Stein, J. L.; Hofer, E.; Renteria, M. E.; Bis, J. C.; Arias-Vasquez, A.; Ikram, M. K.; Desrivi?res, S.; Vernooij, M. W.; et al. (Nat Commun, 2017)
The hippocampal formation is a brain structure integrally involved in episodic memory, spatial navigation, cognition and stress responsiveness. Structural abnormalities in hippocampal volume and shape are found in several common neuropsychiatric disorders. To identify the genetic underpinnings of hippocampal structure here we perform a genome-wide association study (GWAS) of 33,536 individuals and discover six independent loci significantly associated with hippocampal volume, four of them novel. Of the novel loci, three lie within genes (ASTN2, DPP4 and MAST4) and one is found 200 kb upstream of SHH. A hippocampal subfield analysis shows that a locus within the MSRB3 gene shows evidence of a localized effect along the dentate gyrus, subiculum, CA1 and fissure. Further, we show that genetic variants associated with decreased hippocampal volume are also associated with increased risk for Alzheimer's disease (rg=-0.155). Our findings suggest novel biological pathways through which human genetic variation influences hippocampal volume and risk for neuropsychiatric illness.

PCSK9 Loss-of-Function Variants, Low-Density Lipoprotein Cholesterol, and Risk of Coronary Heart Disease and Stroke: Data From 9 Studies of Blacks and Whites. - Kent, Shia T; Rosenson, Robert S; Avery, Christy L; Chen, Yii-der I; Correa, Adolfo; Cummings, Steven R; Cupples, L Adrienne; Cushman, Mary; Evans, Daniel S; Gudnason, Vilmundur; Harris, Tamara B; Howard, George; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: PCSK9 loss-of-function (LOF) variants allow for the examination of the effects of lifetime reduced low-density lipoprotein cholesterol (LDL-C) on cardiovascular events. We examined the association of PCSK9 LOF variants with LDL-C and incident coronary heart disease and stroke through a meta-analysis of data from 8 observational cohorts and 1 randomized trial of statin therapy. METHODS AND RESULTS: These 9 studies together included 17 459 blacks with 403 (2.3%) having at least 1 Y142X or C679X variant and 31 306 whites with 955 (3.1%) having at least 1 R46L variant. Unadjusted odds ratios for associations between PCSK9 LOF variants and incident coronary heart disease (851 events in blacks and 2662 events in whites) and stroke (523 events in blacks and 1660 events in whites) were calculated using pooled Mantel-Haenszel estimates with continuity correction factors. Pooling results across studies using fixed-effects inverse-variance-weighted models, PCSK9 LOF variants were associated with 35 mg/dL (95% confidence interval [CI], 32-39) lower LDL-C in blacks and 13 mg/dL (95% CI, 11-16) lower LDL-C in whites. PCSK9 LOF variants were associated with a pooled odds ratio for coronary heart disease of 0.51 (95% CI, 0.28-0.92) in blacks and 0.82 (95% CI, 0.63-1.06) in whites. PCSK9 LOF variants were not associated with incident stroke (odds ratio, 0.84; 95% CI, 0.48-1.47 in blacks and odds ratio, 1.06; 95% CI, 0.80-1.41 in whites). CONCLUSIONS: PCSK9 LOF variants were associated with lower LDL-C and coronary heart disease incidence. PCSK9 LOF variants were not associated with stroke risk.

Pharmacogenomics study of thiazide diuretics and QT interval in multi-ethnic populations: the cohorts for heart and aging research in genomic epidemiology. - Seyerle, A A; Sitlani, C M; Noordam, R; Gogarten, S M; Li, J; Li, X; Evans, D S; Sun, F; Laaksonen, M A; Isaacs, A; Kristiansson, K; Highland, H M; et al. (Pharmacogenomics J, 2017)
Thiazide diuretics, commonly used antihypertensives, may cause QT interval (QT) prolongation, a risk factor for highly fatal and difficult to predict ventricular arrhythmias. We examined whether common single-nucleotide polymorphisms (SNPs) modified the association between thiazide use and QT or its component parts (QRS interval, JT interval) by performing ancestry-specific, trans-ethnic and cross-phenotype genome-wide analyses of European (66%), African American (15%) and Hispanic (19%) populations (N=78 199), leveraging longitudinal data, incorporating corrected standard errors to account for underestimation of interaction estimate variances and evaluating evidence for pathway enrichment. Although no loci achieved genome-wide significance (P<5 × 10(-8)), we found suggestive evidence (P<5 × 10(-6)) for SNPs modifying the thiazide-QT association at 22 loci, including ion transport loci (for example, NELL1, KCNQ3). The biologic plausibility of our suggestive results and simulations demonstrating modest power to detect interaction effects at genome-wide significant levels indicate that larger studies and innovative statistical methods are warranted in future efforts evaluating thiazide-SNP interactions.The Pharmacogenomics Journal advance online publication, 18 July 2017; doi:10.1038/tpj.2017.10.

Predictors and outcomes of heart failure with mid-range ejection fraction. - Bhambhani, Vijeta; Kizer, Jorge R; Lima, João A C; van der Harst, Pim; Bahrami, Hossein; Nayor, Matthew; de Filippi, Christopher R; Enserro, Danielle; Blaha, Michael J; Cushman, Mary; Wang, Thomas J; Gansevoort, Ron T; et al. (Eur J Heart Fail, 2017)
AIMS: While heart failure with preserved (HFpEF) and reduced ejection fraction (HFrEF) are well described, determinants and outcomes of heart failure with mid-range ejection fraction (HFmrEF) remain unclear. We sought to examine clinical and biochemical predictors of incident HFmrEF in the community. METHODS AND RESULTS: We pooled data from four community-based longitudinal cohorts, with ascertainment of new heart failure (HF) classified into HFmrEF [ejection fraction (EF) 41-49%], HFpEF (EF ≥50%), and HFrEF (EF ≤40%). Predictors of incident HF subtypes were assessed using multivariable Cox models. Among 28 820 participants free of HF followed for a median of 12 years, there were 200 new HFmrEF cases, compared with 811 HFpEF and 1048 HFrEF. Clinical predictors of HFmrEF included age, male sex, systolic blood pressure, diabetes mellitus, and prior myocardial infarction (multivariable adjusted P ≤ 0.003 for all). Biomarkers that predicted HFmrEF included natriuretic peptides, cystatin-C, and high-sensitivity troponin (P ≤ 0.0004 for all). Natriuretic peptides were stronger predictors of HFrEF [hazard ratio (HR) 2.00 per 1 standard deviation increase, 95% confidence interval (CI) 1.81-2.20] than of HFmrEF (HR 1.51, 95% CI 1.20-1.90, P = 0.01 for difference), and did not differ in their association with incident HFmrEF and HFpEF (HR 1.56, 95% CI 1.41-1.73, P = 0.68 for difference). All-cause mortality following the onset of HFmrEF was worse than that of HFpEF (50 vs. 39 events per 1000 person-years, P = 0.02), but comparable to that of HFrEF (46 events per 1000 person-years, P = 0.78). CONCLUSIONS: We found overlap in predictors of incident HFmrEF with other HF subtypes. In contrast, mortality risk after HFmrEF was worse than HFpEF, and similar to HFrEF.

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10-4) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10-8) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10-10, odds ratio (OR) = 0.68, minor allele frequency (MAF)cases = 0.0059, MAFcontrols = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10-10, OR = 1.43, MAFcases = 0.011, MAFcontrols = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10-14, OR = 1.67, MAFcases = 0.0143, MAFcontrols = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

Rare coding variants pinpoint genes that control human hematological traits. - Mousas, Abdou; Ntritsos, Georgios; Chen, Ming-Huei; Song, Ci; Huffman, Jennifer E; Tzoulaki, Ioanna; Elliott, Paul; Psaty, Bruce M; Auer, Paul L; Johnson, Andrew D; Evangelou, Evangelos; Lettre, Guillaume; et al. (PLoS Genet, 2017)
The identification of rare coding or splice site variants remains the most straightforward strategy to link genes with human phenotypes. Here, we analyzed the association between 137,086 rare (minor allele frequency (MAF) <1%) coding or splice site variants and 15 hematological traits in up to 308,572 participants. We found 56 such rare coding or splice site variants at P<5x10-8, including 31 that are associated with a blood-cell phenotype for the first time. All but one of these 31 new independent variants map to loci previously implicated in hematopoiesis by genome-wide association studies (GWAS). This includes a rare splice acceptor variant (rs146597587, MAF = 0.5%) in interleukin 33 (IL33) associated with reduced eosinophil count (P = 2.4x10-23), and lower risk of asthma (P = 2.6x10-7, odds ratio [95% confidence interval] = 0.56 [0.45-0.70]) and allergic rhinitis (P = 4.2x10-4, odds ratio = 0.55 [0.39-0.76]). The single new locus identified in our study is defined by a rare p.Arg172Gly missense variant (rs145535174, MAF = 0.05%) in plasminogen (PLG) associated with increased platelet count (P = 6.8x10-9), and decreased D-dimer concentration (P = 0.018) and platelet reactivity (P<0.03). Finally, our results indicate that searching for rare coding or splice site variants in very large sample sizes can help prioritize causal genes at many GWAS loci associated with complex human diseases and traits.
Keywords: Asthma; Databases, Genetic; Endometriosis; Female; Fibrin Fibrinogen Degradation Products; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Interleukin-33; Linear Models; Logistic Models; Male; Mutation, Missense; Phenotype; Plasminogen; Platelet Count; Polymorphism, Single Nucleotide; Principal Component Analysis; Protein Splicing; Rhinitis, Allergic; Sequence Analysis, DNA

REPEATED MEASUREMENTS OF BLOOD PRESSURE AND CHOLESTEROL IMPROVES CARDIOVASCULAR DISEASE RISK PREDICTION: AN INDIVIDUAL-PARTICIPANT-DATA META-ANALYSIS. - Paige, Ellie; Barrett, Jessica; Pennells, Lisa; Sweeting, Michael; Willeit, Peter; Di Angelantonio, Emanuele; Gudnason, Vilmundur; Nordestgaard, Børge G; Psaty, Bruce M; Goldbourt, Uri; Best, Lyle G; Assmann, Gerd; et al. (Am J Epidemiol, 2017)
The added value of incorporating information from repeated measurements of blood pressure and cholesterol for cardiovascular disease (CVD) risk prediction has not been rigorously assessed. We used data from the Emerging Risk Factors Collaboration on 191,445 adults (38 cohorts from across 17 countries with data from 1962-2014) with > 1 million measurements of systolic blood pressure, total cholesterol and high-density lipoprotein cholesterol; over a median 12 years of follow-up, 21,170 CVD events occurred. Risk prediction models using cumulative means of repeated measurements and summary measures from longitudinal modelling of the repeated measurements were compared to models using measurements from a single time point. Risk discrimination (C-index) and net reclassification were calculated, and changes in C-indices were meta-analysed across studies. Compared to the single time point model, the cumulative means and the longitudinal models increased the C-index by 0.0040 (95% CI: 0.0023, 0.0057) and 0.0023 (0.0005, 0.0042), respectively. Reclassification was also improved in both models; compared to the single time point model, overall net reclassification improvements were 0.0369 (0.0303, 0.0436) for the cumulative means model and 0.0177 (0.0110, 0.0243) for the longitudinal model. In conclusion, incorporating repeated measurements of blood pressure and cholesterol into CVD risk prediction models slightly improves risk prediction.

Single-trait and multi-trait genome-wide association analyses identify novel loci for blood pressure in African-ancestry populations. - Liang, Jingjing; Le, Thu H; Edwards, Digna R Velez; Tayo, Bamidele O; Gaulton, Kyle J; Smith, Jennifer A; Lu, Yingchang; Jensen, Richard A; Chen, Guanjie; Yanek, Lisa R; Schwander, Karen; Tajuddin, Salman M; et al. (PLoS Genet, 2017)
Hypertension is a leading cause of global disease, mortality, and disability. While individuals of African descent suffer a disproportionate burden of hypertension and its complications, they have been underrepresented in genetic studies. To identify novel susceptibility loci for blood pressure and hypertension in people of African ancestry, we performed both single and multiple-trait genome-wide association analyses. We analyzed 21 genome-wide association studies comprised of 31,968 individuals of African ancestry, and validated our results with additional 54,395 individuals from multi-ethnic studies. These analyses identified nine loci with eleven independent variants which reached genome-wide significance (P < 1.25×10-8) for either systolic and diastolic blood pressure, hypertension, or for combined traits. Single-trait analyses identified two loci (TARID/TCF21 and LLPH/TMBIM4) and multiple-trait analyses identified one novel locus (FRMD3) for blood pressure. At these three loci, as well as at GRP20/CDH17, associated variants had alleles common only in African-ancestry populations. Functional annotation showed enrichment for genes expressed in immune and kidney cells, as well as in heart and vascular cells/tissues. Experiments driven by these findings and using angiotensin-II induced hypertension in mice showed altered kidney mRNA expression of six genes, suggesting their potential role in hypertension. Our study provides new evidence for genes related to hypertension susceptibility, and the need to study African-ancestry populations in order to identify biologic factors contributing to hypertension.
Keywords: African Americans; Animals; Basic Helix-Loop-Helix Transcription Factors; Blood Pressure; Cadherins; Case-Control Studies; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Mice; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Soluble Inflammatory Markers and Risk of Incident Fractures in Older Adults: The Cardiovascular Health Study. - Stojanović, Danijela; Bůzková, Petra; Mukamal, Kenneth J; Heckbert, Susan R; Psaty, Bruce M; Fink, Howard A; Cauley, Jane A; Wallace, Erin; Curtis, Lesley H; Hirsch, Calvin; Budoff, Matthew; Li, Dong; et al. (J Bone Miner Res, 2017)
Several in vitro and animal studies have showed that inflammatory markers play a role in bone remodeling and pathogenesis of osteoporosis. Additionally, some human longitudinal studies showed suggestive associations between elevated inflammatory markers and increased risk of nontraumatic fractures. We examined several inflammatory markers and multiple fracture types in a single study of older individuals with extensive follow-up. We assessed the association of four inflammatory markers with the risk of incident hip fractures among 5265 participants of the Cardiovascular Health Study (CHS) and a composite endpoint of incident fractures of the hip, pelvis, humerus, or proximal forearm in 4477 participants. Among CHS participants followed between 1992 and 2009, we observed 480 incident hip fractures during a median follow-up of 11 years. In the composite fracture analysis cohort of 4477 participants, we observed 711 fractures during a median follow-up of 7 years. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for hip fracture associated with doubling of IL-6 were HR 1.15 (95% CI, 1.02 to 1.30) overall and HR 1.17 (95% CI, 1.01 to 1.35) in women. We also observed a positive association between each unit increase in white blood cell (WBC) count and risk of hip fracture: HR 1.04 (95% CI, 1.01 to 1.06) overall and HR 1.06 (95% CI, 0.95 to 1.20) in women. We observed no significant associations between any of the four inflammatory markers and a composite fracture endpoint. Our findings suggest that chronic inflammatory and immune processes may be related to higher rates of incident hip fractures. © 2017 American Society for Bone and Mineral Research.

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci. - Fernandez-Rhodes, Lindsay; Gong, Jian; Haessler, Jeffrey; Franceschini, Nora; Graff, Mariaelisa; Nishimura, Katherine K; Wang, Yujie; Highland, Heather M; Yoneyama, Sachiko; Bush, William S; Goodloe, Robert; Ritchie, Marylyn D; et al. (Hum Genet, 2017)
Most body mass index (BMI) genetic loci have been identified in studies of primarily European ancestries. The effect of these loci in other racial/ethnic groups is less clear. Thus, we aimed to characterize the generalizability of 170 established BMI variants, or their proxies, to diverse US populations and trans-ethnically fine-map 36 BMI loci using a sample of >102,000 adults of African, Hispanic/Latino, Asian, European and American Indian/Alaskan Native descent from the Population Architecture using Genomics and Epidemiology Study. We performed linear regression of the natural log of BMI (18.5-70 kg/m(2)) on the additive single nucleotide polymorphisms (SNPs) at BMI loci on the MetaboChip (Illumina, Inc.), adjusting for age, sex, population stratification, study site, or relatedness. We then performed fixed-effect meta-analyses and a Bayesian trans-ethnic meta-analysis to empirically cluster by allele frequency differences. Finally, we approximated conditional and joint associations to test for the presence of secondary signals. We noted directional consistency with the previously reported risk alleles beyond what would have been expected by chance (binomial p < 0.05). Nearly, a quarter of the previously described BMI index SNPs and 29 of 36 densely-genotyped BMI loci on the MetaboChip replicated/generalized in trans-ethnic analyses. We observed multiple signals at nine loci, including the description of seven loci with novel multiple signals. This study supports the generalization of most common genetic loci to diverse ancestral populations and emphasizes the importance of dense multiethnic genomic data in refining the functional variation at genetic loci of interest and describing several loci with multiple underlying genetic variants.
Keywords: Body Mass Index; Ethnic Groups; Genetics, Population; Humans; Obesity

Association of biomarker and physiologic indices with mortality in older adults: Cardiovascular Health Study. - Sanders, Jason L; Arnold, Alice M; Boudreau, Robert M; Hirsch, Calvin H; Kizer, Jorge R; Kaplan, Robert C; Cappola, Anne R; Cushman, Mary; Jacob, Mini E; Kritchevsky, Stephen B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2018)
Background: A goal of gerontology is discovering aging phenotypes that reflect biological aging distinct from disease pathogenesis. Biomarkers strongly and independently associated with mortality and which statistically attenuate chronologic age could be used to define such a phenotype. We determined the association of a Biomarker Index (BI) with mortality and compared it to a validated Physiologic Index (PI) in older adults. Methods: The indices were constructed in the Cardiovascular Health Study, mean (SD) age 74.5 (5.1) years. The BI incorporated circulating levels of new biomarkers, including insulin-like growth factor (IGF)-1, IGF binding protein 3, amino-terminal pro-B-type natriuretic peptide, dehydroepiandrosterone sulfate, and interleukin-6, and was built in test (N=2197) and validation (N=1124) samples. The PI included carotid intima-media thickness, pulmonary capacity, brain white matter grade, cystatin-C, and fasting glucose. Multivariable Cox proportional hazards models predicting death were calculated with 10 years of follow-up. Results: In separate age-adjusted models, the hazard ratio (HR) for mortality per point of the BI was 1.30 (95% CI 1.25, 1.34) and the BI attenuated age by 25%. The HR for the PI was 1.28 (1.24, 1.33) (29% age attenuation). In the same model, the HR for the BI was 1.23 (1.18, 1.28) and for the PI was 1.22 (1.17, 1.26), and age was attenuated 42.5%. Associations persisted after further adjustment. Conclusions: The BI and PI were significantly and independently associated with mortality. Both attenuated the age effect on mortality substantially. The indices may be feasible phenotypes for developing interventions hoping to alter the trajectory of aging.

Association of Cardiovascular Biomarkers With Incident Heart Failure With Preserved and Reduced Ejection Fraction. - de Boer, Rudolf A; Nayor, Matthew; deFilippi, Christopher R; Enserro, Danielle; Bhambhani, Vijeta; Kizer, Jorge R; Blaha, Michael J; Brouwers, Frank P; Cushman, Mary; Lima, João A C; Bahrami, Hossein; van der Harst, Pim; et al. (JAMA Cardiol, 2018)
Importance: Nearly half of all patients with heart failure have preserved ejection fraction (HFpEF) as opposed to reduced ejection fraction (HFrEF), yet associations of biomarkers with future heart failure subtype are incompletely understood. Objective: To evaluate the associations of 12 cardiovascular biomarkers with incident HFpEF vs HFrEF among adults from the general population. Design, Setting, and Participants: This study included 4 longitudinal community-based cohorts: the Cardiovascular Health Study (1989-1990; 1992-1993 for supplemental African-American cohort), the Framingham Heart Study (1995-1998), the Multi-Ethnic Study of Atherosclerosis (2000-2002), and the Prevention of Renal and Vascular End-stage Disease study (1997-1998). Each cohort had prospective ascertainment of incident HFpEF and HFrEF. Data analysis was performed from June 25, 2015, to November 9, 2017. Exposures: The following biomarkers were examined: N-terminal pro B-type natriuretic peptide or brain natriuretic peptide, high-sensitivity troponin T or I, C-reactive protein (CRP), urinary albumin to creatinine ratio (UACR), renin to aldosterone ratio, D-dimer, fibrinogen, soluble suppressor of tumorigenicity, galectin-3, cystatin C, plasminogen activator inhibitor 1, and interleukin 6. Main Outcomes and Measures: Development of incident HFpEF and incident HFrEF. Results: Among the 22 756 participants in these 4 cohorts (12 087 women and 10 669 men; mean [SD] age, 60 [13] years) in the study, during a median follow-up of 12 years, 633 participants developed incident HFpEF, and 841 developed HFrEF. In models adjusted for clinical risk factors of heart failure, 2 biomarkers were significantly associated with incident HFpEF: UACR (hazard ratio [HR], 1.33; 95% CI, 1.20-1.48; P < .001) and natriuretic peptides (HR, 1.27; 95% CI, 1.16-1.40; P < .001), with suggestive associations for high-sensitivity troponin (HR, 1.11; 95% CI, 1.03-1.19; P = .008), plasminogen activator inhibitor 1 (HR, 1.22; 95% CI, 1.03-1.45; P = .02), and fibrinogen (HR, 1.12; 95% CI, 1.03-1.22; P = .01). By contrast, 6 biomarkers were associated with incident HFrEF: natriuretic peptides (HR, 1.54; 95% CI, 1.41-1.68; P < .001), UACR (HR, 1.21; 95% CI, 1.11-1.32; P < .001), high-sensitivity troponin (HR, 1.37; 95% CI, 1.29-1.46; P < .001), cystatin C (HR, 1.19; 95% CI, 1.11-1.27; P < .001), D-dimer (HR, 1.22; 95% CI, 1.11-1.35; P < .001), and CRP (HR, 1.19; 95% CI, 1.11-1.28; P < .001). When directly compared, natriuretic peptides, high-sensitivity troponin, and CRP were more strongly associated with HFrEF compared with HFpEF. Conclusions and Relevance: Biomarkers of renal dysfunction, endothelial dysfunction, and inflammation were associated with incident HFrEF. By contrast, only natriuretic peptides and UACR were associated with HFpEF. These findings highlight the need for future studies focused on identifying novel biomarkers of the risk of HFpEF.

Association of lipoprotein-associated phospholipase A and risk of incident atrial fibrillation: Findings from 3 cohorts. - Garg, Parveen K; Bartz, Traci M; Norby, Faye L; Jorgensen, Neal W; McClelland, Robyn L; Ballantyne, Christie M; Chen, Lin Y; Gottdiener, John S; Greenland, Philip; Hoogeveen, Ron; Jenny, Nancy S; Kizer, Jorge R; et al. (Am Heart J, 2018)
BACKGROUND: Multiple prospective studies have established an association between inflammation and higher risk of atrial fibrillation (AF), but the association between lipoprotein-associated phospholipase A (Lp-PLA) mass and activity and incident AF has not been extensively evaluated. METHODS: Using data from 10,794 Atherosclerosis Risk In Communities (ARIC) study participants aged 53-75 years, 5,181 Cardiovascular Health Study (CHS) participants aged 65 to 100 years, and 5,425 Multi-Ethnic Study of Atherosclerosis (MESA) participants aged 45-84 years, we investigated the association between baseline Lp-PLA levels and the risk of developing AF. Incident AF was identified in each cohort by follow-up visit electrocardiograms, hospital discharge coding of AF, or Medicare claims data. RESULTS: Over a mean of 13.1, 11.5, and 10.0 years of follow-up, 1,439 (13%), 2,084 (40%), and 615 (11%) incident AF events occurred in ARIC, CHS, and MESA, respectively. In adjusted analyses, each SD increment in Lp-PLA activity was associated with incident AF in both ARIC (hazard ratio [HR] 1.13, 95% CI 1.06-1.20) and MESA (HR 1.24, 95% CI 1.05-1.46). Each SD increment in Lp-PLA mass was also associated with incident AF in MESA (HR 1.25, 95% CI 1.11-1.41). No significant associations were observed among CHS participants. CONCLUSIONS: Although higher Lp-PLA mass and activity were associated with development of AF in ARIC and MESA, this relationship was not observed in CHS, a cohort of older individuals.

The Association of Obesity and Cardiometabolic Traits With Incident HFpEF and HFrEF. - Savji, Nazir; Meijers, Wouter C; Bartz, Traci M; Bhambhani, Vijeta; Cushman, Mary; Nayor, Matthew; Kizer, Jorge R; Sarma, Amy; Blaha, Michael J; Gansevoort, Ron T; Gardin, Julius M; Hillege, Hans L; et al. (JACC Heart Fail, 2018)
OBJECTIVES: This study evaluated the associations of obesity and cardiometabolic traits with incident heart failure with preserved versus reduced ejection fraction (HFpEF vs. HFrEF). Given known sex differences in HF subtype, we examined men and women separately. BACKGROUND: Recent studies suggest that obesity confers greater risk of HFpEF versus HFrEF. Contributions of associated metabolic traits to HFpEF are less clear. METHODS: We studied 22,681 participants from 4 community-based cohorts followed for incident HFpEF versus HFrEF (ejection fraction ≥50% vs. <50%). We evaluated the association of body mass index (BMI) and cardiometabolic traits with incident HF subtype using Cox models. RESULTS: The mean age was 60 ± 13 years, and 53% were women. Over a median follow-up of 12 years, 628 developed incident HFpEF and 835 HFrEF. Greater BMI portended higher risk of HFpEF compared with HFrEF (hazard ratio [HR]: 1.34 per 1-SD increase in BMI; 95% confidence interval [CI]: 1.24 to 1.45 vs. HR: 1.18; 95% CI: 1.10 to 1.27). Similarly, insulin resistance (homeostatic model assessment of insulin resistance) was associated with HFpEF (HR: 1.20 per 1-SD; 95% CI: 1.05 to 1.37), but not HFrEF (HR: 0.99; 95% CI: 0.88 to 1.11; p < 0.05 for difference HFpEF vs. HFrEF). We found that the differential association of BMI with HFpEF versus HFrEF was more pronounced among women (p for difference HFpEF vs. HFrEF = 0.01) when compared with men (p = 0.34). CONCLUSIONS: Obesity and related cardiometabolic traits including insulin resistance are more strongly associated with risk of future HFpEF versus HFrEF. The differential risk of HFpEF with obesity seems particularly pronounced among women and may underlie sex differences in HF subtypes.

Common and Rare Coding Genetic Variation Underlying the Electrocardiographic PR Interval. - Lin, Honghuang; van Setten, Jessica; Smith, Albert V; Bihlmeyer, Nathan A; Warren, Helen R; Brody, Jennifer A; Radmanesh, Farid; Hall, Leanne; Grarup, Niels; Müller-Nurasyid, Martina; Boutin, Thibaud; Verweij, Niek; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Electrical conduction from the cardiac sinoatrial node to the ventricles is critical for normal heart function. Genome-wide association studies have identified more than a dozen common genetic loci that are associated with PR interval. However, it is unclear whether rare and low-frequency variants also contribute to PR interval heritability. METHODS: We performed large-scale meta-analyses of the PR interval that included 83 367 participants of European ancestry and 9436 of African ancestry. We examined both common and rare variants associated with the PR interval. RESULTS: We identified 31 genetic loci that were significantly associated with PR interval after Bonferroni correction (<1.2×10), including 11 novel loci that have not been reported previously. Many of these loci are involved in heart morphogenesis. In gene-based analysis, we found that multiple rare variants at (=5.9×10) and (=1.1×10) were associated with PR interval. locus also was implicated in the common variant analysis, whereas was a novel locus. CONCLUSIONS: We identified common variants at 11 novel loci and rare variants within 2 gene regions that were significantly associated with PR interval. Our findings provide novel insights to the current understanding of atrioventricular conduction, which is critical for cardiac activity and an important determinant of health.

Common Coding Variants in Are Associated With the Nav1.8 Late Current and Cardiac Conduction. - Macri, Vincenzo; Brody, Jennifer A; Arking, Dan E; Hucker, William J; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W; Sinner, Moritz F; Lubitz, Steven A; Liu, Ching-Ti; Morrison, Alanna C; Alonso, Alvaro; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Genetic variants at the / locus are strongly associated with electrocardiographic PR and QRS intervals. While is the canonical cardiac sodium channel gene, the role of in cardiac conduction is less well characterized. METHODS: We sequenced the locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21,000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. RESULTS: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium (  =0.86) with each other to be the strongest signals for PR (rs10428132, β=-4.74, =1.52×10) and QRS intervals (rs6599251, QRS β=-0.73; =1.2×10), respectively. Although these variants were not associated with or expression in human atrial tissue (n=490), they were in high linkage disequilibrium (  ≥0.72) with a common missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, =0.03, and I962V+V1073A, 22.4±0.8%, =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, =0.03). CONCLUSIONS: Our findings suggest an association between genetic variation in , the late sodium current, and alterations in cardiac conduction.

A comprehensive evaluation of the genetic architecture of sudden cardiac arrest. - Ashar, Foram N; Mitchell, Rebecca N; Albert, Christine M; Newton-Cheh, Christopher; Brody, Jennifer A; Müller-Nurasyid, Martina; Moes, Anna; Meitinger, Thomas; Mak, Angel; Huikuri, Heikki; Junttila, M Juhani; Goyette, Philippe; et al. (Eur Heart J, 2018)
Aims: Sudden cardiac arrest (SCA) accounts for 10% of adult mortality in Western populations. We aim to identify potential loci associated with SCA and to identify risk factors causally associated with SCA. Methods and results: We carried out a large genome-wide association study (GWAS) for SCA (n = 3939 cases, 25 989 non-cases) to examine common variation genome-wide and in candidate arrhythmia genes. We also exploited Mendelian randomization (MR) methods using cross-trait multi-variant genetic risk score associations (GRSA) to assess causal relationships of 18 risk factors with SCA. No variants were associated with SCA at genome-wide significance, nor were common variants in candidate arrhythmia genes associated with SCA at nominal significance. Using cross-trait GRSA, we established genetic correlation between SCA and (i) coronary artery disease (CAD) and traditional CAD risk factors (blood pressure, lipids, and diabetes), (ii) height and BMI, and (iii) electrical instability traits (QT and atrial fibrillation), suggesting aetiologic roles for these traits in SCA risk. Conclusions: Our findings show that a comprehensive approach to the genetic architecture of SCA can shed light on the determinants of a complex life-threatening condition with multiple influencing factors in the general population. The results of this genetic analysis, both positive and negative findings, have implications for evaluating the genetic architecture of patients with a family history of SCA, and for efforts to prevent SCA in high-risk populations and the general community.

{Dairy Consumption and Body Mass Index Among Adults: Mendelian Randomization Analysis of 184802 Individuals from 25 Studies - Huang, T.; Ding, M.; Bergholdt, H. K. M.; Wang, T.; Heianza, Y.; Sun, D.; Frazier-Wood, A. C.; Aslibekyan, S.; North, K. E.; Voortman, T.; Graff, M.; Smith, C. E.; et al. (Clin Chem, 2018)
Associations between dairy intake and body mass index (BMI) have been inconsistently observed in epidemiological studies, and the causal relationship remains ill defined.\ We performed Mendelian randomization (MR) analysis using an established dairy intake-associated genetic polymorphism located upstream of the lactase gene (LCT-13910 C/T, rs4988235) as an instrumental variable (IV). Linear regression models were fitted to analyze associations between (a) dairy intake and BMI, (b) rs4988235 and dairy intake, and (c) rs4988235 and BMI in each study. The causal effect of dairy intake on BMI was quantified by IV estimators among 184802 participants from 25 studies.\ Higher dairy intake was associated with higher BMI (β = 0.03 kg/m2 per serving/day; 95% CI, 0.00-0.06; P = 0.04), whereas the LCT genotype with 1 or 2 T allele was significantly associated with 0.20 (95% CI, 0.14-0.25) serving/day higher dairy intake (P = 3.15 × 10-12) and 0.12 (95% CI, 0.06-0.17) kg/m2 higher BMI (P = 2.11 × 10-5). MR analysis showed that the genetically determined higher dairy intake was significantly associated with higher BMI (β = 0.60 kg/m2 per serving/day; 95% CI, 0.27-0.92; P = 3.0 × 10-4).\ The present study provides strong evidence to support a causal effect of higher dairy intake on increased BMI among adults.

DNA methylation age is associated with an altered hemostatic profile in a multi-ethnic meta-analysis. - Ward-Caviness, Cavin K; Huffman, Jennifer E; Evertt, Karl; Germain, Marine; van Dongen, Jenny; Hill, W David; Jhun, Min A; Brody, Jennifer A; Ghanbari, Mohsen; Du, Lei; Roetker, Nicholas S; de Vries, Paul S; et al. (Blood, 2018)
Many hemostatic factors are associated with age and age-related diseases, however much remains unknown about the biological mechanisms linking aging and hemostatic factors. DNA methylation is a novel means by which to assess epigenetic aging, which is a measure of age and the aging processes as determined by altered epigenetic states. We used a meta-analysis approach to examine the association between measures of epigenetic aging and hemostatic factors, as well as a clotting time measure. For fibrinogen, we used European and African-ancestry participants who were meta-analyzed separately and combined via a random effects meta-analysis. All other measures only included participants of European-ancestry. We found that 1-year higher extrinsic epigenetic age as compared to chronological age was associated with higher fibrinogen (0.004 g/L per year; 95% CI: 0.001, 0.007; P = 0.01) and plasminogen activator inhibitor 1 (PAI-1; 0.13 U/mL per year; 95% CI: 0.07, 0.20; P = 6.6x10-5) concentrations as well as lower activated partial thromboplastin time, a measure of clotting time. We replicated PAI-1 associations using an independent cohort. To further elucidate potential functional mechanisms we associated epigenetic aging with expression levels of the PAI-1 protein encoding gene (SERPINE1) and the three fibrinogen subunit-encoding genes (FGA, FGG, and FGB), in both peripheral blood and aorta intima-media samples. We observed associations between accelerated epigenetic aging and transcription of FGG in both tissues. Collectively, our results indicate that accelerated epigenetic aging is associated with a pro-coagulation hemostatic profile, and that epigenetic aging may regulate hemostasis in part via gene transcription.

Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies. - Pennells, Lisa; Kaptoge, Stephen; Wood, Angela; Sweeting, Mike; Zhao, Xiaohui; White, Ian; Burgess, Stephen; Willeit, Peter; Bolton, Thomas; Moons, Karel G M; van der Schouw, Yvonne T; Selmer, Randi; et al. (Eur Heart J, 2018)
Aims: There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied. Methods and results: Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged ≥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms. Conclusion: Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

Exome Chip Analysis Identifies Low-Frequency and Rare Variants in for White Matter Hyperintensities on Brain Magnetic Resonance Imaging. - Jian, Xueqiu; Satizabal, Claudia L; Smith, Albert V; Wittfeld, Katharina; Bis, Joshua C; Smith, Jennifer A; Hsu, Fang-Chi; Nho, Kwangsik; Hofer, Edith; Hagenaars, Saskia P; Nyquist, Paul A; Mishra, Aniket; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) on brain magnetic resonance imaging are typical signs of cerebral small vessel disease and may indicate various preclinical, age-related neurological disorders, such as stroke. Though WMH are highly heritable, known common variants explain a small proportion of the WMH variance. The contribution of low-frequency/rare coding variants to WMH burden has not been explored. METHODS: In the discovery sample we recruited 20 719 stroke/dementia-free adults from 13 population-based cohort studies within the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, among which 17 790 were of European ancestry and 2929 of African ancestry. We genotyped these participants at ≈250 000 mostly exonic variants with Illumina HumanExome BeadChip arrays. We performed ethnicity-specific linear regression on rank-normalized WMH in each study separately, which were then combined in meta-analyses to test for association with single variants and genes aggregating the effects of putatively functional low-frequency/rare variants. We then sought replication of the top findings in 1192 adults (European ancestry) with whole exome/genome sequencing data from 2 independent studies. RESULTS: At 17q25, we confirmed the association of multiple common variants in , , and (<6×10). We also identified a novel association with 2 low-frequency nonsynonymous variants in (lead, rs34136221; =4.5×10) partially independent of known common signal (=1.4×10). We further identified a locus at 2q33 containing common variants in , , and (lead, rs2351524; =1.9×10). Although our novel findings were not replicated because of limited power and possible differences in study design, meta-analysis of the discovery and replication samples yielded stronger association for the 2 low-frequency variants (=2.8×10). CONCLUSIONS: Both common and low-frequency/rare functional variants influence WMH. Larger replication and experimental follow-up are essential to confirm our findings and uncover the biological causal mechanisms of age-related WMH.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.

ExomeChip-Wide Analysis of 95 626 Individuals Identifies 10 Novel Loci Associated With QT and JT Intervals. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Warren, Helen R; Lin, Honghuang; Isaacs, Aaron; Liu, Ching-Ti; Marten, Jonathan; Radmanesh, Farid; Hall, Leanne M; Grarup, Niels; Mei, Hao; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: QT interval, measured through a standard ECG, captures the time it takes for the cardiac ventricles to depolarize and repolarize. JT interval is the component of the QT interval that reflects ventricular repolarization alone. Prolonged QT interval has been linked to higher risk of sudden cardiac arrest. METHODS AND RESULTS: We performed an ExomeChip-wide analysis for both QT and JT intervals, including 209 449 variants, both common and rare, in 17 341 genes from the Illumina Infinium HumanExome BeadChip. We identified 10 loci that modulate QT and JT interval duration that have not been previously reported in the literature using single-variant statistical models in a meta-analysis of 95 626 individuals from 23 cohorts (comprised 83 884 European ancestry individuals, 9610 blacks, 1382 Hispanics, and 750 Asians). This brings the total number of ventricular repolarization associated loci to 45. In addition, our approach of using coding variants has highlighted the role of 17 specific genes for involvement in ventricular repolarization, 7 of which are in novel loci. CONCLUSIONS: Our analyses show a role for myocyte internal structure and interconnections in modulating QT interval duration, adding to previous known roles of potassium, sodium, and calcium ion regulation, as well as autonomic control. We anticipate that these discoveries will open new paths to the goal of making novel remedies for the prevention of lethal ventricular arrhythmias and sudden cardiac arrest.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic Variation in Genes Underlying Diverse Dementias May Explain a Small Proportion of Cases in the Alzheimer's Disease Sequencing Project. - Blue, Elizabeth E; Bis, Joshua C; Dorschner, Michael O; Tsuang, Debby W; Barral, Sandra M; Beecham, Gary; Below, Jennifer E; Bush, William S; Butkiewicz, Mariusz; Cruchaga, Carlos; DeStefano, Anita; Farrer, Lindsay A; et al. (Dement Geriatr Cogn Disord, 2018)
BACKGROUND/AIMS: The Alzheimer's Disease Sequencing Project (ADSP) aims to identify novel genes influencing Alzheimer's disease (AD). Variants within genes known to cause dementias other than AD have previously been associated with AD risk. We describe evidence of co-segregation and associations between variants in dementia genes and clinically diagnosed AD within the ADSP. METHODS: We summarize the properties of known pathogenic variants within dementia genes, describe the co-segregation of variants annotated as "pathogenic" in ClinVar and new candidates observed in ADSP families, and test for associations between rare variants in dementia genes in the ADSP case-control study. The participants were clinically evaluated for AD, and they represent European, Caribbean Hispanic, and isolate Dutch populations. RESULTS/CONCLUSIONS: Pathogenic variants in dementia genes were predominantly rare and conserved coding changes. Pathogenic variants within ARSA, CSF1R, and GRN were observed, and candidate variants in GRN and CHMP2B were nominated in ADSP families. An independent case-control study provided evidence of an association between variants in TREM2, APOE, ARSA, CSF1R, PSEN1, and MAPT and risk of AD. Variants in genes which cause dementing disorders may influence the clinical diagnosis of AD in a small proportion of cases within the ADSP.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation. - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T; Traglia, Michela; Ahluwalia, Tarunveer S; Akiyama, Masato; Appel, Emil Vincent R; Arking, Dan E; et al. (Nat Commun, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.

Genome-wide association meta-analysis of circulating odd-numbered chain saturated fatty acids: Results from the CHARGE Consortium. - de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Sun, Qi; King, Irena B; Wu, Jason H Y; Manichaikul, Ani; Rich, Stephen S; Tsai, Michael Y; Chen, Y D; Fornage, Myriam; Weihua, Guan; Aslibekyan, Stella; et al. (PLoS One, 2018)
BACKGROUND: Odd-numbered chain saturated fatty acids (OCSFA) have been associated with potential health benefits. Although some OCSFA (e.g., C15:0 and C17:0) are found in meats and dairy products, sources and metabolism of C19:0 and C23:0 are relatively unknown, and the influence of non-dietary determinants, including genetic factors, on circulating levels of OCSFA is not established. OBJECTIVE: To elucidate the biological processes that influence circulating levels of OCSFA by investigating associations between genetic variation and OCSFA. DESIGN: We performed a meta-analysis of genome-wide association studies (GWAS) of plasma phospholipid/erythrocyte levels of C15:0, C17:0, C19:0, and C23:0 among 11,494 individuals of European descent. We also investigated relationships between specific single nucleotide polymorphisms (SNPs) in the lactase (LCT) gene, associated with adult-onset lactase intolerance, with circulating levels of dairy-derived OCSFA, and evaluated associations of candidate sphingolipid genes with C23:0 levels. RESULTS: We found no genome-wide significant evidence that common genetic variation is associated with circulating levels of C15:0 or C23:0. In two cohorts with available data, we identified one intronic SNP (rs13361131) in myosin X gene (MYO10) associated with C17:0 level (P = 1.37×10-8), and two intronic SNP (rs12874278 and rs17363566) in deleted in lymphocytic leukemia 1 (DLEU1) region associated with C19:0 level (P = 7.07×10-9). In contrast, when using a candidate-gene approach, we found evidence that three SNPs in LCT (rs11884924, rs16832067, and rs3816088) are associated with circulating C17:0 level (adjusted P = 4×10-2). In addition, nine SNPs in the ceramide synthase 4 (CERS4) region were associated with circulating C23:0 levels (adjusted P<5×10-2). CONCLUSIONS: Our findings suggest that circulating levels of OCSFA may be predominantly influenced by non-genetic factors. SNPs associated with C17:0 level in the LCT gene may reflect genetic influence in dairy consumption or in metabolism of dairy foods. SNPs associated with C23:0 may reflect a role of genetic factors in the synthesis of sphingomyelin.
Keywords: Fatty Acids; Genome-Wide Association Study; Humans; Introns; Lactase; Myosins; Polymorphism, Single Nucleotide; Sphingomyelins; Sphingosine N-Acyltransferase; Tumor Suppressor Proteins

Genome-wide association study in 79,366 European-ancestry individuals informs the genetic architecture of 25-hydroxyvitamin D levels. - Jiang, Xia; O'Reilly, Paul F; Aschard, Hugues; Hsu, Yi-Hsiang; Richards, J Brent; Dupuis, Josée; Ingelsson, Erik; Karasik, David; Pilz, Stefan; Berry, Diane; Kestenbaum, Bryan; Zheng, Jusheng; et al. (Nat Commun, 2018)
Vitamin D is a steroid hormone precursor that is associated with a range of human traits and diseases. Previous GWAS of serum 25-hydroxyvitamin D concentrations have identified four genome-wide significant loci (GC, NADSYN1/DHCR7, CYP2R1, CYP24A1). In this study, we expand the previous SUNLIGHT Consortium GWAS discovery sample size from 16,125 to 79,366 (all European descent). This larger GWAS yields two additional loci harboring genome-wide significant variants (P = 4.7×10 at rs8018720 in SEC23A, and P = 1.9×10 at rs10745742 in AMDHD1). The overall estimate of heritability of 25-hydroxyvitamin D serum concentrations attributable to GWAS common SNPs is 7.5%, with statistically significant loci explaining 38% of this total. Further investigation identifies signal enrichment in immune and hematopoietic tissues, and clustering with autoimmune diseases in cell-type-specific analysis. Larger studies are required to identify additional common SNPs, and to explore the role of rare or structural variants and gene-gene interactions in the heritability of circulating 25-hydroxyvitamin D levels.

Genome-wide association study of 23,500 individuals identifies 7 loci associated with brain ventricular volume. - Vojinovic, Dina; Adams, Hieab H; Jian, Xueqiu; Yang, Qiong; Smith, Albert Vernon; Bis, Joshua C; Teumer, Alexander; Scholz, Markus; Armstrong, Nicola J; Hofer, Edith; Saba, Yasaman; Luciano, Michelle; et al. (Nat Commun, 2018)
The volume of the lateral ventricles (LV) increases with age and their abnormal enlargement is a key feature of several neurological and psychiatric diseases. Although lateral ventricular volume is heritable, a comprehensive investigation of its genetic determinants is lacking. In this meta-analysis of genome-wide association studies of 23,533 healthy middle-aged to elderly individuals from 26 population-based cohorts, we identify 7 genetic loci associated with LV volume. These loci map to chromosomes 3q28, 7p22.3, 10p12.31, 11q23.1, 12q23.3, 16q24.2, and 22q13.1 and implicate pathways related to tau pathology, S1P signaling, and cytoskeleton organization. We also report a significant genetic overlap between the thalamus and LV volumes (ρ = -0.59, p-value = 3.14 × 10), suggesting that these brain structures may share a common biology. These genetic associations of LV volume provide insights into brain morphology.

Genome-Wide Association Trans-Ethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels. - Sabater-Lleal, Maria; Huffman, Jennifer E; de Vries, Paul S; Marten, Jonathan; Mastrangelo, Michael A; Song, Ci; Pankratz, Nathan; Ward-Caviness, Cavin K; Yanek, Lisa R; Trompet, Stella; Delgado, Graciela E; Guo, Xiuqing; et al. (Circulation, 2018)
BACKGROUND: Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF. METHODS: We meta-analyzed genome-wide association results from 46,354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated approximately 35 million imputed variants with natural-log transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization (MR) analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events. RESULTS: We identified 13 novel genome-wide significant (p≤2.5x10) associations; 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. MR suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk. CONCLUSIONS: The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-wide meta-analysis of 158,000 individuals of European ancestry identifies three loci associated with chronic back pain. - Suri, Pradeep; Palmer, Melody R; Tsepilov, Yakov A; Freidin, Maxim B; Boer, Cindy G; Yau, Michelle S; Evans, Daniel S; Gelemanovic, Andrea; Bartz, Traci M; Nethander, Maria; Arbeeva, Liubov; Karssen, Lennart; et al. (PLoS Genet, 2018)
Back pain is the #1 cause of years lived with disability worldwide, yet surprisingly little is known regarding the biology underlying this symptom. We conducted a genome-wide association study (GWAS) meta-analysis of chronic back pain (CBP). Adults of European ancestry were included from 15 cohorts in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and from the UK Biobank interim data release. CBP cases were defined as those reporting back pain present for ≥3-6 months; non-cases were included as comparisons ("controls"). Each cohort conducted genotyping using commercially available arrays followed by imputation. GWAS used logistic regression models with additive genetic effects, adjusting for age, sex, study-specific covariates, and population substructure. The threshold for genome-wide significance in the fixed-effect inverse-variance weighted meta-analysis was p<5×10-8. Suggestive (p<5×10-7) and genome-wide significant (p<5×10-8) variants were carried forward for replication or further investigation in the remaining UK Biobank participants not included in the discovery sample. The discovery sample comprised 158,025 individuals, including 29,531 CBP cases. A genome-wide significant association was found for the intronic variant rs12310519 in SOX5 (OR 1.08, p = 7.2×10-10). This was subsequently replicated in 283,752 UK Biobank participants not included in the discovery sample, including 50,915 cases (OR 1.06, p = 5.3×10-11), and exceeded genome-wide significance in joint meta-analysis (OR 1.07, p = 4.5×10-19). We found suggestive associations at three other loci in the discovery sample, two of which exceeded genome-wide significance in joint meta-analysis: an intergenic variant, rs7833174, located between CCDC26 and GSDMC (OR 1.05, p = 4.4×10-13), and an intronic variant, rs4384683, in DCC (OR 0.97, p = 2.4×10-10). In this first reported meta-analysis of GWAS for CBP, we identified and replicated a genetic locus associated with CBP (SOX5). We also identified 2 other loci that reached genome-wide significance in a 2-stage joint meta-analysis (CCDC26/GSDMC and DCC).

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Harmonization of Respiratory Data From 9 US Population-Based Cohorts: The NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Cassano, Patricia A; Couper, David; Enright, Paul L; Folsom, Aaron R; Hankinson, John; Jacobs, David R; Kalhan, Ravi; Kaplan, Robert; Kronmal, Richard; Lange, Leslie; et al. (Am J Epidemiol, 2018)
Chronic lower respiratory diseases (CLRDs) are the fourth leading cause of death in the United States. To support investigations into CLRD risk determinants and new approaches to primary prevention, we aimed to harmonize and pool respiratory data from US general population-based cohorts. Data were obtained from prospective cohorts that performed prebronchodilator spirometry and were harmonized following 2005 ATS/ERS standards. In cohorts conducting follow-up for noncardiovascular events, CLRD events were defined as hospitalizations/deaths adjudicated as CLRD-related or assigned relevant administrative codes. Coding and variable names were applied uniformly. The pooled sample included 65,251 adults in 9 cohorts followed-up for CLRD-related mortality over 653,380 person-years during 1983-2016. Average baseline age was 52 years; 56% were female; 49% were never-smokers; and racial/ethnic composition was 44% white, 22% black, 28% Hispanic/Latino, and 5% American Indian. Over 96% had complete data on smoking, clinical CLRD diagnoses, and dyspnea. After excluding invalid spirometry examinations (13%), there were 105,696 valid examinations (median, 2 per participant). Of 29,351 participants followed for CLRD hospitalizations, median follow-up was 14 years; only 5% were lost to follow-up at 10 years. The NHLBI Pooled Cohorts Study provides a harmonization standard applied to a large, US population-based sample that may be used to advance epidemiologic research on CLRD.

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).

{Life-Course Genome-wide Association Study Meta-analysis of Total Body BMD and Assessment of Age-Specific Effects - Medina-Gomez, C.; Kemp, J. P.; Trajanoska, K.; Luan, J.; Chesi, A.; Ahluwalia, T. S.; Mook-Kanamori, D. O.; Ham, A.; Hartwig, F. P.; Evans, D. S.; Joro, R.; Nedeljkovic, I.; et al. (Am J Hum Genet, 2018)
Bone mineral density (BMD) assessed by DXA is used to evaluate bone health. In children, total body (TB) measurements are commonly used; in older individuals, BMD at the lumbar spine (LS) and femoral neck (FN) is used to diagnose osteoporosis. To date, genetic variants in more than 60 loci have been identified as associated with BMD. To investigate the genetic determinants of TB-BMD variation along the life course and test for age-specific effects, we performed a meta-analysis of 30 genome-wide association studies (GWASs) of TB-BMD including 66,628 individuals overall and divided across five age strata, each spanning 15 years. We identified variants associated with TB-BMD at 80 loci, of which 36 have not been previously identified; overall, they explain approximately 10% of the TB-BMD variance when combining all age groups and influence the risk of fracture. Pathway and enrichment analysis of the association signals showed clustering within gene sets implicated in the regulation of cell growth and SMAD proteins, overexpressed in the musculoskeletal system, and enriched in enhancer and promoter regions. These findings reveal TB-BMD as a relevant trait for genetic studies of osteoporosis, enabling the identification of variants and pathways influencing different bone compartments. Only variants in ESR1 and close proximity to RANKL showed a clear effect dependency on age. This most likely indicates that the majority of genetic variants identified influence BMD early in life and that their effect can be captured throughout the life course.

Low thyroid function is not associated with an accelerated deterioration in renal function. - Meuwese, Christiaan L; van Diepen, Merel; Cappola, Anne R; Sarnak, Mark J; Shlipak, Michael G; Bauer, Douglas C; Fried, Linda P; Iacoviello, Massimo; Vaes, Bert; Degryse, Jean; Khaw, Kay-Tee; Luben, Robert N; et al. (Nephrol Dial Transplant, 2018)
Background: Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups. Methods: Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models. Results: A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function. Conclusions: Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

Meta-analysis across Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium provides evidence for an association of serum vitamin D with pulmonary function. - Xu, Jiayi; Bartz, Traci M; Chittoor, Geetha; Eiriksdottir, Gudny; Manichaikul, Ani W; Sun, Fangui; Terzikhan, Natalie; Zhou, Xia; Booth, Sarah L; Brusselle, Guy G; de Boer, Ian H; Fornage, Myriam; et al. (Br J Nutr, 2018)
The role that vitamin D plays in pulmonary function remains uncertain. Epidemiological studies reported mixed findings for serum 25-hydroxyvitamin D (25(OH)D)-pulmonary function association. We conducted the largest cross-sectional meta-analysis of the 25(OH)D-pulmonary function association to date, based on nine European ancestry (EA) cohorts (n 22 838) and five African ancestry (AA) cohorts (n 4290) in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Data were analysed using linear models by cohort and ancestry. Effect modification by smoking status (current/former/never) was tested. Results were combined using fixed-effects meta-analysis. Mean serum 25(OH)D was 68 (sd 29) nmol/l for EA and 49 (sd 21) nmol/l for AA. For each 1 nmol/l higher 25(OH)D, forced expiratory volume in the 1st second (FEV1) was higher by 1·1 ml in EA (95 % CI 0·9, 1·3; P<0·0001) and 1·8 ml (95 % CI 1·1, 2·5; P<0·0001) in AA (P race difference=0·06), and forced vital capacity (FVC) was higher by 1·3 ml in EA (95 % CI 1·0, 1·6; P<0·0001) and 1·5 ml (95 % CI 0·8, 2·3; P=0·0001) in AA (P race difference=0·56). Among EA, the 25(OH)D-FVC association was stronger in smokers: per 1 nmol/l higher 25(OH)D, FVC was higher by 1·7 ml (95 % CI 1·1, 2·3) for current smokers and 1·7 ml (95 % CI 1·2, 2·1) for former smokers, compared with 0·8 ml (95 % CI 0·4, 1·2) for never smokers. In summary, the 25(OH)D associations with FEV1 and FVC were positive in both ancestries. In EA, a stronger association was observed for smokers compared with never smokers, which supports the importance of vitamin D in vulnerable populations.

Meta-analysis of exome array data identifies six novel genetic loci for lung function. - Jackson, Victoria E; Latourelle, Jeanne C; Wain, Louise V; Smith, Albert V; Grove, Megan L; Bartz, Traci M; Obeidat, Ma'en; Province, Michael A; Gao, Wei; Qaiser, Beenish; Porteous, David J; Cassano, Patricia A; et al. (Wellcome Open Res, 2018)
Over 90 regions of the genome have been associated with lung function to date, many of which have also been implicated in chronic obstructive pulmonary disease. We carried out meta-analyses of exome array data and three lung function measures: forced expiratory volume in one second (FEV ), forced vital capacity (FVC) and the ratio of FEV to FVC (FEV /FVC). These analyses by the SpiroMeta and CHARGE consortia included 60,749 individuals of European ancestry from 23 studies, and 7,721 individuals of African Ancestry from 5 studies in the discovery stage, with follow-up in up to 111,556 independent individuals. We identified significant (P<2·8x10 ) associations with six SNPs: a nonsynonymous variant in , which is predicted to be damaging, three intronic SNPs ( and ) and two intergenic SNPs near to and Expression quantitative trait loci analyses found evidence for regulation of gene expression at three signals and implicated several genes, including and . Further interrogation of these loci could provide greater understanding of the determinants of lung function and pulmonary disease.

Multiancestry association study identifies new asthma risk loci that colocalize with immune-cell enhancer marks. - Demenais, Florence; Margaritte-Jeannin, Patricia; Barnes, Kathleen C; Cookson, William O C; Altmüller, Janine; Ang, Wei; Barr, R Graham; Beaty, Terri H; Becker, Allan B; Beilby, John; Bisgaard, Hans; Bjornsdottir, Unnur Steina; et al. (Nat Genet, 2018)
We examined common variation in asthma risk by conducting a meta-analysis of worldwide asthma genome-wide association studies (23,948 asthma cases, 118,538 controls) of individuals from ethnically diverse populations. We identified five new asthma loci, found two new associations at two known asthma loci, established asthma associations at two loci previously implicated in the comorbidity of asthma plus hay fever, and confirmed nine known loci. Investigation of pleiotropy showed large overlaps in genetic variants with autoimmune and inflammatory diseases. The enrichment in enhancer marks at asthma risk loci, especially in immune cells, suggested a major role of these loci in the regulation of immunologically related mechanisms.

Multiancestry genome-wide association study of 520,000 subjects identifies 32 loci associated with stroke and stroke subtypes. - Malik, Rainer; Chauhan, Ganesh; Traylor, Matthew; Sargurupremraj, Muralidharan; Okada, Yukinori; Mishra, Aniket; Rutten-Jacobs, Loes; Giese, Anne-Katrin; van der Laan, Sander W; Gretarsdottir, Solveig; Anderson, Christopher D; Chong, Michael; et al. (Nat Genet, 2018)
Stroke has multiple etiologies, but the underlying genes and pathways are largely unknown. We conducted a multiancestry genome-wide-association meta-analysis in 521,612 individuals (67,162 cases and 454,450 controls) and discovered 22 new stroke risk loci, bringing the total to 32. We further found shared genetic variation with related vascular traits, including blood pressure, cardiac traits, and venous thromboembolism, at individual loci (n = 18), and using genetic risk scores and linkage-disequilibrium-score regression. Several loci exhibited distinct association and pleiotropy patterns for etiological stroke subtypes. Eleven new susceptibility loci indicate mechanisms not previously implicated in stroke pathophysiology, with prioritization of risk variants and genes accomplished through bioinformatics analyses using extensive functional datasets. Stroke risk loci were significantly enriched in drug targets for antithrombotic therapy.

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.

Multiethnic meta-analysis identifies ancestry-specific and cross-ancestry loci for pulmonary function. - Wyss, Annah B; Sofer, Tamar; Lee, Mi Kyeong; Terzikhan, Natalie; Nguyen, Jennifer N; Lahousse, Lies; Latourelle, Jeanne C; Smith, Albert Vernon; Bartz, Traci M; Feitosa, Mary F; Gao, Wei; Ahluwalia, Tarunveer S; et al. (Nat Commun, 2018)
Nearly 100 loci have been identified for pulmonary function, almost exclusively in studies of European ancestry populations. We extend previous research by meta-analyzing genome-wide association studies of 1000 Genomes imputed variants in relation to pulmonary function in a multiethnic population of 90,715 individuals of European (N = 60,552), African (N = 8429), Asian (N = 9959), and Hispanic/Latino (N = 11,775) ethnicities. We identify over 50 additional loci at genome-wide significance in ancestry-specific or multiethnic meta-analyses. Using recent fine-mapping methods incorporating functional annotation, gene expression, and differences in linkage disequilibrium between ethnicities, we further shed light on potential causal variants and genes at known and newly identified loci. Several of the novel genes encode proteins with predicted or established drug targets, including KCNK2 and CDK12. Our study highlights the utility of multiethnic and integrative genomics approaches to extend existing knowledge of the genetics of lung function and clinical relevance of implicated loci.

Multiethnic Meta-Analysis Identifies RAI1 as a Possible Obstructive Sleep Apnea-related Quantitative Trait Locus in Men. - Chen, Han; Cade, Brian E; Gleason, Kevin J; Bjonnes, Andrew C; Stilp, Adrienne M; Sofer, Tamar; Conomos, Matthew P; Ancoli-Israel, Sonia; Arens, Raanan; Azarbarzin, Ali; Bell, Graeme I; Below, Jennifer E; et al. (Am J Respir Cell Mol Biol, 2018)
Obstructive sleep apnea (OSA) is a common heritable disorder displaying marked sexual dimorphism in disease prevalence and progression. Previous genetic association studies have identified a few genetic loci associated with OSA and related quantitative traits, but they have only focused on single ethnic groups, and a large proportion of the heritability remains unexplained. The apnea-hypopnea index (AHI) is a commonly used quantitative measure characterizing OSA severity. Because OSA differs by sex, and the pathophysiology of obstructive events differ in rapid eye movement (REM) and non-REM (NREM) sleep, we hypothesized that additional genetic association signals would be identified by analyzing the NREM/REM-specific AHI and by conducting sex-specific analyses in multiethnic samples. We performed genome-wide association tests for up to 19,733 participants of African, Asian, European, and Hispanic/Latino American ancestry in 7 studies. We identified rs12936587 on chromosome 17 as a possible quantitative trait locus for NREM AHI in men (N = 6,737; P = 1.7 × 10) but not in women (P = 0.77). The association with NREM AHI was replicated in a physiological research study (N = 67; P = 0.047). This locus overlapping the RAI1 gene and encompassing genes PEMT1, SREBF1, and RASD1 was previously reported to be associated with coronary artery disease, lipid metabolism, and implicated in Potocki-Lupski syndrome and Smith-Magenis syndrome, which are characterized by abnormal sleep phenotypes. We also identified gene-by-sex interactions in suggestive association regions, suggesting that genetic variants for AHI appear to vary by sex, consistent with the clinical observations of strong sexual dimorphism.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.

Omega-3 Fatty Acids and Genome-wide Interaction Analyses Reveal DPP10-Pulmonary Function Association. - Xu, Jiayi; Gaddis, Nathan C; Bartz, Traci M; Hou, Ruixue; Manichaikul, Ani W; Pankratz, Nathan; Smith, Albert V; Sun, Fangui; Terzikhan, Natalie; Markunas, Christina A; Patchen, Bonnie K; Schu, Matthew; et al. (Am J Respir Crit Care Med, 2018)
RATIONALE: Omega-3 poly-unsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health. OBJECTIVE: To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility. METHODS: Associations of n-3 PUFA biomarkers (alpha-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (forced expiratory volume in the first second [FEV], forced vital capacity [FVC], and [FEV/FVC]) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N=16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N=11,962) and replicated in one cohort (N=1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of single nucleotide polymorphism (SNP) associations and their interactions with n-3 PUFAs. RESULTS: DPA and DHA were positively associated with FEV1 and FVC (P<0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P=9.4×10 across discovery and replication cohorts). The rs11693320-A allele (frequency~80%) was associated with lower FVC (P=2.1×10; β= -161.0mL), and the association was attenuated by higher DHA levels (P=2.1×10; β=36.2mL). CONCLUSIONS: We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

Outdoor air pollution and mosaic loss of chromosome Y in older men from the Cardiovascular Health Study. - Wong, Jason Y Y; Margolis, Helene G; Machiela, Mitchell; Zhou, Weiyin; Odden, Michelle C; Psaty, Bruce M; Robbins, John; Jones, Rena R; Rotter, Jerome I; Chanock, Stephen J; Rothman, Nathaniel; Lan, Qing; et al. (Environ Int, 2018)
BACKGROUND: Mosaic loss of chromosome Y (mLOY) can occur in a fraction of cells as men age, which is potentially linked to increased mortality risk. Smoking is related to mLOY; however, the contribution of air pollution is unclear. OBJECTIVE: We investigated whether exposure to outdoor air pollution, age, and smoking were associated with mLOY. METHODS: We analyzed baseline (1989-1993) blood samples from 933 men ≥65 years of age from the prospective Cardiovascular Health Study. Particulate matter ≤10 μm (PM), carbon monoxide, nitrogen dioxide, sulfur dioxide, and ozone data were obtained from the U.S. EPA Aerometric Information Retrieval System for the year prior to baseline. Inverse-distance weighted air monitor data were used to estimate each participants' monthly residential exposure. mLOY was detected with standard methods using signal intensity (median log-R ratio (mLRR)) of the male-specific chromosome Y regions from Illumina array data. Linear regression models were used to evaluate relations between mean exposure in the prior year, age, smoking and continuous mLRR. RESULTS: Increased PM was associated with mLOY, namely decreased mLRR (p-trend = 0.03). Compared with the lowest tertile (≤28.5 μg/m), the middle (28.5-31.0 μg/m; β = -0.0044, p = 0.09) and highest (≥31 μg/m; β = -0.0054, p = 0.04) tertiles had decreased mLRR, adjusted for age, clinic, race/cohort, smoking status and pack-years. Additionally, increasing age (β = -0.00035, p = 0.06) and smoking pack-years (β = -0.00011, p = 1.4E-3) were associated with decreased mLRR, adjusted for each other and race/cohort. No significant associations were found for other pollutants. CONCLUSIONS: PM may increase leukocyte mLOY, a marker of genomic instability. The sample size was modest and replication is warranted.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.

Predictive value for cardiovascular events of common carotid intima media thickness and its rate of change in individuals at high cardiovascular risk - Results from the PROG-IMT collaboration. - Lorenz, Matthias W; Gao, Lu; Ziegelbauer, Kathrin; Norata, Giuseppe Danilo; Empana, Jean Philippe; Schmidtmann, Irene; Lin, Hung-Ju; McLachlan, Stela; Bokemark, Lena; Ronkainen, Kimmo; Amato, Mauro; Schminke, Ulf; et al. (PLoS One, 2018)
AIMS: Carotid intima media thickness (CIMT) predicts cardiovascular (CVD) events, but the predictive value of CIMT change is debated. We assessed the relation between CIMT change and events in individuals at high cardiovascular risk. METHODS AND RESULTS: From 31 cohorts with two CIMT scans (total n = 89070) on average 3.6 years apart and clinical follow-up, subcohorts were drawn: (A) individuals with at least 3 cardiovascular risk factors without previous CVD events, (B) individuals with carotid plaques without previous CVD events, and (C) individuals with previous CVD events. Cox regression models were fit to estimate the hazard ratio (HR) of the combined endpoint (myocardial infarction, stroke or vascular death) per standard deviation (SD) of CIMT change, adjusted for CVD risk factors. These HRs were pooled across studies. In groups A, B and C we observed 3483, 2845 and 1165 endpoint events, respectively. Average common CIMT was 0.79mm (SD 0.16mm), and annual common CIMT change was 0.01mm (SD 0.07mm), both in group A. The pooled HR per SD of annual common CIMT change (0.02 to 0.43mm) was 0.99 (95% confidence interval: 0.95-1.02) in group A, 0.98 (0.93-1.04) in group B, and 0.95 (0.89-1.04) in group C. The HR per SD of common CIMT (average of the first and the second CIMT scan, 0.09 to 0.75mm) was 1.15 (1.07-1.23) in group A, 1.13 (1.05-1.22) in group B, and 1.12 (1.05-1.20) in group C. CONCLUSIONS: We confirm that common CIMT is associated with future CVD events in individuals at high risk. CIMT change does not relate to future event risk in high-risk individuals.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Female; Humans; Intersectoral Collaboration; Male; Middle Aged; Prognosis; Risk Factors

Rare loss of function variants in candidate genes and risk of colorectal cancer. - Rosenthal, Elisabeth A; Shirts, Brian H; Amendola, Laura M; Horike-Pyne, Martha; Robertson, Peggy D; Hisama, Fuki M; Bennett, Robin L; Dorschner, Michael O; Nickerson, Deborah A; Stanaway, Ian B; Nassir, Rami; Vickers, Kathy T; et al. (Hum Genet, 2018)
Although ~ 25% of colorectal cancer or polyp (CRC/P) cases show familial aggregation, current germline genetic testing identifies a causal genotype in the 16 major genes associated with high penetrance CRC/P in only 20% of these cases. As there are likely other genes underlying heritable CRC/P, we evaluated the association of variation at novel loci with CRC/P. We evaluated 158 a priori selected candidate genes by comparing the number of rare potentially disruptive variants (PDVs) found in 84 CRC/P cases without an identified CRC/P risk-associated variant and 2440 controls. We repeated this analysis using an additional 73 CRC/P cases. We also compared the frequency of PDVs in select genes among CRC/P cases with two publicly available data sets. We found a significant enrichment of PDVs in cases vs. controls: 20% of cases vs. 11.5% of controls with ≥ 1 PDV (OR = 1.9, p = 0.01) in the original set of cases. Among the second cohort of CRC/P cases, 18% had a PDV, significantly different from 11.5% (p = 0.02). Logistic regression, adjusting for ancestry and multiple testing, indicated association between CRC/P and PDVs in NTHL1 (p = 0.0001), BRCA2 (p = 0.01) and BRIP1 (p = 0.04). However, there was no significant difference in the frequency of PDVs at each of these genes between all 157 CRC/P cases and two publicly available data sets. These results suggest an increased presence of PDVs in CRC/P cases and support further investigation of the association of NTHL1, BRCA2 and BRIP1 variation with CRC/P.

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.

The relation between thyroid function and anemia: a pooled analysis of individual participant data. - Wopereis, Daisy M; Du Puy, Robert S; van Heemst, Diana; Walsh, John P; Bremner, Alexandra; Bakker, Stephan J L; Bauer, Douglas C; Cappola, Anne R; Ceresini, Graziano; Degryse, Jean; Dullaart, Robin P F; Feller, Martin; et al. (J Clin Endocrinol Metab, 2018)
Context: Anemia and thyroid dysfunction often co-occur and both increase with age. Human data on the relationship between thyroid disease and anemia are scarce. Objective: To investigate the cross-sectional and longitudinal associations between clinical thyroid status and anemia. Design: Individual participant data meta-analysis. Setting: Sixteen cohorts participating in the Thyroid Studies Collaboration (n=42 162). Main outcome measures: Primary outcome measure was anemia (hemoglobin <130 g/L in men and <120 g/L in women). Results: Cross-sectionally, participants with abnormal thyroid status had an increased risk of having anemia compared with euthyroid participants (overt hypothyroidism, pooled odds ratio 1.84 [95% CI: 1.35-2.50], subclinical hypothyroidism 1.21 [1.02-1.43], subclinical hyperthyroidism 1.27 [1.03-1.57], overt hyperthyroidism 1.69 [1.00-2.87]). Hemoglobin levels were lower in all groups compared to participants with euthyroidism. In the longitudinal analyses (n=25,466 from 14 cohorts), the pooled hazard ratio for the risk of development of anemia was 1.38 [95% CI: 0.86-2.20] for overt hypothyroidism, 1.18 [1.00-1.38] for subclinical hypothyroidism, 1.15 [0.94-1.42] for subclinical hyperthyroidism and 1.47 [0.91-2.38] for overt hyperthyroidism. Sensitivity analyses excluding thyroid medication or high levels of C-reactive protein yielded similar results. No differences in mean annual change in hemoglobin levels were observed between the thyroid hormone status groups. Conclusion: Higher odds of having anemia were observed in both participants with hypothyroid function and hyperthyroid function. In addition, reduced thyroid function at baseline showed a trend of increased risk of developing anemia during follow-up. It remains to be assessed in a randomized controlled trial whether treatment is effective in reducing anemia.

Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium. - Inker, Lesley A; Grams, Morgan E; Levey, Andrew S; Coresh, Josef; Cirillo, Massimo; Collins, John F; Gansevoort, Ron T; Gutierrez, Orlando M; Hamano, Takayuki; Heine, Gunnar H; Ishikawa, Shizukiyo; Jee, Sun Ha; et al. (Am J Kidney Dis, 2018)
RATIONALE & OBJECTIVE: Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework. STUDY DESIGN: Cross-sectional individual participant-level analyses in a global consortium. SETTING & STUDY POPULATIONS: 17 CKD and 38 general population and high-risk cohorts. SELECTION CRITERIA FOR STUDIES: Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension. DATA EXTRACTION: Data were obtained and analyzed between July 2015 and January 2018. ANALYTICAL APPROACH: We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses. RESULTS: The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g). LIMITATIONS: Variations in study era, health care delivery system, typical diet, and laboratory assays. CONCLUSIONS: Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

Risk thresholds for alcohol consumption: combined analysis of individual-participant data for 599 912 current drinkers in 83 prospective studies. - Wood, Angela M; Kaptoge, Stephen; Butterworth, Adam S; Willeit, Peter; Warnakula, Samantha; Bolton, Thomas; Paige, Ellie; Paul, Dirk S; Sweeting, Michael; Burgess, Stephen; Bell, Steven; Astle, William; et al. (Lancet, 2018)
BACKGROUND: Low-risk limits recommended for alcohol consumption vary substantially across different national guidelines. To define thresholds associated with lowest risk for all-cause mortality and cardiovascular disease, we studied individual-participant data from 599 912 current drinkers without previous cardiovascular disease. METHODS: We did a combined analysis of individual-participant data from three large-scale data sources in 19 high-income countries (the Emerging Risk Factors Collaboration, EPIC-CVD, and the UK Biobank). We characterised dose-response associations and calculated hazard ratios (HRs) per 100 g per week of alcohol (12·5 units per week) across 83 prospective studies, adjusting at least for study or centre, age, sex, smoking, and diabetes. To be eligible for the analysis, participants had to have information recorded about their alcohol consumption amount and status (ie, non-drinker vs current drinker), plus age, sex, history of diabetes and smoking status, at least 1 year of follow-up after baseline, and no baseline history of cardiovascular disease. The main analyses focused on current drinkers, whose baseline alcohol consumption was categorised into eight predefined groups according to the amount in grams consumed per week. We assessed alcohol consumption in relation to all-cause mortality, total cardiovascular disease, and several cardiovascular disease subtypes. We corrected HRs for estimated long-term variability in alcohol consumption using 152 640 serial alcohol assessments obtained some years apart (median interval 5·6 years [5th-95th percentile 1·04-13·5]) from 71 011 participants from 37 studies. FINDINGS: In the 599 912 current drinkers included in the analysis, we recorded 40 310 deaths and 39 018 incident cardiovascular disease events during 5·4 million person-years of follow-up. For all-cause mortality, we recorded a positive and curvilinear association with the level of alcohol consumption, with the minimum mortality risk around or below 100 g per week. Alcohol consumption was roughly linearly associated with a higher risk of stroke (HR per 100 g per week higher consumption 1·14, 95% CI, 1·10-1·17), coronary disease excluding myocardial infarction (1·06, 1·00-1·11), heart failure (1·09, 1·03-1·15), fatal hypertensive disease (1·24, 1·15-1·33); and fatal aortic aneurysm (1·15, 1·03-1·28). By contrast, increased alcohol consumption was log-linearly associated with a lower risk of myocardial infarction (HR 0·94, 0·91-0·97). In comparison to those who reported drinking >0-≤100 g per week, those who reported drinking >100-≤200 g per week, >200-≤350 g per week, or >350 g per week had lower life expectancy at age 40 years of approximately 6 months, 1-2 years, or 4-5 years, respectively. INTERPRETATION: In current drinkers of alcohol in high-income countries, the threshold for lowest risk of all-cause mortality was about 100 g/week. For cardiovascular disease subtypes other than myocardial infarction, there were no clear risk thresholds below which lower alcohol consumption stopped being associated with lower disease risk. These data support limits for alcohol consumption that are lower than those recommended in most current guidelines. FUNDING: UK Medical Research Council, British Heart Foundation, National Institute for Health Research, European Union Framework 7, and European Research Council.

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.

Trans-ethnic analysis of metabochip data identifies two new loci associated with BMI. - Gong, J; Nishimura, K K; Fernandez-Rhodes, L; Haessler, J; Bien, S; Graff, M; Lim, U; Lu, Y; Gross, M; Fornage, M; Yoneyama, S; Isasi, C R; et al. (Int J Obes (Lond), 2018)
OBJECTIVE: Body mass index (BMI) is commonly used to assess obesity, which is associated with numerous diseases and negative health outcomes. BMI has been shown to be a heritable, polygenic trait, with close to 100 loci previously identified and replicated in multiple populations. We aim to replicate known BMI loci and identify novel associations in a trans-ethnic study population. SUBJECTS: Using eligible participants from the Population Architecture using Genomics and Epidemiology consortium, we conducted a trans-ethnic meta-analysis of 102 514 African Americans, Hispanics, Asian/Native Hawaiian, Native Americans and European Americans. Participants were genotyped on over 200 000 SNPs on the Illumina Metabochip custom array, or imputed into the 1000 Genomes Project (Phase I). Linear regression of the natural log of BMI, adjusting for age, sex, study site (if applicable), and ancestry principal components, was conducted for each race/ethnicity within each study cohort. Race/ethnicity-specific, and combined meta-analyses used fixed-effects models. RESULTS: We replicated 15 of 21 BMI loci included on the Metabochip, and identified two novel BMI loci at 1q41 (rs2820436) and 2q31.1 (rs10930502) at the Metabochip-wide significance threshold (P<2.5 × 10). Bioinformatic functional investigation of SNPs at these loci suggests a possible impact on pathways that regulate metabolism and adipose tissue. CONCLUSION: Conducting studies in genetically diverse populations continues to be a valuable strategy for replicating known loci and uncovering novel BMI associations.

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2018)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.

Whole genome sequencing of Caribbean Hispanic families with late-onset Alzheimer's disease. - Vardarajan, Badri N; Barral, Sandra; Jaworski, James; Beecham, Gary W; Blue, Elizabeth; Tosto, Giuseppe; Reyes-Dumeyer, Dolly; Medrano, Martin; Lantigua, Rafael; Naj, Adam; Thornton, Timothy; DeStefano, Anita; et al. (Ann Clin Transl Neurol, 2018)
Objective: To identify rare causal variants underlying known loci that segregate with late-onset Alzheimer's disease (LOAD) in multiplex families. Methods: We analyzed whole genome sequences (WGS) from 351 members of 67 Caribbean Hispanic (CH) families from Dominican Republic and New York multiply affected by LOAD. Members of 67 CH and additional 47 Caucasian families underwent WGS as a part of the Alzheimer's Disease Sequencing Project (ADSP). All members of 67 CH families, an additional 48 CH families and an independent CH case-control cohort were subsequently genotyped for validation. Patients met criteria for LOAD, and controls were determined to be dementia free. We investigated rare variants segregating within families and gene-based associations with disease within LOAD GWAS loci. Results: A variant in p.R434W, segregated significantly with LOAD in two large families (OR = 5.77, 95% CI: 1.07-30.9, = 0.041). In addition, missense mutations in and under previously reported linkage peaks at 7q14.3 and 11q12.3 segregated completely in one family and in follow-up genotyping both were nominally significant ( < 0.05). We also identified rare variants in a number of genes associated with LOAD in prior genome wide association studies, including ( = 0.049), ( = 0.0098) and ( = 0.040). Conclusions and Relevance: Rare variants in multiple genes influence the risk of LOAD disease in multiplex families. These results suggest that rare variants may underlie loci identified in genome wide association studies.

Admixture mapping identifies novel loci for obstructive sleep apnea in Hispanic/Latino Americans. - Wang, Heming; Cade, Brian E; Sofer, Tamar; Sands, Scott A; Chen, Han; Browning, Sharon R; Stilp, Adrienne M; Louie, Tin L; Thornton, Timothy A; Johnson, W Craig; Below, Jennifer E; Conomos, Matthew P; et al. (Hum Mol Genet, 2019)
Obstructive sleep apnea (OSA) is a common disorder associated with increased risk of cardiovascular disease and mortality. Its prevalence and severity vary across ancestral background. Although OSA traits are heritable, few genetic associations have been identified. To identify genetic regions associated with OSA and improve statistical power, we applied admixture mapping on three primary OSA traits [the apnea hypopnea index (AHI), overnight average oxyhemoglobin saturation (SaO2) and percentage time SaO2 < 90%] and a secondary trait (respiratory event duration) in a Hispanic/Latino American population study of 11 575 individuals with significant variation in ancestral background. Linear mixed models were performed using previously inferred African, European and Amerindian local genetic ancestry markers. Global African ancestry was associated with a lower AHI, higher SaO2 and shorter event duration. Admixture mapping analysis of the primary OSA traits identified local African ancestry at the chromosomal region 2q37 as genome-wide significantly associated with AHI (P < 5.7 × 10-5), and European and Amerindian ancestries at 18q21 suggestively associated with both AHI and percentage time SaO2 < 90% (P < 10-3). Follow-up joint ancestry-SNP association analyses identified novel variants in ferrochelatase (FECH), significantly associated with AHI and percentage time SaO2 < 90% after adjusting for multiple tests (P < 8 × 10-6). These signals contributed to the admixture mapping associations and were replicated in independent cohorts. In this first admixture mapping study of OSA, novel associations with variants in the iron/heme metabolism pathway suggest a role for iron in influencing respiratory traits underlying OSA.

Albuminuria, Lung Function Decline, and Risk of Incident Chronic Obstructive Pulmonary Disease. The NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Grams, Morgan E; Cassano, Patricia A; Jacobs, David R; Barr, R Graham; Burkart, Kristin M; Kalhan, Ravi; Kronmal, Richard; Loehr, Laura R; O'Connor, George T; Schwartz, Joseph E; et al. (Am J Respir Crit Care Med, 2019)
RATIONALE: Chronic lower respiratory diseases (CLRDs), including chronic obstructive pulmonary disease (COPD) and asthma, are the fourth leading cause of death. Prior studies suggest that albuminuria, a biomarker of endothelial injury, is increased in patients with COPD. OBJECTIVES: To test whether albuminuria was associated with lung function decline and incident CLRDs. METHODS: Six U.S. population-based cohorts were harmonized and pooled. Participants with prevalent clinical lung disease were excluded. Albuminuria (urine albumin-to-creatinine ratio) was measured in spot samples. Lung function was assessed by spirometry. Incident CLRD-related hospitalizations and deaths were classified via adjudication and/or administrative criteria. Mixed and proportional hazards models were used to test individual-level associations adjusted for age, height, weight, sex, race/ethnicity, education, birth year, cohort, smoking status, pack-years of smoking, renal function, hypertension, diabetes, and medications. MEASUREMENTS AND MAIN RESULTS: Among 10,961 participants with preserved lung function, mean age at albuminuria measurement was 60 years, 51% were never-smokers, median albuminuria was 5.6 mg/g, and mean FEV decline was 31.5 ml/yr. For each SD increase in log-transformed albuminuria, there was 2.81% greater FEV decline (95% confidence interval [CI], 0.86-4.76%; P = 0.0047), 11.02% greater FEV/FVC decline (95% CI, 4.43-17.62%; P = 0.0011), and 15% increased hazard of incident spirometry-defined moderate-to-severe COPD (95% CI, 2-31%, P = 0.0021). Each SD log-transformed albuminuria increased hazards of incident COPD-related hospitalization/mortality by 26% (95% CI, 18-34%, P < 0.0001) among 14,213 participants followed for events. Asthma events were not significantly associated. Associations persisted in participants without current smoking, diabetes, hypertension, or cardiovascular disease. CONCLUSIONS: Albuminuria was associated with greater lung function decline, incident spirometry-defined COPD, and incident COPD-related events in a U.S. population-based sample.

Assessment of the Relationship Between Genetic Determinants of Thyroid Function and Atrial Fibrillation: A Mendelian Randomization Study. - Ellervik, Christina; Roselli, Carolina; Christophersen, Ingrid E; Alonso, Alvaro; Pietzner, Maik; Sitlani, Collen M; Trompet, Stella; Arking, Dan E; Geelhoed, Bastiaan; Guo, Xiuqing; Kleber, Marcus E; Lin, Henry J; et al. (JAMA Cardiol, 2019)
Importance: Increased free thyroxine (FT4) and decreased thyrotropin are associated with increased risk of atrial fibrillation (AF) in observational studies, but direct involvement is unclear. Objective: To evaluate the potential direct involvement of thyroid traits on AF. Design, Setting, and Participants: Study-level mendelian randomization (MR) included 11 studies, and summary-level MR included 55 114 AF cases and 482 295 referents, all of European ancestry. Exposures: Genomewide significant variants were used as instruments for standardized FT4 and thyrotropin levels within the reference range, standardized triiodothyronine (FT3):FT4 ratio, hypothyroidism, standardized thyroid peroxidase antibody levels, and hyperthyroidism. Mendelian randomization used genetic risk scores in study-level analysis or individual single-nucleotide polymorphisms in 2-sample MR for the summary-level data. Main Outcomes and Measures: Prevalent and incident AF. Results: The study-level analysis included 7679 individuals with AF and 49 233 referents (mean age [standard error], 62 [3] years; 15 859 men [29.7%]). In study-level random-effects meta-analysis, the pooled hazard ratio of FT4 levels (nanograms per deciliter) for incident AF was 1.55 (95% CI, 1.09-2.20; P = .02; I2 = 76%) and the pooled odds ratio (OR) for prevalent AF was 2.80 (95% CI, 1.41-5.54; P = .003; I2 = 64%) in multivariable-adjusted analyses. The FT4 genetic risk score was associated with an increase in FT4 by 0.082 SD (standard error, 0.007; P < .001) but not with incident AF (risk ratio, 0.84; 95% CI, 0.62-1.14; P = .27) or prevalent AF (OR, 1.32; 95% CI, 0.64-2.73; P = .46). Similarly, in summary-level inverse-variance weighted random-effects MR, gene-based FT4 within the reference range was not associated with AF (OR, 1.01; 95% CI, 0.89-1.14; P = .88). However, gene-based increased FT3:FT4 ratio, increased thyrotropin within the reference range, and hypothyroidism were associated with AF with inverse-variance weighted random-effects OR of 1.33 (95% CI, 1.08-1.63; P = .006), 0.88 (95% CI, 0.84-0.92; P < .001), and 0.94 (95% CI, 0.90-0.99; P = .009), respectively, and robust to tests of horizontal pleiotropy. However, the subset of hypothyroidism single-nucleotide polymorphisms involved in autoimmunity and thyroid peroxidase antibodies levels were not associated with AF. Gene-based hyperthyroidism was associated with AF with MR-Egger OR of 1.31 (95% CI, 1.05-1.63; P = .02) with evidence of horizontal pleiotropy (P = .045). Conclusions and Relevance: Genetically increased FT3:FT4 ratio and hyperthyroidism, but not FT4 within the reference range, were associated with increased AF, and increased thyrotropin within the reference range and hypothyroidism were associated with decreased AF, supporting a pathway involving the pituitary-thyroid-cardiac axis.

{Association of dietary folate and vitamin B-12 intake with genome-wide DNA methylation in blood: a large-scale epigenome-wide association analysis in 5841 individuals - Mandaviya, P. R.; Joehanes, R.; Brody, J.; Castillo-Fernandez, J. E.; Dekkers, K. F.; Do, A. N.; Graff, M.; H?nninen, I. K.; Tanaka, T.; de Jonge, E. A. L.; Kiefte-de Jong, J. C.; Absher, D. M.; et al. (Am J Clin Nutr, 2019)
Folate and vitamin B-12 are essential micronutrients involved in the donation of methyl groups in cellular metabolism. However, associations between intake of these nutrients and genome-wide DNA methylation levels have not been studied comprehensively in humans.\ The aim of this study was to assess whether folate and/or vitamin B-12 intake are asssociated with genome-wide changes in DNA methylation in leukocytes.\ A large-scale epigenome-wide association study of folate and vitamin B-12 intake was performed on DNA from 5841 participants from 10 cohorts using Illumina 450k arrays. Folate and vitamin B-12 intakes were calculated from food-frequency questionnaires (FFQs). Continuous and categorical (low compared with high intake) linear regression mixed models were applied per cohort, controlling for confounders. A meta-analysis was performed to identify significant differentially methylated positions (DMPs) and regions (DMRs), and a pathway analysis was performed on the DMR annotated genes.\ The categorical model resulted in 6 DMPs, which are all negatively associated with folate intake, annotated to FAM64A, WRAP73, FRMD8, CUX1, and LCN8 genes, which have a role in cellular processes including centrosome localization, cell proliferation, and tumorigenesis. Regional analysis showed 74 folate-associated DMRs, of which 73 were negatively associated with folate intake. The most significant folate-associated DMR was a 400-base pair (bp) spanning region annotated to the LGALS3BP gene. In the categorical model, vitamin B-12 intake was associated with 29 DMRs annotated to 48 genes, of which the most significant was a 1100-bp spanning region annotated to the calcium-binding tyrosine phosphorylation-regulated gene (CABYR). Vitamin B-12 intake was not associated with DMPs.\ We identified novel epigenetic loci that are associated with folate and vitamin B-12 intake. Interestingly, we found a negative association between folate and DNA methylation. Replication of these methylation loci is necessary in future studies.

Association of variants in HTRA1 and NOTCH3 with MRI-defined extremes of cerebral small vessel disease in older subjects. - Mishra, Aniket; Chauhan, Ganesh; Violleau, Marie-Helene; Vojinovic, Dina; Jian, Xueqiu; Bis, Joshua C; Li, Shuo; Saba, Yasaman; Grenier-Boley, Benjamin; Yang, Qiong; Bartz, Traci M; Hofer, Edith; et al. (Brain, 2019)
We report a composite extreme phenotype design using distribution of white matter hyperintensities and brain infarcts in a population-based cohort of older persons for gene-mapping of cerebral small vessel disease. We demonstrate its application in the 3C-Dijon whole exome sequencing (WES) study (n = 1924, nWESextremes = 512), with both single variant and gene-based association tests. We used other population-based cohort studies participating in the CHARGE consortium for replication, using whole exome sequencing (nWES = 2,868, nWESextremes = 956) and genome-wide genotypes (nGW = 9924, nGWextremes = 3308). We restricted our study to candidate genes known to harbour mutations for Mendelian small vessel disease: NOTCH3, HTRA1, COL4A1, COL4A2 and TREX1. We identified significant associations of a common intronic variant in HTRA1, rs2293871 using single variant association testing (Pdiscovery = 8.21 × 10-5, Preplication = 5.25 × 10-3, Pcombined = 4.72 × 10-5) and of NOTCH3 using gene-based tests (Pdiscovery = 1.61 × 10-2, Preplication = 3.99 × 10-2, Pcombined = 5.31 × 10-3). Follow-up analysis identified significant association of rs2293871 with small vessel ischaemic stroke, and two blood expression quantitative trait loci of HTRA1 in linkage disequilibrium. Additionally, we identified two participants in the 3C-Dijon cohort (0.4%) carrying heterozygote genotypes at known pathogenic variants for familial small vessel disease within NOTCH3 and HTRA1. In conclusion, our proof-of-concept study provides strong evidence that using a novel composite MRI-derived phenotype for extremes of small vessel disease can facilitate the identification of genetic variants underlying small vessel disease, both common variants and those with rare and low frequency. The findings demonstrate shared mechanisms and a continuum between genes underlying Mendelian small vessel disease and those contributing to the common, multifactorial form of the disease.

Associations of autozygosity with a broad range of human phenotypes. - Clark, David W; Okada, Yukinori; Moore, Kristjan H S; Mason, Dan; Pirastu, Nicola; Gandin, Ilaria; Mattsson, Hannele; Barnes, Catriona L K; Lin, Kuang; Zhao, Jing Hua; Deelen, Patrick; Rohde, Rebecca; et al. (Nat Commun, 2019)
In many species, the offspring of related parents suffer reduced reproductive success, a phenomenon known as inbreeding depression. In humans, the importance of this effect has remained unclear, partly because reproduction between close relatives is both rare and frequently associated with confounding social factors. Here, using genomic inbreeding coefficients (F) for >1.4 million individuals, we show that F is significantly associated (p < 0.0005) with apparently deleterious changes in 32 out of 100 traits analysed. These changes are associated with runs of homozygosity (ROH), but not with common variant homozygosity, suggesting that genetic variants associated with inbreeding depression are predominantly rare. The effect on fertility is striking: F equivalent to the offspring of first cousins is associated with a 55% decrease [95% CI 44-66%] in the odds of having children. Finally, the effects of F are confirmed within full-sibling pairs, where the variation in F is independent of all environmental confounding.

Associations of variants In the hexokinase 1 and interleukin 18 receptor regions with oxyhemoglobin saturation during sleep. - Cade, Brian E; Chen, Han; Stilp, Adrienne M; Louie, Tin; Ancoli-Israel, Sonia; Arens, Raanan; Barfield, Richard; Below, Jennifer E; Cai, Jianwen; Conomos, Matthew P; Evans, Daniel S; Frazier-Wood, Alexis C; et al. (PLoS Genet, 2019)
Sleep disordered breathing (SDB)-related overnight hypoxemia is associated with cardiometabolic disease and other comorbidities. Understanding the genetic bases for variations in nocturnal hypoxemia may help understand mechanisms influencing oxygenation and SDB-related mortality. We conducted genome-wide association tests across 10 cohorts and 4 populations to identify genetic variants associated with three correlated measures of overnight oxyhemoglobin saturation: average and minimum oxyhemoglobin saturation during sleep and the percent of sleep with oxyhemoglobin saturation under 90%. The discovery sample consisted of 8,326 individuals. Variants with p < 1 × 10(-6) were analyzed in a replication group of 14,410 individuals. We identified 3 significantly associated regions, including 2 regions in multi-ethnic analyses (2q12, 10q22). SNPs in the 2q12 region associated with minimum SpO2 (rs78136548 p = 2.70 × 10(-10)). SNPs at 10q22 were associated with all three traits including average SpO2 (rs72805692 p = 4.58 × 10(-8)). SNPs in both regions were associated in over 20,000 individuals and are supported by prior associations or functional evidence. Four additional significant regions were detected in secondary sex-stratified and combined discovery and replication analyses, including a region overlapping Reelin, a known marker of respiratory complex neurons.These are the first genome-wide significant findings reported for oxyhemoglobin saturation during sleep, a phenotype of high clinical interest. Our replicated associations with HK1 and IL18R1 suggest that variants in inflammatory pathways, such as the biologically-plausible NLRP3 inflammasome, may contribute to nocturnal hypoxemia.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cell Adhesion Molecules, Neuronal; Computational Biology; Extracellular Matrix Proteins; Female; Gene Regulatory Networks; Genetic Variation; Genome-Wide Association Study; Hexokinase; Humans; Hypoxia; Interleukin-18 Receptor alpha Subunit; Male; Middle Aged; Nerve Tissue Proteins; NLR Family, Pyrin Domain-Containing 3 Protein; Oxygen; Oxyhemoglobins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Serine Endopeptidases; Sleep; Sleep Apnea Syndromes; Young Adult

Biomarkers of Dietary Omega-6 Fatty Acids and Incident Cardiovascular Disease and Mortality. - Marklund, Matti; Wu, Jason H Y; Imamura, Fumiaki; Del Gobbo, Liana C; Fretts, Amanda; de Goede, Janette; Shi, Peilin; Tintle, Nathan; Wennberg, Maria; Aslibekyan, Stella; Chen, Tzu-An; de Oliveira Otto, Marcia C; et al. (Circulation, 2019)
BACKGROUND: Global dietary recommendations for and cardiovascular effects of linoleic acid, the major dietary omega-6 fatty acid, and its major metabolite, arachidonic acid, remain controversial. To address this uncertainty and inform international recommendations, we evaluated how in vivo circulating and tissue levels of linoleic acid (LA) and arachidonic acid (AA) relate to incident cardiovascular disease (CVD) across multiple international studies. METHODS: We performed harmonized, de novo, individual-level analyses in a global consortium of 30 prospective observational studies from 13 countries. Multivariable-adjusted associations of circulating and adipose tissue LA and AA biomarkers with incident total CVD and subtypes (coronary heart disease, ischemic stroke, cardiovascular mortality) were investigated according to a prespecified analytic plan. Levels of LA and AA, measured as the percentage of total fatty acids, were evaluated linearly according to their interquintile range (ie, the range between the midpoint of the first and fifth quintiles), and categorically by quintiles. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Heterogeneity was explored by age, sex, race, diabetes mellitus, statin use, aspirin use, omega-3 levels, and fatty acid desaturase 1 genotype (when available). RESULTS: In 30 prospective studies with medians of follow-up ranging 2.5 to 31.9 years, 15 198 incident cardiovascular events occurred among 68 659 participants. Higher levels of LA were significantly associated with lower risks of total CVD, cardiovascular mortality, and ischemic stroke, with hazard ratios per interquintile range of 0.93 (95% CI, 0.88-0.99), 0.78 (0.70-0.85), and 0.88 (0.79-0.98), respectively, and nonsignificantly with lower coronary heart disease risk (0.94; 0.88-1.00). Relationships were similar for LA evaluated across quintiles. AA levels were not associated with higher risk of cardiovascular outcomes; in a comparison of extreme quintiles, higher levels were associated with lower risk of total CVD (0.92; 0.86-0.99). No consistent heterogeneity by population subgroups was identified in the observed relationships. CONCLUSIONS: In pooled global analyses, higher in vivo circulating and tissue levels of LA and possibly AA were associated with lower risk of major cardiovascular events. These results support a favorable role for LA in CVD prevention.

Blood Leukocyte DNA Methylation Predicts Risk of Future Myocardial Infarction and Coronary Heart Disease. - Agha, Golareh; Mendelson, Michael M; Ward-Caviness, Cavin K; Joehanes, Roby; Huan, Tianxiao; Gondalia, Rahul; Salfati, Elias; Brody, Jennifer A; Fiorito, Giovanni; Bressler, Jan; Chen, Brian H; Ligthart, Symen; et al. (Circulation, 2019)
BACKGROUND: DNA methylation is implicated in coronary heart disease (CHD), but current evidence is based on small, cross-sectional studies. We examined blood DNA methylation in relation to incident CHD across multiple prospective cohorts. METHODS: Nine population-based cohorts from the United States and Europe profiled epigenome-wide blood leukocyte DNA methylation using the Illumina Infinium 450k microarray, and prospectively ascertained CHD events including coronary insufficiency/unstable angina, recognized myocardial infarction, coronary revascularization, and coronary death. Cohorts conducted race-specific analyses adjusted for age, sex, smoking, education, body mass index, blood cell type proportions, and technical variables. We conducted fixed-effect meta-analyses across cohorts. RESULTS: Among 11 461 individuals (mean age 64 years, 67% women, 35% African American) free of CHD at baseline, 1895 developed CHD during a mean follow-up of 11.2 years. Methylation levels at 52 CpG (cytosine-phosphate-guanine) sites were associated with incident CHD or myocardial infarction (false discovery rate<0.05). These CpGs map to genes with key roles in calcium regulation (ATP2B2, CASR, GUCA1B, HPCAL1), and genes identified in genome- and epigenome-wide studies of serum calcium (CASR), serum calcium-related risk of CHD (CASR), coronary artery calcified plaque (PTPRN2), and kidney function (CDH23, HPCAL1), among others. Mendelian randomization analyses supported a causal effect of DNA methylation on incident CHD; these CpGs map to active regulatory regions proximal to long non-coding RNA transcripts. CONCLUSION: Methylation of blood-derived DNA is associated with risk of future CHD across diverse populations and may serve as an informative tool for gaining further insight on the development of CHD.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; CpG Islands; DNA Methylation; Europe; Female; Genome-Wide Association Study; Humans; Incidence; Leukocytes; Male; Middle Aged; Myocardial Infarction; Population Groups; Prognosis; Prospective Studies; Risk; United States

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Discriminative Accuracy of FEV1:FVC Thresholds for COPD-Related Hospitalization and Mortality. - Bhatt, Surya P; Balte, Pallavi P; Schwartz, Joseph E; Cassano, Patricia A; Couper, David; Jacobs, David R; Kalhan, Ravi; O'Connor, George T; Yende, Sachin; Sanders, Jason L; Umans, Jason G; Dransfield, Mark T; et al. (JAMA, 2019)
Importance: According to numerous current guidelines, the diagnosis of chronic obstructive pulmonary disease (COPD) requires a ratio of the forced expiratory volume in the first second to the forced vital capacity (FEV1:FVC) of less than 0.70, yet this fixed threshold is based on expert opinion and remains controversial. Objective: To determine the discriminative accuracy of various FEV1:FVC fixed thresholds for predicting COPD-related hospitalization and mortality. Design, Setting, and Participants: The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study harmonized and pooled data from 4 US general population-based cohorts (Atherosclerosis Risk in Communities Study; Cardiovascular Health Study; Health, Aging, and Body Composition Study; and Multi-Ethnic Study of Atherosclerosis). Participants aged 45 to 102 years were enrolled from 1987 to 2000 and received follow-up longitudinally through 2016. Exposures: Presence of airflow obstruction, which was defined by a baseline FEV1:FVC less than a range of fixed thresholds (0.75 to 0.65) or less than the lower limit of normal as defined by Global Lung Initiative reference equations (LLN). Main Outcomes and Measures: The primary outcome was a composite of COPD hospitalization and COPD-related mortality, defined by adjudication or administrative criteria. The optimal fixed FEV1:FVC threshold was defined by the best discrimination for these COPD-related events as indexed using the Harrell C statistic from unadjusted Cox proportional hazards models. Differences in C statistics were compared with respect to less than 0.70 and less than LLN thresholds using a nonparametric approach. Results: Among 24 207 adults in the pooled cohort (mean [SD] age at enrollment, 63 [10.5] years; 12 990 [54%] women; 16 794 [69%] non-Hispanic white; 15 181 [63%] ever smokers), complete follow-up was available for 11 077 (77%) at 15 years. During a median follow-up of 15 years, 3925 participants experienced COPD-related events over 340 757 person-years of follow-up (incidence density rate, 11.5 per 1000 person-years), including 3563 COPD-related hospitalizations and 447 COPD-related deaths. With respect to discrimination of COPD-related events, the optimal fixed threshold (0.71; C statistic for optimal fixed threshold, 0.696) was not significantly different from the 0.70 threshold (difference, 0.001 [95% CI, -0.002 to 0.004]) but was more accurate than the LLN threshold (difference, 0.034 [95% CI, 0.028 to 0.041]). The 0.70 threshold provided optimal discrimination in the subgroup analysis of ever smokers and in adjusted models. Conclusions and Relevance: Defining airflow obstruction as FEV1:FVC less than 0.70 provided discrimination of COPD-related hospitalization and mortality that was not significantly different or was more accurate than other fixed thresholds and the LLN. These results support the use of FEV1:FVC less than 0.70 to identify individuals at risk of clinically significant COPD.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Forced Expiratory Volume; Hospitalization; Humans; Male; Middle Aged; Prognosis; Proportional Hazards Models; Pulmonary Disease, Chronic Obstructive; Risk Assessment; Vital Capacity

Disentangling the genetics of lean mass. - Karasik, David; Zillikens, M Carola; Hsu, Yi-Hsiang; Aghdassi, Ali; Åkesson, Kristina; Amin, Najaf; Barroso, Inês; Bennett, David A; Bertram, Lars; Bochud, Murielle; Borecki, Ingrid B; Broer, Linda; et al. (Am J Clin Nutr, 2019)
Background: Lean body mass (LM) plays an important role in mobility and metabolic function. We previously identified five loci associated with LM adjusted for fat mass in kilograms. Such an adjustment may reduce the power to identify genetic signals having an association with both lean mass and fat mass. Objectives: To determine the impact of different fat mass adjustments on genetic architecture of LM and identify additional LM loci. Methods: We performed genome-wide association analyses for whole-body LM (20 cohorts of European ancestry with n = 38,292) measured using dual-energy X-ray absorptiometry) or bioelectrical impedance analysis, adjusted for sex, age, age2, and height with or without fat mass adjustments (Model 1 no fat adjustment; Model 2 adjustment for fat mass as a percentage of body mass; Model 3 adjustment for fat mass in kilograms). Results: Seven single-nucleotide polymorphisms (SNPs) in separate loci, including one novel LM locus (TNRC6B), were successfully replicated in an additional 47,227 individuals from 29 cohorts. Based on the strengths of the associations in Model 1 vs Model 3, we divided the LM loci into those with an effect on both lean mass and fat mass in the same direction and refer to those as "sumo wrestler" loci (FTO and MC4R). In contrast, loci with an impact specifically on LM were termed "body builder" loci (VCAN and ADAMTSL3). Using existing available genome-wide association study databases, LM increasing alleles of SNPs in sumo wrestler loci were associated with an adverse metabolic profile, whereas LM increasing alleles of SNPs in "body builder" loci were associated with metabolic protection. Conclusions: In conclusion, we identified one novel LM locus (TNRC6B). Our results suggest that a genetically determined increase in lean mass might exert either harmful or protective effects on metabolic traits, depending on its relation to fat mass.

Epigenome-wide association analysis of daytime sleepiness in the Multi-Ethnic Study of Atherosclerosis reveals African-American-specific associations. - Barfield, Richard; Wang, Heming; Liu, Yongmei; Brody, Jennifer A; Swenson, Brenton; Li, Ruitong; Bartz, Traci M; Sotoodehnia, Nona; Chen, Yii-der I; Cade, Brian E; Chen, Han; Patel, Sanjay R; et al. (Sleep, 2019)
STUDY OBJECTIVES: Daytime sleepiness is a consequence of inadequate sleep, sleep-wake control disorder, or other medical conditions. Population variability in prevalence of daytime sleepiness is likely due to genetic and biological factors as well as social and environmental influences. DNA methylation (DNAm) potentially influences multiple health outcomes. Here, we explored the association between DNAm and daytime sleepiness quantified by the Epworth Sleepiness Scale (ESS). METHODS: We performed multi-ethnic and ethnic-specific epigenome-wide association studies for DNAm and ESS in the Multi-Ethnic Study of Atherosclerosis (MESA; n = 619) and the Cardiovascular Health Study (n = 483), with cross-study replication and meta-analysis. Genetic variants near ESS-associated DNAm were analyzed for methylation quantitative trait loci and followed with replication of genotype-sleepiness associations in the UK Biobank. RESULTS: In MESA only, we detected four DNAm-ESS associations: one across all race/ethnic groups; three in African-Americans (AA) only. Two of the MESA AA associations, in genes KCTD5 and RXRA, nominally replicated in CHS (p-value < 0.05). In the AA meta-analysis, we detected 14 DNAm-ESS associations (FDR q-value < 0.05, top association p-value = 4.26 × 10-8). Three DNAm sites mapped to genes (CPLX3, GFAP, and C7orf50) with biological relevance. We also found evidence for associations with DNAm sites in RAI1, a gene associated with sleep and circadian phenotypes. UK Biobank follow-up analyses detected SNPs in RAI1, RXRA, and CPLX3 with nominal sleepiness associations. CONCLUSIONS: We identified methylation sites in multiple genes possibly implicated in daytime sleepiness. Most significant DNAm-ESS associations were specific to AA. Future work is needed to identify mechanisms driving ancestry-specific methylation effects.

{Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies - Pennells, L.; Kaptoge, S.; Wood, A.; Sweeting, M.; Zhao, X.; White, I.; Burgess, S.; Willeit, P.; Bolton, T.; Moons, K. G. M.; van der Schouw, Y. T.; Selmer, R.; et al. (Eur Heart J, 2019)
There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied.\ Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged â‰¥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms.\ Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

{Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls - Flannick, J.; Mercader, J. M.; Fuchsberger, C.; Udler, M. S.; Mahajan, A.; Wessel, J.; Teslovich, T. M.; Caulkins, L.; Koesterer, R.; Barajas-Olmos, F.; Blackwell, T. W.; Boerwinkle, E.; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 Ã— 10-3) and candidate genes from knockout mice (P = 5.2 Ã— 10-3). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)
) with at least one obesity or lipid trait. Candidate genes include PRKAR2A, PTH1R, and HDAC9, which have been suggested to play roles in adipocyte differentiation or bone marrow adipose tissue. Taken together, these findings provide further insights into the processes that influence circulating adiponectin levels.

Genetic architecture of subcortical brain structures in 38,851 individuals. - Satizabal, Claudia L; Adams, Hieab H H; Hibar, Derrek P; White, Charles C; Knol, Maria J; Stein, Jason L; Scholz, Markus; Sargurupremraj, Muralidharan; Jahanshad, Neda; Roshchupkin, Gennady V; Smith, Albert V; Bis, Joshua C; et al. (Nat Genet, 2019)
Subcortical brain structures are integral to motion, consciousness, emotions and learning. We identified common genetic variation related to the volumes of the nucleus accumbens, amygdala, brainstem, caudate nucleus, globus pallidus, putamen and thalamus, using genome-wide association analyses in almost 40,000 individuals from CHARGE, ENIGMA and UK Biobank. We show that variability in subcortical volumes is heritable, and identify 48 significantly associated loci (40 novel at the time of analysis). Annotation of these loci by utilizing gene expression, methylation and neuropathological data identified 199 genes putatively implicated in neurodevelopment, synaptic signaling, axonal transport, apoptosis, inflammation/infection and susceptibility to neurological disorders. This set of genes is significantly enriched for Drosophila orthologs associated with neurodevelopmental phenotypes, suggesting evolutionarily conserved mechanisms. Our findings uncover novel biology and potential drug targets underlying brain development and disease.

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.

{Genome-wide association meta-analyses and fine-mapping elucidate pathways influencing albuminuria - Teumer, A.; Li, Y.; Ghasemi, S.; Prins, B. P.; Wuttke, M.; Hermle, T.; Giri, A.; Sieber, K. B.; Qiu, C.; Kirsten, H.; Tin, A.; Chu, A. Y.; et al. (Nat Commun, 2019)
Increased levels of the urinary albumin-to-creatinine ratio (UACR) are associated with higher risk of kidney disease progression and cardiovascular events, but underlying mechanisms are incompletely understood. Here, we conduct trans-ethnic (n = 564,257) and European-ancestry specific meta-analyses of genome-wide association studies of UACR, including ancestry- and diabetes-specific analyses, and identify 68 UACR-associated loci. Genetic correlation analyses and risk score associations in an independent electronic medical records database (n = 192,868) reveal connections with proteinuria, hyperlipidemia, gout, and hypertension. Fine-mapping and trans-Omics analyses with gene expression in 47 tissues and plasma protein levels implicate genes potentially operating through differential expression in kidney (including TGFB1, MUC1, PRKCI, and OAF), and allow coupling of UACR associations to altered plasma OAF concentrations. Knockdown of OAF and PRKCI orthologs in Drosophila nephrocytes reduces albumin endocytosis. Silencing fly PRKCI further impairs slit diaphragm formation. These results generate a priority list of genes and pathways for translational research to reduce albuminuria.

{A genome-wide association study identifies genetic loci associated with specific lobar brain volumes - van der Lee, S. J.; Knol, M. J.; Chauhan, G.; Satizabal, C. L.; Smith, A. V.; Hofer, E.; Bis, J. C.; Hibar, D. P.; Hilal, S.; van den Akker, E. B.; Arfanakis, K.; Bernard, M.; et al. (Commun Biol, 2019)
Brain lobar volumes are heritable but genetic studies are limited. We performed genome-wide association studies of frontal, occipital, parietal and temporal lobe volumes in 16,016 individuals, and replicated our findings in 8,789 individuals. We identified six genetic loci associated with specific lobar volumes independent of intracranial volume. Two loci, associated with occipital (6q22.32) and temporal lobe volume (12q14.3), were previously reported to associate with intracranial and hippocampal volume, respectively. We identified four loci previously unknown to affect brain volumes: 3q24 for parietal lobe volume, and 1q22, 4p16.3 and 14q23.1 for occipital lobe volume. The associated variants were located in regions enriched for histone modifications (DAAM1 and THBS3), or close to genes causing Mendelian brain-related diseases (ZIC4 and FGFRL1). No genetic overlap between lobar volumes and neurological or psychiatric diseases was observed. Our findings reveal part of the complex genetics underlying brain development and suggest a role for regulatory regions in determining brain volumes.

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

{Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group - Irvin, M. R.; Sitlani, C. M.; Floyd, J. S.; Psaty, B. M.; Bis, J. C.; Wiggins, K. L.; Whitsel, E. A.; Sturmer, T.; Stewart, J.; Raffield, L.; Sun, F.; Liu, C. T.; et al. (Am J Hypertens, 2019)
{Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described.\ We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP â‰¥ 140 mm Hg and/or diastolic BP â‰¥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931

Genomewide Association Study of Statin-Induced Myopathy in Patients Recruited Using the UK Clinical Practice Research Datalink. - Carr, Daniel F; Francis, Ben; Jorgensen, Andrea L; Zhang, Eunice; Chinoy, Hector; Heckbert, Susan R; Bis, Joshua C; Brody, Jennifer A; Floyd, James S; Psaty, Bruce M; Molokhia, Mariam; Lapeyre-Mestre, Maryse; et al. (Clin Pharmacol Ther, 2019)
Statins can be associated with myopathy. We have undertaken a genomewide association study (GWAS) to discover and validate genetic risk factors for statin-induced myopathy in a "real-world" setting. One hundred thirty-five patients with statin myopathy recruited via the UK Clinical Practice Research Datalink were genotyped using the Illumina OmniExpress Exome version 1.0 Bead Chip and compared with the Wellcome Trust Case-Control Consortium (n = 2,501). Nominally statistically significant single nucleotide polymorphism (SNP) signals in the GWAS (P < 5 × 10 ) were further evaluated in several independent cohorts (comprising 332 cases and 449 drug-tolerant controls). Only one (rs4149056/c.521C>T in the SLCO1B1 gene) SNP was genomewide significant in the severe myopathy (creatine kinase > 10 × upper limit of normal or rhabdomyolysis) group (P = 2.55 × 10 ; odds ratio 5.15; 95% confidence interval 3.13-8.45). The association with SLCO1B1 was present for several statins and replicated in the independent validation cohorts. The data highlight the role of SLCO1B1 c.521C>T SNP as a replicable genetic risk factor for statin myopathy. No other novel genetic risk factors with a similar effect size were identified.
Keywords: Adverse Drug Reaction Reporting Systems; Case-Control Studies; Databases, Factual; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Liver-Specific Organic Anion Transporter 1; Muscular Diseases; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Severity of Illness Index; United Kingdom

{Genome-Wide Association Transethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels - Sabater-Lleal, M.; Huffman, J. E.; de Vries, P. S.; Marten, J.; Mastrangelo, M. A.; Song, C.; Pankratz, N.; Ward-Caviness, C. K.; Yanek, L. R.; Trompet, S.; Delgado, G. E.; Guo, X.; et al. (Circulation, 2019)
Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF.\ We meta-analyzed genome-wide association results from 46 354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated ≈35 million imputed variants with natural log-transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events.\ We identified 13 novel genome-wide significant ( P≤2.5×10-8) associations, 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. Mendelian randomization suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk.\ The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-wide meta-analysis of variant-by-diuretic interactions as modulators of lipid traits in persons of European and African ancestry. - de Las Fuentes, L; Sung, Y J; Sitlani, C M; Avery, C L; Bartz, T M; Keyser, C de; Evans, D S; Li, X; Musani, S K; Ruiter, R; Smith, A V; Sun, F; et al. (Pharmacogenomics J, 2019)
Hypertension (HTN) is a significant risk factor for cardiovascular morbidity and mortality. Metabolic abnormalities, including adverse cholesterol and triglycerides (TG) profiles, are frequent comorbid findings with HTN and contribute to cardiovascular disease. Diuretics, which are used to treat HTN and heart failure, have been associated with worsening of fasting lipid concentrations. Genome-wide meta-analyses with 39,710 European-ancestry (EA) individuals and 9925 African-ancestry (AA) individuals were performed to identify genetic variants that modify the effect of loop or thiazide diuretic use on blood lipid concentrations. Both longitudinal and cross sectional data were used to compute cohort-specific interaction results, which were then combined through meta-analysis in each ancestry. These ancestry-specific results were further combined through trans-ancestry meta-analysis. Analysis of EA data identified two genome-wide significant (p < 5 × 10) loci with single nucleotide variant (SNV)-loop diuretic interaction on TG concentrations (including COL11A1). Analysis of AA data identified one genome-wide significant locus adjacent to BMP2 with SNV-loop diuretic interaction on TG concentrations. Trans-ancestry analysis strengthened evidence of association for SNV-loop diuretic interaction at two loci (KIAA1217 and BAALC). There were few significant SNV-thiazide diuretic interaction associations on TG concentrations and for either diuretic on cholesterol concentrations. Several promising loci were identified that may implicate biologic pathways that contribute to adverse metabolic side effects from diuretic therapy.

Genomic and transcriptomic association studies identify 16 novel susceptibility loci for venous thromboembolism. - Lindström, Sara; Wang, Lu; Smith, Erin N; Gordon, William; van Hylckama Vlieg, Astrid; de Andrade, Mariza; Brody, Jennifer A; Pattee, Jack W; Haessler, Jeffrey; Brumpton, Ben M; Chasman, Daniel I; Suchon, Pierre; et al. (Blood, 2019)
Venous thromboembolism (VTE) is a significant contributor to morbidity and mortality. To advance our understanding of the biology contributing to VTE, we conducted a genome-wide association study (GWAS) of VTE and a transcriptome-wide association study (TWAS) based on imputed gene expression from whole blood and liver. We meta-analyzed GWAS data from 18 studies for 30 234 VTE cases and 172 122 controls and assessed the association between 12 923 718 genetic variants and VTE. We generated variant prediction scores of gene expression from whole blood and liver tissue and assessed them for association with VTE. Mendelian randomization analyses were conducted for traits genetically associated with novel VTE loci. We identified 34 independent genetic signals for VTE risk from GWAS meta-analysis, of which 14 are newly reported associations. This included 11 newly associated genetic loci (C1orf198, PLEK, OSMR-AS1, NUGGC/SCARA5, GRK5, MPHOSPH9, ARID4A, PLCG2, SMG6, EIF5A, and STX10) of which 6 replicated, and 3 new independent signals in 3 known genes. Further, TWAS identified 5 additional genetic loci with imputed gene expression levels differing between cases and controls in whole blood (SH2B3, SPSB1, RP11-747H7.3, RP4-737E23.2) and in liver (ERAP1). At some GWAS loci, we found suggestive evidence that the VTE association signal for novel and previously known regions colocalized with expression quantitative trait locus signals. Mendelian randomization analyses suggested that blood traits may contribute to the underlying risk of VTE. To conclude, we identified 16 novel susceptibility loci for VTE; for some loci, the association signals are likely mediated through gene expression of nearby genes.

Genomics of 1 million parent lifespans implicates novel pathways and common diseases and distinguishes survival chances. - Timmers, Paul Rhj; Mounier, Ninon; Läll, Kristi; Fischer, Krista; Ning, Zheng; Feng, Xiao; Bretherick, Andrew D; Clark, David W; Agbessi, M; Ahsan, H; Alves, I; Andiappan, A; et al. (Elife, 2019)
We use a genome-wide association of 1 million parental lifespans of genotyped subjects and data on mortality risk factors to validate previously unreplicated findings near , , , , , and 13q21.31, and identify and replicate novel findings near , , and . We also validate previous findings near 5q33.3/ and , whilst finding contradictory evidence at other loci. Gene set and cell-specific analyses show that expression in foetal brain cells and adult dorsolateral prefrontal cortex is enriched for lifespan variation, as are gene pathways involving lipid proteins and homeostasis, vesicle-mediated transport, and synaptic function. Individual genetic variants that increase dementia, cardiovascular disease, and lung cancer - but not other cancers - explain the most variance. Resulting polygenic scores show a mean lifespan difference of around five years of life across the deciles. Editorial note: This article has been through an editorial process in which the authors decide how to respond to the issues raised during peer review. The Reviewing Editor's assessment is that all the issues have been addressed (see decision letter).

High-dimensional longitudinal classification with the multinomial fused lasso. - Adhikari, Samrachana; Lecci, Fabrizio; Becker, James T; Junker, Brian W; Kuller, Lewis H; Lopez, Oscar L; Tibshirani, Ryan J (Stat Med, 2019)
We study regularized estimation in high-dimensional longitudinal classification problems, using the lasso and fused lasso regularizers. The constructed coefficient estimates are piecewise constant across the time dimension in the longitudinal problem, with adaptively selected change points (break points). We present an efficient algorithm for computing such estimates, based on proximal gradient descent. We apply our proposed technique to a longitudinal data set on Alzheimer's disease from the Cardiovascular Health Study Cognition Study. Using data analysis and a simulation study, we motivate and demonstrate several practical considerations such as the selection of tuning parameters and the assessment of model stability. While race, gender, vascular and heart disease, lack of caregivers, and deterioration of learning and memory are all important predictors of dementia, we also find that these risk factors become more relevant in the later stages of life.

{The impact of APOE genotype on survival: Results of 38,537 participants from six population-based cohorts (E2-CHARGE) - Wolters, F. J.; Yang, Q.; Biggs, M. L.; Jakobsdottir, J.; Li, S.; Evans, D. S.; Bis, J. C.; Harris, T. B.; Vasan, R. S.; Zilhao, N. R.; Ghanbari, M.; Ikram, M. A.; et al. (PLoS One, 2019)
Apolipoprotein E is a glycoprotein best known as a mediator and regulator of lipid transport and uptake. The APOE-Îµ4 allele has long been associated with increased risks of Alzheimer's disease and mortality, but the effect of the less prevalent APOE-Îµ2 allele on diseases in the elderly and survival remains elusive.\ We aggregated data of 38,537 individuals of European ancestry (mean age 65.5 years; 55.6% women) from six population-based cohort studies (Rotterdam Study, AGES-Reykjavik Study, Cardiovascular Health Study, Health-ABC Study, and the family-based Framingham Heart Study and Long Life Family Study) to determine the association of APOE, and in particular APOE-Îµ2, with survival in the population.\ During a mean follow-up of 11.7 years, 17,021 individuals died. Compared with homozygous APOE-Îµ3 carriers, APOE-Îµ2 carriers were at lower risk of death (hazard ratio,95% confidence interval: 0.94,0.90-0.99; P = 1.1*10-2), whereas APOE-Îµ4 carriers were at increased risk of death (HR 1.17,1.12-1.21; P = 2.8*10-16). APOE was associated with mortality risk in a dose-dependent manner, with risk estimates lowest for homozygous APOE-Îµ2 (HR 0.89,0.74-1.08), and highest for homozygous APOE-Îµ4 (HR 1.52,1.37-1.70). After censoring for dementia, effect estimates remained similar for APOE-Îµ2 (HR 0.95,0.90-1.01), but attenuated for APOE-Îµ4 (HR 1.07,1.01-1.12). Results were broadly similar across cohorts, and did not differ by age or sex. APOE genotype was associated with baseline lipid fractions (e.g. mean difference(95%CI) in LDL(mg/dL) for Îµ2 versus Îµ33: -17.1(-18.1-16.0), and Îµ4 versus Îµ33: +5.7(4.8;6.5)), but the association between APOE and mortality was unaltered after adjustment for baseline LDL or cardiovascular disease. Given the European ancestry of the study population, results may not apply to other ethnicities.\ Compared with APOE-Îµ3, APOE-Îµ2 is associated with prolonged survival, whereas mortality risk is increased for APOE-Îµ4 carriers. Further collaborative efforts are needed to unravel the role of APOE and in particular APOE-Îµ2 in health and disease.

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.

A large-scale exome array analysis of venous thromboembolism. - Lindström, Sara; Brody, Jennifer A; Turman, Constance; Germain, Marine; Bartz, Traci M; Smith, Erin N; Chen, Ming-Huei; Puurunen, Marja; Chasman, Daniel; Hassler, Jeffrey; Pankratz, Nathan; Basu, Saonli; et al. (Genet Epidemiol, 2019)
Although recent Genome-Wide Association Studies have identified novel associations for common variants, there has been no comprehensive exome-wide search for low-frequency variants that affect the risk of venous thromboembolism (VTE). We conducted a meta-analysis of 11 studies comprising 8,332 cases and 16,087 controls of European ancestry and 382 cases and 1,476 controls of African American ancestry genotyped with the Illumina HumanExome BeadChip. We used the seqMeta package in R to conduct single variant and gene-based rare variant tests. In the single variant analysis, we limited our analysis to the 64,794 variants with at least 40 minor alleles across studies (minor allele frequency [MAF] ~0.08%). We confirmed associations with previously identified VTE loci, including ABO, F5, F11, and FGA. After adjusting for multiple testing, we observed no novel significant findings in single variant or gene-based analysis. Given our sample size, we had greater than 80% power to detect minimum odds ratios greater than 1.5 and 1.8 for a single variant with MAF of 0.01 and 0.005, respectively. Larger studies and sequence data may be needed to identify novel low-frequency and rare variants associated with VTE risk.

{Low thyroid function is not associated with an accelerated deterioration in renal function - Meuwese, C. L.; van Diepen, M.; Cappola, A. R.; Sarnak, M. J.; Shlipak, M. G.; Bauer, D. C.; Fried, L. P.; Iacoviello, M.; Vaes, B.; Degryse, J.; Khaw, K. T.; Luben, R. N.; et al. (Nephrol Dial Transplant, 2019)
Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups.\ Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models.\ A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function.\ Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

Mendelian randomization evaluation of causal effects of fibrinogen on incident coronary heart disease. - Ward-Caviness, Cavin K; de Vries, Paul S; Wiggins, Kerri L; Huffman, Jennifer E; Yanek, Lisa R; Bielak, Lawrence F; Giulianini, Franco; Guo, Xiuqing; Kleber, Marcus E; Kacprowski, Tim; Groß, Stefan; Petersman, Astrid; et al. (PLoS One, 2019)
BACKGROUND: Fibrinogen is an essential hemostatic factor and cardiovascular disease risk factor. Early attempts at evaluating the causal effect of fibrinogen on coronary heart disease (CHD) and myocardial infraction (MI) using Mendelian randomization (MR) used single variant approaches, and did not take advantage of recent genome-wide association studies (GWAS) or multi-variant, pleiotropy robust MR methodologies. METHODS AND FINDINGS: We evaluated evidence for a causal effect of fibrinogen on both CHD and MI using MR. We used both an allele score approach and pleiotropy robust MR models. The allele score was composed of 38 fibrinogen-associated variants from recent GWAS. Initial analyses using the allele score used a meta-analysis of 11 European-ancestry prospective cohorts, free of CHD and MI at baseline, to examine incidence CHD and MI. We also applied 2 sample MR methods with data from a prevalent CHD and MI GWAS. Results are given in terms of the hazard ratio (HR) or odds ratio (OR), depending on the study design, and associated 95% confidence interval (CI). In single variant analyses no causal effect of fibrinogen on CHD or MI was observed. In multi-variant analyses using incidence CHD cases and the allele score approach, the estimated causal effect (HR) of a 1 g/L higher fibrinogen concentration was 1.62 (CI = 1.12, 2.36) when using incident cases and the allele score approach. In 2 sample MR analyses that accounted for pleiotropy, the causal estimate (OR) was reduced to 1.18 (CI = 0.98, 1.42) and 1.09 (CI = 0.89, 1.33) in the 2 most precise (smallest CI) models, out of 4 models evaluated. In the 2 sample MR analyses for MI, there was only very weak evidence of a causal effect in only 1 out of 4 models. CONCLUSIONS: A small causal effect of fibrinogen on CHD is observed using multi-variant MR approaches which account for pleiotropy, but not single variant MR approaches. Taken together, results indicate that even with large sample sizes and multi-variant approaches MR analyses still cannot exclude the null when estimating the causal effect of fibrinogen on CHD, but that any potential causal effect is likely to be much smaller than observed in epidemiological studies.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
Human longevity is heritable, but genome-wide association (GWA) studies have had limited success. Here, we perform two meta-analyses of GWA studies of a rigorous longevity phenotype definition including 11,262/3484 cases surviving at or beyond the age corresponding to the 90th/99th survival percentile, respectively, and 25,483 controls whose age at death or at last contact was at or below the age corresponding to the 60th survival percentile. Consistent with previous reports, rs429358 (apolipoprotein E (ApoE) Îµ4) is associated with lower odds of surviving to the 90th and 99th percentile age, while rs7412 (ApoE Îµ2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

Multi-Ancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
An individual's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multi-ancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in Stage 1 (genome-wide discovery) and 66 studies in Stage 2 (focused follow-up), for a total of 394,584 individuals from five ancestry groups. Genetic main and interaction effects were jointly assessed by a 2 degrees of freedom (DF) test, and a 1 DF test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in Stage 1 and were evaluated in Stage 2, followed by combined analyses of Stage 1 and Stage 2. In the combined analysis of Stage 1 and Stage 2, 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2 DF tests, of which 18 were novel. No genome-wide significant associations were found testing the interaction effect alone. The novel loci included several genes (PCSK5, VEGFB, and A1CF) with a putative role in lipid metabolism based on existing evidence from cellular and experimental models.

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.

{A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure - Sung, Y. J.; de Las Fuentes, L.; Winkler, T. W.; Chasman, D. I.; Bentley, A. R.; Kraja, A. T.; Ntalla, I.; Warren, H. R.; Guo, X.; Schwander, K.; Manning, A. K.; Brown, M. R.; et al. (Hum. Mol. Genet., 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 Ã— 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic Americans; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Young Adult

Multiethnic Genome-Wide Association Study of Diabetic Retinopathy Using Liability Threshold Modeling of Duration of Diabetes and Glycemic Control. - Pollack, Samuela; Igo, Robert P; Jensen, Richard A; Christiansen, Mark; Li, Xiaohui; Cheng, Ching-Yu; Ng, Maggie C Y; Smith, Albert V; Rossin, Elizabeth J; Segrè, Ayellet V; Davoudi, Samaneh; Tan, Gavin S; et al. (Diabetes, 2019)
To identify genetic variants associated with diabetic retinopathy (DR), we performed a large multiethnic genome-wide association study. Discovery included eight European cohorts ( = 3,246) and seven African American cohorts ( = 2,611). We meta-analyzed across cohorts using inverse-variance weighting, with and without liability threshold modeling of glycemic control and duration of diabetes. Variants with a value <1 × 10 were investigated in replication cohorts that included 18,545 European, 16,453 Asian, and 2,710 Hispanic subjects. After correction for multiple testing, the C allele of rs142293996 in an intron of nuclear VCP-like () was associated with DR in European discovery cohorts ( = 2.1 × 10), but did not reach genome-wide significance after meta-analysis with replication cohorts. We applied the Disease Association Protein-Protein Link Evaluator (DAPPLE) to our discovery results to test for evidence of risk being spread across underlying molecular pathways. One protein-protein interaction network built from genes in regions associated with proliferative DR was found to have significant connectivity ( = 0.0009) and corroborated with gene set enrichment analyses. These findings suggest that genetic variation in as well as variation within a protein-protein interaction network that includes genes implicated in inflammation, may influence risk for DR.

{New alcohol-related genes suggest shared genetic mechanisms with neuropsychiatric disorders - Evangelou, E.; Gao, H.; Chu, C.; Ntritsos, G.; Blakeley, P.; Butts, A. R.; Pazoki, R.; Suzuki, H.; Koskeridis, F.; Yiorkas, A. M.; Karaman, I.; Elliott, J.; et al. (Nat Hum Behav, 2019)
Excessive alcohol consumption is one of the main causes of death and disability worldwide. Alcohol consumption is a heritable complex trait. Here we conducted a meta-analysis of genome-wide association studies of alcohol consumption (g d-1) from the UK Biobank, the Alcohol Genome-Wide Consortium and the Cohorts for Heart and Aging Research in Genomic Epidemiology Plus consortia, collecting data from 480,842 people of European descent to decipher the genetic architecture of alcohol intake. We identified 46 new common loci and investigated their potential functional importance using magnetic resonance imaging data and gene expression studies. We identify genetic pathways associated with alcohol consumption and suggest genetic mechanisms that are shared with neuropsychiatric disorders such as schizophrenia.

No causal effects of serum urate levels on the risk of chronic kidney disease: A Mendelian randomization study. - Jordan, Daniel M; Choi, Hyon K; Verbanck, Marie; Topless, Ruth; Won, Hong-Hee; Nadkarni, Girish; Merriman, Tony R; Do, Ron (PLoS Med, 2019)
BACKGROUND: Studies have shown strong positive associations between serum urate (SU) levels and chronic kidney disease (CKD) risk; however, whether the relation is causal remains uncertain. We evaluate whether genetic data are consistent with a causal impact of SU level on the risk of CKD and estimated glomerular filtration rate (eGFR). METHODS AND FINDINGS: We used Mendelian randomization (MR) methods to evaluate the presence of a causal effect. We used aggregated genome-wide association data (N = 110,347 for SU, N = 69,374 for gout, N = 133,413 for eGFR, N = 117,165 for CKD), electronic-medical-record-linked UK Biobank data (N = 335,212), and population-based cohorts (N = 13,425), all in individuals of European ancestry, for SU levels and CKD. Our MR analysis showed that SU has a causal effect on neither eGFR level nor CKD risk across all MR analyses (all P > 0.05). These null associations contrasted with our epidemiological association findings from the 4 population-based cohorts (change in eGFR level per 1-mg/dl [59.48 μmol/l] increase in SU: -1.99 ml/min/1.73 m2; 95% CI -2.86 to -1.11; P = 8.08 × 10(-6); odds ratio [OR] for CKD: 1.48; 95% CI 1.32 to 1.65; P = 1.52 × 10(-11)). In contrast, the same MR approaches showed that SU has a causal effect on the risk of gout (OR estimates ranging from 3.41 to 6.04 per 1-mg/dl increase in SU, all P < 10-3), which served as a positive control of our approach. Overall, our MR analysis had >99% power to detect a causal effect of SU level on the risk of CKD of the same magnitude as the observed epidemiological association between SU and CKD. Limitations of this study include the lifelong effect of a genetic perturbation not being the same as an acute perturbation, the inability to study non-European populations, and some sample overlap between the datasets used in the study. CONCLUSIONS: Evidence from our series of causal inference approaches using genetics does not support a causal effect of SU level on eGFR level or CKD risk. Reducing SU levels is unlikely to reduce the risk of CKD development.
Keywords: Adult; Age Factors; Female; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Male; Mendelian Randomization Analysis; Renal Insufficiency, Chronic; Sex Factors; Uric Acid; Young Adult

{Omega-3 Fatty Acids and Genome-Wide Interaction Analyses Reveal DPP10-Pulmonary Function Association - Xu, J.; Gaddis, N. C.; Bartz, T. M.; Hou, R.; Manichaikul, A. W.; Pankratz, N.; Smith, A. V.; Sun, F.; Terzikhan, N.; Markunas, C. A.; Patchen, B. K.; Schu, M.; et al. (Am J Respir Crit Care Med, 2019)
Omega-3 polyunsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health.\ To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility.\ Associations of n-3 PUFA biomarkers (α-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (FEV1, FVC, and FEV1/FVC) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N = 16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N = 11,962) and replicated in one cohort (N = 1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of SNP associations and their interactions with n-3 PUFAs.\ DPA and DHA were positively associated with FEV1 and FVC (P < 0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P2df = 9.4 × 10-9 across discovery and replication cohorts). The rs11693320-A allele (frequency, ∼80%) was associated with lower FVC (PSNP = 2.1 × 10-9; βSNP = -161.0 ml), and the association was attenuated by higher DHA levels (PSNP×DHA interaction = 2.1 × 10-7; βSNP×DHA interaction = 36.2 ml).\ We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

Plasma Ceramides and Sphingomyelins in Relation to Heart Failure Risk. - Lemaitre, Rozenn N; Jensen, Paul N; Hoofnagle, Andrew; McKnight, Barbara; Fretts, Amanda M; King, Irena B; Siscovick, David S; Psaty, Bruce M; Heckbert, Susan R; Mozaffarian, Dariush; Sotoodehnia, Nona (Circ Heart Fail, 2019)
BACKGROUND: Ceramides exhibit multiple biological activities that may influence the pathophysiology of heart failure. These activities may be influenced by the saturated fatty acid carried by the ceramide (Cer). However, the associations of different circulating Cer species, and their sphingomyelin (SM) precursors, with heart failure have received limited attention. METHODS AND RESULTS: We studied the associations of plasma Cer and SM species with incident heart failure in the Cardiovascular Health Study. We examined 8 species: Cer and SM with palmitic acid (Cer-16 and SM-16), species with arachidic acid (Cer-20 and SM-20), species with behenic acid (Cer-22 and SM-22), and species with lignoceric acid (Cer-24 and SM-24). During a median follow-up of 9.4 years, we identified 1179 cases of incident heart failure among 4249 study participants. In Cox regression analyses adjusted for risk factors, higher levels of Cer-16 and SM-16 were associated with higher risk of incident heart failure (hazard ratio for one SD increase:1.25 [95% CI, 1.16-1.36] and 1.28 [1.18-1.40], respectively). In contrast, higher levels of Cer-22 were associated with lower risk of heart failure in multivariable analyses further adjusted for Cer-16 (hazard ratio, 0.85 [0.78-0.92]); and higher levels of SM-20, SM-22 and SM-24 were associated with lower risk of heart failure in analyses further adjusted for SM-16 (hazard ratios, 0.83 [0.77-0.90], 0.81 [0.75-0.88], and 0.83 [0.77-0.90], respectively). No statistically significant interactions with age, sex, black race, body mass index, or baseline coronary heart disease were detected. Similar associations were observed for heart failure with preserved (n=529) or reduced (n=348) ejection fraction. CONCLUSIONS: This study shows associations of higher plasma levels of Cer-16 and SM-16 with increased risk of heart failure and higher levels of Cer-22, SM-20, SM-22, and SM-24 with decreased risk of heart failure. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00005133.

{Quality of dietary fat and genetic risk of type 2 diabetes: individual participant data meta-analysis - Merino, J.; Guasch-Ferr?, M.; Ellervik, C.; Dashti, H. S.; Sharp, S. J.; Wu, P.; Overvad, K.; Sarnowski, C.; Kuokkanen, M.; Lemaitre, R. N.; Justice, A. E.; Ericson, U.; et al. (BMJ, 2019)
{To investigate whether the genetic burden of type 2 diabetes modifies the association between the quality of dietary fat and the incidence of type 2 diabetes.\ Individual participant data meta-analysis.\ Eligible prospective cohort studies were systematically sourced from studies published between January 1970 and February 2017 through electronic searches in major medical databases (Medline, Embase, and Scopus) and discussion with investigators.\ Data from cohort studies or multicohort consortia with available genome-wide genetic data and information about the quality of dietary fat and the incidence of type 2 diabetes in participants of European descent was sought. Prospective cohorts that had accrued five or more years of follow-up were included. The type 2 diabetes genetic risk profile was characterized by a 68-variant polygenic risk score weighted by published effect sizes. Diet was recorded by using validated cohort-specific dietary assessment tools. Outcome measures were summary adjusted hazard ratios of incident type 2 diabetes for polygenic risk score, isocaloric replacement of carbohydrate (refined starch and sugars) with types of fat, and the interaction of types of fat with polygenic risk score.\ Of 102 305 participants from 15 prospective cohort studies, 20 015 type 2 diabetes cases were documented after a median follow-up of 12 years (interquartile range 9.4-14.2). The hazard ratio of type 2 diabetes per increment of 10 risk alleles in the polygenic risk score was 1.64 (95% confidence interval 1.54 to 1.75

{Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium - Inker, L. A.; Grams, M. E.; Levey, A. S.; Coresh, J.; Cirillo, M.; Collins, J. F.; Gansevoort, R. T.; Gutierrez, O. M.; Hamano, T.; Heine, G. H.; Ishikawa, S.; Jee, S. H.; et al. (Am J Kidney Dis, 2019)
Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework.\ Cross-sectional individual participant-level analyses in a global consortium.\ 17 CKD and 38 general population and high-risk cohorts.\ Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension.\ Data were obtained and analyzed between July 2015 and January 2018.\ We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses.\ The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m2), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g).\ Variations in study era, health care delivery system, typical diet, and laboratory assays.\ Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

Serum magnesium and calcium levels in relation to ischemic stroke: Mendelian randomization study. - Larsson, Susanna C; Traylor, Matthew; Burgess, Stephen; Boncoraglio, Giorgio B; Jern, Christina; Michaëlsson, Karl; Markus, Hugh S (Neurology, 2019)
OBJECTIVE: To determine whether serum magnesium and calcium concentrations are causally associated with ischemic stroke or any of its subtypes using the mendelian randomization approach. METHODS: Analyses were conducted using summary statistics data for 13 single-nucleotide polymorphisms robustly associated with serum magnesium (n = 6) or serum calcium (n = 7) concentrations. The corresponding data for ischemic stroke were obtained from the MEGASTROKE consortium (34,217 cases and 404,630 noncases). RESULTS: In standard mendelian randomization analysis, the odds ratios for each 0.1 mmol/L (about 1 SD) increase in genetically predicted serum magnesium concentrations were 0.78 (95% confidence interval [CI] 0.69-0.89; = 1.3 × 10) for all ischemic stroke, 0.63 (95% CI 0.50-0.80; = 1.6 × 10) for cardioembolic stroke, and 0.60 (95% CI 0.44-0.82; = 0.001) for large artery stroke; there was no association with small vessel stroke (odds ratio 0.90, 95% CI 0.67-1.20; = 0.46). Only the association with cardioembolic stroke was robust in sensitivity analyses. There was no association of genetically predicted serum calcium concentrations with all ischemic stroke (per 0.5 mg/dL [about 1 SD] increase in serum calcium: odds ratio 1.03, 95% CI 0.88-1.21) or with any subtype. CONCLUSIONS: This study found that genetically higher serum magnesium concentrations are associated with a reduced risk of cardioembolic stroke but found no significant association of genetically higher serum calcium concentrations with any ischemic stroke subtype.

{Sex Differences in the Association Between Pentraxin 3 and Cognitive Decline: The Cardiovascular Health Study - Miller, L. M.; Jenny, N. S.; Rawlings, A. M.; Arnold, A. M.; Fitzpatrick, A. L.; Lopez, O. L.; Odden, M. C. (J. Gerontol. A Biol. Sci. Med. Sci., 2019)
The importance of systemic inflammation, measured by C-reactive protein, in cognitive decline has been demonstrated; however, the role of vascular inflammation is less understood. Pentraxin 3 (PTX3) is a novel marker of vascular inflammation.\ We followed adults 65 and older, free of cardiovascular disease (CVD) for up to 9 years (n = 1,547) in the Cardiovascular Health Study. We evaluated the relationship between PTX3 and change in cognitive function, measured using the Modified Mini-Mental State Examination (3MSE), and incident cognitive impairment (3MSE < 80). Mediation by CVD events, and effect modification by sex and apolipoprotein E É›4 allele (APOE4) were also examined.\ The average decline in 3MSE was 0.77 points per year. The association between PTX3 and change in 3MSE differed between women and men (p = .02). In the adjusted model, each standard deviation higher in PTX3 was associated with a 0.20 greater decline in 3MSE score per year in women over follow-up (95% CI: -0. 37, -0.03; p = .02), compared to no change in men (Î² = 0.07; 95% CI: -0.08, 0.22). CVD events had a minor effect on the associations. No effect modification by APOE4 was found, although we observed the association of PTX3 and cognitive impairment in women was attenuated and nonsignificant after adjustment for APOE4. There was a paradoxical protective association between PTX3 and reduced cognitive impairment in men, even after adjustment for APOE4.\ We found that vascular inflammation was significantly associated with cognitive decline in older women, but not men.

Statin-induced LDL cholesterol response and type 2 diabetes: a bidirectional two-sample Mendelian randomization study. - Smit, Roelof A J; Trompet, Stella; Leong, Aaron; Goodarzi, Mark O; Postmus, Iris; Warren, Helen; Theusch, Elizabeth; Barnes, Michael R; Arsenault, Benoit J; Li, Xiaohui; Feng, QiPing; Chasman, Daniel I; et al. (Pharmacogenomics J, 2019)
It remains unclear whether the increased risk of new-onset type 2 diabetes (T2D) seen in statin users is due to low LDL-C concentrations, or due to the statin-induced proportional change in LDL-C. In addition, genetic instruments have not been proposed before to examine whether liability to T2D might cause greater proportional statin-induced LDL-C lowering. Using summary-level statistics from the Genomic Investigation of Statin Therapy (GIST, n = 40,914) and DIAGRAM (n = 159,208) consortia, we found a positive genetic correlation between LDL-C statin response and T2D using LD score regression (r = 0.36, s.e. = 0.13). However, mendelian randomization analyses did not provide support for statin response having a causal effect on T2D risk (OR 1.00 (95% CI: 0.97, 1.03) per 10% increase in statin response), nor that liability to T2D has a causal effect on statin-induced LDL-C response (0.20% increase in response (95% CI: -0.40, 0.80) per doubling of odds of liability to T2D). Although we found no evidence to suggest that proportional statin response influences T2D risk, a definitive assessment should be made in populations comprised exclusively of statin users, as the presence of nonstatin users in the DIAGRAM dataset may have substantially diluted our effect estimate.

Systematic analysis of dark and camouflaged genes reveals disease-relevant genes hiding in plain sight. - Ebbert, Mark T W; Jensen, Tanner D; Jansen-West, Karen; Sens, Jonathon P; Reddy, Joseph S; Ridge, Perry G; Kauwe, John S K; Belzil, Veronique; Pregent, Luc; Carrasquillo, Minerva M; Keene, Dirk; Larson, Eric; et al. (Genome Biol, 2019)
BACKGROUND: The human genome contains "dark" gene regions that cannot be adequately assembled or aligned using standard short-read sequencing technologies, preventing researchers from identifying mutations within these gene regions that may be relevant to human disease. Here, we identify regions with few mappable reads that we call dark by depth, and others that have ambiguous alignment, called camouflaged. We assess how well long-read or linked-read technologies resolve these regions. RESULTS: Based on standard whole-genome Illumina sequencing data, we identify 36,794 dark regions in 6054 gene bodies from pathways important to human health, development, and reproduction. Of these gene bodies, 8.7% are completely dark and 35.2% are ≥ 5% dark. We identify dark regions that are present in protein-coding exons across 748 genes. Linked-read or long-read sequencing technologies from 10x Genomics, PacBio, and Oxford Nanopore Technologies reduce dark protein-coding regions to approximately 50.5%, 35.6%, and 9.6%, respectively. We present an algorithm to resolve most camouflaged regions and apply it to the Alzheimer's Disease Sequencing Project. We rescue a rare ten-nucleotide frameshift deletion in CR1, a top Alzheimer's disease gene, found in disease cases but not in controls. CONCLUSIONS: While we could not formally assess the association of the CR1 frameshift mutation with Alzheimer's disease due to insufficient sample-size, we believe it merits investigating in a larger cohort. There remain thousands of potentially important genomic regions overlooked by short-read sequencing that are largely resolved by long-read technologies.
Keywords: Genetic Predisposition to Disease; Genome, Human; Humans; Mutation

Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels. - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nat Genet, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.

Trans-ethnic association study of blood pressure determinants in over 750,000 individuals. - Giri, Ayush; Hellwege, Jacklyn N; Keaton, Jacob M; Park, Jihwan; Qiu, Chengxiang; Warren, Helen R; Torstenson, Eric S; Kovesdy, Csaba P; Sun, Yan V; Wilson, Otis D; Robinson-Cohen, Cassianne; Roumie, Christianne L; et al. (Nat Genet, 2019)
In this trans-ethnic multi-omic study, we reinterpret the genetic architecture of blood pressure to identify genes, tissues, phenomes and medication contexts of blood pressure homeostasis. We discovered 208 novel common blood pressure SNPs and 53 rare variants in genome-wide association studies of systolic, diastolic and pulse pressure in up to 776,078 participants from the Million Veteran Program (MVP) and collaborating studies, with analysis of the blood pressure clinical phenome in MVP. Our transcriptome-wide association study detected 4,043 blood pressure associations with genetically predicted gene expression of 840 genes in 45 tissues, and mouse renal single-cell RNA sequencing identified upregulated blood pressure genes in kidney tubule cells.

{Variants Associated with the Ankle Brachial Index Differ by Hispanic/Latino Ethnic Group: a genome-wide association study in the Hispanic Community Health Study/Study of Latinos - Sofer, T.; Emery, L.; Jain, D.; Ellis, A. M.; Laurie, C. C.; Allison, M. A.; Lee, J.; Kurniansyah, N.; Kerr, K. F.; Gonz?lez, H. M.; Tarraf, W.; Criqui, M. H.; et al. (Sci Rep, 2019)
Lower extremity peripheral artery disease (PAD) burden differs by race/ethnicity. Although familial aggregation and heritability studies suggest a genetic basis, little is known about the genetic susceptibility to PAD, especially in non-European descent populations. Genome-wide association studies (GWAS) of the ankle brachial index (ABI) and PAD (defined as an ABI < 0.90) have not been conducted in Hispanics/Latinos. We performed a GWAS of PAD and the ABI in 7,589 participants aged >45 years from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). We also performed GWAS for ABI stratified by Hispanic/Latino ethnic subgroups: Central American, Mexican, and South American (Mainland group), and Cuban, Dominican, and Puerto Rican (Caribbean group). We detected two genome-wide significant associations for the ABI in COMMD10 in Puerto Ricans, and at SYBU in the Caribbean group. The lead SNP rs4466200 in the COMMD10 gene had a replication p = 0.02 for the ABI in Multi-Ethnic Study of Atherosclerosis (MESA) African Americans, but it did not replicate in African Americans from the Cardiovascular Health Study (CHS). In a regional look-up, a nearby SNP rs12520838 had Bonferroni adjusted p = 0.05 (unadjusted p = 7.5 Ã— 10-5) for PAD in MESA Hispanics. Among three suggestive associations (p < 10-7) in subgroup-specific analyses, DMD on chromosome X, identified in Central Americans, replicated in MESA Hispanics (p = 2.2 Ã— 10-4). None of the previously reported ABI and PAD associations in whites generalized to Hispanics/Latinos.

Alzheimer Disease Pathology-Associated Polymorphism in a Complex Variable Number of Tandem Repeat Region Within the MUC6 Gene, Near the AP2A2 Gene. - Katsumata, Yuriko; Fardo, David W; Bachstetter, Adam D; Artiushin, Sergey C; Wang, Wang-Xia; Wei, Angela; Brzezinski, Lena J; Nelson, Bela G; Huang, Qingwei; Abner, Erin L; Anderson, Sonya; Patel, Indumati; et al. (J Neuropathol Exp Neurol, 2020)
We found evidence of late-onset Alzheimer disease (LOAD)-associated genetic polymorphism within an exon of Mucin 6 (MUC6) and immediately downstream from another gene: Adaptor Related Protein Complex 2 Subunit Alpha 2 (AP2A2). PCR analyses on genomic DNA samples confirmed that the size of the MUC6 variable number tandem repeat (VNTR) region was highly polymorphic. In a cohort of autopsied subjects with quantitative digital pathology data (n = 119), the size of the polymorphic region was associated with the severity of pTau pathology in neocortex. In a separate replication cohort of autopsied subjects (n = 173), more pTau pathology was again observed in subjects with longer VNTR regions (p = 0.031). Unlike MUC6, AP2A2 is highly expressed in human brain. AP2A2 expression was lower in a subset analysis of brain samples from persons with longer versus shorter VNTR regions (p = 0.014 normalizing with AP2B1 expression). Double-label immunofluorescence studies showed that AP2A2 protein often colocalized with neurofibrillary tangles in LOAD but was not colocalized with pTau proteinopathy in progressive supranuclear palsy, or with TDP-43 proteinopathy. In summary, polymorphism in a repeat-rich region near AP2A2 was associated with neocortical pTau proteinopathy (because of the unique repeats, prior genome-wide association studies were probably unable to detect this association), and AP2A2 was often colocalized with neurofibrillary tangles in LOAD.
Keywords: Adaptor Protein Complex 2; Adaptor Protein Complex alpha Subunits; Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Minisatellite Repeats; Mucin-6; Neurofibrillary Tangles; Polymorphism, Genetic; Polymorphism, Single Nucleotide; TDP-43 Proteinopathies

Association of Genetic Variation With Keratoconus. - McComish, Bennet J; Sahebjada, Srujana; Bykhovskaya, Yelena; Willoughby, Colin E; Richardson, Andrea J; Tenen, Abi; Charlesworth, Jac C; Macgregor, Stuart; Mitchell, Paul; Lucas, Sionne E M; Mills, Richard A; Mackey, David A; et al. (JAMA Ophthalmol, 2020)
Importance: Keratoconus is a condition in which the cornea progressively thins and protrudes in a conical shape, severely affecting refraction and vision. It is a major indication for corneal transplant. To discover new genetic loci associated with keratoconus and better understand the causative mechanism of this disease, we performed a genome-wide association study on patients with keratoconus. Objective: To identify genetic susceptibility regions for keratoconus in the human genome. Design, Setting, and Participants: This study was conducted with data from eye clinics in Australia, the United States, and Northern Ireland. The discovery cohort of individuals with keratoconus and control participants from Australia was genotyped using the Illumina HumanCoreExome single-nucleotide polymorphism array. After quality control and data cleaning, genotypes were imputed against the 1000 Genomes Project reference panel (phase III; version 5), and association analyses were completed using PLINK version 1.90. Single-nucleotide polymorphisms with P < 1.00 × 10-6 were assessed for replication in 3 additional cohorts. Control participants were drawn from the cohorts of the Blue Mountains Eye Study and a previous study of glaucoma. Replication cohorts were from a previous keratoconus genome-wide association study data set from the United States, a cohort of affected and control participants from Australia and Northern Ireland, and a case-control cohort from Victoria, Australia. Data were collected from January 2006 to March 2019. Main Outcomes and Measures: Associations between keratoconus and 6 252 612 genetic variants were estimated using logistic regression after adjusting for ancestry using the first 3 principal components. Results: The discovery cohort included 522 affected individuals and 655 control participants, while the replication cohorts included 818 affected individuals (222 from the United States, 331 from Australia and Northern Ireland, and 265 from Victoria, Australia) and 3858 control participants (2927 from the United States, 229 from Australia and Northern Ireland, and 702 from Victoria, Australia). Two novel loci reached genome-wide significance (defined as P < 5.00 × 10-8), with a P value of 7.46 × 10-9 at rs61876744 in patatin-like phospholipase domain-containing 2 gene (PNPLA2) on chromosome 11 and a P value of 6.35 × 10-12 at rs138380, 2.2 kb upstream of casein kinase I isoform epsilon gene (CSNK1E) on chromosome 22. One additional locus was identified with a P value less than 1.00 × 10-6 in mastermind-like transcriptional coactivator 2 (MAML2) on chromosome 11 (P = 3.91 × 10-7). The novel locus in PNPLA2 reached genome-wide significance in an analysis of all 4 cohorts (P = 2.45 × 10-8). Conclusions and Relevance: In this relatively large keratoconus genome-wide association study, we identified a genome-wide significant locus for keratoconus in the region of PNPLA2 on chromosome 11.
Keywords: Adult; Female; Fuchs' Endothelial Dystrophy; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Keratoconus; Lipase; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide

Association of Nonobstructive Chronic Bronchitis With Respiratory Health Outcomes in Adults. - Balte, Pallavi P; Chaves, Paulo H M; Couper, David J; Enright, Paul; Jacobs, David R; Kalhan, Ravi; Kronmal, Richard A; Loehr, Laura R; London, Stephanie J; Newman, Anne B; O'Connor, George T; Schwartz, Joseph E; et al. (JAMA Intern Med, 2020)
Importance: Chronic bronchitis has been associated with cigarette smoking as well as with e-cigarette use among young adults, but the association of chronic bronchitis in persons without airflow obstruction or clinical asthma, described as nonobstructive chronic bronchitis, with respiratory health outcomes remains uncertain. Objective: To assess whether nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes in adult ever smokers and never smokers. Design, Setting, and Participants: This prospective cohort study included 22 325 adults without initial airflow obstruction (defined as the ratio of forced expiratory volume in the first second [FEV1] to forced vital capacity [FVC] of <0.70) or clinical asthma at baseline. The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study harmonized and pooled data from 9 US general population-based cohorts. Thus present study is based on data from 5 of these cohorts. Participants were enrolled from August 1971 through May 2007 and were followed up through December 2018. Exposures: Nonobstructive chronic bronchitis was defined by questionnaire at baseline as both cough and phlegm for at least 3 months for at least 2 consecutive years. Main Outcomes and Measures: Lung function was measured by prebronchodilator spirometry. Hospitalizations and deaths due to chronic lower respiratory disease and respiratory disease-related mortality were defined by events adjudication and administrative criteria. Models were stratified by smoking status and adjusted for anthropometric, sociodemographic, and smoking-related factors. The comparison group was participants without nonobstructive chronic bronchitis. Results: Among 22 325 adults included in the analysis, mean (SD) age was 53.0 (16.3) years (range, 18.0-95.0 years), 58.2% were female, 65.9% were non-Hispanic white, and 49.6% were ever smokers. Among 11 082 ever smokers with 99 869 person-years of follow-up, participants with nonobstructive chronic bronchitis (300 [2.7%]) had accelerated decreases in FEV1 (4.1 mL/y; 95% CI, 2.1-6.1 mL/y) and FVC (4.7 mL/y; 95% CI, 2.2-7.2 mL/y), increased risks of chronic lower respiratory disease-related hospitalization or mortality (hazard ratio [HR], 2.2; 95% CI, 1.7-2.7), and greater respiratory disease-related (HR, 2.0; 95% CI, 1.1-3.8) and all-cause mortality (HR, 1.5; 95% CI, 1.3-1.8) compared with ever smokers without nonobstructive chronic bronchitis. Among 11 243 never smokers with 120 004 person-years of follow-up, participants with nonobstructive chronic bronchitis (151 [1.3%]) had greater rates of chronic lower respiratory disease-related hospitalization or mortality (HR, 3.1; 95% CI, 2.1-4.5) compared with never smokers without nonobstructive chronic bronchitis. Nonobstructive chronic bronchitis was not associated with FEV1:FVC decline or incident airflow obstruction. The presence of at least 1 of the component symptoms of nonobstructive chronic bronchitis (ie, chronic cough or phlegm), which was common in both ever smokers (11.0%) and never smokers (6.7%), was associated with adverse respiratory health outcomes. Conclusions and Relevance: The findings suggest that nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes, particularly in ever smokers, and may be a high-risk phenotype suitable for risk stratification and targeted therapies.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asthma; Bronchitis, Chronic; Female; Humans; Lung; Male; Middle Aged; Prospective Studies; Respiratory Function Tests; Smokers; Smoking; Young Adult

Association of skeletal muscle mass, kidney disease and mortality in older men and women: the cardiovascular health study. - Kruse, Nicholas T; Bůzková, Petra; Barzilay, Joshua I; Valderrábano, Rodrigo J; Robbins, John A; Fink, Howard A; Jalal, Diana I (Aging (Albany NY), 2020)
Low muscle mass (sarcopenia) is a prevalent and major concern in the aging population as well as in patients with chronic kidney disease (CKD). We hypothesized that sarcopenia is an independent predictor of incident and progressive CKD and increased mortality in older men and women (≥65 years) from the Cardiovascular Health Study. Sarcopenia was defined by bioimpedance-estimated skeletal muscle mass index (SMI) as a continuous variable and categorically (normal, class I, and class II). Cox regression hazard ratios (HRs) estimated the risk of incident and prevalent CKD and mortality in individuals with and without CKD. Low SMI was associated with increased prevalence of CKD in men (p<0.001), but lower prevalence of CKD in women (p=0.03). Low muscle mass was not associated with incident CKD or rapid CKD progression (>3 ml/minute/1.73m/year decline in eGFR) in men, but was associated with lower risk of incident CKD in women ([adjusted RR=0.69, 95% (0.51,0.94)]. Low muscle mass (class II) was independently associated with higher mortality only in men [(adjusted HR=1.26, 95% (1.05,1.50)]. Neither definition of sarcopenia was associated with mortality in men or women with CKD. Further studies are needed to understand the mechanisms by which sarcopenia contributes to higher mortality in aging men.

{Cerebral small vessel disease genomics and its implications across the lifespan - Sargurupremraj, M.; Suzuki, H.; Jian, X.; Sarnowski, C.; Evans, T. E.; Bis, J. C.; Eiriksdottir, G.; Sakaue, S.; Terzikhan, N.; Habes, M.; Zhao, W.; Armstrong, N. J.; et al. (Nat Commun, 2020)
White matter hyperintensities (WMH) are the most common brain-imaging feature of cerebral small vessel disease (SVD), hypertension being the main known risk factor. Here, we identify 27 genome-wide loci for WMH-volume in a cohort of 50,970 older individuals, accounting for modification/confounding by hypertension. Aggregated WMH risk variants were associated with altered white matter integrity (p = 2.5Ã—10-7) in brain images from 1,738 young healthy adults, providing insight into the lifetime impact of SVD genetic risk. Mendelian randomization suggested causal association of increasing WMH-volume with stroke, Alzheimer-type dementia, and of increasing blood pressure (BP) with larger WMH-volume, notably also in persons without clinical hypertension. Transcriptome-wide colocalization analyses showed association of WMH-volume with expression of 39 genes, of which four encode known drug targets. Finally, we provide insight into BP-independent biological pathways underlying SVD and suggest potential for genetic stratification of high-risk individuals and for genetically-informed prioritization of drug targets for prevention trials.

Chronic obstructive pulmonary disease and related phenotypes: polygenic risk scores in population-based and case-control cohorts. - Moll, Matthew; Sakornsakolpat, Phuwanat; Shrine, Nick; Hobbs, Brian D; DeMeo, Dawn L; John, Catherine; Guyatt, Anna L; McGeachie, Michael J; Gharib, Sina A; Obeidat, Ma'en; Lahousse, Lies; Wijnant, Sara R A; et al. (Lancet Respir Med, 2020)
BACKGROUND: Genetic factors influence chronic obstructive pulmonary disease (COPD) risk, but the individual variants that have been identified have small effects. We hypothesised that a polygenic risk score using additional variants would predict COPD and associated phenotypes. METHODS: We constructed a polygenic risk score using a genome-wide association study of lung function (FEV and FEV/forced vital capacity [FVC]) from the UK Biobank and SpiroMeta. We tested this polygenic risk score in nine cohorts of multiple ethnicities for an association with moderate-to-severe COPD (defined as FEV/FVC <0·7 and FEV <80% of predicted). Associations were tested using logistic regression models, adjusting for age, sex, height, smoking pack-years, and principal components of genetic ancestry. We assessed predictive performance of models by area under the curve. In a subset of studies, we also studied quantitative and qualitative CT imaging phenotypes that reflect parenchymal and airway pathology, and patterns of reduced lung growth. FINDINGS: The polygenic risk score was associated with COPD in European (odds ratio [OR] per SD 1·81 [95% CI 1·74-1·88] and non-European (1·42 [1·34-1·51]) populations. Compared with the first decile, the tenth decile of the polygenic risk score was associated with COPD, with an OR of 7·99 (6·56-9·72) in European ancestry and 4·83 (3·45-6·77) in non-European ancestry cohorts. The polygenic risk score was superior to previously described genetic risk scores and, when combined with clinical risk factors (ie, age, sex, and smoking pack-years), showed improved prediction for COPD compared with a model comprising clinical risk factors alone (AUC 0·80 [0·79-0·81] vs 0·76 [0·75-0·76]). The polygenic risk score was associated with CT imaging phenotypes, including wall area percent, quantitative and qualitative measures of emphysema, local histogram emphysema patterns, and destructive emphysema subtypes. The polygenic risk score was associated with a reduced lung growth pattern. INTERPRETATION: A risk score comprised of genetic variants can identify a small subset of individuals at markedly increased risk for moderate-to-severe COPD, emphysema subtypes associated with cigarette smoking, and patterns of reduced lung growth. FUNDING: US National Institutes of Health, Wellcome Trust.
Keywords: Adult; Case-Control Studies; Cohort Studies; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Phenotype; Pulmonary Disease, Chronic Obstructive; Risk Factors; Vital Capacity

{Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals - Surendran, P.; Feofanova, E. V.; Lahrouchi, N.; Ntalla, I.; Karthikeyan, S.; Cook, J.; Chen, L.; Mifsud, B.; Yao, C.; Kraja, A. T.; Cartwright, J. H.; Hellwege, J. N.; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to 1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency â‰¤ 0.01) variant BP associations (P < 5 Ã— 10-8), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were 8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.

A Dyadic Growth Modeling Approach for Examining Associations Between Weight Gain and Lung Function Decline. - Cornelius, Talea; Schwartz, Joseph E; Balte, Pallavi; Bhatt, Surya P; Cassano, Patricia A; Currow, David; Jacobs, David R; Johnson, Miriam; Kalhan, Ravi; Kronmal, Richard; Loehr, Laura; O'Connor, George T; et al. (Am J Epidemiol, 2020)
The relationship between body weight and lung function is complex. Using a dyadic multilevel linear modeling approach, treating body mass index (BMI; weight (kg)/height (m)2) and lung function as paired, within-person outcomes, we tested the hypothesis that persons with more rapid increase in BMI exhibit more rapid decline in lung function, as measured by forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), and their ratio (FEV1:FVC). Models included random intercepts and slopes and adjusted for sociodemographic and smoking-related factors. A sample of 9,115 adults with paired measurements of BMI and lung function taken at ≥3 visits were selected from a pooled set of 5 US population-based cohort studies (1983-2018; mean age at baseline = 46 years; median follow-up, 19 years). At age 46 years, average annual rates of change in BMI, FEV1, FVC, and FEV1:FVC ratio were 0.22 kg/m2/year, -25.50 mL/year, -21.99 mL/year, and -0.24%/year, respectively. Persons with steeper BMI increases had faster declines in FEV1 (r = -0.16) and FVC (r = -0.26) and slower declines in FEV1:FVC ratio (r = 0.11) (all P values < 0.0001). Results were similar in subgroup analyses. Residual correlations were negative (P < 0.0001), suggesting additional interdependence between BMI and lung function. Results show that greater rates of weight gain are associated with greater rates of lung function loss.
Keywords: Adult; Aged; Body Mass Index; Cohort Studies; Humans; Linear Models; Lung; Middle Aged; Respiratory Function Tests; Weight Gain

{Dynamic incorporation of multiple in silico functional annotations empowers rare variant association analysis of large whole-genome sequencing studies at scale - Li, X.; Li, Z.; Zhou, H.; Gaynor, S. M.; Liu, Y.; Chen, H.; Sun, R.; Dey, R.; Arnett, D. K.; Aslibekyan, S.; Ballantyne, C. M.; Bielak, L. F.; et al. (Nat Genet, 2020)
Large-scale whole-genome sequencing studies have enabled the analysis of rare variants (RVs) associated with complex phenotypes. Commonly used RV association tests have limited scope to leverage variant functions. We propose STAAR (variant-set test for association using annotation information), a scalable and powerful RV association test method that effectively incorporates both variant categories and multiple complementary annotations using a dynamic weighting scheme. For the latter, we introduce 'annotation principal components', multidimensional summaries of in silico variant annotations. STAAR accounts for population structure and relatedness and is scalable for analyzing very large cohort and biobank whole-genome sequencing studies of continuous and dichotomous traits. We applied STAAR to identify RVs associated with four lipid traits in 12,316 discovery and 17,822 replication samples from the Trans-Omics for Precision Medicine Program. We discovered and replicated new RV associations, including disruptive missense RVs of NPC1L1 and an intergenic region near APOC1P1 associated with low-density lipoprotein cholesterol.

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2020)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.

The genetic architecture of the human cerebral cortex - Grasby, Katrina L.; Jahanshad, Neda; Painter, Jodie N.; Colodro-Conde, Lucía; Bralten, Janita; Hibar, Derrek P.; Lind, Penelope A.; Pizzagalli, Fabrizio; Ching, Christopher R. K.; McMahon, Mary Agnes B.; Shatokhina, Natalia; Zsembik, Leo C. P.; et al. (Science, 2020)

{Genetic correlations and genome-wide associations of cortical structure in general population samples of 22,824 adults - Hofer, E.; Roshchupkin, G. V.; Adams, H. H. H.; Knol, M. J.; Lin, H.; Li, S.; Zare, H.; Ahmad, S.; Armstrong, N. J.; Satizabal, C. L.; Bernard, M.; Bis, J. C.; et al. (Nat Commun, 2020)
Cortical thickness, surface area and volumes vary with age and cognitive function, and in neurological and psychiatric diseases. Here we report heritability, genetic correlations and genome-wide associations of these cortical measures across the whole cortex, and in 34 anatomically predefined regions. Our discovery sample comprises 22,824 individuals from 20 cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank. We identify genetic heterogeneity between cortical measures and brain regions, and 160 genome-wide significant associations pointing to wnt/Î²-catenin, TGF-Î² and sonic hedgehog pathways. There is enrichment for genes involved in anthropometric traits, hindbrain development, vascular and neurodegenerative disease and psychiatric conditions. These data are a rich resource for studies of the biological mechanisms behind cortical development and aging.

{Genetic Determinants of Electrocardiographic P-wave Duration and Relation to Atrial Fibrillation - Weng, L. C.; Hall, A. W.; Choi, S. H.; Jurgens, S. J.; Haessler, J.; Bihlmeyer, N. A.; Grarup, N.; Lin, H.; Teumer, A.; Li-Gao, R.; Yao, J.; Guo, X.; et al. (Circ Genom Precis Med, 2020)
Background - The P-wave duration (PWD) is an electrocardiographic (ECG) measurement that represents cardiac conduction in the atria. Shortened or prolonged PWD is associated with atrial fibrillation (AF). We used exome chip data to examine the associations between common and rare variants with PWD. Methods - Fifteen studies comprising 64,440 individuals (56,943 European, 5,681 African, 1,186 Hispanic, 630 Asian), and 230,000 variants were used to examine associations with maximum PWD across the 12-lead ECG. Meta-analyses summarized association results for common variants; gene-based burden and SKAT tests examined low-frequency variant-PWD associations. Additionally, we examined the associations between PWD loci and AF using previous AF GWAS. Results - We identified 21 common and low-frequency genetic loci (14 novel) associated with maximum PWD, including several AF loci (TTN, CAND2, SCN10A, PITX2, CAV1, SYNPO2L, SOX5, TBX5, MYH6, RPL3L). The top variants at known sarcomere genes (TTN, MYH6) were associated with longer PWD and increased AF risk. However, top variants at other loci (e.g., PITX2 and SCN10A) were associated with longer PWD but lower AF risk. Conclusions - Our results highlight multiple novel genetic loci associated with PWD, and underscore the shared mechanisms of atrial conduction and AF. Prolonged PWD may be an endophenotype for several different genetic mechanisms of AF.

Genetic Studies of Leptin Concentrations Implicate Leptin in the Regulation of Early Adiposity. - Yaghootkar, Hanieh; Zhang, Yiying; Spracklen, Cassandra N; Karaderi, Tugce; Huang, Lam Opal; Bradfield, Jonathan; Schurmann, Claudia; Fine, Rebecca S; Preuss, Michael H; Kutalik, Zoltán; Wittemans, Laura Bl; Lu, Yingchang; et al. (Diabetes, 2020)
Leptin influences food intake by informing the brain about the status of body fat stores. Rare mutations associated with congenital leptin deficiency cause severe early-onset obesity that can be mitigated by administering leptin. However, the role of genetic regulation of leptin in polygenic obesity remains poorly understood. We performed an exome-based analysis in up to 57,232 individuals of diverse ancestries to identify genetic variants that influence adiposity-adjusted leptin concentrations. We identify five novel variants, including four missense variants, in , and , and one intergenic variant near The missense variant Val94Met (rs17151919) in was common in individuals of African ancestry only and its association with lower leptin concentrations was specific to this ancestry (P=2x10, n=3,901). Using analyses, we show that the Met94 allele decreases leptin secretion. We also show that the Met94 allele is associated with higher BMI in young African-ancestry children but not in adults, suggesting leptin regulates early adiposity.

{Genome-wide association and Mendelian randomisation analysis provide insights into the pathogenesis of heart failure - Shah, S.; Henry, A.; Roselli, C.; Lin, H.; Sveinbj?rnsson, G.; Fatemifar, G.; Hedman, ?. K.; Wilk, J. B.; Morley, M. P.; Chaffin, M. D.; Helgadottir, A.; Verweij, N.; et al. (Nat Commun, 2020)
Heart failure (HF) is a leading cause of morbidity and mortality worldwide. A small proportion of HF cases are attributable to monogenic cardiomyopathies and existing genome-wide association studies (GWAS) have yielded only limited insights, leaving the observed heritability of HF largely unexplained. We report results from a GWAS meta-analysis of HF comprising 47,309 cases and 930,014 controls. Twelve independent variants at 11 genomic loci are associated with HF, all of which demonstrate one or more associations with coronary artery disease (CAD), atrial fibrillation, or reduced left ventricular function, suggesting shared genetic aetiology. Functional analysis of non-CAD-associated loci implicate genes involved in cardiac development (MYOZ1, SYNPO2L), protein homoeostasis (BAG3), and cellular senescence (CDKN1A). Mendelian randomisation analysis supports causal roles for several HF risk factors, and demonstrates CAD-independent effects for atrial fibrillation, body mass index, and hypertension. These findings extend our knowledge of the pathways underlying HF and may inform new therapeutic strategies.

{An individual participant data analysis of prospective cohort studies on the association between subclinical thyroid dysfunction and depressive symptoms - Wildisen, L.; Del Giovane, C.; Moutzouri, E.; Beglinger, S.; Syrogiannouli, L.; Collet, T. H.; Cappola, A. R.; ?svold, B. O.; Bakker, S. J. L.; Yeap, B. B.; Almeida, O. P.; Ceresini, G.; et al. (Sci Rep, 2020)
{In subclinical hypothyroidism, the presence of depressive symptoms is often a reason for starting levothyroxine treatment. However, data are conflicting on the association between subclinical thyroid dysfunction and depressive symptoms. We aimed to examine the association between subclinical thyroid dysfunction and depressive symptoms in all prospective cohorts with relevant data available. We performed a systematic review of the literature from Medline, Embase, Cumulative Index to Nursing and Allied Health Literature, and the Cochrane Library from inception to 10th May 2019. We included prospective cohorts with data on thyroid status at baseline and depressive symptoms during follow-up. The primary outcome was depressive symptoms measured at first available follow-up, expressed on the Beck's Depression Inventory (BDI) scale (range 0-63, higher values indicate more depressive symptoms, minimal clinically important difference: 5 points). We performed a two-stage individual participant data (IPD) analysis comparing participants with subclinical hypo- or hyperthyroidism versus euthyroidism, adjusting for depressive symptoms at baseline, age, sex, education, and income (PROSPERO CRD42018091627). Six cohorts met the inclusion criteria, with IPD on 23,038 participants. Their mean age was 60 years, 65% were female, 21,025 were euthyroid, 1342 had subclinical hypothyroidism and 671 subclinical hyperthyroidism. At first available follow-up [mean 8.2 (Â± 4.3) years], BDI scores did not differ between participants with subclinical hypothyroidism (mean difference = 0.29, 95% confidence interval = - 0.17 to 0.76

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.

Lung function decline in former smokers and low-intensity current smokers: a secondary data analysis of the NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Bhatt, Surya P; Cassano, Patricia A; Couper, David; Folsom, Aaron R; Freedman, Neal D; Jacobs, David R; Kalhan, Ravi; Mathew, Amanda R; Kronmal, Richard A; Loehr, Laura R; et al. (Lancet Respir Med, 2020)
BACKGROUND: Former smokers now outnumber current smokers in many developed countries, and current smokers are smoking fewer cigarettes per day. Some data suggest that lung function decline normalises with smoking cessation; however, mechanistic studies suggest that lung function decline could continue. We hypothesised that former smokers and low-intensity current smokers have accelerated lung function decline compared with never-smokers, including among those without prevalent lung disease. METHODS: We used data on six US population-based cohorts included in the NHLBI Pooled Cohort Study. We restricted the sample to participants with valid spirometry at two or more exams. Two cohorts recruited younger adults (≥17 years), two recruited middle-aged and older adults (≥45 years), and two recruited only elderly adults (≥65 years) with examinations done between 1983 and 2014. FEV decline in sustained former smokers and current smokers was compared to that of never-smokers by use of mixed models adjusted for sociodemographic and anthropometric factors. Differential FEV decline was also evaluated according to duration of smoking cessation and cumulative (number of pack-years) and current (number of cigarettes per day) cigarette consumption. FINDINGS: 25 352 participants (ages 17-93 years) completed 70 228 valid spirometry exams. Over a median follow-up of 7 years (IQR 3-20), FEV decline at the median age (57 years) was 31·01 mL per year (95% CI 30·66-31·37) in sustained never-smokers, 34·97 mL per year (34·36-35·57) in former smokers, and 39·92 mL per year (38·92-40·92) in current smokers. With adjustment, former smokers showed an accelerated FEV decline of 1·82 mL per year (95% CI 1·24-2·40) compared to never-smokers, which was approximately 20% of the effect estimate for current smokers (9·21 mL per year; 95% CI 8·35-10·08). Compared to never-smokers, accelerated FEV decline was observed in former smokers for decades after smoking cessation and in current smokers with low cumulative cigarette consumption (<10 pack-years). With respect to current cigarette consumption, the effect estimate for FEV decline in current smokers consuming less than five cigarettes per day (7·65 mL per year; 95% CI 6·21-9·09) was 68% of that in current smokers consuming 30 or more cigarettes per day (11·24 mL per year; 9·86-12·62), and around five times greater than in former smokers (1·57 mL per year; 1·00-2·14). Among participants without prevalent lung disease, associations were attenuated but were consistent with the main results. INTERPRETATION: Former smokers and low-intensity current smokers have accelerated lung function decline compared with never-smokers. These results suggest that all levels of smoking exposure are likely to be associated with lasting and progressive lung damage. FUNDING: National Institutes of Health, National Heart Lung and Blood Institute, and US Environmental Protection Agency.
Keywords: Adult; Aged; Case-Control Studies; Ex-Smokers; Female; Follow-Up Studies; Humans; Lung; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Non-Smokers; Respiratory Physiological Phenomena; Smokers; Smoking; Spirometry; United States; Young Adult

Mendelian randomization analysis does not support causal associations of birth weight with hypertension risk and blood pressure in adulthood. - Zheng, Yan; Huang, Tao; Wang, Tiange; Mei, Zhendong; Sun, Zhonghan; Zhang, Tao; Ellervik, Christina; Chai, Jin-Fang; Sim, Xueling; van Dam, Rob M; Tai, E-Shyong; Koh, Woon-Puay; et al. (Eur J Epidemiol, 2020)
Epidemiology studies suggested that low birthweight was associated with a higher risk of hypertension in later life. However, little is known about the causality of such associations. In our study, we evaluated the causal association of low birthweight with adulthood hypertension following a standard analytic protocol using the study-level data of 183,433 participants from 60 studies (CHARGE-BIG consortium), as well as that with blood pressure using publicly available summary-level genome-wide association data from EGG consortium of 153,781 participants, ICBP consortium and UK Biobank cohort together of 757,601 participants. We used seven SNPs as the instrumental variable in the study-level analysis and 47 SNPs in the summary-level analysis. In the study-level analyses, decreased birthweight was associated with a higher risk of hypertension in adults (the odds ratio per 1 standard deviation (SD) lower birthweight, 1.22; 95% CI 1.16 to 1.28), while no association was found between genetically instrumented birthweight and hypertension risk (instrumental odds ratio for causal effect per 1 SD lower birthweight, 0.97; 95% CI 0.68 to 1.41). Such results were consistent with that from the summary-level analyses, where the genetically determined low birthweight was not associated with blood pressure measurements either. One SD lower genetically determined birthweight was not associated with systolic blood pressure (β = - 0.76, 95% CI - 2.45 to 1.08 mmHg), 0.06 mmHg lower diastolic blood pressure (β = - 0.06, 95% CI - 0.93 to 0.87 mmHg), or pulse pressure (β = - 0.65, 95% CI - 1.38 to 0.69 mmHg, all p > 0.05). Our findings suggest that the inverse association of birthweight with hypertension risk from observational studies was not supported by large Mendelian randomization analyses.

Meta-analysis uncovers genome-wide significant variants for rapid kidney function decline. - Gorski, Mathias; Jung, Bettina; Li, Yong; Matias-Garcia, Pamela R; Wuttke, Matthias; Coassin, Stefan; Thio, Chris H L; Kleber, Marcus E; Winkler, Thomas W; Wanner, Veronika; Chai, Jin-Fang; Chu, Audrey Y; et al. (Kidney Int, 2020)
Rapid decline of glomerular filtration rate estimated from creatinine (eGFRcrea) is associated with severe clinical endpoints. In contrast to cross-sectionally assessed eGFRcrea, the genetic basis for rapid eGFRcrea decline is largely unknown. To help define this, we meta-analyzed 42 genome-wide association studies from the Chronic Kidney Diseases Genetics Consortium and United Kingdom Biobank to identify genetic loci for rapid eGFRcrea decline. Two definitions of eGFRcrea decline were used: 3 mL/min/1.73m/year or more ("Rapid3"; encompassing 34,874 cases, 107,090 controls) and eGFRcrea decline 25% or more and eGFRcrea under 60 mL/min/1.73m at follow-up among those with eGFRcrea 60 mL/min/1.73m or more at baseline ("CKDi25"; encompassing 19,901 cases, 175,244 controls). Seven independent variants were identified across six loci for Rapid3 and/or CKDi25: consisting of five variants at four loci with genome-wide significance (near UMOD-PDILT (2), PRKAG2, WDR72, OR2S2) and two variants among 265 known eGFRcrea variants (near GATM, LARP4B). All these loci were novel for Rapid3 and/or CKDi25 and our bioinformatic follow-up prioritized variants and genes underneath these loci. The OR2S2 locus is novel for any eGFRcrea trait including interesting candidates. For the five genome-wide significant lead variants, we found supporting effects for annual change in blood urea nitrogen or cystatin-based eGFR, but not for GATM or LARP4B. Individuals at high compared to those at low genetic risk (8-14 vs 0-5 adverse alleles) had a 1.20-fold increased risk of acute kidney injury (95% confidence interval 1.08-1.33). Thus, our identified loci for rapid kidney function decline may help prioritize therapeutic targets and identify mechanisms and individuals at risk for sustained deterioration of kidney function.

Multi-ancestry GWAS of the electrocardiographic PR interval identifies 202 loci underlying cardiac conduction. - Ntalla, Ioanna; Weng, Lu-Chen; Cartwright, James H; Hall, Amelia Weber; Sveinbjornsson, Gardar; Tucker, Nathan R; Choi, Seung Hoan; Chaffin, Mark D; Roselli, Carolina; Barnes, Michael R; Mifsud, Borbala; Warren, Helen R; et al. (Nat Commun, 2020)
The electrocardiographic PR interval reflects atrioventricular conduction, and is associated with conduction abnormalities, pacemaker implantation, atrial fibrillation (AF), and cardiovascular mortality. Here we report a multi-ancestry (N = 293,051) genome-wide association meta-analysis for the PR interval, discovering 202 loci of which 141 have not previously been reported. Variants at identified loci increase the percentage of heritability explained, from 33.5% to 62.6%. We observe enrichment for cardiac muscle developmental/contractile and cytoskeletal genes, highlighting key regulation processes for atrioventricular conduction. Additionally, 8 loci not previously reported harbor genes underlying inherited arrhythmic syndromes and/or cardiomyopathies suggesting a role for these genes in cardiovascular pathology in the general population. We show that polygenic predisposition to PR interval duration is an endophenotype for cardiovascular disease, including distal conduction disease, AF, and atrioventricular pre-excitation. These findings advance our understanding of the polygenic basis of cardiac conduction, and the genetic relationship between PR interval duration and cardiovascular disease.

Orthostatic Hypotension, Dizziness, Neurology Outcomes, and Death in Older Adults. - Juraschek, Stephen P; Longstreth, W T; Lopez, Oscar L; Gottdiener, John S; Lipsitz, Lewis A; Kuller, Lewis H; Mukamal, Kenneth J (Neurology, 2020)
OBJECTIVE: To test the hypothesis that orthostatic hypotension (OH) might cause cerebral hypoperfusion and injury, we examined the longitudinal relationship between orthostatic hypotension (OH) or orthostatic symptoms and incident neurologic outcomes in a community population of older adults. METHODS: Cardiovascular Health Study (CHS) participants (≥65yrs) without dementia or stroke had blood pressure (BP) measured after lying 20-minutes and after standing 3-minutes. Participants reported dizziness immediately upon standing and any dizziness in the past 2wks. OH was defined as a drop in standing systolic/diastolic BP ≥20/≥10mmHg. We determined the association between OH or dizziness with (1) MRI brain findings (ventricular size, white matter hyperintensities, brain infarcts) using linear or logistic regression, (2) cognitive function (baseline and over time) using generalized estimating equations, and (3) prospective adjudicated events (dementia, stroke, death) using Cox models. Models were adjusted for demographic characteristics and OH risk factors. We used multiple imputation to account for missing OH or dizziness (N=534). RESULTS: Prior to imputation, there were 5,007 participants (mean age 72.7±5.5yrs, 57.6% women, 10.9% black, 16% with OH). OH was modestly associated with death (HR=1.11; 95%CI:1.02,1.20), but not MRI findings, cognition, dementia, or stroke. In contrast, dizziness upon standing was associated with lower baseline cognition (β=-1.20;-1.94,-0.47), incident dementia (HR=1.32;1.04,1.62), incident stroke (HR=1.22;1.06,1.41), and death (HR=1.13; 1.06,1.21). Similarly, dizziness over the past two weeks was associated with higher white matter grade (β=0.16;0.03,0.30), brain infarcts (OR=1.31;1.06,1.63), lower baseline cognition (β=-1.18;-2.01,-0.34), and death (HR=1.13;1.04,1.22). CONCLUSIONS: Dizziness was more consistently associated with neurologic outcomes than OH 3-minutes after standing. Delayed OH assessments may miss pathologic information related to cerebral injury.

Plasma Ceramides and Sphingomyelins in Relation to Atrial Fibrillation Risk: The Cardiovascular Health Study. - Jensen, Paul N; Fretts, Amanda M; Hoofnagle, Andrew N; Sitlani, Colleen M; McKnight, Barbara; King, Irena B; Siscovick, David S; Psaty, Bruce M; Heckbert, Susan R; Mozaffarian, Dariush; Sotoodehnia, Nona; Lemaitre, Rozenn N (J Am Heart Assoc, 2020)
Background Ceramides exhibit multiple biological activities that may influence the pathophysiological characteristics of atrial fibrillation (AF). Whether the length of the saturated fatty acid carried by the ceramide or their sphingomyelin precursors are associated with AF risk is not known. Methods and Results Among 4206 CHS (Cardiovascular Health Study) participants (mean age, 76 years; 40% men) who were free of prevalent AF at baseline, we identified 1198 incident AF cases over a median 8.7 years of follow-up. We examined 8 sphingolipid species: ceramide and sphingomyelin species with palmitic acid and species with very-long-chain saturated fatty acids: arachidic; behenic; and lignoceric. In adjusted Cox regression analyses, ceramides and sphingomyelins with very-long-chain saturated fatty acids were associated with reduced AF risk (ie, per 2-fold higher ceramide with behenic acid hazard ratio, 0.71; 95% CI, 0.59-0.86; sphingomyelin with behenic acid hazard ratio, 0.60; 95% CI, 0.46-0.77). In contrast, ceramides and sphingomyelins with palmitic acid were associated with increased AF risk (ceramide with palmitic acid hazard ratio, 1.31; 95% CI, 1.03-1.66; sphingomyelin with palmitic acid hazard ratio, 1.73; 95% CI, 1.18-2.55). Associations were attenuated with adjustment for NT-proBNP (N-terminal pro-B-type natriuretic peptide), but did not differ significantly by age, sex, race, body mass index, or history of coronary heart disease. Conclusions Our findings suggest that several ceramide and sphingomyelin species are associated with incident AF, and that these associations differ on the basis of the fatty acid. Ceramides and sphingomyelins with palmitic acid were associated with increased AF risk, whereas ceramides and sphingomyelins with very-long-chain saturated fatty acids were associated with reduced AF risk.

The Polygenic and Monogenic Basis of Blood Traits and Diseases. - Vuckovic, Dragana; Bao, Erik L; Akbari, Parsa; Lareau, Caleb A; Mousas, Abdou; Jiang, Tao; Chen, Ming-Huei; Raffield, Laura M; Tardaguila, Manuel; Huffman, Jennifer E; Ritchie, Scott C; Megy, Karyn; et al. (Cell, 2020)
Blood cells play essential roles in human health, underpinning physiological processes such as immunity, oxygen transport, and clotting, which when perturbed cause a significant global health burden. Here we integrate data from UK Biobank and a large-scale international collaborative effort, including data for 563,085 European ancestry participants, and discover 5,106 new genetic variants independently associated with 29 blood cell phenotypes covering a range of variation impacting hematopoiesis. We holistically characterize the genetic architecture of hematopoiesis, assess the relevance of the omnigenic model to blood cell phenotypes, delineate relevant hematopoietic cell states influenced by regulatory genetic variants and gene networks, identify novel splice-altering variants mediating the associations, and assess the polygenic prediction potential for blood traits and clinical disorders at the interface of complex and Mendelian genetics. These results show the power of large-scale blood cell trait GWAS to interrogate clinically meaningful variants across a wide allelic spectrum of human variation.

Sex Differences in the Association Between Pentraxin 3 and Cognitive Decline: The Cardiovascular Health Study. - Miller, Lindsay M; Jenny, Nancy S; Rawlings, Andreea M; Arnold, Alice M; Fitzpatrick, Annette L; Lopez, Oscar L; Odden, Michelle C (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: The importance of systemic inflammation, measured by C-reactive protein, in cognitive decline has been demonstrated; however, the role of vascular inflammation is less understood. Pentraxin 3 (PTX3) is a novel marker of vascular inflammation. METHODS: We followed adults 65 and older, free of cardiovascular disease (CVD) for up to 9 years (n = 1,547) in the Cardiovascular Health Study. We evaluated the relationship between PTX3 and change in cognitive function, measured using the Modified Mini-Mental State Examination (3MSE), and incident cognitive impairment (3MSE < 80). Mediation by CVD events, and effect modification by sex and apolipoprotein E ɛ4 allele (APOE4) were also examined. RESULTS: The average decline in 3MSE was 0.77 points per year. The association between PTX3 and change in 3MSE differed between women and men (p = .02). In the adjusted model, each standard deviation higher in PTX3 was associated with a 0.20 greater decline in 3MSE score per year in women over follow-up (95% CI: -0. 37, -0.03; p = .02), compared to no change in men (β = 0.07; 95% CI: -0.08, 0.22). CVD events had a minor effect on the associations. No effect modification by APOE4 was found, although we observed the association of PTX3 and cognitive impairment in women was attenuated and nonsignificant after adjustment for APOE4. There was a paradoxical protective association between PTX3 and reduced cognitive impairment in men, even after adjustment for APOE4. CONCLUSIONS: We found that vascular inflammation was significantly associated with cognitive decline in older women, but not men.

Sex-Specific Associations of Cardiovascular Risk Factors and Biomarkers With Incident Heart Failure. - Suthahar, Navin; Lau, Emily S; Blaha, Michael J; Paniagua, Samantha M; Larson, Martin G; Psaty, Bruce M; Benjamin, Emelia J; Allison, Matthew A; Bartz, Traci M; Januzzi, James L; Levy, Daniel; Meems, Laura M G; et al. (J Am Coll Cardiol, 2020)
BACKGROUND: Whether cardiovascular (CV) disease risk factors and biomarkers associate differentially with heart failure (HF) risk in men and women is unclear. OBJECTIVES: The purpose of this study was to evaluate sex-specific associations of CV risk factors and biomarkers with incident HF. METHODS: The analysis was performed using data from 4 community-based cohorts with 12.5 years of follow-up. Participants (recruited between 1989 and 2002) were free of HF at baseline. Biomarker measurements included natriuretic peptides, cardiac troponins, plasminogen activator inhibitor-1, D-dimer, fibrinogen, C-reactive protein, sST2, galectin-3, cystatin-C, and urinary albumin-to-creatinine ratio. RESULTS: Among 22,756 participants (mean age 60 ± 13 years, 53% women), HF occurred in 2,095 participants (47% women). Age, smoking, type 2 diabetes mellitus, hypertension, body mass index, atrial fibrillation, myocardial infarction, left ventricular hypertrophy, and left bundle branch block were strongly associated with HF in both sexes (p < 0.001), and the combined clinical model had good discrimination in men (C-statistic = 0.80) and in women (C-statistic = 0.83). The majority of biomarkers were strongly and similarly associated with HF in both sexes. The clinical model improved modestly after adding natriuretic peptides in men (ΔC-statistic = 0.006; likelihood ratio chi-square = 146; p < 0.001), and after adding cardiac troponins in women (ΔC-statistic = 0.003; likelihood ratio chi-square = 73; p < 0.001). CONCLUSIONS: CV risk factors are strongly and similarly associated with incident HF in both sexes, highlighting the similar importance of risk factor control in reducing HF risk in the community. There are subtle sex-related differences in the predictive value of individual biomarkers, but the overall improvement in HF risk estimation when included in a clinical HF risk prediction model is limited in both sexes.

Trans-ethnic and Ancestry-Specific Blood-Cell Genetics in 746,667 Individuals from 5 Global Populations. - Chen, Ming-Huei; Raffield, Laura M; Mousas, Abdou; Sakaue, Saori; Huffman, Jennifer E; Moscati, Arden; Trivedi, Bhavi; Jiang, Tao; Akbari, Parsa; Vuckovic, Dragana; Bao, Erik L; Zhong, Xue; et al. (Cell, 2020)
Most loci identified by GWASs have been found in populations of European ancestry (EUR). In trans-ethnic meta-analyses for 15 hematological traits in 746,667 participants, including 184,535 non-EUR individuals, we identified 5,552 trait-variant associations at p < 5 × 10, including 71 novel associations not found in EUR populations. We also identified 28 additional novel variants in ancestry-specific, non-EUR meta-analyses, including an IL7 missense variant in South Asians associated with lymphocyte count in vivo and IL-7 secretion levels in vitro. Fine-mapping prioritized variants annotated as functional and generated 95% credible sets that were 30% smaller when using the trans-ethnic as opposed to the EUR-only results. We explored the clinical significance and predictive value of trans-ethnic variants in multiple populations and compared genetic architecture and the effect of natural selection on these blood phenotypes between populations. Altogether, our results for hematological traits highlight the value of a more global representation of populations in genetic studies.

Whole Blood DNA Methylation Signatures of Diet Are Associated With Cardiovascular Disease Risk Factors and All-Cause Mortality. - Ma, Jiantao; Rebholz, Casey M; Braun, Kim V E; Reynolds, Lindsay M; Aslibekyan, Stella; Xia, Rui; Biligowda, Niranjan G; Huan, Tianxiao; Liu, Chunyu; Mendelson, Michael M; Joehanes, Roby; Hu, Emily A; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: DNA methylation patterns associated with habitual diet have not been well studied. METHODS: Diet quality was characterized using a Mediterranean-style diet score and the Alternative Healthy Eating Index score. We conducted ethnicity-specific and trans-ethnic epigenome-wide association analyses for diet quality and leukocyte-derived DNA methylation at over 400 000 CpGs (cytosine-guanine dinucleotides) in 5 population-based cohorts including 6662 European ancestry, 2702 African ancestry, and 360 Hispanic ancestry participants. For diet-associated CpGs identified in epigenome-wide analyses, we conducted Mendelian randomization (MR) analysis to examine their relations to cardiovascular disease risk factors and examined their longitudinal associations with all-cause mortality. RESULTS: We identified 30 CpGs associated with either Mediterranean-style diet score or Alternative Healthy Eating Index, or both, in European ancestry participants. Among these CpGs, 12 CpGs were significantly associated with all-cause mortality (Bonferroni corrected <1.6×10). Hypermethylation of cg18181703 () was associated with higher scores of both Mediterranean-style diet score and Alternative Healthy Eating Index and lower risk for all-cause mortality (=5.7×10). Ten additional diet-associated CpGs were nominally associated with all-cause mortality (<0.05). MR analysis revealed 8 putatively causal associations for 6 CpGs with 4 cardiovascular disease risk factors (body mass index, triglycerides, high-density lipoprotein cholesterol concentrations, and type 2 diabetes mellitus; Bonferroni corrected MR <4.5×10). For example, hypermethylation of cg11250194 () was associated with lower triglyceride concentrations (MR, =1.5×10).and hypermethylation of cg02079413 (; ) was associated with body mass index (corrected MR, =1×10). CONCLUSIONS: Habitual diet quality was associated with differential peripheral leukocyte DNA methylation levels of 30 CpGs, most of which were also associated with multiple health outcomes, in European ancestry individuals. These findings demonstrate that integrative genomic analysis of dietary information may reveal molecular targets for disease prevention and treatment.

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

{Association between ABO haplotypes and the risk of venous thrombosis: impact on disease risk estimation - Goumidi, L.; Thibord, F.; Wiggins, K. L.; Li-Gao, R.; Brown, M. R.; van Hylckama Vlieg, A.; Souto, J. C.; Soria, J. M.; Ibrahim-Kosta, M.; Saut, N.; Daian, D.; Olaso, R.; et al. (Blood, 2021)
10.1182/blood.2020008997Genetic risk score (GRS) analysis is a popular approach to derive individual risk prediction models for complex diseases. In venous thrombosis (VT), such type of analysis shall integrate information at the ABO blood group locus, which is one of the major susceptibility loci. However, there is no consensus about which single nucleotide polymorphisms (SNPs) must be investigated when properly assessing association between ABO locus and VT risk. Using comprehensive haplotype analyses of ABO blood group tagging SNPs in 5425 cases and 8445 controls from 6 studies, we demonstrate that using only rs8176719 (tagging O1) to correctly assess the impact of ABO locus on VT risk is suboptimal, because 5% of rs8176719-delG carriers do not have an increased risk of developing VT. Instead, we recommend the use of 4 SNPs, rs2519093 (tagging A1), rs1053878 (A2), rs8176743 (B), and rs41302905 (O2), when assessing the impact of ABO locus on VT risk to avoid any risk misestimation. Compared with the O1 haplotype, the A2 haplotype is associated with a modest increase in VT risk (odds ratio, ∼1.2), the A1 and B haplotypes are associated with an ∼1.8-fold increased risk, whereas the O2 haplotype tends to be slightly protective (odds ratio, ∼0.80). In addition, although the A1 and B blood groups are associated with increased von Willebrand factor and factor VIII plasma levels, only the A1 blood group is associated with ICAM levels, but in an opposite direction, leaving additional avenues to be explored to fully understand the spectrum of biological effects mediated by ABO locus on cardiovascular traits.

Association Between Preserved Ratio Impaired Spirometry and Clinical Outcomes in US Adults. - Wan, Emily S; Balte, Pallavi; Schwartz, Joseph E; Bhatt, Surya P; Cassano, Patricia A; Couper, David; Daviglus, Martha L; Dransfield, Mark T; Gharib, Sina A; Jacobs, David R; Kalhan, Ravi; London, Stephanie J; et al. (JAMA, 2021)
Importance: Chronic lung diseases are a leading cause of morbidity and mortality. Unlike chronic obstructive pulmonary disease, clinical outcomes associated with proportional reductions in expiratory lung volumes without obstruction, otherwise known as preserved ratio impaired spirometry (PRISm), are poorly understood. Objective: To examine the prevalence, correlates, and clinical outcomes associated with PRISm in US adults. Design, Setting, and Participants: The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study was a retrospective study with harmonized pooled data from 9 US general population-based cohorts (enrollment, 65 251 participants aged 18 to 102 years of whom 53 701 participants had valid baseline lung function) conducted from 1971-2011 (final follow-up, December 2018). Exposures: Participants were categorized into mutually exclusive groups by baseline lung function. PRISm was defined as the ratio of forced expiratory volume in the first second to forced vital capacity (FEV1:FVC) greater than or equal to 0.70 and FEV1 less than 80% predicted; obstructive spirometry FEV1:FVC ratio of less than 0.70; and normal spirometry FEV1:FVC ratio greater than or equal to 0.7 and FEV1 greater than or equal to 80% predicted. Main Outcomes and Measures: Main outcomes were all-cause mortality, respiratory-related mortality, coronary heart disease (CHD)-related mortality, respiratory-related events (hospitalizations and mortality), and CHD-related events (hospitalizations and mortality) classified by adjudication or validated administrative criteria. Absolute risks were adjusted for age and smoking status. Poisson and Cox proportional hazards models comparing PRISm vs normal spirometry were adjusted for age, sex, race and ethnicity, education, body mass index, smoking status, cohort, and comorbidities. Results: Among all participants (mean [SD] age, 53.2 [15.8] years, 56.4% women, 48.5% never-smokers), 4582 (8.5%) had PRISm. The presence of PRISm relative to normal spirometry was significantly associated with obesity (prevalence, 48.3% vs 31.4%; prevalence ratio [PR], 1.68 [95% CI, 1.55-1.82]), underweight (prevalence, 1.4% vs 1.0%; PR, 2.20 [95% CI, 1.72-2.82]), female sex (prevalence, 60.3% vs 59.0%; PR, 1.07 [95% CI, 1.01-1.13]), and current smoking (prevalence, 25.2% vs 17.5%; PR, 1.33 [95% CI, 1.22-1.45]). PRISm, compared with normal spirometry, was significantly associated with greater all-cause mortality (29.6/1000 person-years vs 18.0/1000 person-years; difference, 11.6/1000 person-years [95% CI, 10.0-13.1]; adjusted hazard ratio [HR], 1.50 [95% CI, 1.42-1.59]), respiratory-related mortality (2.1/1000 person-years vs 1.0/1000 person-years; difference, 1.1/1000 person-years [95% CI, 0.7-1.6]; adjusted HR, 1.95 [95% CI, 1.54-2.48]), CHD-related mortality (5.4/1000 person-years vs 2.6/1000 person-years; difference, 2.7/1000 person-years [95% CI, 2.1-3.4]; adjusted HR, 1.55 [95% CI, 1.36-1.77]), respiratory-related events (12.2/1000 person-years vs 6.0/1000 person-years; difference, 6.2/1000 person-years [95% CI, 4.9-7.5]; adjusted HR, 1.90 [95% CI, 1.69-2.14]), and CHD-related events (11.7/1000 person-years vs 7.0/1000 person-years; difference, 4.7/1000 person-years [95% CI, 3.7-5.8]; adjusted HR, 1.30 [95% CI, 1.18-1.42]). Conclusions and Relevance: In a large, population-based sample of US adults, baseline PRISm, compared with normal spirometry, was associated with a small but statistically significant increased risk for mortality and adverse cardiovascular and respiratory outcomes. Further research is needed to explore whether this association is causal.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Forced Expiratory Volume; Humans; Lung; Lung Diseases; Male; Middle Aged; Prevalence; Retrospective Studies; Spirometry; United States; Vital Capacity

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Association of Trimethylamine N-Oxide and Related Metabolites in Plasma and Incident Type 2 Diabetes: The Cardiovascular Health Study. - Lemaitre, Rozenn N; Jensen, Paul N; Wang, Zeneng; Fretts, Amanda M; McKnight, Barbara; Nemet, Ina; Biggs, Mary L; Sotoodehnia, Nona; de Oliveira Otto, Marcia C; Psaty, Bruce M; Siscovick, David S; Hazen, Stanley L; et al. (JAMA Netw Open, 2021)
Importance: Although rodent studies suggest that trimethylamine N-oxide (TMAO) influences glucose homeostasis and risk of type 2 diabetes, evidence in humans is limited. Objective: To examine the associations of serial measures of plasma TMAO and related metabolite concentrations with incident type 2 diabetes, fasting plasma insulin and glucose levels, and the Gutt insulin sensitivity index (ISI). Design, Setting, and Participants: This prospective cohort design assessed the association of plasma TMAO and related metabolite concentrations with diabetes outcome, whereas a cross-sectional design assessed the association with insulin and glucose levels and Gutt ISI. The participants were a cohort of older US adults from the Cardiovascular Health Study (CHS). Data from June 1989 to May 1990, from November 1992 to June 1993, and from June 1995 to June 1997 were included, with follow-up through June 2010. Levels of TMAO and related metabolites were measured in CHS plasma samples. Data were analyzed from July 2019 to September 2020. Exposures: Plasma concentrations of TMAO, carnitine, betaine, choline, crotonobetaine, and γ-butyrobetaine, measured by high-performance liquid chromatography and mass spectrometry. Main Outcomes and Measures: Linear regression for associations of TMAO and related metabolites with insulin and glucose levels and Gutt ISI, and proportional hazards regression for associations with diabetes. Results: The study included 4442 participants without diabetes at baseline (mean [SD] age, 73 [6] years at entry; 2710 [61%] women). In multivariable analyses, plasma TMAO, carnitine, crotonobetaine, and γ-butyrobetaine concentrations were positively associated with fasting insulin level (insulin mean geometric ratio comparing fifth with first quintiles of metabolite concentration: 1.07 [95% CI, 1.04-1.10] for TMAO; 1.07 [95% CI, 1.03-1.10] for carnitine; 1.05 [95% CI, 1.02-1.08] for crotonobetaine; and 1.06 [95% CI, 1.02-1.09] for γ-butyrobetaine). In contrast, betaine and choline concentrations were associated with greater insulin sensitivity (mean difference in Gutt ISI comparing fifth with first quintiles: 6.46 [95% CI, 4.32-8.60] and 2.27 [95% CI, 0.16-4.38], respectively). Incident diabetes was identified in 661 participants during a median 12.1 (interquartile range, 6.9-17.1) years of follow-up. In multivariable analyses, TMAO and metabolites were not significantly associated with type 2 diabetes risk (hazard ratios of diabetes comparing fifth with first quintile: 1.20 [95% CI, 0.94-1.55] for TMAO; 0.96 [95% CI, 0.74-1.24] for choline; 0.88 [95% CI, 0.67-1.15] for betaine; 1.07 [95% CI, 0.83-1.37] for carnitine; 0.79 [95% CI, 0.60-1.04] for γ-butyrobetaine; and 1.06 [95% CI, 0.83-1.35] for crotonobetaine). Conclusions and Relevance: Plasma TMAO and related metabolites were not significantly associated with type 2 diabetes among older adults. The metabolites TMAO, carnitine, γ-butyrobetaine, and crotonobetaine may be associated with insulin resistance, and betaine and choline may be associated with greater insulin sensitivity, but temporality of the associations was not established.

BinomiRare: A robust test for association of a rare genetic variant with a binary outcome for mixed models and any case-control proportion. - Sofer, Tamar; Lee, Jiwon; Kurniansyah, Nuzulul; Jain, Deepti; Laurie, Cecelia A; Gogarten, Stephanie M; Conomos, Matthew P; Heavner, Ben; Hu, Yao; Kooperberg, Charles; Haessler, Jeffrey; Vasan, Ramachandran S; et al. (HGG Adv, 2021)
Whole-genome sequencing (WGS) and whole-exome sequencing studies have become increasingly available and are being used to identify rare genetic variants associated with health and disease outcomes. Investigators routinely use mixed models to account for genetic relatedness or other clustering variables (e.g., family or household) when testing genetic associations. However, no existing tests of the association of a rare variant with a binary outcome in the presence of correlated data control the type 1 error where there are (1) few individuals harboring the rare allele, (2) a small proportion of cases relative to controls, and (3) covariates to adjust for. Here, we address all three issues in developing a framework for testing rare variant association with a binary trait in individuals harboring at least one risk allele. In this framework, we estimate outcome probabilities under the null hypothesis and then use them, within the individuals with at least one risk allele, to test variant associations. We extend the BinomiRare test, which was previously proposed for independent observations, and develop the Conway-Maxwell-Poisson (CMP) test and study their properties in simulations. We show that the BinomiRare test always controls the type 1 error, while the CMP test sometimes does not. We then use the BinomiRare test to test the association of rare genetic variants in target genes with small-vessel disease (SVD) stroke, short sleep, and venous thromboembolism (VTE), in whole-genome sequence data from the Trans-Omics for Precision Medicine (TOPMed) program.

Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies. - Harris, William S; Tintle, Nathan L; Imamura, Fumiaki; Qian, Frank; Korat, Andres V Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K; et al. (Nat Commun, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15-18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20-22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death.
Keywords: Aged; Aged, 80 and over; Cause of Death; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Male; Middle Aged; Mortality, Premature; Prospective Studies; Protective Factors; Risk Factors

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.

Circulating Ceramides and Sphingomyelins and Risk of Mortality: The Cardiovascular Health Study. - Fretts, Amanda M; Jensen, Paul N; Hoofnagle, Andrew N; McKnight, Barbara; Sitlani, Colleen M; Siscovick, David S; King, Irena B; Psaty, Bruce M; Sotoodehnia, Nona; Lemaitre, Rozenn N (Clin Chem, 2021)
BACKGROUND: Recent studies suggest that associations of ceramides (Cer) and sphingomyelins (SM) with health outcomes differ according to the fatty acid acylated to the sphingoid backbone. The purpose of this study was to assess associations of Cer and SM species with mortality. METHODS: The study population included participants from the Cardiovascular Health Study (CHS), a community-based cohort of adults aged ≥65 years who were followed from 1992-2015 (n = 4612). Associations of plasma Cer and SM species carrying long-chain (i.e., 16:0) and very-long-chain (i.e., 20:0, 22:0, 24:0) saturated fatty acids with mortality were assessed using Cox proportional hazards models. RESULTS: During a median follow-up of 10.2 years, 4099 deaths occurred. High concentrations of Cer and SM carrying fatty acid 16:0 were each associated with an increased risk of mortality. Conversely, high concentrations of several ceramide and sphingomyelin species carrying longer fatty acids were each associated with a decreased risk of mortality. The hazard ratios for total mortality per 2-fold difference in each Cer and SM species were: 1.89 (95% CI), 1.65-2.17 for Cer-16, 0.79 (95% CI, 0.70-0.88) for Cer-22, 0.74 (95% CI, 0.65-0.84) for Cer-24, 2.51 (95% CI, 2.01-3.14) for SM-16, 0.68 (95% CI, 0.58-0.79) for SM-20, 0.57 (95% CI, 0.49-0.67) for SM-22, and 0.66 (0.57-0.75) for SM-24. We found no association of Cer-20 with risk of death. CONCLUSIONS: Associations of Cer and SM with the risk of death differ according to the length of their acylated saturated fatty acid. Future studies are needed to explore mechanisms underlying these relationships.

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Discovery and fine-mapping of height loci via high-density imputation of GWASs in individuals of African ancestry. - Graff, Mariaelisa; Justice, Anne E; Young, Kristin L; Marouli, Eirini; Zhang, Xinruo; Fine, Rebecca S; Lim, Elise; Buchanan, Victoria; Rand, Kristin; Feitosa, Mary F; Wojczynski, Mary K; Yanek, Lisa R; et al. (Am J Hum Genet, 2021)
Although many loci have been associated with height in European ancestry populations, very few have been identified in African ancestry individuals. Furthermore, many of the known loci have yet to be generalized to and fine-mapped within a large-scale African ancestry sample. We performed sex-combined and sex-stratified meta-analyses in up to 52,764 individuals with height and genome-wide genotyping data from the African Ancestry Anthropometry Genetics Consortium (AAAGC). We additionally combined our African ancestry meta-analysis results with published European genome-wide association study (GWAS) data. In the African ancestry analyses, we identified three novel loci (SLC4A3, NCOA2, ECD/FAM149B1) in sex-combined results and two loci (CRB1, KLF6) in women only. In the African plus European sex-combined GWAS, we identified an additional three novel loci (RCCD1, G6PC3, CEP95) which were equally driven by AAAGC and European results. Among 39 genome-wide significant signals at known loci, conditioning index SNPs from European studies identified 20 secondary signals. Two of the 20 new secondary signals and none of the 8 novel loci had minor allele frequencies (MAF) < 5%. Of 802 known European height signals, 643 displayed directionally consistent associations with height, of which 205 were nominally significant (p < 0.05) in the African ancestry sex-combined sample. Furthermore, 148 of 241 loci contained ≤20 variants in the credible sets that jointly account for 99% of the posterior probability of driving the associations. In summary, trans-ethnic meta-analyses revealed novel signals and further improved fine-mapping of putative causal variants in loci shared between African and European ancestry populations.

Egg consumption, overall diet quality, and risk of type 2 diabetes and coronary heart disease: A pooling project of US prospective cohorts. - Djoussé, Luc; Zhou, Guohai; McClelland, Robyn L; Ma, Nanxun; Zhou, Xia; Kabagambe, Edmond K; Talegawkar, Sameera A; Judd, Suzanne E; Biggs, Mary L; Fitzpatrick, Annette L; Clark, Cheryl R; Gagnon, David R; et al. (Clin Nutr, 2021)
BACKGROUND AND AIMS: Data on the relation of egg consumption with risk of type 2 diabetes (T2D) and coronary heart disease (CHD) are limited and inconsistent. Few studies have controlled for overall dietary patterns in egg-T2D or egg-CHD analyses, and it is unclear whether any observed elevated risks of T2D and CHD with frequent egg consumption is real or due to confounding by dietary habits. We tested the hypothesis that frequent egg consumption is associated with a higher risk of T2D and CHD risk after adjustment for overall dietary patterns among adults. DESIGN: We used prospective cohort design to complete time-to-event analyses. METHODS: We pooled de novo, harmonized, individual-level analyses from nine US cohorts (n = 103,811). Cox regression was used to estimate hazard ratios separately in each cohort adjusting for age, ethnicity, body mass index (BMI), exercise, smoking, alcohol intake, and dietary patterns. We pooled cohort-specific results using an inverse-variance weighted method to estimate summary relative risks. RESULTS: Median age ranged from 25 to 72 years. Median egg consumption was 1 egg per week in most of the cohorts. While egg consumption up to one per week was not associated with T2D risk, consumption of ≥2 eggs per week was associated with elevated risk [27% elevated risk of T2D comparing 7+ eggs/week with none (95% CI: 16%-37%)]. There was little evidence for heterogeneity across cohorts and we observed similar conclusions when stratified by BMI. Overall, egg consumption was not associated with the risk of CHD. However, in a sensitivity analysis, there was a 30% higher risk of CHD (95% CI: 3%-56%) restricted to older adults consuming 5-6 eggs/week. CONCLUSIONS: Our data showed an elevated risk of T2D with egg consumption of ≥2 eggs per week but not with <2 eggs/week. While there was no overall association of egg consumption with CHD risk, the elevated CHD observed with consumption of 5-6 eggs/week in older cohorts merits further investigation.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Diet; Eggs; Humans; Middle Aged; Prospective Studies; Risk Factors; United States

Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus. - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Kuhns, Victoria L Halperin; et al. (Nat Commun, 2021)
Elevated serum urate levels, a complex trait and major risk factor for incident gout, are correlated with cardiometabolic traits via incompletely understood mechanisms. DNA methylation in whole blood captures genetic and environmental influences and is assessed in transethnic meta-analysis of epigenome-wide association studies (EWAS) of serum urate (discovery, n = 12,474, replication, n = 5522). The 100 replicated, epigenome-wide significant (p < 1.1E-7) CpGs explain 11.6% of the serum urate variance. At SLC2A9, the serum urate locus with the largest effect in genome-wide association studies (GWAS), five CpGs are associated with SLC2A9 gene expression. Four CpGs at SLC2A9 have significant causal effects on serum urate levels and/or gout, and two of these partly mediate the effects of urate-associated GWAS variants. In other genes, including SLC7A11 and PHGDH, 17 urate-associated CpGs are associated with conditions defining metabolic syndrome, suggesting that these CpGs may represent a blood DNA methylation signature of cardiometabolic risk factors. This study demonstrates that EWAS can provide new insights into GWAS loci and the correlation of serum urate with other complex traits.
Keywords: Amino Acid Transport System y+; Cohort Studies; CpG Islands; DNA Methylation; Epigenome; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Transport Proteins, Facilitative; Gout; Humans; Male; Uric Acid

Estimating Systolic Blood Pressure Intervention Trial Participant Posttrial Survival Using Pooled Epidemiologic Cohort Data. - Bellows, Brandon K; Zhang, Yiyi; Zhang, Zugui; Lloyd-Jones, Donald M; Bress, Adam P; King, Jordan B; Kolm, Paul; Cushman, William C; Johnson, Karen C; Tamariz, Leonardo; Oelsner, Elizabeth C; Shea, Steven; et al. (J Am Heart Assoc, 2021)
Background Intensive systolic blood pressure treatment (<120 mm Hg) in SPRINT (Systolic Blood Pressure Intervention Trial) improved survival compared with standard treatment (<140 mm Hg) over a median follow-up of 3.3 years. We projected life expectancy after observed follow-up in SPRINT using SPRINT-eligible participants in the NHLBI-PCS (National Heart, Lung, and Blood Institute Pooled Cohorts Study). Methods and Results We used propensity scores to weight SPRINT-eligible NHLBI-PCS participants to resemble SPRINT participants. In SPRINT participants, we estimated in-trial survival (<4 years) using a time-based flexible parametric survival model. In SPRINT-eligible NHLBI-PCS participants, we estimated posttrial survival (≥4 years) using an age-based flexible parametric survival model and applied the formula to SPRINT participants to predict posttrial survival. We projected overall life expectancy for each SPRINT participant and compared it to parametric regression (eg, Gompertz) projections based on SPRINT data alone. We included 8584 SPRINT and 10 593 SPRINT-eligible NHLBI-PCS participants. After propensity weighting, mean (SD) age was 67.9 (9.4) and 68.2 (8.8) years, and 35.5% and 37.6% were women in SPRINT and NHLBI-PCS, respectively. Using the NHLBI-PCS-based method, projected mean life expectancy from randomization was 21.0 (7.4) years with intensive and 19.1 (7.2) years with standard treatment. Using the Gompertz regression, life expectancy was 11.2 (2.3) years with intensive and 10.5 (2.2) years with standard treatment. Conclusions Combining SPRINT and NHLBI-PCS observed data likely offers a more realistic estimate of life expectancy than parametrically extrapolating SPRINT data alone. These results offer insight into the potential long-term effectiveness of intensive SBP goals.

FGL1 as a modulator of plasma D-dimer levels: Exome-wide marker analysis of plasma tPA, PAI-1, and D-dimer. - Thibord, Florian; Song, Ci; Pattee, Jack; Rodriguez, Benjamin A T; Chen, Ming-Huei; O'Donnell, Christopher J; Kleber, Marcus E; Delgado, Graciela E; Guo, Xiuqing; Yao, Jie; Taylor, Kent D; Ozel, Ayse Bilge; et al. (J Thromb Haemost, 2021)
BACKGROUND: Use of targeted exome-arrays with common, rare variants and functionally enriched variation has led to discovery of new genes contributing to population variation in risk factors. Plasminogen activator-inhibitor 1 (PAI-1), tissue plasminogen activator (tPA), and the plasma product D-dimer are important components of the fibrinolytic system. There have been few large-scale genome-wide or exome-wide studies of PAI-1, tPA, and D-dimer. OBJECTIVES: We sought to discover new genetic loci contributing to variation in these traits using an exome-array approach. METHODS: Cohort-level analyses and fixed effects meta-analyses of PAI-1 (n = 15 603), tPA (n = 6876,) and D-dimer (n = 19 306) from 12 cohorts of European ancestry with diverse study design were conducted, including single-variant analyses and gene-based burden testing. RESULTS: Five variants located in NME7, FGL1, and the fibrinogen locus, all associated with D-dimer levels, achieved genome-wide significance (P < 5 × 10 ). Replication was sought for these 5 variants, as well as 45 well-imputed variants with P < 1 × 10 in the discovery using an independent cohort. Replication was observed for three out of the five significant associations, including a novel and uncommon (0.013 allele frequency) coding variant p.Trp256Leu in FGL1 (fibrinogen-like-1) with increased plasma D-dimer levels. Additionally, a candidate-gene approach revealed a suggestive association for a coding variant (rs143202684-C) in SERPINB2, and suggestive associations with consistent effect in the replication analysis include an intronic variant (rs11057830-A) in SCARB1 associated with increased D-dimer levels. CONCLUSION: This work provides new evidence for a role of FGL1 in hemostasis.

Genetic insights into biological mechanisms governing human ovarian ageing. - Ruth, Katherine S; Day, Felix R; Hussain, Jazib; Martínez-Marchal, Ana; Aiken, Catherine E; Azad, Ajuna; Thompson, Deborah J; Knoblochova, Lucie; Abe, Hironori; Tarry-Adkins, Jane L; Gonzalez, Javier Martin; Fontanillas, Pierre; et al. (Nature, 2021)
Reproductive longevity is essential for fertility and influences healthy ageing in women, but insights into its underlying biological mechanisms and treatments to preserve it are limited. Here we identify 290 genetic determinants of ovarian ageing, assessed using normal variation in age at natural menopause (ANM) in about 200,000 women of European ancestry. These common alleles were associated with clinical extremes of ANM; women in the top 1% of genetic susceptibility have an equivalent risk of premature ovarian insufficiency to those carrying monogenic FMR1 premutations. The identified loci implicate a broad range of DNA damage response (DDR) processes and include loss-of-function variants in key DDR-associated genes. Integration with experimental models demonstrates that these DDR processes act across the life-course to shape the ovarian reserve and its rate of depletion. Furthermore, we demonstrate that experimental manipulation of DDR pathways highlighted by human genetics increases fertility and extends reproductive life in mice. Causal inference analyses using the identified genetic variants indicate that extending reproductive life in women improves bone health and reduces risk of type 2 diabetes, but increases the risk of hormone-sensitive cancers. These findings provide insight into the mechanisms that govern ovarian ageing, when they act, and how they might be targeted by therapeutic approaches to extend fertility and prevent disease.

{Genome-Wide Association Study of Circulating Interleukin 6 Levels Identifies Novel Loci - Ahluwalia, T. S.; Prins, B. P.; Abdollahi, M.; Armstrong, N. J.; Aslibekyan, S.; Bain, L.; Jefferis, B.; Baumert, J.; Beekman, M.; Ben-Shlomo, Y.; Bis, J. C.; Mitchell, B. D.; et al. (Hum Mol Genet, 2021)
Interleukin-6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery, and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67 428 (ndiscovery = 52 654 and nreplication = 14 774) individuals of European ancestry. The inverse variance fixed-effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on Chromosome (Chr) 2q14, (pcombined = 1.8 × 10-11), HLA-DRB1/DRB5 rs660895 on Chr6p21 (pcombined = 1.5 × 10-10) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 (pcombined = 1.2 × 10-122). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.

{Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women - Jones, G.; Trajanoska, K.; Santanasto, A. J.; Stringa, N.; Kuo, C. L.; Atkins, J. L.; Lewis, J. R.; Duong, T.; Hong, S.; Biggs, M. L.; Luan, J.; Sarnowski, C.; et al. (Nat Commun, 2021)
Low muscle strength is an important heritable indicator of poor health linked to morbidity and mortality in older people. In a genome-wide association study meta-analysis of 256,523 Europeans aged 60 years and over from 22 cohorts we identify 15 loci associated with muscle weakness (European Working Group on Sarcopenia in Older People definition: n = 48,596 cases, 18.9% of total), including 12 loci not implicated in previous analyses of continuous measures of grip strength. Loci include genes reportedly involved in autoimmune disease (HLA-DQA1 p = 4 × 10-17), arthritis (GDF5 p = 4 × 10-13), cell cycle control and cancer protection, regulation of transcription, and others involved in the development and maintenance of the musculoskeletal system. Using Mendelian randomization we report possible overlapping causal pathways, including diabetes susceptibility, haematological parameters, and the immune system. We conclude that muscle weakness in older adults has distinct mechanisms from continuous strength, including several pathways considered to be hallmarks of ageing.

{The genomics of heart failure: design and rationale of the HERMES consortium - Lumbers, R. T.; Shah, S.; Lin, H.; Czuba, T.; Henry, A.; Swerdlow, D. I.; Malarstig, A.; Andersson, C.; Verweij, N.; Holmes, M. V.; Ärnlöv, J.; Svensson, P.; et al. (ESC Heart Fail, 2021)
The HERMES (HEart failure Molecular Epidemiology for Therapeutic targetS) consortium aims to identify the genomic and molecular basis of heart failure.\ under an additive genetic model.\ HERMES is a global collaboration aiming to (i) identify the genetic determinants of heart failure; (ii) generate insights into the causal pathways leading to heart failure and enable genetic approaches to target prioritization; and (iii) develop genomic tools for disease stratification and risk prediction.

HDL (High-Density Lipoprotein) Subspecies, Prevalent Covert Brain Infarcts, and Incident Overt Ischemic Stroke: Cardiovascular Health Study. - Koch, Manja; Aroner, Sarah A; Fitzpatrick, Annette L; Longstreth, W T; Furtado, Jeremy D; Mukamal, Kenneth J; Jensen, Majken K (Stroke, 2021)
BACKGROUND AND PURPOSE: Whether HDL (high-density lipoprotein) is associated with risk of vascular brain injury is unclear. HDL is comprised of many apo (apolipoprotein) species, creating distinct subtypes of HDL. METHODS: We utilized sandwich ELISA to determine HDL subspecies from plasma collected in 1998/1999 from 2001 CHS (Cardiovascular Health Study) participants (mean age, 80 years). RESULTS: In cross-sectional analyses, participants with higher apoA1 in plasma and lower apoE in HDL were less likely to have prevalent covert magnetic resonance imaging-defined infarcts: odds ratio for apoA1 Q4 versus Q1, 0.68 (95% CI, 0.50-0.93), and odds ratio for apoE Q4 versus Q1, 1.36 (95% CI, 1.01-1.84). Similarly, apoA1 in the subspecies of HDL that lacked apoC3, apoJ, or apoE was inversely related to covert infarcts, and apoE in the subspecies of HDL that lacked apoC3 or apoJ was directly related to covert infarcts in prospective analyses. In contrast, the concentrations of apoA1 and apoE in the complementary subspecies of HDL that contained these apos were unrelated to covert infarcts. Patterns of associations between incident overt ischemic stroke and apoA1, apoE, and apoA1 and apoE in subspecies of HDL were similar to those observed for covert infarcts but less pronounced. CONCLUSIONS: This study highlights HDL subspecies defined by apo content as relevant biomarkers of covert and overt vascular brain injury.

Hemostatic factor levels and cognitive decline in older adults: The Cardiovascular Health Study. - Harrington, Laura B; Ehlert, Alexa N; Thacker, Evan L; Jenny, Nancy S; Lopez, Oscar; Cushman, Mary; Fitzpatrick, Annette; Mukamal, Kenneth J; Jensen, Majken K (J Thromb Haemost, 2021)
BACKGROUND: Hemostasis is a key factor in cerebrovascular disease, but the association of hemostatic factors with cognitive decline is unclear. OBJECTIVE: To prospectively evaluate associations of 20 hemostatic factor levels with changes in cognition during ≥8 years of follow-up in the Cardiovascular Health Study (CHS) of older adults. METHODS: We included participants of an existing CHS cross-sectional substudy (n = 400) with hemostatic factors measured in 1989-1990. Between 1989-1990 and 1998-1999, cognitive function was measured using the Modified Mini-Mental State Examination (3MSE) and Digit Symbol Substitution Tests. Mixed-effects linear regression models estimated change in cognitive function over time, adjusting for sociodemographic and clinical factors and APOE genotype, using Bonferroni adjustment. We also derived principal components to account for the interrelationship among factors. RESULTS: Of 20 factors evaluated individually, only higher levels of plasmin-α -antiplasmin complex (PAP), tissue factor pathway inhibitor (TFPI), and lower factor X (FXc) levels were associated with faster cognitive decline, estimated by annual change in 3MSE points (1 standard deviation PAP β = -0.65, 95% confidence interval [CI]: -1.08 to -0.21; TFPI β = -0.55, 95% CI: -0.90 to -0.19; FXc β = 0.52, 95% CI: 0.21-0.84). One of four principal components, loading positively on D-dimer, prothrombin fragment 1.2 (F1.2), and PAP was significantly associated with change in 3MSE. CONCLUSIONS: Levels of PAP, TPFI, and FXc and a combination of factors driven by PAP, D-dimer, and F1.2 were associated with cognitive decline. Whether these findings can be used to improve dementia prevention or prediction requires further study.

Identification of Functional Genetic Determinants of Cardiac Troponin T and I in a Multiethnic Population and Causal Associations With Atrial Fibrillation. - Yang, Yunju; Bartz, Traci M; Brown, Michael R; Guo, Xiuqing; Zilhão, Nuno R; Trompet, Stella; Weiss, Stefan; Yao, Jie; Brody, Jennifer A; deFilippi, Christopher R; Hoogeveen, Ron C; Lin, Henry J; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: Elevated cardiac troponin levels in blood are associated with increased risk of cardiovascular diseases and mortality. Cardiac troponin levels are heritable, but their genetic architecture remains elusive. METHODS: We conducted a transethnic genome-wide association analysis on high-sensitivity cTnT (cardiac troponin T; hs-cTnT) and high-sensitivity cTnI (cardiac troponin I; hs-cTnI) levels in 24 617 and 14 336 participants free of coronary heart disease and heart failure from 6 population-based cohorts, followed by a series of bioinformatic analyses to decipher the genetic architecture of hs-cTnT and hs-cTnI. RESULTS: We identified 4 genome-wide significant loci for hs-cTnT including a novel locus rs3737882 in and 3 previously reported loci at , , and . One known locus at was replicated for hs-cTnI. One copy of C allele for rs3737882 was associated with a 6% increase in hs-cTnT levels (minor allele frequency, 0.18; =2.80×10). We observed pleiotropic loci located at and . The proportions of variances explained by single-nucleotide polymorphisms were 10.15% and 7.74% for hs-cTnT and hs-cTnI, respectively. Single-nucleotide polymorphisms were colocalized with expression in heart tissues and hs-cTnT and with expression in artery, heart tissues, and whole blood and both troponins. Mendelian randomization analyses showed that genetically increased hs-cTnT and hs-cTnI levels were associated with higher odds of atrial fibrillation (odds ratio, 1.38 [95% CI, 1.25-1.54] for hs-cTnT and 1.21 [95% CI, 1.06-1.37] for hs-cTnI). CONCLUSIONS: We identified a novel genetic locus associated with hs-cTnT in a multiethnic population and found that genetically regulated troponin levels were associated with atrial fibrillation.

Identification of novel and rare variants associated with handgrip strength using whole genome sequence data from the NHLBI Trans-Omics in Precision Medicine (TOPMed) Program. - Sarnowski, Chloe; Chen, Han; Biggs, Mary L; Wassertheil-Smoller, Sylvia; Bressler, Jan; Irvin, Marguerite R; Ryan, Kathleen A; Karasik, David; Arnett, Donna K; Cupples, L Adrienne; Fardo, David W; Gogarten, Stephanie M; et al. (PLoS One, 2021)
Handgrip strength is a widely used measure of muscle strength and a predictor of a range of morbidities including cardiovascular diseases and all-cause mortality. Previous genome-wide association studies of handgrip strength have focused on common variants primarily in persons of European descent. We aimed to identify rare and ancestry-specific genetic variants associated with handgrip strength by conducting whole-genome sequence association analyses using 13,552 participants from six studies representing diverse population groups from the Trans-Omics in Precision Medicine (TOPMed) Program. By leveraging multiple handgrip strength measures performed in study participants over time, we increased our effective sample size by 7-12%. Single-variant analyses identified ten handgrip strength loci among African-Americans: four rare variants, five low-frequency variants, and one common variant. One significant and four suggestive genes were identified associated with handgrip strength when aggregating rare and functional variants; all associations were ancestry-specific. We additionally leveraged the different ancestries available in the UK Biobank to further explore the ancestry-specific association signals from the single-variant association analyses. In conclusion, our study identified 11 new loci associated with handgrip strength with rare and/or ancestry-specific genetic variations, highlighting the added value of whole-genome sequencing in diverse samples. Several of the associations identified using single-variant or aggregate analyses lie in genes with a function relevant to the brain or muscle or were reported to be associated with muscle or age-related traits. Further studies in samples with sequence data and diverse ancestries are needed to confirm these findings.

Meta-analyses identify DNA methylation associated with kidney function and damage. - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Adeyemo, Adebowale A; et al. (Nat Commun, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.
Keywords: Adult; Aged; CpG Islands; DNA Methylation; Female; Glomerular Filtration Rate; Humans; Interferon Regulatory Factors; Kidney; Kidney Function Tests; LIM Domain Proteins; Male; Membrane Proteins; Middle Aged; Renal Insufficiency, Chronic; Transcription Factors

Meta-analysis of epigenome-wide association studies of carotid intima-media thickness. - Portilla-Fernández, Eliana; Hwang, Shih-Jen; Wilson, Rory; Maddock, Jane; Hill, W David; Teumer, Alexander; Mishra, Pashupati P; Brody, Jennifer A; Joehanes, Roby; Ligthart, Symen; Ghanbari, Mohsen; Kavousi, Maryam; et al. (Eur J Epidemiol, 2021)
Common carotid intima-media thickness (cIMT) is an index of subclinical atherosclerosis that is associated with ischemic stroke and coronary artery disease (CAD). We undertook a cross-sectional epigenome-wide association study (EWAS) of measures of cIMT in 6400 individuals. Mendelian randomization analysis was applied to investigate the potential causal role of DNA methylation in the link between atherosclerotic cardiovascular risk factors and cIMT or clinical cardiovascular disease. The CpG site cg05575921 was associated with cIMT (beta = -0.0264, p value = 3.5 × 10) in the discovery panel and was replicated in replication panel (beta = -0.07, p value = 0.005). This CpG is located at chr5:81649347 in the intron 3 of the aryl hydrocarbon receptor repressor gene (AHRR). Our results indicate that DNA methylation at cg05575921 might be in the pathway between smoking, cIMT and stroke. Moreover, in a region-based analysis, 34 differentially methylated regions (DMRs) were identified of which a DMR upstream of ALOX12 showed the strongest association with cIMT (p value = 1.4 × 10). In conclusion, our study suggests that DNA methylation may play a role in the link between cardiovascular risk factors, cIMT and clinical cardiovascular disease.

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

{A multi-ethnic epigenome-wide association study of leukocyte DNA methylation and blood lipids - Jhun, M. A.; Mendelson, M.; Wilson, R.; Gondalia, R.; Joehanes, R.; Salfati, E.; Zhao, X.; Braun, K. V. E.; Do, A. N.; Hedman, Å. K.; Zhang, T.; Carnero-Montoro, E.; et al. (Nat Commun, 2021)
10.1038/s41467-021-23899-yHere we examine the association between DNA methylation in circulating leukocytes and blood lipids in a multi-ethnic sample of 16,265 subjects. We identify 148, 35, and 4 novel associations among Europeans, African Americans, and Hispanics, respectively, and an additional 186 novel associations through a trans-ethnic meta-analysis. We observe a high concordance in the direction of effects across racial/ethnic groups, a high correlation of effect sizes between high-density lipoprotein and triglycerides, a modest overlap of associations with epigenome-wide association studies of other cardio-metabolic traits, and a largely non-overlap with lipid loci identified to date through genome-wide association studies. Thirty CpGs reached significance in at least 2 racial/ethnic groups including 7 that showed association with the expression of an annotated gene. CpGs annotated to CPT1A showed evidence of being influenced by triglycerides levels. DNA methylation levels of circulating leukocytes show robust and consistent association with blood lipid levels across multiple racial/ethnic groups.

is mutated in clonal hematopoiesis and myelodysplastic syndromes and impacts RNA splicing. - Beauchamp, Ellen M; Leventhal, Matthew; Bernard, Elsa; Hoppe, Emma R; Todisco, Gabriele; Creignou, Maria; Gallì, Anna; Castellano, Cecilia A; McConkey, Marie; Tarun, Akansha; Wong, Waihay; Schenone, Monica; et al. (Blood Cancer Discov, 2021)
Clonal hematopoiesis results from somatic mutations in cancer driver genes in hematopoietic stem cells. We sought to identify novel drivers of clonal expansion using an unbiased analysis of sequencing data from 84,683 persons and identified common mutations in the 5-methylcytosine reader, , as well as in , , and . We also identified these mutations at low frequency in myelodysplastic syndrome patients. edited mouse hematopoietic stem and progenitor cells exhibited a competitive advantage and increased genome-wide intron retention. mutations potentially link DNA methylation and RNA splicing, the two most commonly mutated pathways in clonal hematopoiesis and MDS.

The Pharmacogenetics of Statin Therapy on Clinical Events: No Evidence that Genetic Variation Affects Statin Response on Myocardial Infarction. - Trompet, Stella; Postmus, Iris; Warren, Helen R; Noordam, Raymond; Smit, Roelof A J; Theusch, Elizabeth; Li, Xiaohui; Arsenault, Benoit; Chasman, Daniel I; Hitman, Graham A; Munroe, Patricia B; Rotter, Jerome I; et al. (Front Pharmacol, 2021)
The pharmacogenetic effect on cardiovascular disease reduction in response to statin treatment has only been assessed in small studies. In a pharmacogenetic genome wide association study (GWAS) analysis within the Genomic Investigation of Statin Therapy (GIST) consortium, we investigated whether genetic variation was associated with the response of statins on cardiovascular disease risk reduction. The investigated endpoint was incident myocardial infarction (MI) defined as coronary heart disease death and definite and suspect non-fatal MI. For imputed single nucleotide polymorphisms (SNPs), regression analysis was performed on expected allelic dosage and meta-analysed with a fixed-effects model, inverse variance weighted meta-analysis. All SNPs with -values <5.0 × 10 in stage 1 GWAS meta-analysis were selected for further investigation in stage-2. As a secondary analysis, we extracted SNPs from the Stage-1 GWAS meta-analysis results based on predefined hypotheses to possibly modifying the effect of statin therapy on MI. In stage-1 meta-analysis (eight studies, = 10,769, 4,212 cases), we observed no genome-wide significant results ( < 5.0 × 10). A total of 144 genetic variants were followed-up in the second stage (three studies, = 1,525, 180 cases). In the combined meta-analysis, no genome-wide significant hits were identified. Moreover, none of the look-ups of SNPs known to be associated with either CHD or with statin response to cholesterol levels reached Bonferroni level of significance within our stage-1 meta-analysis. This GWAS analysis did not provide evidence that genetic variation affects statin response on cardiovascular risk reduction. It does not appear likely that genetic testing for predicting effects of statins on clinical events will become a useful tool in clinical practice.

Plasma Ceramides containing Saturated Fatty Acids are Associated with Risk of Type 2 Diabetes. - Fretts, Amanda M; Jensen, Paul N; Hoofnagle, Andrew N; McKnight, Barbara; Howard, Barbara V; Umans, Jason; Sitlani, Colleen M; Siscovick, David S; King, Irena B; Djoussé, Luc; Sotoodehnia, Nona; Lemaitre, Rozenn N (J Lipid Res, 2021)
Recent studies suggest that the type of saturated fatty acid bound to sphingolipids influences the biological activity of those sphingolipids. However, it is unknown whether associations of sphingolipids with diabetes may differ by the identity of bound lipid species. Here we investigated associations of 15 ceramide and sphingomyelin species (i.e., all sphingolipids, measured with coefficient of variation less than 20%) with incident type 2 diabetes in the Cardiovascular Health Study (n = 3,645), a large cohort study of cardiovascular disease (CVD) among elderly adults who were followed from 1989-2015. Diabetes incidence was defined as fasting glucose ≥126 mg/dL or non-fasting glucose ≥200 mg/dL; reported use of insulin or oral hypoglycemic medication; or documentation of diabetes diagnosis through the Centers for Medicare and Medicaid Services records. Associations of each sphingolipid with incident diabetes were assessed using a Cox proportional hazards regression model. We found that higher circulating levels of ceramide with acylated palmitic acid (Cer-16), stearic acid containing ceramide (Cer-18), arachidic acid containing ceramide (Cer-20), and behenic acid containing ceramide (Cer-22) were each associated with a higher risk of diabetes. The hazard ratios for incident diabetes per 1 SD higher log levels of each ceramide species were: 1.21 (95% CI 1.09-1.34) for Cer-16, 1.23 (95% CI 1.10-1.37) for Cer-18, 1.14 (95% CI 1.02-1.26) for Cer-20, and 1.18 (95% CI 1.06-1.32) for Cer-22. In conclusion, higher levels of Cer-16, Cer-18, Cer-20, and Cer-22 were associated with a higher risk of diabetes.

{The power of genetic diversity in genome-wide association studies of lipids - Graham, S. E.; Clarke, S. L.; Wu, K. H.; Kanoni, S.; Zajac, G. J. M.; Ramdas, S.; Surakka, I.; Ntalla, I.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Nature, 2021)
application of polygenic scores in clinical practice.

{Rare and low-frequency exonic variants and gene-by-smoking interactions in pulmonary function - Yang, T.; Jackson, V. E.; Smith, A. V.; Chen, H.; Bartz, T. M.; Sitlani, C. M.; Psaty, B. M.; Gharib, S. A.; O'Connor, G. T.; Dupuis, J.; Xu, J.; Lohman, K.; et al. (Sci Rep, 2021)
. This study investigates the utility of assessing gene-by-smoking interactions and underscores their effects on potential pulmonary function.

{Rare Coding Variants Associated With Electrocardiographic Intervals Identify Monogenic Arrhythmia Susceptibility Genes: A Multi-Ancestry Analysis - Choi, S. H.; Jurgens, S. J.; Haggerty, C. M.; Hall, A. W.; Halford, J. L.; Morrill, V. N.; Weng, L. C.; Lagerman, B.; Mirshahi, T.; Pettinger, M.; Guo, X.; Lin, H. J.; et al. (Circ Genom Precis Med, 2021)
Alterations in electrocardiographic (ECG) intervals are well-known markers for arrhythmia and sudden cardiac death (SCD) risk. While the genetics of arrhythmia syndromes have been studied, relations between electrocardiographic intervals and rare genetic variation at a population level are poorly understood.\ Using a discovery sample of 29 000 individuals with whole-genome sequencing from Trans-Omics in Precision Medicine and replication in nearly 100 000 with whole-exome sequencing from the UK Biobank and MyCode, we examined associations between low-frequency and rare coding variants with 5 routinely measured electrocardiographic traits (RR, P-wave, PR, and QRS intervals and corrected QT interval).\ ), a marker of SCD risk. Incomplete penetrance of such deleterious variation was common as over 70% of carriers had normal electrocardiographic intervals.\ Our findings indicate that large-scale high-depth sequence data and electrocardiographic analysis identifies monogenic arrhythmia susceptibility genes and rare variants with large effects. Known pathogenic variation in conventional arrhythmia and SCD genes exhibited incomplete penetrance and accounted for only a small fraction of marked electrocardiographic interval prolongation.

Rare variants in the endocytic pathway are associated with Alzheimer's disease, its related phenotypes, and functional consequences. - Zhan, Lingyu; Li, Jiajin; Jew, Brandon; Sul, Jae Hoon (PLoS Genet, 2021)
Late-onset Alzheimer's disease (LOAD) is the most common type of dementia causing irreversible brain damage to the elderly and presents a major public health challenge. Clinical research and genome-wide association studies have suggested a potential contribution of the endocytic pathway to AD, with an emphasis on common loci. However, the contribution of rare variants in this pathway to AD has not been thoroughly investigated. In this study, we focused on the effect of rare variants on AD by first applying a rare-variant gene-set burden analysis using genes in the endocytic pathway on over 3,000 individuals with European ancestry from three large whole-genome sequencing (WGS) studies. We identified significant associations of rare-variant burden within the endocytic pathway with AD, which were successfully replicated in independent datasets. We further demonstrated that this endocytic rare-variant enrichment is associated with neurofibrillary tangles (NFTs) and age-related phenotypes, increasing the risk of obtaining severer brain damage, earlier age-at-onset, and earlier age-of-death. Next, by aggregating rare variants within each gene, we sought to identify single endocytic genes associated with AD and NFTs. Careful examination using NFTs revealed one significantly associated gene, ANKRD13D. To identify functional associations, we integrated bulk RNA-Seq data from over 600 brain tissues and found two endocytic expression genes (eGenes), HLA-A and SLC26A7, that displayed significant influences on their gene expressions. Differential expressions between AD patients and controls of these three identified genes were further examined by incorporating scRNA-Seq data from 48 post-mortem brain samples and demonstrated distinct expression patterns across cell types. Taken together, our results demonstrated strong rare-variant effect in the endocytic pathway on AD risk and progression and functional effect of gene expression alteration in both bulk and single-cell resolution, which may bring more insight and serve as valuable resources for future AD genetic studies, clinical research, and therapeutic targeting.
Keywords: Alzheimer Disease; Endocytosis; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; Mägi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; M?gi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

Statins and cognitive decline in the Cardiovascular Health Study: A comparison of different analytical approaches. - Zeki Al Hazzouri, Adina; Jawadekar, Neal; Grasset, Leslie; Kaiser, Paulina; Kezios, Katrina; Calonico, Sebastian; Glymour, M Maria; Hirsch, Calvin; Arnold, Alice M; Varadhan, Ravi; Opoodden, Michelle C (J Gerontol A Biol Sci Med Sci, 2021)
BACKGROUND: Despite their well-established benefits for the prevention of cardiovascular disease, robust evidence on the effects of statins on cognition is largely inconclusive. We apply various study designs and analytical approaches to mimic randomized controlled trial (RCT) effects from observational data. METHODS: We used observational data from 5,580 participants enrolled in the Cardiovascular Health Study from 1989/90 to 1999/2000. We conceptualized the cohort as an overlapping sequence of non-randomized trials. We compared multiple selection (eligible population, prevalent users, new-users) and analytic approaches (multivariable adjustment, inverse probability treatment weights, propensity score matching) to evaluate the association between statin use and 5-year change in global cognitive function, assessed using the Modified Mini-Mental State (3MS) examination. RESULTS: When comparing prevalent users to non-users (N=2,772), statin use was associated with slower cognitive decline over 5 years (adjusted annual change in 3MSE = 0.34 points/year; 95% CI:0.05;0.63). Compared to prevalent user design, estimates from new user designs (e.g. comparing eligible statin initiators to non-initiators) were attenuated showing either null or negative association, though not significant. For example, in a propensity score-matched sample of statin-eligible individuals (N=454), annual 3MS change comparing statin initiators to non-initiators was -0.21 points/year (95% CI:-0.81;0.39). CONCLUSIONS: The association of statin use and cognitive decline is attenuated towards the null when using rigorous analytical approaches that more closely mimic RCTs. Point estimates, even within the same study, may vary depending on the analytical methods used. Further studies that leverage natural or quasi experiments around statin use are needed to replicate our findings.

A System for Phenotype Harmonization in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. - Stilp, Adrienne M; Emery, Leslie S; Broome, Jai G; Buth, Erin J; Khan, Alyna T; Laurie, Cecelia A; Wang, Fei Fei; Wong, Quenna; Chen, Dongquan; D'Augustine, Catherine M; Heard-Costa, Nancy L; Hohensee, Chancellor R; et al. (Am J Epidemiol, 2021)
Genotype-phenotype association studies often combine phenotype data from multiple studies to increase power. Harmonization of the data usually requires substantial effort due to heterogeneity in phenotype definitions, study design, data collection procedures, and data set organization. Here we describe a centralized system for phenotype harmonization that includes input from phenotype domain and study experts, quality control, documentation, reproducible results, and data sharing mechanisms. This system was developed for the National Heart, Lung and Blood Institute's Trans-Omics for Precision Medicine program, which is generating genomic and other omics data for >80 studies with extensive phenotype data. To date, 63 phenotypes have been harmonized across thousands of participants from up to 17 studies per phenotype (participants recruited 1948-2012). We discuss challenges in this undertaking and how they were addressed. The harmonized phenotype data and associated documentation have been submitted to National Institutes of Health data repositories for controlled-access by the scientific community. We also provide materials to facilitate future harmonization efforts by the community, which include (1) the code used to generate the 63 harmonized phenotypes, enabling others to reproduce, modify or extend these harmonizations to additional studies; and (2) results of labeling thousands of phenotype variables with controlled vocabulary terms.

Total carotenoid intake is associated with reduced loss of grip strength and gait speed over time in adults: The Framingham Offspring Study. - Sahni, Shivani; Dufour, Alyssa B; Fielding, Roger A; Newman, Anne B; Kiel, Douglas P; Hannan, Marian T; Jacques, Paul F (Am J Clin Nutr, 2021)
BACKGROUND: Lower antioxidant serum concentrations have been linked to declines in lean mass and physical function in older adults. Yet population data on the effect of dietary antioxidants on loss of muscle strength and physical function are lacking. OBJECTIVE: We sought to determine the association of antioxidant intake [vitamin C, vitamin E, and total and individual carotenoids (α-carotene, β-carotene, β-cryptoxanthin, lycopene, and lutein + zeaxanthin)] with annualized change in grip strength and gait speed in adults from the Framingham Offspring study. METHODS: This prospective cohort study included participants with a valid FFQ at the index examination and up to 2 prior examinations and at ≥2 measures of primary outcomes: grip strength (n = 2452) and/or gait speed (n = 2422) measured over 3 subsequent examinations. Annualized change in grip strength (kg/y) and change in gait speed (m/s/y) over the follow-up period were used. Linear regression was used to calculate β coefficients and P values, adjusting for covariates. RESULTS: Mean ± SD age of participants was 61 ± 9 y (range: 33-88 y). Median intakes (IQR, mg/d) of vitamin C, vitamin E, and total carotenoid across available examinations were 209.2 (133.1-394.2), 27.1 (7.4-199.0), and 15.3 (10.4-21.3), respectively. The mean follow-up time was ∼12 ± 2 y (range: 4.5-15.4 y). In the sex-combined sample, higher intakes of total carotenoids, lycopene, and lutein + zeaxanthin were associated with increased annualized change in grip strength [β (SE) per 10-mg higher intake/d, range: 0.0316 (0.0146) to 0.1223 (0.0603) kg/y)]. All antioxidants except for vitamin C were associated with faster gait speed [β (SE) per 10-mg higher intake/d, range: 0.00008 (0.00004) to 0.0187 (0.0081) m/s/y]. CONCLUSIONS: Higher antioxidant intake was associated with increase in grip strength and faster gait speed in this cohort of adults. This finding highlights the need for a randomized controlled trial of dietary antioxidants and their effect on muscle strength and physical function.
Keywords: Adult; Aged; Aged, 80 and over; Carotenoids; Cohort Studies; Diet; Female; Hand Strength; Humans; Male; Middle Aged; Prospective Studies; Walking Speed

{The trans-ancestral genomic architecture of glycemic traits - Chen, J.; Spracklen, C. N.; Marenne, G.; Varshney, A.; Corbin, L. J.; Luan, J.; Willems, S. M.; Wu, Y.; Zhang, X.; Horikoshi, M.; Boutin, T. S.; Mägi, R.; et al. (Nat Genet, 2021)
10.1038/s41588-021-00852-9Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10-8), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.

What Cut-Point in Gait Speed Best Discriminates Community-Dwelling Older Adults With Mobility Complaints From Those Without? A Pooled Analysis From the Sarcopenia Definitions and Outcomes Consortium. - Cawthon, Peggy M; Patel, Sheena M; Kritchevsky, Stephen B; Newman, Anne B; Santanasto, Adam; Kiel, Douglas P; Travison, Thomas G; Lane, Nancy; Cummings, Steven R; Orwoll, Eric S; Duchowny, Kate A; Kwok, Timothy; et al. (J Gerontol A Biol Sci Med Sci, 2021)
BACKGROUND: Cut-points to define slow walking speed have largely been derived from expert opinion. METHODS: Study participants (13 589 men and 5043 women aged ≥65years) had walking speed (m/s) measured over 4-6 m (mean ± SD: 1.20 ± 0.27 m/s in men and 0.94 ± 0.24 m/s in women.) Mobility limitation was defined as any self-reported difficulty with walking approximately 1/4 mile (prevalence: 12.6% men, 26.4% women). Sex-stratified classification and regression tree (CART) models with 10-fold cross-validation identified walking speed cut-points that optimally discriminated those who reported mobility limitation from those who did not. RESULTS: Among 5043 women, CART analysis identified 2 cut-points, classifying 4144 (82.2%) with walking speed ≥0.75 m/s, which we labeled as "fast"; 478 (9.5%) as "intermediate" (walking speed ≥0.62 m/s but <0.75 m/s); and 421 (8.3%) as "slow" (walking speed <0.62 m/s). Among 13 589 men, CART analysis identified 3 cut-points, classifying 10 001 (73.6%) with walking speed ≥1.00 m/s ("very fast"); 2901 (21.3%) as "fast" (walking speed ≥0.74 m/s but <1.00 m/s); 497 (3.7%) as "intermediate" (walking speed ≥0.57 m/s but <0.74 m/s); and 190 (1.4%) as "slow" (walking speed <0.57 m/s). Prevalence of self-reported mobility limitation was lowest in the "fast" or "very fast" (11% for men and 19% for women) and highest in the "slow" (60.5% in men and 71.0% in women). Rounding the 2 slower cut-points to 0.60 m/s and 0.75 m/s reclassified very few participants. CONCLUSIONS: Cut-points in walking speed of approximately 0.60 m/s and 0.75 m/s discriminate those with self-reported mobility limitation from those without.
Keywords: Aged; Female; Gait; Humans; Independent Living; Male; Mobility Limitation; Sarcopenia; Walking; Walking Speed

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.

Whole genome sequence analysis of platelet traits in the NHLBI trans-omics for precision medicine initiative. - Little, Amarise; Hu, Yao; Sun, Quan; Jain, Deepti; Broome, Jai; Chen, Ming-Huei; Thibord, Florian; McHugh, Caitlin; Surendran, Praveen; Blackwell, Thomas W; Brody, Jennifer A; Bhan, Arunoday; et al. (Hum Mol Genet, 2021)
Platelets play a key role in thrombosis and hemostasis. Platelet count (PLT) and mean platelet volume (MPV) are highly heritable quantitative traits, with hundreds of genetic signals previously identified, mostly in European ancestry populations. We here utilize whole genome sequencing from NHLBI's Trans-Omics for Precision Medicine Initiative (TOPMed) in a large multi-ethnic sample to further explore common and rare variation contributing to PLT (n = 61 200) and MPV (n = 23 485). We identified and replicated secondary signals at MPL (rs532784633) and PECAM1 (rs73345162), both more common in African ancestry populations. We also observed rare variation in Mendelian platelet related disorder genes influencing variation in platelet traits in TOPMed cohorts (not enriched for blood disorders). For example, association of GP9 with lower PLT and higher MPV was partly driven by a pathogenic Bernard-Soulier syndrome variant (rs5030764, p.Asn61Ser), and the signals at TUBB1 and CD36 were partly driven by loss of function variants not annotated as pathogenic in ClinVar (rs199948010 and rs571975065). However, residual signal remained for these gene-based signals after adjusting for lead variants, suggesting that additional variants in Mendelian genes with impacts in general population cohorts remain to be identified. Gene-based signals were also identified at several GWAS identified loci for genes not annotated for Mendelian platelet disorders (PTPRH, TET2, CHEK2), with somatic variation driving the result at TET2. These results highlight the value of whole genome sequencing in populations of diverse genetic ancestry to identify novel regulatory and coding signals, even for well-studied traits like platelet traits.

Whole-genome sequencing association analysis of quantitative red blood cell phenotypes: The NHLBI TOPMed program. - Hu, Yao; Stilp, Adrienne M; McHugh, Caitlin P; Rao, Shuquan; Jain, Deepti; Zheng, Xiuwen; Lane, John; Méric de Bellefon, Sébastian; Raffield, Laura M; Chen, Ming-Huei; Yanek, Lisa R; Wheeler, Marsha; et al. (Am J Hum Genet, 2021)
Whole-genome sequencing (WGS), a powerful tool for detecting novel coding and non-coding disease-causing variants, has largely been applied to clinical diagnosis of inherited disorders. Here we leveraged WGS data in up to 62,653 ethnically diverse participants from the NHLBI Trans-Omics for Precision Medicine (TOPMed) program and assessed statistical association of variants with seven red blood cell (RBC) quantitative traits. We discovered 14 single variant-RBC trait associations at 12 genomic loci, which have not been reported previously. Several of the RBC trait-variant associations (RPN1, ELL2, MIDN, HBB, HBA1, PIEZO1, and G6PD) were replicated in independent GWAS datasets imputed to the TOPMed reference panel. Most of these discovered variants are rare/low frequency, and several are observed disproportionately among non-European Ancestry (African, Hispanic/Latino, or East Asian) populations. We identified a 3 bp indel p.Lys2169del (g.88717175_88717177TCT[4]) (common only in the Ashkenazi Jewish population) of PIEZO1, a gene responsible for the Mendelian red cell disorder hereditary xerocytosis (MIM: 194380), associated with higher mean corpuscular hemoglobin concentration (MCHC). In stepwise conditional analysis and in gene-based rare variant aggregated association analysis, we identified several of the variants in HBB, HBA1, TMPRSS6, and G6PD that represent the carrier state for known coding, promoter, or splice site loss-of-function variants that cause inherited RBC disorders. Finally, we applied base and nuclease editing to demonstrate that the sentinel variant rs112097551 (nearest gene RPN1) acts through a cis-regulatory element that exerts long-range control of the gene RUVBL1 which is essential for hematopoiesis. Together, these results demonstrate the utility of WGS in ethnically diverse population-based samples and gene editing for expanding knowledge of the genetic architecture of quantitative hematologic traits and suggest a continuum between complex trait and Mendelian red cell disorders.
Keywords: Adult; Aged; Chromosomes, Human, Pair 16; Datasets as Topic; Erythrocytes; Female; Gene Editing; Genetic Variation; Genome-Wide Association Study; HEK293 Cells; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Quality Control; Reproducibility of Results; United States

Whole-genome sequencing in diverse subjects identifies genetic correlates of leukocyte traits: The NHLBI TOPMed program. - Mikhaylova, Anna V; McHugh, Caitlin P; Polfus, Linda M; Raffield, Laura M; Boorgula, Meher Preethi; Blackwell, Thomas W; Brody, Jennifer A; Broome, Jai; Chami, Nathalie; Chen, Ming-Huei; Conomos, Matthew P; Cox, Corey; et al. (Am J Hum Genet, 2021)
Many common and rare variants associated with hematologic traits have been discovered through imputation on large-scale reference panels. However, the majority of genome-wide association studies (GWASs) have been conducted in Europeans, and determining causal variants has proved challenging. We performed a GWAS of total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts generated from 109,563,748 variants in the autosomes and the X chromosome in the Trans-Omics for Precision Medicine (TOPMed) program, which included data from 61,802 individuals of diverse ancestry. We discovered and replicated 7 leukocyte trait associations, including (1) the association between a chromosome X, pseudo-autosomal region (PAR), noncoding variant located between cytokine receptor genes (CSF2RA and CLRF2) and lower eosinophil count; and (2) associations between single variants found predominantly among African Americans at the S1PR3 (9q22.1) and HBB (11p15.4) loci and monocyte and lymphocyte counts, respectively. We further provide evidence indicating that the newly discovered eosinophil-lowering chromosome X PAR variant might be associated with reduced susceptibility to common allergic diseases such as atopic dermatitis and asthma. Additionally, we found a burden of very rare FLT3 (13q12.2) variants associated with monocyte counts. Together, these results emphasize the utility of whole-genome sequencing in diverse samples in identifying associations missed by European-ancestry-driven GWASs.
Keywords: Asthma; Biomarkers; Dermatitis, Atopic; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Leukocytes; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Prognosis; Proteome; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; United Kingdom; United States; Whole Genome Sequencing

Assessing the contribution of rare variants to complex trait heritability from whole-genome sequence data. - Wainschtein, Pierrick; Jain, Deepti; Zheng, Zhili; Cupples, L Adrienne; Shadyab, Aladdin H; McKnight, Barbara; Shoemaker, Benjamin M; Mitchell, Braxton D; Psaty, Bruce M; Kooperberg, Charles; Liu, Ching-Ti; Albert, Christine M; et al. (Nat Genet, 2022)
Analyses of data from genome-wide association studies on unrelated individuals have shown that, for human traits and diseases, approximately one-third to two-thirds of heritability is captured by common SNPs. However, it is not known whether the remaining heritability is due to the imperfect tagging of causal variants by common SNPs, in particular whether the causal variants are rare, or whether it is overestimated due to bias in inference from pedigree data. Here we estimated heritability for height and body mass index (BMI) from whole-genome sequence data on 25,465 unrelated individuals of European ancestry. The estimated heritability was 0.68 (standard error 0.10) for height and 0.30 (standard error 0.10) for body mass index. Low minor allele frequency variants in low linkage disequilibrium (LD) with neighboring variants were enriched for heritability, to a greater extent for protein-altering variants, consistent with negative selection. Our results imply that rare variants, in particular those in regions of low linkage disequilibrium, are a major source of the still missing heritability of complex traits and disease.

Association of Trimethylamine N-Oxide and Metabolites With Mortality in Older Adults. - Fretts, Amanda M; Hazen, Stanley L; Jensen, Paul; Budoff, Matthew; Sitlani, Colleen M; Wang, Meng; de Oliveira Otto, Marcia C; DiDonato, Joseph A; Lee, Yujin; Psaty, Bruce M; Siscovick, David S; Sotoodehnia, Nona; et al. (JAMA Netw Open, 2022)
Importance: Little is known about the association of trimethylamine N-oxide (TMAO), a novel plasma metabolite derived from L-carnitine and phosphatidylcholine, and related metabolites (ie, choline, betaine, carnitine, and butyrobetaine) with risk of death among older adults in the general population. Objective: To investigate the associations of serial measures of plasma TMAO and related metabolites with risk of total and cause-specific death (ie, deaths from cardiovascular diseases [CVDs] and non-CVDs) among older adults in the US. Design, Setting, and Participants: This prospective cohort study involved 5333 participants from the Cardiovascular Health Study-a community-based longitudinal cohort of adults aged 65 years or older-who were followed up from June 1, 1989, to December 31, 2015. Participants were from 4 communities in the US (Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania). Data were analyzed from March 17 to June 23, 2021. Exposures: Plasma TMAO, choline, betaine, carnitine, and butyrobetaine levels were measured using stored samples from baseline (June 1, 1989, to May 31, 1990, or November 1, 1992, to June 31, 1993) and follow-up examination (June 1, 1996, to May 31, 1997). Measurements were performed through stable-isotope dilution liquid chromatography with tandem mass spectrometry using high-performance liquid chromatography with online electrospray ionization tandem mass spectrometry. Main Outcomes and Measures: Deaths (total and cause specific) were adjudicated by a centralized Cardiovascular Health Study events committee based on information from medical records, laboratory and diagnostic reports, death certificates, and/or interviews with next of kin. The associations of each metabolite with mortality were assessed using Cox proportional hazards regression models. Results: Among 5333 participants in the analytic sample, the mean (SD) age was 73 (6) years; 2149 participants (40.3%) were male, 3184 (59.7%) were female, 848 (15.9%) were African American, 4450 (83.4%) were White, and 35 (0.01%) were of other races (12 were American Indian or Alaska Native, 4 were Asian or Pacific Islander, and 19 were of other races or ethnicities). During a median follow-up of 13.2 years (range, 0-26.9 years), 4791 deaths occurred. After adjustment for potential confounders, the hazard ratios for death from any cause (ie, total mortality) comparing extreme quintiles (fifth vs first) of plasma concentrations were 1.30 (95% CI, 1.17-1.44) for TMAO, 1.19 (95% CI, 1.08-1.32) for choline, 1.26 (95% CI, 1.15-1.40) for carnitine, and 1.26 (95% CI, 1.13-1.40) for butyrobetaine. Plasma betaine was not associated with risk of death. The extent of risk estimates was similar for CVD and non-CVD mortality. Conclusions and Relevance: In this cohort study, plasma concentrations of TMAO and related metabolites were positively associated with risk of death. These findings suggest that circulating TMAO is an important novel risk factor associated with death among older adults.
Keywords: Aged; Betaine; Cardiovascular Diseases; Carnitine; Choline; Cohort Studies; Female; Humans; Male; Methylamines; Prospective Studies

An association test of the spatial distribution of rare missense variants within protein structures identifies Alzheimer's disease-related patterns - Jin, B.; Capra, J. A.; Benchek, P.; Wheeler, N.; Naj, A. C.; Hamilton-Nelson, K. L.; Farrell, J. J.; Leung, Y. Y.; Kunkle, B.; Vadarajan, B.; Schellenberg, G. D.; Mayeux, R.; et al. (Genome Res, 2022)
is a novel AD risk gene that has a cluster of variants primarily shared by case subjects around the Sec6 domain. This cluster is also validated in an independent replication data set and a validation data set with a larger sample size.

Associations between Alcohol Consumption and HDL Subspecies Defined by ApoC3, ApoE and ApoJ: the Cardiovascular Health Study. - Wilkens, Trine L; Sørensen, Helle; Jensen, Majken K; Furtado, Jeremy D; Dragsted, Lars O; Mukamal, Kenneth J (Curr Probl Cardiol, 2022)
Alcohol consumption increases circulating high-density lipoprotein cholesterol (HDL-C), but HDL protein cargo may better reflect HDL function. This study examined the associations between alcohol intake and HDL subspecies containing or lacking apoC3, apoE, and apoJ in a well-phenotyped cohort. We performed a cross-sectional analysis of 2092 Cardiovascular Health Study participants aged 70 or older with HDL subspecies measured in stored specimens from 1998 to 1999. Associations between alcohol intake and apoA1 defined HDL subspecies lacking or containing apoC3, apoE, and apoJ, and circulating levels of total apoA1, apoC3, apoE, and apoJ were examined. HDL subspecies lacking and containing apoC3, apoE, and apoJ were all positively associated with alcohol intake, with ∼1% per additional drink per week or ∼7% per additional drink per day (subspecies without the apolipoproteins, P ≤ 2 × 10, subspecies with the apolipoproteins, P ≤ 3 × 10). Total apoA1 was also directly associated with alcohol consumption, with a 1% increase per additional drink per week (P = 1 × 10). Total apoC3 blood levels were 0.5% higher per additional drink per week (P = 0.01), but the association was driven by a few heavily drinking men. Alcohol intake was positively associated with HDL subspecies lacking and containing apoC3, apoE, or apoJ, and with total plasma apoA1. ApoC3 was directly, albeit not as robustly associated with alcohol intake. HDL protein cargo is crucial for its anti-atherosclerotic functions, but it remains to be determined whether HDL subspecies play a role in the putative association between limited alcohol intake and lower risk of coronary heart disease.

Associations of modifiable behavioral risk factor combinations at 65-74 years old with cognitive healthspan over 20 years. - Smagula, Stephen F; Biggs, Mary L; Jacob, Mini E; Rawlings, Andreea M; Odden, Michelle C; Arnold, Alice; Newman, Anne B; Buysse, Daniel J (Psychosom Med, 2022)
OBJECTIVE: Behavioral risk factors for dementia tend to co-occur and inter-relate, especially poor diet, physical inactivity, sleep disturbances, and depression. Having multiple of these modifiable behavioral risk factors (MBRFs) may predict a particularly shortened cognitive healthspan, and therefore, may signal high-risk status/high intervention need. METHODS: This secondary analyses of data from the Cardiovascular Health Study included 3149 participants aged 65-74 years (mean age = 69.5, standard deviation (SD) = 2.5; 59.6% female). MBRF exposures were self-reports regarding: (1) diet, (2) activity, (3) sleep, and (4) depression symptoms. We primarily analyzed MBRF counts. Over up to 26 years of follow-up, we assessed the: (1) number of remaining cognitively healthy life years (CHLYs); and (2) percentage of remaining life years (LYs) that were CHLYs (%CHLY). We estimated CHLYs as time before a dementia diagnosis, cognitive screener scores indicating impairment, proxy port indicating significant cognitive decline, or dementia medication use. RESULTS: Participants averaged a remaining 16 LYs (SD = 7), 12.2 CHLYs (SD = 6.6), and 78.1% of LYs being CHLYs (SD = 25.6). Compared with having no MBRFs, having one was associated with ~1 less LY and CHLY, but not a relatively lower %CHLY. In contrast, having 3+ MBRFs was associated with about 2-3 fewer LYs and CHLYs as well as about 6% lower %CHLY (95% confidence interval: -9.0, -2.5 %CHLYs), p = 0.001). CONCLUSIONS: MBRF-related reductions in the cognitive healthspan are most apparent when people have multiple MBRFs. Future research is needed to determine if/how behavioral risks converge mechanistically, and if dementia prevention efficacy improves when targeting MBRF combinations.

Circulating Soluble CD163, Associations With Cardiovascular Outcomes and Mortality, and Identification of Genetic Variants in Older Individuals: The Cardiovascular Health Study. - Durda, Peter; Raffield, Laura M; Lange, Ethan M; Olson, Nels C; Jenny, Nancy Swords; Cushman, Mary; Deichgraeber, Pia; Grarup, Niels; Jonsson, Anna; Hansen, Torben; Mychaleckyj, Josyf C; Psaty, Bruce M; et al. (J Am Heart Assoc, 2022)
Background Monocytes/macrophages participate in cardiovascular disease. CD163 (cluster of differentiation 163) is a monocyte/macrophage receptor, and the shed sCD163 (soluble CD163) reflects monocyte/macrophage activation. We examined the association of sCD163 with incident cardiovascular disease events and performed a genome-wide association study to identify sCD163-associated variants. Methods and Results We measured plasma sCD163 in 5214 adults (aged ≥65 years, 58.7% women, 16.2% Black) of the CHS (Cardiovascular Health Study). We used Cox regression models (associations of sCD163 with incident events and mortality); median follow-up was 26 years. Genome-wide association study analyses were stratified on race. Adjusted for age, sex, and race and ethnicity, sCD163 levels were associated with all-cause mortality (hazard ratio [HR], 1.08 [95% CI, 1.04-1.12] per SD increase), cardiovascular disease mortality (HR, 1.15 [95% CI, 1.09-1.21]), incident coronary heart disease (HR, 1.10 [95% CI, 1.04-1.16]), and incident heart failure (HR, 1.18 [95% CI, 1.12-1.25]). When further adjusted (eg, cardiovascular disease risk factors), only incident coronary heart disease lost significance. In European American individuals, genome-wide association studies identified 38 variants on chromosome 2 near (top result rs62165726, =3.3×10),19 variants near chromosome 17 gene (rs55714927, =1.5×10), and 18 variants near chromosome 11 gene . These regions replicated in the European ancestry ADDITION-PRO cohort, a longitudinal cohort study nested in the Danish arm of the Anglo-Danish-Dutch study of Intensive Treatment Intensive Treatment In peOple with screeNdetcted Diabetes in Primary Care. In Black individuals, we identified 9 variants on chromosome 6 (rs3129781 =7.1×10) in the region, and 3 variants (rs115391969 =4.3×10) near the chromosome 16 gene Conclusions Monocyte function, as measured by sCD163, may be predictive of overall and cardiovascular-specific mortality and incident heart failure.
Keywords: Aged; Antigens, CD; Antigens, Differentiation, Myelomonocytic; Asialoglycoprotein Receptor; Biomarkers; Cardiovascular Diseases; Female; Genome-Wide Association Study; Heart Failure; Humans; Longitudinal Studies; Male

Clonal Hematopoiesis Is Associated With Higher Risk of Stroke. - Bhattacharya, Romit; Zekavat, Seyedeh M; Haessler, Jeffrey; Fornage, Myriam; Raffield, Laura; Uddin, Md Mesbah; Bick, Alexander G; Niroula, Abhishek; Yu, Bing; Gibson, Christopher; Griffin, Gabriel; Morrison, Alanna C; et al. (Stroke, 2022)
BACKGROUND AND PURPOSE: Clonal hematopoiesis of indeterminate potential (CHIP) is a novel age-related risk factor for cardiovascular disease-related morbidity and mortality. The association of CHIP with risk of incident ischemic stroke was reported previously in an exploratory analysis including a small number of incident stroke cases without replication and lack of stroke subphenotyping. The purpose of this study was to discover whether CHIP is a risk factor for ischemic or hemorrhagic stroke. METHODS: We utilized plasma genome sequence data of blood DNA to identify CHIP in 78 752 individuals from 8 prospective cohorts and biobanks. We then assessed the association of CHIP and commonly mutated individual CHIP driver genes (, , and ) with any stroke, ischemic stroke, and hemorrhagic stroke. RESULTS: CHIP was associated with an increased risk of total stroke (hazard ratio, 1.14 [95% CI, 1.03-1.27]; =0.01) after adjustment for age, sex, and race. We observed associations with CHIP with risk of hemorrhagic stroke (hazard ratio, 1.24 [95% CI, 1.01-1.51]; =0.04) and with small vessel ischemic stroke subtypes. In gene-specific association results, showed the strongest association with total stroke and ischemic stroke, whereas and were each associated with increased risk of hemorrhagic stroke. CONCLUSIONS: CHIP is associated with an increased risk of stroke, particularly with hemorrhagic and small vessel ischemic stroke. Future studies clarifying the relationship between CHIP and subtypes of stroke are needed.

{Clonal hematopoiesis of indeterminate potential, DNA methylation, and risk for coronary artery disease - Uddin, M. D. M.; Nguyen, N. Q. H.; Yu, B.; Brody, J. A.; Pampana, A.; Nakao, T.; Fornage, M.; Bressler, J.; Sotoodehnia, N.; Weinstock, J. S.; Honigberg, M. C.; Nachun, D.; et al. (Nat Commun, 2022)
Age-related changes to the genome-wide DNA methylation (DNAm) pattern observed in blood are well-documented. Clonal hematopoiesis of indeterminate potential (CHIP), characterized by the age-related acquisition and expansion of leukemogenic mutations in hematopoietic stem cells (HSCs), is associated with blood cancer and coronary artery disease (CAD). Epigenetic regulators DNMT3A and TET2 are the two most frequently mutated CHIP genes. Here, we present results from an epigenome-wide association study for CHIP in 582 Cardiovascular Health Study (CHS) participants, with replication in 2655 Atherosclerosis Risk in Communities (ARIC) Study participants. We show that DNMT3A and TET2 CHIP have distinct and directionally opposing genome-wide DNAm association patterns consistent with their regulatory roles, albeit both promoting self-renewal of HSCs. Mendelian randomization analyses indicate that a subset of DNAm alterations associated with these two leading CHIP genes may promote the risk for CAD.

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors. - Thibord, Florian; Klarin, Derek; Brody, Jennifer A; Chen, Ming-Huei; Levin, Michael G; Chasman, Daniel I; Goode, Ellen L; Hveem, Kristian; Teder-Laving, Maris; Martinez-Perez, Angel; Aïssi, Dylan; Daian-Bacq, Delphine; et al. (Circulation, 2022)
BACKGROUND: Venous thromboembolism (VTE) is a life-threatening vascular event with environmental and genetic determinants. Recent VTE genome-wide association studies (GWAS) meta-analyses involved nearly 30 000 VTE cases and identified up to 40 genetic loci associated with VTE risk, including loci not previously suspected to play a role in hemostasis. The aim of our research was to expand discovery of new genetic loci associated with VTE by using cross-ancestry genomic resources. METHODS: We present new cross-ancestry meta-analyzed GWAS results involving up to 81 669 VTE cases from 30 studies, with replication of novel loci in independent populations and loci characterization through in silico genomic interrogations. RESULTS: In our genetic discovery effort that included 55 330 participants with VTE (47 822 European, 6320 African, and 1188 Hispanic ancestry), we identified 48 novel associations, of which 34 were replicated after correction for multiple testing. In our combined discovery-replication analysis (81 669 VTE participants) and ancestry-stratified meta-analyses (European, African, and Hispanic), we identified another 44 novel associations, which are new candidate VTE-associated loci requiring replication. In total, across all GWAS meta-analyses, we identified 135 independent genomic loci significantly associated with VTE risk. A genetic risk score of the significantly associated loci in Europeans identified a 6-fold increase in risk for those in the top 1% of scores compared with those with average scores. We also identified 31 novel transcript associations in transcriptome-wide association studies and 8 novel candidate genes with protein quantitative-trait locus Mendelian randomization analyses. In silico interrogations of hemostasis and hematology traits and a large phenome-wide association analysis of the 135 GWAS loci provided insights to biological pathways contributing to VTE, with some loci contributing to VTE through well-characterized coagulation pathways and others providing new data on the role of hematology traits, particularly platelet function. Many of the replicated loci are outside of known or currently hypothesized pathways to thrombosis. CONCLUSIONS: Our cross-ancestry GWAS meta-analyses identified new loci associated with VTE. These findings highlight new pathways to thrombosis and provide novel molecules that may be useful in the development of improved antithrombosis treatments.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Thrombosis; Venous Thromboembolism

Differential and shared genetic effects on kidney function between diabetic and non-diabetic individuals. - Winkler, Thomas W; Rasheed, Humaira; Teumer, Alexander; Gorski, Mathias; Rowan, Bryce X; Stanzick, Kira J; Thomas, Laurent F; Tin, Adrienne; Hoppmann, Anselm; Chu, Audrey Y; Tayo, Bamidele; Thio, Chris H L; et al. (Commun Biol, 2022)
Reduced glomerular filtration rate (GFR) can progress to kidney failure. Risk factors include genetics and diabetes mellitus (DM), but little is known about their interaction. We conducted genome-wide association meta-analyses for estimated GFR based on serum creatinine (eGFR), separately for individuals with or without DM (n = 178,691, n = 1,296,113). Our genome-wide searches identified (i) seven eGFR loci with significant DM/noDM-difference, (ii) four additional novel loci with suggestive difference and (iii) 28 further novel loci (including CUBN) by allowing for potential difference. GWAS on eGFR among DM individuals identified 2 known and 27 potentially responsible loci for diabetic kidney disease. Gene prioritization highlighted 18 genes that may inform reno-protective drug development. We highlight the existence of DM-only and noDM-only effects, which can inform about the target group, if respective genes are advanced as drug targets. Largely shared effects suggest that most drug interventions to alter eGFR should be effective in DM and noDM.
Keywords: Creatinine; Diabetes Mellitus; Diabetic Nephropathies; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney

{DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases - Wielscher, M.; Mandaviya, P. R.; Kuehnel, B.; Joehanes, R.; Mustafa, R.; Robinson, O.; Zhang, Y.; Bodinier, B.; Walton, E.; Mishra, P. P.; Schlosser, P.; Wilson, R.; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.

Endophenotype effect sizes support variant pathogenicity in monogenic disease susceptibility genes. - Halford, Jennifer L; Morrill, Valerie N; Choi, Seung Hoan; Jurgens, Sean J; Melloni, Giorgio; Marston, Nicholas A; Weng, Lu-Chen; Nauffal, Victor; Hall, Amelia W; Gunn, Sophia; Austin-Tse, Christina A; Pirruccello, James P; et al. (Nat Commun, 2022)
Accurate and efficient classification of variant pathogenicity is critical for research and clinical care. Using data from three large studies, we demonstrate that population-based associations between rare variants and quantitative endophenotypes for three monogenic diseases (low-density-lipoprotein cholesterol for familial hypercholesterolemia, electrocardiographic QTc interval for long QT syndrome, and glycosylated hemoglobin for maturity-onset diabetes of the young) provide evidence for variant pathogenicity. Effect sizes are associated with pathogenic ClinVar assertions (P < 0.001 for each trait) and discriminate pathogenic from non-pathogenic variants (area under the curve 0.82-0.84 across endophenotypes). An effect size threshold of ≥ 0.5 times the endophenotype standard deviation nominates up to 35% of rare variants of uncertain significance or not in ClinVar in disease susceptibility genes with pathogenic potential. We propose that variant associations with quantitative endophenotypes for monogenic diseases can provide evidence supporting pathogenicity.
Keywords: Disease Susceptibility; Endophenotypes; Humans; Long QT Syndrome; Virulence

Epigenetic and integrative cross-omics analyses of cerebral white matter hyperintensities on MRI. - Yang, Yunju; Knol, Maria J; Wang, Ruiqi; Mishra, Aniket; Liu, Dan; Luciano, Michelle; Teumer, Alexander; Armstrong, Nicola; Bis, Joshua C; Jhun, Min A; Li, Shuo; Adams, Hieab H H; et al. (Brain, 2022)
Cerebral white matter hyperintensities on MRI are markers of cerebral small vessel disease, a major risk factor for dementia and stroke. Despite the successful identification of multiple genetic variants associated with this highly heritable condition, its genetic architecture remains incompletely understood. More specifically, the role of DNA methylation has received little attention. We investigated the association between white matter hyperintensity burden and DNA methylation in blood at approximately 450,000 CpG sites in 9,732 middle-aged to older adults from 14 community-based studies. Single-CpG and region-based association analyses were carried out. Functional annotation and integrative cross-omics analyses were performed to identify novel genes underlying the relationship between DNA methylation and white matter hyperintensities. We identified 12 single-CpG and 46 region-based DNA methylation associations with white matter hyperintensity burden. Our top discovery single CpG, cg24202936 (P = 7.6 × 10-8), was associated with F2 expression in blood (P = 6.4 × 10-5), and colocalized with FOLH1 expression in brain (posterior probability =0.75). Our top differentially methylated regions were in PRMT1 and in CCDC144NL-AS1, which were also represented in single-CpG associations (cg17417856 and cg06809326, respectively). Through Mendelian randomization analyses cg06809326 was putatively associated with white matter hyperintensity burden (P = 0.03) and expression of CCDC144NL-AS1 possibly mediated this association. Differentially methylated region analysis, joint epigenetic association analysis, and multi-omics colocalization analysis consistently identified a role of DNA methylation near SH3PXD2A, a locus previously identified in genome-wide association studies of white matter hyperintensities. Gene set enrichment analyses revealed functions of the identified DNA methylation loci in the blood-brain barrier and in the immune response. Integrative cross-omics analysis identified 19 key regulatory genes in two networks related to extracellular matrix organization, and lipid and lipoprotein metabolism. A drug repositioning analysis indicated antihyperlipidemic agents, more specifically peroxisome proliferator-activated receptor alpha, as possible target drugs for white matter hyperintensities. Our epigenome-wide association study and integrative cross-omics analyses implicate novel genes influencing white matter hyperintensity burden, which converged on pathways related to the immune response and to a compromised blood brain barrier possibly due to disrupted cell-cell and cell-extracellular matrix interactions. The results also suggest that antihyperlipidemic therapy may contribute to lowering risk for white matter hyperintensities possibly through protection against blood brain barrier disruption.

{Gene Set Enrichment Analsyes Identify Pathways Involved in Genetic Risk for Diabetic Retinopathy - Sobrin, L.; Susarla, G.; Stanwyck, L.; Rouhana, J. M.; Li, A.; Pollack, S.; Igo, R. P.; Jensen, R. A.; Li, X.; Ng, M. C. Y.; Smith, A. V.; Kuo, J. Z.; et al. (Am J Ophthalmol, 2022)
{To identify functionally related genes associated with diabetic retinopathy (DR) risk using gene set enrichment analyses applied to genome-wide association study meta-analyses.\ .05.\ .05) in the other method. These pathways were regulation of the lipid catabolic process (2-fold enrichment

{Gene-mapping study of extremes of cerebral small vessel disease reveals TRIM47 as a strong candidate - Mishra, A.; Duplaà, C.; Vojinovic, D.; Suzuki, H.; Sargurupremraj, M.; Zilhao, N. R.; Li, S.; Bartz, T. M.; Jian, X.; Zhao, W.; Hofer, E.; Wittfeld, K.; et al. (Brain, 2022)
Cerebral small vessel disease is a leading cause of stroke and a major contributor to cognitive decline and dementia, but our understanding of specific genes underlying the cause of sporadic cerebral small vessel disease is limited. We report a genome-wide association study and a whole-exome association study on a composite extreme phenotype of cerebral small vessel disease derived from its most common MRI features: white matter hyperintensities and lacunes. Seventeen population-based cohorts of older persons with MRI measurements and genome-wide genotyping (n = 41 326), whole-exome sequencing (n = 15 965), or exome chip (n = 5249) data contributed 13 776 and 7079 extreme small vessel disease samples for the genome-wide association study and whole-exome association study, respectively. The genome-wide association study identified significant association of common variants in 11 loci with extreme small vessel disease, of which the chr12q24.11 locus was not previously reported to be associated with any MRI marker of cerebral small vessel disease. The whole-exome association study identified significant associations of extreme small vessel disease with common variants in the 5' UTR region of EFEMP1 (chr2p16.1) and one probably damaging common missense variant in TRIM47 (chr17q25.1). Mendelian randomization supports the causal association of extensive small vessel disease severity with increased risk of stroke and Alzheimer's disease. Combined evidence from summary-based Mendelian randomization studies and profiling of human loss-of-function allele carriers showed an inverse relation between TRIM47 expression in the brain and blood vessels and extensive small vessel disease severity. We observed significant enrichment of Trim47 in isolated brain vessel preparations compared to total brain fraction in mice, in line with the literature showing Trim47 enrichment in brain endothelial cells at single cell level. Functional evaluation of TRIM47 by small interfering RNAs-mediated knockdown in human brain endothelial cells showed increased endothelial permeability, an important hallmark of cerebral small vessel disease pathology. Overall, our comprehensive gene-mapping study and preliminary functional evaluation suggests a putative role of TRIM47 in the pathophysiology of cerebral small vessel disease, making it an important candidate for extensive in vivo explorations and future translational work.

{Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways - Young, W. J.; Lahrouchi, N.; Isaacs, A.; Duong, T.; Foco, L.; Ahmed, F.; Brody, J. A.; Salman, R.; Noordam, R.; Benjamins, J. W.; Haessler, J.; Lyytikäinen, L. P.; et al. (Nat Commun, 2022)
250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.

{Genetic and clinical determinants of abdominal aortic diameter: genome-wide association studies, exome array data and Mendelian randomization study - Portilla-Fernandez, E.; Klarin, D.; Hwang, S. J.; Biggs, M. L.; Bis, J. C.; Weiss, S.; Rospleszcz, S.; Natarajan, P.; Hoffmann, U.; Rogers, I. S.; Truong, Q. A.; lker, U.; et al. (Hum Mol Genet, 2022)
0.0001), known risk factors for AAA, consistent with a causal association with AAD. Our findings point to new biology as well as highlighting gene regions in mechanisms that have previously been implicated in the genetics of other vascular diseases.

Genetic loci and prioritization of genes for kidney function decline derived from a meta-analysis of 62 longitudinal genome-wide association studies. - Gorski, Mathias; Rasheed, Humaira; Teumer, Alexander; Thomas, Laurent F; Graham, Sarah E; Sveinbjornsson, Gardar; Winkler, Thomas W; Günther, Felix; Stark, Klaus J; Chai, Jin-Fang; Tayo, Bamidele O; Wuttke, Matthias; et al. (Kidney Int, 2022)
Estimated glomerular filtration rate (eGFR) reflects kidney function. Progressive eGFR-decline can lead to kidney failure, necessitating dialysis or transplantation. Hundreds of loci from genome-wide association studies (GWAS) for eGFR help explain population cross section variability. Since the contribution of these or other loci to eGFR-decline remains largely unknown, we derived GWAS for annual eGFR-decline and meta-analyzed 62 longitudinal studies with eGFR assessed twice over time in all 343,339 individuals and in high-risk groups. We also explored different covariate adjustment. Twelve genome-wide significant independent variants for eGFR-decline unadjusted or adjusted for eGFR-baseline (11 novel, one known for this phenotype), including nine variants robustly associated across models were identified. All loci for eGFR-decline were known for cross-sectional eGFR and thus distinguished a subgroup of eGFR loci. Seven of the nine variants showed variant-by-age interaction on eGFR cross section (further about 350,000 individuals), which linked genetic associations for eGFR-decline with age-dependency of genetic cross-section associations. Clinically important were two to four-fold greater genetic effects on eGFR-decline in high-risk subgroups. Five variants associated also with chronic kidney disease progression mapped to genes with functional in-silico evidence (UMOD, SPATA7, GALNTL5, TPPP). An unfavorable versus favorable nine-variant genetic profile showed increased risk odds ratios of 1.35 for kidney failure (95% confidence intervals 1.03-1.77) and 1.27 for acute kidney injury (95% confidence intervals 1.08-1.50) in over 2000 cases each, with matched controls). Thus, we provide a large data resource, genetic loci, and prioritized genes for kidney function decline, which help inform drug development pipelines revealing important insights into the age-dependency of kidney function genetics.

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Boerwinkle, Eric; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.

{Genome-wide studies reveal factors associated with circulating uromodulin and its relationships to complex diseases - Li, Y.; Cheng, Y.; Consolato, F.; Schiano, G.; Chong, M. R.; Pietzner, M.; Nguyen, N. Q. H.; Scherer, N.; Biggs, M. L.; Kleber, M. E.; Haug, S.; Göçmen, B.; et al. (JCI Insight, 2022)
Uromodulin (UMOD) is a major risk gene for monogenic and complex forms of kidney disease. The encoded kidney-specific protein uromodulin is highly abundant in urine and related to chronic kidney disease, hypertension, and pathogen defense. To gain insights into potential systemic roles, we performed genome-wide screens of circulating uromodulin using complementary antibody-based and aptamer-based assays. We detected 3 and 10 distinct significant loci, respectively. Integration of antibody-based results at the UMOD locus with functional genomics data (RNA-Seq, ATAC-Seq, Hi-C) of primary human kidney tissue highlighted an upstream variant with differential accessibility and transcription in uromodulin-synthesizing kidney cells as underlying the observed cis effect. Shared association patterns with complex traits, including chronic kidney disease and blood pressure, placed the PRKAG2 locus in the same pathway as UMOD. Experimental validation of the third antibody-based locus, B4GALNT2, showed that the p.Cys466Arg variant of the encoded N-acetylgalactosaminyltransferase had a loss-of-function effect leading to higher serum uromodulin levels. Aptamer-based results pointed to enzymes writing glycan marks present on uromodulin and to their receptors in the circulation, suggesting that this assay permits investigating uromodulin's complex glycosylation rather than its quantitative levels. Overall, our study provides insights into circulating uromodulin and its emerging functions.

{Implicating genes, pleiotropy, and sexual dimorphism at blood lipid loci through multi-ancestry meta-analysis - Kanoni, S.; Graham, S. E.; Wang, Y.; Surakka, I.; Ramdas, S.; Zhu, X.; Clarke, S. L.; Bhatti, K. F.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Genome Biol, 2022)
Genetic variants within nearly 1000 loci are known to contribute to modulation of blood lipid levels. However, the biological pathways underlying these associations are frequently unknown, limiting understanding of these findings and hindering downstream translational efforts such as drug target discovery.\ 1,654,960) of blood lipids to prioritize putative causal genes for 2286 lipid associations using six gene prediction approaches. Using phenome-wide association (PheWAS) scans, we identify relationships of genetically predicted lipid levels to other diseases and conditions. We confirm known pleiotropic associations with cardiovascular phenotypes and determine novel associations, notably with cholelithiasis risk. We perform sex-stratified GWAS meta-analysis of lipid levels and show that 3-5% of autosomal lipid-associated loci demonstrate sex-biased effects. Finally, we report 21 novel lipid loci identified on the X chromosome. Many of the sex-biased autosomal and X chromosome lipid loci show pleiotropic associations with sex hormones, emphasizing the role of hormone regulation in lipid metabolism.\ Taken together, our findings provide insights into the biological mechanisms through which associated variants lead to altered lipid levels and potentially cardiovascular disease risk.

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.

Integrative analysis of clinical and epigenetic biomarkers of mortality. - Huan, Tianxiao; Nguyen, Steve; Colicino, Elena; Ochoa-Rosales, Carolina; Hill, W David; Brody, Jennifer A; Soerensen, Mette; Zhang, Yan; Baldassari, Antoine; Elhadad, Mohamed Ahmed; Toshiko, Tanaka; Zheng, Yinan; et al. (Aging Cell, 2022)
DNA methylation (DNAm) has been reported to be associated with many diseases and with mortality. We hypothesized that the integration of DNAm with clinical risk factors would improve mortality prediction. We performed an epigenome-wide association study of whole blood DNAm in relation to mortality in 15 cohorts (n = 15,013). During a mean follow-up of 10 years, there were 4314 deaths from all causes including 1235 cardiovascular disease (CVD) deaths and 868 cancer deaths. Ancestry-stratified meta-analysis of all-cause mortality identified 163 CpGs in European ancestry (EA) and 17 in African ancestry (AA) participants at p < 1 × 10 , of which 41 (EA) and 16 (AA) were also associated with CVD death, and 15 (EA) and 9 (AA) with cancer death. We built DNAm-based prediction models for all-cause mortality that predicted mortality risk after adjusting for clinical risk factors. The mortality prediction model trained by integrating DNAm with clinical risk factors showed an improvement in prediction of cancer death with 5% increase in the C-index in a replication cohort, compared with the model including clinical risk factors alone. Mendelian randomization identified 15 putatively causal CpGs in relation to longevity, CVD, or cancer risk. For example, cg06885782 (in KCNQ4) was positively associated with risk for prostate cancer (Beta = 1.2, P  = 4.1 × 10 ) and negatively associated with longevity (Beta = -1.9, P  = 0.02). Pathway analysis revealed that genes associated with mortality-related CpGs are enriched for immune- and cancer-related pathways. We identified replicable DNAm signatures of mortality and demonstrated the potential utility of CpGs as informative biomarkers for prediction of mortality risk.
Keywords: Biomarkers; Cardiovascular Diseases; DNA Methylation; Epigenesis, Genetic; Epigenomics; Humans; Male; Neoplasms

Large-scale genome-wide association study of coronary artery disease in genetically diverse populations. - Tcheandjieu, Catherine; Zhu, Xiang; Hilliard, Austin T; Clarke, Shoa L; Napolioni, Valerio; Ma, Shining; Lee, Kyung Min; Fang, Huaying; Chen, Fei; Lu, Yingchang; Tsao, Noah L; Raghavan, Sridharan; et al. (Nat Med, 2022)
We report a genome-wide association study (GWAS) of coronary artery disease (CAD) incorporating nearly a quarter of a million cases, in which existing studies are integrated with data from cohorts of white, Black and Hispanic individuals from the Million Veteran Program. We document near equivalent heritability of CAD across multiple ancestral groups, identify 95 novel loci, including nine on the X chromosome, detect eight loci of genome-wide significance in Black and Hispanic individuals, and demonstrate that two common haplotypes at the 9p21 locus are responsible for risk stratification in all populations except those of African origin, in which these haplotypes are virtually absent. Moreover, in the largest GWAS for angiographically derived coronary atherosclerosis performed to date, we find 15 loci of genome-wide significance that robustly overlap with established loci for clinical CAD. Phenome-wide association analyses of novel loci and polygenic risk scores (PRSs) augment signals related to insulin resistance, extend pleiotropic associations of these loci to include smoking and family history, and precisely document the markedly reduced transferability of existing PRSs to Black individuals. Downstream integrative analyses reinforce the critical roles of vascular endothelial, fibroblast, and smooth muscle cells in CAD susceptibility, but also point to a shared biology between atherosclerosis and oncogenesis. This study highlights the value of diverse populations in further characterizing the genetic architecture of CAD.
Keywords: Coronary Artery Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

Lung function impairment and risk of incident heart failure: the NHLBI Pooled Cohorts Study. - Eckhardt, Christina M; Balte, Pallavi P; Barr, Robert Graham; Bertoni, Alain G; Bhatt, Surya P; Cuttica, Michael; Cassano, Patricia A; Chaves, Paolo; Couper, David; Jacobs, David R; Kalhan, Ravi; Kronmal, Richard; et al. (Eur Heart J, 2022)
AIMS: The aim is to evaluate associations of lung function impairment with risk of incident heart failure (HF). METHODS AND RESULTS: Data were pooled across eight US population-based cohorts that enrolled participants from 1987 to 2004. Participants with self-reported baseline cardiovascular disease were excluded. Spirometry was used to define obstructive [forced expiratory volume in 1 s/forced vital capacity (FEV1/FVC) <0.70] or restrictive (FEV1/FVC ≥0.70, FVC <80%) lung physiology. The incident HF was defined as hospitalization or death caused by HF. In a sub-set, HF events were sub-classified as HF with reduced ejection fraction (HFrEF; EF <50%) or preserved EF (HFpEF; EF ≥50%). The Fine-Gray proportional sub-distribution hazards models were adjusted for sociodemographic factors, smoking, and cardiovascular risk factors. In models of incident HF sub-types, HFrEF, HFpEF, and non-HF mortality were treated as competing risks. Among 31 677 adults, there were 3344 incident HF events over a median follow-up of 21.0 years. Of 2066 classifiable HF events, 1030 were classified as HFrEF and 1036 as HFpEF. Obstructive [adjusted hazard ratio (HR) 1.17, 95% confidence interval (CI) 1.07-1.27] and restrictive physiology (adjusted HR 1.43, 95% CI 1.27-1.62) were associated with incident HF. Obstructive and restrictive ventilatory defects were associated with HFpEF but not HFrEF. The magnitude of the association between restrictive physiology and HFpEF was similar to associations with hypertension, diabetes, and smoking. CONCLUSION: Lung function impairment was associated with increased risk of incident HF, and particularly incident HFpEF, independent of and to a similar extent as major known cardiovascular risk factors.
Keywords: Adult; Heart Failure; Hospitalization; Humans; Lung; National Heart, Lung, and Blood Institute (U.S.); Prognosis; Risk Factors; Stroke Volume; United States

Monogenic and Polygenic Contributions to QTc Prolongation in the Population. - Nauffal, Victor; Morrill, Valerie N; Jurgens, Sean J; Choi, Seung Hoan; Hall, Amelia W; Weng, Lu-Chen; Halford, Jennifer L; Austin-Tse, Christina; Haggerty, Christopher M; Harris, Stephanie L; Wong, Eugene K; Alonso, Alvaro; et al. (Circulation, 2022)
Rare sequence variation in genes underlying cardiac repolarization and common polygenic variation influence QT interval duration. However, current clinical genetic testing of individuals with unexplained QT prolongation is restricted to examination of monogenic rare variants. The recent emergence of large-scale biorepositories with sequence data enables examination of the joint contribution of rare and common variation to the QT interval in the population. We performed a genome wide association study (GWAS) of the QTc in 84,630 United Kingdom Biobank (UKB) participants and created a polygenic risk score (PRS). Among 26,976 participants with whole genome sequencing and electrocardiogram data in the Trans-Omics for Precision Medicine (TOPMed) program, we identified 160 carriers of putative pathogenic rare variants in 10 genes known to be associated with the QT interval. We examined QTc associations with the PRS and with rare variants in TOPMed. Fifty-four independent loci were identified by GWAS in the UKB. Twenty-one loci were novel, of which 12 were replicated in TOPMed. The PRS comprising 1,110,494 common variants was significantly associated with the QTc in TOPMed (ΔQTc/ = 1.4 ms, 95% CI 1.3 -1.5; p-value=1.1×10). Carriers of putative pathogenic rare variants had longer QTc than non-carriers (ΔQTc=10.9 ms [7.4-14.4]). 23.7% of individuals with QTc>480 ms carried either a monogenic rare variant or had a PRS in the top decile (3.4% monogenic, 21% top decile of PRS). QTc duration in the population is influenced by both rare variants in genes underlying cardiac repolarization and polygenic risk, with a sizeable contribution from polygenic risk. Comprehensive assessment of the genetic determinants of QTc prolongation includes incorporation of both polygenic and monogenic risk.

Multi-ancestry genetic study of type 2 diabetes highlights the power of diverse populations for discovery and translation. - Mahajan, Anubha; Spracklen, Cassandra N; Zhang, Weihua; Ng, Maggie C Y; Petty, Lauren E; Kitajima, Hidetoshi; Yu, Grace Z; Rüeger, Sina; Speidel, Leo; Kim, Young Jin; Horikoshi, Momoko; Mercader, Josep M; et al. (Nat Genet, 2022)
We assembled an ancestrally diverse collection of genome-wide association studies (GWAS) of type 2 diabetes (T2D) in 180,834 affected individuals and 1,159,055 controls (48.9% non-European descent) through the Diabetes Meta-Analysis of Trans-Ethnic association studies (DIAMANTE) Consortium. Multi-ancestry GWAS meta-analysis identified 237 loci attaining stringent genome-wide significance (P < 5 × 10), which were delineated to 338 distinct association signals. Fine-mapping of these signals was enhanced by the increased sample size and expanded population diversity of the multi-ancestry meta-analysis, which localized 54.4% of T2D associations to a single variant with >50% posterior probability. This improved fine-mapping enabled systematic assessment of candidate causal genes and molecular mechanisms through which T2D associations are mediated, laying the foundations for functional investigations. Multi-ancestry genetic risk scores enhanced transferability of T2D prediction across diverse populations. Our study provides a step toward more effective clinical translation of T2D GWAS to improve global health for all, irrespective of genetic background.
Keywords: Diabetes Mellitus, Type 2; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

Multi-Scalar Data Integration Links Glomerular Angiopoietin-Tie Signaling Pathway Activation With Progression of Diabetic Kidney Disease. - Liu, Jiahao; Nair, Viji; Zhao, Yi-Yang; Chang, Dong-Yuan; Limonte, Christine; Bansal, Nisha; Fermin, Damian; Eichinger, Felix; Tanner, Emily C; Bellovich, Keith A; Steigerwalt, Susan; Bhat, Zeenat; et al. (Diabetes, 2022)
Diabetic kidney disease (DKD) is the leading cause of end-stage kidney disease (ESKD). Prognostic biomarkers reflective of underlying molecular mechanisms are critically needed for effective management of DKD. A three-marker panel was derived from a proteomics analysis of plasma samples by an unbiased machine learning approach from participants (N = 58) in the Clinical Phenotyping and Resource Biobank study. In combination with standard clinical parameters, this panel improved prediction of the composite outcome of ESKD or a 40% decline in glomerular filtration rate. The panel was validated in an independent group (N = 68), who also had kidney transcriptomic profiles. One marker, plasma angiopoietin 2 (ANGPT2), was significantly associated with outcomes in cohorts from the Cardiovascular Health Study (N = 3,183) and the Chinese Cohort Study of Chronic Kidney Disease (N = 210). Glomerular transcriptional angiopoietin/Tie (ANG-TIE) pathway scores, derived from the expression of 154 ANG-TIE signaling mediators, correlated positively with plasma ANGPT2 levels and kidney outcomes. Higher receptor expression in glomeruli and higher ANG-TIE pathway scores in endothelial cells corroborated potential functional effects in the kidney from elevated plasma ANGPT2 levels. Our work suggests that ANGPT2 is a promising prognostic endothelial biomarker with likely functional impact on glomerular pathogenesis in DKD.
Keywords: Angiopoietin-1; Angiopoietin-2; Angiopoietins; Biomarkers; Cohort Studies; Diabetes Mellitus; Diabetic Nephropathies; Disease Progression; Endothelial Cells; Humans; Kidney Failure, Chronic; Receptor, TIE-2; Signal Transduction

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

{Obesity Partially Mediates the Diabetogenic Effect of Lowering LDL Cholesterol - Wu, P.; Moon, J. Y.; Daghlas, I.; Franco, G.; Porneala, B. C.; Ahmadizar, F.; Richardson, T. G.; Isaksen, J. L.; Hindy, G.; Yao, J.; Sitlani, C. M.; Raffield, L. M.; et al. (Diabetes Care, 2022)
LDL cholesterol (LDLc)-lowering drugs modestly increase body weight and type 2 diabetes risk, but the extent to which the diabetogenic effect of lowering LDLc is mediated through increased BMI is unknown.\ We conducted summary-level univariable and multivariable Mendelian randomization (MR) analyses in 921,908 participants to investigate the effect of lowering LDLc on type 2 diabetes risk and the proportion of this effect mediated through BMI. We used data from 92,532 participants from 14 observational studies to replicate findings in individual-level MR analyses.\ A 1-SD decrease in genetically predicted LDLc was associated with increased type 2 diabetes odds (odds ratio [OR] 1.12 [95% CI 1.01, 1.24]) and BMI (β = 0.07 SD units [95% CI 0.02, 0.12]) in univariable MR analyses. The multivariable MR analysis showed evidence of an indirect effect of lowering LDLc on type 2 diabetes through BMI (OR 1.04 [95% CI 1.01, 1.08]) with a proportion mediated of 38% of the total effect (P = 0.03). Total and indirect effect estimates were similar across a number of sensitivity analyses. Individual-level MR analyses confirmed the indirect effect of lowering LDLc on type 2 diabetes through BMI with an estimated proportion mediated of 8% (P = 0.04).\ These findings suggest that the diabetogenic effect attributed to lowering LDLc is partially mediated through increased BMI. Our results could help advance understanding of adipose tissue and lipids in type 2 diabetes pathophysiology and inform strategies to reduce diabetes risk among individuals taking LDLc-lowering medications.

Plasma epoxyeicosatrienoic acids and diabetes-related cardiovascular disease: The cardiovascular health study. - Lemaitre, Rozenn N; Jensen, Paul N; Zeigler, Maxwell; Fretts, Amanda M; Umans, Jason G; Howard, Barbara V; Sitlani, Colleen M; McKnight, Barbara; Gharib, Sina A; King, Irena B; Siscovick, David S; Psaty, Bruce M; et al. (EBioMedicine, 2022)
BACKGROUND: Epoxyeicosatrienoic acids (EETs) are metabolites of arachidonic acid that may impact atherosclerosis, and animal experimental studies suggest EETs protect cardiac function. Plasma EETs are mostly esterified to phospholipids and part of an active pool. To address the limited information about EETs and CVD in humans, we conducted a prospective study of total plasma EETs (free + esterified) and diabetes-related CVD in the Cardiovascular Health Study (CHS). METHODS: We measured 4 EET species and their metabolites, dihydroxyepoxyeicosatrienoic acids (DHETs), in plasma samples from 892 CHS participants with type 2 diabetes. We determined the association of EETs and DHETs with incident myocardial infarction (MI) and ischemic stroke using Cox regression. FINDINGS: During follow-up (median 7.5 years), we identified 150 MI and 134 ischemic strokes. In primary, multivariable analyses, elevated levels of each EET species were associated with non-significant lower risk of incident MI (for example, hazard ratio for 1 SD higher 14,15-EET: 0.86, 95% CI: 0.72-1.02; p=0.08). The EETs-MI associations became significant in analyses further adjusted for DHETs (hazard ratio for 1 SD higher 14,15-EET adjusted for 14,15-DHET: 0.76, 95% CI: 0.63-0.91; p=0.004). Elevated EET levels were associated with higher risk of ischemic stroke in primary but not secondary analyses. Three DHET species were associated with higher risk of ischemic stroke in all analyses. INTERPRETATION: Findings from this prospective study complement the extensive studies in animal models showing EETs protect cardiac function and provide new information in humans. Replication is needed to confirm the associations. FUNDING: US National Institutes of Health.
Keywords: Animals; Arachidonic Acids; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Eicosanoids; Humans; Ischemic Stroke; Prospective Studies

Polygenic transcriptome risk scores for COPD and lung function improve cross-ethnic portability of prediction in the NHLBI TOPMed program. - Hu, Xiaowei; Qiao, Dandi; Kim, Wonji; Moll, Matthew; Balte, Pallavi P; Lange, Leslie A; Bartz, Traci M; Kumar, Rajesh; Li, Xingnan; Yu, Bing; Cade, Brian E; Laurie, Cecelia A; et al. (Am J Hum Genet, 2022)
While polygenic risk scores (PRSs) enable early identification of genetic risk for chronic obstructive pulmonary disease (COPD), predictive performance is limited when the discovery and target populations are not well matched. Hypothesizing that the biological mechanisms of disease are shared across ancestry groups, we introduce a PrediXcan-derived polygenic transcriptome risk score (PTRS) to improve cross-ethnic portability of risk prediction. We constructed the PTRS using summary statistics from application of PrediXcan on large-scale GWASs of lung function (forced expiratory volume in 1 s [FEV] and its ratio to forced vital capacity [FEV/FVC]) in the UK Biobank. We examined prediction performance and cross-ethnic portability of PTRS through smoking-stratified analyses both on 29,381 multi-ethnic participants from TOPMed population/family-based cohorts and on 11,771 multi-ethnic participants from TOPMed COPD-enriched studies. Analyses were carried out for two dichotomous COPD traits (moderate-to-severe and severe COPD) and two quantitative lung function traits (FEV and FEV/FVC). While the proposed PTRS showed weaker associations with disease than PRS for European ancestry, the PTRS showed stronger association with COPD than PRS for African Americans (e.g., odds ratio [OR] = 1.24 [95% confidence interval [CI]: 1.08-1.43] for PTRS versus 1.10 [0.96-1.26] for PRS among heavy smokers with ≥ 40 pack-years of smoking) for moderate-to-severe COPD. Cross-ethnic portability of the PTRS was significantly higher than the PRS (paired t test p < 2.2 × 10 with portability gains ranging from 5% to 28%) for both dichotomous COPD traits and across all smoking strata. Our study demonstrates the value of PTRS for improved cross-ethnic portability compared to PRS in predicting COPD risk.

Pooled Cohort Probability Score for Subclinical Airflow Obstruction. - Bhatt, Surya P; Balte, Pallavi P; Schwartz, Joseph E; Jaeger, Byron C; Cassano, Patricia A; Chaves, Paulo H; Couper, David; Jacobs, David R; Kalhan, Ravi; Kaplan, Robert; Lloyd-Jones, Donald; Newman, Anne B; et al. (Ann Am Thorac Soc, 2022)
Early detection of chronic obstructive pulmonary disease (COPD) is a public health priority. Airflow obstruction is the single most important risk factor for adverse COPD outcomes, but spirometry is not routinely recommended for screening. To describe the burden of subclinical airflow obstruction (SAO) and to develop a probability score for SAO to inform potential detection and prevention programs. Lung function and clinical data were harmonized and pooled across nine U.S. general population cohorts. Adults with respiratory symptoms, inhaler use, or prior diagnosis of COPD or asthma were excluded. A probability score for prevalent SAO (forced expiratory volume in 1 second/forced vital capacity < 0.70) was developed via hierarchical group-lasso regularization from clinical variables in strata of sex and smoking status, and its discriminative accuracy for SAO was assessed in the pooled cohort as well as in an external validation cohort (NHANES [National Health and Nutrition Examination Survey] 2011-2012). Incident hospitalizations and deaths due to COPD (respiratory events) were defined by adjudication or administrative criteria in four of nine cohorts. Of 33,546 participants (mean age 52 yr, 54% female, 44% non-Hispanic White), 4,424 (13.2%) had prevalent SAO. The incidence of respiratory events ( = 14,024) was threefold higher in participants with SAO versus those without (152 vs. 39 events/10,000 person-years). The probability score, which was based on six commonly available variables (age, sex, race and/or ethnicity, body mass index, smoking status, and smoking pack-years) was well calibrated and showed excellent discrimination in both the testing sample (C-statistic, 0.81; 95% confidence interval [CI], 0.80-0.82) and in NHANES (C-statistic, 0.83; 95% CI, 0.80-0.86). Among participants with predicted probabilities ⩾ 15%, 3.2 would need to undergo spirometry to detect one case of SAO. Adults with SAO demonstrate excess respiratory hospitalization and mortality. A probability score for SAO using commonly available clinical risk factors may be suitable for targeting screening and primary prevention strategies.
Keywords: Adult; Female; Forced Expiratory Volume; Humans; Lung; Male; Middle Aged; Nutrition Surveys; Pulmonary Disease, Chronic Obstructive; Risk Factors; Spirometry; Vital Capacity

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Rare genetic variants explain missing heritability in smoking. - Jang, Seon-Kyeong; Evans, Luke; Fialkowski, Allison; Arnett, Donna K; Ashley-Koch, Allison E; Barnes, Kathleen C; Becker, Diane M; Bis, Joshua C; Blangero, John; Bleecker, Eugene R; Boorgula, Meher Preethi; Bowden, Donald W; et al. (Nat Hum Behav, 2022)
Common genetic variants explain less variation in complex phenotypes than inferred from family-based studies, and there is a debate on the source of this 'missing heritability'. We investigated the contribution of rare genetic variants to tobacco use with whole-genome sequences from up to 26,257 unrelated individuals of European ancestries and 11,743 individuals of African ancestries. Across four smoking traits, single-nucleotide-polymorphism-based heritability ([Formula: see text]) was estimated from 0.13 to 0.28 (s.e., 0.10-0.13) in European ancestries, with 35-74% of it attributable to rare variants with minor allele frequencies between 0.01% and 1%. These heritability estimates are 1.5-4 times higher than past estimates based on common variants alone and accounted for 60% to 100% of our pedigree-based estimates of narrow-sense heritability ([Formula: see text], 0.18-0.34). In the African ancestry samples, [Formula: see text] was estimated from 0.03 to 0.33 (s.e., 0.09-0.14) across the four smoking traits. These results suggest that rare variants are important contributors to the heritability of smoking.

{A saturated map of common genetic variants associated with human height - Yengo, L.; Vedantam, S.; Marouli, E.; Sidorenko, J.; Bartell, E.; Sakaue, S.; Graff, M.; Eliasen, A. U.; Jiang, Y.; Raghavan, S.; Miao, J.; Arias, J. D.; et al. (Nature, 2022)
) account for 40% (45%) of phenotypic variance in populations of European ancestry but only around 10-20% (14-24%) in populations of other ancestries. Effect sizes, associated regions and gene prioritization are similar across ancestries, indicating that reduced prediction accuracy is likely to be explained by linkage disequilibrium and differences in allele frequency within associated regions. Finally, we show that the relevant biological pathways are detectable with smaller sample sizes than are needed to implicate causal genes and variants. Overall, this study provides a comprehensive map of specific genomic regions that contain the vast majority of common height-associated variants. Although this map is saturated for populations of European ancestry, further research is needed to achieve equivalent saturation in other ancestries.

Stroke genetics informs drug discovery and risk prediction across ancestries. - Mishra, Aniket; Malik, Rainer; Hachiya, Tsuyoshi; Jürgenson, Tuuli; Namba, Shinichi; Posner, Daniel C; Kamanu, Frederick K; Koido, Masaru; Le Grand, Quentin; Shi, Mingyang; He, Yunye; Georgakis, Marios K; et al. (Nature, 2022)
Previous genome-wide association studies (GWASs) of stroke - the second leading cause of death worldwide - were conducted predominantly in populations of European ancestry. Here, in cross-ancestry GWAS meta-analyses of 110,182 patients who have had a stroke (five ancestries, 33% non-European) and 1,503,898 control individuals, we identify association signals for stroke and its subtypes at 89 (61 new) independent loci: 60 in primary inverse-variance-weighted analyses and 29 in secondary meta-regression and multitrait analyses. On the basis of internal cross-ancestry validation and an independent follow-up in 89,084 additional cases of stroke (30% non-European) and 1,013,843 control individuals, 87% of the primary stroke risk loci and 60% of the secondary stroke risk loci were replicated (P < 0.05). Effect sizes were highly correlated across ancestries. Cross-ancestry fine-mapping, in silico mutagenesis analysis, and transcriptome-wide and proteome-wide association analyses revealed putative causal genes (such as SH3PXD2A and FURIN) and variants (such as at GRK5 and NOS3). Using a three-pronged approach, we provide genetic evidence for putative drug effects, highlighting F11, KLKB1, PROC, GP1BA, LAMC2 and VCAM1 as possible targets, with drugs already under investigation for stroke for F11 and PROC. A polygenic score integrating cross-ancestry and ancestry-specific stroke GWASs with vascular-risk factor GWASs (integrative polygenic scores) strongly predicted ischaemic stroke in populations of European, East Asian and African ancestry. Stroke genetic risk scores were predictive of ischaemic stroke independent of clinical risk factors in 52,600 clinical-trial participants with cardiometabolic disease. Our results provide insights to inform biology, reveal potential drug targets and derive genetic risk prediction tools across ancestries.

The Value of Rare Genetic Variation in the Prediction of Common Obesity in European Ancestry Populations. - Wang, Zhe; Choi, Shing Wan; Chami, Nathalie; Boerwinkle, Eric; Fornage, Myriam; Redline, Susan; Bis, Joshua C; Brody, Jennifer A; Psaty, Bruce M; Kim, Wonji; McDonald, Merry-Lynn N; Regan, Elizabeth A; et al. (Front Endocrinol (Lausanne), 2022)
Polygenic risk scores (PRSs) aggregate the effects of genetic variants across the genome and are used to predict risk of complex diseases, such as obesity. Current PRSs only include common variants (minor allele frequency (MAF) ≥1%), whereas the contribution of rare variants in PRSs to predict disease remains unknown. Here, we examine whether augmenting the standard common variant PRS (PRS) with a rare variant PRS (PRS) improves prediction of obesity. We used genome-wide genotyped and imputed data on 451,145 European-ancestry participants of the UK Biobank, as well as whole exome sequencing (WES) data on 184,385 participants. We performed single variant analyses (for both common and rare variants) and gene-based analyses (for rare variants) for association with BMI (kg/m), obesity (BMI ≥ 30 kg/m), and extreme obesity (BMI ≥ 40 kg/m). We built PRSs and PRSs using a range of methods (Clumping+Thresholding [C+T], PRS-CS, lassosum, gene-burden test). We selected the best-performing PRSs and assessed their performance in 36,757 European-ancestry unrelated participants with whole genome sequencing (WGS) data from the Trans-Omics for Precision Medicine (TOPMed) program. The best-performing PRS explained 10.1% of variation in BMI, and 18.3% and 22.5% of the susceptibility to obesity and extreme obesity, respectively, whereas the best-performing PRS explained 1.49%, and 2.97% and 3.68%, respectively. The PRS was associated with an increased risk of obesity and extreme obesity (OR = 1.37 per SD, = 1.7x10; OR = 1.55 per SD, = 3.8x10), which was attenuated, after adjusting for PRS (OR = 1.08 per SD, = 9.8x10; OR= 1.09 per SD, = 0.02). When PRS and PRS are combined, the increase in explained variance attributed to PRS was small (incremental Nagelkerke R = 0.24% for obesity and 0.51% for extreme obesity). Consistently, combining PRS to PRS provided little improvement to the prediction of obesity (PRS AUC = 0.591; PRS AUC = 0.708; PRS AUC = 0.710). In summary, while rare variants show convincing association with BMI, obesity and extreme obesity, the PRS provides limited improvement over PRS in the prediction of obesity risk, based on these large populations.
Keywords: Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Obesity; Whole Genome Sequencing

Whole exome sequencing of 14 389 individuals from the ESP and CHARGE consortia identifies novel rare variation associated with hemostatic factors. - Pankratz, Nathan; Wei, Peng; Brody, Jennifer A; Chen, Ming-Huei; Vries, Paul S; Huffman, Jennifer E; Stimson, Mary Rachel; Auer, Paul L; Boerwinkle, Eric; Cushman, Mary; Maat, Moniek P M; Folsom, Aaron R; et al. (Hum Mol Genet, 2022)
Plasma levels of fibrinogen, coagulation factors VII and VIII, and von Willebrand factor (vWF) are four intermediate phenotypes that are heritable and have been associated with the risk of clinical thrombotic events. To identify rare and low-frequency variants associated with these hemostatic factors, we conducted whole exome sequencing in 10 860 individuals of European ancestry (EA) and 3529 African Americans (AAs) from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium and the National Heart, Lung, and Blood Institute's Exome Sequencing Project (ESP). Gene-based tests demonstrated significant associations with rare variation (minor allele frequency < 5%) in FGG (with fibrinogen, p = 9.1x10-13), F7 (with factor VII, p = 1.3x10-72; seven novel variants), and VWF (with factor VIII and vWF; p = 3.2x10-14; one novel variant). These eight novel rare variant associations were independent of the known common variants at these loci and tended to have much larger effect sizes. In addition, one of the rare novel variants in F7 was significantly associated with an increased risk of venous thromboembolism in AAs (Ile200Ser; rs141219108; p = 4.2x10-5). After restricting gene-based analyses to only loss-of-function variants, a novel significant association was detected and replicated between factor VIII levels and a stop-gain mutation exclusive to African Americans (rs3211938) in CD36. This variant has previously been linked to dyslipidemia but not with levels of a hemostatic factor. These efforts represent the largest integration of whole exome sequence data from two national projects to identify genetic variation associated with plasma hemostatic factors.

Whole genome sequence association analysis of fasting glucose and fasting insulin levels in diverse cohorts from the NHLBI TOPMed program. - DiCorpo, Daniel; Gaynor, Sheila M; Russell, Emily M; Westerman, Kenneth E; Raffield, Laura M; Majarian, Timothy D; Wu, Peitao; Sarnowski, Chloe; Highland, Heather M; Jackson, Anne; Hasbani, Natalie R; de Vries, Paul S; et al. (Commun Biol, 2022)
The genetic determinants of fasting glucose (FG) and fasting insulin (FI) have been studied mostly through genome arrays, resulting in over 100 associated variants. We extended this work with high-coverage whole genome sequencing analyses from fifteen cohorts in NHLBI's Trans-Omics for Precision Medicine (TOPMed) program. Over 23,000 non-diabetic individuals from five race-ethnicities/populations (African, Asian, European, Hispanic and Samoan) were included. Eight variants were significantly associated with FG or FI across previously identified regions MTNR1B, G6PC2, GCK, GCKR and FOXA2. We additionally characterize suggestive associations with FG or FI near previously identified SLC30A8, TCF7L2, and ADCY5 regions as well as APOB, PTPRT, and ROBO1. Functional annotation resources including the Diabetes Epigenome Atlas were compiled for each signal (chromatin states, annotation principal components, and others) to elucidate variant-to-function hypotheses. We provide a catalog of nucleotide-resolution genomic variation spanning intergenic and intronic regions creating a foundation for future sequencing-based investigations of glycemic traits.
Keywords: Diabetes Mellitus, Type 2; Fasting; Glucose; Humans; Insulin; National Heart, Lung, and Blood Institute (U.S.); Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Precision Medicine; Receptors, Immunologic; United States

Whole genome sequencing identifies structural variants contributing to hematologic traits in the NHLBI TOPMed program. - Wheeler, Marsha M; Stilp, Adrienne M; Rao, Shuquan; Halldorsson, Bjarni V; Beyter, Doruk; Wen, Jia; Mihkaylova, Anna V; McHugh, Caitlin P; Lane, John; Jiang, Min-Zhi; Raffield, Laura M; Jun, Goo; et al. (Nat Commun, 2022)
Genome-wide association studies have identified thousands of single nucleotide variants and small indels that contribute to variation in hematologic traits. While structural variants are known to cause rare blood or hematopoietic disorders, the genome-wide contribution of structural variants to quantitative blood cell trait variation is unknown. Here we utilized whole genome sequencing data in ancestrally diverse participants of the NHLBI Trans Omics for Precision Medicine program (N = 50,675) to detect structural variants associated with hematologic traits. Using single variant tests, we assessed the association of common and rare structural variants with red cell-, white cell-, and platelet-related quantitative traits and observed 21 independent signals (12 common and 9 rare) reaching genome-wide significance. The majority of these associations (N = 18) replicated in independent datasets. In genome-editing experiments, we provide evidence that a deletion associated with lower monocyte counts leads to disruption of an S1PR3 monocyte enhancer and decreased S1PR3 expression.
Keywords: Blood Cells; Genome-Wide Association Study; Humans; Whole Genome Sequencing

{Whole-Genome Sequencing Association Analyses of Stroke and Its Subtypes in Ancestrally Diverse Populations From Trans-Omics for Precision Medicine Project - Hu, Y.; Haessler, J. W.; Manansala, R.; Wiggins, K. L.; Moscati, A.; Beiser, A.; Heard-Costa, N. L.; Sarnowski, C.; Raffield, L. M.; Chung, J.; Marini, S.; Anderson, C. D.; et al. (Stroke, 2022)
Stroke is the leading cause of death and long-term disability worldwide. Previous genome-wide association studies identified 51 loci associated with stroke (mostly ischemic) and its subtypes among predominantly European populations. Using whole-genome sequencing in ancestrally diverse populations from the Trans-Omics for Precision Medicine (TOPMed) Program, we aimed to identify novel variants, especially low-frequency or ancestry-specific variants, associated with all stroke, ischemic stroke and its subtypes (large artery, cardioembolic, and small vessel), and hemorrhagic stroke and its subtypes (intracerebral and subarachnoid).\ Whole-genome sequencing data were available for 6833 stroke cases and 27 116 controls, including 22 315 European, 7877 Black, 2616 Hispanic/Latino, 850 Asian, 54 Native American, and 237 other ancestry participants. In TOPMed, we performed single variant association analysis examining 40 million common variants and aggregated association analysis focusing on rare variants. We also combined TOPMed European populations with over 28 000 additional European participants from the UK BioBank genome-wide array data through meta-analysis.\ .\ We represent the first association analysis for stroke and its subtypes using whole-genome sequencing data from ancestrally diverse populations. While our findings suggest the potential benefits of combining whole-genome sequencing data with populations of diverse genetic backgrounds to identify possible low-frequency or ancestry-specific variants, they also highlight the need to increase genome coverage and sample sizes.

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Antithrombin, Protein C, and Protein S: Genome and Transcriptome-Wide Association Studies Identify 7 Novel Loci Regulating Plasma Levels. - Ji, Yuekai; Temprano-Sagrera, Gerard; Holle, Lori A; Bebo, Allison; Brody, Jennifer A; Le, Ngoc-Quynh; Kangro, Kadri; Brown, Michael R; Martinez-Perez, Angel; Sitlani, Colleen M; Suchon, Pierre; Kleber, Marcus E; et al. (Arterioscler Thromb Vasc Biol, 2023)
BACKGROUND: Antithrombin, PC (protein C), and PS (protein S) are circulating natural anticoagulant proteins that regulate hemostasis and of which partial deficiencies are causes of venous thromboembolism. Previous genetic association studies involving antithrombin, PC, and PS were limited by modest sample sizes or by being restricted to candidate genes. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, we meta-analyzed across ancestries the results from 10 genome-wide association studies of plasma levels of antithrombin, PC, PS free, and PS total. METHODS: Study participants were of European and African ancestries, and genotype data were imputed to TOPMed, a dense multiancestry reference panel. Each of the 10 studies conducted a genome-wide association studies for each phenotype and summary results were meta-analyzed, stratified by ancestry. Analysis of antithrombin included 25 243 European ancestry and 2688 African ancestry participants, PC analysis included 16 597 European ancestry and 2688 African ancestry participants, PSF and PST analysis included 4113 and 6409 European ancestry participants. We also conducted transcriptome-wide association analyses and multiphenotype analysis to discover additional associations. Novel genome-wide association studies and transcriptome-wide association analyses findings were validated by in vitro functional experiments. Mendelian randomization was performed to assess the causal relationship between these proteins and cardiovascular outcomes. RESULTS: Genome-wide association studies meta-analyses identified 4 newly associated loci: 3 with antithrombin levels (, , and ) and 1 with PS levels (-). transcriptome-wide association analyses identified 3 newly associated genes: 1 with antithrombin level (), 1 with PC (), and 1 with PS (). In addition, we replicated 7 independent loci reported in previous studies. Functional experiments provided evidence for the involvement of , , and genes in antithrombin regulation. CONCLUSIONS: The use of larger sample sizes, diverse populations, and a denser imputation reference panel allowed the detection of 7 novel genomic loci associated with plasma antithrombin, PC, and PS levels.
Keywords: Anticoagulants; Antithrombin III; Antithrombins; Genome-Wide Association Study; Polymorphism, Single Nucleotide; Protein C; Protein S; Transcriptome

Association Between Acute Myocardial Infarction and Cognition. - Johansen, Michelle C; Ye, Wen; Gross, Alden; Gottesman, Rebecca F; Han, Dehua; Whitney, Rachael; Briceño, Emily M; Giordani, Bruno J; Shore, Supriya; Elkind, Mitchell S V; Manly, Jennifer J; Sacco, Ralph L; et al. (JAMA Neurol, 2023)
IMPORTANCE: The magnitude of cognitive change after incident myocardial infarction (MI) is unclear. OBJECTIVE: To assess whether incident MI is associated with changes in cognitive function after adjusting for pre-MI cognitive trajectories. DESIGN, SETTING, AND PARTICIPANTS: This cohort study included adults without MI, dementia, or stroke and with complete covariates from the following US population-based cohort studies conducted from 1971 to 2019: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study. Data were analyzed from July 2021 to January 2022. EXPOSURES: Incident MI. MAIN OUTCOMES AND MEASURES: The main outcome was change in global cognition. Secondary outcomes were changes in memory and executive function. Outcomes were standardized as mean (SD) T scores of 50 (10); a 1-point difference represented a 0.1-SD difference in cognition. Linear mixed-effects models estimated changes in cognition at the time of MI (change in the intercept) and the rate of cognitive change over the years after MI (change in the slope), controlling for pre-MI cognitive trajectories and participant factors, with interaction terms for race and sex. RESULTS: The study included 30 465 adults (mean [SD] age, 64 [10] years; 56% female), of whom 1033 had 1 or more MI event, and 29 432 did not have an MI event. Median follow-up was 6.4 years (IQR, 4.9-19.7 years). Overall, incident MI was not associated with an acute decrease in global cognition (-0.18 points; 95% CI, -0.52 to 0.17 points), executive function (-0.17 points; 95% CI, -0.53 to 0.18 points), or memory (0.62 points; 95% CI, -0.07 to 1.31 points). However, individuals with incident MI vs those without MI demonstrated faster declines in global cognition (-0.15 points per year; 95% CI, -0.21 to -0.10 points per year), memory (-0.13 points per year; 95% CI, -0.22 to -0.04 points per year), and executive function (-0.14 points per year; 95% CI, -0.20 to -0.08 points per year) over the years after MI compared with pre-MI slopes. The interaction analysis suggested that race and sex modified the degree of change in the decline in global cognition after MI (race × post-MI slope interaction term, P = .02; sex × post-MI slope interaction term, P = .04), with a smaller change in the decline over the years after MI in Black individuals than in White individuals (difference in slope change, 0.22 points per year; 95% CI, 0.04-0.40 points per year) and in females than in males (difference in slope change, 0.12 points per year; 95% CI, 0.01-0.23 points per year). CONCLUSIONS: This cohort study using pooled data from 6 cohort studies found that incident MI was not associated with a decrease in global cognition, memory, or executive function at the time of the event compared with no MI but was associated with faster declines in global cognition, memory, and executive function over time. These findings suggest that prevention of MI may be important for long-term brain health.

Association Between Whole Blood-Derived Mitochondrial DNA Copy Number, Low-Density Lipoprotein Cholesterol, and Cardiovascular Disease Risk. - Liu, Xue; Sun, Xianbang; Zhang, Yuankai; Jiang, Wenqing; Lai, Meng; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Haessler, Jeffrey; Zheng, Yinan; et al. (J Am Heart Assoc, 2023)
Background The relationship between mitochondrial DNA copy number (mtDNA CN) and cardiovascular disease remains elusive. Methods and Results We performed cross-sectional and prospective association analyses of blood-derived mtDNA CN and cardiovascular disease outcomes in 27 316 participants in 8 cohorts of multiple racial and ethnic groups with whole-genome sequencing. We also performed Mendelian randomization to explore causal relationships of mtDNA CN with coronary heart disease (CHD) and cardiometabolic risk factors (obesity, diabetes, hypertension, and hyperlipidemia). <0.01 was used for significance. We validated most of the previously reported associations between mtDNA CN and cardiovascular disease outcomes. For example, 1-SD unit lower level of mtDNA CN was associated with 1.08 (95% CI, 1.04-1.12; <0.001) times the hazard for developing incident CHD, adjusting for covariates. Mendelian randomization analyses showed no causal effect from a lower level of mtDNA CN to a higher CHD risk (β=0.091; =0.11) or in the reverse direction (β=-0.012; =0.076). Additional bidirectional Mendelian randomization analyses revealed that low-density lipoprotein cholesterol had a causal effect on mtDNA CN (β=-0.084; <0.001), but the reverse direction was not significant (=0.059). No causal associations were observed between mtDNA CN and obesity, diabetes, and hypertension, in either direction. Multivariable Mendelian randomization analyses showed no causal effect of CHD on mtDNA CN, controlling for low-density lipoprotein cholesterol level (=0.52), whereas there was a strong direct causal effect of higher low-density lipoprotein cholesterol on lower mtDNA CN, adjusting for CHD status (β=-0.092; <0.001). Conclusions Our findings indicate that high low-density lipoprotein cholesterol may underlie the complex relationships between mtDNA CN and vascular atherosclerosis.

Association of a blood-based aging biomarker index with death and chronic disease: Cardiovascular Health Study. - Zhang, Xiao; Sanders, Jason L; Boudreau, Robert M; Arnold, Alice M; Justice, Jamie N; Espeland, Mark A; Kuchel, George A; Barzilai, Nir; Kuller, Lewis H; Lopez, Oscar L; Kritchevsky, Stephen B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: A goal of gerontology is to discover phenotypes that reflect biological aging distinct from disease pathogenesis. Biomarkers that are strongly associated with mortality could be used to define such a phenotype. However, the relation of such an index with multiple chronic conditions warrants further exploration. METHODS: A Biomarker Index (BI) was constructed in the Cardiovascular Health Study (N=3197), with a mean age of 74 years. The BI incorporated circulating levels of new biomarkers, including insulin-like growth factor-1, interleukin-6, amino-terminal pro-B-type natriuretic peptide, cystatin-C, C-reactive protein, tumor necrosis factor-alpha soluble receptor 1, fasting insulin, and fasting glucose, and was built based on their relationships with mortality. Cox proportional hazards models predicting a composite of death and chronic disease involving cardiovascular disease, dementia, and cancer were calculated with 6 years of follow-up. RESULTS: The hazard ratio (HR, 95% CI) for the composite outcome of death or chronic disease per category of BI was 1.65 (1.52, 1.80) and 1.75 (1.58, 1.94) in women and men, respectively. The HR (95% CI) per 5 years of age was 1.57 (1.48, 1.67) and 1.55 (1.44, 1.67) in women and men, respectively. Moreover, BI could attenuate the effect of age on the composite outcome by 16.7% and 22.0% in women and men, respectively. CONCLUSIONS: BI was significantly and independently associated with a composite outcome of death and chronic disease, and attenuated the effect of age. The BI that is composed of plasma biomarkers may be a practical intermediate phenotype for interventions aiming to modify the course of aging.

Association of omega 3 polyunsaturated fatty acids with incident chronic kidney disease: pooled analysis of 19 cohorts. - Ong, Kwok Leung; Marklund, Matti; Huang, Liping; Rye, Kerry-Anne; Hui, Nicholas; Pan, Xiong-Fei; Rebholz, Casey M; Kim, Hyunju; Steffen, Lyn M; van Westing, Anniek C; Geleijnse, Johanna M; Hoogeveen, Ellen K; et al. (BMJ, 2023)
OBJECTIVE: To assess the prospective associations of circulating levels of omega 3 polyunsaturated fatty acid (n-3 PUFA) biomarkers (including plant derived α linolenic acid and seafood derived eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid) with incident chronic kidney disease (CKD). DESIGN: Pooled analysis. DATA SOURCES: A consortium of 19 studies from 12 countries identified up to May 2020. STUDY SELECTION: Prospective studies with measured n-3 PUFA biomarker data and incident CKD based on estimated glomerular filtration rate. DATA EXTRACTION AND SYNTHESIS: Each participating cohort conducted de novo analysis with prespecified and consistent exposures, outcomes, covariates, and models. The results were pooled across cohorts using inverse variance weighted meta-analysis. MAIN OUTCOME MEASURES: Primary outcome of incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m. In a sensitivity analysis, incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m and <75% of baseline rate. RESULTS: 25 570 participants were included in the primary outcome analysis and 4944 (19.3%) developed incident CKD during follow-up (weighted median 11.3 years). In multivariable adjusted models, higher levels of total seafood n-3 PUFAs were associated with a lower incident CKD risk (relative risk per interquintile range 0.92, 95% confidence interval 0.86 to 0.98; P=0.009, I=9.9%). In categorical analyses, participants with total seafood n-3 PUFA level in the highest fifth had 13% lower risk of incident CKD compared with those in the lowest fifth (0.87, 0.80 to 0.96; P=0.005, I=0.0%). Plant derived α linolenic acid levels were not associated with incident CKD (1.00, 0.94 to 1.06; P=0.94, I=5.8%). Similar results were obtained in the sensitivity analysis. The association appeared consistent across subgroups by age (≥60 <60 years), estimated glomerular filtration rate (60-89 ≥90 mL/min/1.73 m), hypertension, diabetes, and coronary heart disease at baseline. CONCLUSIONS: Higher seafood derived n-3 PUFA levels were associated with lower risk of incident CKD, although this association was not found for plant derived n-3 PUFAs. These results support a favourable role for seafood derived n-3 PUFAs in preventing CKD.
Keywords: alpha-Linolenic Acid; Fatty Acids, Omega-3; Fatty Acids, Unsaturated; Humans; Middle Aged; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Boerwinkle, Eric; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.

The associations of markers of endothelial dysfunction with hip fracture risk. - Barzilay, Joshua I; Bůzková, Petra; Fink, Howard A; Cauley, Jane A; Carbone, Laura; Elam, Rachel; Robbins, John A; Stein, Phyllis; Sheets, Kerry; Jalal, Diana; Mukamal, Kenneth J (Arch Osteoporos, 2023)
UNLABELLED: Endothelial dysfunction underlies the development of atherosclerotic vascular disease, which in turn is associated with osteoporotic fractures. Here, we examined the association of two markers of endothelial dysfunction with incident hip fracture risk in older adults but found no statistically significant associations between them. PURPOSE/INTRODUCTION: Endothelial dysfunction underlies the development of atherosclerotic vascular disease. Vascular disease, in turn, is associated with the risk of osteoporotic fractures, such as hip fractures. Here, we examine whether two measures of endothelial dysfunction are related to hip fracture risk. METHODS: Participants for this study were 2792 individuals (mean age 78.6 years) who had flow-mediated dilation (FMD) measured after ischemia in the forearm and 2255 adults (mean age 73.3 years) with measured soluble intercellular adhesion molecule (siCAM) levels, a constitutive endothelial cell membrane protein associated with the initiation of atherosclerosis. Mean follow-up was 9.7 and 11.7 years, respectively. There were 375 and 265 incident hip fractures, respectively, in each group. RESULTS: In Cox proportional hazards models, there was no significant association between FMD response and incident hip fracture (HR per 1% higher FMD was 0.98 [0.93, 1.04]; p = 0.44). In exploratory analyses, when data were examined dichotomously, participants in the lowest 80% of FMD (≤ 4.5%) had an adjusted 1.29 (0.98, 1.68; p = 0.067) higher hazard of hip fracture compared to participants in the upper 20% of FMD change. There were no significant associations between siCAM and incident hip fracture whether examined as a continuous or dichotomized variable. CONCLUSIONS: Among older adults, two measures of endothelial dysfunction were not significantly associated with hip fracture risk. There was a trend for higher fracture risk with lower FMD.
Keywords: Aged; Forearm; Hip Fractures; Humans; Osteoporotic Fractures; Vascular Diseases

Carriers of rare damaging genetic variants are at lower risk of atherosclerotic disease. - Georgakis, Marios K; Malik, Rainer; Hasbani, Natalie R; Shakt, Gabrielle; Morrison, Alanna C; Tsao, Noah L; Judy, Renae; Mitchell, Braxton D; Xu, Huichun; Montasser, May E; Do, Ron; Kenny, Eimear E; et al. (medRxiv, 2023)
BACKGROUND: The CCL2/CCR2 axis governs monocyte trafficking and recruitment to atherosclerotic lesions. Human genetic analyses and population-based studies support an association between circulating CCL2 levels and atherosclerosis. Still, it remains unknown whether pharmacological targeting of CCR2, the main CCL2 receptor, would provide protection against human atherosclerotic disease. METHODS: In whole-exome sequencing data from 454,775 UK Biobank participants (40-69 years), we identified predicted loss-of-function (LoF) or damaging missense (REVEL score >0.5) variants within the gene. We prioritized variants associated with lower monocyte count (p<0.05) and tested associations with vascular risk factors and risk of atherosclerotic disease over a mean follow-up of 14 years. The results were replicated in a pooled cohort of three independent datasets (TOPMed, deCODE and Penn Medicine BioBank; total n=441,445) and the effect of the most frequent damaging variant was experimentally validated. RESULTS: A total of 45 predicted LoF or damaging missense variants were identified in the gene, 4 of which were also significantly associated with lower monocyte count, but not with other white blood cell counts. Heterozygous carriers of these variants were at a lower risk of a combined atherosclerosis outcome, showed a lower burden of atherosclerosis across four vascular beds, and were at a lower lifetime risk of coronary artery disease and myocardial infarction. There was no evidence of association with vascular risk factors including LDL-cholesterol, blood pressure, glycemic status, or C-reactive protein. Using a cAMP assay, we found that cells transfected with the most frequent damaging variant (3:46358273:T:A, M249K, 547 carriers, frequency: 0.14%) show a decrease in signaling in response to CCL2. The associations of the M249K variant with myocardial infarction were consistent across cohorts (OR : 0.62 95%CI: 0.39-0.96; OR : 0.64 95%CI: 0.34-1.19; OR : 0.64 95%CI: 0.45-0.90). In a phenome-wide association study, we found no evidence for higher risk of common infections or mortality among carriers of damaging variants. CONCLUSIONS: Heterozygous carriers of damaging variants have a lower burden of atherosclerosis and lower lifetime risk of myocardial infarction. In conjunction with previous evidence from experimental and epidemiological studies, our findings highlight the translational potential of CCR2-targeting as an atheroprotective approach.

Clonal hematopoiesis is associated with protection from Alzheimer's disease. - Bouzid, Hind; Belk, Julia A; Jan, Max; Qi, Yanyan; Sarnowski, Chloe; Wirth, Sara; Ma, Lisa; Chrostek, Matthew R; Ahmad, Herra; Nachun, Daniel; Yao, Winnie; Beiser, Alexa; et al. (Nat Med, 2023)
Clonal hematopoiesis of indeterminate potential (CHIP) is a premalignant expansion of mutated hematopoietic stem cells. As CHIP-associated mutations are known to alter the development and function of myeloid cells, we hypothesized that CHIP may also be associated with the risk of Alzheimer's disease (AD), a disease in which brain-resident myeloid cells are thought to have a major role. To perform association tests between CHIP and AD dementia, we analyzed blood DNA sequencing data from 1,362 individuals with AD and 4,368 individuals without AD. Individuals with CHIP had a lower risk of AD dementia (meta-analysis odds ratio (OR) = 0.64, P = 3.8 × 10), and Mendelian randomization analyses supported a potential causal association. We observed that the same mutations found in blood were also detected in microglia-enriched fraction of the brain in seven of eight CHIP carriers. Single-nucleus chromatin accessibility profiling of brain-derived nuclei in six CHIP carriers revealed that the mutated cells comprised a large proportion of the microglial pool in the samples examined. While additional studies are required to validate the mechanistic findings, these results suggest that CHIP may have a role in attenuating the risk of AD.

Clonal Hematopoiesis of Indeterminate Potential is Associated with Acute Kidney Injury. - Vlasschaert, Caitlyn; Robinson-Cohen, Cassianne; Kestenbaum, Bryan; Silver, Samuel A; Chen, Jian-Chun; Akwo, Elvis; Bhatraju, Pavan K; Zhang, Ming-Zhi; Cao, Shirong; Jiang, Ming; Wang, Yinqiu; Niu, Aolei; et al. (medRxiv, 2023)
Age is a predominant risk factor for acute kidney injury (AKI), yet the biological mechanisms underlying this risk are largely unknown and to date no genetic mechanisms for AKI have been established. Clonal hematopoiesis of indeterminate potential (CHIP) is a recently recognized biological mechanism conferring risk of several chronic aging diseases including cardiovascular disease, pulmonary disease and liver disease. In CHIP, blood stem cells acquire mutations in myeloid cancer driver genes such as and and the myeloid progeny of these mutated cells contribute to end-organ damage through inflammatory dysregulation. We sought to establish whether CHIP causes acute kidney injury (AKI). To address this question, we first evaluated associations with incident AKI events in three population-based epidemiology cohorts (N = 442,153). We found that CHIP was associated with a greater risk of AKI (adjusted HR 1.26, 95% CI: 1.19-1.34, p<0.0001), which was more pronounced in patients with AKI requiring dialysis (adjusted HR 1.65, 95% CI: 1.24-2.20, p=0.001). The risk was particularly high in the subset of individuals where CHIP was driven by mutations in genes other than (HR: 1.49, 95% CI: 1.37-1.61, p<0.0001). We then examined the association between CHIP and recovery from AKI in the ASSESS-AKI cohort and identified that non- CHIP was more common among those with a non-resolving pattern of injury (HR 2.3, 95% CI: 1.14-4.64, p = 0.03). To gain mechanistic insight, we evaluated the role of -CHIP to AKI in ischemia-reperfusion injury (IRI) and unilateral ureteral obstruction (UUO) mouse models. In both models, we observed more severe AKI and greater post-AKI kidney fibrosis in -CHIP mice. Kidney macrophage infiltration was markedly increased in -CHIP mice and -CHIP mutant renal macrophages displayed greater pro-inflammatory responses. In summary, this work establishes CHIP as a genetic mechanism conferring risk of AKI and impaired kidney function recovery following AKI via an aberrant inflammatory response in CHIP derived renal macrophages.

Complexities of cerebral small vessel disease, blood pressure, and dementia relationship: new insights from genetics. - Sargurupremraj, Muralidharan; Soumaré, Aïcha; Bis, Joshua C; Surakka, Ida; Jürgenson, Tuuli; Joly, Pierre; Knol, Maria J; Wang, Ruiqi; Yang, Qiong; Satizabal, Claudia L; Gudjonsson, Alexander; Mishra, Aniket; et al. (medRxiv, 2023)
IMPORTANCE: There is increasing recognition that vascular disease, which can be treated, is a key contributor to dementia risk. However, the contribution of specific markers of vascular disease is unclear and, as a consequence, optimal prevention strategies remain unclear. OBJECTIVE: To disentangle the causal relation of several key vascular traits to dementia risk: (i) white matter hyperintensity (WMH) burden, a highly prevalent imaging marker of covert cerebral small vessel disease (cSVD); (ii) clinical stroke; and (iii) blood pressure (BP), the leading risk factor for cSVD and stroke, for which efficient therapies exist. To account for potential epidemiological biases inherent to late-onset conditions like dementia. DESIGN SETTING AND PARTICIPANTS: This study first explored the association of genetically determined WMH, BP levels and stroke risk with AD using summary-level data from large genome-wide association studies (GWASs) in a two-sample Mendelian randomization (MR) framework. Second, leveraging individual-level data from large longitudinal population-based cohorts and biobanks with prospective dementia surveillance, the association of weighted genetic risk scores (wGRSs) for WMH, BP, and stroke with incident all-cause-dementia was explored using Cox-proportional hazard and multi-state models. The data analysis was performed from July 26, 2020, through July 24, 2022. EXPOSURES: Genetically determined levels of WMH volume and BP (systolic, diastolic and pulse blood pressures) and genetic liability to stroke. MAIN OUTCOMES AND MEASURES: The summary-level MR analyses focused on the outcomes from GWAS of clinically diagnosed AD (n-cases=21,982) and GWAS additionally including self-reported parental history of dementia as a proxy for AD diagnosis (AD , n-cases=53,042). For the longitudinal analyses, individual-level data of 157,698 participants with 10,699 incident all-cause-dementia were studied, exploring AD, vascular or mixed dementia in secondary analyses. RESULTS: In the two-sample MR analyses, WMH showed strong evidence for a causal association with increased risk of AD (OR, 1.16; 95%CI:1.05-1.28; P=.003) and AD (OR, 1.28; 95%CI:1.07-1.53; P=.008), after accounting for genetically determined pulse pressure for the latter. Genetically predicted BP traits showed evidence for a protective association with both clinically defined AD and AD , with evidence for confounding by shared genetic instruments. In longitudinal analyses the wGRSs for WMH, but not BP or stroke, showed suggestive association with incident all-cause-dementia (HR, 1.02; 95%CI:1.00-1.04; P=.06). BP and stroke wGRSs were strongly associated with mortality but there was no evidence for selective survival bias during follow-up. In secondary analyses, polygenic scores with more liberal instrument definition showed association of both WMH and stroke with all-cause-dementia, AD, and vascular or mixed dementia; associations of stroke, but not WMH, with dementia outcomes were markedly attenuated after adjusting for interim stroke. CONCLUSION: These findings provide converging evidence that WMH is a leading vascular contributor to dementia risk, which may better capture the brain damage caused by BP (and other etiologies) than BP itself and should be targeted in priority for dementia prevention in the population. KEY POINTS: Do instrumental variable analyses leveraging genetic information provide evidence for a causal association of various vascular traits with Alzheimer's disease (AD) and all-cause-dementia? How do these associations compare for white matter hyperintensity (WMH) burden, a highly prevalent marker of covert cerebral small vessel disease (cSVD), stroke, and blood pressure traits, the strongest known risk factor for cSVD and stroke? Using Mendelian randomization (MR) leveraging large, published genome-wide association studies, this study showed a putative causal association of larger WMH burden with increased AD risk after accounting for pulse pressure effects, and some evidence for association of lower BP with AD risk with possible confounding by shared genetic instruments. Longitudinal analyses on individual-level data also supported association of genetically determined WMH with incident all-cause-dementia and AD, independently of interim stroke. This study using complementary genetic epidemiology approaches, identified increasing WMH burden to be associated with dementia and AD risk, suggesting the association as specific for cSVD and independent of BP and stroke.

Determinants of mosaic chromosomal alteration fitness. - Pershad, Yash; Mack, Taralynn; Poisner, Hannah; Jakubek, Yasminka A; Stilp, Adrienne M; Mitchell, Braxton D; Lewis, Joshua P; Boerwinkle, Eric; Loos, Ruth J; Chami, Nathalie; Wang, Zhe; Barnes, Kathleen; et al. (medRxiv, 2023)
Clonal hematopoiesis (CH) is characterized by the acquisition of a somatic mutation in a hematopoietic stem cell that results in a clonal expansion. These driver mutations can be single nucleotide variants in cancer driver genes or larger structural rearrangements called mosaic chromosomal alterations (mCAs). The factors that influence the variations in mCA fitness and ultimately result in different clonal expansion rates are not well-understood. We used the Passenger-Approximated Clonal Expansion Rate (PACER) method to estimate clonal expansion rate for 6,381 individuals in the NHLBI TOPMed cohort with gain, loss, and copy-neutral loss of heterozygosity mCAs. Our estimates of mCA fitness were correlated (R = 0.49) with an alternative approach that estimated fitness of mCAs in the UK Biobank using a theoretical probability distribution. Individuals with lymphoid-associated mCAs had a significantly higher white blood cell count and faster clonal expansion rate. In a cross-sectional analysis, genome-wide association study of estimates of mCA expansion rate identified , , and locus variants as modulators of mCA clonal expansion rate.

{Early-onset Alzheimer's disease explained by polygenic risk of late-onset disease? - Mantyh, W. G.; Cochran, J. N.; Taylor, J. W.; Broce, I. J.; Geier, E. G.; Bonham, L. W.; Anderson, A. G.; Sirkis, D. W.; Joie, R.; Iaccarino, L.; Chaudhary, K.; Edwards, L.; et al. (Alzheimers Dement (Amst), 2023)
There is a unique genetic architecture of early- versus late-onset Alzheimer's disease (AD).Late-onset AD polygenic risk is not an explanation for early-onset AD.Polygenic risk of late-onset AD does not predict early-onset AD biology.Unique genetic architecture of early- versus late-onset AD parallels AD heterogeneity.

Effect of 2022 ACC/AHA/HFSA Criteria on Stages of Heart Failure in a Pooled Community Cohort. - Mohebi, Reza; Wang, Dongyu; Lau, Emily S; Parekh, Juhi K; Allen, Norrina; Psaty, Bruce M; Benjamin, Emelia J; Levy, Daniel; Wang, Thomas J; Shah, Sanjiv J; Gottdiener, John S; Januzzi, James L; et al. (J Am Coll Cardiol, 2023)
BACKGROUND: The 2022 American College of Cardiology (ACC)/American Heart Association (AHA)/Heart Failure Society of America (HFSA) clinical practice guideline proposed an updated definition for heart failure (HF) stages. OBJECTIVES: This study aimed to compare prevalence and prognosis of HF stages according to classification/definition originally described in 2013 and 2022 ACC/AHA/HFSA definitions. METHODS: Study participants from 3 longitudinal cohorts (the MESA [Multi-Ethnic Study of Atherosclerosis], CHS [Cardiovascular Health Study], and the FHS [Framingham Heart Study]), were categorized into 4 HF stages according to the 2013 and 2022 criteria. Cox proportional hazards regression was used to assess predictors of progression to symptomatic HF and adverse clinical outcomes associated with each HF stage. RESULTS: Among 11,618 study participants, according to the 2022 staging, 1,943 (16.7%) were healthy, 4,348 (37.4%) were in stage A (at risk), 5,019 (43.2%) were in stage B (pre-HF), and 308 (2.7%) were in stage C/D (symptomatic HF). Compared to the classification/definition originally described in 2013, the 2022 ACC/AHA/HFSA approach resulted in a higher proportion of individuals with stage B HF (increase from 15.9% to 43.2%); this shift disproportionately involved women as well as Hispanic and Black individuals. Despite the 2022 criteria designating a greater proportion of individuals as stage B, the relative risk of progression to symptomatic HF remained similar (HR: 10.61; 95% CI: 9.00-12.51; P < 0.001). CONCLUSIONS: New standards for HF staging resulted in a substantial shift of community-based individuals from stage A to stage B. Those with stage B HF in the new system were at high risk for progression to symptomatic HF.
Keywords: American Heart Association; Atherosclerosis; Cardiology; Female; Heart Failure; Humans; Longitudinal Studies; Prognosis; United States

Elevated Plasma Levels of Ketone Bodies Are Associated With All-Cause Mortality and Incidence of Heart Failure in Older Adults: The CHS. - Niezen, Sebastian; Connelly, Margery A; Hirsch, Calvin; Kizer, Jorge R; Benitez, Maria E; Minchenberg, Scott; Perez-Matos, Maria Camila; Jiang, Zhenghui Gordon; Mukamal, Kenneth J (J Am Heart Assoc, 2023)
Background Chronic disease, such as heart failure, influences cellular metabolism and shapes circulating metabolites. The relationships between key energy metabolites and chronic diseases in aging are not well understood. This study aims to determine the relationship between main components of energy metabolism with all-cause mortality and incident heart failure. Methods and Results We analyzed the association between plasma metabolite levels with all-cause mortality and incident heart failure among US older adults in the CHS (Cardiovascular Health Study). We followed 1758 participants without heart failure at baseline with hazard ratios (HRs) of analyte levels and metabolic profiles characterized by high levels of ketone bodies for all-cause mortality and incident heart failure. Multivariable Cox analyses revealed a dose-response relationship of 50% increase in all-cause mortality between lowest and highest quintiles of ketone body concentrations (HR, 1.5 [95% CI, 1.0-1.9]; =0.007). Ketone body levels remained associated with incident heart failure after adjusting for cardiovascular disease confounders (HR, 1.2 [95% CI, 1.0-1.3]; =0.02). Using K-means cluster analysis, we identified a cluster with higher levels of ketone bodies, citrate, interleukin-6, and B-type natriuretic peptide but lower levels of pyruvate, body mass index, and estimated glomerular filtration rate. The cluster with elevated ketone body levels was associated with higher all-cause mortality (HR, 1.7 [95% CI, 1.1-2.7]; =0.01). Conclusions Higher concentrations of ketone bodies predict incident heart failure and all-cause mortality in an older US population, independent of metabolic and cardiovascular confounders. This association suggests a potentially important relationship between ketone body metabolism and aging.
Keywords: Aged; Aging; Cardiovascular Diseases; Heart Failure; Humans; Incidence; Ketone Bodies

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease. - Young, William J; Haessler, Jeffrey; Benjamins, Jan-Walter; Repetto, Linda; Yao, Jie; Isaacs, Aaron; Harper, Andrew R; Ramirez, Julia; Garnier, Sophie; Van Duijvenboden, Stefan; Baldassari, Antoine R; Concas, Maria Pina; et al. (Nat Commun, 2023)
The 3-dimensional spatial and 2-dimensional frontal QRS-T angles are measures derived from the vectorcardiogram. They are independent risk predictors for arrhythmia, but the underlying biology is unknown. Using multi-ancestry genome-wide association studies we identify 61 (58 previously unreported) loci for the spatial QRS-T angle (N = 118,780) and 11 for the frontal QRS-T angle (N = 159,715). Seven out of the 61 spatial QRS-T angle loci have not been reported for other electrocardiographic measures. Enrichments are observed in pathways related to cardiac and vascular development, muscle contraction, and hypertrophy. Pairwise genome-wide association studies with classical ECG traits identify shared genetic influences with PR interval and QRS duration. Phenome-wide scanning indicate associations with atrial fibrillation, atrioventricular block and arterial embolism and genetically determined QRS-T angle measures are associated with fascicular and bundle branch block (and also atrioventricular block for the frontal QRS-T angle). We identify potential biology involved in the QRS-T angle and their genetic relationships with cardiovascular traits and diseases, may inform future research and risk prediction.
Keywords: Arrhythmias, Cardiac; Atrioventricular Block; Biomarkers; Cardiovascular Diseases; Electrocardiography; Genome-Wide Association Study; Humans; Risk Factors

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Boerwinkle, Eric; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Gibbs, Richard; Hersh, Craig P; et al. (bioRxiv, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-seq data in GTEx v8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased WGS data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Boerwinkle, Eric; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

{Identification of circulating proteins associated with general cognitive function among middle-aged and older adults - Tin, A.; Fohner, A. E.; Yang, Q.; Brody, J. A.; Davies, G.; Yao, J.; Liu, D.; Caro, I.; Lindbohm, J. V.; Duggan, M. R.; Meirelles, O.; Harris, S. E.; et al. (Commun Biol, 2023)
2.0E-4). Proteins implicated as causes or consequences of AD susceptibility may provide new insight into the potential relationship between immunity and AD susceptibility as well as potential therapeutic targets.

Large-scale exome array summary statistics resources for glycemic traits to aid effector gene prioritization. - Willems, Sara M; Ng, Natasha H J; Fernandez, Juan; Fine, Rebecca S; Wheeler, Eleanor; Wessel, Jennifer; Kitajima, Hidetoshi; Marenne, Gaelle; Sim, Xueling; Yaghootkar, Hanieh; Wang, Shuai; Chen, Sai; et al. (Wellcome Open Res, 2023)
BACKGROUND: Genome-wide association studies for glycemic traits have identified hundreds of loci associated with these biomarkers of glucose homeostasis. Despite this success, the challenge remains to link variant associations to genes, and underlying biological pathways. METHODS: To identify coding variant associations which may pinpoint effector genes at both novel and previously established genome-wide association loci, we performed meta-analyses of exome-array studies for four glycemic traits: glycated hemoglobin (HbA1c, up to 144,060 participants), fasting glucose (FG, up to 129,665 participants), fasting insulin (FI, up to 104,140) and 2hr glucose post-oral glucose challenge (2hGlu, up to 57,878). In addition, we performed network and pathway analyses. RESULTS: Single-variant and gene-based association analyses identified coding variant associations at more than 60 genes, which when combined with other datasets may be useful to nominate effector genes. Network and pathway analyses identified pathways related to insulin secretion, zinc transport and fatty acid metabolism. HbA1c associations were strongly enriched in pathways related to blood cell biology. CONCLUSIONS: Our results provided novel glycemic trait associations and highlighted pathways implicated in glycemic regulation. Exome-array summary statistic results are being made available to the scientific community to enable further discoveries.

loss-of-function variants: Compatible with longevity and associated with resistance to Alzheimer's Disease pathology - Chemparathy, A.; Guen, Y. L.; Chen, S.; Lee, E. G.; Leong, L.; Gorzynski, J.; Xu, G.; Belloy, M.; Kasireddy, N.; Tauber, A. P.; Williams, K.; Stewart, I.; et al. (medRxiv, 2023)
4 or its protein product as a viable therapeutic option.

Machine learning models for blood pressure phenotypes combining multiple polygenic risk scores. - Hrytsenko, Yana; Shea, Benjamin; Elgart, Michael; Kurniansyah, Nuzulul; Lyons, Genevieve; Morrison, Alanna C; Carson, April P; Haring, Bernhard; Mitchel, Braxton D; Psaty, Bruce M; Jaeger, Byron C; Gu, C Charles; et al. (medRxiv, 2023)
We construct non-linear machine learning (ML) prediction models for systolic and diastolic blood pressure (SBP, DBP) using demographic and clinical variables and polygenic risk scores (PRSs). We developed a two-model ensemble, consisting of a baseline model, where prediction is based on demographic and clinical variables only, and a genetic model, where we also include PRSs. We evaluate the use of a linear versus a non-linear model at both the baseline and the genetic model levels and assess the improvement in performance when incorporating multiple PRSs. We report the ensemble model's performance as percentage variance explained (PVE) on a held-out test dataset. A non-linear baseline model improved the PVEs from 28.1% to 30.1% (SBP) and 14.3% to 17.4% (DBP) compared with a linear baseline model. Including seven PRSs in the genetic model computed based on the largest available GWAS of SBP/DBP improved the genetic model PVE from 4.8% to 5.1% (SBP) and 4.7% to 5% (DBP) compared to using a single PRS. Adding additional 14 PRSs computed based on two independent GWASs further increased the genetic model PVE to 6.3% (SBP) and 5.7% (DBP). PVE differed across self-reported race/ethnicity groups, with primarily all non-White groups benefitting from the inclusion of additional PRSs.

Mosaic chromosomal alterations in blood across ancestries using whole-genome sequencing. - Jakubek, Yasminka A; Zhou, Ying; Stilp, Adrienne; Bacon, Jason; Wong, Justin W; Ozcan, Zuhal; Arnett, Donna; Barnes, Kathleen; Bis, Joshua C; Boerwinkle, Eric; Brody, Jennifer A; Carson, April P; et al. (Nat Genet, 2023)
Megabase-scale mosaic chromosomal alterations (mCAs) in blood are prognostic markers for a host of human diseases. Here, to gain a better understanding of mCA rates in genetically diverse populations, we analyzed whole-genome sequencing data from 67,390 individuals from the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine program. We observed higher sensitivity with whole-genome sequencing data, compared with array-based data, in uncovering mCAs at low mutant cell fractions and found that individuals of European ancestry have the highest rates of autosomal mCAs and the lowest rates of chromosome X mCAs, compared with individuals of African or Hispanic ancestry. Although further studies in diverse populations will be needed to replicate our findings, we report three loci associated with loss of chromosome X, associations between autosomal mCAs and rare variants in DCPS, ADM17, PPP1R16B and TET2 and ancestry-specific variants in ATM and MPL with mCAs in cis.
Keywords: Black People; Genome, Human; Genome-Wide Association Study; Hispanic or Latino; Humans; Mosaicism; Precision Medicine

Multi-ancestry genome-wide study identifies effector genes and druggable pathways for coronary artery calcification. - Kavousi, Maryam; Bos, Maxime M; Barnes, Hanna J; Lino Cardenas, Christian L; Wong, Doris; Lu, Haojie; Hodonsky, Chani J; Landsmeer, Lennart P L; Turner, Adam W; Kho, Minjung; Hasbani, Natalie R; de Vries, Paul S; et al. (Nat Genet, 2023)
Coronary artery calcification (CAC), a measure of subclinical atherosclerosis, predicts future symptomatic coronary artery disease (CAD). Identifying genetic risk factors for CAC may point to new therapeutic avenues for prevention. Currently, there are only four known risk loci for CAC identified from genome-wide association studies (GWAS) in the general population. Here we conducted the largest multi-ancestry GWAS meta-analysis of CAC to date, which comprised 26,909 individuals of European ancestry and 8,867 individuals of African ancestry. We identified 11 independent risk loci, of which eight were new for CAC and five had not been reported for CAD. These new CAC loci are related to bone mineralization, phosphate catabolism and hormone metabolic pathways. Several new loci harbor candidate causal genes supported by multiple lines of functional evidence and are regulators of smooth muscle cell-mediated calcification ex vivo and in vitro. Together, these findings help refine the genetic architecture of CAC and extend our understanding of the biological and potential druggable pathways underlying CAC.

Multi-ancestry genome-wide study in >2.5 million individuals reveals heterogeneity in mechanistic pathways of type 2 diabetes and complications. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Rayner, Nigel W; Bocher, Ozvan; Ana Luiza de, S V Arruda; Sonehara, Kyuto; et al. (medRxiv, 2023)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes. To characterise the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study (GWAS) data from 2,535,601 individuals (39.7% non-European ancestry), including 428,452 T2D cases. We identify 1,289 independent association signals at genome-wide significance (P<5×10 ) that map to 611 loci, of which 145 loci are previously unreported. We define eight non-overlapping clusters of T2D signals characterised by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial, and enteroendocrine cells. We build cluster-specific partitioned genetic risk scores (GRS) in an additional 137,559 individuals of diverse ancestry, including 10,159 T2D cases, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned GRS are more strongly associated with coronary artery disease and end-stage diabetic nephropathy than an overall T2D GRS across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings demonstrate the value of integrating multi-ancestry GWAS with single-cell epigenomics to disentangle the aetiological heterogeneity driving the development and progression of T2D, which may offer a route to optimise global access to genetically-informed diabetes care.

Multi-ancestry transcriptome-wide association analyses yield insights into tobacco use biology and drug repurposing. - Chen, Fang; Wang, Xingyan; Jang, Seon-Kyeong; Quach, Bryan C; Weissenkampen, J Dylan; Khunsriraksakul, Chachrit; Yang, Lina; Sauteraud, Renan; Albert, Christine M; Allred, Nicholette D D; Arnett, Donna K; Ashley-Koch, Allison E; et al. (Nat Genet, 2023)
Most transcriptome-wide association studies (TWASs) so far focus on European ancestry and lack diversity. To overcome this limitation, we aggregated genome-wide association study (GWAS) summary statistics, whole-genome sequences and expression quantitative trait locus (eQTL) data from diverse ancestries. We developed a new approach, TESLA (multi-ancestry integrative study using an optimal linear combination of association statistics), to integrate an eQTL dataset with a multi-ancestry GWAS. By exploiting shared phenotypic effects between ancestries and accommodating potential effect heterogeneities, TESLA improves power over other TWAS methods. When applied to tobacco use phenotypes, TESLA identified 273 new genes, up to 55% more compared with alternative TWAS methods. These hits and subsequent fine mapping using TESLA point to target genes with biological relevance. In silico drug-repurposing analyses highlight several drugs with known efficacy, including dextromethorphan and galantamine, and new drugs such as muscle relaxants that may be repurposed for treating nicotine addiction.
Keywords: Biology; Drug Repositioning; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Tobacco Use; Transcriptome

Plasma Ceramides and Sphingomyelins and Sudden Cardiac Death in the Cardiovascular Health Study. - Bockus, Lee B; Jensen, Paul N; Fretts, Amanda M; Hoofnagle, Andrew N; McKnight, Barbara; Sitlani, Colleen M; Siscovick, David S; King, Irena B; Psaty, Bruce M; Sotoodehnia, Nona; Lemaitre, Rozenn N (JAMA Netw Open, 2023)
IMPORTANCE: Sphingolipids, including ceramides and sphingomyelins, may influence the pathophysiology and risk of sudden cardiac death (SCD) through multiple biological activities. Whether the length of the fatty acid acylated to plasma sphingolipid species is associated with SCD risk is not known. OBJECTIVE: To determine whether the saturated fatty acid length of plasma ceramides and sphingomyelins influences the association with SCD risk. DESIGN, SETTING, AND PARTICIPANTS: In this cohort study, multivariable Cox proportional hazards regression models were used to examine the association of sphingolipid species with SCD risk. The study population included 4612 participants in the Cardiovascular Health Study followed up prospectively for a median of 10.2 (IQR, 5.5-11.6) years. Baseline data were collected from January 1992 to December 1995 during annual examinations. Data were analyzed from February 11, 2020, to September 9, 2023. EXPOSURES: Eight plasma sphingolipid species (4 ceramides and 4 sphingomyelins) with saturated fatty acids of 16, 20, 22, and 24 carbons. MAIN OUTCOME AND MEASURE: Association of plasma ceramides and sphingomyelins with saturated fatty acids of different lengths with SCD risk. RESULTS: Among the 4612 CHS participants included in the analysis (mean [SD] age, 77 [5] years; 2724 [59.1%] women; 6 [0.1%] American Indian; 4 [0.1%] Asian; 718 [15.6%] Black; 3869 [83.9%] White, and 15 [0.3%] Other), 215 SCD cases were identified. In adjusted Cox proportional hazards regression analyses, plasma ceramides and sphingomyelins with palmitic acid (Cer-16 and SM-16) were associated with higher SCD risk per higher SD of log sphingolipid levels (hazard ratio [HR] for Cer-16, 1.34 [95% CI, 1.12-1.59]; HR for SM-16, 1.37 [95% CI, 1.12-1.67]). Associations did not differ by baseline age, sex, race, or body mass index. No significant association of SCD with sphingolipids with very-long-chain saturated fatty acids was observed after correction for multiple testing (HR for ceramide with arachidic acid, 1.06 [95% CI, 0.90-1.24]; HR for ceramide with behenic acid, 0.92 [95% CI, 0.77-1.10]; HR for ceramide with lignoceric acid, 0.92 [95% CI, 0.77-1.09]; HR for sphingomyelin with arachidic acid, 0.83 [95% CI, 0.71-0.98]; HR for sphingomyelin with behenic acid, 0.84 [95% CI, 0.70-1.00]; HR for sphingomyelin with lignoceric acid, 0.86 [95% CI, 0.72-1.03]). CONCLUSIONS AND RELEVANCE: The findings of this large, population-based cohort study of SCD identified that higher plasma levels of Cer-16 and SM-16 were associated with higher risk of SCD. Future studies are needed to examine the underlying mechanism of these associations.
Keywords: Aged; Ceramides; Cohort Studies; Death, Sudden, Cardiac; Eicosanoic Acids; Fatty Acids; Female; Humans; Male; Sphingolipids; Sphingomyelins

Plasma sphingolipids, lung function and COPD: the Cardiovascular Health Study. - Gharib, Arya R; Jensen, Paul N; Psaty, Bruce M; Hoofnagle, Andrew N; Siscovick, David; Gharib, Sina A; Sitlani, Colleen M; Sotoodehnia, Nona; Lemaitre, Rozenn N (ERJ Open Res, 2023)
RATIONALE: COPD is the third leading cause of death in the United States. Sphingolipids, structural membrane constituents that play a role in cellular stress and apoptosis signalling, may be involved in lung function. METHODS: In the Cardiovascular Health Study, a prospective cohort of older adults, we cross-sectionally examined the association of plasma levels of 17 sphingolipid species with lung function and COPD. Multivariable linear regression and logistic regression were used to evaluate associations of sphingolipid concentrations with forced expiratory volume in 1 s (FEV) and odds of COPD, respectively. RESULTS: Of the 17 sphingolipids evaluated, ceramide-18 (Cer-18) and sphingomyelin-18 (SM-18) were associated with lower FEV values (-0.061 L per two-fold higher Cer-18, p=0.001; -0.092 L per two-fold higher SM-18, p=0.002) after correction for multiple testing. Several other associations were significant at a 0.05 level, but did not reach statistical significance after correction for multiple testing. Specifically, Cer-18 and SM-18 were associated with higher odds of COPD (odds ratio per two-fold higher Cer-18 1.29, p=0.03 and SM-18 1.73, p=0.008). Additionally, Cer-16 and SM-16 were associated with lower FEV values, and Cer-14, SM-14 and SM-16 with a higher odds of COPD. CONCLUSION: In this large cross-sectional study, specific ceramides and sphingomyelins were associated with reduced lung function in a population-based study. Future studies are needed to examine whether these biomarkers are associated with longitudinal change in FEV within individuals or with incident COPD.

Plasma Trimethylamine--Oxide and Incident Ischemic Stroke: The Cardiovascular Health Study and the Multi-Ethnic Study of Atherosclerosis. - Lemaitre, Rozenn N; Jensen, Paul N; Wang, Zeneng; Fretts, Amanda M; Sitlani, Colleen M; Nemet, Ina; Sotoodehnia, Nona; de Oliveira Otto, Marcia C; Zhu, Weifei; Budoff, Matt; Longstreth, W T; Psaty, Bruce M; et al. (J Am Heart Assoc, 2023)
Background The association of circulating trimethylamine--oxide (TMAO) with stroke has received limited attention. To address this gap, we examined the associations of serial measures of plasma TMAO with incident ischemic stroke. Methods and Results We used a prospective cohort design with data pooled from 2 cohorts. The settings were the CHS (Cardiovascular Health Study), a cohort of older adults, and the MESA (Multi-Ethnic Study of Atherosclerosis), both in the United States. We measured plasma concentrations of TMAO at baseline and again during the follow-up using high-performance liquid chromatography and mass spectrometry. We assessed the association of plasma TMAO with incident ischemic stroke using proportional hazards regression adjusted for risk factors. The combined cohorts included 11 785 participants without a history of stroke, on average 73 (CHS) and 62 (MESA) years old at baseline, including 60% (CHS) and 53% (MESA) women. We identified 1031 total incident ischemic strokes during a median 15-year follow-up in the combined cohorts. In multivariable analyses, TMAO was significantly associated with incident ischemic stroke risk (hazard ratios comparing a doubling of TMAO: 1.11 [1.03-1.18], =0.004). The association was linear over the range of TMAO concentrations and appeared restricted to those without diagnosed coronary heart disease. An association with hemorrhagic stroke was not found. Conclusions Plasma TMAO levels are associated with incident ischemic stroke in a diverse population. Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT00005133.
Keywords: Aged; Atherosclerosis; Female; Humans; Ischemic Stroke; Methylamines; Oxides; Prospective Studies; Risk Factors; Stroke; United States

A proteomic analysis of atrial fibrillation in a prospective longitudinal cohort (AGES-Reykjavik study). - Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Austin, Thomas R; Frick, Elisabet A; Axelsson, Gisli T; Launer, Lenore; Psaty, Bruce M; Loureiro, Joseph; Orth, Anthony P; Aspelund, Thor; Emilsson, Valur; Floyd, James S; et al. (Europace, 2023)
AIMS: Atrial fibrillation (AF) is associated with high risk of comorbidities and mortality. Our aim was to examine causal and predictive relationships between 4137 serum proteins and incident AF in the prospective population-based Age, Gene/Environment Susceptibility-Reykjavik (AGES-Reykjavik) study. METHODS AND RESULTS: The study included 4765 participants, of whom 1172 developed AF. Cox proportional hazards regression models were fitted for 4137 baseline protein measurements adjusting for known risk factors. Protein associations were tested for replication in the Cardiovascular Health Study (CHS). Causal relationships were examined in a bidirectional, two-sample Mendelian randomization analysis. The time-dependent area under the receiver operating characteristic curve (AUC)-statistic was examined as protein levels and an AF-polygenic risk score (PRS) were added to clinical risk models. The proteomic signature of incident AF consisted of 76 proteins, of which 63 (83%) were novel and 29 (38%) were replicated in CHS. The signature included both N-terminal prohormone of brain natriuretic peptide (NT-proBNP)-dependent (e.g. CHST15, ATP1B1, and SVEP1) and independent components (e.g. ASPN, AKR1B, and LAMA1/LAMB1/LAMC1). Nine causal candidates were identified (TAGLN, WARS, CHST15, CHMP3, COL15A1, DUSP13, MANBA, QSOX2, and SRL). The reverse causal analysis suggested that most AF-associated proteins were affected by the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide improved the prediction of incident AF events close to baseline with further improvements gained by the AF-PRS at all time points. CONCLUSION: The AF proteomic signature includes biologically relevant proteins, some of which may be causal. It mainly reflects an NT-proBNP-dependent consequence of the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide is a promising marker for incident AF in the short term, but risk assessment incorporating a PRS may improve long-term risk assessment.
Keywords: Atrial Fibrillation; Biomarkers; Endosomal Sorting Complexes Required for Transport; Humans; Natriuretic Peptide, Brain; Oxidoreductases Acting on Sulfur Group Donors; Peptide Fragments; Prognosis; Prospective Studies; Proteomics; Risk Factors

Proteomic prediction of incident heart failure and its main subtypes. - Emilsson, Valur; Jonsson, Brynjolfur G; Austin, Thomas R; Gudmundsdottir, Valborg; Axelsson, Gisli T; Frick, Elisabet A; Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Loureiro, Joseph; Brody, Jennifer A; Aspelund, Thor; Launer, Lenore J; et al. (Eur J Heart Fail, 2023)
AIM: To examine the ability of serum proteins in predicting future heart failure (HF) events, including HF with reduced or preserved ejection fraction (HFrEF or HFpEF), in relation to event time, and with or without considering established HF-associated clinical variables. METHODS AND RESULTS: In the prospective population-based Age, Gene/Environment Susceptibility Reykjavik Study (AGES-RS), 440 individuals developed HF after their first visit with a median follow-up of 5.45 years. Among them, 167 were diagnosed with HFrEF and 188 with HFpEF. A least absolute shrinkage and selection operator regression model with nonparametric bootstrap were used to select predictors from an analysis of 4782 serum proteins, and several pre-established clinical parameters linked to HF. A subset of 8-10 distinct or overlapping serum proteins predicted different future HF outcomes, and C-statistics were used to assess discrimination, revealing proteins combined with a C-index of 0.80 for all incident HF, 0.78 and 0.80 for incident HFpEF or HFrEF, respectively. In the AGES-RS, protein panels alone encompassed the risk contained in the clinical information and improved the performance characteristics of prediction models based on NT-proBNP and clinical risk factors. Finally, the protein predictors performed particularly well close to the time of an HF event, an outcome that was replicated in the Cardiovascular Health Study (CHS). CONCLUSION: A small number of circulating proteins accurately predicted future HF in the AGES-RS cohort of older adults, and they alone encompass the risk information found in a collection of clinical data. Incident HF events were predicted up to eight years, with predictor performance significantly improving for events occurring less than one year ahead, a finding replicated in an external cohort study. This article is protected by copyright. All rights reserved.

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Boerwinkle, Eric; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

{Serum NfL and GFAP are associated with incident dementia and dementia mortality in older adults: The cardiovascular health study - é, H. T.; Liu, X.; Odden, M. C.; Moseholm, K. F.; Seshadri, S.; Satizabal, C. L.; Lopez, O. L.; Bis, J. C.; é, L.; Fohner, A. E.; Psaty, B. M.; Tracy, R. P.; et al. (Alzheimers Dement, 2023)
Circulating neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) have been independently associated with dementia risk. Their additive association, and their associations with dementia-specific mortality, have not been investigated.\ We associated serum NfL, GFAP, total tau ,and ubiquitin carboxyl-terminal hydrolase-L1, measured in 1712 dementia-free adults, with 19-year incident dementia and dementia-specific mortality risk, and with 3-year cognitive decline.\ 2.06 (1.60-2.67) and 9.22 (4.48-18.9). NfL was independently associated with accelerated cognitive decline.\ Circulating NfL and GFAP may, independently and jointly, provide useful clinical insight regarding dementia risk and prognosis.

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People with Type 2 Diabetes Mellitus. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (medRxiv, 2023)
BACKGROUND: Type 2 diabetes mellitus (T2D) confers a two- to three-fold increased risk of cardiovascular disease (CVD). However, the mechanisms underlying increased CVD risk among people with T2D are only partially understood. We hypothesized that a genetic association study among people with T2D at risk for developing incident cardiovascular complications could provide insights into molecular genetic aspects underlying CVD. METHODS: From 16 studies of the Cohorts for Heart & Aging Research in Genomic Epidemiology (CHARGE) Consortium, we conducted a multi-ancestry time-to-event genome-wide association study (GWAS) for incident CVD among people with T2D using Cox proportional hazards models. Incident CVD was defined based on a composite of coronary artery disease (CAD), stroke, and cardiovascular death that occurred at least one year after the diagnosis of T2D. Cohort-level estimated effect sizes were combined using inverse variance weighted fixed effects meta-analysis. We also tested 204 known CAD variants for association with incident CVD among patients with T2D. RESULTS: A total of 49,230 participants with T2D were included in the analyses (31,118 European ancestries and 18,112 non-European ancestries) which consisted of 8,956 incident CVD cases over a range of mean follow-up duration between 3.2 and 33.7 years (event rate 18.2%). We identified three novel, distinct genetic loci for incident CVD among individuals with T2D that reached the threshold for genome-wide significance ( <5.0×10 ): rs147138607 (intergenic variant between and ) with a hazard ratio (HR) 1.23, 95% confidence interval (CI) 1.15 - 1.32, =3.6×10 , rs11444867 (intergenic variant near ) with HR 1.89, 95% CI 1.52 - 2.35, =9.9×10 , and rs335407 (intergenic variant between and ) HR 1.25, 95% CI 1.16 - 1.35, =1.5×10 . Among 204 known CAD loci, 32 were associated with incident CVD in people with T2D with <0.05, and 5 were significant after Bonferroni correction ( <0.00024, 0.05/204). A polygenic score of these 204 variants was significantly associated with incident CVD with HR 1.14 (95% CI 1.12 - 1.16) per 1 standard deviation increase ( =1.0×10 ). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D. CLINICAL PERSPECTIVE: We conducted a large-scale multi-ancestry time-to-event GWAS to identify genetic variants associated with CVD among people with T2D. Three variants were significantly associated with incident CVD in people with T2D: rs147138607 (intergenic variant between and ), rs11444867 (intergenic variant near ), and rs335407 (intergenic variant between and ). A polygenic score composed of known CAD variants identified in the general population was significantly associated with the risk of CVD in people with T2D. There are genetic risk factors specific to T2D that could at least partially explain the excess risk of CVD in people with T2D.In addition, we show that people with T2D have enrichment of known CAD association signals which could also explain the excess risk of CVD.

Time-Varying Food Retail and Incident Disease in the Cardiovascular Health Study. - Lovasi, Gina S; Boise, Sarah; Jogi, Siddharth; Hurvitz, Philip M; Rundle, Andrew G; Diez, Julia; Hirsch, Jana A; Fitzpatrick, Annette; Biggs, Mary L; Siscovick, David S (Am J Prev Med, 2023)
INTRODUCTION: Natural experiments can strengthen evidence linking neighborhood food retail presence to dietary intake patterns and cardiometabolic health outcomes, yet sample size and follow-up duration are typically not extensive. To complement natural experiment evidence, longitudinal data were used to estimate the impacts of neighborhood food retail presence on incident disease. METHODS: The Cardiovascular Health Study recruited adults aged 65+ years in 1989-1993. Analyses conducted in 2021-2022 included those in good baseline health, with addresses updated annually through the year of death (restricted to 91% who died during >2 decades of cohort follow-up). Baseline and annually updated presence of 2 combined food retail categories (supermarkets/produce markets and convenience/snack focused) was characterized using establishment-level data for 1-km and 5-km Euclidean buffers. Cox proportional hazards models estimated associations with time to each incident outcome (cardiovascular disease, diabetes), adjusting for individual and area-based confounders. RESULTS: Among 2,939 participants, 36% with baseline supermarket/produce market presence within 1 km had excess incident cardiovascular disease (hazard ratio=1.12; 95% CI=1.01, 1.24); the association was attenuated and no longer statistically significant after adjustment for sociodemographic characteristics. Adjusted associations were robustly null for time-varying supermarket/produce market or convenience/fast food retail presence across analyses with outcomes of cardiovascular disease or diabetes incidence. CONCLUSIONS: Food environment changes continue to be studied to provide an evidence base for policy decisions, and null findings in this longitudinal analysis add literature that casts doubt on the sufficiency of strategies targeting food retail presence alone of an elderly cohort for curtailing incident events of clinical importance.

Type 2 Diabetes Modifies the Association of CAD Genomic Risk Variants With Subclinical Atherosclerosis. - Hasbani, Natalie R; Westerman, Kenneth E; Heon Kwak, Soo; Chen, Han; Li, Xihao; DiCorpo, Daniel; Wessel, Jennifer; Bis, Joshua C; Sarnowski, Chloe; Wu, Peitao; Bielak, Lawrence F; Guo, Xiuqing; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of coronary artery disease (CAD), but questions remain about the underlying pathology. Identifying which CAD loci are modified by T2D in the development of subclinical atherosclerosis (coronary artery calcification [CAC], carotid intima-media thickness, or carotid plaque) may improve our understanding of the mechanisms leading to the increased CAD in T2D. METHODS: We compared the common and rare variant associations of known CAD loci from the literature on CAC, carotid intima-media thickness, and carotid plaque in up to 29 670 participants, including up to 24 157 normoglycemic controls and 5513 T2D cases leveraging whole-genome sequencing data from the Trans-Omics for Precision Medicine program. We included first-order T2D interaction terms in each model to determine whether CAD loci were modified by T2D. The genetic main and interaction effects were assessed using a joint test to determine whether a CAD variant, or gene-based rare variant set, was associated with the respective subclinical atherosclerosis measures and then further determined whether these loci had a significant interaction test. RESULTS: Using a Bonferroni-corrected significance threshold of <1.6×10, we identified 3 genes (, , and ) associated with CAC and 2 genes ( and ) associated with carotid intima-media thickness and carotid plaque, respectively, through gene-based rare variant set analysis. Both and also had significantly different associations for CAC in T2D cases versus controls. No significant interaction tests were identified through the candidate single-variant analysis. CONCLUSIONS: These results highlight T2D as an important modifier of rare variant associations in CAD loci with CAC.

Whole genome analysis of plasma fibrinogen reveals population-differentiated genetic regulators with putative liver roles. - Huffman, Jennifer E; Nicolas, Jayna; Hahn, Julie; Heath, Adam S; Raffield, Laura M; Yanek, Lisa R; Brody, Jennifer A; Thibord, Florian; Almasy, Laura; Bartz, Traci M; Bielak, Lawrence F; Bowler, Russell P; et al. (medRxiv, 2023)
UNLABELLED: Genetic studies have identified numerous regions associated with plasma fibrinogen levels in Europeans, yet missing heritability and limited inclusion of non-Europeans necessitates further studies with improved power and sensitivity. Compared with array-based genotyping, whole genome sequencing (WGS) data provides better coverage of the genome and better representation of non-European variants. To better understand the genetic landscape regulating plasma fibrinogen levels, we meta-analyzed WGS data from the NHLBI's Trans-Omics for Precision Medicine (TOPMed) program (n=32,572), with array-based genotype data from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium (n=131,340) imputed to the TOPMed or Haplotype Reference Consortium panel. We identified 18 loci that have not been identified in prior genetic studies of fibrinogen. Of these, four are driven by common variants of small effect with reported MAF at least 10% higher in African populations. Three ( , and signals contain predicted deleterious missense variants. Two loci, and , each harbor two conditionally distinct, non-coding variants. The gene region encoding the protein chain subunits ( ), contains 7 distinct signals, including one novel signal driven by rs28577061, a variant common (MAF=0.180) in African reference panels but extremely rare (MAF=0.008) in Europeans. Through phenome-wide association studies in the VA Million Veteran Program, we found associations between fibrinogen polygenic risk scores and thrombotic and inflammatory disease phenotypes, including an association with gout. Our findings demonstrate the utility of WGS to augment genetic discovery in diverse populations and offer new insights for putative mechanisms of fibrinogen regulation. KEY POINTS: Largest and most diverse genetic study of plasma fibrinogen identifies 54 regions (18 novel), housing 69 conditionally distinct variants (20 novel).Sufficient power achieved to identify signal driven by African population variant.Links to (1) liver enzyme, blood cell and lipid genetic signals, (2) liver regulatory elements, and (3) thrombotic and inflammatory disease.

Whole Genome Analysis of Venous Thromboembolism: the Trans-Omics for Precision Medicine Program. - Seyerle, Amanda A; Laurie, Cecelia A; Coombes, Brandon J; Jain, Deepti; Conomos, Matthew P; Brody, Jennifer; Chen, Ming-Huei; Gogarten, Stephanie M; Beutel, Kathleen M; Gupta, Namrata; Heckbert, Susan R; Jackson, Rebecca D; et al. (Circ Genom Precis Med, 2023)
Background Risk for venous thromboembolism has a strong genetic component. Whole genome sequencingfrom the Trans-Omics for Precision Medicine program allowed us to look for new associations, particularly rare variants missed by standard genome-wide association studies. Methods The 3793 cases and 7834 controls (11.6% of cases were Black, Hispanic/Latino, or Asian American) were analyzed using a single variant approach and an aggregate gene-based approach using our primary filter (included only loss-of-function and missense variants predicted to be deleterious) and our secondary filter (included all missense variants). Results Single variant analyses identified associations at 5 known loci. Aggregate gene-based analyses identified only (odds ratio, 6.2 for carriers of rare variants; =7.4×10) when using our primary filter. Employing our secondary variant filter led to a smaller effect size at (odds ratio, 3.8; =1.6×10), while excluding variants found only in rare isoforms led to a larger one (odds ratio, 7.5). Different filtering strategies improved the signal for 2 other known genes: became significant (minimum =1.8×10 with the secondary filter), while did not (minimum =4.4×10 with minor allele frequency <0.0005). Results were largely the same when restricting the analyses to include only unprovoked cases; however, one novel gene, , became significant (=4.4×10 using all missense variants with minor allele frequency <0.0005). Conclusions Here, we have demonstrated the importance of using multiple variant filtering strategies, as we detected additional genes when filtering variants based on their predicted deleteriousness, frequency, and presence on the most expressed isoforms. Our primary analyses did not identify new candidate loci; thus larger follow-up studies are needed to replicate the novel locus and to identify additional rare variation associated with venous thromboembolism.

WHOLE GENOME SEQUENCING ANALYSIS OF BODY MASS INDEX IDENTIFIES NOVEL AFRICAN ANCESTRY-SPECIFIC RISK ALLELE. - Zhang, Xinruo; Brody, Jennifer A; Graff, Mariaelisa; Highland, Heather M; Chami, Nathalie; Xu, Hanfei; Wang, Zhe; Ferrier, Kendra; Chittoor, Geetha; Josyula, Navya S; Li, Xihao; Li, Zilin; et al. (medRxiv, 2023)
Obesity is a major public health crisis associated with high mortality rates. Previous genome-wide association studies (GWAS) investigating body mass index (BMI) have largely relied on imputed data from European individuals. This study leveraged whole-genome sequencing (WGS) data from 88,873 participants from the Trans-Omics for Precision Medicine (TOPMed) Program, of which 51% were of non-European population groups. We discovered 18 BMI-associated signals ( < 5 × 10 ). Notably, we identified and replicated a novel low frequency single nucleotide polymorphism (SNP) in that was common in individuals of African descent. Using a diverse study population, we further identified two novel secondary signals in known BMI loci and pinpointed two likely causal variants in the and loci. Our work demonstrates the benefits of combining WGS and diverse cohorts in expanding current catalog of variants and genes confer risk for obesity, bringing us one step closer to personalized medicine.

Whole Genome Sequencing Based Analysis of Inflammation Biomarkers in the Trans-Omics for Precision Medicine (TOPMed) Consortium. - Jiang, Min-Zhi; Gaynor, Sheila M; Li, Xihao; Van Buren, Eric; Stilp, Adrienne; Buth, Erin; Wang, Fei Fei; Manansala, Regina; Gogarten, Stephanie M; Li, Zilin; Polfus, Linda M; Salimi, Shabnam; et al. (bioRxiv, 2023)
Inflammation biomarkers can provide valuable insight into the role of inflammatory processes in many diseases and conditions. Sequencing based analyses of such biomarkers can also serve as an exemplar of the genetic architecture of quantitative traits. To evaluate the biological insight, which can be provided by a multi-ancestry, whole-genome based association study, we performed a comprehensive analysis of 21 inflammation biomarkers from up to 38,465 individuals with whole-genome sequencing from the Trans-Omics for Precision Medicine (TOPMed) program. We identified 22 distinct single-variant associations across 6 traits - E-selectin, intercellular adhesion molecule 1, interleukin-6, lipoprotein-associated phospholipase A2 activity and mass, and P-selectin - that remained significant after conditioning on previously identified associations for these inflammatory biomarkers. We further expanded upon known biomarker associations by pairing the single-variant analysis with a rare variant set-based analysis that further identified 19 significant rare variant set-based associations with 5 traits. These signals were distinct from both significant single variant association signals within TOPMed and genetic signals observed in prior studies, demonstrating the complementary value of performing both single and rare variant analyses when analyzing quantitative traits. We also confirm several previously reported signals from semi-quantitative proteomics platforms. Many of these signals demonstrate the extensive allelic heterogeneity and ancestry-differentiated variant-trait associations common for inflammation biomarkers, a characteristic we hypothesize will be increasingly observed with well-powered, large-scale analyses of complex traits.

Whole-genome sequencing uncovers two loci for coronary artery calcification and identifies ARSE as a regulator of vascular calcification. - de Vries, Paul S; Conomos, Matthew P; Singh, Kuldeep; Nicholson, Christopher J; Jain, Deepti; Hasbani, Natalie R; Jiang, Wanlin; Lee, Sujin; Lino Cardenas, Christian L; Lutz, Sharon M; Wong, Doris; Guo, Xiuqing; et al. (Nat Cardiovasc Res, 2023)
Coronary artery calcification (CAC) is a measure of atherosclerosis and a well-established predictor of coronary artery disease (CAD) events. Here we describe a genome-wide association study (GWAS) of CAC in 22,400 participants from multiple ancestral groups. We confirmed associations with four known loci and identified two additional loci associated with CAC ( and ), with evidence of significant associations in replication analyses for both novel loci. Functional assays of and in human vascular smooth muscle cells (VSMCs) demonstrate that is a promoter of VSMC calcification and VSMC phenotype switching from a contractile to a calcifying or osteogenic phenotype. Furthermore, we show that the association of variants near with reduced CAC is likely explained by reduced expression with the G allele of enhancer variant rs5982944. Our study highlights ARSE as an important contributor to atherosclerotic vascular calcification, and a potential drug target for vascular calcific disease.

Alzheimer's Disease Sequencing Project Release 4 Whole Genome Sequencing Dataset - Leung, Y. Y.; Lee, W. P.; Kuzma, A. B.; Nicaretta, H.; Valladares, O.; Gangadharan, P.; Qu, L.; Zhao, Y.; Ren, Y.; Cheng, P. L.; Kuksa, P. P.; Wang, H.; et al. (medRxiv, 2024)
The Alzheimer's Disease Sequencing Project (ADSP) is a national initiative to understand the genetic architecture of Alzheimer's Disease and Related Dementias (AD/ADRD) by sequencing whole genomes of affected participants and age-matched cognitive controls from diverse populations. The Genome Center for Alzheimer's Disease (GCAD) processed whole-genome sequencing data from 36,361 ADSP participants, including 35,014 genetically unique participants of which 45% are from non-European ancestry, across 17 cohorts in 14 countries in this fourth release (R4). This sequencing effort identified 387 million bi-allelic variants, 42 million short insertions/deletions, and 2.2 million structural variants. Annotations and quality control data are available for all variants and samples. Additionally, detailed phenotypes from 15,927 participants across 10 domains are also provided. A linkage disequilibrium panel was created using unrelated AD cases and controls. Researchers can access and analyze the genetic data via NIAGADS Data Sharing Service, the VariXam tool, or NIAGADS GenomicsDB.

Association of Coagulation Factor XI Level With Cardiovascular Events and Cardiac Function in Community-Dwelling Adults: From ARIC and CHS. - Ji, Yuekai; Zhang, Michael J; Wang, Wendy; Norby, Faye L; Eaton, Anne A; Inciardi, Riccardo M; Alonso, Alvaro; Sedaghat, Sanaz; Ganz, Peter; Van't Hof, Jeremy; Solomon, Scott D; Chaves, Paulo H M; et al. (Circulation, 2024)
BACKGROUND: Coagulation factor XI (FXI) inhibitors are a promising and novel class of anticoagulants, but a recent animal study found that FXI inhibition exacerbated diastolic dysfunction and heart failure (HF). In the ARIC study (Atherosclerosis Risk in Communities), we investigated whether plasma FXI level was associated with cardiovascular events and cardiac function. METHODS: ARIC was our primary analytic cohort. We included 4471 participants (median age, 75 years; 57% female; 17% Black) who attended visit 5 (2011-2013) with Somalogic-quantified plasma FXI levels and echocardiographic cardiac function. Prevalent HF and atrial fibrillation (AF) cases were defined as having HF or AF diagnosed at or before each participant's visit 5 exam date. Incident HF and AF events were ascertained through 2021. Associations were assessed using Cox, logistic, and linear regression models. Primary prospective associations were also validated in the CHS (Cardiovascular Health Study) using an orthogonal FXI assay (enzyme-linked immunosorbent assay). RESULTS: At ARIC visit 5, there were 665 and 419 participants with prevalent HF and AF, respectively. During a median follow-up of 9 years, there were 580 and 788 incident HF and AF events, respectively. Lower FXI level was associated prospectively with higher incidence of HF (hazard ratio [HR], 1.36 [for each 1-unit decrement of log-transformed FXI level] [95% CI, 1.01-1.83]) but not incident AF, and cross-sectionally with increased odds of AF (odds ratio [OR], 1.96 [95% CI, 1.23-3.07]) but not HF. In age-stratified analyses, decreased FXI was associated with higher incidence of HF in participants ≥75 years of age (HR, 1.57 [95% CI, 1.08-2.28]) but not <75 years of age (HR, 1.11 [95% CI, 0.68-1.79]). The inverse FXI-HF association was validated in CHS (HR, 1.18 [95% CI, 1.02-1.36]). At ARIC visit 5, lower FXI level was also associated with higher prevalence of diastolic dysfunction and worse E/A ratio, left atrial (LA) volume index, LA function, and left ventricular mass index, but not left ventricular ejection fraction or global longitudinal strain. CONCLUSIONS: Decreased FXI level is associated with greater incidence of HF, especially in older adults. It is also associated with prevalent AF, worse diastolic function, worse LA function, and greater LA size. More research is needed to assess potential unwanted effects of FXI inhibition on the risk of cardiovascular events and cardiac function.

Association of Fibroblast Growth Factor 23 and Cardiac Mechanics in the Cardiovascular Health Study. - Jain, Keertana; Katz, Ronit; Isakova, Tamara; Kizer, Jorge R; Sharma, Shilpa; Psaty, Bruce M; Shah, Sanjiv; Ix, Joachim; Mehta, Rupal (Kidney360, 2024)
BACKGROUND: Elevated levels of fibroblast growth factor 23 (FGF23) are associated with left ventricular hypertrophy and heart failure (HF) in individuals with and without kidney disease. Prior studies investigated the association of FGF23 and structural cardiac changes using conventional echocardiography, which is limited in its ability to detect early cardiac dysfunction. We investigated the relationship between FGF23 levels and cardiac dynamics using two-dimensional speckle tracking echocardiography (2D-STE), a novel imaging modality. METHODS: This was a cross-sectional analysis of data from the Cardiovascular Health Study, an ongoing prospective, population-based cohort study. The study population included 506 participants from CHS with available c-terminal (cFGF23) and intact FGF23 (iFGF23) measurements from 1996-1997 and 2D-STE images from 1994-1995. Forty two percent of the study population had CKD, defined as an eGFR < 60 ml/min/1.73m2, and the mean eGFR was 63 ml/min/1.73m2. The primary exposures were cFGF23 and iFGF23. The primary outcomes were six 2D-STE parameters performed at the 1994-1995 study visit. Linear regression models were used to examine the independent associations of FGF23 with six cardiac 2D-STE indices adjusting for demographics, cardiovascular risk factors, markers of kidney disease severity, and inflammation. RESULTS: cFGF23 levels were moderately correlated with iFGF23 levels in the CHS population. In fully adjusted models, cFGF23 was associated with left atrial dysfunction, but no other cardiac imaging parameter (β estimate -2.47; 95% Confidence Interval -4.68, -0.25; Table 2 ). iFGF23 was not associated with any of the six 2D-STE indices. Limitations include small sample size and noncurrent FGF23 measurements and 2D-STE imaging. CONCLUSIONS: In a limited sample of individuals enrolled in the CHS with c- and i-FGF23 measurements, we did not find consistent associations between FGF23 levels and 2D-STE parameters. Further investigations in a larger population with concurrent 2D-STE are needed to better understand the associations of FGF23 with early changes in cardiac mechanics.

Associations of Neurological Biomarkers in Serum with Gait Measures: The Cardiovascular Health Study. - Nadkarni, Abhijay; Mukamal, Kenneth J; Zhu, Xiaonan; Siscovick, David; Brach, Jennifer S; Jacob, Mini; Seshadri, Sudha; Abe, Temidayo; Rosano, Caterina; Djoussé, Luc; Rosso, Andrea L (J Gerontol A Biol Sci Med Sci, 2024)
BACKGROUND: Gait impairment leads to increased mobility decline and may have neurological contributions. This study explores how neurological biomarkers are related to gait in older adults. METHODS: We studied participants in the Cardiovascular Health Study, a population-based cohort of older Americans, who underwent a serum biomarker assessment from samples collected in 1996-97 for neurofilament light-chain (NfL), glial fibrillary acidic protein (GFAP), ubiquitin carboxy-terminal hydrolase L1 (UCH-L1), and total tau (n=1959, mean age=78.0 years, 60.8% female). In a subsample (n=380), cross-sectional associations with quantitative gait measures were explored. This subsample was assessed on a mat for gait speed, step length, double support time, step time, step length variability and step time variability. Gait speed was also measured over a 15-ft walkway annually from 1996-97 to 1998-99, for longitudinal analyses. Linear regression models assessed cross-sectional associations of biomarkers with gait measures, while mixed effects models assessed longitudinal gait speed change from baseline to 1998-99. RESULTS: NfL was significantly associated with annual gait speed decline (standardized β = -0.64 m/s, 95% CI: [-1.23, -0.06]) after adjustment for demographic and health factors. Among gait mat-assessed phenotypes, NfL was also cross-sectionally associated with gait speed (β = 0.001 m/s [0.0003, 0.002]) but not with other gait measures. None of the remaining biomarkers were significantly related to gait in either longitudinal or cross-sectional analyses. CONCLUSION: Higher NfL levels were related to greater annual gait speed decline. Gait speed decline may be related to axonal degeneration. The clinical utility of NfL should be explored.

Circulating Ketone Bodies, Pyruvate, and Citrate and Risk of Cognitive Decline, Structural Brain Abnormalities, and Dementia. - Gutierrez-Tordera, Laia; Moseholm, Kristine F; Trius-Soler, Marta; Bulló, Mònica; Fitzpatrick, Annette; Connelly, Margery A; Lopez, Oscar L; Jensen, Majken K; Guasch-Ferré, Marta; Mukamal, Kenneth J (Aging Dis, 2024)
The relationship between key energy metabolites and brain health is not well understood. We investigated the association between circulating ketone bodies, pyruvate, and citrate with cognitive decline, structural brain characteristics, and risk of dementia. We measured ketone bodies (acetoacetate, β-hydroxybutyrate, and acetone), pyruvate, and citrate species using NMR in plasma samples from 1,850 older adults in the Cardiovascular Health Study collected in 1989-90 or 1992-93. Cognitive decline was assessed using the modified Mini-Mental State Examination and the Digit Symbol Substitution Test. Dementia was adjudicated by a committee of experts through comprehensive evaluations including cognitive tests, medical records, and interviews with the next of kin. Dementia-related mortality was confirmed by a committee using death certificates and other clinical data from hospitalization. Multivariable linear mixed models were used to assess 9-year cognitive decline, while multivariable Cox regression models evaluated 6-year dementia incidence and 22-year dementia-related mortality. White matter lesions and ventricular size were measured using MRI in 1992-94 and were analyzed using multivariable linear regression models. Higher plasma levels of ketones, particularly β-hydroxybutyrate, were associated with faster cognitive decline (β, -0.10; 95% CI, -0.15 to -0.05; P&;lt.001) and dementia-related mortality (HR per SD, 1.29; 95% CI, 1.07 to 1.56; P=0.023). Higher pyruvate concentrations were associated with slower cognitive decline, smaller ventricular size, lower dementia risk (HR per SD, 0.87; 95% CI, 0.77 to 0.97; P=0.013; P=0.073), and lower dementia mortality. Higher citrate levels were associated with less cognitive decline and lower dementia risk. In adults aged 65 years and older, circulating ketone bodies are associated with faster cognitive decline and higher dementia mortality, while pyruvate and citrate are associated with lower dementia risk.

Circulating sphingolipids and subclinical brain pathology: the cardiovascular health study. - Moseholm, Kristine F; Horn, Jens W; Fitzpatrick, Annette L; Djoussé, Luc; Longstreth, W T; Lopez, Oscar L; Hoofnagle, Andrew N; Jensen, Majken K; Lemaitre, Rozenn N; Mukamal, Kenneth J (Front Neurol, 2024)
BACKGROUND: Sphingolipids are implicated in neurodegeneration and neuroinflammation. We assessed the potential role of circulating ceramides and sphingomyelins in subclinical brain pathology by investigating their association with brain magnetic resonance imaging (MRI) measures and circulating biomarkers of brain injury, neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) in the Cardiovascular Health Study (CHS), a large and intensively phenotyped cohort of older adults. METHODS: Brain MRI was offered twice to CHS participants with a mean of 5 years between scans, and results were available from both time points in 2,116 participants (mean age 76 years; 40% male; and 25% ε4 allele carriers). We measured 8 ceramide and sphingomyelin species in plasma samples and examined the associations with several MRI, including worsening grades of white matter hyperintensities and ventricular size, number of brain infarcts, and measures of brain atrophy in a subset with quantitative measures. We also investigated the sphingolipid associations with serum NfL and GFAP. RESULTS: In the fully adjusted model, higher plasma levels of ceramides and sphingomyelins with a long (16-carbon) saturated fatty acid were associated with higher blood levels of NfL [β = 0.05, false-discovery rate corrected () = 0.004 and β = 0.06,  = < 0.001, respectively]. In contrast, sphingomyelins with very long (20- and 22-carbon) saturated fatty acids tended to have an inverse association with levels of circulating NfL. In secondary analyses, we found an interaction between ceramide d18:1/20:0 and sex ( for interaction = <0.001), such that ceramide d18:1/20:0 associated with higher odds for infarcts in women [OR = 1.26 (95%CI: 1.07, 1.49),  = 0.03]. We did not observe any associations with GFAP blood levels, white matter grade, ventricular grade, mean bilateral hippocampal volume, or total brain volume. CONCLUSION: Overall, our comprehensive investigation supports the evidence that ceramides and sphingomyelins are associated with increased aging brain pathology and that the direction of association depends on the fatty acid attached to the sphingosine backbone.

Circulating sphingolipids in relation to cognitive decline and incident dementia: The Cardiovascular Health Study. - Moseholm, Kristine F; Cronjé, Héléne T; Koch, Manja; Fitzpatrick, Annette L; Lopez, Oscar L; Otto, Marcia C de Oliveira; Longstreth, W T; Hoofnagle, Andrew N; Mukamal, Kenneth J; Lemaitre, Rozenn N; Jensen, Majken K (Alzheimers Dement (Amst), 2024)
INTRODUCTION: Whether circulating levels of sphingolipids are prospectively associated with cognitive decline and dementia risk is uncertain. METHODS: We measured 14 sphingolipid species in plasma samples from 4488 participants (mean age 76.2 years; 40% male; and 25% apolipoprotein E ( ε4 allele carriers). Cognitive decline was assessed annually across 6 years using modified Mini-Mental State Examination (3MSE) and Digital Symbol Substitution Test (DSST). Additionally, a subset of 3050 participants were followed for clinically adjudicated dementia. RESULTS: Higher plasma levels of sphingomyelin-d18:1/16:0 (SM-16) were associated with a faster cognitive decline measured with 3MSE, in contrast, higher levels of sphingomyelin-d18:1/22:0 (SM-22) were associated with slower decline in cognition measured with DSST. In Cox regression, higher levels of SM-16 (hazard ration [HR] = 1.24 [95% confidence interval [CI]: 1.08-1.44]) and ceramide-d18:1/16:0 (Cer-16) (HR = 1.26 [95% CI: 1.10-1.45]) were associated with higher risk of incident dementia. DISCUSSION: Several sphingolipid species appear to be involved in cognitive decline and dementia risk. HIGHLIGHTS: Plasma levels of sphingolipids were associated with cognitive decline and dementia risk.Ceramides and sphingomyelins with palmitic acid were associated with faster annual cognitive decline and increased risk of dementia.The direction of association depended on the covalently bound saturated fatty acid chain length in analysis of cognitive decline.

{Cohort Profile: Dementia Risk Prediction Project (DRPP) - Krefman, A. E.; Stephen, J.; Carolan, P.; Sedaghat, S.; Mansolf, M.; Soumare, A.; Gross, A. L.; Aiello, A. E.; Singh-Manoux, A.; Ikram, M. A.; Helmer, C.; Tzourio, C.; et al. (Int J Epidemiol, 2024)

Cost-Effectiveness of Screening Asymptomatic Carotid Stenosis by Atherosclerotic Cardiovascular Risk. - Zhu, Jinyi; Jhang, Janice; Yu, Hanxuan; Mushlin, Alvin I; Kamel, Hooman; Alemayehu, Nathaniel; Giardina, John C; Gupta, Ajay; Pandya, Ankur (medRxiv, 2024)
IMPORTANCE: Extracranial internal carotid artery stenosis (50-99% arterial narrowing) is an important risk factor for ischemic stroke. Yet, the benefits and harms of targeted screening for asymptomatic carotid artery stenosis (ACAS) have not been assessed in population-based studies. OBJECTIVE: To estimate the cost-effectiveness of one-time, targeted ACAS screening stratified by atherosclerotic cardiovascular disease (ASCVD) risk using the American Heart Association's Pooled Cohort Equations. DESIGN SETTING AND PARTICIPANTS: We developed a lifetime microsimulation model of ACAS and stroke for a hypothetical cohort representative of US adults aged 50-80 years without stroke history. We used the Cardiovascular Health Study to estimate the probability and severity of ACAS based on individual characteristics (e.g., age, sex, smoking status, blood pressure, and cholesterol). Stroke risks were functions of these characteristics and ACAS severity. In the model, individuals testing positive for >70% stenosis with Duplex ultrasound and a confirmatory diagnostic test undergo revascularization, which may reduce the risk of stroke but also introduces complication risks. Diagnostic performance parameters, revascularization benefits and risks, utility weights, and costs were estimated from published sources. Cost-effectiveness was assessed from the health care sector perspective using a $100,000/quality-adjusted life year (QALY) threshold. MAIN OUTCOMES AND MEASURES: Estimated stroke events prevented, lifetime costs, QALYs, and incremental cost-effectiveness ratios (ICERs) associated with ACAS screening. Costs (2023 USD) and QALYs were discounted at 3% annually. RESULTS: We found that screening individuals with a 10-year ASCVD risk >30% was the most cost-effective strategy, with an ICER of $89,000/QALY. This strategy would make approximately 11.9% of the population eligible for screening, averting an estimated 24,084 strokes. Results were sensitive to variations in the efficacy and complication risk of revascularization. In probabilistic sensitivity analysis, screening those in lower ASCVD risk groups (0-20%) only had a 0.6% chance of being cost-effective. CONCLUSION AND RELEVANCE: A one-time screening may only be cost-effective for adults at a relatively high ASCVD risk. Our findings provide a framework that can be adapted as future clinical trial data continue to improve our understanding of the role of revascularization and intensive medical therapy in contemporary stroke prevention secondary to carotid disease.

Cumulative Systolic Blood Pressure and Incident Stroke Type Variation by Race and Ethnicity. - Johnson, Kimson E; Li, Hanyu; Zhang, Min; Springer, Mellanie V; Galecki, Andrzej T; Whitney, Rachael T; Gottesman, Rebecca F; Hayward, Rodney A; Sidney, Stephen; Elkind, Mitchell S V; Longstreth, W T; Heckbert, Susan R; et al. (JAMA Netw Open, 2024)
IMPORTANCE: Stroke risk varies by systolic blood pressure (SBP), race, and ethnicity. The association between cumulative mean SBP and incident stroke type is unclear, and whether this association differs by race and ethnicity remains unknown. OBJECTIVE: To examine the association between cumulative mean SBP and first incident stroke among 3 major stroke types-ischemic stroke (IS), intracerebral hemorrhage (ICH), and subarachnoid hemorrhage (SAH)-and explore how these associations vary by race and ethnicity. DESIGN, SETTING, AND PARTICIPANTS: Individual participant data from 6 US longitudinal cohorts (January 1, 1971, to December 31, 2019) were pooled. The analysis was performed from January 1, 2022, to January 2, 2024. The median follow-up was 21.6 (IQR, 13.6-31.8) years. EXPOSURE: Time-dependent cumulative mean SBP. MAIN OUTCOMES AND MEASURES: The primary outcome was time from baseline visit to first incident stroke. Secondary outcomes consisted of time to first incident IS, ICH, and SAH. RESULTS: Among 40 016 participants, 38 167 who were 18 years or older at baseline with no history of stroke and at least 1 SBP measurement before the first incident stroke were included in the analysis. Of these, 54.0% were women; 25.0% were Black, 8.9% were Hispanic of any race, and 66.2% were White. The mean (SD) age at baseline was 53.4 (17.0) years and the mean (SD) SBP at baseline was 136.9 (20.4) mm Hg. A 10-mm Hg higher cumulative mean SBP was associated with a higher risk of overall stroke (hazard ratio [HR], 1.20 [95% CI, 1.18-1.23]), IS (HR, 1.20 [95% CI, 1.17-1.22]), and ICH (HR, 1.31 [95% CI, 1.25-1.38]) but not SAH (HR, 1.13 [95% CI, 0.99-1.29]; P = .06). Compared with White participants, Black participants had a higher risk of IS (HR, 1.20 [95% CI, 1.09-1.33]) and ICH (HR, 1.67 [95% CI, 1.30-2.13]) and Hispanic participants of any race had a higher risk of SAH (HR, 3.81 [95% CI, 1.29-11.22]). There was no consistent evidence that race and ethnicity modified the association of cumulative mean SBP with first incident stroke and stroke type. CONCLUSIONS AND RELEVANCE: The findings of this cohort study suggest that cumulative mean SBP was associated with incident stroke type, but the associations did not differ by race and ethnicity. Culturally informed stroke prevention programs should address modifiable risk factors such as SBP along with social determinants of health and structural inequities in society.
Keywords: Adult; Aged; Black or African American; Blood Pressure; Cerebral Hemorrhage; Ethnicity; Female; Hispanic or Latino; Humans; Hypertension; Incidence; Ischemic Stroke; Longitudinal Studies; Male; Middle Aged; Racial Groups; Risk Factors; Stroke; Subarachnoid Hemorrhage; United States; White; White People

Development and validation of a machine learning-based approach to identify high-risk diabetic cardiomyopathy phenotype. - Segar, Matthew W; Usman, Muhammad Shariq; Patel, Kershaw V; Khan, Muhammad Shahzeb; Butler, Javed; Manjunath, Lakshman; Lam, Carolyn S P; Verma, Subodh; Willett, DuWayne; Kao, David; Januzzi, James L; Pandey, Ambarish (Eur J Heart Fail, 2024)
AIMS: Abnormalities in specific echocardiographic parameters and cardiac biomarkers have been reported among individuals with diabetes. However, a comprehensive characterization of diabetic cardiomyopathy (DbCM), a subclinical stage of myocardial abnormalities that precede the development of clinical heart failure (HF), is lacking. In this study, we developed and validated a machine learning-based clustering approach to identify the high-risk DbCM phenotype based on echocardiographic and cardiac biomarker parameters. METHODS AND RESULTS: Among individuals with diabetes from the Atherosclerosis Risk in Communities (ARIC) cohort who were free of cardiovascular disease and other potential aetiologies of cardiomyopathy (training, n = 1199), unsupervised hierarchical clustering was performed using echocardiographic parameters and cardiac biomarkers of neurohormonal stress and chronic myocardial injury (total 25 variables). The high-risk DbCM phenotype was identified based on the incidence of HF on follow-up. A deep neural network (DeepNN) classifier was developed to predict DbCM in the ARIC training cohort and validated in an external community-based cohort (Cardiovascular Health Study [CHS]; n = 802) and an electronic health record (EHR) cohort (n = 5071). Clustering identified three phenogroups in the derivation cohort. Phenogroup-3 (n = 324, 27% of the cohort) had significantly higher 5-year HF incidence than other phenogroups (12.1% vs. 4.6% [phenogroup 2] vs. 3.1% [phenogroup 1]) and was identified as the high-risk DbCM phenotype. The key echocardiographic predictors of high-risk DbCM phenotype were higher NT-proBNP levels, increased left ventricular mass and left atrial size, and worse diastolic function. In the CHS and University of Texas (UT) Southwestern EHR validation cohorts, the DeepNN classifier identified 16% and 29% of participants with DbCM, respectively. Participants with (vs. without) high-risk DbCM phenotype in the external validation cohorts had a significantly higher incidence of HF (hazard ratio [95% confidence interval] 1.61 [1.18-2.19] in CHS and 1.34 [1.08-1.65] in the UT Southwestern EHR cohort). CONCLUSION: Machine learning-based techniques may identify 16% to 29% of individuals with diabetes as having a high-risk DbCM phenotype who may benefit from more aggressive implementation of HF preventive strategies.

Development and Validation of the American Heart Association's PREVENT Equations. - Khan, Sadiya S; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Grams, Morgan E; Surapaneni, Aditya; Blaha, Michael J; Carson, April P; Chang, Alexander R; Ciemins, Elizabeth; Go, Alan S; Gutierrez, Orlando M; et al. (Circulation, 2024)
BACKGROUND: Multivariable equations are recommended by primary prevention guidelines to assess absolute risk of cardiovascular disease (CVD). However, current equations have several limitations. Therefore, we developed and validated the American Heart Association Predicting Risk of CVD EVENTs (PREVENT) equations among US adults 30 to 79 years of age without known CVD. METHODS: The derivation sample included individual-level participant data from 25 data sets (N=3 281 919) between 1992 and 2017. The primary outcome was CVD (atherosclerotic CVD and heart failure). Predictors included traditional risk factors (smoking status, systolic blood pressure, cholesterol, antihypertensive or statin use, and diabetes) and estimated glomerular filtration rate. Models were sex-specific, race-free, developed on the age scale, and adjusted for competing risk of non-CVD death. Analyses were conducted in each data set and meta-analyzed. Discrimination was assessed using the Harrell C-statistic. Calibration was calculated as the slope of the observed versus predicted risk by decile. Additional equations to predict each CVD subtype (atherosclerotic CVD and heart failure) and include optional predictors (urine albumin-to-creatinine ratio and hemoglobin A1c), and social deprivation index were also developed. External validation was performed in 3 330 085 participants from 21 additional data sets. RESULTS: Among 6 612 004 adults included, mean±SD age was 53±12 years, and 56% were women. Over a mean±SD follow-up of 4.8±3.1 years, there were 211 515 incident total CVD events. The median C-statistics in external validation for CVD were 0.794 (interquartile interval, 0.763-0.809) in female and 0.757 (0.727-0.778) in male participants. The calibration slopes were 1.03 (interquartile interval, 0.81-1.16) and 0.94 (0.81-1.13) among female and male participants, respectively. Similar estimates for discrimination and calibration were observed for atherosclerotic CVD- and heart failure-specific models. The improvement in discrimination was small but statistically significant when urine albumin-to-creatinine ratio, hemoglobin A1c, and social deprivation index were added together to the base model to total CVD (ΔC-statistic [interquartile interval] 0.004 [0.004-0.005] and 0.005 [0.004-0.007] among female and male participants, respectively). Calibration improved significantly when the urine albumin-to-creatinine ratio was added to the base model among those with marked albuminuria (>300 mg/g; 1.05 [0.84-1.20] versus 1.39 [1.14-1.65]; =0.01). CONCLUSIONS: PREVENT equations accurately and precisely predicted risk for incident CVD and CVD subtypes in a large, diverse, and contemporary sample of US adults by using routinely available clinical variables.
Keywords: Adult; Aged; Albumins; American Heart Association; Atherosclerosis; Cardiovascular Diseases; Creatinine; Female; Glycated Hemoglobin; Heart Failure; Humans; Male; Middle Aged; Risk Assessment; Risk Factors

Epigenetic and proteomic signatures associate with clonal hematopoiesis expansion rate. - Mack, Taralynn M; Raddatz, Michael A; Pershad, Yash; Nachun, Daniel C; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Kenny, Eimear E; Loos, Ruth J F; Redline, Susan; Cade, Brian E; et al. (Nat Aging, 2024)
Clonal hematopoiesis of indeterminate potential (CHIP), whereby somatic mutations in hematopoietic stem cells confer a selective advantage and drive clonal expansion, not only correlates with age but also confers increased risk of morbidity and mortality. Here, we leverage genetically predicted traits to identify factors that determine CHIP clonal expansion rate. We used the passenger-approximated clonal expansion rate method to quantify the clonal expansion rate for 4,370 individuals in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) cohort and calculated polygenic risk scores for DNA methylation aging, inflammation-related measures and circulating protein levels. Clonal expansion rate was significantly associated with both genetically predicted and measured epigenetic clocks. No associations were identified with inflammation-related lab values or diseases and CHIP expansion rate overall. A proteome-wide search identified predicted circulating levels of myeloid zinc finger 1 and anti-Müllerian hormone as associated with an increased CHIP clonal expansion rate and tissue inhibitor of metalloproteinase 1 and glycine N-methyltransferase as associated with decreased CHIP clonal expansion rate. Together, our findings identify epigenetic and proteomic patterns associated with the rate of hematopoietic clonal expansion.

Epigenome-wide DNA Methylation Association Study of CHIP Provides Insight into Perturbed Gene Regulation. - Levy, Daniel; Kirmani, Sara; Huan, Tianxiao; Van Amburg, Joseph; Joehanes, Roby; Uddin, Md Mesbah; Nguyen, Ngoc Quynh; Yu, Bing; Brody, Jennifer; Fornage, Myriam; Bressler, Jan; Sotoodehnia, Nona; et al. (Res Sq, 2024)
With age, hematopoietic stem cells can acquire somatic mutations in leukemogenic genes that confer a proliferative advantage in a phenomenon termed "clonal hematopoiesis of indeterminate potential" (CHIP). How these mutations confer a proliferative advantage and result in increased risk for numerous age-related diseases remains poorly understood. We conducted a multiracial meta-analysis of epigenome-wide association studies (EWAS) of CHIP and its subtypes in four cohorts (N=8196) to elucidate the molecular mechanisms underlying CHIP and illuminate how these changes influence cardiovascular disease risk. The EWAS findings were functionally validated using human hematopoietic stem cell (HSC) models of CHIP. A total of 9615 CpGs were associated with any CHIP, 5990 with DNMT3A CHIP, 5633 with TET2 CHIP, and 6078 with ASXL1 CHIP (P <1×10). CpGs associated with CHIP subtypes overlapped moderately, and the genome-wide DNA methylation directions of effect were opposite for TET2 and DNMT3A CHIP, consistent with their opposing effects on global DNA methylation. There was high directional concordance between the CpGs shared from the meta-EWAS and human edited CHIP HSCs. Expression quantitative trait methylation analysis further identified transcriptomic changes associated with CHIP-associated CpGs. Causal inference analyses revealed 261 CHIP-associated CpGs associated with cardiovascular traits and all-cause mortality (FDR adjusted p-value <0.05). Taken together, our study sheds light on the epigenetic changes impacted by CHIP and their associations with age-related disease outcomes. The novel genes and pathways linked to the epigenetic features of CHIP may serve as therapeutic targets for preventing or treating CHIP-mediated diseases.

{A genetic association study of circulating coagulation Factor VIII and von Willebrand Factor levels - de Vries, P. S.; Reventun, P.; Brown, M. R.; Heath, A. S.; Huffman, J. E.; Le, N. Q.; Bebo, A.; Brody, J. A.; Temprano-Sagrera, G.; Raffield, L. M.; Ozel, A. B.; Thibord, F.; et al. (Blood, 2024)
10-9) at seven new loci for FVIII (ST3GAL4, CLEC4M, B3GNT2, ASGR1, F12, KNG1, and TREM1/NCR2) and one for VWF (B3GNT2). VWF, ABO, and STAB2 were associated with FVIII and VWF in gene-based analyses. Multi-phenotype analysis of FVIII and VWF identified another three new loci, including PDIA3. Silencing of B3GNT2 and the previously reported CD36 gene decreased release of FVIII by HLECs, while silencing of B3GNT2, CD36, and PDIA3 decreased release of VWF by HVECs. Mendelian randomization supports causal association of higher FVIII and VWF with increased risk of thrombotic outcomes. Seven new loci were identified for FVIII and one for VWF, with evidence supporting causal associations of FVIII and VWF with thrombotic outcomes. B3GNT2, CD36, and PDIA3 modulate the release of FVIII and/or VWF in vitro.

{Genetic associations with dementia-related proteinopathy: Application of item response theory - Katsumata, Y.; Fardo, D. W.; Shade, L. M. P.; Wu, X.; Karanth, S. D.; Hohman, T. J.; Schneider, J. A.; Bennett, D. A.; Farfel, J. M.; Gauthreaux, K.; Mock, C.; Kukull, W. A.; et al. (Alzheimers Dement, 2024)
Although dementia-related proteinopathy has a strong negative impact on public health, and is highly heritable, understanding of the related genetic architecture is incomplete.\ -synuclein, and TDP-43.\ -synuclein/Lewy bodies. Novel suggestive proteinopathy-linked alleles were also discovered, including several (SDHAF1, TMEM68, and ARHGEF28) with colocalization analyses and/or high degrees of biologic credibility.\ A novel methodology using GPCM enabled insights into gene candidates for driving misfolded proteinopathies.\ Latent factor scores for proteinopathies were estimated using a generalized partial credit model. The three latent continuous scores corresponded well with proteinopathy severity. Novel genes associated with proteinopathies were identified. Several genes had high degrees of biologic credibility for dementia risk factors.

Genetic Complexities of Cerebral Small Vessel Disease, Blood Pressure, and Dementia. - Sargurupremraj, Muralidharan; Soumaré, Aïcha; Bis, Joshua C; Surakka, Ida; Jürgenson, Tuuli; Joly, Pierre; Knol, Maria J; Wang, Ruiqi; Yang, Qiong; Satizabal, Claudia L; Gudjonsson, Alexander; Mishra, Aniket; et al. (JAMA Netw Open, 2024)
IMPORTANCE: Vascular disease is a treatable contributor to dementia risk, but the role of specific markers remains unclear, making prevention strategies uncertain. OBJECTIVE: To investigate the causal association between white matter hyperintensity (WMH) burden, clinical stroke, blood pressure (BP), and dementia risk, while accounting for potential epidemiologic biases. DESIGN, SETTING, AND PARTICIPANTS: This study first examined the association of genetically determined WMH burden, stroke, and BP levels with Alzheimer disease (AD) in a 2-sample mendelian randomization (2SMR) framework. Second, using population-based studies (1979-2018) with prospective dementia surveillance, the genetic association of WMH, stroke, and BP with incident all-cause dementia was examined. Data analysis was performed from July 26, 2020, through July 24, 2022. EXPOSURES: Genetically determined WMH burden and BP levels, as well as genetic liability to stroke derived from genome-wide association studies (GWASs) in European ancestry populations. MAIN OUTCOMES AND MEASURES: The association of genetic instruments for WMH, stroke, and BP with dementia was studied using GWASs of AD (defined clinically and additionally meta-analyzed including both clinically diagnosed AD and AD defined based on parental history [AD-meta]) for 2SMR and incident all-cause dementia for longitudinal analyses. RESULTS: In 2SMR (summary statistics-based) analyses using AD GWASs with up to 75 024 AD cases (mean [SD] age at AD onset, 75.5 [4.4] years; 56.9% women), larger WMH burden showed evidence for a causal association with increased risk of AD (odds ratio [OR], 1.43; 95% CI, 1.10-1.86; P = .007, per unit increase in WMH risk alleles) and AD-meta (OR, 1.19; 95% CI, 1.06-1.34; P = .008), after accounting for pulse pressure for the former. Blood pressure traits showed evidence for a protective association with AD, with evidence for confounding by shared genetic instruments. In the longitudinal (individual-level data) analyses involving 10 699 incident all-cause dementia cases (mean [SD] age at dementia diagnosis, 74.4 [9.1] years; 55.4% women), no significant association was observed between larger WMH burden and incident all-cause dementia (hazard ratio [HR], 1.02; 95% CI, 1.00-1.04; P = .07). Although all exposures were associated with mortality, with the strongest association observed for systolic BP (HR, 1.04; 95% CI, 1.03-1.06; P = 1.9 × 10-14), there was no evidence for selective survival bias during follow-up using illness-death models. In secondary analyses using polygenic scores, the association of genetic liability to stroke, but not genetically determined WMH, with dementia outcomes was attenuated after adjusting for interim stroke. CONCLUSIONS: These findings suggest that WMH is a primary vascular factor associated with dementia risk, emphasizing its significance in preventive strategies for dementia. Future studies are warranted to examine whether this finding can be generalized to non-European populations.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Blood Pressure; Cerebral Small Vessel Diseases; Dementia; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Mendelian Randomization Analysis; Prospective Studies; Risk Factors; Stroke

The Genetic Determinants and Genomic Consequences of Non-Leukemogenic Somatic Point Mutations. - Weinstock, Joshua S; Chaudhry, Sharjeel A; Ioannou, Maria; Viskadourou, Maria; Reventun, Paula; Jakubek, Yasminka A; Alexander Liggett, L; Laurie, Cecelia; Broome, Jai G; Khan, Alyna; Taylor, Kent D; Guo, Xiuqing; et al. (medRxiv, 2024)
Clonal hematopoiesis (CH) is defined by the expansion of a lineage of genetically identical cells in blood. Genetic lesions that confer a fitness advantage, such as point mutations or mosaic chromosomal alterations (mCAs) in genes associated with hematologic malignancy, are frequent mediators of CH. However, recent analyses of both single cell-derived colonies of hematopoietic cells and population sequencing cohorts have revealed CH frequently occurs in the absence of known driver genetic lesions. To characterize CH without known driver genetic lesions, we used 51,399 deeply sequenced whole genomes from the NHLBI TOPMed sequencing initiative to perform simultaneous germline and somatic mutation analyses among individuals without leukemogenic point mutations (LPM), which we term CH-LPMneg. We quantified CH by estimating the total mutation burden. Because estimating somatic mutation burden without a paired-tissue sample is challenging, we developed a novel statistical method, the Genomic and Epigenomic informed Mutation (GEM) rate, that uses external genomic and epigenomic data sources to distinguish artifactual signals from true somatic mutations. We performed a genome-wide association study of GEM to discover the germline determinants of CH-LPMneg. After fine-mapping and variant-to-gene analyses, we identified seven genes associated with CH-LPMneg ( , , ), and one locus associated with a sex-associated mutation pathway ( . We performed a secondary analysis excluding individuals with mCAs, finding that the genetic architecture was largely unaffected by their inclusion. Functional analyses of and implicated altered HSC self-renewal and proliferation as the primary mediator of mutation burden in blood. We then performed comprehensive multi-tissue transcriptomic analyses, finding that the expression levels of 404 genes are associated with GEM. Finally, we performed phenotypic association meta-analyses across four cohorts, finding that GEM is associated with increased white blood cell count and increased risk for incident peripheral artery disease, but is not significantly associated with incident stroke or coronary disease events. Overall, we develop GEM for quantifying mutation burden from WGS without a paired-tissue sample and use GEM to discover the genetic, genomic, and phenotypic correlates of CH-LPMneg.

Genetic drivers of heterogeneity in type 2 diabetes pathophysiology. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Melloni, Giorgio E M; Kanoni, Stavroula; Rayner, Nigel W; Bocher, Ozvan; et al. (Nature, 2024)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes and molecular mechanisms that are often specific to cell type. Here, to characterize the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study data from 2,535,601 individuals (39.7% not of European ancestry), including 428,452 cases of T2D. We identify 1,289 independent association signals at genome-wide significance (P < 5 × 10) that map to 611 loci, of which 145 loci are, to our knowledge, previously unreported. We define eight non-overlapping clusters of T2D signals that are characterized by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type-specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial cells and enteroendocrine cells. We build cluster-specific partitioned polygenic scores in a further 279,552 individuals of diverse ancestry, including 30,288 cases of T2D, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned polygenic scores are associated with coronary artery disease, peripheral artery disease and end-stage diabetic nephropathy across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings show the value of integrating multi-ancestry genome-wide association study data with single-cell epigenomics to disentangle the aetiological heterogeneity that drives the development and progression of T2D. This might offer a route to optimize global access to genetically informed diabetes care.

Genome-wide analysis in over 1 million individuals of European ancestry yields improved polygenic risk scores for blood pressure traits. - Keaton, Jacob M; Kamali, Zoha; Xie, Tian; Vaez, Ahmad; Williams, Ariel; Goleva, Slavina B; Ani, Alireza; Evangelou, Evangelos; Hellwege, Jacklyn N; Yengo, Loic; Young, William J; Traylor, Matthew; et al. (Nat Genet, 2024)
Hypertension affects more than one billion people worldwide. Here we identify 113 novel loci, reporting a total of 2,103 independent genetic signals (P < 5 × 10) from the largest single-stage blood pressure (BP) genome-wide association study to date (n = 1,028,980 European individuals). These associations explain more than 60% of single nucleotide polymorphism-based BP heritability. Comparing top versus bottom deciles of polygenic risk scores (PRSs) reveals clinically meaningful differences in BP (16.9 mmHg systolic BP, 95% CI, 15.5-18.2 mmHg, P = 2.22 × 10) and more than a sevenfold higher odds of hypertension risk (odds ratio, 7.33; 95% CI, 5.54-9.70; P = 4.13 × 10) in an independent dataset. Adding PRS into hypertension-prediction models increased the area under the receiver operating characteristic curve (AUROC) from 0.791 (95% CI, 0.781-0.801) to 0.826 (95% CI, 0.817-0.836, ∆AUROC, 0.035, P = 1.98 × 10). We compare the 2,103 loci results in non-European ancestries and show significant PRS associations in a large African-American sample. Secondary analyses implicate 500 genes previously unreported for BP. Our study highlights the role of increasingly large genomic studies for precision health research.

{Genome-wide association study of preserved ratio impaired spirometry (PRISm) - Higbee, D. H.; Lirio, A.; Hamilton, F.; Granell, R.; Wyss, A. B.; London, S. J.; Bartz, T. M.; Gharib, S. A.; Cho, M. H.; Wan, E.; Silverman, E.; Crapo, J. D.; et al. (Eur Respir J, 2024)
{0.70. PRISm is associated with respiratory symptoms and comorbidities. Our objective was to discover novel genetic signals for PRISm and see if they provide insight into the pathogenesis of PRISm and associated comorbidities.\ We undertook a genome-wide association study (GWAS) of PRISm in UK Biobank participants (Stage 1), and selected single nucleotide polymorphisms (SNPs) reaching genome-wide significance for replication in 13 cohorts (Stage 2). A combined meta-analysis of Stage 1 and Stage 2 was done to determine top SNPs. We used cross-trait linkage disequilibrium score regression to estimate genome-wide genetic correlation between PRISm and pulmonary and extrapulmonary traits. Phenome-wide association studies of top SNPs were performed.\ =0.12

Human Plasma Proteomic Profile of Clonal Hematopoiesis. - Yu, Zhi; Vromman, Amélie; Nguyen, Ngoc Quynh H; Schuermans, Art; Rentz, Thiago; Vellarikkal, Shamsudheen K; Uddin, Md Mesbah; Niroula, Abhishek; Griffin, Gabriel; Honigberg, Michael C; Lin, Amy E; Gibson, Christopher J; et al. (bioRxiv, 2024)
Plasma proteomic profiles associated with subclinical somatic mutations in blood cells may offer novel insights into downstream clinical consequences. Here, we explore such patterns in clonal hematopoiesis of indeterminate potential (CHIP), which is linked to several cancer and non-cancer outcomes, including coronary artery disease (CAD). Among 61,833 ancestrally diverse participants (3,881 with CHIP) from NHLBI TOPMed and UK Biobank with blood-based DNA sequencing and proteomic measurements (1,148 proteins by SomaScan in TOPMed and 2,917 proteins by Olink in UK Biobank), we identified 32 and 345 unique proteins from TOPMed and UK Biobank, respectively, associated with the most prevalent driver genes (, , and ). These associations showed substantial heterogeneity by driver genes, sex, and race, and were enriched for immune response and inflammation pathways. Mendelian randomization in humans, coupled with ELISA in hematopoietic -/- vs wild-type mice validation, disentangled causal proteomic perturbations from CHIP. Lastly, we identified plasma proteins shared between CHIP and CAD.

Large-scale circulating proteome association study (CPAS) meta-analysis identifies circulating proteins and pathways predicting incident hip fractures. - Austin, Thomas R; Fink, Howard A; Jalal, Diana I; Törnqvist, Anna E; Bůzková, Petra; Barzilay, Joshua I; Lu, Tianyuan; Carbone, Laura; Gabrielsen, Maiken E; Grahnemo, Louise; Hveem, Kristian; Jonasson, Christian; et al. (J Bone Miner Res, 2024)
Hip fractures are associated with significant disability, high cost, and mortality. However, the exact biological mechanisms underlying susceptibility to hip fractures remain incompletely understood. In an exploratory search of the underlying biology as reflected through the circulating proteome, we performed a comprehensive Circulating Proteome Association Study (CPAS) meta-analysis for incident hip fractures. Analyses included 6430 subjects from two prospective cohort studies (Cardiovascular Health Study and Trøndelag Health Study) with circulating proteomics data (aptamer-based 5 K SomaScan version 4.0 assay; 4979 aptamers). Associations between circulating protein levels and incident hip fractures were estimated for each cohort using age and sex-adjusted Cox regression models. Participants experienced 643 incident hip fractures. Compared with the individual studies, inverse-variance weighted meta-analyses yielded more statistically significant associations, identifying 23 aptamers associated with incident hip fractures (conservative Bonferroni correction 0.05/4979, P < 1.0 × 10-5). The aptamers most strongly associated with hip fracture risk corresponded to two proteins of the growth hormone/insulin growth factor system (GHR and IGFBP2), as well as GDF15 and EGFR. High levels of several inflammation-related proteins (CD14, CXCL12, MMP12, ITIH3) were also associated with increased hip fracture risk. Ingenuity pathway analysis identified reduced LXR/RXR activation and increased acute phase response signaling to be overrepresented among those proteins associated with increased hip fracture risk. These analyses identified several circulating proteins and pathways consistently associated with incident hip fractures. These findings underscore the usefulness of the meta-analytic approach for comprehensive CPAS in a similar manner as has previously been observed for large-scale human genetic studies. Future studies should investigate the underlying biology of these potential novel drug targets.

Levels of procoagulant factors and peak thrombin generation in relation to dementia risk in older adults: The Cardiovascular Health Study. - Harrington, Laura B; Ehlert, Alexa N; Thacker, Evan L; Jenny, Nancy S; Lopez, Oscar; Cushman, Mary; Olson, Nels C; Fitzpatrick, Annette; Mukamal, Kenneth J; Jensen, Majken K (Thromb Res, 2024)
INTRODUCTION: Markers of hemostasis such as procoagulant factors and peak thrombin generation are associated with cardiovascular outcomes, but their associations with dementia risk are unclear. We aimed to evaluate prospective associations of selected procoagulant factors and peak thrombin generation with dementia risk. METHODS: We measured levels of 7 hemostatic factors (fibrinogen, factor VII coagulant activity [FVIIc], activated factor VII [FVIIa], factor VIIa-antithrombin [FVIIa-AT], factor XI antigen [FXI], peak thrombin generation, and platelet count) among participants in the Cardiovascular Health Study, a cohort of older adults free of dementia in 1992/1993 (n = 3185). Dementia was adjudicated and classified by DSM-IV criteria through 1998/1999. Cox proportional hazards models estimated hazard ratios (HRs) for any dementia associated with 1-standard deviation (SD) differences, adjusting for sociodemographic and clinical factors and APOE genotype. Secondary analyses separately evaluated the risk of vascular dementia, Alzheimer's disease, and mixed dementia. RESULTS: At baseline, participants had a median age of 73 years. Over 5.4 years of follow-up, we identified 448 dementia cases. There was no evidence of linear associations between levels of these hemostatic factors with any dementia risk (HRs per 1-SD difference ranged from 1.0 to 1.1; 95 % confidence intervals included 1.0). Results of secondary analyses by dementia subtype were similar. CONCLUSIONS: In this prospective study, there was no strong evidence of linear associations between levels of fibrinogen, FVIIc, FVIIa, FVIIa-AT, FXI, peak thrombin generation, or platelet count with dementia risk. Despite their associations with cardiovascular disease, higher levels of these biomarkers measured among older adults may not reflect dementia risk.
Keywords: Aged; Anticoagulants; Antithrombin III; Antithrombins; Dementia; Factor VIIa; Fibrinogen; Hemostatics; Humans; Prospective Studies; Thrombin

Low-Density Lipoprotein Cholesterol Level Distributions Across Different Ages: Implications for Screening Children for Severe and Familial Hypercholesterolemia. - Liu, Junxiu; Bellows, Brandon K; Jacobs, David R; Woo, Jessica G; Urbina, Elaine M; Balte, Pallavi P; Oelsner, Elizabeth C; Kazi, Dhruv S; Siscovick, David; Allen, Norrina B; Rana, Jamal S; Wilkins, John T; et al. (Circulation, 2024)

Machine learning models for predicting blood pressure phenotypes by combining multiple polygenic risk scores. - Hrytsenko, Yana; Shea, Benjamin; Elgart, Michael; Kurniansyah, Nuzulul; Lyons, Genevieve; Morrison, Alanna C; Carson, April P; Haring, Bernhard; Mitchell, Braxton D; Psaty, Bruce M; Jaeger, Byron C; Gu, C Charles; et al. (Sci Rep, 2024)
We construct non-linear machine learning (ML) prediction models for systolic and diastolic blood pressure (SBP, DBP) using demographic and clinical variables and polygenic risk scores (PRSs). We developed a two-model ensemble, consisting of a baseline model, where prediction is based on demographic and clinical variables only, and a genetic model, where we also include PRSs. We evaluate the use of a linear versus a non-linear model at both the baseline and the genetic model levels and assess the improvement in performance when incorporating multiple PRSs. We report the ensemble model's performance as percentage variance explained (PVE) on a held-out test dataset. A non-linear baseline model improved the PVEs from 28.1 to 30.1% (SBP) and 14.3% to 17.4% (DBP) compared with a linear baseline model. Including seven PRSs in the genetic model computed based on the largest available GWAS of SBP/DBP improved the genetic model PVE from 4.8 to 5.1% (SBP) and 4.7 to 5% (DBP) compared to using a single PRS. Adding additional 14 PRSs computed based on two independent GWASs further increased the genetic model PVE to 6.3% (SBP) and 5.7% (DBP). PVE differed across self-reported race/ethnicity groups, with primarily all non-White groups benefitting from the inclusion of additional PRSs. In summary, non-linear ML models improves BP prediction in models incorporating diverse populations.
Keywords: Blood Pressure; Female; Genetic Predisposition to Disease; Genetic Risk Score; Genome-Wide Association Study; Humans; Hypertension; Machine Learning; Male; Middle Aged; Models, Genetic; Multifactorial Inheritance; Phenotype; Risk Factors

Methylation patterns associated with C-reactive protein in racially and ethnically diverse populations. - Lundin, Jessica I; Peters, Ulrike; Hu, Yao; Ammous, Farah; Avery, Christy L; Benjamin, Emelia J; Bis, Joshua C; Brody, Jennifer A; Carlson, Chris; Cushman, Mary; Gignoux, Chris; Guo, Xiuqing; et al. (Epigenetics, 2024)
Systemic low-grade inflammation is a feature of chronic disease. C-reactive protein (CRP) is a common biomarker of inflammation and used as an indicator of disease risk; however, the role of inflammation in disease is not completely understood. Methylation is an epigenetic modification in the DNA which plays a pivotal role in gene expression. In this study we evaluated differential DNA methylation patterns associated with blood CRP level to elucidate biological pathways and genetic regulatory mechanisms to improve the understanding of chronic inflammation. The racially and ethnically diverse participants in this study were included as 50% White, 41% Black or African American, 7% Hispanic or Latino/a, and 2% Native Hawaiian, Asian American, American Indian, or Alaska Native (total  = 13,433) individuals. We replicated 113 CpG sites from 87 unique loci, of which five were novel (, , and cg03282312), across a discovery set of 1,150 CpG sites associated with CRP level ( < 1.2E-7). The downstream pathways affected by DNA methylation included the identification of and CpG-gene transcript pairs which contributed to the innate immune response gene enrichment pathway along with , , and . Gene enrichment analysis also identified the nuclear factor-kappaB transcription pathway. Using two-sample Mendelian randomization (MR) we inferred methylation at three CpG sites as causal for CRP levels using both White and Black or African American MR instrument variables. Overall, we identified novel CpG sites and gene transcripts that could be valuable in understanding the specific cellular processes and pathogenic mechanisms involved in inflammation.
Keywords: C-Reactive Protein; CpG Islands; DNA; DNA Methylation; Epigenesis, Genetic; Genome-Wide Association Study; Humans; Inflammation; Intracellular Signaling Peptides and Proteins

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

{Multi-trait analysis characterizes the genetics of thyroid function and identifies causal associations with clinical implications - Sterenborg, R. B. T. M.; Steinbrenner, I.; Li, Y.; Bujnis, M. N.; Naito, T.; Marouli, E.; Galesloot, T. E.; Babajide, O.; Andreasen, L.; Astrup, A.; svold, B. O.; Bandinelli, S.; et al. (Nat Commun, 2024)
T3, whereas the FT4 associations represent the thyroid hormone metabolism. Polygenic risk score and Mendelian randomization analyses showed the effects of genetically determined variation in thyroid function on various clinical outcomes, including cardiovascular risk factors and diseases, autoimmune diseases, and cancer. In conclusion, our results improve the understanding of thyroid hormone physiology and highlight the pleiotropic effects of thyroid function on various diseases.

NIAGADS: A Comprehensive National Data Repository for Alzheimer's Disease and Related Dementia Genetics and Genomics Research - Kuzma, A.; Valladares, O.; Greenfest-Allen, E.; Nicaretta, H.; Kirsch, M.; Ren, Y.; Katanic, Z.; White, H.; Wilk, A.; Bass, L.; Brettschneider, J.; Carter, L.; et al. (medRxiv, 2024)
NIAGADS is the National Institute on Aging (NIA) designated national data repository for human genetics research on Alzheimer's Disease and related dementia (ADRD). NIAGADS maintains a high-quality data collection for ADRD genetic/genomic research and supports genetics data production and analysis. NIAGADS hosts whole genome and exome sequence data from the Alzheimer's Disease Sequencing Project (ADSP) and other genotype/phenotype data, encompassing 209,000 samples. NIAGADS shares these data with hundreds of research groups around the world via the Data Sharing Service, a FISMA moderate compliant cloud-based platform that fully supports the NIH Genome Data Sharing Policy. NIAGADS Open Access consists of multiple knowledge bases with genome-wide association summary statistics and rich annotations on the biological significance of genetic variants and genes across the human genome. NIAGADS stands as a keystone in promoting collaborations to advance the understanding and treatment of Alzheimer's disease.

A plasma protein-based risk score to predict hip fractures. - Austin, Thomas R; Nethander, Maria; Fink, Howard A; Törnqvist, Anna E; Jalal, Diana I; Bůzková, Petra; Barzilay, Joshua I; Carbone, Laura; Gabrielsen, Maiken E; Grahnemo, Louise; Lu, Tianyuan; Hveem, Kristian; et al. (Nat Aging, 2024)
As there are effective treatments to reduce hip fractures, identification of patients at high risk of hip fracture is important to inform efficient intervention strategies. To obtain a new tool for hip fracture prediction, we developed a protein-based risk score in the Cardiovascular Health Study using an aptamer-based proteomic platform. The proteomic risk score predicted incident hip fractures and improved hip fracture discrimination in two Trøndelag Health Study validation cohorts using the same aptamer-based platform. When transferred to an antibody-based proteomic platform in a UK Biobank validation cohort, the proteomic risk score was strongly associated with hip fractures (hazard ratio per s.d. increase, 1.64; 95% confidence interval 1.53-1.77). The proteomic risk score, but not available polygenic risk scores for fractures or bone mineral density, improved the C-index beyond the fracture risk assessment tool (FRAX), which integrates information from clinical risk factors (C-index, FRAX 0.735 versus FRAX + proteomic risk score 0.776). The developed proteomic risk score constitutes a new tool for stratifying patients according to hip fracture risk; however, its improvement in hip fracture discrimination is modest and its clinical utility beyond FRAX with information on femoral neck bone mineral density remains to be determined.

Plasma proteome-wide analysis of cerebral small vessel disease identifies novel biomarkers and disease pathways. - Gomez, Gabriela T; Shi, Liu; Fohner, Alison E; Chen, Jingsha; Yang, Yunju; Fornage, Myriam; Duggan, Michael R; Peng, Zhongsheng; Daya, Gulzar N; Tin, Adrienne; Schlosser, Pascal; Longstreth, W T; et al. (medRxiv, 2024)
Cerebral small vessel disease (SVD), as defined by neuroimaging characteristics such as white matter hyperintensities (WMHs), cerebral microhemorrhages (CMHs), and lacunar infarcts, is highly prevalent and has been associated with dementia risk and other clinical sequelae. Although conditions such as hypertension are known to contribute to SVD, little is known about the diverse set of subclinical biological processes and molecular mediators that may also influence the development and progression of SVD. To better understand the mechanisms underlying SVD and to identify novel SVD biomarkers, we used a large-scale proteomic platform to relate 4,877 plasma proteins to MRI-defined SVD characteristics within 1,508 participants of the Atherosclerosis Risk in Communities (ARIC) Study cohort. Our proteome-wide analysis of older adults (mean age: 76) identified 13 WMH-associated plasma proteins involved in synaptic function, endothelial integrity, and angiogenesis, two of which remained associated with late-life WMH volume when measured nearly 20 years earlier, during midlife. We replicated the relationship between 9 candidate proteins and WMH volume in one or more external cohorts; we found that 11 of the 13 proteins were associated with risk for future dementia; and we leveraged publicly available proteomic data from brain tissue to demonstrate that a subset of WMH-associated proteins was differentially expressed in the context of cerebral atherosclerosis, pathologically-defined Alzheimer's disease, and cognitive decline. Bidirectional two-sample Mendelian randomization analyses examined the causal relationships between candidate proteins and WMH volume, while pathway and network analyses identified discrete biological processes (lipid/cholesterol metabolism, NF-kB signaling, hemostasis) associated with distinct forms of SVD. Finally, we synthesized these findings to identify two plasma proteins, oligodendrocyte myelin glycoprotein (OMG) and neuronal pentraxin receptor (NPTXR), as top candidate biomarkers for elevated WMH volume and its clinical manifestations.

Plasma proteomic signature of human longevity. - Liu, Xiaojuan; Axelsson, Gisli Thor; Newman, Anne B; Psaty, Bruce M; Boudreau, Robert M; Wu, Chenkai; Arnold, Alice M; Aspelund, Thor; Austin, Thomas R; Gardin, Julius M; Siggeirsdottir, Kristin; Tracy, Russell P; et al. (Aging Cell, 2024)
The identification of protein targets that exhibit anti-aging clinical potential could inform interventions to lengthen the human health span. Most previous proteomics research has been focused on chronological age instead of longevity. We leveraged two large population-based prospective cohorts with long follow-ups to evaluate the proteomic signature of longevity defined by survival to 90 years of age. Plasma proteomics was measured using a SOMAscan assay in 3067 participants from the Cardiovascular Health Study (discovery cohort) and 4690 participants from the Age Gene/Environment Susceptibility-Reykjavik Study (replication cohort). Logistic regression identified 211 significant proteins in the CHS cohort using a Bonferroni-adjusted threshold, of which 168 were available in the replication cohort and 105 were replicated (corrected p value <0.05). The most significant proteins were GDF-15 and N-terminal pro-BNP in both cohorts. A parsimonious protein-based prediction model was built using 33 proteins selected by LASSO with 10-fold cross-validation and validated using 27 available proteins in the validation cohort. This protein model outperformed a basic model using traditional factors (demographics, height, weight, and smoking) by improving the AUC from 0.658 to 0.748 in the discovery cohort and from 0.755 to 0.802 in the validation cohort. We also found that the associations of 169 out of 211 proteins were partially mediated by physical and/or cognitive function. These findings could contribute to the identification of biomarkers and pathways of aging and potential therapeutic targets to delay aging and age-related diseases.

Proteogenomics in cerebrospinal fluid and plasma reveals new biological fingerprint of cerebral small vessel disease. - Debette, Stephanie; Caro, Ilana; Western, Daniel; Namba, Shinichi; Sun, Na; Kawaguchi, Shuji; He, Yunye; Fujita, Masashi; Roshchupkin, Gennady; D'Aoust, Tim; Duperron, Marie-Gabrielle; Sargurupremraj, Murali; et al. (Res Sq, 2024)
Cerebral small vessel disease (cSVD) is a leading cause of stroke and dementia with no specific mechanism-based treatment. We used Mendelian randomization to combine a unique cerebrospinal fluid (CSF) and plasma pQTL resource with the latest European-ancestry GWAS of MRI-markers of cSVD (white matter hyperintensities, perivascular spaces). We describe a new biological fingerprint of 49 protein-cSVD associations, predominantly in the CSF. We implemented a multipronged follow-up, across fluids, platforms, and ancestries (Europeans and East-Asian), including testing associations of direct plasma protein measurements with MRI-cSVD. We highlight 16 proteins robustly associated in both CSF and plasma, with 24/4 proteins identified in CSF/plasma only. cSVD-proteins were enriched in extracellular matrix and immune response pathways, and in genes enriched in microglia and specific microglial states (integration with single-nucleus RNA sequencing). Immune-related proteins were associated with MRI-cSVD already at age twenty. Half of cSVD-proteins were associated with stroke, dementia, or both, and seven cSVD-proteins are targets for known drugs (used for other indications in directions compatible with beneficial therapeutic effects. This first cSVD proteogenomic signature opens new avenues for biomarker and therapeutic developments.

Rare variant contribution to the heritability of coronary artery disease. - Rocheleau, Ghislain; Clarke, Shoa L; Auguste, Gaëlle; Hasbani, Natalie R; Morrison, Alanna C; Heath, Adam S; Bielak, Lawrence F; Iyer, Kruthika R; Young, Erica P; Stitziel, Nathan O; Jun, Goo; Laurie, Cecelia; et al. (Nat Commun, 2024)
Whole genome sequences (WGS) enable discovery of rare variants which may contribute to missing heritability of coronary artery disease (CAD). To measure their contribution, we apply the GREML-LDMS-I approach to WGS of 4949 cases and 17,494 controls of European ancestry from the NHLBI TOPMed program. We estimate CAD heritability at 34.3% assuming a prevalence of 8.2%. Ultra-rare (minor allele frequency ≤ 0.1%) variants with low linkage disequilibrium (LD) score contribute ~50% of the heritability. We also investigate CAD heritability enrichment using a diverse set of functional annotations: i) constraint; ii) predicted protein-altering impact; iii) cis-regulatory elements from a cell-specific chromatin atlas of the human coronary; and iv) annotation principal components representing a wide range of functional processes. We observe marked enrichment of CAD heritability for most functional annotations. These results reveal the predominant role of ultra-rare variants in low LD on the heritability of CAD. Moreover, they highlight several functional processes including cell type-specific regulatory mechanisms as key drivers of CAD genetic risk.
Keywords: Case-Control Studies; Coronary Artery Disease; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; White People; Whole Genome Sequencing

Role of Polyunsaturated Fat in Modifying Cardiovascular Risk Associated With Family History of Cardiovascular Disease: Pooled De Novo Results From 15 Observational Studies. - Laguzzi, Federica; Åkesson, Agneta; Marklund, Matti; Qian, Frank; Gigante, Bruna; Bartz, Traci M; Bassett, Julie K; Birukov, Anna; Campos, Hannia; Hirakawa, Yoichiro; Imamura, Fumiaki; Jäger, Susanne; et al. (Circulation, 2024)
BACKGROUND: It is unknown whether dietary intake of polyunsaturated fatty acids (PUFA) modifies the cardiovascular disease (CVD) risk associated with a family history of CVD. We assessed interactions between biomarkers of low PUFA intake and a family history in relation to long-term CVD risk in a large consortium. METHODS: Blood and tissue PUFA data from 40 885 CVD-free adults were assessed. PUFA levels ≤25th percentile were considered to reflect low intake of linoleic, alpha-linolenic, and eicosapentaenoic/docosahexaenoic acids (EPA/DHA). Family history was defined as having ≥1 first-degree relative who experienced a CVD event. Relative risks with 95% CI of CVD were estimated using Cox regression and meta-analyzed. Interactions were assessed by analyzing product terms and calculating relative excess risk due to interaction. RESULTS: After multivariable adjustments, a significant interaction between low EPA/DHA and family history was observed (product term pooled RR, 1.09 [95% CI, 1.02-1.16]; =0.01). The pooled relative risk of CVD associated with the combined exposure to low EPA/DHA, and family history was 1.41 (95% CI, 1.30-1.54), whereas it was 1.25 (95% CI, 1.16-1.33) for family history alone and 1.06 (95% CI, 0.98-1.14) for EPA/DHA alone, compared with those with neither exposure. The relative excess risk due to interaction results indicated no interactions. CONCLUSIONS: A significant interaction between biomarkers of low EPA/DHA intake, but not the other PUFA, and a family history was observed. This novel finding might suggest a need to emphasize the benefit of consuming oily fish for individuals with a family history of CVD.
Keywords: Animals; Biomarkers; Cardiovascular Diseases; Docosahexaenoic Acids; Fatty Acids, Omega-3; Risk Factors

Single-Ancestry versus Multi-Ancestry Polygenic Risk Scores for CKD in Black American Populations. - Jones, Alana C; Patki, Amit; Srinivasasainagendra, Vinodh; Tiwari, Hemant K; Armstrong, Nicole D; Chaudhary, Ninad S; Limdi, Nita A; Hidalgo, Bertha A; Davis, Brittney; Cimino, James J; Khan, Atlas; Kiryluk, Krzysztof; et al. (J Am Soc Nephrol, 2024)

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People With Type 2 Diabetes. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (Diabetes Care, 2024)
OBJECTIVE: To identify genetic risk factors for incident cardiovascular disease (CVD) among people with type 2 diabetes (T2D). RESEARCH DESIGN AND METHODS: We conducted a multiancestry time-to-event genome-wide association study for incident CVD among people with T2D. We also tested 204 known coronary artery disease (CAD) variants for association with incident CVD. RESULTS: Among 49,230 participants with T2D, 8,956 had incident CVD events (event rate 18.2%). We identified three novel genetic loci for incident CVD: rs147138607 (near CACNA1E/ZNF648, hazard ratio [HR] 1.23, P = 3.6 × 10-9), rs11444867 (near HS3ST1, HR 1.89, P = 9.9 × 10-9), and rs335407 (near TFB1M/NOX3, HR 1.25, P = 1.5 × 10-8). Among 204 known CAD loci, 5 were associated with incident CVD in T2D (multiple comparison-adjusted P < 0.00024, 0.05/204). A standardized polygenic score of these 204 variants was associated with incident CVD with HR 1.14 (P = 1.0 × 10-16). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D.

Trajectory of Cognitive Function After Incident Heart Failure. - Shore, Supriya; Li, Hanyu; Zhang, Min; Whitney, Rachael; Gross, Alden L; Bhatt, Ankeet S; Nallamothu, Brahmajee K; Giordani, Bruno; Briceño, Emily M; Sussman, Jeremy B; Gutierrez, Jose; Yaffe, Kristine; et al. (medRxiv, 2024)
BACKGROUND: The size/magnitude of cognitive changes after incident heart failure (HF) are unclear. We assessed whether incident HF is associated with changes in cognitive function after accounting for pre-HF cognitive trajectories and known determinants of cognition. METHODS: This pooled cohort study included adults without HF, stroke, or dementia from six US population-based cohort studies from 1971-2019: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study. Linear mixed-effects models estimated changes in cognition at the time of HF (change in the intercept) and the rate of cognitive change over the years after HF (change in the slope), controlling for pre-HF cognitive trajectories and participant factors. Change in global cognition was the primary outcome. Change in executive function and memory were secondary outcomes. Cognitive outcomes were standardized to a -score metric (mean [SD], 50 [10]); a 1-point difference represented a 0.1-SD difference in cognition. RESULTS: The study included 29,614 adults (mean [SD] age was 61.1 [10.5] years, 55% female, 70.3% White, 22.2% Black 7.5% Hispanic). During a median follow-up of 6.6 (Q1-Q3: 5-19.8) years, 1,407 (4.7%) adults developed incident HF. Incident HF was associated with an acute decrease in global cognition (-1.08 points; 95% CI -1.36, -0.80) and executive function (-0.65 points; 95% CI -0.96, -0.34) but not memory (-0.51 points; 95% CI -1.37, 0.35) at the time of the event. Greater acute decreases in global cognition after HF were seen in those with older age, female sex and White race. Individuals with incident HF, compared to HF-free individuals, demonstrated faster declines in global cognition (-0.15 points per year; 95% CI, -0.21, -0.09) and executive function (-0.16 points per year; 95% CI -0.23, -0.09) but not memory ( -0.11 points per year; 95% CI -0.26, 0.04) compared with pre-HF slopes. CONCLUSIONS: In this pooled cohort study, incident HF was associated with an acute decrease in global cognition and executive function at the time of the event and faster declines in global cognition and executive function over the following years.

Trimethylamine -Oxide and Related Gut Microbe-Derived Metabolites and Incident Heart Failure Development in Community-Based Populations. - Tang, W H Wilson; Lemaitre, Rozenn N; Jensen, Paul N; Wang, Meng; Wang, Zeneng; Li, Xinmin S; Nemet, Ina; Lee, Yujin; Lai, Heidi T M; de Oliveira Otto, Marcia C; Fretts, Amanda M; Sotoodehnia, Nona; et al. (Circ Heart Fail, 2024)
BACKGROUND: Growing evidence indicates that trimethylamine -oxide, a gut microbial metabolite of dietary choline and carnitine, promotes both cardiovascular disease and chronic kidney disease risk. It remains unclear how circulating concentrations of trimethylamine -oxide and its related dietary and gut microbe-derived metabolites (choline, betaine, carnitine, γ-butyrobetaine, and crotonobetaine) affect incident heart failure (HF). METHODS: We evaluated 11 768 participants from the Cardiovascular Health Study and the Multi-Ethnic Study of Atherosclerosis with serial measures of metabolites. Cox proportional hazard models were used to examine the associations between metabolites and incident HF, adjusted for cardiovascular disease risk factors. RESULTS: In all, 2102 cases of HF occurred over a median follow-up of 15.9 years. After adjusting for traditional risk factors, higher concentrations of trimethylamine -oxide (hazard ratio, 1.15 [95% CI, 1.09-1.20]; <0.001), choline (hazard ratio, 1.44 [95% CI, 1.26-1.64]; <0.001), and crotonobetaine (hazard ratio, 1.24 [95% CI, 1.16-1.32]; <0.001) were associated with increased risk for incident HF. After further adjustment for renal function (potential confounder or mediator), these associations did not reach Bonferroni-corrected statistical significance (=0.01, 0.049, and 0.006, respectively). Betaine and carnitine were nominally associated with a higher incidence of HF (<0.05). In exploratory analyses, results were similar for subtypes of HF based on left ventricular ejection fraction, and associations appeared generally stronger among Black and Hispanic/Latino versus White adults, although there were no interactions for any metabolites with race. CONCLUSIONS: In this pooled analysis of 2 well-phenotyped, diverse, community-based cohorts, circulating concentrations of gut microbe-derived metabolites such as trimethylamine -oxide, choline, and crotonobetaine were independently associated with a higher risk of developing HF. REGISTRATION: URL: https://www.clinicaltrials.gov/; Unique identifiers: NCT00005133 and NCT00005487.
Keywords: Aged; Aged, 80 and over; Betaine; Biomarkers; Carnitine; Choline; Female; Gastrointestinal Microbiome; Heart Failure; Humans; Incidence; Male; Methylamines; Middle Aged; Risk Factors; United States

X-chromosome and kidney function: evidence from a multi-trait genetic analysis of 908,697 individuals reveals sex-specific and sex-differential findings in genes regulated by androgen response elements. - Scholz, Markus; Horn, Katrin; Pott, Janne; Wuttke, Matthias; Kühnapfel, Andreas; Nasr, M Kamal; Kirsten, Holger; Li, Yong; Hoppmann, Anselm; Gorski, Mathias; Ghasemi, Sahar; Li, Man; et al. (Nat Commun, 2024)
X-chromosomal genetic variants are understudied but can yield valuable insights into sexually dimorphic human traits and diseases. We performed a sex-stratified cross-ancestry X-chromosome-wide association meta-analysis of seven kidney-related traits (n = 908,697), identifying 23 loci genome-wide significantly associated with two of the traits: 7 for uric acid and 16 for estimated glomerular filtration rate (eGFR), including four novel eGFR loci containing the functionally plausible prioritized genes ACSL4, CLDN2, TSPAN6 and the female-specific DRP2. Further, we identified five novel sex-interactions, comprising male-specific effects at FAM9B and AR/EDA2R, and three sex-differential findings with larger genetic effect sizes in males at DCAF12L1 and MST4 and larger effect sizes in females at HPRT1. All prioritized genes in loci showing significant sex-interactions were located next to androgen response elements (ARE). Five ARE genes showed sex-differential expressions. This study contributes new insights into sex-dimorphisms of kidney traits along with new prioritized gene targets for further molecular research.
Keywords: Androgens; Chromosomes, Human, X; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kidney; Male; Polymorphism, Single Nucleotide; Response Elements; Tetraspanins

Association Between Cigarette Smoking and Subclinical Markers of Cardiovascular Harm. - Yao, Zhiqi; Tasdighi, Erfan; Dardari, Zeina A; Jha, Kunal K; Osuji, Ngozi; Rajan, Tanuja; Boakye, Ellen; Rodriguez, Carlos J; Matsushita, Kunihiro; Simonsick, Eleanor M; Lima, João A C; Widome, Rachel; et al. (J Am Coll Cardiol, 2025)
BACKGROUND: Cigarette smoking is a strong risk factor for cardiovascular harm. OBJECTIVES: The study sought to explore the detailed relationships between smoking intensity, pack-years, and time since cessation with inflammation, thrombosis, and subclinical atherosclerosis markers of cardiovascular harm. METHODS: We included 182,364 participants (mean age 58.2 years, 69.0% female) from 22 cohorts of the Cross Cohort Collaboration with self-reported smoking status, including smoking intensity and/or pack-years, and concurrent subclinical marker measurements. Markers were categorized into 3 domains: inflammation (high-sensitivity C-reactive protein, interleukin-6, glycoprotein acetylation), thrombosis (fibrinogen, D-dimer), and subclinical atherosclerosis (coronary artery calcium, carotid intima-media thickness, carotid plaque, and ankle-brachial index). Utilizing multivariate regression models and restricted cubic splines, we assessed associations of smoking status, intensity, pack-years, time since cessation, and subclinical markers. RESULTS: A total of 15.3% of participants currently smoke (mean 16.7 cigarettes/day, mean 30.0 pack-years), and 34.6% of participants formerly smoked (median 19.0 years since quitting, mean 22.4 pack-years). Participants with a history of smoking showed higher levels of all subclinical markers compared with those who have never smoked, with stronger associations observed in those currently smoke. Among participants who currently smoke, smoking intensity showed a clear dose-response relationship with all markers, except for D-dimer, specifically with incremental 1% to 9% higher levels of subclinical markers per 10 cigarettes. After 20 cigarettes, the patterns appeared to plateau for blood markers, while they continued to increase for atherosclerosis markers. Among those who have ever smoked, robust dose-response relationships were observed for pack-years with all subclinical markers, with incremental 1% to 9% higher levels per 10 pack-years. The dose-response effects persisted after 20 pack-years for all markers, though with a milder slope. Among participants who smoked formerly, there were substantially lower levels of biomarkers with longer time since quitting, and most markers were not different compared with those who have never smoked by 30 years, except for the coronary artery calcium score, which remained 19% higher even beyond quitting after 30 years. CONCLUSIONS: Smoking-relevant parameters show strong and dose-response relationships across 3 domains of subclinical markers of cardiovascular harm. The sensitivity of the tested subclinical markers to small increments in cigarette exposure suggests potential value in the regulation of new and existing tobacco products.
Keywords: Aged; Atherosclerosis; Biomarkers; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cigarette Smoking; Cohort Studies; Female; Humans; Male; Middle Aged; Risk Factors

Association between spatial social polarisation and high blood pressure in older adults. - Abdel Magid, Hoda S; Jaros, Samuel; Lovasi, Gina S; Rosso, Andrea L; Tan, Annabel X; Rehkopf, David H; Nelson, Lorene M; Carlson, Michelle; Judd, Suzanne E; Odden, Michelle C (J Epidemiol Community Health, 2025)
BACKGROUND: Using data from the Cardiovascular Health Study (CHS) and the REasons for Geographic And Racial Differences in Stroke (REGARDS) study, we investigate the association between socioeconomic polarisation and blood pressure outcomes in black and white adults. We also validate previous findings that joint racial/ethnic and income measures of spatial social polarisation (SSP) outperform single domain measures. METHODS: We conducted a cross-sectional analysis using a retrospective cohort combining CHS (recruited 1989-1990 and 1992-1993) and REGARDS (recruited 2003-2007). The study included 5888 CHS participants aged ≥65 years and 30 183 REGARDS participants aged ≥45 years. SSP was measured using the Index of Concentration at the Extremes for education, race/ethnicity, income, home ownership, and joint race/ethnicity and income at ZIP code, census tract and county levels. The SSP measures were modelled against the presence of high blood pressure and systolic blood pressure. RESULTS: The sample had a mean age of 66 (SD: 9), was majority female (56%), white/other (63%), and at least high school graduates (85%). A total of 26% had high blood pressure, with a mean systolic blood pressure of 129 mm Hg (SD: 18). Census tract-level models showed low-income black areas had 25% (95% CI 11%-40%) higher odds of high blood pressure and 1.8 mm Hg (95% CI 1.0-2.5) higher mean systolic blood pressure than high-income White areas. CONCLUSION: Greater SSP is associated with a higher risk of high blood pressure and higher systolic blood pressure. Further investigating and reducing polarisation could help mitigate cardiovascular health disparities, improving outcomes for socioeconomically deprived communities.

Cardiac Troponins and Cardiovascular Disease Risk Prediction: An Individual-Participant-Data Meta-Analysis. - Shah, Anoop S V; Keene, Spencer J; Pennells, Lisa; Kaptoge, Stephen; Kimenai, Dorien M; Walker, Matthew; Halley, Julianne D; Rocha, Sara; Hoogeveen, Ron C; Gudnason, Vilmundur; Bakker, Stephan J L; Wannamethee, Sasiwarang G; et al. (J Am Coll Cardiol, 2025)
BACKGROUND: The extent to which high-sensitivity cardiac troponin can predict cardiovascular disease (CVD) is uncertain. OBJECTIVES: We aimed to quantify the potential advantage of adding information on cardiac troponins to conventional risk factors in the prevention of CVD. METHODS: We meta-analyzed individual-participant data from 15 cohorts, comprising 62,150 participants without prior CVD. We calculated HRs, measures of risk discrimination, and reclassification after adding cardiac troponin T (cTnT) or I (cTnI) to conventional risk factors. The primary outcome was first-onset CVD (ie, coronary heart disease or stroke). We then modeled the implications of initiating statin therapy using incidence rates from 2.1 million individuals from the United Kingdom. RESULTS: Among participants with cTnT or cTnI measurements, 8,133 and 3,749 incident CVD events occurred during a median follow-up of 11.8 and 9.8 years, respectively. HRs for CVD per 1-SD higher concentration were 1.31 (95% CI: 1.25-1.37) for cTnT and 1.26 (95% CI: 1.19-1.33) for cTnI. Addition of cTnT or cTnI to conventional risk factors was associated with C-index increases of 0.015 (95% CI: 0.012-0.018) and 0.012 (95% CI: 0.009-0.015) and continuous net reclassification improvements of 6% and 5% in cases and 22% and 17% in noncases. One additional CVD event would be prevented for every 408 and 473 individuals screened based on statin therapy in those whose CVD risk is reclassified from intermediate to high risk after cTnT or cTnI measurement, respectively. CONCLUSIONS: Measurement of cardiac troponin results in a modest improvement in the prediction of first-onset CVD that may translate into population health benefits if used at scale.
Keywords: Biomarkers; Cardiovascular Diseases; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Risk Assessment; Risk Factors; Troponin I; Troponin T

Circulating non-esterified fatty acids, risk of dementia and cognitive decline: The cardiovascular health study and multi-ethnic study of atherosclerosis. - Moseholm, Kristine F; Jensen, Majken K; Bůzková, Petra; Aroner, Sarah A; Fitzpatrick, Annette L; Longstreth, W T; Lopez, Oscar; Siscovick, David S; Kizer, Jorge R; Ix, Joachim H; Hughes, Timothy M; Hayden, Kathleen M; et al. (Neurobiol Aging, 2025)
Circulating non-esterified fatty acids (NEFAs) have toxic effects on a variety of organs central to cardiometabolic disease and can cross the blood-brain barrier. Whether NEFAs associate with cognitive decline or dementia remains unknown. Circulating total NEFA levels were measured in 3242 participants without dementia among older adults of the Cardiovascular Health Study (CHS) and related to adjudicated dementia over 6 years (n = 456 cases) and annually assessed cognitive decline. For confirmation, we related circulating NEFAs to cognition assessed 10 years later among 4361 participants in the Multi-Ethnic Study of Atherosclerosis (MESA). In CHS participants, each SD higher NEFA levels were associated with a hazard ratio (HR) for all-cause dementia of 1.11 (95 % CI: 1.01; 1.22). Baseline NEFA levels were also associated with more rapid decline in cognition over 6 years of follow-up. In MESA, circulating NEFA measurements were associated with lower cognitive scores measured 10 years later.'
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognitive Dysfunction; Cohort Studies; Dementia; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Male; Middle Aged; Risk; Risk Factors

Genome-wide association study meta-analysis provides insights into the etiology of heart failure and its subtypes. - Henry, Albert; Mo, Xiaodong; Finan, Chris; Chaffin, Mark D; Speed, Doug; Issa, Hanane; Denaxas, Spiros; Ware, James S; Zheng, Sean L; Mälarstig, Anders; Gratton, Jasmine; Bond, Isabelle; et al. (Nat Genet, 2025)
Heart failure (HF) is a major contributor to global morbidity and mortality. While distinct clinical subtypes, defined by etiology and left ventricular ejection fraction, are well recognized, their genetic determinants remain inadequately understood. In this study, we report a genome-wide association study of HF and its subtypes in a sample of 1.9 million individuals. A total of 153,174 individuals had HF, of whom 44,012 had a nonischemic etiology (ni-HF). A subset of patients with ni-HF were stratified based on left ventricular systolic function, where data were available, identifying 5,406 individuals with reduced ejection fraction and 3,841 with preserved ejection fraction. We identify 66 genetic loci associated with HF and its subtypes, 37 of which have not previously been reported. Using functionally informed gene prioritization methods, we predict effector genes for each identified locus, and map these to etiologic disease clusters through phenome-wide association analysis, network analysis and colocalization. Through heritability enrichment analysis, we highlight the role of extracardiac tissues in disease etiology. We then examine the differential associations of upstream risk factors with HF subtypes using Mendelian randomization. These findings extend our understanding of the mechanisms underlying HF etiology and may inform future approaches to prevention and treatment.

Genomic and phenotypic correlates of mosaic loss of chromosome Y in blood. - Jakubek, Yasminka A; Ma, Xiaolong; Stilp, Adrienne M; Yu, Fulong; Bacon, Jason; Wong, Justin W; Aguet, Francois; Ardlie, Kristin; Arnett, Donna K; Barnes, Kathleen; Bis, Joshua C; Blackwell, Tom; et al. (Am J Hum Genet, 2025)
Mosaic loss of Y (mLOY) is the most common somatic chromosomal alteration detected in human blood. The presence of mLOY is associated with altered blood cell counts and increased risk of Alzheimer disease, solid tumors, and other age-related diseases. We sought to gain a better understanding of genetic drivers and associated phenotypes of mLOY through analyses of whole-genome sequencing (WGS) of a large set of genetically diverse males from the Trans-Omics for Precision Medicine (TOPMed) program. We show that haplotype-based calling methods can be used with WGS data to successfully identify mLOY events. This approach enabled us to identify differences in mLOY frequencies across populations defined by genetic similarity, revealing a higher frequency of mLOY in the European (EUR) ancestry group compared to other ancestries. We identify multiple loci associated with mLOY susceptibility and show that subsets of human hematopoietic stem cells are enriched for the activity of mLOY susceptibility variants. Finally, we found that certain alleles on chromosome Y are more likely to be lost than others in detectable mLOY clones.
Keywords: Alleles; Chromosome Deletion; Chromosomes, Human, Y; Genomics; Haplotypes; Humans; Male; Mosaicism; Phenotype; Whole Genome Sequencing

The impact of common and rare genetic variants on bradyarrhythmia development. - Weng, Lu-Chen; Rämö, Joel T; Jurgens, Sean J; Khurshid, Shaan; Chaffin, Mark; Hall, Amelia Weber; Morrill, Valerie N; Wang, Xin; Nauffal, Victor; Sun, Yan V; Beer, Dominik; Lee, Simon; et al. (Nat Genet, 2025)
To broaden our understanding of bradyarrhythmias and conduction disease, we performed common variant genome-wide association analyses in up to 1.3 million individuals and rare variant burden testing in 460,000 individuals for sinus node dysfunction (SND), distal conduction disease (DCD) and pacemaker (PM) implantation. We identified 13, 31 and 21 common variant loci for SND, DCD and PM, respectively. Four well-known loci (SCN5A/SCN10A, CCDC141, TBX20 and CAMK2D) were shared for SND and DCD, while others were more specific for SND or DCD. SND and DCD showed a moderate genetic correlation (r = 0.63). Cardiomyocyte-expressed genes were enriched for contributions to DCD heritability. Rare-variant analyses implicated LMNA for all bradyarrhythmia phenotypes, SMAD6 and SCN5A for DCD and TTN, MYBPC3 and SCN5A for PM. These results show that variation in multiple genetic pathways (for example, ion channel function, cardiac developmental programs, sarcomeric structure and cellular homeostasis) appear critical to the development of bradyarrhythmias.
Keywords: Bradycardia; Cardiac Conduction System Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Pacemaker, Artificial; Phenotype; Polymorphism, Single Nucleotide; Sick Sinus Syndrome

A Large-Scale Genome-wide Association Study of Blood Pressure Accounting for Gene-Depressive Symptomatology Interactions in 564,680 Individuals from Diverse Populations. - Lee, Songmi; Miller, Clint L; Bentley, Amy R; Brown, Michael R; Nagarajan, Pavithra; Noordam, Raymond; Morrison, John; Schwander, Karen; Westerman, Kenneth; Kho, Minjung; Kraja, Aldi T; de Vries, Paul S; et al. (Res Sq, 2025)
BACKGROUND: Gene-environment interactions may enhance our understanding of hypertension. Our previous study highlighted the importance of considering psychosocial factors in gene discovery for blood pressure (BP) but was limited in statistical power and population diversity. To address these challenges, we conducted a multi-population genome-wide association study (GWAS) of BP accounting for gene-depressive symptomatology (DEPR) interactions in a larger and more diverse sample. RESULTS: Our study included 564,680 adults aged 18 years or older from 67 cohorts and 4 population backgrounds (African (5%), Asian (7%), European (85%), and Hispanic (3%)). We discovered seven novel gene-DEPR interaction loci for BP traits. These loci mapped to genes implicated in neurogenesis (), lipid metabolism (), neuronal apoptosis (), and synaptic activity (). We also identified evidence for gene-DEPR interaction at nine known BP loci, further suggesting links between mood disturbance and BP regulation. Of the 16 identified loci, 11 loci were derived from African, Asian, or Hispanic populations. Post-GWAS analyses prioritized 36 genes, including genes involved in synaptic functions () and neuronal signaling (). Integrative druggability analyses identified 11 druggable candidate gene targets, including genes implicated in pathways linked to mood disorders as well as gene products targeted by known antihypertensive drugs. CONCLUSIONS: Our findings emphasize the importance of considering gene-DEPR interactions on BP, particularly in non-European populations. Our prioritized genes and druggable targets highlight biological pathways connecting mood disorders and hypertension and suggest opportunities for BP drug repurposing and risk factor prevention, especially in individuals with DEPR.

LD-informed deep learning for Alzheimer's gene loci detection using WGS data - Jo, T.; Bice, P.; Nho, K.; Saykin, A. J. (Alzheimers Dement (N Y), 2025)
The exponential growth of genomic datasets necessitates advanced analytical tools to effectively identify genetic loci from large-scale high throughput sequencing data. This study presents Deep-Block, a multi-stage deep learning framework that incorporates biological knowledge into its AI architecture to identify genetic regions as significantly associated with Alzheimer's disease (AD). The framework employs a three-stage approach: (1) genome segmentation based on linkage disequilibrium (LD) patterns, (2) selection of relevant LD blocks using sparse attention mechanisms, and (3) application of TabNet and Random Forest algorithms to quantify single nucleotide polymorphism (SNP) feature importance, thereby identifying genetic factors contributing to AD risk.\ The Deep-Block was applied to a large-scale whole genome sequencing (WGS) dataset from the Alzheimer's Disease Sequencing Project (ADSP), comprising 7416 non-Hispanic white (NHW) participants (3150 cognitively normal older adults (CN), 4266 AD).\ rs429358 and rs769449. Expression Quantitative Trait Loci (eQTL) analysis across 13 brain regions provided functional evidence for the identified variants. The results were cross-validated against established AD-associated loci from the European Alzheimer's and Dementia Biobank (EADB) and the GWAS catalog.\ The Deep-Block framework effectively processes large-scale high throughput sequencing data while preserving SNP interactions during dimensionality reduction, minimizing bias and information loss. The framework's findings are supported by tissue-specific eQTL evidence across brain regions, indicating the functional relevance of the identified variants. Additionally, the Deep-Block approach has identified both known and novel genetic variants, enhancing our understanding of the genetic architecture and demonstrating its potential for application in large-scale sequencing studies.\ ) were significant.The AI framework uses biological knowledge to enhance detection of Alzheimer's loci.

Low Lung Function Is Associated with High Population Attributable Fraction for Cardiovascular Mortality. - Bhatt, Surya P; Wu, Chaoqi; Sun, Yifei; Balte, Pallavi P; Schwartz, Joseph E; Divo, Miguel J; Jaeger, Byron C; Chaves, Paulo H; Couper, David; Jacobs, David R; Lloyd-Jones, Donald; Kalhan, Ravi; et al. (Ann Am Thorac Soc, 2025)
Chronic lung diseases are associated with increased risk of mortality due to coronary heart disease (CHD). Nonetheless, the population attributable fraction (PAF) of lung function impairment relative to other established cardiovascular risk factors is unclear. To evaluate the PAF of low lung function for CHD mortality We harmonized and pooled lung function and clinical data across eight U.S. general population cohorts. Impaired lung function was defined as forced expiratory volume in 1 second (FEV) and/or forced vital capacity ≤ 95% predicted on baseline spirometry. The association between CHD mortality and risk factors was assessed using cause-specific proportional hazards and Fine-Gray proportional subdistribution hazard models, treating non-CHD mortality as a competing risk. Models were adjusted for lung function as well as age, sex, race/ethnicity, educational attainment, body mass index, smoking status, pack-years of smoking, diabetes mellitus, high-density lipoprotein, and high low-density lipoprotein (≥130 mg/dl). PAF was calculated as the relative change in the average absolute risk of 10-year CHD mortality by elimination of lung function lower than 95% predicted. Among 35,143 participants, 1,844 of 13,174 (14.0%) deaths were due to CHD. Compared with percentage predicted FEV (FEVpp) > 95%, the subdistribution adjusted hazard ratio for low FEVpp was 1.30 (95% confidence interval, 1.18-1.44). The PAF for FEVpp ≤ 95% was 12%, ranking low FEV third on the list of PAF for CHD mortality, after hypertension and diabetes. Low FEVpp ranked second in the subgroup of active smokers (PAF 14%), after hypertension. Low lung function, even in the range considered clinically normal, ranks high on the list of attributable risk factors for CHD mortality and should be considered in cardiovascular risk stratification.
Keywords: Adult; Aged; Coronary Disease; Female; Forced Expiratory Volume; Humans; Lung; Lung Diseases; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Smoking; Spirometry; United States; Vital Capacity

Meta-analysis of genome-wide associations and polygenic risk prediction for atrial fibrillation in more than 180,000 cases. - Roselli, Carolina; Surakka, Ida; Olesen, Morten S; Sveinbjornsson, Gardar; Marston, Nicholas A; Choi, Seung Hoan; Holm, Hilma; Chaffin, Mark; Gudbjartsson, Daniel; Hill, Matthew C; Aegisdottir, Hildur; Albert, Christine M; et al. (Nat Genet, 2025)
Atrial fibrillation (AF) is the most common heart rhythm abnormality and is a leading cause of heart failure and stroke. This large-scale meta-analysis of genome-wide association studies increased the power to detect single-nucleotide variant associations and found more than 350 AF-associated genetic loci. We identified candidate genes related to muscle contractility, cardiac muscle development and cell-cell communication at 139 loci. Furthermore, we assayed chromatin accessibility using assay for transposase-accessible chromatin with sequencing and histone H3 lysine 4 trimethylation in stem cell-derived atrial cardiomyocytes. We observed a marked increase in chromatin accessibility for our sentinel variants and prioritized genes in atrial cardiomyocytes. Finally, a polygenic risk score (PRS) based on our updated effect estimates improved AF risk prediction compared to the CHARGE-AF clinical risk score and a previously reported PRS for AF. The doubling of known risk loci will facilitate a greater understanding of the pathways underlying AF.
Keywords: Atrial Fibrillation; Chromatin; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Multifactorial Inheritance; Myocytes, Cardiac; Polymorphism, Single Nucleotide; Risk Factors

Plasma Proteomic Assessment of Calcific Aortic Valve Disease in Older Adults. - Bortnick, Anna E; Austin, Thomas R; Hamerton, Emily; Gudmundsdottir, Valborg; Emilsson, Valur; Jennings, Lori L; Gudnason, Vilmundur; Owens, David S; Massera, Daniele; Dufresne, Line; Yang, Ta-Yu; Engert, James C; et al. (J Am Heart Assoc, 2025)
BACKGROUND: Calcific aortic valve disease (CAVD), and ensuing severe aortic stenosis (AS), is the foremost valvular disorder of aging, yet preventive therapies are lacking. A better understanding of the molecular underpinnings of aortic valve calcification (AVC) is necessary to develop pharmacologic interventions. METHODS AND RESULTS: We undertook large-scale plasma proteomics in a cohort study of adults ≥65 years old, the CHS (Cardiovascular Health Study), to identify individual proteins associated with echocardiographic AVC and incident moderate/severe AS. Proteomics measurements were performed with the aptamer-based SomaLogic platform of ~5000 proteins. Significant proteins were validated in a second cohort, the AGES-RS (Age, Gene/Environment Susceptibility-Reykjavik Study), which assessed AVC and AS by computed tomography. The potential causal associations of replicated proteins were tested in 2-sample Mendelian randomization using identified cis protein quantitative trait loci in consortia having computed tomography-quantified AVC or AS as outcomes. Six proteins showed Bonferroni-corrected significant relationships with AVC in CHS. Three of these, CXCL-12 (C-X-C chemokine ligand 12), KLKB1 (kallikrein), and leptin, replicated in AGES-RS, of which the former 2 are novel. Only 1 protein, CXCL6, which showed a near-significant association with AS in the replication cohort, was significantly (positively) associated with incident AS. Mendelian randomization analysis was conducted for KLKB1, CXCL12, and CXCL6, which supported a causal relationship for higher KLKB1 with lower AVC (beta=-0.25, =0.009). CONCLUSIONS: This study of older adults newly identified and largely replicated associations of 3 circulating proteins with calcific aortic valve disease, of which the relationship of plasma KLKB1 may have a causal basis. Additional investigation is necessary to determine if KLKB1 could be harnessed for calcific aortic valve disease therapeutics.
Keywords: Age Factors; Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Biomarkers; Blood Proteins; Calcinosis; Chemokine CXCL12; Echocardiography; Female; Humans; Male; Mendelian Randomization Analysis; Proteomics; Severity of Illness Index

Plasma TAR DNA-binding protein 43 (TDP-43) levels in a population-based cohort of older adults: The cardiovascular health study. - Fohner, Alison E; Sitlani, Colleen M; Jayadev, Suman; Bis, Joshua C; Trittschuh, Emily H; Lopez, Oscar L; Tracy, Russel P; Psaty, Bruce M; Longstreth, W T; Seshadri, Sudha (J Alzheimers Dis, 2025)
Brain deposition of transactive response DNA-binding protein 43 (TDP-43) is a feature of neurodegenerative syndromes. We evaluated TDP-43 plasma concentrations in 1058 participants in the Cardiovascular Health Study (CHS), a population-based longitudinal cohort. The cohort was 38% male, 11% Black, had a mean age 75 years, and 261 people developed dementia over a mean of 5.5 years of follow up. Median TDP-43 levels were 211.0 pg/mL (IQR: 134.0-341.0 pg/mL). TDP-43 levels were not associated with cross-sectional or longitudinal change in cognitive scores, with plasma AD biomarkers, with brain MRI volumes, with incident dementia, or with demographic characteristics.

Rare damaging CCR2 variants are associated with lower lifetime cardiovascular risk. - Georgakis, Marios K; Malik, Rainer; Bounkari, Omar El; Hasbani, Natalie R; Li, Jiang; Huffman, Jennifer E; Shakt, Gabrielle; Tack, Reinier W P; Kimball, Tamara N; Asare, Yaw; Morrison, Alanna C; Tsao, Noah L; et al. (Genome Med, 2025)
BACKGROUND: Previous work has shown a role of CCL2, a key chemokine governing monocyte trafficking, in atherosclerosis. However, it remains unknown whether targeting CCR2, the cognate receptor of CCL2, provides protection against human atherosclerotic cardiovascular disease. METHODS: Computationally predicted damaging or loss-of-function (REVEL > 0.5) variants within CCR2 were detected in whole-exome-sequencing data from 454,775 UK Biobank participants and tested for association with cardiovascular endpoints in gene-burden tests. Given the key role of CCR2 in monocyte mobilization, variants associated with lower monocyte count were prioritized for experimental validation. The response to CCL2 of human cells transfected with these variants was tested in migration and cAMP assays. Validated damaging variants were tested for association with cardiovascular endpoints, atherosclerosis burden, and vascular risk factors. Significant associations were replicated in six independent datasets (n = 1,062,595). RESULTS: Carriers of 45 predicted damaging or loss-of-function CCR2 variants (n = 787 individuals) were at lower risk of myocardial infarction and coronary artery disease. One of these variants (M249K, n = 585, 0.15% of European ancestry individuals) was associated with lower monocyte count and with both decreased downstream signaling and chemoattraction in response to CCL2. While M249K showed no association with conventional vascular risk factors, it was consistently associated with a lower risk of myocardial infarction (odds ratio [OR]: 0.66, 95% confidence interval [CI]: 0.54-0.81, p = 6.1 × 10) and coronary artery disease (OR: 0.74, 95%CI: 0.63-0.87, p = 2.9 × 10) in the UK Biobank and in six replication cohorts. In a phenome-wide association study, there was no evidence of a higher risk of infections among M249K carriers. CONCLUSIONS: Carriers of an experimentally confirmed damaging CCR2 variant are at a lower lifetime risk of myocardial infarction and coronary artery disease without carrying a higher risk of infections. Our findings provide genetic support for the translational potential of CCR2-targeting as an atheroprotective approach.
Keywords: Aged; Cardiovascular Diseases; Chemokine CCL2; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Monocytes; Receptors, CCR2

Sequencing in over 50,000 cases identifies coding and structural variation underlying atrial fibrillation risk. - Choi, Seung Hoan; Jurgens, Sean J; Xiao, Ling; Hill, Matthew C; Haggerty, Christopher M; Sveinbjörnsson, Garðar; Morrill, Valerie N; Marston, Nicholas A; Weng, Lu-Chen; Pirruccello, James P; Arnar, David O; Gudbjartsson, Daniel Fannar; et al. (Nat Genet, 2025)
Atrial fibrillation (AF) is a prevalent and morbid abnormality of the heart rhythm with a strong genetic component. Here, we meta-analyzed genome and exome sequencing data from 36 studies that included 52,416 AF cases and 277,762 controls. In burden tests of rare coding variation, we identified novel associations between AF and the genes MYBPC3, LMNA, PKP2, FAM189A2 and KDM5B. We further identified associations between AF and rare structural variants owing to deletions in CTNNA3 and duplications of GATA4. We broadly replicated our findings in independent samples from MyCode, deCODE and UK Biobank. Finally, we found that CRISPR knockout of KDM5B in stem-cell-derived atrial cardiomyocytes led to a shortening of the action potential duration and widespread transcriptomic dysregulation of genes relevant to atrial homeostasis and conduction. Our results highlight the contribution of rare coding and structural variants to AF, including genetic links between AF and cardiomyopathies, and expand our understanding of the rare variant architecture for this common arrhythmia.
Keywords: Atrial Fibrillation; Case-Control Studies; Exome Sequencing; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Myocytes, Cardiac; Risk Factors

A statistical framework for multi-trait rare variant analysis in large-scale whole-genome sequencing studies. - Li, Xihao; Chen, Han; Selvaraj, Margaret Sunitha; Van Buren, Eric; Zhou, Hufeng; Wang, Yuxuan; Sun, Ryan; McCaw, Zachary R; Yu, Zhi; Jiang, Min-Zhi; DiCorpo, Daniel; Gaynor, Sheila M; et al. (Nat Comput Sci, 2025)
Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical framework and computationally scalable analytical pipeline for functionally informed multi-trait rare variant analysis in large-scale WGS studies. MultiSTAAR accounts for relatedness, population structure and correlation among phenotypes by jointly analyzing multiple traits, and further empowers rare variant association analysis by incorporating multiple functional annotations. We applied MultiSTAAR to jointly analyze three lipid traits in 61,838 multi-ethnic samples from the Trans-Omics for Precision Medicine (TOPMed) Program. We discovered and replicated new associations with lipid traits missed by single-trait analysis.
Keywords: Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipids; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Whole Genome Sequencing

Whole genome sequencing analysis of body mass index identifies novel African ancestry-specific risk allele. - Zhang, Xinruo; Brody, Jennifer A; Graff, Mariaelisa; Highland, Heather M; Chami, Nathalie; Xu, Hanfei; Wang, Zhe; Ferrier, Kendra R; Chittoor, Geetha; Josyula, Navya Shilpa; Meyer, Mariah; Gupta, Shreyash; et al. (Nat Commun, 2025)
Obesity is a major public health crisis associated with high mortality rates. Previous genome-wide association studies (GWAS) investigating body mass index (BMI) have largely relied on imputed data from European individuals. This study leveraged whole-genome sequencing (WGS) data from 88,873 participants from the Trans-Omics for Precision Medicine (TOPMed) Program, of which 51% were of non-European population groups. We discovered 18 BMI-associated signals (P < 5 × 10), including two secondary signals. Notably, we identified and replicated a novel low-frequency single nucleotide polymorphism (SNP) in MTMR3 that was common in individuals of African descent. Using a diverse study population, we further identified two novel secondary signals in known BMI loci and pinpointed two likely causal variants in the POC5 and DMD loci. Our work demonstrates the benefits of combining WGS and diverse cohorts in expanding current catalog of variants and genes confer risk for obesity, bringing us one step closer to personalized medicine.
Keywords: Adult; African People; Alleles; Body Mass Index; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Population Groups; Whole Genome Sequencing